2D van der Waals Heterojunction of Organic and Inorganic Monolayers for High Responsivity Phototransistors - Zhao, Baolin; Gan, Ziyang; Johnson, Manuel; Najafidehaghani, Emad; Rejek, Tobias; George, Antony; Fink, Rainer; Turchanin, Andrey; Halik, Marcus (Advanced Functional Materials, 2021)
Van der Waals (vdW) heterostructures composing of organic molecules with inorganic 2D crystals open the door to fabricate various promising hybrid devices. Here, a fully ordered organic self-assembled monolayer (SAM) to construct hybrid organic–inorganic vdW heterojunction phototransistors for highly sensitive light detection is used. The heterojunctions, formed by layering MoS2 monolayer crystals onto organic [12-(benzo[b]benzo[4,5]thieno[2,3-d]thiophen-2-yl)dodecyl)]phosphonic acid SAM, are characterized by Raman and photoluminescence spectroscopy as well as Kelvin probe force microscopy. Remarkably, this vdW heterojunction transistor exhibits a superior photoresponsivity of 475 A W−1 and enhanced external quantum efficiency of 1.45 × 105%, as well as an extremely low dark photocurrent in the pA range. This work demonstrates that hybridizing SAM with 2D materials can be a promising strategy for fabricating diversified optoelectronic devices with unique properties.
CRIS-Team Scopus Importer:2021-08-06
Keywords: charge transfer; organic–inorganic hybrid; photodetection; self-assembled monolayer; transition metal dichalcogenides; van der Waals heterojunction

2H-Tetrakis(3,5-di-tert-butyl)phenylporphyrin on a Cu(110) Surface: Room-Temperature Self-Metalation and Surface-Reconstruction-Facilitated Self-Assembly - Zhang, Liang; Lepper, Michael; Stark, Michael Werner; Schuster, Ralf; Lungerich, Dominik; Jux, Norbert; Steinrück, Hans-Peter; Marbach, Hubertus (Chemistry - A European Journal, 2016)
The adsorption behavior of 2H-tetrakis(3,5-di-tert-butyl)phenylporphyrin (2HTTBPP) on Cu(110) and Cu(110)-(2x1)O surfaces have been investigated by using variable-temperature scanning tunneling microscopy (STM) under ultrahigh vacuum conditions. On the bare Cu(110) surface, individual 2HTTBPP molecules are observed. These molecules are immobilized on the surface with a particular orientation with respect to the crystallographic directions of the Cu(110) surface and do not form supramolecular aggregates up to full monolayer coverage. In contrast, a chiral supramolecular structure is formed on the Cu(110)-(2x1)O surface, which is stabilized by van der Waals interactions between the tert-butyl groups of neighboring molecules. These findings are explained by weakened molecule-substrate interactions on the Cu(110)-(2x1)O surface relative to the bare Cu(110) surface. By comparison with the corresponding results of Cu-tetrakis(3,5-di-tert-butyl)phenylporphyrin (CuTTBPP) on Cu(110) and Cu(110)-(2x1)O surfaces, we find that the 2HTTBPP molecules can self-metalate on both surfaces with copper atoms from the substrate at room temperature (RT). The possible origins of the self-metalation reaction at RT are discussed. Finally, peculiar irreversible temperature-dependent switching of the intramolecular conformations of the investigated molecules on the Cu(110) surface was observed and interpreted.
Keywords: adsorption; porphyrinoids; scanning tunneling microscopy; self-assembly; surfaces and interfaces

3.8.7 Cyclic Hydrocarbons - Held, Georg; Steinrück, Hans-Peter (Springer Berlin Heidelberg, 2005)

Abrupt coverage-induced enhancement of the self-metalation of tetraphenylporphyrin with Cu(111) - Röckert, Michael; Ditze, Stefanie; Stark, Michael Werner; Xiao, Jie; Steinrück, Hans-Peter; Marbach, Hubertus; Lytken, Ole (Journal of Physical Chemistry C, 2014)
Using X-ray photoelectron spectroscopy (XPS) and scanning tunneling microscopy (STM), the coverage-dependent self-metalation of 2H- tetraphenylporphyrin (2HTPP) with Cu on Cu(111) at 400 K has been studied. At low coverages the porphyrin molecules are adsorbed as isolated molecules, and the rate of metalation is slow. As the coverage is increased beyond ∼0.36 molecules/nm, a supramolecular checkerboard structure is formed, with every second molecule slightly elevated above the surface. The appearance of this checkerboard structure coincides with a dramatic increase in the rate of metalation. This enhancement is attributed to a smaller activation barrier for the elevated molecules, which have an internal conformation similar to that of the free molecule, whereas the less reactive molecules in direct contact with the surface are strongly distorted. © 2013 American Chemical Society.

Accurate Determination of Adsorption-Energy Differences of Metalloporphyrins on Rutile TiO2(110) 1 x 1 - Muth, Maximilian; Wolfram, Alexander; Kataev, Elmar; Köbl, Julia; Steinrück, Hans-Peter; Lytken, Ole (Langmuir, 2022)
Understanding the adsorption of organic molecules on surfaces is of essential importance for many applications. Adsorption energies are typically measured using temperature-programmed desorption. However, for large organic molecules, often only desorption of the multilayers is possible, while the bottom monolayer in direct contact to the surface cannot be desorbed without decomposition. Nevertheless, the adsorption energies of these directly adsorbed molecules are the ones of the most interest. We use a layer-exchange process investigated with X-ray photoelectron spectroscopy to compare the relative adsorption energies of several metalated tetraphenylporphyrins on rutile TiO2(110) 1 x 1. We deposit a mixture of two different molecules, one on top of the other, and slowly anneal above their multilayer desorption temperature. During the slow heating, the molecules begin to diffuse between the layers and the molecules with the stronger interaction with the surface displace the weaker-interacting molecules from the surface and push them into the multilayer. The multilayers eventually desorb, leaving behind a monolayer of strongly interacting molecules. From the ratio of the two different porphyrin molecules in the residual monolayer and the desorbed multilayer, we can calculate the equilibrium constant of the layer-exchange process and thereby the difference in adsorption energy between the two different porphyrin molecules.
CRIS-Team WoS Importer:2022-07-29

A combined density-functional and IRAS study on the interaction of NO with Pd nanoparticles: Identifying new adsorption sites with novel properties - Vines Solana, Francesc; Desikusumastuti, Aine; Staudt, T.; Görling, Andreas; Libuda, Jörg; Neyman, Konstantin M. (Journal of Physical Chemistry C, 2008)
Nanocrystalline particles expose special adsorption sites close to edges and corners, giving rise to novel adsorption and reaction properties. The spectroscopic identification of these sites represents a great challenge, however. Here, we present results of a combined experimental and theoretical study on the adsorption of NO on Pd nanoparticles, using infrared reflection absorption spectroscopy (IRAS) and calculations based on density-functional theory (DFT). This approach facilitates identification of the adsorption sites available on the nanoparticles and reveals detailed information on their bonding properties, on the vibrational parameters of NO adsorbed on these sites, and on their sequence of occupation. With respect to all these aspects, the adsorption behavior of NO on the Pd nanoparticles notably differs from any single crystal reference data available. The IRAS studies are performed on well-defined Pd nanoparticles supported on an ordered AlO film on NiAl(110). The growth and structure of these particles has been characterized previously, predominately exposing (111) and a small fraction of (100) facets. Here, we systematically monitor the NO adsorption as a function of exposure in a temperature region between 100 and 300 K by means of time-resolved IRAS in combination with molecular beam (MB) dosing. We interpret these experimental data with the help of DFT calculations on the adsorption of NO on unsupported cuboctahedral Pd clusters cut from Pd bulk and containing up to 140 atoms; for comparison, calculations of the reference adsorption complexes of NO on single-crystal Pd(111) surface have also been performed. NO molecules are shown to most favorably adsorb on hollow μ-sites on (111) facets of Pd clusters, closely followed by bridge μ-sites at the edges between adjacent (111) facets. Both sites give rise to characteristic features in the vibrational spectrum and are populated sequentially. At higher coverage (and low temperature) on-top μ-sites on the (111) facets begin to be occupied. At variance with the adsorption on Pd(111) surface, however, additional on-top-sites are available at the particle edges and corners, which reveal stronger NO adsorption. In spite of the strong adsorption in bridge (μ) coordination geometry at edges, our calculations predict that intermolecular repulsion between adjacent μ-NO species gives rise to the formation of mixed bridge/on-top structures at high coverage. Similarly to the bridge NO at particle edges, the edge- and corner-related μ-NO species reveal characteristic vibrational frequencies, allowing for direct verification of this prediction by IRAS. The present results make possible the identification and monitoring of the occupation of specific sites on Pd nanoparticles by NO during adsorption and reaction processes. © 2008 American Chemical Society.

A comparative study of a triphenylene tricarbonyl chromium complex and its uncoordinated arene ligand on the Ag(111) surface: Influence of the complexation on the adsorption - Schmitz, Christoph H.; Rang, Carola; Bai, Yun; Kossev, Iordan; Ikonomov, Julian; Su, Yang; Kotsis, Konstantinos; Soubatch, Serguei; Neucheva, Olga; Tautz, F. Stefan; Neese, Frank; Steinrück, Hans-Peter; et al. (Journal of Physical Chemistry C, 2009)
An aromatic triphenylene molecule (2,3-diethyl-1,4-dimethoxytriphenylene; TPH) and its regioselectively Cr(CO)-labeled complex (η-(1,2,3,4,4a,12b)-tricarbonyl(2,3-diethyl-1, 4-dimethoxytriphenylene)chromium(0); α-TPHC) were deposited on a Ag(111) surface by vapor deposition. The monolayers were investigated by X-ray photoelectron spectroscopy and scanning tunneling microscopy. Both substances adsorb with the extended π-system parallel to the surface and form long-range ordered monolayers. The Cr(CO) group of the α-TPHC complex is oriented toward the vacuum. Although the footprints of both substances are similar, the additional Cr(CO) group on the α-TPHC leads to a lateral order (unit cell) that is significantly different from that of TPH. © 2009 American Chemical Society.

Activated adsorption of methane on Pt (111) - An in situ XPS study - Fuhrmann, Thomas; Kinne, Markus; Tränkenschuh, Barbara; Papp, Christian; Zhu, Junfa; Denecke, Reinhard; Steinrück, Hans-Peter (New Journal of Physics, 2005)
We have investigated the activated adsorption of methane on Pt(111) by the combination of a supersonic molecular beam and in situ high-resolution X-ray photoelectron spectroscopy at the German synchrotron radiation facility BESSY II. On exposing the surface to a methane beam with kinetic energies between 0.30 and 0.83eV, CH is formed as a stable species at 120 K; upon heating, at around 260 K the adsorbed methyl partly dehydrogenates to CH and partly recombines to methane, which desorbs. Upon adsorption at 300 K, CH is directly formed as a stable surface species. To verify the chemical identity of CH as an intermediate, we have also investigated the thermal evolution of a saturated ethylene layer. Upon heating, at ∼ 290 K partial ethylene desorption and the formation of ethylidyne is clearly observed in the spectra, as expected from the literature. From the binding energies and also from the vibrational signature of the C 1s spectra, an unequivocal assignment of the various surface species is possible. Measurements of the sticking coefficients of methane show that the saturation coverage at 120 K depends on the kinetic energy of the molecule; furthermore, the sticking coefficient for vibrationally excited molecules is strongly enhanced. © IOP Publishing Ltd and Deutsche Physikalische Gesellschaft.

Activation energy for the self-metalation reaction of 2H- tetraphenylporphyrin on Cu(111) - Ditze, Stefanie; Stark, Michael Werner; Drost, Martin; Buchner, Florian; Steinrück, Hans-Peter; Marbach, Hubertus (Angewandte Chemie International Edition, 2012)
By simply counting individual molecules in STM images after defined heating steps, the kinetic parameters and the activation energy of a complex surface reaction can be determined quantitatively. This procedure was demonstrated for the metalation of 2H-tetraphenylporphyrin (2HTPP) with substrate atoms on a Cu(111) surface. Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Activation of n-butane with translational energy on Ir(110)-(1×2) - Hamza, Alex; Steinrück, Hans-Peter; Madix, R.J. (Journal of Chemical Physics, 1986)

Additive fabrication of nanostructures with focused soft X-rays - Späth, Andreas; TU, Fan; Vollnhals, Florian; Drost, Martin; Krick Calderon, Sandra; Watts, Benjamin; Fink, Rainer; Marbach, Hubertus (RSC Advances, 2016)
We report on a novel technique for the fabrication of metallic nanostructures via soft X-ray irradiation of precursor molecules supplied from the gas phase. With this technique we were able to produce localized Co nanostructures with a growth rate and purity competitive with electron beam induced deposition. We demonstrate that our approach exhibits significant selectivity with respect to incident photon energy leading to enhanced growth for resonant absorption energy of the precursor molecule. Based on this finding we propose a unique new pathway of selective deposition from precursor mixtures. Furthermore, we investigated the growth rate with respect to precursor pressure and growth time and discuss the potential resolution limits of this new technique.
EAM Import::2019-03-13

Additive Nano-Lithography with Focused Soft X-rays: Basics, Challenges, and Opportunities - Späth, Andreas (Micromachines, 2019)
Focused soft X-ray beam induced deposition (FXBID) is a novel technique for direct-write nanofabrication of metallic nanostructures from metal organic precursor gases. It combines the established concepts of focused electron beam induced processing (FEBIP) and X-ray lithography (XRL). The present setup is based on a scanning transmission X-ray microscope (STXM) equipped with a gas flow cell to provide metal organic precursor molecules towards the intended deposition zone. Fundamentals of X-ray microscopy instrumentation and X-ray radiation chemistry relevant for FXBID development are presented in a comprehensive form. Recently published proof-of-concept studies on initial experiments on FXBID nanolithography are reviewed for an overview on current progress and proposed advances of nanofabrication performance. Potential applications and advantages of FXBID are discussed with respect to competing electron/ion based techniques.
CRIS-Team WoS Importer:2020-01-31

A detailed analysis of vibrational excitations in x-ray photoelectron spectra of adsorbed small hydrocarbons - Steinrück, Hans-Peter; Fuhrmann, Thomas; Papp, Christian; Tränkenschuh, Barbara; Denecke, Reinhard (Journal of Chemical Physics, 2006)
The vibrational fine structure of x-ray photoelectron (XP) spectra of a number of different small hydrocarbon molecules and reaction intermediates adsorbed on Pt(111) and Ni(111) has been investigated in detail. The data for methyl, methylidyne, acetylene, and ethylene can consistently be analyzed within the linear coupling model. The S factor, i.e., the intensity ratio of the first vibrationally excited to the adiabatic transition, is obtained to be 0.17±0.02 per C-H bond; for the deuterated species a value of 0.23±0.02 is obtained. Therefore, the vibrational fine structure can be used for fingerprinting in the analysis of XP spectra and for identifying unknown reaction intermediates. From the data, Δr, the change of the minimum in the potential energy curve upon core ionization, is calculated within the linear coupling model using a first order correction. For all adsorbates, including the deuterated ones, a value of Δr=0.060±0.004 Å is obtained. Furthermore, from the binding energy of the adiabatic peak and from the energy of the vibrational excitation in the ionic final state some information on the adsorbate/substrate bond and the adsorption site can be derived. © 2006 American Institute of Physics.

Adsorption and Activation of CO on Co3O4(111) Thin Films - Ferstl, Pascal; Mehl, Sascha; Arman, M. A.; Schuler, Marina; Toghan, A.; Laszlo, B.; Lykhach, Yaroslava; Brummel, Olaf; Lundgren, Edvin; Knudsen, J.; Hammer, Lutz; Schneider, M. Alexander; et al. (Journal of Physical Chemistry C, 2015)
To explore the catalytic properties of cobalt oxide at the atomic level, we have studied the interaction of CO and O2 with well-ordered Co3O4(111) thin films using scanning tunneling microscopy (STM), high-resolution X-ray photoelectron spectroscopy (HR-XPS), infrared reflection absorption spectroscopy (IRAS), and temperature-programmed desorption spectroscopy (TPD) under ultrahigh vacuum (UHV) conditions. At low coverage and temperature, CO binds to surface Co2+ ions on the (111) facets. At larger exposure, a compressed phase is formed in which additional CO is located at sites in between the Co2+ ions. In addition, a bridging carbonate species forms that is associated with defects such as step edges of Co3O4(111) terraces or the side facets of the (111) oriented grains. Preadsorbed oxygen neither affects CO adsorption at low coverage nor the formation of the surface carbonate, but it blocks formation of the high coverage CO phase. Desorption of the molecularly bound CO occurs up to 180 K, whereas the surface carbonate decomposes in a broad temperature range up to 400 K under the release of CO and, to a lesser extent, of CO2. Upon strong loss of crystalline oxygen, the Co3O4 grains eventually switch to the CoO rocksalt structure.

Adsorption and Decomposition of Formic Acid on Model Ceria and Pt/Ceria Catalysts - Lykhach, Yaroslava; Happel, Markus; Johanek, Viktor; Skala, Tomas; Kollhoff, Fabian; Tsud, Nataliya; Dvorak, Filip; Prince, Kevin C.; Matolin, Vladimir; Libuda, Jörg (Journal of Physical Chemistry C, 2013)
Adsorption and reaction of formic acid on stoichiometric CeO2(111), partially reduced CeO2-x, and Pt/CeO2(111) films prepared on Cu(111) were studied by means of synchrotron radiation photoelectron spectroscopy (SRPES), resonant photoemission spectroscopy (APES), infrared reflection absorption spectroscopy (IRAS), and temperature-programmed desorption (TPD). On all studied samples, the principal species formed during formic acid adsorption below 160 K were formate and molecular formic acid. In the presence of Pt particles, formate species were predominantly localized on Pt at 100 K, and on ceria at or above 300 K. Below 400 K, molecular formic acid decomposes to formate with partial release of CO2, CO, hydrogen, and water. Analysis of the TPD fragmentation suggests additional evolution of methane. Above 400 K, desorption of CO2, CO, hydrogen, and water is observed. This process is controlled by the stoichiometry of ceria and the presence of Pt particles. In particular, desorption of CO2 is suppressed on CeO2-x but is enhanced on Pt/CeO2. APES suggests that the reaction of formic acid does not alter the oxidation state of cerium cations on CeO2(111). By contrast, we observed significant reoxidation on partially reduced CeO2-x, between 250 and 400 K, followed by reduction between 400 and 500 K.

Adsorption and desorption of CO on Pt(1 1 1): A comprehensive analysis - Mcewen, Jean-Sabin; Payne, Stephen H.; Kreuzer, Hans Jürgen; Kinne, Martin; Denecke, Reinhard; Steinrück, Hans-Peter (Surface Science, 2003)
A comprehensive theory of the adsorption of CO on Pt(1 1 1) is developed to describe equilibrium properties as well as the adsorption and desorption kinetics. The basis is a multi-site lattice gas model which allows for adsorption at on-top and bridge sites, and includes site exclusion and lateral interactions out to second neighbour unit cells as well as a mean field to account for long ranged dipolar interactions between CO molecules. The theory reproduces the coverage and temperature dependence of pressure isotherms, partial coverages, heat of adsorption, total sticking coefficients, and isothermal and temperature-programmed desorption rates. The quality of the fits and the internal consistency of the theory are such that a number of minor inconsistencies in available experimental data can be identified and discussed. © 2003 Elsevier B.V. All rights reserve
Keywords: Equilibrium thermodynamics and statistical mechanics; Models of surface kinetics; X-ray photoelectron spectroscopy; Adsorption kinetics; Sticking; Thermal desorption; Platinum; Carbon monoxide

Adsorption and reaction of acetylene on clean and oxygen-precovered Pd(100) studied with high-resolution X-ray photoelectron spectroscopy - Höfert, Oliver; Lorenz, Michael Peter Andreas; Streber, Regine; Zhao, Wei; Bayer, Andreas; Steinrück, Hans-Peter; Papp, Christian (Journal of Chemical Physics, 2013)
We investigated the adsorption and thermal evolution of acetylene on clean Pd(100) and Pd(100) precovered with 0.25 ML oxygen. The measurements were performed in situ by fast XPS at the synchrotron radiation facility BESSY II. On Pd(100) acetylene molecularly adsorbs at 130 K. Upon heating transformation to a CCH species occurs around 390 K along with the formation of a completely dehydrogenated carbon species. On the oxygen-precovered surface partial CCH formation already occurs upon adsorption at 130 K, and the dehydrogenation temperature and the stability range of CCH are shifted to lower temperatures by ∼200 K. © 2013 AIP Publishing LLC.

Adsorption and reaction of cyclohexene on a Ni(111) surface - Papp, Christian; Denecke, Reinhard; Steinrück, Hans-Peter (Langmuir, 2007)
We studied the adsorption and reaction of cyclohexene (CH ) on Ni(111) at different temperatures with highresolution in-situ X-ray photoelectron spectroscopy (HR-XPS). For exposure at 125 K, we find intact cyclohexene with two distinct C Is signals at 283.3 and 284.2 eV, due to the nonequivalent carbon atoms in the molecule. The energetic separation is significantly increased relative to the gas-phase value, due to the interaction with the substrate. Upon exposure at 210 K, complete dehydrogenation of cyclohexene to benzene (CH) and hydrogen is observed; coverage-dependent changes of the benzene adsorption site occur in a way similar to those for pure benzene layers, which indicates a phase separation in benzene and hydrogen islands. The thermal evolution of the adsorbed layers was studied by temperature-programmed (TP-) XPS and temperature-programmed desorption spectroscopy (TPD). Upon heating, the benzene + hydrogen layer formed at 210 K shows a coverage-dependent reorientation of the benzene molecules during partial desorption. The cyclohexene layer adsorbed at 125 K only shows partial conversion of cyclohexene to benzene and hydrogen upon heating to 185 or 210 K, with the remaining cyclohexene being stable up to ∼300 K. We propose that upon heating these molecules are stabilized by coadsorbed benzene and hydrogen; furthermore, the mobility of benzene and hydrogen in this coadsorbed layer is reduced, so that no phase separation can occur. © 2007 American Chemical Society.

Adsorption and reaction of methanol on clean and oxygen precovered Cu(111) - Pöllmann, Silke Andrea; Bayer, Andreas; Ammon, Christian; Steinrück, Hans-Peter (Zeitschrift für Physikalische Chemie-International Journal of Research in Physical Chemistry & Chemical Physics, 2004)
The adsorption of methanol on the clean and oxygen precovered Cu(111) surface was studied by means of high resolution X-ray photoelectron spectroscopy (XPS), ultraviolet photoelectron spectroscopy (UPS), and temperature programmed desorption (TPD). On clean Cu(111) methanol is adsorbed molecularly at 100 K. Only small amounts of methoxy are formed by heating to 160-180 K, whereas the main part of methanol desorbs molecularly. The formation of methoxy drastically increases on the oxygen precovered surface. In the UP spectra the peaks of molecular methanol disappear and the peaks of methoxy develop. TPD measurements show that methoxy desorbs dissociatively as formaldehyde and hydrogen with the rate maxima at around 430 K. The efficiency of the oxidation of methanol to formaldehyde depends on the amount of predosed oxygen, with a maximum methoxy coverage obtained for an oxygen precoverage of 0.18 ML. From the quantitative analysis we propose an additional reaction pathway involving not only the formation, but also the decomposition of an hydroxyl intermediate, parallel to the previously reported pathway, which leads to the desorption of wate

Adsorption and reaction of NO2 on ordered alumina films and mixed baria-alumina nanoparticles: Cooperative versus non-cooperative reaction mechanisms - Desikusumastuti, Aine; Staudt, Thorsten; Happel, Markus; Laurin, Mathias; Libuda, Jörg (Journal of Catalysis, 2008)
In order to obtain insights into the mechanism and kinetics of adsorption and reaction of NO2 on aluminum and barium oxide surfaces, we have performed systematic adsorption experiments on single-crystal-based model materials. As a model surface, we use BaO containing nanoparticles grown by physical vapor deposition (PVD) of Ba under ultrahigh vacuum (UHV) conditions on an ordered Al2O3 film on NiAl(110) and subsequent oxidation and annealing. The growth behavior, the morphology and the chemical composition of the three-dimensional mixed barium aluminum oxide particles (BaAl2xO1+3x) formed via this procedure have previously been characterized by scanning tunneling microscopy (STM) and high-resolution photoelectron spectroscopy (HR-PES). In order to monitor adsorption and reaction processes on these systems, we perform time-resolved infrared reflection absorption spectroscopy (TR-IRAs) during exposure to a molecular beam (MB) of NO2. In a first step, the interaction of NO2 with the Al2O3/NiAl(110) model support is probed. At 100 K, only molecular adsorption occurs in form of the D-2h dimer (N2O4) in all coverage regions from the submonolayer up to multilayers. At 300 K, a slow surface reaction occurs, initially leading to the formation of surface nitrites and, subsequently, of surface nitrates in bridging adsorption geometry. On the BaAl2xO1+3x, particles on Al2O3/NiAl(110), NO2 shows a very different and strongly temperature-dependent behavior. At 100 K, molecular adsorption of the D-2h dimer (N2O4) is accompanied by a highly efficient reaction channel, leading to the formation of surface nitrites and nitrates. With the surface temperature increasing to 300 K, however, the reaction probability decreases by several orders of magnitude. In contrast to reaction at 100 K, surface nitrites in flat-lying adsorption geometry are the only primary product, indicating a temperature-dependent change in the reaction mechanism from a cooperative to a non-cooperative pathway. With increasing exposure, the nitrite coverage increases and, finally, the surface nitrites are converted into bridging and monodentate Surface nitrates. The latter reaction shows a complex kinetics, including an initial induction period. For temperatures of 400 K and above, nitrate formation becomes more efficient, eventually resulting in the formation of ionic nitrates. The vibrational properties of these ionic species sensitively depend on the reaction temperature, indicating the formation of well-defined structures in a narrow temperature interval around 500 K. The mechanism of the NOx storage process and the vibrational assignments of the related surface species are critically discussed on the basis of the present results. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: Nitrogen dioxide; Barium oxide; Aluminum oxide; Supported model catalysts; NSR catalysts; Scanning tunneling microscopy; IR reflection absorption spectroscopy; Molecular beams

Adsorption and reaction of SO2 on clean and oxygen precovered Pd(100) - A combined HR-XPS and DF study - Luckas, Nicola; Gotterbarm, Karin; Streber, Regine; Lorenz, Michael Peter Andreas; Höfert, Oliver; Vines, Francesc; Papp, Christian; Görling, Andreas; Steinrück, Hans-Peter (Physical Chemistry Chemical Physics, 2011)
We studied the adsorption and reactivity of SO on clean and oxygen precovered Pd(100) with high resolution X-ray photoelectron spectroscopy and density functional calculations. Upon adsorption at 120 K two different SO species were detected, which were identified as upright-standing and flat-lying molecules by comparing the calculated core level shifts. In agreement with the relative stabilities determined by the calculations the intensities of the photoelectron spectra indicate that the majority species are upright-standing SO . Upon heating the quantitative analysis of the data indicates desorption of SO and formation of atomic sulfur. On the oxygen precovered surface small amounts of SO are formed already upon SO adsorption at low temperatures. Upon heating stepwise oxidation of SO to SO and, eventually, to SO is found. Two different SO species were detected, which are assigned to SO bound in the proximity of or remote from oxygen adatoms, according to core level shift estimates. © 2011 the Owner Societies.

Adsorption and Reaction of SO2 on Graphene-Supported Pt Nanoclusters - Gotterbarm, Karin; Späth, Florian; Bauer, Udo; Steinrück, Hans-Peter; Papp, Christian (Topics in Catalysis, 2015)
Atomic sulfur and its oxides are common catalyst poisons and intriguing research subjects. Recently, graphene-supported nanoclusters were introduced as suitable model catalysts. We investigated the adsorption and reaction of SO2 on graphene-supported Pt nanocluster arrays with high-resolution X-ray photoelectron spectroscopy. SO2 adsorbs in two geometries-perpendicular and parallel to the surface-on both cluster facets and steps. Further insight is gained from the comparison of our results to previous data of SO2 on Pt(111) and two stepped single crystal surfaces-Pt(322) and Pt(355)-with (100) and (111) steps, respectively. We find a remarkable similarity to the adsorption situation on Pt(322). However, thermal evolution experiments revealed several similarities to both Pt(322) and Pt(355), showing that the Pt nanoclusters exhibit a mixture of (100) and (111) steps.
Keywords: XPS; Platinum; Nanoclusters; SO2; Graphene

Adsorption and reaction of terephthaloyl chloride on Ag(111): X-ray photoelectron spectroscopy and density functional theory investigations - Schmid, Martin; Hieringer, Wolfgang; Schmitz, Christoph H.; Steinrück, Hans-Peter; Sokolowski, Moritz; Gottfried, Michael (Journal of Physical Chemistry C, 2011)
The adsorption and reaction of terephthaloyl chloride (TPC) on a Ag(111) surface was investigated with X-ray photoelectron spectroscopy (XPS) and density functional theory (DFT) calculations. Below 120 K, TPC forms multilayers without reacting with the Ag(111) substrate. Multilayer desorption starts above 120 K and is accompanied by a chemical reaction between the TPC molecules and the Ag surface. This reaction involves scission of the carbon-chlorine bond, resulting in the formation of adsorbed chlorine atoms and a p-phenylene dicarbonyl (pPDC) species. This molecular fragment is stable at room temperature and does not undergo further decomposition, presumably due to stabilization by adsorbate-substrate interactions and/or oligomerization. The DFT calculations confirm that pPDC is a possible intermediate or final reaction product and show that the two carbonyl C atoms form covalent bonds to the Ag substrate. © 2011 American Chemical Society.

Adsorption and thermal evolution of [C1C1Im][Tf2N] on Pt(111) - Massicot, Stephen; Gezmis, Emine; Talwar, Timo; Meusel, Manuel; Jaekel, Simon; Adhikari, Rajan; Winter, Leonhard; Fernández Fernández, Cynthia; Bayer, Andreas; Maier, Florian; Steinrück, Hans-Peter (Physical Chemistry Chemical Physics, 2023)
In the context of ionic liquid (IL)-assisted catalysis, we have investigated the adsorption and thermal evolution of the IL 1,3-dimethylimidazolium bis(trifluoromethylsulfonyl)imide ([C1C1Im][Tf2N]) on Pt(111) between 100 and 800 K by angle-resolved X-ray photoelectron spectroscopy and scanning tunneling microscopy. Defined amounts of IL in the coverage range of a complete first wetting layer were deposited at low temperature (100-200 K), and subsequently heated to 300 K, or directly at 300 K. At 100 K, the IL adsorbs as an intact disordered layer. Upon heating to 200 K, the IL stays intact, but forms an ordered and well-oriented structure. Upon heating to 250 K, the surface order increases, but at the same time STM and XPS indicate the onset of decomposition. Upon heating to 300 K, decomposition progresses, such that 50-60% of the IL is decomposed. The anion-related reaction products desorb instantaneously, and the cation-related products remain on the surface. Thereby, the surface is partly passivated, enabling the remaining IL to still be adsorbed intact at 300 K. For IL deposition directly at 300 K, a fraction of the IL instantaneously decomposes, with the anion-related products desorbing, opening free space for further deposition of IL. Hence, cation-related species accumulate at the expense of anions, until one fully closed wetting layer is formed. As a consequence, a higher dose is required to reach this coverage at 300 K, compared to 100-200 K.
CRIS-Team Scopus Importer:2023-11-17

Adsorption and thermal evolution of SO2 on the Pt(110) surface - Zebisch, P.; Stichler, M.; Trischberger, P.; Weinelt, M.; Steinrück, Hans-Peter (Surface Science, 1997)
The adsorption and thermal evolution of SO on a Pt(110) surface was studied by temperature programmed desorption, angle-resolved UV photoelectron spectroscopy and X-ray photoelectron spectroscopy. At 140 K two molecular SO species are observed that are attributed to adsorption on different adsorption sites. Upon heating to 340 K atomic S and molecular SO and SO are formed with the amount of the various products depending on the initial SO coverage. For high SO coverages these reactions are accompanied by molecular SO desorption. The SO species decomposes upon further heating to 500 K leading to SO desorption. SO, which is only formed for high initial SO coverages, is stable up to this temperature but decomposes upon further heating to 650 K. In the same temperature range atomic sulphur and oxygen recombine to desorb as SO.

Adsorption Behavior of a Cyano-Functionalized Porphyrin on Cu(111) and Ag(111): From Molecular Wires to Ordered Supramolecular Two-Dimensional Aggregates - Lepper, Michael; Schmitt, Tobias; Gurrath, Martin; Raschmann, Marco; Zhang, Liang; Stark, Michael Werner; Hölzel, Helen; Jux, Norbert; Meyer, Bernd; Schneider, M. Alexander; Steinrück, Hans-Peter; Marbach, Hubertus (Journal of Physical Chemistry C, 2017)
We investigate the impact of peripheral cyano functionalization of the previously well-studied 2H-tetraphenylporphyrin (2HTPP) by scanning tunneling microscopy (STM) and density functional theory (DFT). The adsorption behavior of 2H-tetralds(p-cyano)-phenylporphyrin (2HTCNPP) is studied at room temperature and at 80 K on Cu(111) and Ag(111). Interestingly, the cyano-functionalized porphyrins tend to form isolated ID chains on Cu(111), in particular after mild annealing at 350 K. The individual 2HTCNPPs as well as the formed chains are oriented along the main crystallographic directions of the Cu(111) substrate due to a strongly attractive and site-specific interaction between the iminic nitrogens of the 2HTCNPP and Cu substrate atoms. The linking within the 1D molecular chains is realized by Cu adatoms as evidenced by comparison of STM and DFT. In contrast, on Ag(111) the molecules assemble into 2D supramolecular layers with long-range order and a square unit cell, stabilized by molecule-molecule interactions. The orientation of the molecules with respect to the unit cell lattice vectors leads to organizational chirality. By codeposition of cobalt, the porphyrin molecules are metalated at room temperature. We did not observe any evidence for metal-organic network formation on Ag(111), even after varying the deposition parameters or the order of metal and porphyrin deposition. Our study shows that cyano functionalization of porphyrins can give rise to novel and unique self-assembled structures like 1D molecular chains without any cross-connections via adatom linking.

Adsorption energies of porphyrins on MgO(100): An experimental benchmark for dispersion-corrected density-functional theory - Wolfram, Alexander; Tariq, Quratulain; Fernández, Cynthia C.; Muth, Maximilian; Gurrath, Martin; Wechsler, Daniel; Franke, Matthias; Williams, Federico J.; Steinrück, Hans-Peter; Meyer, Bernd; Lytken, Ole (Surface Science, 2022)
Using temperature-programmed desorption, adsorption energies of metallotetraphenylporphyrins were measured and used as a benchmark for dispersion-corrected density-functional theory calculations. Experimentally, simple Redhead analysis was used to extract monolayer adsorption energies for cobalt, zinc and magnesium 5,10,15,20-tetraphenyl porphyrin on MgO(100) thin films grown on Ag(100), where the prefactor for desorption was calculated by transition-state theory. Magnesium exhibits the highest experimental adsorption energy of 217 kJ/mol, while zinc and cobalt have adsorption energies of 193 and 186 kJ/mol, respectively. Using density-functional theory with a modified Grimme D3 scheme resulted in calculated adsorption energies of 209, 171 and 174 kJ/mol. The trend and even the absolute values of the experiment and the theory are in good agreement. Additionally, the calculations allow us to break down the different contributions to the adsorption energies, showing the interplay of van der Waals interactions, chemical bonds and deformation energies.
CRIS-Team Scopus Importer:2021-12-24
Keywords: Adsorption energies; Dispersion-corrected density-functional theory; MgO(100); Porphyrins; Temperature-programmed desorption

Adsorption geometry of carboxylic acid functionalized porphyrin molecules on TiO2(110) - Fernández, Cynthia C.; Wechsler, Daniel; Rocha, Tulio C.R.; Steinrück, Hans-Peter; Lytken, Ole; Williams, Federico J. (Surface Science, 2019)
Controlling the adsorption geometry of porphyrin molecules on titania surfaces is an important step in the rational design of molecular devices such as dye-sensitized solar cells. We employed X-ray Photoelectron Spectroscopy (XPS) and Near-Edge X-Ray-Absorption Fine Structure (NEXAFS) spectroscopy to determine the binding mode, the electronic structure and the adsorption geometry of carboxylic acid functionalized tetraphenylporphyrin molecules. Molecules with one (mono), two (cis and trans) and four (tetra) carboxylic acid anchoring groups were adsorbed on rutile TiO2(110). XPS shows that the iminic nitrogen atoms at the macrocycle center are partially protonated after adsorption, and that the degree of protonation increases with the number of –COOH functional groups in the molecule. NEXAFS measurements show that molecules with either one or two groups in cis configuration adsorb with the macrocycle tilted away from the surface. In contrast, molecules with two carboxylic-acid groups in trans configuration adsorb with what is probably a flat-lying, but distorted macrocycle. Finally, molecules with four carboxylic-acid groups show no linear dichroism, indicating an intermediate adsorption angle. Our results show how the number and position of the –COOH functional groups determine the molecular adsorption geometry.
CRIS-Team Scopus Importer:2019-07-16
Keywords: Adsorption geometry; Carboxylic acids; Near Edge X-Ray Absorption Fine Structure; Porphyrin molecules; Titanium oxide; X-ray photoelectron spectroscopy

Adsorption kinetics of CO on Cr/Ru surfaces - Denecke, Reinhard; Tränkenschuh, Barbara; Engelhardt, Martin Peter; Steinrück, Hans-Peter (Surface Science, 2003)
We report on sticking coefficient measurements for CO adsorption at 90 K on differently prepared Cr layers on Ru(0 0 0 1). Using a supersonic molecular beam we study initial and coverage-dependent sticking coefficients, S and S(θ), respectively, as function of the kinetic energy of the CO molecules. For a pseudomorphic Cr monolayer (prepared at 700 K), S decreases from 0.93 for low kinetic energies (0.09 eV) to 0.82 at 0.4 eV, and stays unchanged for higher kinetic energies up to 2.15 eV. In contrast, on a Cr/Ru surface alloy (for Cr deposition at 1000 K) S closely follows the behavior of clean Ru(0 0 0 1), decreasing from 0.93 to about 0.6 for 2.15 eV. The coverage-dependent sticking coefficients at low kinetic energies show pronounced precursor-mediated behavior, while for higher kinetic energies a Langmuir-like adsorption kinetics is found, which is most prominent for the Cr monolayer. © 2003 Elsevier Science B.V. All rights reserved.

Adsorption Motifs and Molecular Orientation at the Ionic Liquid/Noble Metal Interface: [C(2)C(1)Im][NTf2] on Pt(111) - Hohner, Chantal; Fromm, Lukas; Schuschke, Christian; Taccardi, Nicola; Xu, Tao; Wasserscheid, Peter; Görling, Andreas; Libuda, Jörg (Langmuir, 2021)
In solid catalysts with ionic liquid layers (SCILLs), ionic liquid (IL) thin films are used to modify the activity and selectivity of catalytic materials. In this work, we investigated the adsorption behavior of the IL 1-ethyl-3-methyl-imidazolium bis(trifluoromethylsulfonyl)imide [C(2)C(1)Im][NTf2] on Pt(111) by combining experimental and theoretical studies. Under ultrahigh vacuum (UHV) conditions, the IL was deposited onto a Pt(111) single crystal surface by physical vapor deposition (PVD) at different surface temperatures (200, 300, and 400 K). The adsorption process was monitored by in situ infrared reflection absorption spectroscopy (IRAS). Complementary to the IRAS studies, we performed density functional theory (DFT) calculations and analyzed the adsorption motifs and orientation of the IL ions. In total, we calculated four different systems: (a) [C(2)C(1)Im](+) and [NTf2](-) ions in the gas phase; [NTf2](-) anions in (b) small (4 x 4) and (c) large (6 x 6) Pt(111) supercells; and (d) a complete ion pair of [C(2)C(1)Im][NTf2] in a (6 x 6) Pt(111) supercell. Based on DFT, we simulated IR spectra and compared them to the experimental data. Our results suggest that the binding motif and orientation of the IL is strongly dependent on the actual IL coverage. In the monolayer (ML), [NTf2](-) interacts strongly with the metal surface and adopts a specific orientation in which it interacts with the Pt surface via the SO2 groups. Also the [C(2)C(1)Im](+) cations adopt a preferential orientation up to coverages of 1 ML. Upon transition to the multilayer region, the specific orientation of the ions is gradually lost.
CRIS-Team WoS Importer:2021-11-12

Adsorption of cobalt (II) octaethyIporphyrin and 2H-octaethylporphyrin on Ag(111): New insight into the surface coordinative bond - Bai, Yun; Buchner, Florian; Kellner, Ina; Schmid, Martin; Vollnhals, Florian; Steinrück, Hans-Peter; Marbach, Hubertus; Gottfried, Michael (New Journal of Physics, 2009)
The adsorption of cobalt (II) octaethylporphyrin (CoOEP) and 2H-octaethylporphyrin (2HOEP) on Ag(111) was investigated with scanning tunneling microscopy (STM) and photoelectron spectroscopy (XPS/UPS), in order to achieve a detailed mechanistic understanding of the surface chemical bond of coordinated metal ions. Previous studies of related systems, especially cobalt (II) tetraphenylporphyrin (CoTPP) on Ag(111), have revealed adsorptioninduced changes of the oxidation state of the Co ion and the appearance of a new valence state. These effects were attributed to a covalent interaction of the Co ion with the silver substrate. However, recent studies show that the porphyrin ligand of adsorbed CoTPP undergoes a pronounced saddle-shape distortion, which could alter the electronic structure and thus provide an alternative explanation for the new valence state previously attributed to the formation of a surface coordinative bond. With the octaethylporphyrins investigated here, which were found to adsorb in a flat, undistorted conformation on Ag(111), the effects of geometric distortion can be separated from those of the electronic interaction with the substrate. The CoOEP monolayer gives rise to an adsorption-induced shift of the Co 2p signal (-1.9 eV relative to the multilayer), a new valence state at 0.6 eV below the Fermi energy, and a work-function shift of -0.84eV (2HOEP: -0.44eV) relative to the clean surface. Comparison with data for the distorted CoTPP confirms the existence of a covalent ion-surface interaction that is insensitive to the conformation of the ligand. © IOP Publishing Ltd and Deutsche Physikalische Gesellschaft.

Adsorption of CO on ultrathin Cr layers on Ru(0 0 0 1) - Engelhardt, Martin Peter; Fuhrmann, Thomas; Held, Georg; Denecke, Reinhard; Steinrück, Hans-Peter (Surface Science, 2002)
We studied the adsorption of CO on ultrathin Cr layers on Ru(0 0 0 1) as a function of Cr coverage and deposition temperature. The preparation of the Cr layers was characterized by Auger electron spectroscopy, low energy electron diffraction, and the subsequent CO adsorption itself. At 90 K Cr grows statistically on Ru(0 0 0 1). For Cr deposition at 700 K, a pseudomorphic monolayer is formed; thereafter Cr grows in three dimensional islands and the formation of a highly ordered bcc(1 1 0) Cr phase is observed. For Cr deposition at 1000 K we propose the formation of a stable surface alloy. Temperature programmed desorption of CO after dosing onto the Cr layers prepared at 700 and 1000 K indicates an enhanced reactivity of the layers towards CO dissociation upon heating as compared to Ru(0 0 0 1). In both cases a high temperature CO desorption state (above 700 K) is observed that is attributed to recombinative desorption of CO; its intensity increases up to a nominal Cr coverage of 1 ML. For the Cr layers prepared at 700 K, this state is observed already at the lowest Cr coverage studied (0.12 ML); for 1 ML Cr, 47% of the saturated CO layer decompose upon heating. For the Cr layers prepared at 1000 K (surface alloy) significant decomposition is observed only for Cr coverages larger than 0.5 ML; a maximum fraction of 18% of the saturated CO layer decomposes upon heating. Thus, the Cr layer prepared at 700 K is more reactive towards CO dissociation than the one prepared at 1000 K. © 2002 Elsevier Science B.V. All rights reserved.

Adsorption of phenylphosphonic acid on rutile TiO2(110) - Köbl, Julia; Wechsler, Daniel; Kataev, Elmar; Williams, Federico J.; Tsud, Nataliya; Franchi, Stefano; Steinrück, Hans-Peter; Lytken, Ole (Surface Science, 2020)
Binding of functionalized organic molecules to oxide surfaces is an important step in the rational design of molecular devices. In the present investigation, we used synchrotron radiation photoelectron spectroscopy and near-edge X-ray absorption fine structure spectroscopy to determine the binding mode, electronic structure and adsorption geometry of phenylphosphonic acid (PPA) on TiO2(110)–(1 × 1). We found that PPA multilayers desorb below 380 K leaving a compact PPA monolayer adsorbed on the surface, which remains stable up to 780 K. In the 380–520 K temperature range, molecules are anchored to the surface via a single P–O–Ti covalent bond (monodentate configuration). Furthermore, the phenyl ring is tilted 45° with respect to the surface plane and it either forms 45° or is randomly oriented with respect to [001] crystallographic direction. Raising the temperature above 520 K partially transforms the monodentate configuration to a mixed one- and twofold deprotonated bidentate binding mode, presumably after surface hydroxyl groups leave the surface as water molecules. This change in molecular binding does not alter the molecular electronic structure nor the adsorption geometry, which remain essentially unchanged.
CRIS-Team Scopus Importer:2020-06-05

Adsorption of Phosphonic-Acid-Functionalized Porphyrin Molecules on TiO2(110) - Fernández, Cynthia C.; Wechsler, Daniel; Rocha, Tulio C.R.; Steinrück, Hans-Peter; Lytken, Ole; Williams, Federico J. (Journal of Physical Chemistry C, 2019)
We studied the adsorption geometry and bonding of mono- and tetraphosphonic-acid-functionalized tetraphenylporphyrin molecules on rutile TiO 2 (110) surfaces. The investigation was carried out by means of X-ray photoelectron spectroscopy and near edge X-ray absorption fine structure (NEXAFS) measurements. We found that the molecules bind covalently to the surface in a mixed monodentate and bidentate mode implying deprotonation of one or two phosphonate hydroxyl groups. Our NEXAFS data suggest that molecules containing one functional phosphonic acid group are on average tilted further away from the surface than molecules with four functional groups. The highest occupied electronic state of both molecules is in the band gap at 2.1 eV below the Fermi level. Our results demonstrate that the number of functional phosphonic acid groups determine the adsorption geometry of tetraphenylporphyrins.
CRIS-Team Scopus Importer:2019-05-14

Adsorption of (Small) Molecules on Metals - Denecke, Reinhard; Steinrück, Hans-Peter (Wiley Blackwell, 2016)
The adsorption of small molecules is a major step in surface reactions typically involved in heterogeneous catalysis. The detailed description of this process and the resulting adsorbate layer is essential in order to fully understand such systems. In this chapter, the adsorption process is described, and selected examples are discussed, demonstrating how this process can be investigated by spectroscopic methods, often combined with molecular beam techniques. Emphasis is put on stepped substrates as model systems for more complex catalytic particles. As a next step, the geometric structure of adsorbate layers is discussed, again including different investigation methods. Closely related to the geometric structure is the electronic structure of the adsorbed layers. Here, different examples are presented to illustrate how the orientation of adsorbed molecules and the resulting two-dimensional band structure can be derived using angle-resolved ultraviolet photoelectron spectroscopy.
Keywords: Adsorption; Band structure; Benzene; CO; Electronic structure; Ethylene; Geometric structure; Model system; Molecular beam techniques; Oxygen; Single crystal; Spectroscopy

Adsorption, Ordering, and Metalation of Porphyrins on MgO Nanocube Surfaces: The Directional Role of Carboxylic Anchoring Groups - Schneider, Johannes; Kollhoff, Fabian; Schindler, Torben; Bichlmaier, Stephan; Bernardi, Johannes; Unruh, Tobias; Libuda, Jörg; Berger, Thomas; Diwald, Oliver (Journal of Physical Chemistry C, 2016)
The understanding of porphyrin adsorption on oxide nanoparticles including knowledge about coverages and adsorbate geometries is a prerequisite for the improvement and optimization of hybrid materials. The combination of molecular spectroscopies with small-angle X-ray scattering provides molecular insights into porphyrin adsorption on MgO nanocube dispersions in organic solvents. In particular, we address the influence of terminal carboxyl groups on the adsorption of free base porphyrins, on their chemical binding, on the metalation reaction as well as on the coverage and orientation of adsorbate molecules. We compare the free base form 5,10,15,20-tetraphenyl-21,23H-porphyrin (2HTPP) with the carboxyl-functionalized 5,10,15,20-tetrakis(4-carboxyphenyl)-21,23H-porphyrin (2HTCPP) and show that without carboxylic anchoring groups the free base form metalates on the nanocube surface and adopts a flat-lying adsorbate geometry. The saturation limit for flat-lying adsorption on nanocubes with an average edge length of 6 nm corresponds to 90 14 molecules per particle. This limit is surpassed when 2HTCPP molecules attach via their terminal carboxyl groups to the surface. The resulting upright adsorption geometry suppresses self-metalation, on the one hand, and allows for much higher porphyrin coverages, on the other (at porphyrin concentrations in the stock solution of 2 X 10(-2) mol.L-1). UV-vis diffuse reflectance results are perfectly consistent with conclusions from SAXS data analysis. The experiments reveal concentration dependent 2HTCPP coverages in the range between 0.4 to 1.9 molecules nm(-2) which correspond to the formation of a shell of upright standing porphyrin molecules around the MgO nanocubes. In contrast, after adsorption and metalation of nonfunctionalized 2HTPP the resulting porphyrin shells are in the range of a tenth of a nanometer and thus too thin to be captured by SAXS measurements. Related insights advance our opportunities to prepare well-defined nanohybrids containing highly organized porphyrin films.

Adsorption probabilities of H2 and D2 on various flat and stepped nickel surfaces - Steinrück, Hans-Peter; Luger, M.; Winkler, A.; Rendulic, K.D. (Physical Review B, 1985)
From the measurement of the angular variation of the sticking coefficient and its change with beam energy one can conclude that adsorption of hydrogen on Ni(111) is an activated process whereas on Ni(110) no activation barrier exists. Adsorption on a stepped Ni(997) surface exhibits a pronounced minimum of the sticking coefficient at a gas temperature of 230 K. The activity of the steps for dissociation of H2 is confined to low gas temperatures. Detailed balancing is obeyed rigorously for adsorption and desorption on the Ni(111) and Ni(110) surface even at situations deviating from quasiequilibrium. On the stepped surface on the other hand establishing microscopic reversibility requires strict adherence to quasiequilibrium conditions. Permeation experiments lead to good agreement with low-temperature desorption on the Ni(111) surface but to complete disagreement with the data for the Ni(110) surface. As suggested by Comsa, permeating hydrogen in some cases seems to originate from a subsurface location rather than from an adsorbed state. Besides a small effect at low temperatures on the Ni(997) and Ni(110) surfaces no isotope effects for H2 and D2 are detected. © 1985 The American Physical Society.

Adsorption Properties of Stepped Surfaces. - Karner, H.; Luger, M.; Steinrück, Hans-Peter; Rendulic, K.D.; Winkler, A. (Vacuum, 1985)
We have determined the sticking probability of hydrogen and deuterium on a stepped nickel surface at different adsorption angles and for different surface and gas temperatures. The initial sticking coefficient shows a highly asymmetric behavior with respect to the surface normal; hydrogen molecules at room temperature impinging in the 'step-up' direction have a considerably higher sticking probability than the 'step-down' direction. This behavior is more pronounced for lower gas temperatures (T equals 150 K) and almost vanishes for higher gas temperatures (T equals 900 K). Blocking the active step sites with oxygen reduces the asymmetric adsorption behavior yielding an angular variation similar to the adsorption on a flat Ni(111) surface. The influence of the surface temperature on the sticking coefficient is much less pronounced in the experimentally accessible region (150-300 K). In the behavior of hydrogen and deuterium there are no prominent differences.

Adsorption sites, metal-support interactions, and oxygen spillover identified by vibrational spectroscopy of adsorbed CO: A model study on Pt/ceria catalysts - Happel, Markus; Myslivecek, Josef; Johanek, Viktor; Dvorak, Filip; Stetsovych, Oleksandr; Lykhach, Yaroslava; Matolin, Vladimir; Libuda, Jörg (Journal of Catalysis, 2012)
Vibrational spectroscopy of adsorbed CO is commonly used for the characterization of oxide-supported metal catalysts, in spite of persisting ambiguities concerning the band assignment. Here, we present reference data on well-defined Pt/CeO2(1 1 1)/Cu(1 1 1) model catalysts aiming at clear identification of the related features. Growth and morphology of the Pt particles are investigated by scanning tunneling microscopy (STM), the adsorption properties are probed by temperature programmed desorption (TPD), and the electronic structure has previously been studied by photoelectron spectroscopy (PES) and resonant photoelectron spectroscopy (RPES). Combining molecular beam (MB) methods and infrared reflection absorption spectroscopy (IRAS), we correlate this information to the interaction with CO.Two types of defect adsorption sites are identified on the ceria support (2097 cm(-1), 2120 cm(-1)), which are assigned to structural defects and reduced Ce3+ centers. The relative abundance of these sites changes upon thermal treatment. On the Pt nanoparticles, CO first adsorbs on-top at step and edge sites (2066 cm(-1)), before adsorption on the (1 1 1) facets occurs in bridging (1875 cm(-1)) and on-top (2080-2097 cm(-1)) geometry. For the first time, we identify vibrational CO features, which arise from electronic metal-support interactions and from oxygen reverse spillover. On reduced CeO2-x(1 1 1), a red-shifted band at 2053 cm(-1) appears, which is attributed to increased pi-backbonding from Pt to CO, as a result of a change in electronic metal-oxide interaction. Thermal treatment also activates oxygen reverse spillover from the support to the Pt nanoparticle, which gives rise to a blue-shifted feature in the CO spectrum (2090-2105 cm(-1)) due to coadsorbed oxygen next to CO sites. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Model catalysis; Cerium oxide; Platinum; Metal-oxide interaction; Carbon monoxide; Infrared spectroscopy; Scanning tunneling microscopy

Adsorption Structure of Cobalt Tetraphenylporphyrin on Ag(100) - Wechsler, Daniel; Franke, Matthias; Tariq, Quratulain; Zhang, Liang; Lee, Tien-Lin; Thakur, Pardeep Kumar; Tsud, Nataliya; Bercha, Sofiia; Prince, Kevin Charles; Steinrück, Hans-Peter; Lytken, Ole (Journal of Physical Chemistry C, 2017)
Using a combination of LEED, high-resolution XPS, XSW, and NEXAFS, we have studied the adsorption of cobalt(II) 5,10,15,20-tetraphenylporphyrin (CoTPP) on Ag(100) at 300 K. In agreement with previous studies on Ag(111), we find a charge transfer from the silver surface to the porphyrin molecule, reducing the metal center. At high coverages we observe a square-shaped 1.41 X 1.41 nm(2) adsorption structure, which becomes more open at lower coverages. Because of the superior energy resolution of the Diamond i09 beamline, we are able to resolve a low binding-energy shoulder in the C 1s spectrum, originating from the lower carbon atoms in the rotated phenyl rings. This is confirmed by XSW measurements, which also gives the adsorption heights of the other atoms in the molecule. In addition, the XSW and complementary NEXAFS measurements yield information about the rotation of the phenyl rings and the deformation of the macrocycle.

Adsorption, Wetting, Growth, and Thermal Stability of the Protic Ionic Liquid Diethylmethylammonium Trifluoromethanesulfonate on Ag(111) and Au(111) - Massicot, Stephen; Sasaki, Tomoya; Lexow, Matthias; Shin, Sunghwan; Maier, Florian; Kuwabata, Susumu; Steinrück, Hans-Peter (Langmuir, 2021)
We have studied the adsorption, wetting, growth, and thermal evolution of the protic IL diethylmethylammonium trifluoromethanesulfonate ([dema][TfO]) on Au(111) and Ag(111). Ultrathin films were deposited at room temperature (RT) and at 90 K, and were characterized in situ by angle-resolved X-ray photoelectron spectroscopy. For both surfaces, we observe that independent of temperature, initially, a closed 2D wetting layer forms. While the film thickness does not increase past this wetting layer at RT, at 200 K and below, "moderate"3D island growth occurs on top of the wetting layer. Upon heating, on Au(111), the [dema][TfO] multilayers desorb at 292 K, leaving an intact [dema][TfO] wetting layer, which desorbs intact at 348 K. The behavior on Ag(111) is much more complex. Upon heating [dema][TfO] deposited at 90 K, the [dema]+ cations deprotonate in two steps at 185 and 305 K, yielding H[TfO] and volatile [dema]0. At 355 K, the formed H[TfO] wetting layer partly desorbs (∼50%) and partly decomposes to form an F-containing surface species, which is stable up to 570 K.
CRIS-Team Scopus Importer:2021-10-29

Advanced and In-Situ Electron Microscopy Investigation of Phase Composition and Phase Transformation in Ga-Rh Liquid Metal Catalysts - Wu, Mingjian; Grabau, Mathias; Taccardi, Nicola; Papp, Christian; Steinrück, Hans-Peter; Wasserscheid, Peter; Spiecker, Erdmann (Microscopy and Microanalysis, 2019)

Advanced thin film technology for ultrahigh resolution X-ray microscopy - Fink, Rainer; Raabe, Jörg; David, Christian; et al. (Ultramicroscopy, 2009)
Further progress in the spatial resolution of X-ray microscopes is currently impaired by fundamental limitations in the production of X-ray diffractive lenses. Here, we demonstrate how advanced thin film technologies can be applied to boost the fabrication and characterization of ultrahigh resolution X-ray optics. Specifically, Fresnel zone plates were fabricated by combining electron-beam lithography with atomic layer deposition and focused ion beam induced deposition. They were tested in a scanning transmission X-ray microscope at 1.2 keV photon energy using line pair structures of a sample prepared by metalorganic vapor phase epitaxy. For the first time in X-ray microscopy, features below 10 nm in width were resolved. © 2009 Elsevier B.V. All rights reserved.

A facile approach to synthesize an oxo-functionalized graphene/polymer composite for low-voltage operating memory devices - Wang, Zhenxing; Eigler, Siegfried; Ishii, Yoshitaka; Hu, Yichen; Papp, Christian; Lytken, Ole; Steinrück, Hans-Peter; Halik, Marcus (Journal of Materials Chemistry C, 2015)
Memory devices are a key technology of our era and one of the constant challenges is the reduction of their power consumption. Herein, we demonstrate that graphene oxide with very few defects, that is, about 1 nm thin oxo-functionalized graphene derivative, can be used in memory devices operating at 3 V. A memory device stores charges in the material of the active channel. Thereby, writing and erasing information can be performed at low voltage, facilitating low power consumption. To enable operation at low voltage, a novel synthetic approach is necessary. We find that the selective non-covalent electrostatic functionalization of mainly organosulfate ions is possible with dodecylammonium. This functionalization allows the non-covalent coating of flakes with a polystyrene-derivative as nm-thin dielectric medium. The resulting polymer-wrapped composite has a height of about 5 nm. We find that the thin coating of a few nm is mandatory to make the memory device work at low voltage. Furthermore, a self-assembled monolayer of an imidazolium derivative further enhances the function of the memory device. The prepared composite materials are characterized by state-of-the-art analysis including solid state nuclear magnetic resonance spectroscopy and thermogravimetric analysis coupled with gas chromatography, mass spectroscopy or infrared spectroscopy. Reference experiments prove the importance of the controlled synthesis to enable the function of the memory device.

A fast x-ray photoelectron spectroscopy study of the adsorption and temperature-dependent decomposition of propene on Ni(100) - Whelan, Caroline; Neubauer, Ralf; Borgmann, Dieter; Denecke, Reinhard; Steinrück, Hans-Peter (Journal of Chemical Physics, 2001)
Propene uptake at 105 was experimentally studied. A single molecular adsorption state was observed. Changes in methyl group peak binding energy revealed adsorbate-adsorbate interactions and a dispersed phase growth mechanism. A notable result is the observation that a new surface species evolves above 200 K from decomposition of di-σ-bonded propene.

A generic interface to reduce the efficiency-stability-cost gap of perovskite solar cells - Hou, Yi; Du, Xiaoyan; Scheiner, Simon; McMeekin, David P.; Wang, Zhiping; Li, Ning; Killian, Manuela; Chen, Haiwei; Richter, Moses; Levchuk, Ievgen; Schrenker, Nadine; Spiecker, Erdmann; et al. (Science, 2017)
A major bottleneck delaying the further commercialization of thin-film solar cells based on hybrid organohalide lead perovskites is the interface losses in state-of-the-art devices. We present a generic interface architecture that combines solution-processed, reliable, and cost-efficient hole-transporting materials, without compromising efficiency, stability or scalability of perovskite solar cells. Tantalum doped tungsten oxide (Ta-WOx)/conjugated polymer multilayers offer a surprisingly small interface barrier and form quasi-ohmic contacts universally with various scalable conjugated polymers. Using a simple regular planar architecture device, Ta-WOx doped interface-based perovskite solar cells achieve maximum efficiencies of 21.2% and combined with over 1000 hours of light stability based on a self-assembled monolayer. By eliminating additional ionic dopants, these findings open up the whole class of organics as scalable hole-transporting materials for perovskite solar cell

A Highly Transparent Self-Powered Touch Sensor Based on Hierarchical (Micro-Nano) Cu Grid on Polyethylene Terephthalate Composite Electrodes for Smart Wear - Cao, Weiqi; Shaker, Majid; Lei, Wenqian; Yu, Hua (Journal of Materials Engineering and Performance, 2023)
With the expansion of the applications of sensors, requirements such as flexibility, visual transparency, and self-powering have become critical. In this work, firstly we have adopted photoetch and hierarchical (micro-nano) manufacturing techniques to fabricate a micro-scale copper grid on polyethylene terephthalate (PET). This material (Cu grid @PET) exhibits high transmittance (89% at 550 nm, only 2.7% lower than PET substrate) and low electric resistance (6.7 Ω sq−1) compared with other reports. Then, the as-fabricated Cu grid @PET composite electrode, poly-dimethylsiloxane (PDMS), and polymethyl methacrylate (PMMA) were utilized to fabricate a sandwich-like structured transparent self-powered sensor (TSPFS) with high optical transmittance of 85.5-87.5% (450 620 nm). A complete novel control method combining with sensor’s electrical signal test was implemented by Dynamic Mechanical Analyzer (DMA), verifying the simulation response to space of COMSOL. Voltage signals could be also observed when the sensor was touched by fingers without receiving electric energy from external sources. Finally, the paper shows a kind of smart goggles made of the produced transparent device, exhibiting heating, antifogging, and sensing functions.
CRIS-Team Scopus Importer:2023-03-03
Keywords: coating; laser photoetching; smart wear; transparent and flexible electrode; zero-energy sensor

A high-resolution X-ray photoelectron spectroscopy study on the adsorption and reaction of ethylene on Rh(1 1 1) - Freiberger, Eva Marie; Düll, Fabian; Wichmann, Christoph; Bauer, Udo; Steinrück, Hans-Peter; Papp, Christian (Chemical Physics Letters, 2022)
The adsorption and thermal evolution of ethylene on Rh(1 1 1) were investigated by state-of-the-art surface science techniques. Synchrotron radiation-based high-resolution X-ray photoelectron spectroscopy (XPS) and temperature-programmed XPS allowed for the examination of the adsorption process and the reaction pathway of ethylene on Rh(1 1 1). At 140 K, ethylene adsorbs molecularly in a symmetrical geometry. The reaction intermediates formed upon heating were identified by the vibrational fine structure of XPS. At approximately 200 K, ethylidyne emerges, as expected from literature. Above 350 K, we observe the evolution of methylidyne. Simultaneously, decomposition to carbides sets in, which is completed at ∼ 460 K.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Coking; Ethylene; Ethylidyne; High-resolution X-ray photoelectron spectroscopy; Methylidyne; Rhodium; Unsaturated hydrocarbons; Vibrational fine structure

A HR-XPS study of the formation of h-BN on Ni(111) from the two precursors, ammonia borane and borazine - Bachmann, Philipp; Düll, Fabian; Späth, Florian; Bauer, Udo; Steinrück, Hans-Peter; Papp, Christian (Journal of Chemical Physics, 2018)
Together with borazine, ammonia borane is a prominent precursor molecule for the formation of hexagonal boron nitride, which is of high interest as a 2D-material and graphene analog. Ammonia borane is also a possible solid hydrogen carrier for renewable energies with high storage density. Using X-ray photoelectron spectroscopy and temperature-programmed desorption, we investigated low-temperature adsorption and dehydrogenation during heating of borazine and ammonia borane on Ni(111) to form h-BN. For borazine, we observe the formation of disordered boron nitride above 300 K, which starts to form hexagonal boron nitride above 600 K. Ammonia borane shows multiple dehydrogenation steps at the boron and nitrogen atoms up to 300 K. This results in various BHxNHy species, including borazine-like intermediates, before the formation of disordered boron nitride and finally hexagonal boron nitride, analogous to the borazine decomposition. Published by AIP Publishing.

Alkyl chain length-dependent surface reaction of dodecahydro-N-alkylcarbazoles on Pt model catalysts - Gleichweit, Christoph; Amende, Maximilian; Bauer, Udo; Schernich, Stefan; Höfert, Oliver; Lorenz, Michael Peter Andreas; Zhao, Wei; Müller, Michael; Koch, Marcus; Bachmann, Philipp; Wasserscheid, Peter; Libuda, Jörg; et al. (Journal of Chemical Physics, 2014)
The concept of liquid organic hydrogen carriers (LOHC) holds the potential for large scale chemical storage of hydrogen at ambient conditions. Herein, we compare the dehydrogenation and decomposition of three alkylated carbazole-based LOHCs, dodecahydro-N-ethylcarbazole (H-NEC), dodecahydro-N- propylcarbazole (H-NPC), and dodecahydro-N-butylcarbazole (H -NBC), on Pt(111) and on AlO-supported Pt nanoparticles. We follow the thermal evolution of these systems quantitatively by in situ high-resolution X-ray photoelectron spectroscopy. We show that on Pt(111) the relevant reaction steps are not affected by the different alkyl substituents: for all LOHCs, stepwise dehydrogenation to NEC, NPC, and NBC is followed by cleavage of the C-N bond of the alkyl chain starting at 380-390 K. On Pt/AlO, we discern dealkylation on defect sites already at 350 K, and on ordered, (111)-like facets at 390 K. The dealkylation process at the defects is most pronounced for NEC and least pronounced for NBC. © 2014 AIP Publishing LLC.

A LOW COVERAGE STUDY OF NO ON NI(111) BY ANGLE RESOLVED AUGER-ELECTRON SPECTROSCOPY AT RESONANCE EXCITATION - Steinrück, Hans-Peter; Pache, T.; Huber, W. (Physica Scripta, 1990)

A microspectroscopic insight into the resistivity switching of individual Ag-TCNQ nanocrystals - Rösner, Benedikt; Ran, Ke; Butz, Benjamin; Schmidt, Ute; Spiecker, Erdmann; Fink, Rainer (Physical Chemistry Chemical Physics, 2015)
We investigate the resistivity switching in individual Ag-TCNQ wires with on/off-ratios of up to 103. Raman and soft X-ray absorption microspectroscopy studies disclose reverse charge transfer. Quantifying of the fraction of neutral TCNQ within the switched material yields values up to 22.3%. These findings expedite the understanding of the switching process in Ag-TCNQ nanowires.

A modern look at a medieval bilayer metal leaf: nanotomography of Zwischgold - Wu, Qing; Soppa, Karolina; Mueller, Elisabeth; Mueller, Julian; Odstrcil, Michal; Tsai, Esther Hsiao Rho; Späth, Andreas; Holler, Mirko; Guizar-Sicairos, Manuel; Butz, Benjamin; Fink, Rainer; Watts, Benjamin (Nanoscale, 2022)
Many European sculptures and altarpieces from the Middle Ages were decorated with Zwischgold, a bilayer metal leaf with an ultra-thin gold face backed by silver. Zwischgold corrodes quickly when exposed to air, causing the surface of the artefact to darken and lose gloss. The conservation of such Zwischgold applied artefacts has been an obstinate problem. We have acquired quantitative, 3D nanoscale images of Zwischgold samples from 15th century artefacts and modern materials using ptychographic X-ray computed tomography (PXCT), a recently developed coherent diffractive imaging technique, to investigate the leaf structure and chemical state of Zwischgold. The measurements clearly demonstrate decreasing density (increasing porosity) of the leaf materials and their corrosion products, as well as delamination of the leaves from their substrate. Each of these effects speak to typically observed issues in the conservation of such Zwischgold applied artefacts. Further, a rare variant of Zwischgold that contains extremely thin multiple gold layers and an overlapping phenomenon of Zwischgold with other metal leaves are observed through PXCT. As supportive data, scanning electron microscopy (SEM) and scanning transmission electron microscopy (STEM) coupled with energy dispersive X-ray analysis (EDX) were performed on the medieval samples.
CRIS-Team Scopus Importer:2022-11-04

A molecular beam investigation on the kinetic energy dependence of the activation of ethane on the reconstructed Ir(110)-(1 × 2) surface - Steinrück, Hans-Peter; Hamza, Alex; Madix, R.J. (Surface Science, 1986)
Using molecular beam techniques we have investigated the initial dissociative sticking probability for ethane on a reconstructed Ir(110)-(1 × 2) surface. At kinetic energies below 15 kcal mol the probability of activation at zero surface coverage, S, is constant at about 0.03. With increasing beam energy S increases nearly linearly to a value of 0.40 at an energy near 40 kcal mol. Variation of surface temperature in the range 300 ≤ T ≤ 1400 K does not influence the dependence of S on kinetic energy. © 1986.

A molecular beam study of the adsorption dynamics of CO on Ru(0001), Cu(111) and a pseudomorphic Cu monolayer on Ru(0001) - Kneitz, Stefan; Gemeinhardt, J.; Steinrück, Hans-Peter (Surface Science, 1999)
We have investigated the sticking coefficient of CO on Ru(0001), a pseudomorphic Cu monolayer on Ru(0001), and a fully relaxed Cu(111) multilayer as function of kinetic energy, surface coverage, and surface temperature. At a low kinetic energy of 0.09 eV, the initial sticking coefficients, S , on these surfaces are determined to be 0.92, 0.96 and 0.87, respectively. In all cases, a decrease of S with increasing beam energy was observed, yielding values of 0.58, 0.14 and 0.07, respectively, at a kinetic energy of ∼2.0 eV. For all three surfaces the coverage dependent sticking coefficients, S(Θ), display very characteristic behavior at low kinetic energies: S(Θ) remains more or less constant up to coverages close to saturation, indicative of precursor adsorption kinetics. However, characteristic minima at intermediate coverages are observed, which are correlated to the formation of well ordered adsorbate phases. For high kinetic energies we observe a transition towards a linear decrease of S(Θ) for Ru(0001). In contrast, for the pseudomorphic Cu monolayer and for Cu(111) we find an increase in the sticking coefficients at low coverages, followed by a decrease close to saturation. This behavior is attributed to adsorbate assisted sticking, that is, to a higher sticking coefficient on adsorbate covered regions than on the bare surface. The comparison between the pseudomorphic monolayer and Cu(111) reveals that the CO bond strength to the former is larger by ∼40%. The initial sticking coefficients for both surfaces are very similar at low kinetic energies; at high kinetic energies, S for the pseudomorphic Cu monolayer is, however, larger by a factor of two. © 1999 Elsevier Science B.V. All rights reserved.

A Molecular Popeye: Li+@C60 and its Complexes with [n]Cycloparaphenylenes - Freiberger, Markus; Solymosi, Iris; Freiberger, Eva Marie; Hirsch, Andreas; Perez-Ojeda Rodriguez, Maria Eugenia; Drewello, Thomas (Nanoscale, 2023)
In this work, we compare for the first time the stability of [n]cycloparaphenylene ([n]CPP)-based host–guest complexes with Li+@C60 and C60 in the gas and the solution phase. Our gas-phase experiments reveal a significant increase in stability for the complexes featuring [9–12]CPP with Li+@C60. This increased interaction strength is also observed in solution. Isothermal titration calorimetry shows for the formation of [10]CPP⊃Li+@C60 a two orders of magnitude larger association constant than that for the C60 analog. Additionally, an increased binding entropy is observed. This study contributes to a better understanding of host–guest complexes between [n]CPPs and endohedral metallofullerenes at a molecular level, which is the prerequisite for future applications.

A multimethod-investigation of the adsorption of ethylene oxide on Ni(110) - Weinelt, M.; Zebisch, P.; Steinrück, Hans-Peter (Surface Science, 1993)
The adsorption of ethylene oxide on Ni(110) has been studied by TPD, work function measurements, LEED, XPS, and angle resolved UPS using linearly polarized synchrotron radiation. At temperatures below 100 K ethylene oxide adsorbs in molecular form on Ni(110) with a saturation coverage of ∼ 0.5 ML (1 ML = 1 molecule Ni atom). Upon heating, molecular desorption occurs in a broad peak ranging from ∼ 110 to 240 K; there is no indication of dissociation, as concluded from TPD and XPS. At saturation a sharp c(2 × 2) LEED pattern is observed. From ARUPS we deduce that the C rotation axis of the molecule is tilted away from the surface normal and that the mirror planes of the molecule do not coincide with the substrate mirror planes, independent of coverage. © 1993.

An accurate technique to measure angle-resolved flash desorption spectra - Steinrück, Hans-Peter; Winkler, A.; Rendulic, K.D. (Surface Science, 1985)
A collimator system using four apertures is used to select a narrow beam of ∓ 2° opening from a single crystal sample. Since the apertures only "see" a small strip of the sample surface, signals from the edges of the crystal are eliminated. Detector is an ion gauge located off the beam axis to guarantee energy independence of the detected signals. A large number of measurements for varying coverage, different crystal orientations and different azimuth positions of the sample are described for the system H/Ni and CO/Ni. © 1985.

Anchoring of a Carboxyl-Functionlized Norbornadiene Derivative to an Atomically-Defined Cobalt Oxide Surface - Schwarz, Matthias; Mohr, Susanne; Xu, Tao; Döpper, Tibor; Weiß, Cornelius; Civale, Katharina; Hirsch, Andreas; Görling, Andreas; Libuda, Jörg (Journal of Chemical Physics, 2017)
We have investigated the anchoring of the molecular energy carrier norbornadiene (NBD) to an atomically defined oxide surface. To this end, we synthesized a carboxyl-functionalized NBD derivative, namely 1-(2′-norbornadienyl)pentanoic acid (NBDA), and deposited it by physical vapor deposition (PVD) under ultrahigh vacuum (UHV) conditions onto a well-ordered Co3O4(111) film grown on Ir(100). In addition, we performed a comparative growth study with benzoic acid (BA) under identical conditions which was used as a reference. The interaction and orientation of NBDA and BA with the oxide surface were monitored in situ during film growth by isothermal time-resolved infrared reflection–absorption spectroscopy (TR-IRAS), both below and above the multilayer desorption temperature. The thermal behavior and stability of the films were investigated by temperature-programmed IRAS (TP-IRAS), with help of density functional (DF) calculations. BA binds to Co3O4(111) under formation of a symmetric chelating carboxylate with the molecular plane oriented nearly perpendicular to the surface. At low temperature (130 K), intact BA physisorbs in form of dimers on top of the saturated monolayer. Upon annealing to 155 K, a reordering transition is observed, in which BA in the multilayer adopts a more flat-lying orientation. The BA multilayer desorbs at 220 K, whereas the surface-anchored BA monolayer is stable up to 400 K. At higher temperature (400–550 K), desorption and decomposition are observed. Very similar to BA, NBDA binds to Co3O4(111) by formation of a symmetric chelating carboxylate. In the multilayer, which desorbs at 240 K, hydrogen-bonded NBDA dimers are formed. Upon PVD of NBDA at 300 K, only a surface anchored carboxylate is stable. The anchored NBDA film shows a characteristic restructuring behavior as a function of coverage. At low coverage the NBDA, adopts a flat-lying structure in which the norbornadiene unit interacts with the Co3O4 surface. With increasing coverage, the norbornadiene units detach from the oxide and the NBDA adopts an upright-standing orientation. Similar to BA, the anchored film is stable up to 400 K and decomposes in the temperature region between 400 and 550 K, leaving behind hydrocarbon residues on the oxide surface.

Anchoring of carboxyl-functionalized porphyrins on MgO, TiO2, and Co3O4 nanoparticles - Kollhoff, Fabian; Schneider, Johannes; Li, Gao; Barkaoui, Sami; Shen, Wenjie; Berger, Thomas; Diwald, Oliver; Libuda, Jörg (Physical Chemistry Chemical Physics, 2018)
Hybrid materials consisting of functional organic molecules on metal oxide nanomaterials are key components in emerging technologies, for example in energy conversion and molecular electronics. In this work, we present the results of a comparative study of carboxyl-functionalized porphyrins on different oxide nanomaterials. Specifically, we investigated the interaction of 5(3-carboxyphenyl)-10,15,20-triphenyl-21,23H-porphyrin (2H-3-MCTPP) and 5(4-carboxyphenyl)-10,15,20-triphenyl-21,23H-porphyrin (2H-4-MCTPP), on MgO, TiO2, and Co3O4 nanoparticles (NPs) using isothermal and temperature-programmed diffuse reflection infrared Fourier transform spectroscopy (DRIFTS). We show that both porphyrins bind to the NPs, yielding stable monolayer films consisting of tilted surface carboxylates. In all cases, anchoring through the carboxylic acid group suppresses self-metalation of the porphyrin unit. Upon annealing, all anchored porphyrin films undergo metalation. The position of the acid group has no major influence on the reactivity. The same is true for the nature of the metal oxide, suggesting that the observed behaviour is general for most anchored porphyrin films on oxide nanomaterials.

Anchoring of phthalic acid on MgO(100) - Kataev, Elmar; Fromm, Lukas; Tariq, Quratulain; Wechsler, Daniel; Williams, Federico J.; Tsud, Nataliya; Franchi, Stefano; Steinrück, Hans-Peter; Görling, Andreas; Lytken, Ole (Surface Science, 2022)
Carboxylic acids are often used to anchor large organic molecules to oxide surfaces. To understand the mechanism of this anchoring we have studied the temperature and coverage-dependent adsorption and reactions of phthalic acid on MgO(100) by a combination of X-ray photoelectron spectroscopy, near-edge X-ray absorption, UV photoelectron spectroscopy and density-functional theory. At 110 K, phthalic acid partly deprotonates on MgO(100) at low coverage and forms a dicarboxylate species. At higher coverage, the fraction of intact phthalic acid increases to a larger extent than that of the deprotonated species. Subsequent annealing of these mixed structures results in the full conversion of the remaining intact acid groups to carboxylate, that is, doubly deprotonated phthalic acid, at 250 K. Depending on coverage, the carboxylate-bonded species remain stable up to 500 – 600 K. Above this temperature, the molecules decompose and desorb as fragments, leaving only a small carbon residue behind on the surface.
CRIS-Team Scopus Importer:2022-02-25
Keywords: Magnesium oxide; Organic thin films; Phthalic acid; X-ray photoelectron spectroscopy

A new asymmetric Pseudo-Voigt function for more efficient fitting of XPS lines - Schmid, Martin; Steinrück, Hans-Peter; Gottfried, J. Michael (Surface and Interface Analysis, 2014)
Asymmetric peak profiles for the application in spectroscopy can be obtained in a simple way by substituting the usually constant full width at half maximum parameter in Pseudo-Voigt functions with an energy-dependent expression, for instance of sigmoidal shape. While this approach has been successfully applied to vibrational spectra, we find that the resulting curves are less suitable for least-squares fits of X-ray photoelectron spectroscopy (XPS) data. However, if one additionally allows a variable displacement of the sigmoidal step relative to the peak, excellent fitting results can be obtained. We demonstrate the applicability of our extended approach on several inherently asymmetric XPS lines, i.e. the C 1s signal of graphite and CH/Pd(100), the 3d-3d doublet of palladium, and the 4f-4f doublet of platinum. Comparison of the corresponding fit results with the results obtained by the application of more elaborate, theory-based line profiles (Doniach-Šunjić and Mahan functions) shows that the modified Pseudo-Voigt function gives practically identical results in terms of peak shape and area, while requiring much less computational effort since no convolution procedures are required for its calculation. Thus, this function is most suitable for application in one of the following situations: (i) the peak shape of a given signal is known but cannot be calculated with ease, and (ii) the theoretical peak shape is not (yet) known, however, one wants to perform a first quantitative screening of the data at issue. © 2014 John Wiley & Sons, Ltd.

A new asymmetric Pseudo-Voigt function for more efficient fitting of XPS lines (vol 46, pg 505, 2014) - Schmid, Martin; Steinrück, Hans-Peter; Gottfried, Michael (Surface and Interface Analysis, 2015)

An experimental investigation of detailed balancing for the systems H2/nickel and CO/nickel - Steinrück, Hans-Peter; Rendulic, K.D.; Winkler, A. (Proc. Symposium on Surface Science, 1985)
UnivIS-Import:2015-04-16:Pub.1985.nat.dchph.lpc2.anexpe

An experimental investigation of detailed balancing for the systems H2/nickel und CO/nickel - Steinrück, Hans-Peter; Rendulic, K.D.; Winkler, A. (Proceeding on Surface Science 3S'85, 1985)

Angle-resolved photoemission studies of adsorbed hydrocarbons - Steinrück, Hans-Peter (Journal of Physics: Condensed Matter, 1996)
Angle-resolved UV photoelectron spectroscopy is used to investigate the electronic structure and bonding of adsorbed hydrocarbons, the orientation and symmetry of the adsorbate on the surface, the influence of lateral interactions, and the formation of two-dimensional adsorbate band structures. Several examples of simple hydrocarbon molecules such as benzene, ethylene and acetylene adsorbed on Ni(110), Ni(111), Ru(001) and the reconstructed Pt(110)1x2 surface are presented. The experimental studies are accompanied by theoretical calculation. In addition some special aspects of the photoemission process, namely the photoionization cross section and vibronic coupling, are discussed.

Angle-resolved thermal desorption spectra for CO and H2 from Ni(111), Ni(110) and polycrystalline nickel - Steinrück, Hans-Peter; Winkler, A.; Rendulic, K.D. (Journal of Physics. C. Solid State Physics, 1984)
Flux measurements for desorption angles -60 degrees

Angle-resolved UV-photoelectron spectroscopy - Steinrück, Hans-Peter (Vacuum, 1994)

Angle-resolved UV-photoelectron spectroscopy - Steinrück, Hans-Peter (Pergamon, 1994)

Angle resolved UV-photoelectron spectroscopy of adsorbed molecules - Steinrück, Hans-Peter (Proc. Symposium on Surface Science 3S'91, 1991)

Angle-resolved UV photoelectron spectroscopy of ethylene and benzene on nickel - Steinrück, Hans-Peter (Applied Physics A: Solids and Surfaces, 1994)
A review of results obtained by Angle-Resolved UV-Photoelectron Spectroscopy (ARUPS) using linearly polarized synchrotron radiation is presented for two model systems, ethylene/Ni and benzene/Ni. It is shown that for these systems detailed conclusions concerning adsorbate/substrate and adsorbate/adsorbate interactions can be derived from ARUPS spectra using symmetry selection rules, and in combination with model calculations. In particular, electronic structure, bonding, orientation and symmetry of the adsorbates in dilute and saturated layers will be discussed. It is shown that at high adsorbate coverages lateral interactions in the adsorbate layer play a dominant role. Steric effects in densely packed layers can lead to a reorientation of the molecules as compared to the orientation of the single molecules. The ARUPS spectra of well ordered, densely packed layers exhibit significant (up to 2 eV) dispersion of the various adsorbate bands and allow detailed conclusions on two-dimensional adsorbate band structures. © 1994 Springer-Verlag.

An in situ photoemission study of the dehydrogenation reaction of methanol on Ni(1 0 0) - Neubauer, Ralf; Whelan, Caroline; Denecke, Reinhard; Steinrück, Hans-Peter (Surface Science, 2002)
Making use of the high intensity and resolution of synchrotron radiation at MAX-II (Sweden) we studied the dehydrogenation reaction of methanol on Ni(1 0 0) as a function of temperature by core level photoelectron spectroscopy. The temperature was increased linearly from 105 to 425 K with a heating rate of 0.06 K s. Measurement times of 60 s per C 1s spectrum allowed the dehydrogenation reaction to be monitored in situ. The different binding energies of the core level characteristic of different adsorbed species are reported. After exposure at 105 K, the C 1s spectra exhibit two peaks, representing methanol in multilayer and monolayer states. Above 160 K the multilayer is completely desorbed and methanol from the monolayer starts to dehydrogenate to form a methoxy species which decomposes above 240 K to carbon monoxide adsorbed in the bridge site. The onset of the on-top site occupation is observed at 270 K. The data suggests conversion from bridge to on-top site CO around 290 K. Our results show good agreement with literature values from temperature programmed desorption and Fourier transform infra-red experiments and provide new information in the form of quantitative data on the decomposition pathway of methanol adsorbed on Ni(1 0 0). © 2002 Elsevier Science B.V. All rights reserved.

Anion Exchange at the Liquid/Solid Interface of Ultrathin Ionic Liquid Films on Ag(111) - Lexow, Matthias; Heller, Bettina; Maier, Florian; Steinrück, Hans-Peter (ChemPhysChem, 2018)

An operando DRIFTS-MS study of NH3 removal by supported ionic liquid phase (SILP) materials - Kaftan, Andre; Klefer, Heiko; Haumann, Marco; Laurin, Mathias; Wasserscheid, Peter; Libuda, Jörg (Separation and Purification Technology, 2017)
A novel gas purification material using a supported ionic liquid phase (SILP) has been investigated for removal of NH3 from ambient gas streams (1500 ppm NH3 in Ar). The SILP material is made of a thin film of an imidazolium based ionic liquid and a dissolved copper metal complex ([C(2)C(1)Im]Cl/CuC1(2)), which were dispersed in the pores of a silica 100 support. Diffuse reflection infrared Fourier transform spectroscopy (DRIFTS) was used to investigate the irreversible absorption from a 1500 ppm NH3 gas stream and to identify species formed upon physisorption and chemisorption of ammonia. Additionally, temperature-programmed DRIFTS combined with in situ mass spectrometry were used to evaluate the reversibility and regenerability of the system. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Infrared spectroscopy; Online mass spectrometry; Ammonia absorption; Ionic liquid

An STM study of growth and alloying of Cr on Ru(0 0 0 1) and CO adsorption on the alloy - Engelhardt, Martin Peter; Schmid, M.; Biedermann, A.; Denecke, Reinhard; Steinrück, Hans-Peter; Varga, P. (Surface Science, 2005)
We have investigated the growth of Cr on Ru(0 0 0 1) using scanning tunneling microscopy (STM). In the submonolayer regime (θ = 0.25 ML) monatomically high islands are formed at 300 K, accompanied by step decoration. The island density decreases upon heating to 700 K. Small amounts of Cr are incorporated in the Ru substrate at this temperature. For higher Cr coverages (2 ML), three-dimensional growth is observed at 300 K. Annealing this Cr layer to 500 and 700 K leads to the formation of Cr islands (4-5 layers high) with an elongated shape and bcc(1 1 0) structure with a pseudomorphic Cr monolayer covering the remaining substrate. As shown by atomically resolved images, the Cr bcc(1 1 0) islands have Kurdjumov-Sachs orientation with respect to the Ru(0 0 0 1) substrate. After annealing at 1000 K, the formation of a hexagonal, chemically disordered CrRu alloy is observed, in agreement with a previous study [Engelhardt et al., Surf. Sci. 512 (2002) 107]. The room-temperature STM investigation of CO adsorption on the CrRu alloy with approx. 34% Cr in the first layer shows that adsorbed molecular CO resides only on Ru atoms, not on Cr, mostly in an on-top geometry. The CO occupation of Ru sites increases slightly with the number of neighbouring Cr atoms, indicating a weak ligand effect. We also find indications that the few threefold hollow sites surrounded by three Cr atoms become occupied by atomic C or O, due to dissociation of a small fraction of the adsorbed CO molecules; thus, we cannot unambiguously determine whether molecular CO can bind to these threefold sites at room temperature. © 2005 Elsevier B.V. All rights reserved.

Anthracene-Pentacene Dyads: Synthesis and OFET Characterization - Hauschild, Miriam; Chen, Lan; Etschel, Sebastian; Ferguson, Michael J.; Hampel, Frank; Halik, Marcus; Tykwinski, Rik R. (ChemPlusChem, 2020)
The synthesis of a series of unsymmetrical derivatives of pentacene appended with functionalized anthracene moieties is reported. These anthracene-pentacene dyads have been characterized by UV-vis spectroscopy and cyclic voltammetry to examine their electronic properties. X-ray crystallographic analysis was used to examine the solid-state features of anthracene-pentacene dyads 1 a-d with H-, F-, Cl-, and Br- substituents on the 9-position of anthracene, and shows that the packing arrangement of anthracene-pentacene derivatives 1 b,d,e are remarkably similar irrespective of the presence of fluoride, bromide or methyl substituents. The pentacene-anthracene dyads have been incorporated into OTFTs to evaluate their semiconducting properties. The pentacene derivative 1 b shows ambipolar behavior using AlOx C14 PA as the gate dielectric (electron and hole mobilities of 7.6 ⋅ 10-3 and 1.6 ⋅ 10-1 cm2 V-1 s-1 ), while performance of all derivatives was poor using p-doped Silicon as the substrate. These studies highlight the importance of thin-film formation over molecular structure.
CRIS-Team Scopus Importer:2020-05-22
Keywords: acenes; anthracenes; organic field-effect transistor; organic semiconductor; pentacenes

A review of nitrogen-doped carbon materials for lithium-ion battery anodes - Shaker, Majid; Ghazvini, Ali Asghar Sadeghi; Shahalizade, Taieb; Gaho, Mehran Ali; Mumtaz, Asim; Javanmardi, Shayan; Riahifar, Reza; Meng, Xiao min; Jin, Zhan; Ge, Qi (New Carbon Materials, 2023)
One of the most important research areas related to Li-ion batteries is the replacement of the graphite anode with other carbon materials such as hard carbons, activated carbons, carbon nanotubes, graphene, porous carbons, and carbon fibers. Although such materials have shown better electrochemical performance for lithium storage compared to graphite, there is plenty of room for improvement. One of the most effective approaches is to dope heteroatoms (e. g. nitrogen) in the structure of the carbon materials to improve their electrochemical performance when they are used as anode materials. We first describe how N-doping has a positive effect on lithium storage and then provide numerous selected examples of this approach being applied to various carbon materials. The characterization of N doped in the structure of different carbon materials by X-ray photoelectron spectroscopy and scanning tunneling microscopy is then presented since they are able to characterize the N in these structures with a high (atomic) resolution. Finally, a statistical analysis is performed to show how the amount of doped N affects the specific capacity of the N-doped carbon materials.
CRIS-Team Scopus Importer:2023-04-28
Keywords: Carbon nanotubes; Graphene; Hard carbon; Lithium-ion battery; Nitrogen doping; Porous carbon

A review on the role of graphene quantum dots and carbon quantum dots in secondary-ion battery electrodes - Shaker, Majid; Shahalizade, Taieb; Mumtaz, Asim; Hemmati Saznaghi, Maryam; Javanmardi, Shayan; Gaho, Mehran Ali; Cao, Weiqi; Hu, Wei; Jin, Zhan; Ge, Qi; Ghazvini, Ali Asghar Sadeghi (FlatChem, 2023)
Developing advanced electrode materials is currently crucial for elevating the capacity and energy density of secondary-ion batteries. Among the plenty of candidates, quantum dots (QDs), especially carbon dots (CDs) and graphene quantum dots (GQDs) have shown promising results to achieve this aim. CDs and GQDs are able to solely or in combination with other electrode materials, provide excellent electrochemical properties. Regarding the literature, the addition of these carbonaceous QDs to the electrode materials and fabricating composite electrode materials is able to remarkably enhance the capacity of the probing devices. Therefore, in this review, firstly an introduction to the role of CDs and GQDs in secondary-ion batteries is given. Then, the application of these QDs is reviewed in lithium-, sodium-, potassium-, aluminum-, and zinc-ion batteries as well as lithium-sulfur batteries. Finally, a conclusion is indited and the outlook of this topic is described.
CRIS-Team Scopus Importer:2023-06-09
Keywords: Carbon dots; Electrochemical performance; Graphene quantum dots; Secondary-ion battery

Argon desorption as a tool to study the growth of molecular layers - Stichler, M.; Zebisch, P.; Weinelt, M.; Steinrück, Hans-Peter (Surface Science, 1996)
We demonstrate that temperature programmed desorption (TPD) of argon is a sensitive and non-destructive probe to study the properties of an underlying substrate: the desorption temperatures of the first argon layer from the clean Ni(111) surface, the saturated chemisorbed benzene layer, the first physisorbed benzene layer (on top of chemisorbed benzene) and thicker physisorbed benzene layers on Ni(111) are determined to 39.0, 43.5, 36.5 and 30-32 K, respectively. We have applied argon desorption to investigate the initial growth behavior of physisorbed benzene layers on top of the chemisorbed (√7×√7)R19.1° benzene layer on Ni(111): the argon TPD spectra show that the growth mode of the first physisorbed benzene layers strongly depends on adsorption temperature and on the number of defects in the chemisorbed layer.

A route to continuous ultra-thin cerium oxide films on Cu(111) - Staudt, T.; Lykhach, Yaroslava; Hammer, Lutz; Schneider, M. Alexander; Matolin, Vladimir; Libuda, Jörg (Surface Science, 2009)
The growth and morphology of ultra-thin CeO(2) (1 1 1) films on a Cu(1 1 1) substrate were investigated by means of low energy electron diffraction (LEED) and scanning tunneling microscopy (STM). The films were grown by physical vapor deposition of cerium in an oxygen atmosphere at different sample temperatures. The preparation procedure is based on a modification of a previous method suggested by Matolin and co-workers [1], involving growth at elevated temperature (520 K). Here, LEED shows good long range ordering with a "(1.5 x 1.5)" superstructure, but STM reveals a three-dimensional growth mode (Vollmer-Weber) with formation of a closed film only at larger thickness. Using a kinetically limited growth process by reactive deposition at low sample temperatures (100 K) and subsequent annealing, we show that closed layers of ceria with atomically flat terraces can be prepared even in the regime of ultra-thin films (1.5 ML). Closed and atomically flat ceria films of larger thickness (3 ML) are obtained by applying a multistep preparation procedure, in which successive ceria layers are homoepitaxially grown on this initial film. The resulting overlayers show strong similarities with the morphology of CeO(2)(1 1 1) single crystal surfaces, suggesting the possibility to model bulk ceria by thin film systems. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Ceria; Ultra-thin oxide films; Scanning tunneling microscopy; Low energy electron diffraction; Model catalysts

A simple design for a helium scattering apparatus - Maier, Florian; Kneitz, Stefan; Koschel, Herbert; Steinrück, Hans-Peter (Surface Science, 1997)
We have designed a simple helium scattering apparatus for gas-surface scattering experiments. The effusive source is a glass multicapillary array, operated at large Knudsen numbers which produces a highly collimated thermal He beam (FWHM≈3°) with a Maxwellian velocity distribution. The detector is a Bayard Alpert ionization gauge, mounted in a tube that is separated from the main UHV chamber via a second multicapillary array. This setup allows one to select only those He atoms that are reflected by the sample in the specular direction and thus to measure the reflectivity of the surface. Examples of its performance are presented for the adsorption of CO on Ru(001), and for thermal annealing of a Ru(001) surface sputtered with argon ions at different energies.

A simple high-intensity UV-photon source for photochemical studies in UHV: Application to the photoconversion of norbornadiene to quadricyclane - Schwarz, Matthias; Schuschke, Christian; Nascimento Silva, Thais; Mohr, Susanne; Waidhas, Fabian; Brummel, Olaf; Libuda, Jörg (Review of Scientific Instruments, 2019)
Photochemical in situ studies in a well-controlled surface science environment can help to understand photochemical reactions in organic thin films in more detail. To perform such studies without external focusing or light guiding systems, we designed a high-intensity UV-photon source, which is compatible with an ultra-high vacuum (UHV) environment. The UV source is based on a high power light-emitting diode (LED), soldered onto a copper heat reservoir to avoid overheating. The LED can be placed in close vicinity in front of a single crystal, providing flux densities of 2 x 10(18) photons s(-1) cm(-2) at a wavelength of 365 nm. Thus, the device provides light intensities one order of magnitude higher as compared to conventional continuous wave arc lamps, at only a small variation of the flux of less than +/- 20% over a sample surface of 10 x 8 mm(2). The UV source is mounted in a UHV infrared reflection absorption spectroscopy system and triggered by using the IR spectrometer. This allows fully automatized in situ IR studies of photochemical reactions at interfaces and thin films. We prove the functionality of the device by studying the photochemical conversion of norbornadiene (NBD) to quadricyclane (QC) mediated by the photosensitizer 4,4'-bis(dimethylamino) benzophenone (Michler's ketone, MK). NBD and MK were grown by physical vapor deposition in the form of thin films on Pt(111) at 120 K. Even at prolonged UV irradiation (>100 s), the temperature of the sample increased by less than 10 K. We report first successful conversion of NBD to QC under UHV conditions and follow the conversion behavior as a function of the photon dose and NBD/MK ratio. Initial quantum yields of up to 23% and selectivity for a QC of 70% are obtained at NBD/MK of 7.4:1, indicating good electronic coupling between NBD and MK even in a frozen multilayer. For both very small and very large NBD loadings, the conversion efficiency decreases, which is attributed to the effect of the metallic substrate and phase separation in thick multilayers, respectively. Published under license by AIP Publishing.
CRIS-Team WoS Importer:2019-03-20

A site-selective in situ study of CO adsorption and desorption on Pt(355) - Tränkenschuh, Barbara; Fritsche Richter, Nicole; Fuhrmann, Thomas; Papp, Christian; Zhu, Junfa; Denecke, Reinhard; Steinrück, Hans-Peter (Journal of Chemical Physics, 2006)
Using time-dependent high-resolution x-ray photoelectron spectroscopy at BESSY II, the adsorption and desorption processes of CO on stepped Pt (355) =Pt [5 (111) × (111)] were investigated. From a quantitative analysis of C 1s data, the distribution of CO on the various adsorption sites can be determined continuously during adsorption and desorption. These unique data show that the terrace sites are only occupied when the step sites are almost saturated, even at temperatures as low as 130 K. The coverage-dependent occupation of on-top and bridge adsorption sites on the (111) terraces of Pt(355) is found to differ from that on Pt(111), which is attributed to the finite width of the terraces and changes in adsorbate-adsorbate interactions. In particular, no long-range order of the adsorbate layer could be observed by low-energy electron diffraction. Further details are derived from sticking coefficient measurements using the method devised by King and Wells [Proc. R. Soc. London, Ser. A 339, 245 (1974)] and temperature-programmed desorption. The CO saturation coverage is found to be slightly smaller on the stepped surface as compared to that on Pt(111). The initial sticking coefficient has the same high value of 0.91 for both surfaces. © 2006 American Institute of Physics.

Assignment of near-edge x-ray absorption fine structure spectra of metalloporphyrins by means of time-dependent density-functional calculations - Schmidt, Norman Anja; Fink, Rainer; Hieringer, Wolfgang (Journal of Chemical Physics, 2010)
The C 1s and N 1s near-edge x-ray absorption fine structure (NEXAFS) spectra of three prototype tetraphenyl porphyrin (TPP) molecules are discussed in the framework of a combined experimental and theoretical study. We employ time-dependent density-functional theory (TDDFT) to compute the NEXAFS spectra of the open- and closed-shell metalloporphyrins CoTPP and ZnTPP as well as the free-base 2HTPP in realistic nonplanar conformations. Using Becke's well-known half-and-half hybrid functional, the computed core excitation spectra are mostly in good agreement with the experimental data in the low-energy region below the appropriate ionization threshold. To make these calculations feasible, we apply a new, simple scheme based on TDDFT using a modified single-particle input spectrum. This scheme is very easy to implement in standard codes and allows one to compute core excitation spectra at a similar cost as ordinary UV/vis spectra even for larger molecules. We employ these calculations for a detailed assignment of the NEXAFS spectra including subtle shifts in certain peaks of the N 1s spectra, which depend on the central coordination of the TPP ligand. We furthermore assign the observed NEXAFS resonances to the individual molecular subunits of the investigated TPP molecules. © 2010 American Institute of Physics.

Asymmetry Matters: Structure Elucidation and Application Potential of Solution-Processed Monoalkylated BTBT Thin Films - Hawly, Tim; Johnson, Manuel; Zhao, Baolin; Wu, Mingjian; Späth, Andreas; Streller, Fabian; Nickles Jäkel, Hannah; Halik, Marcus; Spiecker, Erdmann; Watts, Benjamin; Nefedov, Alexei; Fink, Rainer (ACS Applied Electronic Materials, 2022)
Two-dimensionally (2D) extended thin films of p-type organic semiconductor C13-BTBT (BTBT = [1]benzothieno[3,2-b]-[1]benzothiophene) were fabricated via self-controlled growth at the liquid-liquid interface. Depicting a compound class originally developed for further functionalization and subsequent realization of self-assembled monolayers (SAMs), the potent BTBT core unit commonly excels in high-quality structure formation as well as charge-transport characteristics. Utilizing a manifold spectromicroscopic toolbox, we observe extraordinarily crystalline C13-BTBT films with an upright standing configuration of the backbone unit accounting for superior intermolecular orbital overlap. The well-defined morphology and internal structure of the film are being underpinned by charge-transport parameters that are in the range of comparable organic electronic devices based on bisubstituted BTBT films from the same processing technique. The inherently favorable membrane-like bilayer molecular arrangement is confirmed by unambiguous representation of the unit cell as derived from electron tomography.
CRIS-Team WoS Importer:2023-01-27

Asymptotic analysis of the current-voltage curve of a pnpn semiconductor device - Steinrück, Hans-Peter (IMA Journal of Applied Mathematics, 1989)
We consider the one-dimensional steady-state semiconductor device equations modelling a pnpn device. There are two relevant scalings of the equations corresponding to small and large applied voltages. In both scalings, the semiconductor equations can be considered as singularly perturbed. It turns out that the small-voltage scaling breaks down for current values between two saturation currents. In that interval, the large-voltage scaling has to be employed. For both scalings, we derive the first-order terms of an asymptotic expansion and show that the reduced problem has a solution. An example verifies that the current-voltage curves obtained have the expected qualitative structure. © 1989 Oxford University Press.

A temperature-programmed x-ray photoelectron spectroscopy study of the decomposition reactions of unsaturated hydrocarbons on Ni(100) - Whelan, Caroline; Neubauer, Ralf; Denecke, Reinhard; Steinrück, Hans-Peter (Surface Review and Letters, 2002)
We present a temperature-programmed x-ray photoelectron spectroscopy study of the thermal chemistry of acetylene, ethylene and propene on Ni(100) using synchrotron radiation. The use of a third generation light source makes it possible to measure high resolution photoemission spectra within a few seconds approaching the ideal of real-time analysis. The evolution of the C 1s core level spectra has been monitored in situ as a function of sample temperature from 90 to 530 K. Analysis of binding energies and changes in intensities and correlation with previous data from the literature have allowed us to distinguish the surface intermediates formed during the thermal reactions. The resultant temperature-dependent intensity curves clarify the dehydrogenation mechanisms of acetylene and ethylene and provide new insight into the decomposition of propene.

A test of capillary array beam sources for very large Knudsen numbers - Steinrück, Hans-Peter; Rendulic, K.D. (Vacuum, 1986)
An experimental test of the angular distribution function of particles originating from long capillaries has been performed. Gas pressures at the tube entrance corresponding to Knudsen numbers of 10-10 were used. The results can be described very well by the elementary Clausing theory. The cosine law for gas reflection inside the tubes is fulfilled with high accuracy. No differences in the behaviour of CO, CO, N and O could be detected. The investigation is also considered to be an accurate test of the simple beam detector used in the investigation. © 1986.

Atmospheric adsorption on pristine and nitrogen-doped graphene: doping-dependent, spatially selective - Kolesov, Egor A.; Tivanov, Mikhail S.; Korolik, Olga; Kataev, Elmar; Xiao, Fu; Kapitanova, Olesya O.; Cho, Hak Dong; Kang, Tae Won; Panin, Gennady N. (Journal of Physics D: Applied Physics, 2020)
Using Raman and photoemission spectroscopy, we probe the atmospheric adsorption on pristine and nitrogen p-doped graphene supported by SiO2/Si. Laser annealing in vacuum led to a pronounced change in Raman spectra parameters, corresponding to a decrease in hole density due to adsorbate removal from the sample surface. We found that the shift inversely correlates with a degree of initial nitrogen doping, and thus less p-type adsorption doping takes place on graphene with a higher density of charge carriers with the same sign. The amount of hole doping required for the absence of atmospheric adsorption doping was found to be p(noad) = (3.87 +/- 0.31) x 10(13) cm(-2) (similar to 2.3% of pyridine-like nitrogen), while the electronic doping required to fully compensate adsorption hole doping was n(equil) = (0.46 +/- 0.12) x 10(13) cm(-2) (similar to 0.2% of graphitic nitrogen). We showed that atmospheric adsorption on pristine graphene increases the spatial charge carrier inhomogeneity; in contrast, the adsorption on nitrogen-doped graphene shows a spatially selective nature and reduces the inhomogeneity of charge carriers. This study is useful for graphene applications which require specific adsorption properties, as well as for taking these properties into account when designing graphene-based nanoelectronic devices.
CRIS-Team WoS Importer:2019-12-13

Atomically Defined Co 3 O 4 (111) Thin Films Prepared in Ultrahigh Vacuum: Stability under Electrochemical Conditions - Faisal, Firas; Bertram, Manon; Stumm, Corinna; Cherevko, Serhiy; Geiger, Simon; Kasian, Olga; Lykhach, Yaroslava; Lytken, Ole; Mayrhofer, Karl J. J.; Brummel, Olaf; Libuda, Jörg (Journal of Physical Chemistry C, 2018)
We have explored the stability, the structure, and the chemical transformations of atomically defined Co3O4(111) thin films under electrochemical conditions. The well-ordered Co3O4(111) films were prepared on an Ir(100) single crystal under ultrahigh vacuum (UHV) conditions and subsequently transferred and characterized in the electrochemical environment by means of cyclic voltammetry (CV), scanning flow cell inductively coupled plasma mass spectrometry (SCF-ICP-MS), and electrochemical infrared reflection absorption spectroscopy (EC-IRRAS). We have found that the Co3O4(111) films are stable in phosphate buffer at pH 10 at potentials between 0.33 to 1.33 VRHE. In the corresponding potential range, the corrosion rates established by means of SCF-ICP-MS were well below 0.1 monolayer per hour. Additionally, low-energy electron diffraction (LEED) and X-ray photoelectron spectroscopy (XPS) studies have shown that the long-range order, the thickness, and the composition of the films were preserved under electrochemical conditions. Disintegration of the film and formation of holes after repeated potential cycling within the stability window were ruled out by EC-IRRAS using CO as a probe molecule. In general, the stability of the Co3O4(111) films depends critically on both the pH and electrode potential. Increasing the pH from 10 to 12 compromised the structural stability of the Co3O4(111) films due to faster redox processes at the surface. In particular, we observed accelerated oxidation of cobalt followed by the formation of oxyhydroxide during the anodic scan and accelerated reduction to cobalt hydroxides during the cathodic scan. Decreasing the pH from pH 10 to pH 8, on the other hand, led to faster dissolution, in particular at potentials below 0.2 VRHE, where the dissolution rate increased rapidly due to formation of soluble Co(II) species. Our studies demonstrate that thin well-ordered oxide films prepared in UHV can be transferred into the electrochemical environment while preserving their atomic surface structure if the conditions are chosen carefully. This opens a surface science approach to atomically defined oxide–electrolyte interfaces.
EAM Import::2019-03-13

Atomically Defined Co3O4(111) Thin Films Prepared in Ultrahigh Vacuum: Stability under Electrochemical Conditions - Faisal, Firas; Bertram, Manon; Stumm, Corinna; Cherevko, Serhiy; Geiger, Simon; Kasian, Olga; Lykhach, Yaroslava; Lytken, Ole; Mayrhofer, Karl J. J.; Brummel, Olaf; Libuda, Jörg (Journal of Physical Chemistry C, 2018)
We have explored the stability, the structure, and the chemical transformations of atomically defined Co3O4(111) thin films under electrochemical conditions. The well-ordered Co3O4(111) films were prepared on an Ir(100) single crystal under ultrahigh vacuum (UHV) conditions and subsequently transferred and characterized in the electrochemical environment by means of cyclic voltammetry (CV), scanning flow cell inductively coupled plasma mass spectrometry (SCF-ICP-MS), and electrochemical infrared reflection absorption spectroscopy (EC-IRRAS). We have found that the Co3O4(111) films are stable in phosphate buffer at pH 10 at potentials between 0.33 to 1.33 V-RHE. In the corresponding potential range, the corrosion rates established by means of SCF-ICP-MS were well below 0.1 monolayer per hour. Additionally, low-energy electron diffraction (LEED) and X-ray photoelectron spectroscopy (XPS) studies have shown that the long-range order, the thickness, and the composition of the films were preserved under electrochemical conditions. Disintegration of the film and formation of holes after repeated potential cycling within the stability window were ruled out by EC-IRRAS using CO as a probe molecule. In general, the stability of the Co3O4(111) films depends critically on both the pH and electrode potential. Increasing the pH from 10 to 12 compromised the structural stability of the Co3O4(111) films due to faster redox processes at the surface. In particular, we observed accelerated oxidation of cobalt followed by the formation of oxyhydroxide during the anodic scan and accelerated reduction to cobalt hydroxides during the cathodic scan. Decreasing the pH from pH 10 to pH 8, on the other hand, led to faster dissolution, in particular at potentials below 0.2 V-RHE, where the dissolution rate increased rapidly due to formation of soluble Co(II) species. Our studies demonstrate that thin well-ordered oxide films prepared in UHV can be transferred into the electrochemical environment while preserving their atomic surface structure if the conditions are chosen carefully. This opens a surface science approach to atomically defined oxide-electrolyte interfaces.

Atomically-defined model catalysts in ultrahigh vacuum and in liquid electrolytes: particle size-dependent CO adsorption on Pt nanoparticles on ordered Co3O4(111) films - Faisal, Firas; Stumm, Corinna; Bertram, Manon; Wähler, Tobias; Schuster, Ralf; Xiang, Feifei; Lytken, Ole; Katsounaros, Ioannis; Mayrhofer, Karl; Schneider, M. Alexander; Brummel, Olaf; Libuda, Jörg (Physical Chemistry Chemical Physics, 2018)
We have studied particle size effects on atomically-defined model catalysts both in ultrahigh vacuum (UHV) and under electrochemical (EC) conditions in liquid electrolytes. The model catalysts were prepared in UHV by physical vapour deposition (PVD) of Pt onto an ordered Co3O4(111) film on Ir(100), yielding nanoparticles (NPs) with an average size from 10 to 500 atoms per particle (0.8 to 3 nm). The model systems were characterized in UHV using surface science methods including scanning tunnelling microscopy (STM), before transferring them out of the UHV and into the electrolyte without contact to ambient conditions. By X-ray photoelectron spectroscopy (XPS) we show that the model surfaces are stable in the EC environment under the applied conditions (0.1 to 1 M phosphate buffer, pH 10, 0.33 to 1.03 V-RHE). As a reference, we study Pt(111) under identical conditions. In UHV, we also investigated the adsorption of CO using infrared reflection absorption spectroscopy (IRRAS). Under EC conditions, we performed equivalent experiments using EC infrared reflection absorption spectroscopy (EC-IRRAS) in combination with cyclic voltammetry (CV). Characteristic differences were observed between the IR spectra under EC conditions and in UHV. Besides the red-shift induced by the interfacial electric field (Stark effect), the EC IR bands of CO on Pt(111) show a larger width (by a factor of 2) as a result of local variations in the CO environment and coupling to the electrolyte. The CO IR bands of the Pt NPs are even broader (by a factor of 5), which is attributed to local variations of the interfacial electric field at the NP surface. Further pronounced differences are observed between the spectra taken in UHV and in the electrolyte regarding the site occupation and its dependence on particle size. In UHV, adsorption at on-top sites is preferred on Pt(111) at low coverage and similar adsorption ratios of on-top and bridge-bonded CO are formed at saturation coverage. In sharp contrast, on-top adsorption of CO on Pt(111) is partially suppressed under EC conditions. This effect is attributed to the competitive adsorption of anions from the electrolyte and leads to a clear preference for bridge sites at higher potentials (>0.5 V-RHE). For the Pt NPs, the situation is different and an increasing fraction of on-top CO is observed with decreasing particle size, both under EC conditions and in UHV. For the smallest particles (10-20 atoms) we do not detect any bridge-bonded CO. This change in site preference as a function of particle size is attributed to stronger on-top adsorption on low-coordinated Pt atoms of small Pt NPs. The effect leads to a clear preference for on-top adsorption in the electrolyte even at low CO coverage and over the full potential range studied.

Atomically-defined model systems for oxide-based electrodes: From surface science to the electrified interface - Libuda, Jörg (ABSTRACTS OF PAPERS OF THE AMERICAN CHEMICAL SOCIETY, 2019)
CRIS-Team WoS Importer:2019-08-23

Atomically Dispersed Pd, Ni, and Pt Species in Ceria-Based Catalysts: Principal Differences in Stability and Reactivity - Neitzel, Armin; Figueroba, Alberto; Lykhach, Yaroslava; Skala, Tomas; Vorokhta, Mykhailo; Tsud, Nataliya; Mehl, Sascha; Sevcikova, Klara; Prince, Kevin C.; Neyman, Konstantin M.; Matolin, Vladimir; Libuda, Jörg (Journal of Physical Chemistry C, 2016)
We have investigated the stability and the reactivity of atomically dispersed Pt, Pd, and Ni species on nanostructured CeO2 films by means of synchrotron radiation photoelectron spectroscopy and resonant photoemission spectroscopy in combination with density functional calculations. All three metals reveal specific similarities associated with the high adsorption energy of atomically dispersed Pt2+, Pd2+, and Ni2+ species that exceeds the corresponding cohesive energies of the bulk metals. The corresponding Pt-CeO2, Pd-CeO2, and Ni-CeO2 model catalysts have been prepared in the form of thin films on CeO2(111)/Cu(111) substrates and investigated experimentally under ultrahigh vacuum conditions. The atomically dispersed Pt2+, Pd2+, and Ni-2 species were formed exclusively at low concentrations of the corresponding metals. High concentrations resulted in the presence of additional metal oxide phases and emergence of metallic particles. We found that under the employed experimental conditions the Pd-CeO2 films closely resemble the Pt-CeO2 system with respect to the redox behavior upon reaction with hydrogen. Unlike Pt-CeO2, the Pd-CeO2 system shows a strong tendency to stabilize Pd2+ not only at the surface but also in the ceria bulk. In sharp contrast to both Pt-CeO2 and Pd-CeO2, the Ni-CeO2 system does not exhibit the redox functionality required for hydrogen activation due to the remarkably high stability of Ni2+ species.

Atomic Force and Scanning Tunneling Microscopy of Ordered Ionic Liquid Wetting Layers from 110 K up to Room Temperature - Meusel, Manuel; Lexow, Matthias; Gezmis, Afra; Schötz, Simon; Wagner, Margareta; Bayer, Andreas; Maier, Florian; Steinrück, Hans-Peter (ACS nano, 2020)
Ionic liquids (ILs) are used as ultrathin films in many applications. We studied the nanoscale arrangement within the first layer of 1,3-dimethylimidazolium bis[(trifluoromethyl)sulfonyl]imide ([C1C1Im] [Tf2N]) on Au(111) between 400 and 110 K in ultrahigh vacuum by scanning tunneling and noncontact atomic force microscopy with molecular resolution. Compared to earlier studies on similar ILs, a different behavior is observed, which we attribute to the small size and symmetrical shape of the cation: (a) In both AFM and STM only the anions are imaged; (b) only long-range-ordered but no amorphous phases are observed; (c) the hexagonal room-temperature phase melts 30-50 K above the IL's bulk melting point; (d) at 110 K, striped and hexagonal superstructures with two and three ion pairs per unit cell, respectively, are found. AFM turned out to be more stable at higher temperature, while STM revealed more details at low temperature.
CRIS-Team Scopus Importer:2020-08-28
Keywords: atomic force microscopy (AFM); Au(111); interface; ionic liquids (ILs); scanning tunneling microscopy (STM)

Atomic Ordering and Sn Segregation in Pt-Sn Nanoalloys Supported on CeO2 Thin Films - Neitzel, Armin; Kovacs, Gabor; Lykhach, Yaroslava; Kozlov, Sergey M.; Tsud, Nataliya; Skala, Toma; Vorokhta, Mykhailo; Matolin, Vladimir; Neyman, Konstantin M.; Libuda, Jörg (Topics in Catalysis, 2017)
The stability and atomic ordering in Pt-Sn nanoalloys supported on CeO2 thin films have been studied by means of synchrotron radiation photoelectron spectroscopy and density functional calculations. Using CO molecules as a probe, we explored the development of the surface structure of supported Pt-Sn nanoalloys with respect to a reference Pt/CeO2 model system. We found a significant decrease in the density of CO adsorption sites on supported Pt-Sn nanoalloys caused by Sn segregation to the surface upon annealing. Additionally, we found that atomic ordering in Pt-Sn nanoalloys is driven by the balance between the surface segregation energy of Sn atoms and the energy of heteroatomic bond formation. Our calculations demonstrate a clear tendency for Sn segregation to the nanoalloy surface. For Pt105Sn35 and Pt1097Sn386 nanoparticles, we calculated a surface stoichiometry of Pt2Sn which is only slightly dependent on temperature in thermodynamic equilibrium. The analysis of Bader charges in Pt-Sn nanoalloys revealed a strong correlation between the charge and the coordination number of Sn atoms with respect to Pt neighbors. In particular, the magnitude of the charge transfer from Sn to Pt increases as a function of the Sn coordination number.
Keywords: Pt-Sn nanoalloy; CO tolerant catalyst; Model catalyst; Synchrotron radiation photoelectron spectroscopy; Density functional theory

Atomphysik am Computer - Girwidz, Raimund; Gößwein, Oliver; Steinrück, Hans-Peter (Physik in unserer Zeit, 2000)
Die moderne Atomphysik hat von der Bohrschen Theorie bis zu Schrödingers Wellentheorie einen Wandel sowohl in der mathematischen Behandlung als auch in der bildlichen Vorstellung durchgemacht. Am PC lassen sich heute viele abstrakte Rechenergebnisse dieser Theorien veranschaulichen. Dieses Ziel verfolgt das Programmpaket „atomos”︁, das auf unserer Homepage unter www.wiley‐vch.de/home/phiuz abrufbar is
UnivIS-Import:2018-09-04:Pub.2000.nat.dchph.lpc2.atomph

Atomphysik am Computer - Girwidz, Raimund; Steinrück, Hans-Peter; Gößwein, Oliver (Wiley-VCH, 2000)

At the ionic liquidmetal interface: Structure formation and temperature dependent behavior of an ionic liquid adlayer on Au(111) - Uhl, Benedikt; Cremer, Till; Roos, Michael; Maier, Florian; Steinrück, Hans-Peter; Behm, R.Jürgen (Physical Chemistry Chemical Physics, 2013)
The growth, structure formation and thermal disordering of (sub-)monolayer films of 1-butyl-1-methylpyrrolidinium-bis(trifluoromethylsulfonyl)imide [BMP][TFSA] grown under ultrahigh vacuum (UHV) conditions on Au(111) have been investigated using scanning tunneling microscopy (STM) and angle resolved X-ray photoelectron spectroscopy (ARXPS) under UHV conditions at temperatures between 100 and 298 K. At room temperature, two-dimensional film growth occurs up to one monolayer coverage, with both cations and anions in direct contact with the gold substrate, as shown by ARXPS, and STM images reveal a 2D liquid state of the adlayer. At lower temperatures, motion is frozen and a disordered 2D glass state as well as a 2D crystalline phase with long-range order are formed. The structure of the 2D crystalline phase is influenced by the underlying Au(111) reconstruction pattern. Annealing experiments reveal that the 2D crystalline phase is thermally more stable against melting than the 2D glass state, and that the stability is strongly affected by the adsorbate coverage. © 2013 the Owner Societies.

Au-Catalyzed Energy Release in a Molecular Solar Thermal (MOST) System: A Combined Liquid-Phase and Surface Science Study - Eschenbacher, Roman; Hemauer, Felix; Franz, Evanie; Leng, Andreas; Schwaab, Valentin; Waleska-Wellnhofer, Natalie; Freiberger, Eva Marie; Fromm, Lukas; Xu, Tao; Görling, Andreas; Hirsch, Andreas; Steinrück, Hans-Peter; et al. (Chemphotochem, 2023)
Molecular solar thermal systems (MOSTs) are molecular systems based on couples of photoisomers (photoswitches), which combine solar energy conversion, storage, and release. In this work, we address the catalytically triggered energy release in the promising MOST couple phenylethylesternorbornadiene/quadricyclane (PENBD/PEQC) on a Au(111) surface in a combined liquid-phase and surface science study. We investigated the system by photoelectrochemical infrared reflection absorption spectroscopy (PEC-IRRAS) in the liquid phase, conventional IRRAS and synchrotron radiation photoelectron spectroscopy (SRPES) in ultra-high vacuum (UHV). Au(111) is highly active towards catalytically triggered energy release. In the liquid phase, we did not observe any decomposition of the photoswitch, no deactivation of the catalyst within 100 conversion cycles and we could tune the energy release rate of the heterogeneously catalyzed process by applying an external potential. In UHV, submonolayers of PEQC on Au(111) are back-converted to PENBD instantaneously, even at 110 K. Multilayers of PEQC are stable up to 220 K. Above this temperature, the intrinsic mobility of the film is high enough that PEQC molecules come into direct contact with the Au(111) surface, which catalyzes the back-conversion. We suggest that this process occurs via a singlet–triplet mechanism induced by electronic coupling between the PEQC molecules and the Au(111) surface.
CRIS-Team Scopus Importer:2023-12-01
Keywords: norbornadiene; photoswitches; quadricyclane; solar energy storage; surface chemistry

Auf dem Weg zu größtmöglicher Effizienz bei der katalytischen Nutzung von Edelmetallen: Atomar dispergiertes Oberflächen-Platin - Bruix, Albert; Lykhach, Yaroslava; Matolinova, Iva; Neitzel, Armin; Skala, Tomas; Tsud, Nataliya; Vorokhta, Mykhailo; Stetsovych, Vitalii; Sevcikova, Klara; Myslivecek, Josef; Fiala, Roman; Vaclavu, Michal; et al. (Angewandte Chemie, 2014)
Platin ist das am vielseitigsten eingesetzte Element in der Katalyse. Allerdings begrenzt der hohe Preis des Edelmetalls die Verwendung in vielen Bereichen, z. B. in Katalysatormaterialien für Brennstoffzellen. Trotzdem nutzen konventionelle Katalysatoren oftmals nur einen Bruchteil ihres Pt-Gehaltes, nämlich diejenigen Atome, die sich auf der Oberfläche des Katalysators befinden. Eine effizientere Edelmetallnutzung setzt somit eine höhere, bevorzugt atomare Dispersion der Pt-Atome auf der Oberfläche voraus. Tatsächlich ist es möglich, solche atomar dispergierten Pt-Spezies mit sehr hoher Stabilität auf einer Katalysatoroberfläche herzustellen. Mithilfe von DFT-Rechnungen identifizieren wir ein spezifisches Strukturmerkmal solcher Systeme, eine sogenannte Cerdioxid-“Nanotasche”, die Pt2+-Ionen so stabilisiert, dass diese sowohl thermischem Sintern als auch einer Diffusion in tiefere Katalysatorebenen widerstehen. Die theoretisch vorhergesagte außerordentliche Stabilität wurde experimentell an Modellkatalysatoren verifiziert. In realen Pt-CeO2-Nanomaterialien, die tatsächlich eine sehr hohe katalytische Aktivität in Brennstoffzellen zeigen, identifizieren wir diese Bindungsstellen ebenfalls. Die so erhaltenen neuen Materialien können dazu beitragen, den Bedarf an Edelmetallen für Katalysatormaterialien erheblich zu reduzieren.

Author Correction: Isolated Rh atoms in dehydrogenation catalysis (Scientific Reports, (2023), 13, 1, (4458), 10.1038/s41598-023-31157-y) - Wittkämper, Haiko; Hock, Rainer; Weißer, Matthias; Dallmann, Johannes; Vogel, Carola; Raman, Narayanan; Taccardi, Nicola; Haumann, Marco; Wasserscheid, Peter; Hsieh, Tzung En; Maisel, Sven; Moritz, Michael; et al. (Scientific Reports, 2023)
Correction to: Scientific Reports, published online 17 March 2023 The original version of this Article contained an error in the spelling of the author Nicola Taccardi, which was incorrectly given as Nicola Tacardi. The original Article has been corrected.
CRIS-Team Scopus Importer:2023-06-30

Azimuthal reorientation of adsorbed molecules induced by lateral interactions: benzene/Ni(110) - Huber, W.; Weinelt, M.; Zebisch, P.; Steinrück, Hans-Peter (Surface Science, 1991)
The adsorption of benzene on the Ni(110) surface was studied by TPD, LEED, NEXAFS and ARUPS. At initial coverages below θ = 0.10 ML (relative to Ni) benzene completely decomposes upon heating. At higher coverages molecular benzene desorption is also observed. At the saturation coverage of 0.23 ± 0.04 ML a sharp c(4 × 2) LEED pattern is observed with weak additional reflexes indicating a larger unit mesh. The ARUPS measurements for a dilute layer (θ ≃ 0.5θ ) suggest an orientation of the molecular plane parallel to the surface with C symmetry of the adsorption complex benzene/Ni(110) and the molecules azimuthally oriented with their corners along [001]. For the saturated layer the molecular plane is still parallel to the surface but the symmetry of the adsorption complex is lowered to C , due to an azimuthal rotation of the benzene molecules induced by strong lateral interactions in the densely packed saturated layer. The 2alg band shows strong dispersion (0.8 eV) with the periodicity of the 2D bandstructure corresponding to a c(4 × 2) structure. For the coadsorption of benzene + CO a sharp c(4 × 4) LEED structure is observed with identical CO and benzene coverages of 0.12 ML. The electronic structure, orientation and symmetry of benzene in the coadsorbed layer is identical to that in the dilute pure layer. The photon energy dependence of the photoionization cross section of the 2elu level of benzene in the saturated layer shows a maximum at a photon energy of 25 eV, similar to benzene on Ni(111); the corresponding electron emission is centered along the surface normal. The NEXAFS spectra for the dilute and the saturated layer at normal incidence are also indicative of a flat-lying benzene molecule. © 1991.

Back Cover: Energy Storage in Strained Organic Molecules: (Spectro)Electrochemical Characterization of Norbornadiene and Quadricyclane (ChemSusChem 12/2016) - Brummel, Olaf; Besold, Daniel; Döpper, Tibor; Wu, Yanlin; Bochmann, Sebastian; Lazzari, Federica; Waidhas, Fabian; Bauer, Udo; Bachmann, Philipp; Papp, Christian; Steinrück, Hans-Peter; Görling, Andreas; et al. (ChemSusChem, 2016)
Keywords: infrared spectroscopy; norbornadiene; quadricyclane; spectroelectrochemistry; voltammetry

Band discontinuities and local interface composition in BeTe/ZnSe heterostructures - Nagelstraßer, M.; Dröge, H.; Fischer, F.; Litz, T.; Waag, Andreas; Landwehr, G.; Steinrück, Hans-Peter (Journal of Applied Physics, 1998)
Using photoelectron spectroscopy, we have investigated the band alignment at the interface of pseudomorphic BeTe/ZnSe(100) heterojunctions for different interface terminations. The heterostructures of high structural quality have been produced by molecular beam epitaxy; the interface termination was adjusted by variation of the growth parameters between the growth process of ZnSe and BeTe. The valence band offset for a Zn-rich BeTe/ZnSe interface is determined to be 1.26±0.15 eV, for the Se-rich BeTe/ZnSe interface a value of 0.46±0.15 eV is obtained. Our results show that the band alignment can be modified by the interface composition even for isovalent heterostructures. © 1998 American Institute of Physics.

Band gap effect on the photocatalytic activity of supramolecular structures obtained by entrapping photosensitizers in different inorganic supports - Cojocaru, Bogdan; Neatu, Stefan; Parvulescu, Vasile I.; Dumbuya, Karifala; Steinrück, Hans-Peter; Gottfried, Michael; Aprile, Carmela; Garcia, Hermenegildo; Scaiano, J. C. (Physical Chemistry Chemical Physics, 2009)
Different metallophthalocyanines and 2,4,6-triphenylpyrylium (TP ) ions were entrapped in different inorganic supports such as Y zeolite, mesoporous MCM-41, TiO-SiO and SiO following a specific protocol. The resulting supramolecular structures were characterized by chemical analysis and diffuse reflectance UV-Vis measurements. The determination of the band gap on the basis of UV-Vis measurements showed that the host is not a spectator in this process and an electronic interaction occurs that lowers the band gap of the support. The XPS measurements were performed with an in situ X-ray photoelectron spectrometer, which can be operated at pressures of up to 1 mbar at the sample. They indicated that the formation of the supramolecular structure generates a stable environment, in which the oxidation state of the metal can still be influenced by reaction of the metal center with gas molecules. The photocatalytic tests carried out in photodecomposition of dipropyl sulfide showed a good correlation between the band gap values and the photocatalytic activity for metallophthalocyanine complexes. It is remarkable that the triphenylpyrylium ion follows the same trend observed for metallophthalocyanines, although it is a different type of photosensitizer. © the Owner Societies 2009.

Band structure of BeTe: A combined experimental and theoretical study - Nagelstraßer, M.; Dröge, H.; Steinrück, Hans-Peter; Fischer, F.; Litz, T.; Waag, Andreas; Landwehr, G.; Fleszar, A.; Hanke, W. (Physical Review B, 1998)
Using angle-resolved synchrotron-radiation photoemission spectroscopy we have determined the dispersion of the valence bands of BeTe(100) along ΓX, i.e., the [100] direction. The measurements are analyzed with the aid of a first-principles calculation of the BeTe bulk band structure as well as of the photoemission peaks as given by the momentum-conserving bulk transitions. Taking the calculated unoccupied bands as final states of the photoemission process, we obtain an excellent agreement between experimental and calculated spectra and a clear interpretation of almost all measured bands. In contrast, the free-electron approximation for the final states fails to describe the BeTe bulk band structure along ΓX properly.

Be-chalcogenides: Heteroepitaxy and interface properties - Litz, T.; Fischer, F.; Lugauer, H.-J.; Keim, M.; Zehnder, U.; Ossau, W.; Gerhard, Th.; Gall, R.; Waag, Andreas; Landwehr, G.; Nagelstraßer, M.; Steinrück, Hans-Peter; et al. (Applied Surface Science, 1998)
We report on the molecular beam epitaxy and the properties of Be-chalcogenides. Especially the interface between ZnSe and BeTe and BeTe/ZnSe superlattices have been studied by means of HRXRD (high resolution X-ray diffraction), HRTEM (high resolution transmission-electron-microscopy), RHEED (reflection-high-energy-electron-diffraction), photo-electron-spectroscopy (PES) and photo-luminescence (PL). A strong dependence of the structural and electronic properties of these superlattices (SL) on the interface configuration has been found. A high valence band offset of about 1 eV between BeTe and ZnSe has been determined by means of photo-luminescence and photo-electron-spectroscopy. © 1998 Elsevier Science B.V.

Benzene adsorption on a pseudomorphic Cu monolayer on Ni(111) - a combined TPD and ARUPS study - Koschel, Herbert; Held, Georg; Trischberger, P.; Widdra, Wolf; Steinrück, Hans-Peter (Surface Science, 1999)
The adsorption and desorption of benzene on a pseudomorphic Cu monolayer on Ni(111) has been investigated by temperature programmed desorption (TPD) and angle-resolved ultraviolet (UV) photoelectron spectroscopy (ARUPS) using linearly polarized synchrotron radiation. The experimental results are compared to those of an earlier investigation of benzene adsorbed on Ni(111). Benzene is weakly chemisorbed on the pseudomorphic Cu monolayer on Ni(111): Desorption of the first layer occurs in the temperature range between 155 and 230 K with no sign of dissociation; the analysis of the binding energies of the molecular benzene levels reveals small bonding shifts of 0.2-0.30 eV of the benzene π levels as compared to 1.4 eV for the strongly chemisorbed saturated benzene layer on Ni(111). The orientation of benzene on Cu/Ni(111) is determined from the ARUPS spectra in combination with symmetry selection rules. For low coverages, the molecular plane is oriented parallel to the surface, as is also the case for benzene on Ni(111). However, no well defined azimuthal orientation is observed, which is attributed to frustrated rotations and/or the high mobility of the adsorbed molecules at the temperature of investigation (80 K). For the saturated first benzene layer on Cu/Ni(111), a tilting of the adsorbed molecules occurs due to lateral interactions.

Benzene coadsorbed with CO and NO on Ru(001). I. A UPS study with synchrotron radiation - Heimann, P.A.; Jakob, P.; Pache, T.; Steinrück, Hans-Peter; Menzel, Dietrich (Surface Science, 1989)
Angle-resolved UPS spectra were taken of the coadsorbate systems ( 13 × 13)R13.9° CO+ benzene and (3 × 3) NO+ benzene, on Ru(001). The component molecules were also studied as pure layers. From symmetry selection rules, the benzene molecule is shown to lie parallel to the surface and to retain six-fold symmetry for saturated benzene as well as for both coadsorbed layers. When coadsorbed with benzene, NO is present only in bridge sites. Comparing the pure and coadsorbed layers, the binding energies are different: the coadsorbed benzene orbitals shift to lower values and the CO and NO orbitals shift to higher values. These energy shifts are interpreted as a purely electrostatic initial-state change in the case of CO+ benzene. For NO+ benzene, it is suggested that this electrostatic effect is accompanied by some change in bonding. © 1989.

Benzohydroxamic acid on rutile TiO2(110)-(1×1)– a comparison of ultrahigh-vacuum evaporation with deposition from solution - Köbl, Julia; Fernández, Cynthia C.; Augustin, Lisa-Marie; Kataev, Elmar; Franchi, Stefano; Tsud, Nataliya; Pistonesi, Carolina; Pronsato, M. Estela; Jux, Norbert; Lytken, Ole; Williams, Federico J.; Steinrück, Hans-Peter (Surface Science, 2022)
Hydroxamic acids are an interesting anchor group for organic molecules on oxide surfaces, but very few studies exist on their adsorption on well-defined single-crystal surfaces under well-defined conditions. In the present paper, we use X-ray photoelectron spectroscopy to follow the adsorption of benzohydroxamic acid on a rutile TiO2(110)-(1×1) single-crystal surface. We compare evaporation in ultrahigh vacuum with deposition from ethanol and acetonitrile solutions. Furthermore, we carried out density functional theory calculations to support the assignment of adsorbates. Several species appear on the surface, which are most evident in the N 1s region. The low-coverage species can be explained as originating from a hydroxamate, and decomposed species related to oxygen vacancies or defects. Identification of the high-coverage species, however, remains elusive, and several possibilities are discussed.
CRIS-Team Scopus Importer:2021-12-03
Keywords: Benzohydroxamic acid; Density functional theory calculations; TiO; X-ray photoelectron spectroscopy (XPS)

Benzoic Acid and Phthalic Acid on Atomically Well-Defined MgO(100) Thin Films: Adsorption, Interface Reaction, and Thin Film Growth - Xu, Tao; Mohr, Susanne; Amende, Maximilian; Laurin, Mathias; Döpper, Tibor; Görling, Andreas; Libuda, Jörg (Journal of Physical Chemistry C, 2015)
To better understand the interaction and the growth of thin films of functionalized organic molecules on oxide surfaces, we have studied the adsorption, reaction, and desorption of benzoic acid (BA) and phthalic acid (PA) on a well-ordered MgO(100) thin film grown on a Ag(100) single crystal surface. We have applied isothermal time-resolved infrared reflection absorption spectroscopy (TR-IRAS) and temperature-programmed IRAS (TP-IRAS) under ultrahigh-vacuum (UHV) conditions. BA is dosed using a supersonic molecular beam (SSMB) source while PA is deposited by physical vapor deposition (PVD). For both molecules we have explored the film growth as a function of temperature, both in the monolayer and in the multilayer regime. We have also investigated structural transitions and desorption by temperature-programmed experiments in the range from 100 to 400 K. In addition, we carried out density-functional (DF) calculations. We find that both molecules BA and PA bind through the carboxyl groups to the MgO (100) surface. Upon adsorption at 100 K BA binds in an asymmetric bidentate geometry which exhibits a small tilting angle between the aromatic plane and the surface. Beyond the monolayer, a disordered multilayer film grows, which crystallizes under formation of dimers at around 180 K as indicated by a characteristic splitting of the IR bands. The BA multilayer desorbs at 240 K. Upon adsorption at 300 K, only a BA monolayer forms. Again, BA forms an asymmetric bidentate but with a larger tilting angle compared to low-temperature adsorption. For PA adsorption at 100 K, the adsorption mechanism is observed to change with coverage. At low coverage, both carboxyl groups are deprotonated, and the molecule forms an asymmetric bis-bidentate carboxylate with the aromatic plane nearly perpendicular to the surface. At high coverage, only one carboxyl group binds to the surface and forms an asymmetric bidentate carboxylate while the molecules maintain an upright standing orientation. During PVD of PA, a small fraction of phthalic anhydride (PAA) is formed which coadsorbs at low temperature. Upon annealing, the PAA. desorbs around 250 K, triggering a structural transformation of the PA multilayer during which the PA adopts a more flat lying orientation. The PA multilayer itself desorbs around 310 K. Therefore, only monolayer of PA is stable around 300 K. Again, the adsorption mechanism is coverage dependent, changing from a bis-bidentate carboxylate at lower coverage to a monobidentate carboxylate at higher coverage.

Bimetallic Pd-Pt alloy nanocluster arrays on graphene/Rh(111): formation, stability, and dynamics - Düll, Fabian; Bauer, Udo; Späth, Florian; Bachmann, Philipp; Steinhauer, Johann; Steinrück, Hans-Peter; Papp, Christian (Physical Chemistry Chemical Physics, 2018)
Alloy catalysts have, in many cases, superior properties compared to their single metal counterparts. To gain deeper insights, we used graphene-supported bimetallic nanocluster arrays as a model system. We investigated the site occupation and the dynamic behavior of the metal distribution during adsorption and thermal treatment of CO layers on PdPt alloy nanocluster arrays supported on the graphene/Rh(111) Moire. We find that the adsorption of CO combined with heating to 550 K leads to a rearrangement of the surface atoms, resulting in all the edge sites of the nanoclusters being occupied by Pd atoms. At the same time, Pt gets enriched at the surface.

Bis-polyethylene glycol-functionalized imidazolium ionic liquids: A multi-method approach towards bulk and surface properties - Seidl, Vera; Bosch, Michael; Paap, Ulrike; Livraghi, Mattia; Zhai, Ziwen; Wick, Christian; Koller, Thomas Manfred; Wasserscheid, Peter; Maier, Florian; Smith, Ana-Suncana; Bachmann, Julien; Steinrück, Hans-Peter; et al. (Journal of Ionic Liquids, 2022)
Adding to the versatile class of ionic liquids, we report a new series of hydrophilic polyethylene glycol-functionalized room-temperature ionic liquids, offering interesting thermo- and electrochemical behavior as well as remarkable surface properties. A scalable and generally applicable synthetic procedure for the preparation of N,N’-bis(polyethylene glycol)imidazolium salts, generally abbreviated as [(mPEGn)2Im][A] (n = 2‒6, A = I‒, OMs‒, PF6‒, NTf2‒) was developed. These ionic liquids were studied concerning their thermo- and electrochemical properties, such as phase transition behavior, decomposition temperature, viscosity, and density, as well as electrical conductivity and electrochemical stability, using i.a. differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), electrochemical impedance spectroscopy (EIS) and linear sweep voltammetry (LSV). Additionally, the surface properties were investigated by angle-resolved X-ray photoelectron spectroscopy (ARXPS) and the pendant drop method. olecular dynamics simulations complement the studies and provide insight into the molecular structure of the ionic liquids and their specific orientation at the liquid-vacuum interface.<br

Boosting the Activity in Supported Ionic Liquid-Phase-Catalyzed Hydroformylation via Surface Functionalization of the Carbon Support - Weiß, Alexander; Munoz, Macarena; Haas, Alexander; Rietzler, Florian; Steinrück, Hans-Peter; Haumann, Marco; Wasserscheid, Peter; Etzold, Bastian (ACS Catalysis, 2016)
Supported ionic liquid phase (SILP) catalysts are comprised of a thin ionic liquid film containing a homogeneous transition metal complex that is supported on a highly porous substrate. The application of functionalized activated carbon as a support material for SILP catalysts in a continuous gas-phase propene hydroformylation reaction reveals that the surface properties of the carbon support have a significant influence on the catalytic performance. The catalytic activity of the pristine activated carbon-based SILP catalysts was found to be negligibly small (TOF4h = 3.5 h(-1)) in contrast to that of common oxidic supports such as silica (TOF4h = 15 h(-1)) or alumina. By amine functionalization of the carbon support surface, a dramatic increase in catalytic activity could be observed outperforming the tested oxidic supports by an order of magnitude. A distinct relationship between increased nitrogen content and the point of zero charge of the support and the catalytic activity could be observed. The largest activity increase (TOF4h = 105 h(-1)) was found for functionalized activated carbon SILP catalysts featuring a high point of zero charge and a high nitrogen content. Despite the fact that aldol formation is catalyzed by a base, the respective alcohol was the only detectable byproduct in the reactions.
Keywords: hydroformylation; supported ionic liquid phase; surface functionalization; amino groups; activated carbon

Bromination of 2D materials - Freiberger, Eva Marie; Steffen, Julien; Waleska-Wellnhofer, Natalie; Hemauer, Felix; Schwaab, Valentin; Görling, Andreas; Steinrück, Hans-Peter; Papp, Christian (Nanotechnology, 2024)
The adsorption, reaction and thermal stability of bromine on Rh(111)-supported hexagonal boron nitride (h-BN) and graphene were investigated. Synchrotron radiation-based high-resolution x-ray photoelectron spectroscopy (XPS) and temperature-programmed XPS allowed us to follow the adsorption process and the thermal evolution in situ on the molecular scale. On h-BN/Rh(111), bromine adsorbs exclusively in the pores of the nanomesh while we observe no such selectivity for graphene/Rh(111). Upon heating, bromine undergoes an on-surface reaction on h-BN to form polybromides (170-240 K), which subsequently decompose to bromide (240-640 K). The high thermal stability of Br/h-BN/Rh(111) suggests strong/covalent bonding. Bromine on graphene/Rh(111), on the other hand, reveals no distinct reactivity except for intercalation of small amounts of bromine underneath the 2D layer at high temperatures. In both cases, adsorption is reversible upon heating. Our experiments are supported by a comprehensive theoretical study. DFT calculations were used to describe the nature of the h-BN nanomesh and the graphene moiré in detail and to study the adsorption energetics and substrate interaction of bromine. In addition, the adsorption of bromine on h-BN/Rh(111) was simulated by molecular dynamics using a machine-learning force field.
CRIS-Team Scopus Importer:2024-02-09
Keywords: bromine; functionalization; graphene; hexagonal boron nitride; machine-learning force field; molecular dynamics; x-ray photoelectron spectroscopy

Bromine Adsorption and Thermal Stability on Rh(111): A Combined XPS, LEED and DFT Study - Freiberger, Eva Marie; Steffen, Julien; Waleska-Wellnhofer, Natalie; Harrer, Aileen; Hemauer, Felix; Schwaab, Valentin; Görling, Andreas; Steinrück, Hans-Peter; Papp, Christian (ChemPhysChem, 2023)
This study addresses a fundamental question in surface science: the adsorption of halogens on metal surfaces. Using synchrotron radiation-based high-resolution X-ray photoelectron spectroscopy (XPS), temperature-programmed XPS, low-energy electron diffraction (LEED) and density functional theory (DFT) calculations, we investigated the adsorption and thermal stability of bromine on Rh(111) in detail. The adsorption of elemental bromine on Rh(111) at 170 K was followed in situ by XPS in the Br 3d region, revealing two individual, coverage-dependent species, which we assign to fcc hollow- and bridge-bound atomic bromine. In addition, we find a significant shift in binding energy upon increasing coverage due to adsorbate-adsorbate interactions. Subsequent heating shows a high thermal stability of bromine on Rh(111) up to above 1000 K, indicating strong covalent bonding. To complement the XPS data, LEED was used to study the long-range order of bromine on Rh(111): we observe a (√3×√3)R30° structure for low coverages (≤0.33 ML) and a star-shaped compression structure for higher coverages (0.33–0.43 ML). Combining LEED and DFT calculations, we were able to visualize bromine adsorption on Rh(111) in real space for varying coverages.
CRIS-Team Scopus Importer:2023-09-29
Keywords: adsorption sites; halogens on metals; high-resolution X-ray photoelectron spectroscopy; LEED; synchrotron radiation

C8-BTBT-C8 Thin-Film Transistors Based on Micro-Contact Printed PEDOT:PSS/MWCNT Electrodes - Gubanov, Kirill; Johnson, Manuel; Akay, Melda; Wolz, Benedikt C.; Shen, Dan; Cheng, Xing; Christiansen, Silke; Fink, Rainer (Advanced Electronic Materials, 2023)
Advances in organic materials manufacturing have enabled the creation of electronic devices using solution-processing techniques by employing soluble materials with high conductivity grade. In this exploratory study, the use of micro-contact for poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) polymer ink deposition as high-quality structured electrodes for organic field-effect transistors (OFETs) in top-contact geometry is demonstrated. The optimized OFET's solution-processed fabrication is a promising strategy to be realized in the simple, cost-effective roll-to-roll manufacturing processes. The electrical performance of the fabricated devices is comparable to transistors with gold electrodes prepared via vacuum deposition, and even exceeding the values of the charge carriers’ mobilities and featuring lower contact resistance (Rc), due to lower charge-carrier injection barrier for carbon-based organic electrodes. An addition of multi-walled carbon nanotubes to the PEDOT:PSS decreases Rc even further, changing the work function for better energy alignment with semiconductor materials.
CRIS-Team Scopus Importer:2023-02-17
Keywords: device performance; microcontact printing; microscopy; organic field-effect transistors

Calcium thin film growth on a cyano-substituted poly(p-phenylene vinylene): Interface structure and energetics - Sharp, J. C.; Bebensee, Fabian; Baricuatro, J. H.; Steinrück, Hans-Peter; Gottfried, J. Michael; Campbell, C. T. (Journal of Physical Chemistry C, 2013)
The adsorption of Ca on poly[2-(2-ethylhexyloxy)-5-methoxy-1,4-phenylene cyanovinylene] (MEH-CN-PPV) at 130 and 300 K has been studied by adsorption microcalorimetry, X-ray photoelectron spectroscopy (XPS), and low-energy He ion-scattering spectroscopy (LEIS). The initial heat of adsorption of Ca on MEH-CN-PPV at 300 K is 436 kJ/mol. The heat of adsorption increases to 464 kJ/mol at ∼0.05 ML. We ascribe this initial heat to Ca abstracting cyano groups from the polymer backbone to make Ca(CN) clusters, plus a less important contribution due to Ca abstracting alkoxy groups to make Ca alkoxides. This is supported by XPS which shows the formation of new peaks in the N 1s and C 1s regions consistent with Ca(CN). There is also XPS evidence for Ca reacting with some of the ether groups to make Ca alkoxides at low coverage. Above 0.05 ML Ca coverage, the heat of adsorption decreases nearly exponentially to the sublimation enthalpy of bulk Ca solid (178 kJ/mol) by 5 ML. The observed behavior is attributed to the increasing probability of forming Ca nanoparticles and eventually a continuous solid Ca film on top of the reacted polymer. LEIS, which shows only a slow increase of the signal related to solid Ca, supports this model. Incoming Ca atoms undergo a kinetic competition between diffusing into the polymer to react with subsurface cyano or ether groups and forming or adding to three-dimensional Ca clusters on the surface. For studies done at 130 K, similar behavior is observed, with the heat of adsorption starting lower and decreasing more quickly to the heat of sublimation, already by 1.2 ML Ca coverage. This behavior along with the quicker growth of Ca on the surface of the polymer is attributed to the slower diffusion of Ca adatoms to subsurface cyano and ether groups. The effective thickness of "reacted" polymer (i.e., polymer which has lost its -CN groups and some alkoxy groups) is estimated to be 5.6 nm at 300 K but only 1.0 nm at 130 K. © 2013 American Chemical Society.

Calcium thin film growth on polyfluorenes: Interface structure and energetics - Sharp, J. C.; Feng, X. F.; Farrner, J. A.; Guo, Y. X.; Bebensee, Fabian; Baricuatro, J. H.; Zillner, Elisabeth; Zhu, J. F.; Steinrück, Hans-Peter; Gottfried, Michael; Campbell, C. T. (Journal of Physical Chemistry C, 2014)
The adsorption of Ca vapor on two polyfluorenes, poly(9,9-di-n-hexyl-2,7- fluorene) (PDHF) and poly(9,9-di-n-hexyl-2,7-fluorene vinylene) (PDHFV), has been studied by adsorption microcalorimetry, low-energy He ion scattering spectroscopy (LEIS), and ultraviolet and X-ray photoelectron spectroscopies (UPS and XPS) at surface temperatures between 130 and ∼400 K. At 300 K, the initial heat of adsorption of Ca on PDHF is 250 kJ/mol and on PDHFV is 315 kJ/mol. We ascribe this initial heat to Ca reacting with impurities or defects in the polymers. The heat of adsorption for both polymers decreases nearly exponentially to the sublimation enthalpy of bulk Ca solid (178 kJ/mol) by 0.75 ML. The observed behavior is attributed to the increasing probability of Ca finding and adding to solid three-dimensional Ca islands which nucleate and grow on the polymer surface and eventually grow into a continuous solid Ca film on top of the polymer. LEIS, which shows only a slow increase of the signals related to solid Ca, supports this model. Incoming Ca atoms are subject to a kinetic competition between diffusing into the polymer to react with subsurface defects or impurities versus adding to the three-dimensional Ca clusters on the surface. For studies done at 140 K, a similar behavior is observed, with the heat of adsorption starting lower and decreasing more quickly to the heat of sublimation, already by 0.1 ML Ca coverage. This behavior, along with the quicker growth of Ca on the surface of the polymer, is attributed to the slower diffusion of Ca adatoms to subsurface defects/impurities at 140 K than at 300 K. The opposite effect is observed when studied at 400 K. Calcium induces a downward band bending and work function decrease on both polymers, consistent with transfer of electrons from Ca to the polymers. © 2014 American Chemical Society.

Capture of Carbon Dioxide at the Gas-Liquid Interface Elucidated by Surface Science Approaches - Maier, Florian (Angewandte Chemie International Edition, 2011)
New methods of photoelectron spectroscopy and the application of ionic liquids offer insight into fundamental processes in CO2–liquid systems for carbon dioxide capture and storage, for example, the selective absorption of CO2 in aqueous monoethanolamine.
EAM Import::2019-03-13

Carbon Dioxide Capture by an Amine Functionalized Ionic Liquid: Fundamental Differences of Surface and Bulk Behavior - Niedermaier, Inga; Bahlmann, Matthias; Papp, Christian; Kolbeck, Claudia; Wei, Wei; Krick Calderon, Sandra; Grabau, Mathias; Schulz, Peter; Wasserscheid, Peter; Steinrück, Hans-Peter; Maier, Florian (Journal of the American Chemical Society, 2014)
Carbon dioxide (CO2) absorption by the amine-functionalized ionic liquid (IL) dihydroxyethyl dimethylammonium taurinate at 310 K was studied using surface- and bulk-sensitive experimental techniques. From near-ambient pressure X-ray photoelectron spectroscopy at 0.9 mbar CO2, the amount of captured CO2 per mole of IL in the near-surface region is quantified to similar to 0.58 mol, with similar to 0.15 mol in form of carbamate dianions and similar to 0.43 mol in form of carbamic acid. From isothermal uptake experiments combined with infrared spectroscopy, CO2 is found to be bound in the bulk as carbamate (with nominally 0.5 mol of CO2 bound per 1 mol of IL) up to similar to 2.5 bar CO2, and as carbamic acid (with nominally 1 mol CO2 bound per 1 mol IL) at higher pressures. We attribute the fact that at low pressures carbamic acid is the dominating species in the near-surface region, while only carbamate is formed in the bulk, to differences in solvation in the outermost IL layers as compared to the bulk situation.

Carbon/graphene quantum dots as electrolyte additives for batteries and supercapacitors: A review - Shaker, Majid; Ng, Siow Woon; Sadeghi Ghazvini, Ali Asghar; Javanmardi, Shayan; Gaho, Mehran Ali; Jin, Zhan; Ge, Qi (Journal of Energy Storage, 2024)
Electrolyte is a crucial component in electrochemical energy storage devices (EESDs) such as rechargeable batteries and supercapacitors (SCs). While a substantial effort has been directed to engineering the electrodes, fewer but effective and continuous efforts have been devoted to improve the devices' performance through the modification of their electrolytes. Among these approaches, the strategic integration of minor amounts of additives has led to the formation of appropriate solid-electrolyte interphase (SEI) and cathode-electrolyte interphase (CEI), as well as modifying the ionic conductivity, preventing dendrite growth, and improving charge storage kinetics. Among various additives in the electrolytes, carbon quantum dots (CDs) and graphene quantum dots (GQDs) have emerged as favorable options due to their positive influence on the electrolytes for EESDs. These QDs are soluble in specific solvents and their numerous functional moieties allow them to act as electrolyte additives and polyanions. Furthermore, their excellent physiochemical properties make them excellent candidates as fillers in solid-state electrolytes. The excellence of these QDs is verified by numerous electrochemical and physiochemical characterization methods affirming their positive influence on various parameters such as ion-diffusion kinetics, capacity, and resistance. The application of CDs and GQDs in the electrolytes of EESDs is new and the ruling mechanisms are not well-known yet. This review article provides an overview of the application of CDs and GQDs in both liquid and solid electrolytes for lithium-, sodium-, potassium-, zinc-ion and lithium metal batteries besides SCs. Herein, we aim to offer valuable insights into designing and fabricating a new class of electrolyte additives based on CDs and GQDs for realizing novel electrolytes for EESDs.
CRIS-Team Scopus Importer:2024-03-15
Keywords: Battery; Carbon dots; Electrolyte additives; Graphene quantum dots; Supercapacitor

Catalytically Triggered Energy Release from Strained Organic Molecules: The Surface Chemistry of Quadricyclane and Norbornadiene on Pt(111) - Bauer, Udo; Mohr, Susanne; Döpper, Tibor; Bachmann, Philipp; Späth, Florian; Düll, Fabian; Schwarz, Matthias; Brummel, Olaf; Fromm, Lukas; Pinkert, Ute; Görling, Andreas; Hirsch, Andreas; et al. (Chemistry - A European Journal, 2017)
We have investigated the surface chemistry of the polycyclic valence-isomer pair norbornadiene (NBD) and quadricyclane (QC) on Pt(111). The NBD/QC system is considered to be a prototype for energy storage in strained organic compounds. By using a multimethod approach, including UV photoelectron, high-resolution X-ray photoelectron, and IR reflection-absorption spectroscopic analysis and DFT calculations, we could unambiguously identify and differentiate between the two molecules in the multilayer phase, which implies that the energy-loaded QC molecule is stable in this state. Upon adsorption in the (sub)monolayer regime, the different spectroscopies yielded identical spectra for NBD and QC at 125 and 160K, when multilayer desorption takes place. This behavior is explained by a rapid cycloreversion of QC to NBD upon contact with the Pt surface. The NBD adsorbs in a η:η geometry with an agostic Pt-H interaction of the bridgehead CH subunit and the surface. Strong spectral changes are observed between 190 and 220K because the hydrogen atom that forms the agostic bond is broke. This reaction yields a norbornadienyl intermediate species that is stable up to approximately 380K. At higher temperatures, the molecule dehydrogenates and decomposes into smaller carbonaceous fragment
Keywords: Catalysis; DFT calculations; IR spectroscopy; Photoelectron spectroscopy; Surfaces and interfaces

Cation Exchange at the Interfaces of Ultrathin Films of Fluorous Ionic Liquids on Ag(111) - Lexow, Matthias; Heller, Bettina; Partl, Gabriel; Bhuin, Radha Gobinda; Maier, Florian; Steinrück, Hans-Peter (Langmuir, 2019)
In the context of applications with thin ionic liquid (IL) films on solid supports, we studied the ion distribution within mixed thin IL films by angle-resolved X-ray photoelectron spectroscopy. After the deposition of 1-methyl-3-octylimidazolium hexafluorophosphate, [C(8)C(1)Im][PF6], on top of a wetting layer (WL) of 3-methyl-1-(3,3,4,4,4-pentafluorobutyl)imidazolium hexafluorophosphate, [PFBMIm][PF6], on Ag(111) at room temperature (RT), we find a preferential enrichment of the [PFBMIm](+) cation at the IL/vacuum interface. In a similar deposition experiment at 82 K, this cation exchange at the IL/solid interface does not occur. Upon heating the film from 82 K to RT, we observe the replacement of [C(8)C(1)Im](+) by [PFBMIrn]+ at the IL/vacuum interface between similar to 160 and similar to 220 K. No further changes in the surface composition were observed between 220 K and RT. Upon further heating the mixed IL film, we find the complete desorption of [PFBMIm] [PF6] from the mixed film below 410 K, leaving a WL of pure [C(8)C(1)Im][PF6] on Ag(111), which desorbs until 455 K.
CRIS-Team WoS Importer:2019-02-21

Ceria reoxidation by CO2: A model study - Staudt, Thorsten; Lykhach, Yaroslava; Tsud, Nataliya; Skala, Tomas; Prince, K. C.; Matolin, Vladimir; Libuda, Jörg (Journal of Catalysis, 2010)
The activation of CO2 on ceria-based catalysts opens chemical routes to the use of CO2 as an oxidizing agent. Toward a better understanding of the underlying surface reactions, we have performed a model study on well-defined CeO2-x thin films on Cu(1 1 1) under ultra-high-vacuum conditions. Resonant photoelectron spectroscopy is used as a highly sensitive tool to monitor changes in the oxidation state of cerium as a function of CO2 exposure and thermal treatment. It is shown that partial reoxidation of CeO2-x by CO2 occurs with high reaction probabilities (i) even at temperatures as low as room temperature, (ii) on pure CeO2-x in the complete absence of any noble metal co-catalysts, and (iii) in the absence of surface hydroxyl groups or water. In contrast to previous studies on ceria powders, the findings clearly demonstrate the high activity of pure hydroxyl- and metal-free ceria surfaces for CO2 activation, even at low reaction temperatures. (C) 2010 Elsevier Inc. All rights reserved.
Keywords: Ceria; Carbon dioxide; Model catalyst; Heterogeneous catalysis; Resonant photoelectron spectroscopy

Changes in the adsorption and desorption behavior of cyclohexane and benzene on Ni(111) induced by a monoatomic potassium layer - Zebisch, P.; Huber, W.; Steinrück, Hans-Peter (Surface Science, 1991)
The adsorption and desorption behavior of cyclohexane and benzene on a clean, a potassium precovered, and an oxygen precovered Ni(111) surface have been studied by TPD and LEED. Below 120 K, cyclohexane is molecularly adsorbed on all substrates. On the bare Ni(111) surface cyclohexane shows Stranski-Krastanov growth as concluded from the subsequent development of 3 peaks α,β and γ in the TPD spectra that are assigned to desorption from the first layer, the second layer and bulk cyclohexane, respectively. From the zeroth order behavior of the a-peak, desorption from two-dimensional islands via a two-dimensional gas is concluded. Growth in two-dimensional islands is also suggested by the observation of a (√7 × √7)R19.1 LEED structure starting at a coverage as low as 0.04 ML up to the saturation coverage of 0.143 ML. On the potassium precovered surface (θ = 0.34 ML) cyclohexane exhibits Volmer-Weber growth as indicated by the observation of one single peak in the TPD spectra. This change in growth mode is attributed to a strongly reduced van der Waals interaction of cyclohexane to the K-precovered surface. The results are compared to those obtained for a Ni(111) surface precovered with a p(2 × 2) layer of oxygen (θ = 0.25 ML). Dramatic changes are also induced in the adsorption behavior of benzene by preadsorbed potassium. Benzene is no longer chemisorbed as on the clean Ni(111) surface, but is only weakly bonded to the substrate. Whereas layer-by-layer desorption is observed in the TPD spectra on the clean Ni(111) surface, on the K-precovered surface desorption of benzene occurs in one single peak, again indicating a change from Stranski-Krastanov growth on the clean surface to Volmer-Weber growth on the K-precovered surface. © 1991.

Chapter 6. Coadsorption of NO and Co Pt(111) Surface Studied by High-Resolution Synchrotron Radiation Photoemission - Zhu, Junfa; Kinne, Martin; Fuhrmann, Thomas; Tränkenschuh, Barbara; Denecke, Reinhard; Steinrück, Hans-Peter (Nova Science Publishers, 2005)

Characterization of thin CeO2 films electrochemically deposited on HOPG - Faisal, Firas; Toghan, Arafat; Khalakhan, Ivan; Vorokhta, Mykhailo; Matolin, Vladimir; Libuda, Jörg (ELSEVIER SCIENCE BV, 2015)
Electrodeposition is widely used for industrial applications to deposit thin films, coatings, and adhesion layers. Herein, CeO2 thin films were deposited on a highly oriented pyrolytic graphite (HOPG) substrate by cathodic electrodeposition. The influence of the deposition parameters on the yield and on the film morphology is studied and discussed. Morphology and composition of the electrodeposited films were characterized by in-situ atomic force microscopy (AFM), scanning electron microscopy (SEM), Energy Dispersive X-ray spectroscopy (EDX), and X-ray photoelectron spectroscopy (XPS). By AFM we show that the thickness of CeO2 films can be controlled via the Ce3+ concentration in solution and the deposition time. After exposing the films to ambient air, cracking structures are formed, which were analyzed by AFM in detail. The chemical composition of the deposits was analyzed by XPS indicating the formation of nearly stoichiometric CeO2. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Fuel cell catalyst; Electrodeposition; Cerium oxide; Thin films; AFM; Cracking

Characterization of thin copper films on Ni(111) by CO titration - Held, Georg; Sklarek, Werner; Mayan, M.; Steinrück, Hans-Peter (Surface Science, 1998)
Ultra-thin copper films on Ni(111) (Θ ≤ 1 ML) were studied by the adsorption of CO followed by high resolution X-ray photoelectron spectroscopy. Saturating the surface at 100 K with CO leads to adsorption on the entire surface, i.e. Cu-covered as well as bare Ni(111) areas. Upon annealing to 220 K the Cu-bonded CO molecules desorb leaving only the Ni-areas covered with CO. High resolution XPS spectra in the O 1s and Cu 2p regime have been recorded after adsorption at 100 K and after annealing to 220 K. The total area of Ni-terminated surface regions can be determined from the integrated O 1s XPS intensities after annealing; from the linear decrease of this area versus the amount of adsorbed copper a two-dimensional growth mode can be identified for layers which are annealed to 800 K. In addition, the CO adsorption sites on the Cu-terminated as well as on the Ni-terminated parts of the surface can be determined from the corresponding O Is binding energies. The changes in the O 1s peak shapes with increasing Cu coverage lead to the conclusion that the adlayers have a very high island density. © 1998 Elsevier Science B.V. All rights reserved.

Charge transfer and spillover phenomena in ceria-supported iridium catalysts: A model study - Lykhach, Yaroslava; Kubát, Jan; Neitzel, Armin; Tsud, Nataliya; Vorokhta, Mykhailo; Skála, Tomáš; Dvořák, Filip; Kosto, Yuliia; Prince, Kevin C.; Matolín, Vladimír; Johánek, Viktor; Mysliveček, Josef; et al. (Journal of Chemical Physics, 2019)
Iridium-based materials are among the most active bifunctional catalysts in heterogeneous catalysis and electrocatalysis. We have investigated the properties of atomically defined Ir/CeO2(111) model systems supported on Cu(111) and Ru(0001) by means of synchrotron radiation photoelectron spectroscopy, resonant photoemission spectroscopy, near ambient pressure X-ray photoelectron spectroscopy (NAP XPS), scanning tunneling microscopy, and temperature programmed desorption. Electronic metal-support interactions in the Ir/CeO2(111) system are accompanied by charge transfer and partial reduction of CeO2(111). The magnitude of the charge transfer depends strongly on the Ir coverage. The Ir/CeO2(111) system is stable against sintering upon annealing to 600 K in ultrahigh vacuum (UHV). Annealing of Ir/CeO2(111) in UHV triggers the reverse oxygen spillover above 450 K. The interaction of hydrogen with Ir/CeO2(111) involves hydrogen spillover and reversible spillover between 100 and 400 K accompanied by the formation of water above 190 K. Formation of water coupled with the strong reduction of CeO2(111) represents the dominant reaction channel upon annealing in H2 above 450 K. The interaction of Ir/CeO2(111) with oxygen has been investigated at moderate and NAP conditions. Additionally, the formation and stability of iridium oxide prepared by deposition of Ir in oxygen atmosphere was investigated upon annealing in UHV and under exposure to H2. The oxidation of Ir nanoparticles under NAP conditions yields stable IrOx nanoparticles. The stability of Ir and IrOx nanoparticles under oxidizing conditions is hampered, however, by encapsulation by cerium oxide above 450 K and additionally by copper and ruthenium oxides under NAP conditions.
CRIS-Team Scopus Importer:2019-12-10

Chemical and (Photo)-Catalytical Transformations in Photonic Crystal Fibers - Schmidt, Matthias; Cubillas, Ana Maria; Taccardi, Nicola; Euser, Tijmen; Cremer, Till; Maier, Florian; Steinrück, Hans-Peter; Russell, Philip St. John; Wasserscheid, Peter; Etzold, Bastian (ChemCatChem, 2013)
The concept of employing photonic crystal fibers for chemical and (photo)-catalytical transformations is presented. These optofluidic microdevices represent a versatile platform where light and fluids can interact for spectroscopic or photoactivation purposes. The use of photonic crystal fibers in chemistry and sensing is reviewed and recent applications as catalytic microreactors are presented. Results on homogeneous catalysis and the immobilization of homogeneous and heterogeneous catalysts in the fiber channels are discussed. The examples demonstrate that combining catalysis and the excellent light guidance of photonic crystal fibers provides unique features for example, for photocatalytic activation and quantitative photospectroscopic reaction analysis. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Chemical Bistability on Catalyst Nanoparticles - Libuda, Jörg; et al. (SCIENCES, 2004)
UnivIS-Import:2015-03-09:Pub.2004.nat.dchph.ppc20.chemic

Chemical fingerprints of large organic molecules in scanning tunneling microscopy: Imaging adsorbate-substrate coupling of metalloporphyrins - Buchner, Florian; Warnick, Karl-Georg; Wölfle, Thorsten; Görling, Andreas; Steinrück, Hans-Peter; Hieringer, Wolfgang; Marbach, Hubertus (Journal of Physical Chemistry C, 2009)
In this combined experimental and theoretical work we demonstrate at the example of tetraphenylporphyrins on Ag(111) how differences in individual adsorbate orbitals and their interaction with the substrate can be exploited to switch the appearance of the adsorbate in scanning tunneling microscopy (STM) experiments, such that electronically and chemically very similar large molecules become distinguishable in STM. In particular, an intermixed layer consisting of 2HTPP (TPP ) tetraphenylporphyrin), CoTPP, and FeTPP molecules on Ag(111) was investigated, and it is demonstrated that STM images acquired with different bias voltages constitute fingerprints of the different molecules within the intermixed layer. By means of density functional calculations the observed features could be explained in detail and traced back to a direct orbital interaction of the adsorbed molecule with the surface. The explicit consideration of the surface in the calculations therefore turned out to be decisive to achieve good agreement with experiment. © 2009 American Chemical Society.

Chemistry at surfaces - Steinrück, Hans-Peter; Libuda, Jörg; King, David A. (Chemical Society Reviews, 2008)
No abstract is available for this content:

Chloroalkylsulfonate ionic liquids by ring opening of sultones with organic chloride salts - Paape, Natalia; Wei, Wei; Bösmann, Andreas; Kolbeck, Claudia; Maier, Florian; Steinrück, Hans-Peter; Wasserscheid, Peter; Schulz, Peter (Chemical Communications, 2008)
An efficient route to prepare ionic liquids with chloroalkylsulfonate anions is presented; the synthesis proceeds in a one-step ring-opening reaction of sultones with an organic chloride salt and provides a very attractive access to new anion functionalised ionic liquids. © The Royal Society of Chemistry.

[cis-(1,3-diene) 2W(CO) 2] complexes as MOCVD precursors for the deposition of thin tungsten - Tungsten carbide films - Jipa, Ilona; Heinemann, Frank Wilhelm; Schneider, Andreas; Popovska, Nadejda; Siddiqi, M. Aslam; Siddiqui, Rehan A.; Atakan, B.; Marbach, Hubertus; Papp, Christian; Steinrück, Hans-Peter; Zenneck, Ulrich (Chemical Vapor Deposition, 2010)
Tungsten - tungsten carbide thin films are deposited by metal-organic (MO)CVD on silica-coated silicon wafers using [cis-(1,3-butadiene) W(CO) ] and [cis-(1,3-cyclohexadiene) W(CO) ], respectively, as tunable precursor complexes. The compounds are prepared through photochemical ligand exchange reactions from [W(CO) ] and fully characterized, including X-ray structure determination and detailed differential thermal analysis (DTA)/thermogravimetry (TG) investigations. Gas-phase diffusion coefficients and the vapor pressure of the compounds are calculated. The MOCVD experiments are performed in a vertical cold-wall reactor and the exhaust gas is analyzed by gas chromatography (GC). X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), atomic force microscopy (AFM), and scanning electron microscopy (SEM) measurements are utilized for film characterization. Consequences of the high oxophilicity of freshly formed tungsten surfaces, consecutive surface reactions of the complex ligands, film growth, and film properties are discussed. Inside the layers, tungsten carbide is identified as the main component. © 2010 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Clathrate hydrates in interstellar environment - Ghosh, Jyotirmoy; Methikkalam, Rabin Rajan J.; Bhuin, Radha Gobinda; Ragupathy, Gopi; Choudhary, Nilesh; Kumar, Rajnish; Pradeep, Thalappil (Proceedings of the National Academy of Sciences of the United States of America, 2019)
Clathrate hydrates (CHs) are ubiquitous in earth under high-pressure conditions, but their existence in the interstellar medium (ISM) remains unknown. Here, we report experimental observations of the formation of methane and carbon dioxide hydrates in an environment analogous to ISM. Thermal treatment of solid methane and carbon dioxide–water mixture in ultrahigh vacuum of the order of 10 −10 mbar for extended periods led to the formation of CHs at 30 and 10 K, respectively. High molecular mobility and H bonding play important roles in the entrapment of gases in the in situ formed 5 12 CH cages. This finding implies that CHs can exist in extreme low-pressure environments present in the ISM. These hydrates in ISM, subjected to various chemical processes, may act as sources for relevant prebiotic molecules.
CRIS-Team Scopus Importer:2019-05-07
Keywords: Amorphous solid water; Clathrate hydrate; Interstellar medium; ISM; Ultra-high vacuum

CO2 activation on single crystal based ceria and magnesia/ceria model catalysts - Lykhach, Yaroslava; Staudt, Thorsten; Streber, Regine; Lorenz, Michael Peter Andreas; Bayer, Andreas; Steinrück, Hans-Peter; Libuda, Jörg (European Physical Journal B, 2010)
Novel multifunctional ceria based materials may show an improved performance in catalytic processes involving CO activation and reforming of hydrocarbons. Towards a more detailed understanding of the underlying surface chemistry, we have investigated CO activation on single crystal based ceria and magnesia/ceria model catalysts. All model systems are prepared starting from well-ordered and fully stoichiometric CeO (111) films on a Cu(111) substrate. Samples with different structure, oxidation state and compositions are generated, including CeO /Cu(111) (reduced), MgO/CeO /Cu(111) (reduced), mixed MgO-CeO /Cu(111) (stoichiometric), and mixed MgO-CeO /Cu(111) (reduced). The morphology of the model surfaces is characterized by means of scanning tunneling microscopy (STM), whereas the electronic structure and reactivity is probed by X-ray photoelectron spectroscopy (XPS). The experimental approach allows us to compare the reactivity of samples containing different types of Ce , Ce , and Mg ions towards CO at a sample temperature of 300 K. Briefly, we detect the formation of two CO -derived species, namely carbonate (CO ) and carboxylate (CO ) groups, on the surfaces of all investigated samples after exposure to CO at 300 K. In parallel to formation of the carbonate species, slow partial reoxidation of reduced CeO /Cu(111) occurs at large doses of CO . The reoxidation of the reduced ceria is largely suppressed on MgO-containing samples. The tendency for reoxidation of Ce to Ce by CO decreases with increasing degree of intermixing between MgO and CeO . Additionally, we have studied the stability of the formed carbonate species as a function of annealing temperature. © 2010 EDP Sciences, SIF, Springer-Verlag Berlin Heidelberg.

Coadsorption of D2O and CO on Pt(111) studied by in situ high-resolution x-ray photoelectron spectroscopy - Kinne, Martin; Fuhrmann, Thomas; Zhu, Junfa; Tränkenschuh, Barbara; Denecke, Reinhard; Steinrück, Hans-Peter (Langmuir, 2004)
The adsorption of DO on Pt(111) and the coadsorption with CO have been revisited by quantitative and in situ high-resolution X-ray photoelectron spectroscopy (XPS). During DO adsorption at 110 K, O 1s spectra clearly show the known formation of a bilayer and multilayers. As indicated by a binding energy change of the multilayer peak in the XP spectra recorded during heating, a structural change in the DO multilayer at the onset of multilayer desorption (∼145 K) is observed. Coadsorption of CO and DO leads to occupation of bridge and on-top sites by CO, with the order in site occupation reversed as compared to the clean surface, as previously observed. In addition, a new CO species is clearly resolved in C 1s spectra, which may be identified with CO on hollow sites. Upon DO desorption, this new species disappears and the CO site occupation changes to the value observed on the clean Pt(111). Induced by CO coadsorption, partial replacement of DO from the surface into higher layers is observed, indicated by a reduced desorption temperature of water and an O 1s binding energy shift toward the value of the multilayer signal. Our results suggest an intermixed first layer of CO and DO molecules; DO on top of this layer also influences the CO site distribution. On a surface precovered with 0.5 monolayer (ML) of CO, DO molecules can only adsorb on top of the CO layer and no mixed layer is formed; hence, no site change is observed. The preadsorbed DO bilayer lowers the initial CO sticking coefficient by a factor of ∼13 as compared to the clean surface; this reduction is larger than previously detected.

Coadsorption of NO and CO on a Pt (111) surface studied by high-resolution synchrotron radiation photoemission - Zhu, Junfa; Kinne, Martin; Fuhrmann, Thomas; Tränkenschuh, Barbara; Denecke, Reinhard; Steinrück, Hans-Peter (Surface Science: New Research, 2005)
UnivIS-Import:2015-04-20:Pub.2005.nat.dchph.lpc2.coadso

CO Adsorption on Pd Nanoparticles: Density Functional and Vibrational Spectroscopy Studies - Libuda, Jörg; et al. (Journal of Physical Chemistry B, 2003)
CO adsorption on Pd nanoparticles was discussed. Density functional theory and vibrational spectroscopy were used. Results showed that CO occupies on-top positions at particle edges and defects. Differences between adsorption properties of nanoparticles of Pd with large fraction of (111) facets and adsorption properties of an ideal Pd(111) surface were also studied.
UnivIS-Import:2015-03-09:Pub.2003.nat.dchph.ppc20.coadso

COLL 106-Surface chemistry with metalloporphyrins and metallophthalocyanines: Formation, structure, and reactivity - Bai, Yun; Flechtner, Ken; Marbach, Hubertus; Buchner, Florian; Hieringer, Wolfgang; Görling, Andreas; Shubina, Tatyana; Clark, Timothy; Steinrück, Hans-Peter; Gottfried, Michael (ACS National Meeting Book of Abstracts, 2008)

Combined photoemission and scanning tunneling microscopy study of the surface-assisted ullmann coupling reaction - Chen, Min; Xiao, Jie; Steinrück, Hans-Peter; Wang, Shiyong; Wang, Weihua; Lin, Nian; Hieringer, Wolfgang; Gottfried, J. Michael (Journal of Physical Chemistry C, 2014)
The adsorption and reaction of 4,4-dibromo-para-terphenyl (DBTP) and 1,3,5-tris(4-bromophenyl)benzene (TBB) on Cu(111) surface were studied with X-ray photoelectron spectroscopy (XPS), ultraviolet photoelectron spectroscopy (UPS), and density functional theory (DFT) calculations. In addition, complementary scanning tunneling microscopy (STM) data are presented. At submonolayer coverage, scission of C-Br bonds occurs between 170 and 240 K. The estimated activation energy for this process is considerably lower than the C-Br bond energy, indicating that bond scission is assisted by Cu atoms of the substrate. The remaining molecular backbones undergo linkage by C-Cu-C bonds to form organometallic oligomers. Annealing of these oligomers leads to the formation of C-C bonded covalent two-dimensional networks. Above monolayer coverage, complete C-Br cleavage requires higher temperature, confirming the role of the Cu surface in the reaction. The results provide insight into the C-Br bond scission as the initial step of the surface-assisted Ullmann reaction. © 2014 American Chemical Society.

Comparative study of the carbide-modified surfaces C/Mo(110) and C/Mo(100) using high-resolution x-ray photoelectron spectroscopy - Gleichweit, Christoph; Neiß, Christian; Maisel, Sven; Bauer, Udo; Späth, Florian; Höfert, Oliver; Vollnhals, Florian; Drost, Martin; Marbach, Hubertus; Görling, Andreas; Steinrück, Hans-Peter; Papp, Christian (Physical Review B, 2015)
The preparations of single (monolayer) and bulk carbides on the Mo(110) and Mo(100) single crystals are followed in situ at 1200 K using synchrotron-based high-resolution x-ray photoelectron spectroscopy of the C 1s and core Mo 3d(5/2) levels. By comparing the experimental results to first principles calculations using density functional theory, we suggest real-space surface structures for the carbide-modified surfaces. For a monolayer carbide on Mo(110), carbon dimers adsorb in the long-bridge site, most likely at a coverage of 3/8 ML carbon atoms per Mo surface atom. For the bulk carbide, we find a coverage of similar to 0.5ML on the surface, and the calculations show that single carbon atoms are more stable than dimers on the surface. The monolayer carbide on Mo(100) exhibits a coverage of similar to 1ML and agrees with previous studies, while the bulk carbide preparation probably leads to a faceting of the surfac

Comparative study of the electronic structure of CO, CO + K, NO and NO + K on Ni (111) by ARUPS using synchrotron radiation - Schneider, C.; Steinrück, Hans-Peter; Pache, T.; Heimann, P.A.; Coulman, D.; Umbach, E.; Menzel, Dietrich (Vacuum, 1990)
Using angle-resolved UV photoemission spectroscopy (ARUPS) with linerly polarized synchrotron radiation, the authors have studied the electronic structure, 2D band structure and orientation, and the energy dependence of the photoionization cross-sections of the valence levels for various pure and coadsorbed layers of CO and NO on Ni(111). This report summarizes and compares the results of these investigations. It is shown that the position of the shape resonance in the valence spectra cannot be taken as a measure for the intermolecular bonding distance.

Complex loss function of CdTe - Dröge, H.; Fleszar, A.; Hanke, W.; Sing, M.; Knupfer, M.; Fink, J.; Goschenhofer, F.; Becker, C.R.; Kargerbauer, R.; Steinrück, Hans-Peter (Physical Review B, 1999)
We report results of high-resolution electron energy-loss measurements in transmission of CdTe films. In contrast to simple metals and other semiconductors studied experimentally so far, our results show a number of loss structures of comparable strength occupying a rather narrow energy region around the classical plasmon energy. With increasing momentum transfer these structures show no or only weak dispersion and the relative spectral weight shifts from the energetically lowest to the highest feature. The measurements are analyzed using ab initio calculations of the CdTe loss function. © 1999 The American Physical Society.

Complex Monolayer Growth Dynamics of a Highly Symmetric Molecule: NTCDA on Ag(111) - Schmidt, Thomas; Marchetto, Helder; Groh, Ullrich; Fink, Rainer; Umbach, Eberhard (Journal of Physical Chemistry C, 2019)
The growth dynamics of the highly symmetric planar organic molecule NTCDA (1,4,5,6-naphthalene tetra-carboxylic acid dianhydride) on Ag(111) is rather complex, already in the monolayer regime. This dynamics was investigated in situ with high lateral resolution using the aberration-corrected spectro-microscope SMART. Although the molecular structure of NTCDA is very similar to that of the slightly larger molecule PTCDA, the growth behavior of these two molecules is very different. Several differences of the static geometric, electronic, and vibrational structure have been described previously by several authors, but some dynamic properties hardly accessible by other techniques could be observed in the present real time experiments using the SMART. For instance, it is found by direct observation that after decoration of steps and step bunches and depending on substrate temperature and surface morphology, a two-dimensional lattice gas of diffusing NTCDA molecules is formed. This increases in density upon continuous deposition of molecules before islands nucleate which subsequently grow in size while the density of the lattice gas first remains constant and then is reduced. Furthermore, in a certain temperature and coverage range some macroscopic islands (of micrometer size) abruptly change their shape and position on the time scale of few seconds. These "jumping 2-dim droplets" are observable for adsorption as well as for desorption. Moreover, previously observed 2-dimensional phase transitions can now be followed in real time, yielding further insight into an interesting but complex adsorption system.
CRIS-Team WoS Importer:2019-04-23

Conformation Controls Mobility: 2H-Tetranaphthylporphyrins on Cu(111) - Kuliga, Jan; Massicot, Stephen; Adhikari, Rajan; Ruppel, Michael; Jux, Norbert; Steinrück, Hans-Peter; Marbach, Hubertus (ChemPhysChem, 2020)
The adsorption behavior and the mobility of 2H-Tetranaphthylporphyrin (2HTNP) on Cu(111) was investigated by scanning tunneling microscopy (STM) at room temperature (RT). The molecules adsorb, like the structurally related 2HTPP, in the "inverted" structure with the naphthyl plane restricted to an orientation parallel to the Cu surface. The orientation of the four naphthyl groups yields altogether 16 possible conformations. Due to the existence of rotamer pairs, 10 different appearances are expected on the surface, and all of them are identified by STM at RT. Most interestingly, the orientation of the naphthyl groups significantly influences the diffusion behavior of the molecules on Cu(111). We identify three different groups of conformers, which are either immobile, medium or fast diffusing at RT. The mobility seems to decrease with increasing size of the footprint of the conformers on the surface.
CRIS-Team WoS Importer:2020-03-03

Controlled Catalytic Energy Release of the Norbornadiene/Quadricyclane Molecular Solar Thermal Energy Storage System on Ni(111) - Bauer, Udo; Fromm, Lukas; Weiß, Cornelius; Bachmann, Philipp; Späth, Florian; Düll, Fabian; Steinhauer, Johann; Hieringer, Wolfgang; Görling, Andreas; Hirsch, Andreas; Steinrück, Hans-Peter; Papp, Christian (Journal of Physical Chemistry C, 2019)

Controlled Electron-Induced Fabrication of Metallic Nanostructures on 1 nm Thick Membranes - Preischl, Christian; Le, Linh Hoang; Bilgilisoy Alperen, Elif; Vollnhals, Florian; Gölzhäuser, Armin; Marbach, Hubertus (Small, 2020)
Functional hybrids comprising metallic nanostructures connected and protected by nonmetallic 2D materials are envisioned as miniaturized components for applications in optics, electronics, and magnetics. A promising strategy to build such elements is the direct writing of metallic nanostructures by focused electron beam induced processing (FEBIP) onto insulating 2D materials. Carbon nanomembranes (CNMs), produced via electron-induced crosslinking of self-assembled monolayers (SAMs), are ultrathin and flexible films; their thickness as well as their mechanical and electrical properties are determined by the specific choice of self-assembling molecules. In this work, functionalized CNMs are produced via electron beam induced deposition of Fe(CO)5 onto terphenylthiol SAMs. Clean iron nanostructures of arbitrary size and shape are deposited on the SAMs, and the SAMs are then crosslinked into CNMs. The functionalized CNMs are then transferred onto either solid substrates or onto grids to obtain freestanding metal/CNM hybrid structures. Iron nanostructures with predefined shapes on top of 1 nm thin freestanding CNMs are realized; they stay intact during the fabrication procedures and remain mechanically stable. Combining the ease and versatility of SAMs with the flexibility of FEBIP thus leads to a route for the fabrication of functional hybrid nanostructures.
CRIS-Team Scopus Importer:2020-10-30
Keywords: 2D materials; carbon nanomembranes; electron beam induced depositions; focused electron beam induced processing; iron nanostructures

Controlling additive behavior to reveal an alternative morphology formation mechanism in polymer: Fullerene bulk-heterojunctions - Güldal, Nusret Sena; Berlinghof, Marvin; Kassar, Thaer; Du, Xiaoyan; Jiao, Xuechen; Meyer, Markus; Ameri, Tayebeh; Osvet, Andres; Li, Ning; Destri, Giovanni Li; Fink, Rainer; Ade, Harald; et al. (Journal of Materials Chemistry A, 2016)
One of the most employed morphology optimization methods to design better performing organic photovoltaic devices is ink formulation engineering with additives. In this work, by employing a suboptimal host solvent mixture and 1,8-diiodooctane (DIO) as a very optimal solvent for both components in poly-thieno[3,2b]thiophene-diketopyrrolopyrrole-co-thiophene (DPP-TT-T)-based bulk-heterojunctions (BHJ), an alternative, previously unknown mechanism of additive behavior on BHJ microstructure formation is presented. In situ characterization methods involving grazing incidence X-ray diffraction, white-light reflectometry, laser light scattering and photoluminescence during film drying reveal that the microstructure formation under the influence of DIO is led towards thermodynamic equilibrium during host solvent drying, and the kinetics of morphology formation (i.e. polymer crystallization, fullerene aggregation...) are controlled dominantly by the additive during its evaporation. Ex situ X-ray-based characterization methods, such as scanning transmission X-ray microspectroscopy (STXM) and resonant soft X-ray scattering (R-SoXS), additionally reveal that the microstructure of dried films favors smaller domain sizes with purer domains, smaller fullerene aggregates, bimodal polymer crystallization relative to the substrate and more face-on molecular orientation relative to the donor/acceptor interface, which at the end lead to better performing devices with power conversion efficiencies ranging from 1.25% to 4.68%.
Keywords: Engineering controlled terms: Additives; Fullerenes; Heterojunctions; Interfaces (materials); Light scattering; Microstructure; Molecular orientation; Morphology; Polymers; Solvents; Thiophene; X ray diffraction; X ray scattering Bulk heterojunction (BHJ); Characterization methods; Donor/acceptor interface; Grazing incidence X-ray diffraction; In-situ characterization; Microstructure formation; Organic photovoltaic devices; Power conversion efficiencies Engineering main heading: Polymer films

Controlling metal/oxide interactions in bifunctional nanostructured model catalysts: Pd and BaO on Al2O3/NiAl(110) - Desikusumastuti, Aine; Qin, Zhihui; Staudt, Thorsten; Happel, Markus; Lykhach, Yaroslava; Laurin, Mathias; Shaikhutdinov, Sh.; Libuda, Jörg (Surface Science, 2009)
We have investigated the structure and growth of Pd and BaO containing nanoparticles sequentially co-deposited on an ordered Al2O3/NiAl(1 1 0) by scanning tunneling microscopy (STM), and their interaction with CO and NO2 by infrared reflection absorption spectroscopy (IRAS).Ba deposition and subsequent oxidation result in BaxAl2yOx+3y nanciparticles being formed which are characterized by high particle densities and nucleation both on regular terraces and at oxide defects. In contrast, Pd interaction with the model support is weaker and preferential nucleation occurs mainly at rotational domain boundaries and to a lesser extent at anti-phase domain boundaries. For subsequent co-deposition of Pd on preformed BaxAl2yOx+3y/Al2O3/NiAl(1 1 0), Pd nucleates at the BaxAl2yOx+3y nanoparticles and covers them. The reverse deposition sequence, i.e. Subsequent Ba co-deposition and oxidation on preformed Pd/Al2O3/NiAl(1 1 0), leads to formation of small isolated BaxAl2yOx+3y nanoparticles without contact to Pd, together with large Pd crystallites modified by BaxAl2yOx+3y. The present results provide control over the degree of interaction between metal nanoparticles and oxide nanoparticles on a well-defined model catalyst and thus allow LIS to study effects related effects on the reactivity and catalytic behavior. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Barium oxide; Palladium; Aluminium oxide; Carbon monoxide; Nitrogen dioxide; Scanning tunneling microscopy; IR reflection absorption spectroscopy

Controlling the Adsorption Kinetics via Nanostructuring: Pd Nanoparticles on TiO2 Nanotubes - Honciuc, Andrei; Laurin, Mathias; Albu, Sergiu; Sobota, Marek; Schmuki, Patrik; Libuda, Jörg (Langmuir, 2010)
Activity and selectivity of supported catalysts critically depend on transport and adsorption properties. Combining self-organized porous oxide films with different metal deposition techniques, we have prepared novel Pd/TiO2 catalysts with a new level of structural control. It is shown that these systems make it possible to tune adsorption kinetics via their nanostructure. Self-organized TiO2 nanotubular arrays (TiNTs) prepared by electrochemical methods are used as a support, on which Pd particles are deposited. Whereas physical vapor deposition (PVD) in ultrahigh vacuum (UHV) allows us to selectively grow Pd particles at the tube orifice, Pd/TiNT systems with homogeneously distributed Pd aggregates inside the tubes are available by particle precipitation (PP) from solution. Both methods also provide control over particle size and loading. Using in-situ infrared reflection absorption spectroscopy (IRAS) and molecular beam (MB) methods, we illustrate the relation between the nanostructure of the Pd/TiNT systems and their adsorption kinetics. Control over the metal nanoparticle distribution in the nanotubes leads to drastic differences in adsorption probability and saturation behavior. These differences are rationalized based on differences in surface and gas phase transport resulting from their nanostructure. The results suggest that using carefully designed metal/TiNT systems it may be possible to tailor transport processes in catalytically active materials.

Controlling the Self-Metalation Rate of Tetraphenylporphyrins on Cu(111) via Cyano Functionalization - Lepper, Michael; Köbl, Julia; Zhang, Liang; Meusel, Manuel; Hölzel, Helen; Lungerich, Dominik; Jux, Norbert; De Siervo, Abner; Meyer, Bernd; Steinrück, Hans-Peter; Marbach, Hubertus (Angewandte Chemie International Edition, 2018)
The reaction rate of the self-metalation of free-base tetraphenylporphyrins (TPPs) on Cu(111) increases with the number of cyano groups (n=0, 1, 2, 4) attached at the para positions of the phenyl rings. The findings are based on isothermal scanning tunneling microscopy (STM) measurements. At room temperature, all investigated free-base TPP derivatives adsorb as individual molecules and are aligned with respect to densely packed Cu substrate rows. Annealing at 400K leads to the formation of linear dimers and/or multimers via CN-Cu-CN bonds, accompanied by self-metalation of the free-base porphyrins following a first-order rate equation. When comparing the non-cyano-functionalized and the tetracyano-functionalized molecules, we find a decrease of the reaction rate by a factor of more than 20, corresponding to an increase of the activation energy from 1.48 to 1.59eV. Density functional theory (DFT) calculations give insights into the influence of the peripheral electron-withdrawing cyano groups and explain the experimentally observed effects.
Keywords: cyano functionalization; porphyrinoids; scanning tunneling microscopy; self-metalation; surface chemistry

Conversion of cis- and trans-2-butene with Deuterium on a Pd/Fe3O4 model catalyst - Brandt, Bjoern; Ludwig, Wiebke; Fischer, Jan-Henrik; Libuda, Jörg; Zaera, Francisco; Schauermann, Swetlana (Journal of Catalysis, 2009)
Combining molecular beam (MB) techniques, reflection-absorption infrared spectroscopy (RAIRS), and temperature-programmed desorption (TPD), we have investigated the adsorption and kinetics of conversion of cis- and trans-2-butene with deuterium on a well-defined model supported Pd catalyst. Particular emphasis was placed on the quantitative comparison of the reaction rates of the competing cis-trans isomerization and hydrogenation pathways between both steric isomers. It was observed that the reaction temperature critically affects the cis-trans selectivity of 2-butene in both reaction paths. At low-temperatures (195-210 K), cis-2-butene shows higher activity toward both hydrogenation and isomerization reactions han the trans isomer. At temperatures above 250 K, on the other hand. very similar reaction rates were found for both isomers. Remarkably, deposition of sub-monolayer amounts of strongly dehydrogenated carbonaceous species on the Pd particles results in a significant decrease of the cis-trans isomerization rate for trans-2-butene, but does not affect the rate of this pathway for the cis isomer. Additionally, under high-temperature conditions (250-260 K), co-deposited carbon was shown to assist the catalytic and sustained hydrogenation of both cis- and trans-2-butene, both at similar rates. (C) 2009 Elsevier Inc. All rights reserved.
Keywords: Palladium; Hydrogenation; Isomerization; Selectivity; Molecular Beams; Nanoparticles

Coordination and metalation bifunctionality of Cu with 5,10,15,20-tetra(4- pyridyl)porphyrin: Toward a mixed-valence two-dimensional coordination network - Li, Yang; Xiao, Jie; Shubina, Tatyana; Chen, Min; Shi, Ziliang; Schmid, Martin; Steinrück, Hans-Peter; Gottfried, J. Michael; Lin, Nian (Journal of the American Chemical Society, 2012)
We investigated the coordination self-assembly and metalation reaction of Cu with 5,10,15,20-tetra(4-pyridyl)porphyrin (2HTPyP) on a Au(111) surface by means of scanning tunneling microscopy, X-ray photoelectron spectroscopy, and density functional theory calculations. 2HTPyP was found to interact with Cu through both the peripheral pyridyl groups and the porphyrin core. Pairs of pyridyl groups from neighboring molecules coordinate Cu(0) atoms, which leads to the formation of a supramolecular metal-organic coordination network. The network formation occurs at room temperature; annealing at 450 K enhances the process. The interaction of Cu with the porphyrin core is more complex. At room temperature, formation of an initial complex Cu(0)-2HTPyP is observed. Annealing at 450 K activates an intramolecular redox reaction, by which the coordinated Cu(0) is oxidized to Cu(II) and the complex Cu(II)TPyP is formed. The coordination network consists then of Cu(II) complexes linked by Cu(0) atoms; that is, it represents a mixed-valence two-dimensional coordination network consisting of an ordered array of Cu(II) and Cu(0) centers. Above 520 K, the network degrades and the Cu atoms in the linking positions diffuse into the substrate, while the Cu(II)TPyP complexes form a close-packed structure that is stabilized by weak intermolecular interactions. Density functional theory investigations show that the reaction with Cu(0) proceeds via formation of an initial complex between metal atom and porphyrin followed by formation of Cu(II) porphyrin within the course of the reaction. The activation barrier of the rate limiting step was found to be 24-37 kcal mol depending on the method used. In addition, linear coordination of a Cu atom by two CuTPyP molecules is favorable according to gas-phase calculations. © 2012 American Chemical Society.

Coordination of iron atoms by tetraphenylporphyrin monolayers and multilayers on Ag(111) and formation of iron-tetraphenylporphyrin - Buchner, Florian; Flechtner, Ken; Bai, Yun; Zillner, Elisabeth; Kellner, Ina; Steinrück, Hans-Peter; Marbach, Hubertus; Gottfried, Michael (Journal of Physical Chemistry C, 2008)
The in situ metalation of monolayers and multilayers of 2H-tetraphenylporphyrin (2HTPP) with Fe atoms on Ag(111) was studied with scanning tunneling microscopy (STM) and X-ray photoelectron spectroscopy (XPS). This surface-confined coordination reaction results in the formation of adsorbed iron(II)-tetraphenylporphyrin (FeTPP). It is demonstrated that metalation of 2HTPP is achieved either by depositing iron atoms onto a monolayer of 2HTPP at room temperature or, alternatively, by depositing 2HTPP onto a Ag(111) surface with predeposited iron. The latter route requires elevated temperatures, indicating that this reaction includes at least one step with an activation barrier. In addition, it is demonstrated that vapor deposited Fe atoms also react with multilayers of the porphyrin at room temperature under the formation of FeTPP. © 2008 American Chemical Society.

Coordination reactions and layer exchange processes at a buried metal-organic interface - Chen, Min; Röckert, Michael; Xiao, Jie; Drescher, Hans-Joerg; Steinrück, Hans-Peter; Lytken, Ole; Gottfried, J. Michael (Journal of Physical Chemistry C, 2014)
The reactive interface between phthalocyanine (2HPc) and a Cu(111) surface was investigated with X-ray photoelectron spectroscopy (XPS) and temperature-programmed desorption/reaction (TPD/TPR). 2HPc reacts with Cu(111) to form copper(II) phthalocyanine (CuPc). For 2HPc submonolayers, the reaction starts already below 240 K. Thin 2HPc multilayers (4 monolayers) are completely converted into CuPc at elevated temperatures (500 K). To understand how molecules can react even though they are initially not in contact with the Cu surface, TPD/TPR studies with a NiPc interlayer between Cu and 2HPc were performed. These studies reveal the operation of an exchange mechanism, by which CuPc or NiPc molecules from the first layer are replaced by 2HPc molecules from higher layers. Once a 2HPc molecule comes into contact with the Cu surface, the molecule can react with the surface, forming CuPc, which can then be replaced by another unreacted 2HPc molecule. These findings have important implications for metal-organic interfaces in organic electronic devices, in which the charge carrier injection at the electrodes depends on the electronic properties of the interface. © 2014 American Chemical Society.

CO oxidation on Pt(111) at near ambient pressures - Krick Calderon, Sandra; Grabau, Mathias; Ovari, L.; Kress, B.; Steinrück, Hans-Peter; Papp, Christian (Journal of Chemical Physics, 2016)
The oxidation of CO on Pt(111) was investigated simultaneously by near ambient pressure X-ray photoelectron spectroscopy and online gas analysis. Different CO:O reaction mixtures at total pressures of up to 1 mbar were used in continuous flow mode to obtain an understanding of the surface chemistry. By temperature-programmed and by isothermal measurements, the onset temperature of the reaction was determined for the different reactant mixtures. Highest turnover frequencies were found for the stoichiometric mixture. At elevated temperatures, the reaction becomes diffusion-limited in both temperature-programmed and isothermal measurements. In the highly active regime, no adsorbates were detected on the surface; it is therefore concluded that the catalyst surface is in a metallic state, within the detection limits of the experiment, under the applied conditions. Minor bulk impurities such as silicon were observed to influence the reaction up to total inhibition by formation of non-platinum oxides.

CORE EXCITATION, DECAY, AND FRAGMENTATION IN SOLID BENZENE AS STUDIED BY X-RAY ABSORPTION, RESONANT AUGER, AND PHOTON STIMULATED DESORPTION - Menzel, Dietrich; Rocker, G.; Steinrück, Hans-Peter; Coulman, D.; Heimann, P.A.; Huber, W.; Zebisch, P.; Lloyd, D.R. (Journal of Chemical Physics, 1992)

Correlation between chemical properties and electronic structure of pseudomorphic Cu monolayers on Ni(1 1 1) and Ru(0 0 0 1) - Koschel, Herbert; Birkenheuer, U.; Held, Georg; Steinrück, Hans-Peter (Surface Science, 2001)
The adsorption of CO and benzene on pseudomorphic Cu monolayers on Ni(111) and Ru(0001) shows pronounced differences: For Cu/Ni(111) a behavior very similar to that of Cu(111) is observed, for Cu/Ru(0001) the adsorbate substrate bond is significantly strengthened for both molecules, as is deduced from a shift of the desorption temperature to higher values. Based on angle resolved UV photoelectron spectroscopy using synchrotron radiation at BESSY and density functional calculations we have determined the two-dimensional band structure of the pseudomorphic Cu monolayers on Ni(111) and Ru(0001). Our results show that for Cu/Ni(111) only weak coupling of the Cu3d states to the Ni substrate states occurs. On the other hand, strong coupling is observed for Cu/Ru(0001). This difference is made responsible for the strongly modified chemical properties of Cu/Ru(0001) as compared to Cu/Ni(111). © 2001 Elsevier Science B.V.

CORRIGENDUM: Adsorption of phenylphosphonic acid on rutile TiO2(110) (Surface Science (2020) 698, (S0039602819309410), (10.1016/j.susc.2020.121612)) - Köbl, Julia; Wechsler, Daniel; Kataev, Elmar; Williams, Federico J.; Tsud, Nataliya; Franchi, Stefano; Steinrück, Hans-Peter; Lytken, Ole (Surface Science, 2022)
In the original version of this article, Fig. 6 was plotted incorrectly, since in the input file the data on the polar angle axis were inserted in the inverse order. The correct Fig. 6 is shown below (caption remains unchanged). The error also concerns the deduced angles of the molecular plane relative to the surface plane (polar tilt angle), which are addressed in the manuscript on page 5, left column. The text should correctly read: "Fitting yields a polar tilt angle of 25° of the phenyl ring plane with respect to the surface normal with an azimuthal angle of 42° for the monodentate monolayer (380 K), and a polar tilt angle of 26° with an azimuthal angle of 43° for the mixed bidentate (or mono- and tridentate) monolayer (650–780 K). The fitting procedure was performed following the procedure from Ref. [37] In line with the unchanged electronic structure, the molecular orientation does not change (within the margin of error) when a monodentate monolayer of phenylphosphonic acid is annealed to form a mixed bidentate layer. Notably, for the onefold deprotonated bidentate, a polar tilt angle of ∼40° is estimated from Fig. 8 in Ref. [9]. For comparison, we note that 0.85 ML of phenylphosphonic acid adsorbs on anatase TiO2(101) surfaces at room temperature with a phenyl ring tilted 25° with respect to the surface normal.” Furthermore, the denoted value for the polar angle in the abstract and the summary should be changed to 25° The corrected texts read: Abstract: “Furthermore, the phenyl ring is tilted ∼25º with respect to the surface normal and it either forms 45° or is randomly oriented with respect to [001] crystallographic direction.” Conclusion: “Both monolayers possess essentially the same electronic structure with molecules tilted ∼25° with respect to the surface normal and with either a random azimuthal orientation or a 45° one.”
CRIS-Team Scopus Importer:2021-12-24

Counting electrons on supported nanoparticles - Lykhach, Yaroslava; Kozlov, Sergey M.; Skala, Tomas; Tovt, Andrii; Stetsovych, Vitalii; Tsud, Nataliya; Dvorak, Filip; Johanek, Viktor; Neitzel, Armin; Myslivecek, Josef; Fabris, Stefano; Matolin, Vladimir; et al. (Nature Materials, 2016)
Electronic interactions between metal nanoparticles and oxide supports control the functionality of nanomaterials, for example, the stability, the activity and the selectivity of catalysts(1-5). Such interactions involve electron transfer across the metal/support interface. In this work we quantify this charge transfer on a well-defined platinum/ceria catalyst at particle sizes relevant for heterogeneous catalysis. Combining synchrotron-radiation photoelectron spectroscopy, scanning tunnelling microscopy and density functional calculations we show that the charge transfer per Pt atom is largest for Pt particles of around 50 atoms. Here, approximately one electron is transferred per ten Pt atoms from the nanoparticle to the support. For larger particles, the charge transfer reaches its intrinsic limit set by the support. For smaller particles, charge transfer is partially suppressed by nucleation at defects. These mechanistic and quantitative insights into charge transfer will help to make better use of particle size effects and electronic metal-support interactions in metal/oxide nanomaterials.

Covalent Anchoring and Interfacial Reactions of Adsorbed Porphyrins on Rutile TiO2(110) - Wechsler, Daniel; Fernandez, Cynthia C.; Steinrück, Hans-Peter; Lytken, Ole; Williams, Federico J. (Journal of Physical Chemistry C, 2018)
Adsorption of 5-monocarboxyphenyl-10,15,20-triphenylporphyrin (MCTPP) to rutile TiO2(110) at room temperature produces molecules on the surface covalently anchored through the carboxylate group, coadsorbed with hydroxyl groups. At elevated temperatures, the free-base porphyrin molecules metalate on the surface, forming what we expect to be titanyl (Ti=O) porphyrin. The reaction is strongly coverage dependent with lower coverages metalating at lower temperatures, possibly caused by flat-lying molecules at low coverages being in closer proximity to the surface. This is in contrast to the behavior when exposed to Zn2+ ions in solution, where the coverage dependency is much less pronounced.

Covalent bulk functionalization of graphene - Englert, Jan; Dotzer, Christoph; Yang, Guang; Schmid, Martin; Papp, Christian; Gottfried, Michael; Steinrück, Hans-Peter; Spiecker, Erdmann; Hauke, Frank; Hirsch, Andreas; Hauke, Frank; Spiecker, Erdmann (Nature Chemistry, 2011)
Graphene, a truly two-dimensional and fully π-conjugated honeycomb carbon network, is currently evolving into the most promising successor to silicon in micro- and nanoelectronic applications. However, its wider application is impeded by the difficulties in opening a bandgap in its gapless band-structure, as well as the lack of processability in the resultant intrinscially insoluble material. Covalent chemical modification of the π-electron system is capable of addressing both of these issues through the introduction of variable chemical decoration. Although there has been significant research activity in the field of functionalized graphene, most work to date has focused on the use of graphene oxide. In this Article, we report on the first wet chemical bulk functionalization route beginning with pristine graphite that does not require initial oxidative damage of the graphene basal planes. Through effective reductive activation, covalent functionalization of the charged graphene is achieved by organic diazonium salts. Functionalization was observed spectroscopically, and successfully prevents reaggregation while providing solubility in common organic media. © 2011 Macmillan Publishers Limited. All rights reserved.

Coverage- and Temperature-Dependent Metalation and Dehydrogenation of Tetraphenylporphyrin on Cu(111) - Röckert, Michael; Franke, Matthias; Tariq, Quratulain; Ditze, Stefanie; Stark, Michael Werner; Uffinger, Patrick; Wechsler, Daniel; Singh, Upendra; Xiao, Jie; Marbach, Hubertus; Steinrück, Hans-Peter; Lytken, Ole (Chemistry - A European Journal, 2014)
Using temperature-programmed desorption, supported by X-ray photoelectron spectroscopy and scanning tunneling microscopy, a comprehensive overview of the main reactions of 5,10,15,20-tetraphenyl-21H,23H-porphyrin (2HTPP) on Cu(111) as a function of coverage and temperature is obtained. Three reactions were identified: metalation with Cu substrate atoms, stepwise partial dehydrogenation, and finally complete dehydrogenation. At low coverage the reactions are independent of coverage, but at higher coverage metalation becomes faster and partial dehydrogenation slower. This behavior is explained by a weaker interaction between the iminic nitrogen atoms and the Cu(111) surface in the high-coverage checkerboard structure, leading to faster metalation, and the stabilizing effect of T-type interactions in the [Cu(TPP)] islands formed at high coverage after metalation, leading to slower dehydrogenation. Based on the amount of hydrogen released and the appearance in STM, a structure of the partially dehydrogenated molecule is suggested.

Coverage-Dependent Anchoring of 4,4 '-Biphenyl Dicarboxylic Acid to CoO(111) Thin Films - Mohr, Susanne; Schmitt, Tobias; Döpper, Tibor; Xiang, Feifei; Schwarz, Matthias; Görling, Andreas; Schneider, M. Alexander; Libuda, Jörg (Langmuir, 2017)
We investigated the adsorption behavior of 4,4'-biphenhyl dicarboxylic acid (BDA) on well-ordered CoO(111) films grown on Ir(100) as a function of coverage and temperature using time-resolved and temperature programmed infrared reflection absorption spectroscopy (TR-IRAS, TP-IRAS) in combination with density functional theory (DFT) and scanning tunneling microscopy (STM) under ultrahigh vacuum (UHV) conditions. To compare the binding behavior of BDA as a function of the oxide film thickness, three different CoO(111) film thicknesses were explored: films of about 20 bilayers (BLs) (approximately 5 nm), 2 BLs, and 1 BL. The two carboxylic acid groups of BDA offer two potential anchoring points to the oxide surface. At 150 K, intact BDA adsorbs on 20 BL thick oxide films in planar geometry with the phenyl rings aligned parallel to the surface. With decreasing oxide film thickness, we observe an increasing tendency for deprotonation and the formation of flat-lying BDA molecules anchored as dicarboxylates. After saturation of the first monolayer, intact BDA multilayers grow with molecules aligned parallel to the surface. The BDA multilayer desorbs at around 360 K. Completely different growth behavior is observed if BDA is deposited above the multilayer desorption temperature. Initially, doubly deprotonated dicarboxylates are formed by adopting a flat-lying,orientation. With increasing exposure, however, the adsorbate layer transforms into upright standing monocarboxylates. A sharp OH stretching band (3584 cm(-1)) and a blue-shifted CO stretching band (1759 cm(-1)) indicate weakly interacting apical carboxylic acid groups at the vacuum interface. The anchored monocarboxylate phase slowly desorbs in a temperature range of up to 470 K. At higher temperature, a flat-lying doubly deprotonated BDA is formed, which desorbs and decomposes in a temperature range of up to 600 K.

Coverage-dependent changes in the adsorption geometries of ordered benzene layers on Ru(0 0 0 1) - Braun, Wolfgang; Held, Georg; Steinrück, Hans-Peter; Stellwag, C.; Menzel, Dietrich (Surface Science, 2001)
With its five ordered phases of adsorbed benzene (three commensurate and two incommensurate) the Ru(0 0 0 1) surface offers the unique possibility to study the local adsorption geometry of this molecule on a metal surface over a wide coverage range. We have performed low energy electron diffraction I-V structure analyses of all three commensurate superstructures p(2√3×2√3)R30° (Θ = 0.083 ML), c(2√3×4)rect (Θ = 0.125 ML), and p(√7×√7)R19° (Θ = 0.143 ML). Despite the different lateral distances and lattice symmetries, the geometry of the adsorption complex, i.e. the benzene molecule together with the three Ru atoms forming the hcp adsorption site underneath, is exactly the same in all three phases. We find a significant crown-like buckling distortion of the C ring of about 0.1 angstroms and a small expansion of less than 0.1 angstroms which is within the error bar of the structure determination. The vertical distance between the carbon atoms and the first layer Ru atoms is 2.11 angstroms. The average vertical distance d between the first and the second Ru layer decreases slightly from 2.09 to 2.07 angstroms (±0.05 angstroms) with increasing coverage whereas d increases from 2.13 to 2.16 angstroms (±0.07 angstroms). The largest influence of variations in the benzene coverage is seen for the Ru atoms which are not in direct contact with the benzene molecules.

Coverage dependent disorder-order transition of 2H-tetraphenylporphyrin on Cu(111) - Stark, Michael Werner; Ditze, Stefanie; Drost, Martin; Buchner, Florian; Steinrück, Hans-Peter; Marbach, Hubertus (Langmuir, 2013)
In this study, we investigate the peculiar coverage dependent supramolecular arrangement of 2H-tetraphenylporhpyrin (2HTPP) on Cu(111) with scanning tunneling microscopy at room-temperature. At low coverage, "slow" diffusion of individual 2HTPP molecules along the close-packed atomic rows of the substrate is observed, and no supramolecular ordering occurs. However, at higher coverage, the formation of ordered, checkerboard-like domains is found, with two molecules per unit cell at different distances from the surface. This behavior is attributed to a complex interplay of site specific molecule-substrate interaction, mainly the strong interaction between the iminic N atoms and Cu substrate atoms, with intermolecular T-type and π-π interactions. © 2013 American Chemical Society.

Crystallization of sensitizers controls morphology and performance in Si-/C-PCPDTBT-sensitized P3HT: ICBA ternary blends - Du, Xiaoyan; Jiao, Xuechen; Rechberger, Stefanie; Perea Ospina, Jose Dario; Meyer, Markus; Kazerouni, Negar; Spiecker, Erdmann; Ade, Harald; Brabec, Christoph; Fink, Rainer; Ameri, Tayebeh (Macromolecules, 2017)
Organic solar cells based on multinary components are promising to further boost the device performance. The complex interplay of the morphology and functionality needs further investigations. Here, we report on a systematic study on the morphology evolution of prototype ternary systems upon adding sensitizers featuring similar chemical structures but dramatically different crystallinity, namely poly(3-hexylthiophene) (P3HT) and indene-C-bis-adduct (ICBA) blends with poly[(4,4′-bis(2-ethylhexyl)dithieno[3,2-b:2′,3′-d]silole)-2,6-diyl-alt-(4,7-bis(2-thienyl)-2,1,3-benzothiadi-azole)-5,5′-diyl] (Si-PCPDTBT) and poly[2,6-(4,4-bis(2-ethylhexyl)-4H-cyclopenta[2,1-b;3,4-b′]-dithiophene)-alt-4,7-(2,1,3-benzothiadiazole)] (C-PCPDTBT), employing energy-filtered transmission electron microscopy (EFTEM) and resonant soft X-ray scattering (RSoXS). In addition, a combined density functional theory (DFT) and artificial neuronal network (ANN) computational approach has been utilized to calculate the solubility parameters and Flory-Huggins intermolecular parameters to evaluate the influence of miscibility on the final morphology. Our experiments reveal that the domain spacing and purity of ICBA-rich domains are retained in Si-PCPDTBT-based systems but are strongly reduced in C-PCPDTBT-based ternary systems. The P3HT fiber structure are retained at low sensitizer content but dramatically reduced at high sensitizer content. The theoretical calculations reveal very similar miscibility/compatibility between the two sensitizers and ICBA as well as P3HT. Thus, we conclude that mainly the crystallization of Si-PCPDTBT drives the nanostructure evolution in the ternary systems, while this driving force is absent in C-PCPDTBT-based ternary blends.
Keywords: Computation theoryDeep neural networksHigh resolution transmission electron microscopyMorphologyNeuronsOrganic solar cellsSiliconSolar cellsSolubilityTernary systemsTransmission electron microscopyX ray scattering

Cyano-Functionalized Porphyrins on Cu(111) from One-Dimensional Wires to Two-Dimensional Molecular Frameworks: On the Role of Co-Deposited Metal Atoms - Dos Santos, Alisson Ceccatto; De Campos Ferreira, Rodrigo Cezar; Moreno-Lopez, Juan Carlos; Barreto, Lucas; Lepper, Michael; Landers, Richard; Steinrück, Hans-Peter; Marbach, Hubertus; De Siervo, Abner (Chemistry of Materials, 2020)
Metal adatoms play a key role in surface diffusion, adsorption conformation, and self-assembly of porphyrin molecules on metal surfaces. Herein, we study the specific influence of coadsorption of Fe, Co, and Pd atoms on the behavior of 2H-tetrakis(p-cyano)phenylporphyrin (2H-TCNPP) on Cu(111) using scanning tunneling microscopy. Upon co-deposition of Fe and Co, the molecules form one-dimensional (1D) linear chains after mild annealing on Cu(111) driven by the interaction of its cyano groups with metal adatoms. A similar behavior has been observed previously on Cu(111), mediated by Cu adatoms, where the functional CN groups were also found to lower the reaction rate of the so-called porphyrin self-metalation reaction with Cu atoms significantly, in comparison to the non-cyano-functionalized porphyrin. Upon co-deposition of Pd and mild annealing, we find a remarkably different behavior, that is, a massive reorganization from 1D molecular chains to a peculiar rectangular 2D (two-dimensional) network. The molecular appearance changes to a clover shape, which is attributed to a Pd-induced dehydrogenation and subsequent ring closure reaction of the phenyl and pyrrole groups.
CRIS-Team Scopus Importer:2020-03-27

Cyclic hydrocarbons - Held, Georg; Steinrück, Hans-Peter (Landolt-Börnstein "Physics of Covered Solid Surfaces - Adsorbed Layers on Surfaces", 2005)
UnivIS-Import:2015-04-20:Pub.2005.nat.dchph.lpc2.cyclic

Cyclic thiouronium ionic liquids: Physicochemical properties and their electronic structure probed by X-ray induced photoelectron spectroscopy - Taccardi, Nicola; Niedermaier, Inga; Maier, Florian; Steinrück, Hans-Peter; Wasserscheid, Peter (Chemistry - A European Journal, 2012)
Radiography of a structure skeleton: Cyclic thiouronium ionic liquids have been synthesized and characterized in such a way that the straightforward introduction of three different alkyl substituents at the cation has been realized. X-ray induced photoelectron spectroscopy studies indicated a significant electronic contribution of the free electrons at the sulfur to stabilize the cationic charge, leading to structures with peculiar physicochemical properties (see figure). Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Das Prinzip der Detaillierten Gleichgewichte im System H2/Nickel und CO/Nickel - Steinrück, Hans-Peter (1986)
UnivIS-Import:2015-03-05:Pub.1986.nat.dchph.lpc2.daspri

Das Prinzip der Detaillierten Gleichgewichte im System H 2/Nickel und CO/Nickel - Steinrück, Hans-Peter (1986)

Decomposition of Acetic Acid on Model Pt/CeO2 Catalysts: The Effect of Surface Crowding - Neitzel, Armin; Lykhach, Yaroslava; Johanek, Viktor; Tsud, Nataliya; Skala, Tomas; Prince, Kevin C.; Matolin, Vladimir; Libuda, Jörg (Journal of Physical Chemistry C, 2015)
Adsorption and decomposition of acetic acid were studied by means of synchrotron radiation photoelectron spectroscopy, resonant photoemission spectroscopy, and temperature-programmed desorption on Pt/CeO2(111) model catalysts prepared on Cu(111). Reference experiments under identical conditions were performed on stoichiometric CeO2(111), partially reduced CeO2-x, and oxygen pre-exposed O/Pt/CeO2(111)/Cu(111). The principal species formed on all samples during adsorption of acetic acid at 150 K were acetate and molecularly adsorbed acetic acid. On the basis of the differences in the splitting between the methyl and carboxyl/carboxylate groups in the C 1s spectra, we identified the adsorption sites for acetate and molecularly adsorbed acetic acid on Pt/CeO2. During annealing, we detected an increase in the concentration of acetate on CeO2(111) support exclusively in the presence of supported Pt particles. The effect is caused by the decomposition of molecularly adsorbed acetic acid on Pt particles followed by spillover of acetate to CeO2(111) support. The following surface crowding by acetate on CeO2(111) support alters the decomposition mechanism of acetate with respect to the Pt-free CeO2(111). In particular, the formation of ketene and acetone was largely eliminated on Pt/CeO2. We assume that the surface crowding by acetate triggers a switch in the adsorption geometry of acetate from the bidentate to the monodentate configuration. The acetates in both adsorption geometries were identified according to the different splitting between the methyl and carboxylate groups in the C 1s spectra. Decomposition of acetate did not leave behind any surface carbon on Pt-free CeO2. In contrast, carbonaceous residues were found on CeO2-x, and Pt/CeO2. The carbon residues were oxidatively removed above 500 K only from Pt/CeO2.

Defects in oxygen-depleted titanate nanostructures - Vittadini, Andrea; Schirmer, Michael; Walz, Marie-Madeleine; Vollnhals, Florian; Lukasczyk, Thomas; Steinrück, Hans-Peter; Marbach, Hubertus; Riss, Alexander; Elser, Michael J.; Schürer, Benedikt; Diwald, Oliver (Langmuir, 2012)
The identification of defects and their controlled generation in titanate nanostructures is a key to their successful application in photoelectronic devices. We comprehensively explored the effect of vacuum annealing on morphology and composition of Na Ti O nanowires and protonated H Ti O nanoscrolls using a combination of scanning electron microscopy, Auger and Fourier-transform infrared (FT-IR) spectroscopy, as well as ab initio density functional theory (DFT) calculations. The observation that H Ti O nanoscrolls are more susceptible to electronic reduction and annealing-induced n-type doping than Na Ti O nanowires is attributed to the position of the conduction band minimum. It is close to the vacuum level and, thus, favors the Fermi level-induced compensation of donor states by cation vacancies. In agreement with theoretical predictions that suggest similar formation energies for oxygen and sodium vacancies, we experimentally observed the annealing induced depletion of sodium from the surface of the nanowires. © 2012 American Chemical Society.

Dehydrogenation mechanism of liquid organic hydrogen carriers: Dodecahydro-N-ethylcarbazole on Pd(111) - Amende, Maximilian; Schernich, Stefan; Sobota, Marek; Nikiforidis, Ioannis; Hieringer, Wolfgang; Assenbaum, Daniel; Gleichweit, Christoph; Drescher, Hans-Jörg; Papp, Christian; Steinrück, Hans-Peter; Görling, Andreas; Wasserscheid, Peter; et al. (Chemistry - A European Journal, 2013)
Dodecahydro-N-ethylcarbazole (H-NEC) has been proposed as a potential liquid organic hydrogen carrier (LOHC) for chemical energy storage, as it combines both favourable physicochemical and thermodynamic properties. The design of optimised dehydrogenation catalysts for LOHC technology requires a detailed understanding of the reaction pathways and the microkinetics. Here, we investigate the dehydrogenation mechanism of H-NEC on Pd(111) by using a surface-science approach under ultrahigh vacuum conditions. By combining infrared reflection-absorption spectroscopy, density functional theory calculations and X-ray photoelectron spectroscopy, surface intermediates and their stability are identified. We show that H-NEC adsorbs molecularly up to 173 K. Above this temperature (223 K), activation of C-H bonds is observed within the five-membered ring. Rapid dehydrogenation occurs to octahydro-N-ethylcarbazole (H-NEC), which is identified as a stable surface intermediate at 223 K. Above 273 K, further dehydrogenation of H -NEC proceeds within the six-membered rings. Starting from clean Pd(111), C-N bond scission, an undesired side reaction, is observed above 350 K. By complementing surface spectroscopy, we present a temperature-programmed molecular beam experiment, which permits direct observation of dehydrogenation products in the gas phase during continuous dosing of the LOHC. We identify H-NEC as the main product desorbing from Pd(111). The onset temperature for H-NEC desorption is 330 K, the maximum reaction rate is reached around 550 K. The fact that preferential desorption of H -NEC is observed even above the temperature threshold for H -NEC dehydrogenation on the clean surface is attributed to the presence of surface dehydrogenation and decomposition products during continuous reactant exposure. © 2013 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.

Dehydrogenation of Dodecahydro-N-ethylcarbazole on Pd/Al2O3 Model Catalysts - Sobota, Marek; Nikiforidis, Ioannis; Amende, Maximilian; Sanmartίn Zanón, Beatriz; Staudt, Thorsten; Höfert, Oliver; Lykhach, Yaroslava; Papp, Christian; Hieringer, Wolfgang; Laurin, Mathias; Assenbaum, Daniel; Wasserscheid, Peter; et al. (Chemistry - A European Journal, 2011)
To elucidate the dehydrogenation mechanism of dodecahydro-N-ethylcarbazole (H-12-NEC) on supported Pd catalysts, we have performed a model study under ultra high vacuum (UHV) conditions. H-12-NEC and its final dehydrogenation product, N-ethylcarbazole (NEC), were deposited by physical vapor deposition (PVD) at temperatures between 120 K and 520 K onto a supported model catalyst, which consisted of Pd nanoparticles grown on a well-ordered alumina film on NiAl(110). Adsorption and thermally induced surface reactions were followed by infrared reflection absorption spectroscopy (IRAS) and high-resolution X-ray photoelectron spectroscopy (HR-XPS) in combination with density functional theory (DFT) calculations. It was shown that, at 120 K, H-12-NEC adsorbs molecularly both on the Al2O3/NiAl(110) support and on the Pd particles. Initial activation of the molecule occurs through C-H bond scission at the 8a- and 9a-positions of the carbazole skeleton at temperatures above 170 K. Dehydrogenation successively proceeds with increasing temperature. Around 350 K, breakage of one C-N bond occurs accompanied by further dehydrogenation of the carbon skeleton. The decomposition intermediates reside on the surface up to 500 K. At higher temperatures, further decay to small fragments and atomic species is observed. These species block most of the absorption sites on the Pd particles, but can be oxidatively removed by heating in oxygen at 600 K, fully restoring the original adsorption properties of the model catalyst.
Keywords: density functional calculations; IR spectroscopy; liquid organic hydrogen carriers; photo-electron spectroscopy; supported catalysts

Dehydrogenation of dodecahydro-N-ethylcarbazole on Pt(111) - Gleichweit, Christoph; Amende, Maximilian; Schernich, Stefan; Zhao, Wei; Lorenz, Michael Peter Andreas; Höfert, Oliver; Brückner, Nicole; Wasserscheid, Peter; Libuda, Jörg; Steinrück, Hans-Peter; Papp, Christian (Chemsuschem, 2013)
Sloshing hydrogen: Liquid organic hydrogen carriers are high-boiling organic molecules, which can be reversibly hydrogenated and dehydrogenated in catalytic processes and are, therefore, a promising chemical hydrogen storage material. One of the promising candidates is the pair N-ethylcarbazole/perhydro- N-ethylcarbazole (NEC/H-NEC). The dehydrogenation and possible side reactions on a Pt(111) surface are evaluated in unprecedented detail. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Dehydrogenation of Liquid Organic Hydrogen Carriers on Supported Pd Model Catalysts: Carbon Incorporation Under Operation Conditions - Schuster, Ralf; Waidhas, Fabian; Bertram, Manon; Runge, Henning; Geile, Simon; Shayduk, Roman; Abuin, Manuel; Vonk, Vedran; Noei, Heshmat; Lykhach, Yaroslava; Bertram, Florian; Stierle, Andreas; et al. (Catalysis Letters, 2018)
Liquid organic hydrogen carriers (LOHCs) have great potential as a hydrogen storage medium needed for a future sustainable energy system. Dehydrogenation of LOHCs requires a catalyst, such as supported Pd nanoparticles. Under reaction conditions, hydrogen and carbon may diffuse into the bulk of supported Pd catalyst particles and affect their activity and selectivity. The detailed understanding of this process is critical for the use of LOHCs in future hydrogen storage technologies. In this work, we studied these processes in-situ on a Pd model catalyst using high-energy grazing incidence X-ray diffraction. Pd nanoparticles were evaporated in ultra-high vacuum on a polished alpha-Al2O3(0001) substrate. The particles, with an initial average size of 3.4 nm, were investigated at elevated temperature during their interaction with H-2 and methylcyclohexane (MCH) representing a model LOHC. The interaction with H-2 was studied in-situ at partial pressures up to 1 bar and temperatures between 300 and 500 K. At 300 K, the Pd nanoparticles (NPs) show a transition from alpha-PdH to beta-PdH as a function of the H-2 pressure. The transition occurs gradually, which is attributed to the heterogeneity of the NP system. The hydrogen uptake in beta-PdHx at 300 K and 1 bar is estimated to be X-H 0.37 +/- 0.03 indicating that the miscibility gap is narrowed for the nanoparticular system. With increasing temperature, X-H decreases until no beta-PdH phase is formed anymore at 500 K. At the same temperature, we studied the interaction of the Pd/sapphire model catalyst with MCH, both in the presence and in the absence of H-2. In the absence of H-2, carbon is formed and diffuses into the bulk yielding PdCx with a C concentration of around x 0.05 +/- 0.01. In the presence of H-2 in the gas phase, bulk carbon formation in the Pd/sapphire model catalyst is completely suppressed. These results show that Pd nanoparticles act as an adequate catalyst for the dehydrogenation of MCH.[GRAPHICS].
Keywords: Liquid organic hydrogen carrier; Dehydrogenation; Carbon; XRD; Nanoparticles

Dehydrogenation of the liquid organic hydrogen carrier system 2-methylindole/2-methylindoline/2-methyloctahydroindole on Pt(111) - Bachmann, Philipp; Steinhauer, Johann; Späth, Florian; Düll, Fabian; Bauer, Udo; Eschenbacher, Roman; Hemauer, Felix; Scheuermeyer, Marlene; Bösmann, Andreas; Büttner, Miriam; Neiß, Christian; Görling, Andreas; et al. (Journal of Chemical Physics, 2019)
Among other N-heterocycles, indole and its substituted derivatives, such as methylindoles, are considered promising Liquid Organic Hydrogen Carriers (LOHCs) for the storage of renewable energy. We used X-ray photoelectron spectroscopy (XPS), temperature programmed desorption (TPD), and density-functional theory (DFT) to investigate the low temperature adsorption and consecutive dehydrogenation reaction during heating of 2-methylindole, 2-methylindoline, and 2-methyloctahydroindole on Pt(111) and their viability as the LOHC system. In the photoemission experiments, for all Hx-2-methylindoles, we find deprotonation at the NH bond starting between 240 and 300 K, resulting in a 2-methylindolide species. Simultaneously or before this reaction step, the dehydrogenation of 2-methyloctahydroindole via 2-methylindoline and 2-methylindole intermediates is observed. For 2-methyloctahydroindole, we also find π-allyl intermediates above 230 K. Starting at ∼390 K, decomposition of the remaining 2-methylindolide species takes place under the conditions of our surface science experiments. DFT calculations give insight into the relative energies of the various species, reaction intermediates, and their isomers both in the gas phase and on the Pt(111) surface.
CRIS-Team Scopus Importer:2019-10-22

Dehydrogenation of the Liquid Organic Hydrogen Carrier System Indole/Indoline/Octahydroindole on Pt(111) - Bachmann, Philipp; Schwarz, Matthias; Steinhauer, Johann; Späth, Florian; Düll, Fabian; Bauer, Udo; Nascimento Silva, Thais; Mohr, Susanne; Hohner, Chantal; Scheuermeyer, Marlene; Wasserscheid, Peter; Libuda, Jörg; et al. (Journal of Physical Chemistry C, 2018)
Indole derivatives are considered as promising liquid organic hydrogen carriers for renewable energy storage. Using X-ray photoelectron spectroscopy, temperature-programmed desorption, and infrared reflection absorption spectroscopy, we investigated low-temperature adsorption and dehydrogenation during heating of indole, indoline, and octahydroindole on Pt(111). For all three molecules, we find deprotonation of the NH bond above 270 K, accompanied with dehydrogenation of indoline and octahydroindole via an indole intermediate, resulting in an indolide species above 300 K. For octahydroindole, we also find a side reaction yielding small amounts of a pi-allyl species between 170 and 450 K. Above 450 K, decomposition of the remaining indolide species takes place.

Demetalation of Surface Porphyrins at the Solid-Liquid Interface - Fernández, Cynthia C.; Franke, Matthias; Steinrück, Hans-Peter; Lytken, Ole; Williams, Federico J. (Langmuir, 2021)
Understanding the factors that control the demetalation of surface porphyrins at the solid-liquid interface is important as the molecular properties of porphyrins are largely determined by their metal centers. In this work, we used X-ray photoelectron spectroscopy (XPS) to follow the demetalation of Zn and Cd tetraphenylporphyrin molecules (ZnTPP and CdTPP) adsorbed as three-monolayer-thin multilayer films on Au(111), by exposing the molecular layers to acidic aqueous solutions. We found that porphyrin molecules at the solid-liquid interface are less prone to lose their metal center than molecules in solution. We propose that this behavior is due to either the incoming protons provided by the solution or the outgoing metal ion having to pass through the hydrophobic porphyrin multilayers where they cannot be solvated. Our results are relevant for the design of molecular devices based on porphyrin molecules adsorbed on solid surfaces.
CRIS-Team Scopus Importer:2021-02-12

Density and surface tension of ionic liquids - Kolbeck, Claudia; Lehmann, Julia; Lovelock, Kevin; Cremer, Till; Paape, Natalia; Wasserscheid, Peter; Fröba, Andreas Paul; Maier, Florian; Steinrück, Hans-Peter (Journal of Physical Chemistry B, 2010)
We measured the density and surface tension of 9 bis[(trifluoromethyl) sulfonyl]imide ([Tf N] )-based and 12 1-methyl-3- octylimidazolium ([C C Im] )-based ionic liquids (ILs) with the vibrating tube and the pendant drop method, respectively. This comprehensive set of ILs was chosen to probe the influence of the cations and anions on density and surface tension. When the alkyl chain length in the [C C Im][Tf N] series (n) 1, 2, 4, 6, 8, 10, 12) is increased, a decrease in density is observed. The surface tension initially also decreases but reaches a plateau for alkyl chain lengths greater than n) 8. Functionalizing the alkyl chains with ethylene glycol groups results in a higher density as well as a higher surface tension. For the dependence of density and surface tension on the chemical nature of the anion, relations are only found for subgroups of the studied ILs. Density and surface tension values are discussed with respect to intermolecular interactions and surface composition as determined by angle-resolved X-ray photoelectron spectroscopy (ARXPS). The absence of nonvolatile surface-active contaminants was proven by ARXPS. © 2010 American Chemical Society.

Density functional calculations and IR reflection absorption spectroscopy on the interaction of SO2 with oxide-supported Pd nanoparticles - Luckas, Nicola; Vines Solana, Francesc; Happel, Markus; Desikusumastuti, Aine; Libuda, Jörg; Görling, Andreas (Journal of Physical Chemistry C, 2010)
A systematic study on the interaction of sulfur dioxide (SO) on BaO-supported Pd nanoparticles has been carried out using suitable models and state-of-the-art density functional (DF) calculations. Detailed information concerning the structure and energetics of the different conformations of adsorbed SO is provided as a function of coverage together with calculated infrared reflection absorption spectroscopy (IRAS) spectra. SO may adsorb on Pd(111) in several conformations, some active, η-SO and η-S , and others inactive in IRAS, η-SO O. SO is found to attach stronger to Pd nanoparticle edges and corners, a fact intimately related to catalyst poisoning by site blocking. On Pd nanoparticles, SO is found to preferably adopt adsorption conformations that depend on the specific region on the nanoparticle, thus adding site specificity to vibrational recognition. Molecular beam experiments and IRAS have been performed on a single-crystal-based Pd/BaAlO/NiAl(110) model NO storage and reduction catalyst and its individual components. SO formation on the oxide components, evolution of a SO multilayer, and adsorption of SO on BaO or Pd nanoparticles is linked to DF calculations. The effect of cation intermixing in the oxide support and overlap of absorption bands on the unequivocal discrimination of signals are discussed. © 2010 American Chemical Society.

Determination of adsorption sites of pure and coadsorbed CO on Ni(111) by high resolution X-ray photoelectron spectroscopy - Held, Georg; Schuler, J.; Sklarek, Werner; Steinrück, Hans-Peter (Surface Science, 1998)
O 1s and C 1s peak positions from high resolution X-ray photoelectron spectroscopy were used to determine adsorption sites of CO and CO coadsorbed with O and benzene, respectively, on Ni(111). Pure CO layers at 80 K were characterised by low energy electron diffraction and temperature programmed desorption and studied by X-ray photoelectron spectroscopy in a wide coverage range. For low coverages up to the well-known c(4 × 2) structure (Θ = 0.5 ML) the CO resides on threefold hollow sites. In the p(√7 × √7)R19° structure (Θ = 0.57 ML) the on-top and bridge sites are occupied; for the compressed c(2√3×4) rect structure (Θ = 0.62 ML) there is no clear preference for high symmetry adsorption sites. At room temperature the additional occupation of on-top and bridge sites is even observed at low coverages. In the p(2√3 × 2√3) R30° (benzene+ 2CO) structure the CO resides most likely on threefold hollow sites with benzene molecules occupying the same adsorption sites. After the adsorption onto a p(2 × 2) oxygen layer at about 100 K the CO occupies two sites: on-top and bridge or hollow sites. If this layer is annealed to 260 K only the on-top sites are left on the surface. © 1998 Elsevier Science B.V.

Dicyclohexylmethane as a Liquid Organic Hydrogen Carrier: A Model Study on the Dehydrogenation Mechanism over Pd(111) - Amende, Maximilian; Gleichweit, Christoph; Xu, Tao; Höfert, Oliver; Koch, Marcus; Wasserscheid, Peter; Steinrück, Hans-Peter; Papp, Christian; Libuda, Jörg (Catalysis Letters, 2016)
Abstract: We have studied the dehydrogenation of the liquid organic hydrogen carrier (LOHC) dicyclohexylmethane (DCHM) to diphenylmethane (DPM) and its side reactions on a Pd(111) single crystal surface. The adsorption and thermal evolution of both DPM and DCHM was measured in situ in ultrahigh vacuum (UHV) using synchrotron radiation-based high-resolution X-ray photoelectron spectroscopy (HR-XPS). We found that after deposition at 170 K, the hydrogen-lean DPM undergoes C-H bond scission at the methylene bridge at 200 K and, starting at 360 K, complete dehydrogenation of the phenyl rings occurs. Above 600 K, atomic carbon incorporates into the Pd bulk. For the hydrogen-rich DCHM, the first stable dehydrogenation intermediate, a double π-allylic species, forms already at 190 K. Until 340 K, further dehydrogenation of the phenyl rings and of the methylene bridge occurs, yielding the same intermediate that is formed upon heating of DPM to this temperature, that is, DPM dehydrogenated at the methylene bridge. The onset for the complete dehydrogenation of this intermediate occurs at a much higher temperature than after adsorption of DPM. This behavior is mainly attributed to coadsorbed hydrogen from DCHM dehydrogenation. The results are discussed in comparison to our previous study of DPM and DCHM on Pt(111) revealing strong material dependencies. Graphical Abstract: [Figure not available: see fulltext.]
Keywords: Liquid organic hydrogen carrier; Model catalysis; X-ray photoelectron spectroscopy

Die dynamische Wechselwirkung von n-Butan mit Imidazolium-basierten ionischen Flüssigkeiten - Bhuin, Radha Gobinda; Winter, Leonhard; Lexow, Matthias; Maier, Florian; Steinrück, Hans-Peter (Angewandte Chemie, 2020)
CRIS-Team Scopus Importer:2020-08-14

Diffusion, rotation, and surface chemical bond of individual 2 H-tetraphenylporphyrin molecules on Cu(111) - Buchner, Florian; Xiao, Jie; Zillner, Elisabeth; Chen, Min; Röckert, Michael; Ditze, Stefanie; Stark, Michael Werner; Steinrück, Hans-Peter; Gottfried, Michael; Marbach, Hubertus (Journal of Physical Chemistry C, 2011)
We address the dynamic behavior and the surface chemical bond of 2H-tetraphenylporphyrin (2HTPP) on Cu(111) around room temperature by variable-temperature scanning tunneling microscopy (STM) and X-ray photoelectron spectroscopy (XPS) in ultrahigh vacuum. Between 280 and 345 K, the molecules predominantly display unidirectional diffusion along one of the three densely packed substrate 〈110〉 directions, which is attributed to a high site selectivity of the adsorbate-substrate bond. Above 305 K, the diffusion direction is found to change occasionally by ±120°. The activation barriers for the unidirectional diffusion and for rotation of the diffusion direction are determined to 0.71 ± 0.08 and 1.28 ± 0.12 eV, respectively. XPS shows that the iminic nitrogen atoms of 2HTPP interact strongly with the Cu surface. It is postulated that the local bonding situation is similar as in the initial complex (sitting-atop complex), which has previously been observed during the surface-confined in situ metalation of porphyrins. © 2011 American Chemical Society.

Direct Correlation of Surface Tension and Surface Composition of Ionic Liquid Mixtures—A Combined Vacuum Pendant Drop and Angle-Resolved X-ray Photoelectron Spectroscopy Study - Paap, Ulrike; Seidl, Vera; Meyer, Karsten; Maier, Florian; Steinrück, Hans-Peter (Molecules, 2022)
We investigated the surface tension and surface composition of various mixtures of the two ionic liquids (ILs) 1-methyl-3-octyl-imidazolium hexafluorophosphate [C8C1Im][PF6] and 1,3-bis(polyethylene glycol)imidazolium iodide [(mPEG2)2Im]I in the temperature range from 230 to 370 K under ultraclean vacuum conditions. The surface tension was measured using a newly developed apparatus, and the surface composition was determined by angle-resolved X-ray photoelectron spectroscopy (ARXPS). In the pure ILs, the alkyl chains of [C8C1Im][PF6] and the PEG chains of [(mPEG2)2Im]I are enriched at the IL/vacuum interface. In the mixtures, a strong selective surface enrichment of the alkyl chains occurs, which is most pronounced at low [C8C1Im][PF6] contents. For the surface tension, strong deviations from an ideal mixing behaviour take place. By applying a simple approach based on the surface composition of the mixtures as deduced from ARXPS, we are able to predict and reproduce the experimentally measured temperature-dependent surface tension values with astonishingly high accuracy.
CRIS-Team Scopus Importer:2022-12-23
Keywords: angle-resolved X-ray photoelectron spectroscopy (ARXPS); ionic liquids; pendant drop (PD); surface composition; surface tension; ultra-high vacuum (UHV)

Direct metalation of a phthalocyanine monolayer on Ag(111) with coadsorbed iron atoms - Bai, Yun; Buchner, Florian; Wendahl, Matthew T.; Kellner, Ina; Bayer, Andreas; Steinrück, Hans-Peter; Marbach, Hubertus; Gottfried, Michael (Journal of Physical Chemistry C, 2008)
An ordered monolayer of phthalocyanine on a silver(111) surface reacts with the stoichiometric amount of coadsorbed Fe atoms to form iron(II)- phthalocyanine. This surface-confined redox reaction was studied with X-ray photoelectron spectroscopy (XPS) and scanning tunneling microscopy (STM). The formation of iron-(II)-phthalocyanine was confirmed by comparison with the directly deposited complex. No side reactions such as the coordination of Fe atoms on the peripheral nitrogen atoms of the phthalocyanine molecules were observed. © 2008 American Chemical Society.

Direct synthesis of a metalloporphyrin complex on a surface - Gottfried, Michael; Flechtner, Ken; Kretschmann, Andreas; Lukasczyk, Thomas; Steinrück, Hans-Peter (Journal of the American Chemical Society, 2006)
We demonstrate that well-defined monolayers of a metal complex on a surface can be prepared by direct vapor deposition of the metal atoms on monolayers of the ligand. In particular, ordered monolayers of adsorbed tetraphenylporphyrin (2H-TPP) on a silver surface were exposed to cobalt vapors, resulting in the complexation of the metal by the porphyrin. The formation of the metal complexes was monitored by means of X-ray photoelectron spectroscopy (XPS), which reveals that this metalation reaction leads to a chemical equivalence of all four nitrogen atoms. The described in situ metalation provides a convenient way to produce adsorbed monolayers of more reactive (e.g., air- or solvent-sensitive) or thermally unstable metalloporphyrins that are difficult to evaporate or even to obtain as pure compounds at room temperature. Copyright © 2006 American Chemical Society.

Disordering of an organic overlayer on a metal surface upon cooling - Schoell, A.; Kilian, L.; Zou, Y.; Ziroff, J.; Hame, S.; Reinert, Friedrich; Umbach, E.; Fink, Rainer (Science, 2010)
Inverse melting or disordering, in which the disordered phase forms upon cooling, is known for a few cases in bulk systems under high pressure. We show that inverse disordering also occurs in two dimensions: For a monolayer of 1,4,5,8-naphthalene-tetracarboxylic dianhydride on Ag(111), a completely reversible order-disorder transition appears upon cooling. The transition is driven by strongly anisotropic interactions within the layer versus with the metal substrate. Spectroscopic data reveal changes in the electronic structure of the system corresponding to a strengthening of the interface bonding at low temperatures. We demonstrate that the delicate, temperature-dependent balance between the vertical and lateral forces is the key to understanding this unconventional phase transition.

Dispersion and characterization of arc discharge single-walled carbon nanotubes-towards conducting transparent films - Rösner, Benedikt; Guldi, Dirk Michael; Chen, J.; Minett, A. I.; Fink, Rainer (Nanoscale, 2014)
This study addresses a combination of a well-developed and mild dispersion method and high-quality arc discharge single-walled carbon nanotubes (SWCNTs) as starting materials. Thus, we advance in fabrication of transparent, conducting films with extraordinary low material loss during SWCNT processing. The starting material was characterized by means of thermogravimetric analysis, high-resolution transmission electron microscopy and Raman spectroscopy. The quality of the starting material and produced dispersions was evaluated by ultraviolet and visible light absorption spectroscopy and Raman spectroscopy. A transparent conductive film was fabricated by drop-casting, whereas films were obtained with electrical to optical conductivity ratios (σ/ σ) as high as 2.2, combined with a loss of nanotube material during processing well below 20 wt%. High pressure carbon monoxide conversion (HiPCO) SWCNTs, which are very well described in the literature, were used for comparison. This journal is © the Partner Organisations 2014.

Disproportionation of Nitric Oxide at a Surface-Bound Nickel Porphyrinoid - Stredansky, Matus; Moro, Stefania; Corva, Manuel; Sturmeit, Henning; Mischke, Valentin; Janas, David; Cojocariu, Iulia; Jugovac, Matteo; Cossaro, Albano; Verdini, Alberto; Floreano, Luca; Feng, Zhijing; et al. (Angewandte Chemie International Edition, 2022)
Uncommon metal oxidation states in porphyrinoid cofactors are responsible for the activity of many enzymes. The F430 and P450nor co-factors, with their reduced NiI- and FeIII-containing tetrapyrrolic cores, are prototypical examples of biological systems involved in methane formation and in the reduction of nitric oxide, respectively. Herein, using a comprehensive range of experimental and theoretical methods, we raise evidence that nickel tetraphenyl porphyrins deposited in vacuo on a copper surface are reactive towards nitric oxide disproportionation at room temperature. The interpretation of the measurements is far from being straightforward due to the high reactivity of the different nitrogen oxides species (eventually present in the residual gas background) and of the possible reaction intermediates. The picture is detailed in order to disentangle the challenging complexity of the system, where even a small fraction of contamination can change the scenario.
CRIS-Team Scopus Importer:2022-04-01
Keywords: 2D Materials; Biomimetic Materials; Disproportionation; Nitrogen Monoxide; Porphyrins; Single-Atom Catalysts

Dissociation and oxidation of methanol on Cu(110) - Ammon, Christian; Bayer, Andreas; Held, Georg; Richter, B.; Schmidt, Th.; Steinrück, Hans-Peter (Surface Science, 2002)
We have studied the dissociation and oxidation of methanol on the pure and oxygen-precovered Cu(1 1 0) surface using high resolution X-ray photoelectron spectroscopy (HRXPS) which allows the identification and quantification of reaction intermediates after various annealing steps while they are still on the surface. At 100 K methanol adsorbs molecularly on the clean Cu(1 1 0) surface. Successive annealing causes dissociation into methoxy and formaldehyde around 200 K before eventually all molecular species desorb from the surface. On the oxygen-precovered surface (0.25 ML O) methanol is oxidized on the expense of the preadsorbed oxygen. The analysis of the HRXPS data shows that there are at least three intermediate molecular species present on the surface, most likely methoxy, formaldehyde, and formate. © 2002 Elsevier Science B.V. All rights reserve

Dissociation of water on atomically-defined cobalt oxide nanoislands on Pt(111) and its effect on the adsorption of CO - Wähler, Tobias; Hohner, Chantal; Sun, Zhaozong; Schuster, Ralf; Rodriguez-Fernandez, Jonathan; Lauristen, Jeppe Vang; Libuda, Jörg (Journal of Materials Research, 2019)
We have investigated the adsorption and dissociation of water and its co-adsorption with CO on atomically defined cobalt oxide nanoislands on Pt(111). The CoO islands were prepared under ultrahigh vacuum (UHV) conditions by reactive deposition of Co metal in oxygen atmosphere. The island structure was characterized by scanning tunneling microscopy (STM), showing that the nanoislands consist of a CoO bilayer and are regularly shaped with island edges that are mainly terminated by Co2+ ions. D2O was dosed in UHV onto the CoO islands on Pt(111) after pre-saturation with CO. D2O dissociation was monitored in situ by isothermal and temperature programmed infrared reflection absorption spectroscopy (IRAS). Isotopic exchange experiments were performed with H2O, D2O, and D-2 O-18 to elucidate the nature of the hydroxyl groups. Three principal types of OD species are identified: (i) isolated OD at the edges of the CoO islands (Co-OeD), (ii) OD groups within larger hydroxylated areas on the CoO islands (Co-OcD), and (iii) isolated OD groups on the CoO terraces (Co-OtD). At 400 K, water adsorbs dissociatively on the CoO islands and forms isolated hydroxyl species (Co-OeD) at the island edges only. At room temperature (300 K), the coverage of hydroxyl groups increases rapidly, in line with the water-assisted hydroxylation reaction suggested previously. Adsorption experiments with D-2 O-18 suggest that two equivalent groups are formed from one water molecule after dissociation at island edges, leading to the formation of larger hydroxylated areas on the CoO islands (Co-OcD) and, in addition, isolated OD species on the CoO terraces (Co-OtD). While the initial step of D2O dissociation is facile, the formation of larger hydroxylated areas is a slow and irreversible process. At 200 K, the formation of hydroxylated areas is accompanied by the co-adsorption of molecular water. The hydroxyl groups on the CoO islands are shown to interact with the CO preadsorbed on the CoO/Pt(111) model system. In particular, we observe a new CO species, stabilized by OD groups on the CoO islands, which adsorbs much stronger than CO on the OD-free CoO surface.
CRIS-Team WoS Importer:2019-03-01

Dissociative Adsorption of Benzoic Acid on Well-Ordered Cobalt Oxide Surfaces: Role of the Protons - Schwarz, Matthias; Hohner, Chantal; Mohr, Susanne; Libuda, Jörg (Journal of Physical Chemistry C, 2017)
We performed a surface science model study to reveal the role of the protons which are released upon linking of organic molecules to oxide surfaces via carboxylic acid anchor groups. Specifically, we studied the adsorption, dissociation, and thermal stability of deuterated benzoic acid (C6H5COOD, dl-BA) on three different atomically defined cobalt oxide surfaces, namely, (i) Co3O4(111), (ii) CoO(111), and (iii) CoO(100). All surfaces were prepared in the form of thin films grown on Ir(100). dl-BA was deposited at 300 K via physical vapor deposition (PVD). The interfacial chemistry and film formation was monitored in situ by isothermal time-resolved infrared reflection absorption spectroscopy (TR-IRAS) under ultrahigh vacuum (UHV) conditions. For all three surfaces, we monitored the surface carboxylate and the surface hydroxyl groups as a function of coverage. The thermal stability of the films was probed by temperature-programmed IRAS (TP-IRAS). The comparison between the three surfaces reveals pronounced structure sensitivity. (i) On Co3O4(111), dl-BA binds via a chelating and symmetric carboxylate, strongly tilted with respect to the substrate. The surface hydroxyl groups give rise to a broad vibrational band indicating their involvement in hydrogen bonds. The coadsorbate layer is stable up to 400 K. Above this temperature, hydroxyl desorbs as water, leading to oxygen depletion most likely, followed by decomposition of the benzoate between 420 and 560 K, leaving behind aromatic residues on the surface. (ii) On the oxygen-terminated CoO(111) surface, dl-BA forms of a slightly distorted and slightly tilted bridging carboxylate. Similar as on Co3O4(111), the surface hydroxyl groups form hydrogen bonds. The film is stable up to 420 K. At higher temperature, the surface benzoates decompose slowly over a large temperature range partly, most likely via CO, release and formation of aromatic residues. The surface hydroxyl groups are stable up to higher temperatures (480 K) as compared to Co3O4(111). (iii) On CoO(100) a completely different behavior is observed. The surface benzoate forms a well-defined mixed coadsorbate layer with free surface hydroxyl groups, which are not involved in hydrogen bonds. The orientation of the carboxylate is strongly coverage dependent. At low coverage, the benzoate is tilted with respect to the surface, whereas a fully perpendicular orientation is adopted at high coverage. This film shows the lowest thermal stability. Above 345 K the surface benzoate and protons of the nearby hydroxyl group recombine, leading to desorption of intact dl-BA. Only a small amount of surface benzoate remains, an effect that we mostly attribute to defect sites.

Dissolution of Platinum Single Crystals in Acidic Medium - Sandbeck, Daniel J.S.; Brummel, Olaf; Mayrhofer, Karl J.J.; Libuda, Jörg; Katsounaros, Ioannis; Cherevko, Serhiy (ChemPhysChem, 2019)
Platinum single crystal basal planes consisting of Pt(111), Pt(100), Pt(110) and reference polycrystalline platinum Pt(poly) were subjected to various potentiodynamic and potentiostatic electrochemical treatments in 0.1 M HClO4. Using the scanning flow cell coupled to an inductively coupled plasma mass spectrometer (SFC-ICP-MS) the transient dissolution was detected on-line. Clear trends in dissolution onset potentials and quantities emerged which can be related to the differences in the crystal plane surface structure energies and coordination. Pt(111) is observed to have a higher dissolution onset potential while the generalized trend in dissolution rates and quantities was found to be Pt(110)>P(100)≈Pt(poly)>Pt(111).
CRIS-Team Scopus Importer:2019-11-19
Keywords: fuel cells; platinum; platinum dissolution; platinum single crystals; stability

Doping of Mesoscopic Charge Extraction Layers Enables the Design of Long-Time Stable Organic Solar Cells - Xu, Junyi; Luo, Junsheng; Gubanov, Kirill; Barabash, Anastasiia; Fink, Rainer; Heumüller, Thomas; Brabec, Christoph (ACS Energy Letters, 2024)
Realizing efficient and stable organic solar cells (OSCs) via all-solution processing requires the design of tailored charge extraction interfaces. Herein, we demonstrate a substantially different interface concept for OSC that is based on a low-temperature processed mesoscopic hole transporting layer (HTL) derived from partially covered organic nanoparticles (NPs) in the n-i-p structure. The mesoscopic interface is further doped in a second coating step with an organic salt dopant, BCF-Li. The interactions among the dopant, the solvent for sequential doping, and the semiconductor layer are surprisingly complex. The mesoscopic interface is necessary to evenly wet the semiconductor and prevent the aggregation of the dopant. At the same time, the sequential process reduces the excess acceptor at the interface. Both processes together are necessary to generate an efficiently doped interface for low-Ohmic-charge extraction and stable contacts. Devices with fully solution-processed mesoscopic interfaces show a superb shelf lifetime of over 22000 h without encapsulation and a long-term operational stability under 1 sun illumination for 2000 h (T80). Flexible devices bypass 1000 bending cycles with negligible degradation. Mesoscopic doped interfaces are demonstrated as an alternative to PEDOT:PSS as well as PEDOT related interface concepts for nonfullerene acceptors (NFA) in the n-i-p architecture.
CRIS-Team Scopus Importer:2024-01-12

Double aberration correction in a low-energy electron microscope - Schmidt, Th; Marchetto, H.; Levesque, P. L.; Groh, U.; Maier, F.; Preikszas, D.; Hartel, P.; Spehr, R.; Lilienkamp, G.; Engel, W.; Fink, Rainer; Bauer, E.; et al. (Ultramicroscopy, 2010)
The lateral resolution of a surface sensitive low-energy electron microscope (LEEM) has been improved below 4. nm for the first time. This breakthrough has only been possible by simultaneously correcting the unavoidable spherical and chromatic aberrations of the lens system. We present an experimental criterion to quantify the aberration correction and to optimize the electron optical system. The obtained lateral resolution of 2.6. nm in LEEM enables the first surface sensitive, electron microscopic observation of the herringbone reconstruction on the Au(1. 1. 1) surface. © 2010 Elsevier B.V.

Driving forces for the self-assembly of graphene oxide on organic monolayers - Kirschner, Johannes; Wang, Zhenxing; Eigler, Siegfried; Steinrück, Hans-Peter; Jäger, Christof; Clark, Timothy; Hirsch, Andreas; Halik, Marcus (Nanoscale, 2014)

Dual analyzer system for surface analysis dedicated for angle-resolved photoelectron spectroscopy at liquid surfaces and interfaces - Niedermaier, Inga; Kolbeck, Claudia; Steinrück, Hans-Peter; Maier, Florian (Review of Scientific Instruments, 2016)
The investigation of liquid surfaces and interfaces with the powerful toolbox of ultra-high vacuum (UHV)-based surface science techniques generally has to overcome the issue of liquid evaporation within the vacuum system. In the last decade, however, new classes of liquids with negligible vapor pressure at room temperature-in particular, ionic liquids (ILs)-have emerged for surface science studies. It has been demonstrated that particularly angle-resolved X-ray Photoelectron Spectroscopy (ARXPS) allows for investigating phenomena that occur at gas-liquid and liquid-solid interfaces on the molecular level. The results are not only relevant for IL systems but also for liquids in general. In all of these previous ARXPS studies, the sample holder had to be tilted in order to change the polar detection angle of emitted photoelectrons, which restricted the liquid systems to very thin viscous IL films coating a flat solid support. We now report on the concept and realization of a new and unique laboratory "Dual Analyzer System for Surface Analysis (DASSA)" which enables fast ARXPS, UV photoelectron spectroscopy, imaging XPS, and low-energy ion scattering at the horizontal surface plane of macroscopically thick non-volatile liquid samples. It comprises a UHV chamber equipped with two electron analyzers mounted for simultaneous measurements in 0 degrees and 80 degrees emission relative to the surface normal. The performance of DASSA on a first macroscopic liquid system will be demonstrated. (C) 2016 AIP Publishing LLC.

Dynamic equilibria in supported ionic liquid phase (SILP) catalysis: in situ IR spectroscopy identifies [Ru(CO)xCly]n species in water gas shift catalysis - Bauer, Tanja; Stepic, Robert; Wolf, Patrick; Kollhoff, Fabian; Karawacka, Weronica; Wick, Christian; Haumann, Marco; Wasserscheid, Peter; Smith, David M.; Smith, Ana-Suncana; Libuda, Jörg (Catalysis: Science and Technology, 2018)
Ru-based supported ionic liquid phase (SILP) systems efficiently catalyze the low-temperature water-gas shift reaction (WGSR). While previous studies suggest that Ru-carbonyl species play an important role in the mechanism, detailed knowledge on the catalytically active species is still missing. To identify these carbonyl complexes, we apply in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) in combination with density functional theory (DFT). Investigations of an as-prepared [R(CO)3Cl2]2/ [C4C1C1Im]Cl/Al2O3 catalyst indicate splitting of the dimer induced by Cl−. Subsequently, an equilibrium between several [R(CO)xCly]n species is established, in which the IL serves as an effectively infinite Cl− reservoir. We find that the major species in the system freshly-prepared from [R(CO)3Cl2]2 is indeed [R(CO)3Cl3]−. A smaller amount of [R(CO)2Cl3]− and chloride-rich species [R(CO)2Cl4]2− or [RuCOCl4]2− are also found in the SILP. Similar Ru-carbonyl species are observed during carbonylation of RuCl3/ [C4C1C1Im]Cl/Al2O3, another potential WGSR catalyst. The response of [Ru(CO)3Cl2]2/[C4C1C1Im]Cl/Al2O3 to heating and/or CO dosing was probed in situ and the results confirm the presence of the equilibrium proposed above.
Keywords: SILP catalysis; in situ IR spectroscopy; [Ru(CO)xCly]n species

Effects of deposited Pt particles on the reducibility of CeO2(111) - Bruix, Albert; Migani, Annapaola; Vayssilov, Georgi N.; Neyman, Konstantin M.; Libuda, Jörg; Illas, Francesc (Physical Chemistry Chemical Physics, 2011)
The interaction of Pt particles with the regular CeO2(111) surface has been studied using Pt-8 clusters as representative examples. The atomic and electronic structure of the resulting model systems have been obtained through periodic spin-polarized density functional calculations using the PW91 exchange-correlation potential corrected with the inclusion of a Hubbard U parameter. The focus is on the effect of the metal-support interaction on the surface reducibility of ceria. Several initial geometries and orientations of Pt-8 with respect to the ceria substrate have been explored. It has been found that deposition of Pt-8 over the ceria surface results in spontaneous oxidation of the supported particle with a concomitant reduction of up to two Ce4+ cations to Ce3+. Oxygen vacancy formation on the CeO2(111) surface and oxygen spillover to the adsorbed particle have also been considered. The presence of the supported Pt-8 particles has a rather small effect (similar to 0.2 eV) on the O vacancy formation energy. However, it is predicted that the spillover of atomic oxygen from the substrate to the metal particle greatly facilitates the formation of oxygen vacancies: the calculated energy required to transfer an oxygen atom from the CeO2(111) surface to the supported Pt-8 particle is only 1.00 eV, i.e. considerably smaller than 2.25 eV necessary to form an oxygen vacancy on the bare regular ceria surface. This strongly suggests that the propensity of ceria systems to store and release oxygen is directly affected by the presence of supported Pt particles.

Effects of support and Rh additive on co-based catalysts in the ethanol steam reforming reaction - Ferencz, Zs.; Erdohelyi, A.; Baan, K.; Oszko, A.; Ovari, L.; Konya, Zoltan; Papp, Christian; Steinrück, Hans-Peter; Kiss, J. (ACS Catalysis, 2014)
The effect of the nature of the support and the promotion achieved by a Rh additive on Co-based catalysts in the ethanol steam reforming reaction were studied. The catalysts with 2% Co loading were characterized by temperature-programmed reduction (TPR) and X-ray photoelectron spectroscopy (XPS). In situ diffuse reflectance Fourier-transform infrared spectroscopy (DRIFTS) identified the surface intermediates formed during the reaction, whereas gas phase products were detected by gas chromatography (GC). Upon heating in hydrogen to 773 K, cobalt could not be reduced to Co on alumina, but on silica the reduction was almost complete. On ceria, half of the Co could be reduced to the metallic state. By the presence of a small amount (0.1%) of Rh promoter, the reduction of both cobalt and ceria was greatly enhanced. For Co on the acidic AlO support, the dehydration mechanism was dominant, although on the basic CeO support, a significant amount of hydrogen was also formed. Addition of a small amount of Rh as promoter to the Co/CeO catalyst resulted in a significant further increase in the hydrogen selectivity. © 2014 American Chemical Society.

Electrifying model catalysis: Complex model catalysts studied in ultrahigh vacuum and under electrochemical conditions - Libuda, Jörg (AMER CHEMICAL SOC, 2018)

Electrifying model catalysts for understanding electrocatalytic reactions in liquid electrolytes - Faisal, Firas; Stumm, Corinna; Bertram, Manon; Waidhas, Fabian; Lykhach, Yaroslava; Cherevko, Serhiy; Xiang, Feifei; Ammon, Maximilian Michael; Vorokhta, Mykhailo; Smid, Bretislav; Skala, Tomas; Tsud, Nataliya; et al. (Nature Materials, 2018)
Electrocatalysis is at the heart of our future transition to a renewable energy system. Most energy storage and conversion technologies for renewables rely on electrocatalytic processes and, with increasing availability of cheap electrical energy from renewables, chemical production will witness electrification in the near future(1-3). However, our fundamental understanding of electrocatalysis lags behind the field of classical heterogeneous catalysis that has been the dominating chemical technology for a long time. Here, we describe a new strategy to advance fundamental studies on electrocatalytic materials. We propose to 'electrify' complex oxide-based model catalysts made by surface science methods to explore electrocatalytic reactions in liquid electrolytes. We demonstrate the feasibility of this concept by transferring an atomically defined platinum/cobalt oxide model catalyst into the electrochemical environment while preserving its atomic surface structure. Using this approach, we explore particle size effects and identify hitherto unknown metal-support interactions that stabilize oxidized platinum at the nanoparticle interface. The metal-support interactions open a new synergistic reaction pathway that involves both metallic and oxidized platinum. Our results illustrate the potential of the concept, which makes available a systematic approach to build atomically defined model electrodes for fundamental electrocatalytic studies.

Electrocatalysis with Atomically Defined Model Systems: Metal-Support Interactions between Pt Nanoparticles and Co3O4(111) under Ultrahigh Vacuum and in Liquid Electrolytes - Faisal, Firas; Bertram, Manon; Stumm, Corinna; Wähler, Tobias; Schuster, Ralf; Lykhach, Yaroslava; Neitzel, Armin; Skala, Tomas; Tsud, Nataliya; Beranova, Klara; Prince, Kevin C.; Matolin, Vladimir; et al. (Journal of Physical Chemistry C, 2018)
Electronic metal-support interactions play a key role in the design of heterogeneous catalysts, as they provide a tool for tuning catalytic properties and enhancing catalyst stability. In this work, we explore the role of metal- support interactions in electrocatalysis using a model approach. We investigate the adsorption and reaction behavior of atomically defined Pt/Co3O4 model catalysts under ultrahigh vacuum (UHV) and under electrochemical conditions. The model systems were prepared by physical vapor deposition (PVD) of Pt onto well-ordered Co3O4(111) films on Ir(100), varying the average Pt nanoparticle (NP) size between 10 and 500 atoms per NP. In UHV, the model catalysts were characterized by synchrotron radiation photoelectron spectroscopy (SRPES), temperature-programmed desorption (TPD), and infrared reflection-absorption spectroscopy (IRAS). By SRPES, we show that partially oxidized Pt delta+ species are formed at the interface with the Co3O4 support. CO adsorbs weakly on these Pt delta+ sites and can be identified by IRAS at 115 K. Upon heating, CO adsorbed on metallic Pt-0 reacts with oxygen released from Co3O4 and gives rise to CO2 between 450 and 500 K. As a result of oxygen depletion, the Pt delta+ at the NP interface is reduced to Pt-0. Subsequently, we investigated the adsorption and oxidation of CO under electrochemical conditions on the same Pt/Co3O4 model catalysts. After preparation and characterization in UHV, the model systems were transferred into the electrochemical environment without exposure to ambient conditions. CO adsorption and electrooxidation were performed under conditions where the model system is stable (pH 10, 0.33-1.03 V-RHE, phosphate buffer). By electrochemical infrared reflection-absorption spectroscopy (EC-IRRAS), we show that CO does not adsorb at the partially oxidized Pt delta+ sites in the electrolyte at 300 K. Nevertheless, the Pet(delta+) species at the NP/oxide interface is reduced to Pt-0 upon repeated experimental cycles. This effect increases with decreasing NP size, in line with the behavior observed under UHV conditions. Our findings suggest that electronic metal-support interactions in metal/oxide catalysts play a very similar role in reactions with gaseous reactants and at the electrified interface.

Electrochemically controlled energy storage in a norbornadiene-based solar fuel with 99% reversibility - Waidhas, Fabian; Jevric, Martyn; Fromm, Lukas; Bertram, Manon; Görling, Andreas; Moth-Poulsen, Kasper; Brummel, Olaf; Libuda, Jörg (Nano Energy, 2019)
Solar fuels based on molecular photoswitches hold the potential to combine solar energy conversion, storage, and release in an extremely simple one-photon one-molecule process. In this work we demonstrate electrochemically controlled solar energy storage and release with high reversibility in a tailor-made norbornadiene photoswitch. We investigated the photochemical conversion of the energy-lean 2-cyano-3-(3,4-dimethoxyphenyl)-norbornadiene (NBD’) to its energy-rich counterpart 2-cyano-3-(3,4-dimethoxyphenyl)-quadricyclane (QC’) and the electrochemically triggered reconversion. Characteristic bands of NBD’ and QC’ were identified by density functional theory (DFT) and monitored in-situ during the energy storage and release process by photoelectrochemical infrared reflection absorption spectroscopy (PEC-IRRAS). We identified the stable regions of both isomers at a Pt(111) electrode and tested the stability of the NBD’/QC’ couple over 1000 storage and release cycles. It is shown that reversibilities of more than 99% per cycle can be achieved in this electrochemically triggered energy storage system.
CRIS-Team Scopus Importer:2019-07-23
Keywords: Electrochemistry; Energy conversion; Molecular photoswitches; Norbornadiene; Quadricyclane

Electron affinity of plasma-hydrogenated and chemically oxidized diamond (100) surfaces - Ristein, Jürgen; Maier, Florian; Ley, Lothar (Physical Review B, 2001)
The electron affinity (EA) χ of single crystal diamond (100) is determined as a function of hydrogen and oxygen coverage by a combination of work function and photoemission experiments. For the fully hydrogenated (100)-(2×1):H surface an EA of -1.3 eV and for the oxidized surface C(100)-(1×1):O χ = +1.7 eV are obtained. These are the lowest and the highest electron affinities, respectively, ever reported for any diamond surface. The variation in χ with O and H coverage is well described by a simple dipole model provided that the depolarization is properly taken into account for high adsorbate densities. This analysis favors the bridge position (etherlike) for oxygen on C(100). By mixing H and O adsorbates on a microscopic scale the EA of C(100) can be adjusted at will over 3 eV between the extreme values without jeopardizing the chemical passivation of the diamond surface afforded by H or O termination.
UnivIS-Import:2015-03-09:Pub.2001.nat.dphy.IAP.exphys.electr

Electron-beam induced deposition and autocatalytic decomposition of Co(CO)(3)NO - Vollnhals, Florian; Drost, Martin; TU, Fan; Carrasco Burgos, Esther; Späth, Andreas; Fink, Rainer; Steinrück, Hans-Peter; Marbach, Hubertus (Beilstein Journal of Nanotechnology, 2014)
The autocatalytic growth of arbitrarily shaped nanostructures fabricated by electron beam-induced deposition (EBID) and electron beam-induced surface activation (EBISA) is studied for two precursors: iron pentacarbonyl, Fe(CO)(5), and cobalt tricarbonyl nitrosyl, Co(CO)(3)NO. Different deposits are prepared on silicon nitride membranes and silicon wafers under ultrahigh vacuum conditions, and are studied by scanning electron microscopy (SEM) and scanning transmission X-ray microscopy (STXM), including near edge X-ray absorption fine structure (NEXAFS) spectroscopy. It has previously been shown that Fe(CO)(5) decomposes autocatalytically on Fe seed layers (EBID) and on certain electron beam-activated surfaces, yielding high purity, polycrystalline Fe nanostructures. In this contribution, we investigate the growth of structures from Co(CO)(3)NO and compare it to results obtained from Fe(CO)(5). Co(CO)(3)NO exhibits autocatalytic growth on Co-containing seed layers prepared by EBID using the same precursor. The growth yields granular, oxygen-, carbon- and nitrogen-containing deposits. In contrast to Fe(CO)(5) no decomposition on electron beam-activated surfaces is observed. In addition, we show that the autocatalytic growth of nanostructures from Co(CO)(3)NO can also be initiated by an Fe seed layer, which presents a novel approach to the fabrication of layered nanostructures.
Keywords: autocatalytic growth; cobalt tricarbonyl nitrosyl; electron-beam induced deposition; nanofabrication; scanning transmission X-ray microscopy

Electron-beam-induced deposition and post-treatment processes to locally generate clean titanium oxide nanostructures on Si(100) - Schirmer, Michael; Walz, Marie-Madeleine; Vollnhals, Florian; Lukasczyk, Thomas; Sandmann, Achim; Chen, C.; Steinrück, Hans-Peter; Marbach, Hubertus (Nanotechnology, 2011)
We have investigated the lithographic generation of TiO nanostructures on Si(100) via electron-beam-induced deposition (EBID) of titanium tetraisopropoxide (TTIP) in ultra-high vacuum (UHV) by scanning electron microscopy (SEM) and local Auger electron spectroscopy (AES). In addition, the fabricated nanostructures were also characterized ex situ via atomic force microscopy (AFM) under ambient conditions. In EBID, a highly focused electron beam is used to locally decompose precursor molecules and thereby to generate a deposit. A drawback of this nanofabrication technique is the unintended deposition of material in the vicinity of the impact position of the primary electron beam due to so-called proximity effects. Herein, we present a post-treatment procedure to deplete the unintended deposits by moderate sputtering after the deposition process. Moreover, we were able to observe the formation of pure titanium oxide nanocrystals (>100 nm) in situ upon heating the sample in a well-defined oxygen atmosphere. While the nanocrystal growth for the as-deposited structures also occurs in the surroundings of the irradiated area due to proximity effects, it is limited to the pre-defined regions, if the sample was sputtered before heating the sample under oxygen atmosphere. The described two-step post-treatment procedure after EBID presents a new pathway for the fabrication of clean localized nanostructures. © 2011 IOP Publishing Ltd.

Electron-beam-induced deposition in ultrahigh vacuum: Lithographic fabrication of clean iron nanostructures - Lukasczyk, Thomas; Schirmer, Michael; Steinrück, Hans-Peter; Marbach, Hubertus (Small, 2008)
The generation of nanostructures with arbitrary shapes and well-defined chemical composition is still a challenge and targets the core of the fast-growing field of nanotechnology. One approach is the maskless nanofabrication technique of electron-beam-induced deposition (EBID). Up to now, the purity of these EBID structures has been rather poor. Here we demonstrate that by performing the EBID process solely under ultrahigh vacuum conditions, the lithographic generation of iron nanostructures on Si(100) with an unprecedented purity of higher than 95% is possible. One particular new aspect is the formation of EBID deposits with reduced size in a strain-induced diffusive process, resulting in deposits significantly smaller than 10 nm. © 2008 Wiley-VCH Verlag GmbH & Co.

Electron beam induced surface activation of ultrathin porphyrin layers on Ag(111) - Vollnhals, Florian; Wintrich, Patrick; Walz, Marie-Madeleine; Steinrück, Hans-Peter; Marbach, Hubertus (Langmuir, 2013)
We demonstrate how a focused electron beam can be used to chemically activate porphyrin layers on Ag(111) such that they become locally reactive toward the decomposition of iron pentacarbonyl, Fe(CO). This finding considerably expands the scope of electron beam induced surface activation (EBISA) and also has implications for electron beam induced deposition (EBID). The influence of the porphyrin layer thickness on both processes is studied in detail using scanning tunneling microscopy (STM) and scanning electron microscopy (SEM) as well as Auger electron spectroscopy (AES) and scanning Auger microscopy (SAM). While a closed monolayer of porphyrin molecules does exhibit some activity toward Fe(CO) decomposition after electron irradiation, a growth enhancement is found for bi- and multilayer films. This is attributed to a partial quenching of activated centers in the first layer due to the close proximity of the silver substrate. In addition, we demonstrate that the catalytic decomposition of gaseous Fe(CO) on Ag(111) can be effectively inhibited by introducing a densely packed monolayer of 2H-tetraphenylporphyrin (2HTPP) molecules. © 2013 American Chemical Society.

Electron beam-induced writing of nanoscale iron wires on a functional metal oxide - Vollnhals, Florian; Woolcot, Tom; Walz, Marie-Madeleine; Seiler, Steffen; Steinrück, Hans-Peter; Thornton, Geoff; Marbach, Hubertus (Journal of Physical Chemistry C, 2013)
Electron beam-induced surface activation (EBISA) has been used to grow wires of iron on rutile TiO(110)-(1 × 1) in ultrahigh vacuum. The wires have a width down to ∼20 nm and hence have potential utility as interconnects on this dielectric substrate. Wire formation was achieved using an electron beam from a scanning electron microscope to activate the surface, which was subsequently exposed to Fe(CO). On the basis of scanning tunneling microscopy and Auger electron spectroscopy measurements, the activation mechanism involves electron beam-induced surface reduction and restructuring. © 2013 American Chemical Society.

Electronic band structure of ZnSe(100) - Dröge, H.; Nagelstraßer, M.; Nürnberger, J.; Faschinger, W.; Fleszar, A.; Steinrück, Hans-Peter (Surface Science, 2000)
The k-resolved band structure of an epitaxially grown ZnSe(100) layer was investigated by angle resolved ultraviolet photoelectron spectroscopy combined with ab initio band structure calculations. The ZnSe layer 4 μm thick was grown on a GaAs(100) substrate by molecular beam epitaxy and was transported to the German synchrotron facility BESSY under ultrahigh vacuum (UHV) conditions using a specially designed UHV transport box. The dispersion of the valence bands was measured along the ΓX direction using photon energies between 15.2 and 44 eV. The experimental results are analyzed using the free-electron approximation as well as the calculated ZnSe bulk band structure for the final states.

Electronic properties of a pseudomorphic Cu-layer on Ni(111) - Koschel, Herbert; Held, Georg; Trischberger, P.; Widdra, Wolf; Birkenheuer, U.; Steinrück, Hans-Peter (Applied Surface Science, 1999)
The band structure of a monolayer Cu on Ni(111) was studied both by angle resolved UV photoemission spectroscopy (ARUPS) and density functional (DF) calculations. The Cu 3d-bands at binding energies between 2 eV and 5 eV show a very pronounced k dispersion along the [112̄] and [1̄10] substrate directions, but no dispersion with k. This proves the two-dimensional character of the Cu 3d-bands. The periodicity of the bands coincides with the periodicity of the Ni(111) surface. The experimentally determined two-dimensional band structure of the pseudomorphic Cu monolayer on Ni(111) is in very good agreement with the results of DF calculations on the system. From this comparison we obtain detailed information about the Cu/Ni interaction and the k-dependent coupling of Cu and Ni bands.

Electronic properties of thin Zn layers on Pd(111) during growth and alloying - Bayer, Andreas; Flechtner, Ken; Denecke, Reinhard; Steinrück, Hans-Peter; Neyman, Konstantin; Rösch, Notker (Surface Science, 2006)
The growth and alloying of thin Zn layers on Pd(1 1 1) was investigated using X-ray and ultraviolet photoelectron spectroscopy as well as low energy electron diffraction and correlated with density functional calculations. At 105 K, the formation of a pseudomorphic Zn monolayer is observed. Upon heating this layer to 550 K or upon deposition of 1 ML at 550 K, an ordered p(2 × 1) PdZn surface alloy with a Pd:Zn ratio of ∼1:1 is formed, with a characteristic Pd 3d peak at a binding energy of ∼335.6 eV. For deposition of 3 ML Zn at 550 K or by heating 3 ML, deposited at low temperature, to 500 or 600 K, a PdZn alloy with a Pd:Zn ratio of again ∼1:1 is found in the surface region, with a Pd 3d peak at ∼335.9 eV; the direct preparation at 550 K leads to a more homogeneous and better ordered alloy. The valence band spectrum of this alloy with a low density of states at the Fermi level and pronounced maxima due to the "Pd 4d" band at ∼2.4 and 3.9 eV closely resembles the spectrum of Cu(1 1 1), in good agreement with the calculated density of states for a PdZn alloy of 1:1 stoichiometry. The shift of the "Pd 4d" band to higher binding energies as compared to Pd(1 1 1) indicates a charge transfer from Zn to the Pd 4d levels. Overall, the similarity between the ultraviolet photoelectron spectra for the PdZn alloy and for Cu(1 1 1) is taken as explanation for the similar chemical activity of both systems in methanol steam reforming. © 2005 Elsevier B.V. All rights reserve

Electronic relaxation effects in condensed polyacenes: A high-resolution photoemission study - Rocco, M. L. M.; Haeming, M.; Batchelor, D. R.; Fink, Rainer; Schoell, A.; Umbach, E. (Journal of Chemical Physics, 2008)
We present a high-resolution photoelectron spectroscopy investigation of condensed films of benzene, naphthalene, anthracene, tetracene, and pentacene. High spectroscopic resolution and a systematic variation of the molecular size allow a detailed analysis of the fine structures. The line shapes of the C 1s main lines are analyzed with respect to the different contributions of inhomogeneous broadening, vibronic coupling, and chemical shifts. The shake-up satellite spectra reveal trends, which give insight into the charge redistribution within the molecule upon photoexcitation. In particular, the shake-up between the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) increases in intensity and moves closer toward the C 1s main line if the size of the aromatic system is increased. An explanation is given on the basis of the delocalization of the aromatic system and its capability in screening the photogenerated core hole. A comparison of the HOMO-LUMO shake-up position to the optical band gap gives additional insight into the reorganization of the electronic system upon photoexcitation. © 2008 American Institute of Physics.

Electronic states of an ordered oxide on C-terminated 6H-SiC - Maier, Florian; Ristein, Jürgen; Ley, Lothar; et al. (Surface Science, 1999)
An ordered oxide monolayer with (√3×3√3)R30° periodicity was obtained on carbon-terminated 6H-SiC(000̄3) after preparation with a hydrogen microwave plasma. The stoichiometry of this surface was investigated by X-ray-induced photoelectron spectroscopy. Most components of the Si 2p, C 1s, and O 1s core lines are in agreement with the recently published atomic structure of this ordered monolayer. Beyond this we found hydrocarbon contamination that could be removed by annealing, and small graphitized areas remaining on the surface. We used angle-resolved ultra-violet photoelectron spectroscopy to examine the electronic structure of the valence band. Besides the O 2s and the O 2p lone pair state at 24 eV and 6 eV respectively below the valence band maximum (VBM), we detected a dangling bond state slightly above the VBM and a Si hybrid-O 2p-derived bonding state dispersing between 9.1 and 11.0 eV below the VBM. For the dangling bond state the possibility of a Mott-Hubbard ground state is discussed. In order to clarify the origin of the oxygen-derived states our results are compared with previous investigations of silicon oxides.
UnivIS-Import:2015-03-05:Pub.1999.nat.dphy.IAP.exphys.electr

Electronic structure and orientation of benzene adsorbed on a pseudomorphic Cu monolayer on Ru(0001) - Koschel, Herbert; Held, Georg; Steinrück, Hans-Peter (Surface Science, 2000)
The adsorption of benzene on a pseudomorphic Cu monolayer on Ru(0001) was studied by temperature-programmed desorption and angle-resolved UV photoelectron spectroscopy in combination with symmetry selection rules. Benzene is molecularly adsorbed on the pseudomorphic Cu monolayer on Ru(0001). Desorption of the first layer occurs in the temperature range between 155 and 340 K. In contrast to the clean Ru(0001) surface, no decomposition is observed upon heating. The analysis of the binding energies of the molecular benzene levels reveals a significant bonding shift of 1.1 eV of the benzene π levels, which is nearly as large as the value of 1.4 eV for the strongly chemisorbed saturated benzene layer on Ru(0001). The benzene molecules are azimuthally oriented with the C-H bonds aligned along the [101̄0] direction. This geometry corresponds to an azimuthal rotation of 30° as compared to that on the clean Ru(0001) surface.

Electronic structure and orientation of NO on Ni(111) studied by arups using synchrotron radiation - Steinrück, Hans-Peter; Schneider, C.; Heimann, P.A.; Pache, T.; Umbach, E.; Menzel, Dietrich (Surface Science, 1989)
The electronic structure and the orientation of NO adsorbed on Ni(111) at 120 K was studied by angle resolved UPS using linearly polarized synchrotron radiation and a multichannel angle resolving electron analyzer. The layer investigated corresponds to a coverage of 0.5 ML and exhibits a c(4 × 2) LEED pattern with only twofold bridging sites being occupied. The binding energies for 4 ̃gs, 5 ̃gs and 1 ̃gP at the ḡG point are 15.1, 9.3 and 7.5 eV, respectively; the 1 ̃gP level is very broad which may be due to splitting. The 2D band structure shows a dispersion of 0.3 eV for the 4 ̃gs and 0.6 eV for the 5 ̃gs level, indicative of lateral interactions within the adsorbed NO layer. The photon energy dependence of the photoionization cross sections of the 4 ̃gs, 5 ̃gs and 1 ̃gP NO molecular orbitais has been studied in the energy range 26 eV ≤ ℏgw ≤ 60 eV. The 4 ̃gs level shows a pronounced maximum at ℏω = 36 eV (E = 15 eV) that is peaked in the direction of the surface normal and is interpreted as a shape resonance. For the 5 ̃gs and 1 ̃gP levels no shape resonances are observed. Using dipole selection rules, it is demonstrated independently by initial state and final state arguments that in a c(4 × 2) layer the NO molecules are adsorbed with their molecular axis perpendicular to the surface. © 1989.

Electronic structure of benzene adsorbed on single-domain Si(001)-(2 × 1): A combined experimental and theoretical study - Gokhale, S.; Trischberger, P.; Menzel, Dietrich; Widdra, Wolf; Dröge, H.; Steinrück, Hans-Peter; Birkenheuer, U.; Gutdeutsch, U.; Rösch, Notker (Journal of Chemical Physics, 1998)
Benzene adsorption on a single-domain Si(001)-(2 × 1) surface has been studied by thermal desorption spectroscopy (TPD) and angle-resolved photoelectron spectroscopy (ARUPS) using linearly polarized synchrotron radiation. Angle-resolved photoemission spectra for the saturated benzene layer exhibit well-defined polarization and azimuthal dependencies compatible with a flat-lying benzene molecule with local C symmetry. Based on these results two structure models are proposed. First-principles density functional cluster calculations have been performed for each of these structures. Total energy minimization and a detailed comparison of the experimental ARUPS spectra with the one-particle spectra of the model clusters leads to a 1,4-cyclohexadienelike adsorption complex with a flat-lying benzene molecule which is di-σ bonded to the two dangling bonds of a single Si-Si surface dimer. Especially, one of the unoccupied 1e (π*) orbitals of the free benzene molecule shifts down (by about 3 eV) and evolves into the highest occupied molecular orbital (HOMO) of the chemisorbed molecule. © 1998 American Institute of Physics.

Electronic structure of cyclohexane on Ni(111) - Huber, W.; Zebisch, P.; Bornemann, T.; Steinrück, Hans-Peter (Surface Science, 1990)
Mono- and multilayers of cyclohexane adsorbed on a Ni(111) surface have been studied by angle resolved UV photoelectron spectroscopy (ARUPS) using linearly polarized synchrotron radiation, temperature programmed desorption (TPD) and low energy electron diffraction (LEED). Cyclohexane is molecularly adsorbed on Ni(111) at temperatures below 200 K and desorbs without dehydrogenation. Desorption from the first layer exhibits zeroth-order desorption behavior indicative of desorption from two-dimensional islands. The first layer exhibits a well ordered ( 7 × 7)R19.1° LEED structure starting at coverages of 0.04 ML up to the saturation coverage of 0.143 ML, also indicative of island formation. For cyclohexane in the first layer the binding energies of the various molecular levels are, apart from an overall shift to smaller values by 0.7 eV, within ± 0.1 eV identical to those of condensed cyclohexane. This absence of chemical shifts indicates that there is only very weak (if any) chemical interaction between cyclohexane and the Ni(111) surface. From the normal emission ARUPS spectra and symmetry selection rules we conclude that the symmetry of cyclohexane adsorbed on Ni(111) is lower than C . This is attributed to a slightly inclined adsorption geometry with intramolecular C symmetry of the adsorbed molecules. © 1990.

Electronic structure of HgSe(001) investigated by direct and inverse photoemission - Fink, Rainer; Umbach, Eberhard; Landwehr, G.; et al. (Physical Review B, 2000)
Stimulated by recent photoemission results which suggest a positive fundamental energy gap in HgSe, we have investigated the electronic structure of molecular beam epitaxially grown HgSe(001) c(2X2) layers by a combination of direct ultraviolet photoemission spectroscopy (UPS) and inverse (IPES) photoelectron spectroscopy. Our UPS results do not support the finding of additional peaks above the valence band maximum (VBM) of Gawlik et al. [Phys. Rev. Lett. 78, 3165 (1997)]. A comparison of angle-integrated UPS and IPES spectra and ab initia calculated density of states of HgSe and HgTe demonstrates dissimilar behavior of the two compounds in the dispersion of the conduction bands between 0 and 2 eV above the VBM. Our results are compatible with the common view that HgSe is a semimetal. ©2000 The American Physical Society.
UnivIS-Import:2015-03-06:Pub.2000.nat.dchph.ppc23.electr

Electronic Structure of Magnesia-Ceria Model Catalysts, CO2 Adsorption, and CO2 Activation: A Synchrotron Radiation Photoelectron Spectroscopy Study - Staudt, Thorsten; Lykhach, Yaroslava; Tsud, Nataliya; Skala, Tomas; Prince, Kevin C.; Matolin, Vladimir; Libuda, Jörg (Journal of Physical Chemistry C, 2011)
We have studied the electronic properties of single crystal based ceria and magnesia-ceria model catalysts, the CO2, adsorption, and the CO2-induced reoxidation of these systems by synchrotron radiation photoelectron spectroscopy (SR-PES). All model systems were prepared starting from a fully stoichiometric and well-ordered CeO2(111) film grown on Cu(111). Different magnesia-ceria mixed oxide films were prepared by physical vapor deposition (PVD) of magnesium, oxygen treatment, and subsequent annealing. The preparation procedure was varied to obtain samples with different oxidation state, structure, and surface composition. Different carbon-containing species were identified, including surface carbonates formed in the vicinity of Mg2+ and Ce3+/4+ and surface carboxylates. The presence of Mg2+ was observed to strongly enhance carbonate formation but suppress the formation of carboxylates. Changes in the oxidation state of ceria upon CO2 exposure were monitored with highest sensitivity by resonant photoelectron spectroscopy (RPES). Reoxidation of Ce3+ was observed to be suppressed on magnesia-containing samples, even in the presence of a high surface concentration of Ce3+. The findings suggest that carboxylates are an intermediate step of reoxidation, whereas the generation of stable surface carbonates inhibits formation of this intermediate and, therefore, CO2-induced reoxidation

Electronic Structure of Molecular Magnets - Schmidt, Norman Anja; Graf-Zeiler, Birgit; Scheurer, Andreas; Prakash, Raju; Saalfrank, Rolf; Goering, E.; Fink, Rainer (BESSY Annual Reports 2006, 2006)

Electronic structure, orientation and symmetry of benzene and benzene coadsorbed with CO and NO on NI(111) and RU(001) - Steinrück, Hans-Peter; Heimann, P.A.; Huber, W.; Jakob, P.; Pache, T.; Menzel, Dietrich (Journal of Electron Spectroscopy and Related Phenomena, 1990)
The adsorption of benzene on Ni(111) and Ru(001) was studied by ARUPS using linearly polarized synchrotron radiation for several pure benzene layers and for benzene coadsorbed with CO or NO. On both surfaces the benzene molecules are adsorbed parallel to the surface; the symmetry is reduced to C for Ni(111) and to C for Ru(001), in both cases independent of benzene coverage and the coadsorption of CO or NO. Overall the electronic structure of chemisorbed benzene is very similar for different benzene coverages and coadsorption of CO: only small uniform shifts in the electronic binding energies are observed which are attributed to electrostatic initial state changes. In contrast to CO, coadsorbed NO leads to differential shifts of the benzene molecular levels, indicating some additional changes in bonding. A pronounced maximum in the photoionization cross section of benzene adsorbed on Ni (111) at hstrokeω = 25 eV with the electron emission centered along the surface normal is attributed to a molecular shape resonance into an a final state. © 1990.

Electrons as "Invisible Ink": Fabrication of nanostructures by local electron beam induced activation of SiOx - Walz, Marie-Madeleine; Schirmer, Michael; Vollnhals, Florian; Lukasczyk, Thomas; Steinrück, Hans-Peter; Marbach, Hubertus (Angewandte Chemie International Edition, 2010)
Figure Presented Beam me up: A novel two-step process allows iron nanostructures to be generated locally on SiO/Si at 300 K. The surface is first locally activated by an electron beam. Then the activated structures are exposed to [Fe(CO)], which decomposes and grows autocatalytically to give pure Fe nanocrystals. © 2010 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.

Electron spectroscopic studies of iron and iridium silicides - Probst, Marc; Denecke, Reinhard; Whelan, Caroline; Kinne, Martin; Borgmann, Dieter; Steinrück, Hans-Peter (Surface and Interface Analysis, 2002)
The formation of iron and iridium silicides was studied by means of highly resolved photoelectron spectroscopy of core and valence levels as well as by means of low-energy electron diffraction (LEED). The experiments were carried out at BESSY II in Berlin using synchrotron radiation for the photoemission studies. After evaporation of seven monolayers of Fe on Si(111) at room temperature and annealing to 410 K for 420 s, an ordering of the surface structure and the formation of an (1 × 1) LEED pattern is observed. Upon further heating to 500 K a strong change in both UPS and XPS spectra occurs. This behaviour is attributed to the formation of FeSi (1 ≤ x ≤ 2). After annealing of a thin Ir layer on Si(100) to 1130 K, a p(2 × 2) LEED pattern with respect to the silicon substrate is observed, which indicates the formation of a well-ordered surface compound. Comparison with the literature shows that the formation of an IrSi species is well known, but only an amorphous and a polycrystalline modification have been described upto now.

Electron spectroscopic studies of vapor-deposited Co layers on MoO3 surfaces - Probst, Marc; Voß, Michael; Denecke, Reinhard; Viscido, L.; Heras, José M.; Borgmann, Dieter; Steinrück, Hans-Peter (Journal of Electron Spectroscopy and Related Phenomena, 2001)
The modification of polycrystalline MoO surfaces by vapor-deposited Co atoms was studied by means of X-ray photoelectron spectroscopy (XPS). Thin MoO layers react with evaporated Co atoms already at 90 K. At 300 K this process proceeds with a significantly higher reaction rate. Besides the Mo 3d signal, two new signals are observed in the Mo 3d XP spectra, which are assigned to Mo and Mo. Cobalt is initially oxidized to Co in the surface layer, but with increasing evaporation time the Co intensity steadily increases. During evaporation at a substrate temperature of 800 K, after an initial increase, a steady state of the Mo and Mo intensities develops. Thereafter at a constant evaporation rate no significant variations of the concentrations are detected within the escape depth of the photoelectrons. This behavior is attributed to interdiffusion processes from the surface and interface layers into the bulk. A satisfying fit of the Mo 3d spectra can only be obtained, when an additional Mo species is assumed, which is assigned to a cobalt molybdate.

Electron-vibron coupling in halogenated acenaphthenequinone upon O K-edge soft x-ray absorption - Schmidt, Norman Anja; Clark, Timothy; Urquhart, Stephen G.; Fink, Rainer (Journal of Chemical Physics, 2011)
We present high resolution oxygen K near-edge x-ray absorption spectra of the acenaphthenequinone (ANQ) derivative 3,8-dibromo-5,6-dichloro-ANQ (Br Cl-ANQ). The spectral features exhibit an almost identical vibronic fine structure compared to that shown by ANQ. The unequal distances of the vibronic levels as derived from the least-squares fit analysis of the vibronic progressions allows us to determine the anharmonicity of the excited state potentials involved. We conclude that a single vibrational progression couples to the resonant excitation of O 1s core electrons preferentially. Comparison of the two ANQ derivatives gives a clear indication that the vibronic mode corresponds to a C=O stretching mode, rather than coupling to a C-H mode as suggested previously. These conclusions are supported by density functional theory calculations. © 2011 American Institute of Physics.

Electrospray ionization deposition of ultrathin ionic liquid films: [C 8C1Im]Cl and [C8C1Im][Tf 2N] on Au(111) - Rietzler, Florian; Piermaier, Marius; Deyko, Alexey; Steinrück, Hans-Peter; Maier, Florian (Langmuir, 2014)
We introduce a new method for preparing ultrathin ionic liquid (IL) films on surfaces by means of electrospray ionization deposition (ESID) under ultraclean and well-defined ultra-high-vacuum (UHV) conditions. In contrast to physical vapor deposition (PVD) of ILs under UHV, ESID even allows deposition of ILs, which are prone to thermal decomposition. As proof of concept, we first investigated ultrathin [CCIm][TfN] (=1-methyl-3-octyl imidazolium bis(trifluoromethyl)imide) films on Au(111) by angle-resolved X-ray photoelectron spectroscopy (ARXPS). Films obtained by ESID are found to be virtually identical to films grown by standard PVD. Thereafter, ESID of [CCIm]Cl on Au(111) was studied as a first example of an IL that cannot be prepared as ultrathin film otherwise. [C CIm]Cl forms a wetting layer with a checkerboard arrangement with the cationic imidazolium ring and the chloride anion adsorbed next to each other on the substrate and the alkyl chain pointing toward vacuum. This arrangement within the wetting layer is similar to that observed for [CCIm][TfN], albeit with a higher degree of order of the alkyl chains. Further deposition of [CC Im]Cl leads to a pronounced island growth on top of the wetting layer, which is independently confirmed by ARXPS and atomic force microscopy. This behavior contrasts the growth behavior found for [CC Im][TfN], where layer-by-layer growth on top of the wetting layer is observed. The dramatic difference between both ILs is attributed to differences in the cation-anion interactions and in the degree of order in the wetting layer of the two ILs. © 2014 American Chemical Society.

Employing microspectroscopy to track charge trapping in operating pentacene OFETs - Rösner, Benedikt; Zeilmann, Nina; Schmidt, Ute; Fink, Rainer (Organic Electronics, 2014)
Ultrathin pentacene films resemble benchmark and model materials for organic field-effect transistors (OFETs). We employ scanning transmission X-ray microspectroscopy (STXM) and confocal Raman microspectroscopy as highly resolving probes to obtain insight into the correlation of morphology and charge transport in pentacene OFETs. By combining the operation-induced intensity increase in Raman-active bands with micromorphology, we are able to visualize charge-induced effects, in particular charge trapping in pentacene OFETs during operation. The high sensitivity and specificity of Raman microscopy allows to distinguish between orientation and charge-induced effects and thus to locate the trapped charges at grain boundaries.© 2013 Elsevier B.V. All rights reserved.

Employing x-ray spectromicroscopy for the understanding of anisotropy in organic thin film growth - Hawly, Tim; Späth, Andreas; Johnson, Manuel; Streller, Fabian; Watts, Benjamin; Raabe, Jörg; Fink, Rainer (AIP Conference Proceedings, 2023)
We report on the fabrication of high-quality organic semiconducting thin films from the potent benchmark molecular compounds pentacene and C8-BTBT-C8. For organic films prepared by the floating-lens method, we observe 1D anisotropy in linear NEXAFS dichroism. Based on the molecular orientation contrast in scanning transmission x-ray microspectroscopy (STXM), azimuthal sample rotation and AFM, we can confirm a high degree of long-range molecular order. The experimental results allow for deeper insight into the presumed growth behavior, which appears to crucially depend on the nature, or more specifically, the aromaticity and volatility, of the used solvent.
CRIS-Team Scopus Importer:2023-12-01

Energy and temperature dependent sticking coefficients of CO on ultrathin copper layers on Ru (001) - Kneitz, Stefan; Gemeinhardt, J.; Koschel, Herbert; Held, Georg; Steinrück, Hans-Peter (Surface Science, 1999)
The chemisorption of CO on ultrathin copper layers on Ru(001) has been investigated using a supersonic molecular beam and temperature programmed desorption. We are comparing the adsorption kinetics of CO on clean Ru(001) with those on a pseudomorphic Cu monolayer and a fully relaxed Cu(111) multilayer (>40 layers) on Ru(001). For all three surfaces, a decrease of the initial sticking coefficient, S , with increasing beam energy was observed. For beam energies below 0.3 eV S is highest on the Cu monolayer, even though the binding energy of CO is significantly lower than on Ru(001). For higher energies S scales with the CO binding energy on the different substrates. The dependence of S of a low energy CO beam (0.09 eV) on the copper coverage is consistent with the Stranski-Krastanov growth mode of Cu on Ru(001) that is known from STM measurements. © 1999 Elsevier Science B.V. All rights reserved.

Energy level alignment at zinc blende Cd(Mn)Se/ZnTe/InAs(100) interfaces - Gleim, Thomas; Weinhardt, L.; Schmidt, Th.; Fink, Rainer; Heske, C.; Umbach, E.; Grabs, P.; Schmidt, G.; Molenkamp, L.W.; Richter, B.; Fleszar, A.; Steinrück, Hans-Peter (Applied Physics Letters, 2002)
Experimentally determined band offsets of the CdSe/ZnTe/InAs(100) semiconductor heterostructures were presented. The semimagnetic system showed to behave very similar to the Mn-free model system. A stepwise alignment of the valence bands and in the ZnTe interlayer a 1.1 eV conduction band tunnel barrier were found.

Energy Storage in Strained Organic Molecules: (Spectro)Electrochemical Characterization of Norbornadiene and Quadricyclane - Brummel, Olaf; Besold, Daniel; Döpper, Tibor; Wu, Yanlin; Bochmann, Sebastian; Lazzari, Federica; Waidhas, Fabian; Bauer, Udo; Bachmann, Philipp; Papp, Christian; Steinrück, Hans-Peter; Görling, Andreas; et al. (Chemsuschem, 2016)
We have investigated the electrochemically triggered cycloreversion of quadricyclane (QC) to norbornadiene (NBD), a system that holds the potential to combine both energy storage and conversion in a single molecule. Unambiguous voltammetric traces are obtained for pure NBD and pure QC, the latter a strained polycyclic isomer of the former. The difference in redox potentials is smaller than the energy difference between the neutral molecules. This is owing to a significant energy difference between the corresponding radical cations, as demonstrated by density functional theory (DFT) calculations. The vibrational modes of each pure compound are characterized experimentally in the fingerprint region and identified by DFT methods. Thermal and electrochemical transformations of NBD and QC are monitored insitu by IR spectroelectrochemical methods. The kinetics of the cycloreversion of QC to NBD, which is catalyzed by oxidizing equivalents, can be controlled by an applied electrode potential, which implies the ability to adjust in real time the release of thermal power stored in QC.
Keywords: Infrared spectroscopy; Norbornadiene; Quadricyclane; Spectroelectrochemistry; Voltammetry

Engineering large nanoporous networks with size and shape selected by appropriate precursors - Ceccatto, Alisson; Freiberger, Eva Marie; Waleska-Wellnhofer, Natalie; Jaekel, Simon; Mowbray, Duncan John; Papp, Christian; Steinrück, Hans-Peter; de Siervo, Abner (Carbon, 2024)
Large domains of two-dimensional supramolecular porous nanostructures are interesting for various applications from electronics to biology. Here, we investigate the formation of Cu-coordinated networks on Cu(111) using scanning tunneling microscopy and density functional theory (DFT). We consider two molecules with three pyridyl end groups connected to a central benzene ring by either one or two phenyl groups, namely 1,3,5-tris[4-(pyridin)phenyl]benzene (TPyPB) and 1,3,5-tris[4-(pyridin)-[1,1’-biphenyl]benzene (TPyPPB), respectively. Upon deposition of TPyPB at room temperature, a honeycomb nanostructure forms, which is stabilized by Cu adatoms, as previously seen. Upon deposition at 400 K, the growth dynamics change, and molecules become trapped in the hexagonal pores. In contrast, deposition of TPyPPB at room temperature leads to vitreous structures, which rearrange at 400 K forming a low-defect and extended ordered honeycomb phase, which is also stabilized only in the presence of Cu adatoms. The DFT calculations for both honeycomb phases show an impressive agreement with the experimental results, considering the size of such structures. After annealing at 420 K, a complex flower-like structure composed of a mix of two- and three-fold coordinated Cu centers emerges. Further annealing to above 420 K leads to another new phase composed of a high molecular density motif, the so-called diamond phase.
CRIS-Team Scopus Importer:2024-03-01
Keywords: Cu(111); Metal coordination; Nanoporous organic network; On-surface synthesis; Scanning tunneling microscopy; TPyPB; TPyPPB

Enhanced Activity and Selectivity in Catalytic Methanol Steam Reforming by Basic Alkali Metal Salt Coatings - Kusche, Matthias Manfred; Enzenberger, Florian; Bajus, Stephanie; Niedermeyer, Heiko Jannes; Bösmann, Andreas; Kaftan, Andre; Laurin, Mathias; Libuda, Jörg; Wasserscheid, Peter (Angewandte Chemie International Edition, 2013)
Pt on alumina catalysts can be used for converting methanol and water into hydrogen and carbon dioxide, for applications such as hydrogen storage. Both the activity and selectivity could be enhanced by coating these materials with a thin layer of a molten salt mixture of Li/K/Cs acetate. Potassium doping was indentified by DRIFTS measurements to be an important factor for the boost in catalyst performance.

Enhanced reactivity of Pt nanoparticles supported on ceria thin films during ethylene dehydrogenation - Lykhach, Yaroslava; Staudt, Thorsten; Tsud, Nataliya; Skala, Tomas; Prince, Kevin Charles; Matolin, Vladimir; Libuda, Jörg (Physical Chemistry Chemical Physics, 2011)
The adsorption and reaction of ethylene on Pt/CeO(2-x)/Cu(111) model catalysts were studied by means of high resolution photoelectron spectroscopy (HR-PES) in conjunction with resonant photoemission spectroscopy (RPES). The dehydrogenation mechanism is compared to the HR-PES data obtained on a Pt(111) single crystal under identical conditions. It was found that the Pt nanoparticle system shows a substantially enhanced reactivity and several additional reaction pathways. In sharp contrast to Pt(111), partial dehydrogenation of ethylene on the supported Pt nanoparticles already starts at temperatures as low as 100 K. Similar to the single crystal surface, dehydrogenation occurs via the isomer ethylidene (CHCH(3)) and then mainly via ethylidyne (CCH(3)). In the temperature region between 100 and 250 K there is strong evidence for spillover of hydrocarbon fragments to the ceria support. In addition, splitting of ethylene to C(1) fragments is more facile than on Pt(111), giving rise to the formation of CH species and CO in the temperature region between 250 and 400 K. Upon further annealing, carbonaceous deposits are formed at 450 K. By heating to 700 K, these carbon deposits are completely removed from the surface by reaction with oxygen, provided by reverse spillover of oxygen from the ceria support.

Enrichment effects of ionic liquid mixtures at polarized electrode interfaces monitored by potential screening dagger - Shin, Sunghwan; Greco, Francesco; Maier, Florian; Steinrück, Hans-Peter (Physical Chemistry Chemical Physics, 2021)
The behavior of ionic liquids (ILs) at charged interfaces is pivotal for their application in supercapacitors and electrochemical cells. Recently, we demonstrated for neat ILs that potential screening at polarized electrode interfaces shows a characteristic voltage dependence, as determined in situ by X-ray photoelectron spectroscopy. Herein, we use this fingerprint-type behavior to characterize the nature of the IL/electrode interfaces for IL mixtures of [C(8)C(1)Im][Tf2N] and [C(8)C(1)Im]Cl on Au and Pt electrodes. For Au, the IL/electrode interfaces are dominated by the Cl- anions, even down to a 0.1 mol% [C(8)C(1)Im]Cl content. In contrast, [Tf2N](-) anions enrich at the IL/Pt electrode interfaces down to 10 mol% [C(8)C(1)Im][Tf2N]; only at lower concentrations does a transition to Cl- enrichment occur. These mixture studies demonstrate that even small concentrations of another IL or contamination, e.g. remaining from synthesis, can strongly influence the situation at charged IL interfaces.
CRIS-Team WoS Importer:2021-04-02

Epitaxial Cubic Ce2O3 Films via Ce-CeO2 Interfacial Reaction - Stetsovych, Vitalii; Pagliuca, Federico; Dvorak, Filip; Duchon, Tomas; Vorokhta, Mykhailo; Aulicka, Marie; Lachnitt, Jan; Schernich, Stefan; Matolinova, Iva; Veltruska, Katerina; Skala, Tomas; Mazur, Daniel; et al. (Journal of Physical Chemistry Letters, 2013)
Thin films of reduced ceria supported on metals are often applied as substrates in model studies of the chemical reactivity of ceria based catalysts. Of special interest are the properties of oxygen vacancies in ceria. However, thin films of ceria prepared by established methods become increasingly disordered as the concentration of vacancies increases. Here, we propose an alternative method for preparing ordered reduced ceria films based on the physical vapor deposition and interfacial reaction of Ce with CeO2 films. The method yields bulk-truncated layers of cubic c-Ce2O3. Compared to CeO2 these layers contain 25% of perfectly ordered vacancies in the surface and subsurface allowing well-defined measurements of the properties of ceria in the limit of extreme reduction. Experimentally, c-Ce2O3(111) layers are easily identified by a characteristic 4 x 4 surface reconstruction with respect to CeO2(111). In addition, c-Ce2O3 layers represent an experimental realization of a normally unstable polymorph of Ce2O3. During interfacial reaction, c-Ce2O3 nucleates on the interface between CeO2 buffer and Ce overlayer and is further stabilized most likely by the tetragonal distortion of the ceria layers on Cu. The characteristic kinetics of the metal-oxide interfacial reactions may represent a vehicle for making other metastable oxide structures experimentally available.

Epitaxial Metal Halide Perovskites by Inkjet-Printing on Various Substrates - Sytnyk, Mykhailo; Yousefi-Amin, Amir Abbas; Freund, Tim; Prihoda, Annemarie; Götz, Klaus; Unruh, Tobias; Harreiß, Christina; Will, Johannes; Spiecker, Erdmann; Levchuk, Jevgen; Osvet, Andres; Brabec, Christoph; et al. (Advanced Functional Materials, 2020)
Metal-halide-perovskites revolutionized the field of thin-film semiconductor technology, due to their favorable optoelectronic properties and facile solution processing. Further improvements of perovskite thin-film devices require structural coherence on the atomic scale. Such perfection is achieved by epitaxial growth, a method that is based on the use of high-end deposition chambers. Here epitaxial growth is enabled via a approximate to 1000 times cheaper device, a single nozzle inkjet printer. By printing, single-crystal micro- and nanostructure arrays and crystalline coherent thin films are obtained on selected substrates. The hetero-epitaxial structures of methylammonium PbBr(3)grown on lattice matching substrates exhibit similar luminescence as bulk single crystals, but the crystals phase transitions are shifted to lower temperatures, indicating a structural stabilization due to interfacial lattice anchoring by the substrates. Thus, the inkjet-printing of metal-halide perovskites provides improved material characteristics in a highly economical way, as a future cheap competitor to the high-end semiconductor growth technologies.
CRIS-Team Scopus Importer:2020-09-11
Keywords: epitaxial growth; inkjet printing; metal-halide-perovskites; single-crystal-microstructures

Erratum: "Dual analyzer system for surface analysis dedicated for angle-resolved photoelectron spectroscopy at liquid surfaces and interfaces" [Rev. Sci. Instrum. 87, 045105 (2016) - Niedermaier, Inga; Kolbeck, Claudia; Steinrück, Hans-Peter; Maier, Florian (Review of Scientific Instruments, 2017)
CRIS-Team Scopus Importer:2022-04-14

Erratum: Interaction between silver nanowires and CO on a stepped platinum surface (Journal of Chemisty Physics (2009) 131 (064702)) - Streber, Regine; Tränkenschuh, Barbara; Schöck, Johannes; Papp, Christian; Steinrück, Hans-Peter; Mcewen, J. -S.; Gaspard, P.; Denecke, R. (Journal of Chemical Physics, 2009)

Erratum of: "Jahn-Teller effect of the 2e2g level of chemisorbed benzene", Chem. Phys. Lett. 180 (1991), Nr. 1-2, S. 133-138 - Eiding, J.; Domcke, W.; Huber, W.; Steinrück, Hans-Peter (Chemical Physics Letters, 1991)
UnivIS-Import:2015-03-05:Pub.1991.nat.dchph.lpc2.erratu

Erratum to "advanced thin film technology for ultrahigh resolution X-ray microscopy" [Ultramicroscopy 109 (2009) 1360-1364] (DOI:10.1016/j.ultramic.2009.07.005) - Vila-Comamala, Joan; Jefimovs, Konstantins; Raabe, Joerg; Pilvi, Tero; Fink, Rainer; Senoner, Mathias; Maassdorf, Andre; Ritala, Mikko; David, Christian (Ultramicroscopy, 2010)

Ethene adsorption and dehydrogenation on clean and oxygen precovered Ni(111) studied by high resolution x-ray photoelectron spectroscopy - Lorenz, Michael Peter Andreas; Fuhrmann, Thomas; Streber, R.; Bayer, Andreas; Bebensee, Fabian; Gotterbarm, Karin; Kinne, Martin; Tränkenschuh, Barbara; Zhu, J. F.; Papp, Christian; Denecke, R.; Steinrück, Hans-Peter (Journal of Chemical Physics, 2010)
The adsorption and thermal evolution of ethene (ethylene) on clean and oxygen precovered Ni(111) was investigated with high resolution x-ray photoelectron spectroscopy using synchrotron radiation at BESSY II. The high resolution spectra allow to unequivocally identify the local environment of individual carbon atoms. Upon adsorption at 110 K, ethene adsorbs in a geometry, where the two carbon atoms within the intact ethene molecule occupy nonequivalent sites, most likely hollow and on top; this new result unambiguously solves an old puzzle concerning the adsorption geometry of ethene on Ni(111). On the oxygen precovered surface a different adsorption geometry is found with both carbon atoms occupying equivalent hollow sites. Upon heating ethene on the clean surface, we can confirm the dehydrogenation to ethine (acetylene), which adsorbs in a geometry, where both carbon atoms occupy equivalent sites. On the oxygen precovered surface dehydrogenation of ethene is completely suppressed. For the identification of the adsorbed species and the quantitative analysis the vibrational fine structure of the x-ray photoelectron spectra was analyzed in detail. © 2010 American Institute of Physic

ETHYLENE ADSORBED ON NI(110) - AN EXPERIMENTAL AND THEORETICAL DETERMINATION OF THE 2-DIMENSIONAL BAND-STRUCTURE - Weinelt, M.; Huber, W.; Zebisch, P.; Steinrück, Hans-Peter; Reichert, B.; Birkenheuer, U.; Rösch, Notker (Physical Review B, 1992)

Ethylene: Its adsorption, reaction, and coking on Pt/h-BN/Rh(111) nanocluster arrays - Düll, Fabian; Steinhauer, Johann; Späth, Florian; Bauer, Udo; Bachmann, Philipp; Steinrück, Hans-Peter; Wickert, Sandra; Denecke, Reinhard; Papp, Christian (Journal of Chemical Physics, 2020)
We present well-ordered Pt nanocluster arrays supported on the h-BN/Rh(111) Moiré as a model system for an ethylene dehydrogenation catalyst. Thereby, the h-BN nanomesh serves as a chemically inert eggbox-like template for clusters with a narrow size distribution. The thermal evolution of ethylene is investigated by synchrotron-based high-resolution in situ x-ray photoelectron spectroscopy on the Pt nanoclusters. We compare our results with data on Pt(111) and Pt(355). Interestingly, the Pt nanoclusters and Pt(355) behave very similarly. Both open a new reaction pathway via vinylidene in addition to the route via ethylidyne known for Pt(111). Due to the importance of coking in ethylene dehydrogenation on Pt catalysts, we also studied C2H4 adsorption and decomposition on carbon precovered Pt nanoclusters. While the amount of adsorbed ethylene decreases linearly with the carbon coverage, we found that edge sites are more affected than facet sites and that the vinylidene reaction pathway is effectively suppressed by carbon residues.
CRIS-Team Scopus Importer:2020-06-26

Ethylene oxide on Pt(110) 1×2. A multimethod investigation - Weinelt, M.; Zebisch, P.; Steinrück, Hans-Peter (Chemical Physics, 1993)
The adsorption of ethylene oxide (Et-O) on the reconstructed Pt(110) 1×2 surface has been studied by TPD, LEED, work function measurements, XPS, NEXAFS, and angle-resolved UPS using linearly polarized synchrotron radiation. At temperatures below 120 K Et-O adsorbs in molecular form with a saturation coverage of ≈0.5 monolayers. Upon heating molecular desorption occurs in the temperature range from 140 to 230 K with only minor decomposition (≤0.02 monolayers), as concluded from TPD and XPS. From ARUPS and XPS the existence of two different Et-O species is inferred that are adsorbed at different adsorption sites with different local potential. The molecules are adsorbed with the oxygen end down, as concluded by the strong work function change upon adsorption (ΔΦ=-2.1 eV for the saturated layer). The polarization, polar angle and azimuthal dependence of the ARUPS spectra indicate a preferential orientation of both Et-O species with the CC axis oriented along the [110] direction and the molecular COC plane tilted towards the [001] (or [001]) azimuth. The orientation is, however, not perfect and the symmetry of the adsorption complex is C. The NEXAFS results are consistent with the proposed orientation. A detailed comparison to the results obtained for Et-O on Ni(110) in a previous study is given. © 1993.

Evidence for an active oxygen species on Au/TiO 2(1 1 0) model catalysts during investigation with in situ X-ray photoelectron spectroscopy - Dumbuya, K.; Cabailh, G.; Lazzari, R.; Jupille, J.; Ringel, Lorenz; Pistor, Martina; Lytken, Ole; Steinrück, Hans-Peter; Gottfried, Michael (Catalysis Today, 2012)
The influence of oxygen (O ) and carbon monoxide (CO) on Au nanoparticles supported on TiO (1 1 0) in the size range of 2-3 nm has been studied using X-ray photoelectron spectroscopy (XPS) and in situ (high pressure) XPS at 300 K for O and/or CO pressures of 0.1-1 mbar. These experiments were aimed at revisiting Au 4f core level shifts as reported in the literature and most importantly, to establish the dependence of the core-level shifts on the knowledge that there exists a maximum in reactivity for CO oxidation. Two samples were prepared with a coverage corresponding to that maximum (Au coverage 0.14-0.2 ML, particle size estimated to ∼2-2.5 nm) while a third sample was expected to be less reactive (Au coverage 0.4 ML, particle size estimated to ∼3.3 nm). At elevated O pressures, a new Au 4f component at higher binding energy (2.4-2.6 eV relative to the Au(0) bulk signal) evolved at all particle sizes. Its appearance was attributed to a radiation-induced activation of oxygen and simultaneous oxidation of gold. The activation was much more efficient on the ∼2-2.5 nm particles. The relative intensity of the oxide component depended strongly on O pressure and, thus, on the equilibrium coverage of O . While not present in 0.1 mbar O regardless of exposure time and particle size, it dominated the Au 4f spectrum of particles ∼2-2.5 nm in size at 1 mbar oxygen pressure. This pressure-dependent formation reconciles previously conflicting XPS data. Finally, the activated oxygen species were very reactive toward CO as manifested by the rapid disappearance of the new Au 4f component in a 1:1 mixture of CO and O . The rates of evolution and consumption of this component were found to depend on gold coverage (and thus, particle size) and were highest for the smaller particles. © 2011 Elsevier B.V. All rights reserved.

Evidence for a precursor adcomplex during the metalation of 2HTPP with iron on Ag(100) - Röckert, Michael; Franke, Matthias; Tariq, Quratulain; Steinrück, Hans-Peter; Lytken, Ole (Chemical Physics Letters, 2015)
Using X-ray photoelectron spectroscopy (XPS), we demonstrate that free-base tetraphenylporphyrin (2HTPP) on Ag(1 0 0) forms a theoretically predicted adcomplex with post-deposited iron at 100 K. The formation of the adcomplex, as a precursor for metalation, can be deduced from the N Is spectra showing clearly not-metalated 2HTPP molecules, but with strongly shifted iminic nitrogen peaks, caused by the interaction of the iminic nitrogen atoms with the Fe adatoms. (C) 2015 Elsevier B.V. All rights reserved.

Exceptionally high charge mobility in phthalocyanine-based poly(benzimidazobenzophenanthroline)-ladder-type two-dimensional conjugated polymers - Wang, Mingchao; Fu, Shuai; Petkov, Petko; Fu, Yubin; Zhang, Zhitao; Liu, Yannan; Ma, Ji; Chen, Guangbo; Gali, Sai Manoj; Gao, Lei; Lu, Yang; Paasch, Silvia; et al. (Nature Materials, 2023)
Two-dimensional conjugated polymers (2DCPs), composed of multiple strands of linear conjugated polymers with extended in-plane π-conjugation, are emerging crystalline semiconducting polymers for organic (opto)electronics. They are represented by two-dimensional π-conjugated covalent organic frameworks, which typically suffer from poor π-conjugation and thus low charge carrier mobilities. Here we overcome this limitation by demonstrating two semiconducting phthalocyanine-based poly(benzimidazobenzophenanthroline)-ladder-type 2DCPs (2DCP-MPc, with M = Cu or Ni), which are constructed from octaaminophthalocyaninato metal(ii) and naphthalenetetracarboxylic dianhydride by polycondensation under solvothermal conditions. The 2DCP-MPcs exhibit optical bandgaps of 1.3 eV with highly delocalized π-electrons. Density functional theory calculations unveil strongly dispersive energy bands with small electron–hole reduced effective masses of 0.15m 0 for the layer-stacked 2DCP-MPcs. Terahertz spectroscopy reveals the band transport of Drude-type free carriers in 2DCP-MPcs with exceptionally high sum mobility of electrons and holes of 970 cm2 V−1 s−1 at room temperature, surpassing that of the reported linear conjugated polymers and 2DCPs. This work highlights the critical role of effective conjugation in enhancing the charge transport properties of 2DCPs and the great potential of high-mobility 2DCPs for future (opto)electronics.
CRIS-Team Scopus Importer:2023-06-30

Excitation, deexcitation, and fragmentation in the core region of condensed and adsorbed water - Coulman, D.; Puschmann, A.; Höfer, U.; Steinrück, Hans-Peter; Wurth, W.; Feulner, P.; Menzel, Dietrich (Journal of Chemical Physics, 1990)
Using synchrotron radiation, Auger electron, and H/D -ion yields have been studied at and above the O 1s excitation energies for condensed HO/DO layers of varying thickness, and for two reproducible adsorbate layers (so-called bilayers and monolayers) on Ru(001). Decay electron spectra as well as polarization dependences, angular distributions, and energy distributions of desorbing ions have been investigated. For polarizations with sufficient E component perpendicular to the surface, a sharp peak in the H NEXAFS spectrum is seen for all layers which has no direct counterpart in the Auger NEXAFS spectra, and whose intensity maximizes for E oriented in the detection direction. This observation is interpreted as due to the 1a → 4a core-to-bound transition of the surface molecules whose final state decays electronically and dissociates on comparable time scales. This appears to have the consequence that the symmetry of the coupled excitation is different from that expected for the primary photoabsorption process. There appears also to be an influence of hydrogen bonding on these effects. Similarities and differences between the various layers investigated are also analyzed. © 1990 American Institute of Physics.

Exploring the fabrication and transfer mechanism of metallic nanostructures on carbon nanomembranes via focused electron beam induced processing - Preischl, Christian; Le, Linh Hoang; Bilgilisoy, Elif; Goelzhaeuser, Armin; Marbach, Hubertus (Beilstein Journal of Nanotechnology, 2021)
Focused electron beam-induced processing is a versatile method for the fabrication of metallic nanostructures with arbitrary shape, in particular, on top of two-dimensional (2D) organic materials, such as self-assembled monolayers (SAMs). Two methods, namely electron beam-induced deposition (EBID) and electron beam-induced surface activation (EBISA) are studied with the precursors Fe(CO)(5) and Co(CO)(3)NO on SAMs of 1,1',4',1 ''-terphenyl-4-thiol (TPT). For Co(CO)(3)NO only EBID leads to deposits consisting of cobalt oxide. In the case of Fe(CO)(5) EBID and EBISA yield deposits consisting of iron nanocrystals with high purity. Remarkably, the EBISA process exhibits a strong time dependence, which is analyzed in detail for different electron doses. This time dependence is a new phenomenon, which, to the best of our knowledge, was not reported before. The electron-induced cross-linking of the SAM caused by the cleavage of C-H bonds and the subsequent formation of new C-C bonds between neighboring molecules also seems to play a crucial role in the EBISA process. Previous studies showed that iron nanostructures fabricated on top of a cross-linked SAM on Au/mica can be transferred to solid substrates and grids without any changes, aside from oxidation. Here we demonstrate that iron as well as cobalt oxide structures on top of a cross-linked SAM on Ag/mica do change more significantly. The Fe(NO3)(3) solution used for etching of the Ag layer also dissolves the cobalt oxide structures and causes dissolution and reduction of the iron structures. These results demonstrate that the fabrication of hybrids of metallic nanostructures onto organic 2D materials is an intrinsically complex procedure. The interactions among the metallic deposits, the substrate for the growth of the SAM, and the associated etching/dissolving agent need to be considered and further studied.
CRIS-Team WoS Importer:2021-05-07

Exploring the fabrication of Co and Mn nanostructures with focused soft x-ray beam induced deposition - TU, Fan; Späth, Andreas; Drost, Martin; Vollnhals, Florian; Krick Calderon, Sandra; Fink, Rainer; Marbach, Hubertus (Journal of Vacuum Science & Technology B, Nanotechnology and Microelectronics, 2017)
Focused soft X-ray beam induced deposition of metallic deposits from metal organic precursors is a promising novel technique for additive nanostructure fabrication. In the present work, the authors present a comparative study for deposition and in situ characterization of Co and Mn nanostructures in a scanning transmission x-ray microscope. The authors detect a significant selectivity of the deposition process with respect to the incident photon energy that arises from the enhanced x-ray absorption cross section of the precursor molecules for near-threshold excitation. This effect has been investigated for the L2,3-edges of the respective metal centers of two different precursor molecules as well as the N and O K-edges of the respective ligands. The authors find a photon-limited growth mode for deposition from cobalt tricarbonyl nitrosyl [Co(CO)3NO], while the process is precursor-limited for methylcyclopentadienyl manganese tricarbonyl [MeCpMn(CO)3] possibly due to a comparably low vapor pressure of the latter precursor.
EAM Import::2019-03-14

Exploring the interfacial behavior of ruthenium complexes in ionic liquids: implications for supported ionic liquid phase catalysts - Hemmeter, Daniel; Merlinsky, Luciano Sanchez; Baraldo, Luis M.; Maier, Florian; Williams, Federico J.; Steinrück, Hans-Peter (Physical Chemistry Chemical Physics, 2024)
The interaction of metal complexes with ionic liquids, with a particular focus on the stability and surface concentration of the metal centers, is crucial in applications involving catalysts based on supported ionic liquids. In this study, we synthesized the complexes [Ru(tpy)(bpy)Cl][PF6] and [Ru(tpy)(dcb)Cl][PF6] (tpy = 2,2′,2′′-terpyridine, bpy = 2,2′-bipyridine, dcb = 4,4′-dicarboxy-2,2′-bipyridine) and we prepared solutions using the ionic liquids (ILs) 1-ethyl-3-methylimidazolium acetate [C2C1Im][OAc] and 1-butyl-3-methylimidazolium hexafluorophosphate [C4C1Im][PF6]. The chemical environment of the Ru(ii) metal center and the interfacial behavior of the complexes in the different IL solutions were determined using angle-resolved X-ray photoelectron spectroscopy (ARXPS). In [C4C1Im][PF6], [Ru(tpy)(bpy)Cl][PF6] maintains its chemical structure, while in [C2C1Im][OAc], partial changes in the chemical environment of the Ru center are indicated by XPS, likely due to ligand exchange. The presence of carboxylic acid functional groups in the bipyridyl ligand seems to inhibit this ligand exchange. The investigated complexes do not exhibit surface activity but are depleted from the IL/gas interface. These findings hold significance for the design of new supported ionic liquid phase catalysts based on Ru complexes.
CRIS-Team Scopus Importer:2024-03-01

Exploring the Preparation Dependence of Crystalline 2D-Extended Ultrathin C8-BTBT-C8 Films - Hawly, Tim; Johnson, Manuel; Späth, Andreas; Nickles Jäkel, Hannah; Wu, Mingjian; Spiecker, Erdmann; Watts, Benjamin; Nefedov, Alexei; Fink, Rainer (ACS Applied Materials and Interfaces, 2022)
Crystalline organic semiconducting thin films from the benchmark molecule C8-BTBT-C8 were obtained using physical vapor deposition and various solution-based methods. Utilizing atomic force microscopy and X-ray spectromicroscopy, we illustrate the influence of the underlying growth mechanism and determine the highly preparation-dependent orientation of the thiophene backbone. We observe a continuous trend for crystalline C8-BTBT-C8 thin film domains to extend into the square millimeter-range under near-equilibrium growth conditions. For such well-defined systems, electron diffraction tomography allows us to precisely determine the unit cell directly after film deposition and to reveal an 8° molecular tilt angle with respect to the surface normal. This finding is in almost perfect accordance with the values derived from near-edge X-ray absorption fine structure linear dichroism. Within this work, we shine a light on both the successes and challenges connected to the realization of potent, thiophene-based semiconducting films, paving the way toward square centimeter-sized ultrathin organic crystals and their application in organic circuitry.
CRIS-Team Scopus Importer:2022-04-22
Keywords: 2D nanomaterials; electron tomography; molecular self-assembly; organic semiconductors; organic thin films; X-ray microspectroscopy

Fabrication of layered nanostructures by successive electron beam induced deposition with two precursors: Protective capping of metallic iron structures - Schirmer, Michael; Walz, Marie-Madeleine; Papp, Christian; Kronast, F.; Gray, A.X.; Balke, B.; Cramm, S.; Fadley, C.S.; Steinrück, Hans-Peter; Marbach, Hubertus (Nanotechnology, 2011)
We report on the stepwise generation of layered nanostructures via electron beam induced deposition (EBID) using organometallic precursor molecules in ultra-high vacuum (UHV). In a first step a metallic iron line structure was produced using iron pentacarbonyl; in a second step this nanostructure was then locally capped with a 2-3nm thin titanium oxide-containing film fabricated from titanium tetraisopropoxide. The chemical composition of the deposited layers was analyzed by spatially resolved Auger electron spectroscopy. With spatially resolved x-ray absorption spectroscopy at the Fe L edge, it was demonstrated that the thin capping layer prevents the iron structure from oxidation upon exposure to air. © 2011 IOP Publishing Ltd.

Fabrication of nanoparticulate inks for applications in printable electronics - Reindl, Armin; Aldabergenova, Saule; Altin, Ergün; Frank, Gerhard; Peukert, Wolfgang (4, 2007)
Semiconducting nanoparticles were dispersed systematically in organic solvents using a variety of methods. In the case of silicon particles prepared by gas phase synthesis a high specific energy input is necessary to obtain intrinsically stable suspensions. Therefore Si nanoparticles were dispersed for 24 hours in 1-butanol using a stirred media mill. Via this process intrinsically stable suspensions of Si nanoparticles were produced. The evolution of morphology, particle size and structure was investigated by dynamic light scattering, X-ray diffraction, Raman spectroscopy, and high resolution transmission electron microscopy as a function of dispersing time. The microstructural development with varying crystallite size and crystalline volume fraction was analyzed by Raman spectroscopy and directly confirmed by transmission electron microscopy measurements. The surface chemistry of the Si nanoparticles was analyzed by diffuse reflectance infrared Fourier transform spectroscop
Keywords: Raman spectroscopy; HRTEM; Stirred media mill; Silicon nanoparticles; XRD

Features of hydrogen adsorption on a Ni(997) surface - Karner, H.; Luger, M.; Steinrück, Hans-Peter; Winkler, A.; Rendulic, K.D. (Surface Science, 1985)
The change of the initial sticking coefficient for a Maxwellian beam of hydrogen on Ni(997) has been determined as a function of beam temperature and angle of incidence. At low temperatures adsorption is governed by the steps, at high temperatures adsorption on the terraces is more dominant. Adsorption on the terraces is probably an activated process whereas adsorption on the step sites is non-activated. There seems to be little diffusion of undissociated H between steps and terraces. © 1985.

Few layer 2D pnictogens catalyze the alkylation of soft nucleophiles with esters - Lloret Segura, Vicente Josep; Angel Rivero-Crespo, Miguel; Alejandro Vidal-Moya, Jose; Wild, Stefan; Domenech-Carbo, Antonio; Heller, Bettina; Shin, Sunghwan; Steinrück, Hans-Peter; Maier, Florian; Hauke, Frank; Varela, Maria; Hirsch, Andreas; et al. (Nature Communications, 2019)
Group 15 elements in zero oxidation state (P, As, Sb and Bi), also called pnictogens, are rarely used in catalysis due to the difficulties associated in preparing well-structured and stable materials. Here, we report on the synthesis of highly exfoliated, few layer 2D phosphorene and antimonene in zero oxidation state, suspended in an ionic liquid, with the native atoms ready to interact with external reagents while avoiding aerobic or aqueous decomposition pathways, and on their use as efficient catalysts for the alkylation of nucleophiles with esters. The few layer pnictogen material circumvents the extremely harsh reaction conditions associated to previous superacid-catalyzed alkylations, by enabling an alternative mechanism on surface, protected from the water and air by the ionic liquid. These 2D catalysts allow the alkylation of a variety of acid-sensitive organic molecules and giving synthetic relevancy to the use of simple esters as alkylating agents.
CRIS-Team WoS Importer:2019-02-21

Field-induced modification of the electronic structure in BTBT-based organic thin films observed by NEXAFS spectroscopy - Johnson, Manuel; Hawly, Tim; Zhao, Baolin; Halik, Marcus; Nefedov, A.; Fink, Rainer (Applied Physics Letters, 2022)
We present an in operando near-edge x-ray absorption fine structure (NEXAFS) study on p-type [11-(benzo[b]benzo[4,5]thieno[2,3-d]thiophen-2-yl)dodecyl)] BTBT-based self-assembled monolayer (BTBT-SAM) films. As a 2D-model system, the BTBT-SAM offers direct insight into the active organic semiconductor layer without interfering bulk materials. This allows for the observation of polaronic states caused by charged species at the dielectric/organic interface. Linear NEXAFS dichroism is employed to derive the molecular orientation of the BTBT subunit. Field-induced modifications in the unoccupied molecular orbitals are observed in the NEXAFS spectra. The spectral changes in the on- and off-states are discussed in the context of polaron formation due to charge accumulation induced by the applied electric field. Published under an exclusive license by AIP Publishing.
CRIS-Team WoS Importer:2022-12-02

First experimental determination of an adsorption site using multiple wave number photoelectron diffraction patterns - Zharnikov, M.; Weinelt, M.; Zebisch, P.; Stichler, M.; Steinrück, Hans-Peter (Physical Review Letters, 1994)
Angular distributions of S2p32 photoelectrons were measured for Ni(111)-p(2×2)S at seven kinetic energies between 130 and 322.5 eV. Using these data, the real space structure around the emitter is reconstructed using the multiple wave number phased-sum algorithm. The reconstructed images allow the unequivocal identification of the fcc adsorption site, with a distance from the S atoms to the top Ni layer of 1.6. This is, to our knowledge, the first example wherein the multiple wave number phased-sum method has successfully been applied to determine an adsorption site from experimental data. © 1994 The American Physical Society.

Focused electron beam based direct-write fabrication of graphene and amorphous carbon from oxo-functionalized graphene on silicon dioxide - Schindler, Severin; Vollnhals, Florian; Halbig, Christian Eberhard; Marbach, Hubertus; Steinrück, Hans-Peter; Papp, Christian; Eigler, Siegfried (Physical Chemistry Chemical Physics, 2017)
Controlled patterning of graphene is an important task towards device fabrication and thus is the focus of current research activities. Graphene oxide (GO) is a solution-processible precursor of graphene. It can be patterned by thermal processing. However, thermal processing of GO leads to decomposition and CO2 formation. Alternatively, focused electron beam induced processing (FEBIP) techniques can be used to pattern graphene with high spatial resolution. Based on this approach, we explore FEBIP of GO deposited on SiO2. Using oxo-functionalized graphene (oxo-G) with an in-plane lattice defect density of 1% we are able to image the electron beam-induced effects by scanning Raman microscopy for the first time. Depending on electron energy (2-30 keV) and doses (50-800 mC m(-2)) either reduction of GO or formation of permanent lattice defects occurs. This result reflects a step towards controlled FEBIP processing of oxo-G.

Formation and Surface Behavior of Pt and Pd Complexes with Ligand Systems Derived from Nitrile-functionalized Ionic Liquids Studied by XPS - Hemmeter, Daniel; Paap, Ulrike; Taccardi, Nicola; Mehler, Julian; Schulz, Peter; Wasserscheid, Peter; Maier, Florian; Steinrück, Hans-Peter (ChemPhysChem, 2022)
We studied the formation and surface behavior of Pt(II) and Pd(II) complexes with ligand systems derived from two nitrile-functionalized ionic liquids (ILs) in solution using angle-resolved X-ray photoelectron spectroscopy (ARXPS). These ligand systems enabled a high solubility of the metal complexes in IL solution. The complexes were prepared by simple ligand substitution under vacuum conditions in defined excess of the coordinating ILs, [C3CNC1Im][Tf2N] and [C1CNC1Pip][Tf2N], to immediately yield solutions of the final products. The ILs differ in the cationic head group and the chain length of the functionalized substituent. Our XPS measurements on the neat ILs gave insights in the electronic properties of the coordinating substituents revealing differences in donation capability and stability of the complexes. Investigations on the composition of the outermost surface layers using ARXPS revealed no surface affinity of the nitrile-functionalized chains in the neat ILs. Solutions of the formed complexes in the nitrile ILs showed homogeneous distribution of the solute at the surface with the heterocyclic moieties preferentially orientated towards the vacuum, while the metal centers are rather located further away from the IL/vacuum interface.
CRIS-Team Scopus Importer:2022-10-28
Keywords: catalysis; ionic liquids; organometallic chemistry; surface science; X-ray photoelectron spectroscopy

Formation of a new type of chromium oxide by deposition of chromium onto water precovered Cu(1 1 1) - Pantförder, Jörg; Domnick, Ralph; Ammon, Christian; Held, Georg; Steinrück, Hans-Peter (Surface Science, 2001)
Thin chromiumoxide layers (Θ up to 10 ML) on Cu(1 1 1) were produced by evaporating chromium onto multilayers of water (DO) at 120 K. Their composition and structure were studied by X-ray photoelectron spectroscopy, low-energy electron diffraction and temperature programmed desorption. Annealing the sample to 750 K leads to a new type of chromium oxide CrO with a square two-dimensional lattice and a lattice constant of 2.70 Å. It is stable upon heating up to 950 K. Further oxidation of this oxide layer in an oxygen atmosphere of 10 mbar leads to the formation of α-CrO oriented with its hexagonal (0 0 0 1) plane parallel to the surface. Adsorption/desorption experiments show that the square oxide surface is essentially unable to adsorb CO at 90 K which is in contrast to the hexagonal α-CrO surface. © 2001 Elsevier Science B.V.

Formation of Cubic Ice via Clathrate Hydrate, Prepared in Ultrahigh Vacuum under Cryogenic Conditions - Ghosh, Jyotirmoy; Bhuin, Radha Gobinda; Vishwakarma, Gaurav; Pradeep, Thalappil (Journal of Physical Chemistry Letters, 2019)
Cubic ice (ice Ic) is a crystalline phase of solid water, which exists in the earth's atmosphere and extraterrestrial environments. We provide experimental evidence that dissociation of acetone clathrate hydrate (CH) makes ice Ic in ultrahigh vacuum (UHV) at 130-135 K. In this process, we find that crystallization of ice Ic occurs below its normal crystallization temperature. Time-dependent reflection absorption infrared spectroscopy (RAIRS) and reflection high-energy electron diffraction (RHEED) were utilized to confirm the formation of ice Ic. Associated crystallization kinetics and activation energy (Ea) for the process were evaluated. We suggest that enhanced mobility or diffusion of water molecules during acetone hydrate dissociation enabled crystallization. Moreover, this finding implied that CHs might exist in extreme low-pressure environments present in comets. These hydrates, subjected to prolonged thermal annealing, transform into ice Ic. This unique process of crystallization hints at a possible mechanistic route for the formation of ice Ic in comets.
CRIS-Team Scopus Importer:2019-12-31

Formation of highly ordered molecular porous 2D networks from cyano-functionalized porphyrins on Cu(111) - Steinrück, Hans-Peter; Adhikari, Rajan; Siglreithmaier, Gretel; Gurrath, Martin; Meusel, Manuel; Kuliga, Jan; Lepper, Michael; Hölzel, Helen; Jux, Norbert; Meyer, Bernd; Marbach, Hubertus (Chemistry - A European Journal, 2020)
We investigated the adsorption of three related cyano-functionalized tetraphenyl porphyrin derivatives on Cu(111) by scanning tunneling microscopy (STM) in ultra-high vacuum (UHV) with the goal to identify the role of the cyano group and the central Cu atom for the intermolecular and supramolecular arrangement. The porphyrin derivatives studied were Cu-TCNPP, Cu-cisDCNPP, and 2H-cisDCNPP, that is, Cu-5,10,15,20-tetrakis-(p-cyano)-phenyl-porphyrin, Cu-meso-cis-di(p-cyano)-phenyl-porphyrin and 2H-meso-cis-di(p-cyano)-phenyl-porphyrin, respectively. Starting from different structures obtained after deposition at room temperature, all three molecules form the same long-range ordered hexagonal honeycomb-type structure with triangular pores and three molecules per unit cell. For the metal-free 2H-cisDCNPP, this occurs only after self-metalation upon heating. The structure-forming elements are pores with a distance of 3.1 nm, formed by triangles of porphyrins fused together by cyano-Cu-cyano interactions with Cu adatoms. This finding leads us to suggest that two cyano-phenyl groups in the "cis" position is the minimum prerequisite to form a highly ordered 2D porous molecular pattern. The experimental findings are supported by detailed density functional theory calculations to analyze the driving forces that lead to the formation of the porous hexagonal honeycomb-type structure.
CRIS-Team Scopus Importer:2020-07-03
Keywords: porphyrins coordinated networks cyano functionalization scanning tunneling microscopy (STM) density-functional theory (DFT) calculations

Formation of interface and surface oxides on supported Pd nanoparticles - Libuda, Jörg; et al. (Surface Science, 2006)
We have quantitatively studied the interaction between oxygen and an Fe3O4-supported Pd model catalyst by molecular beam (MB) methods, time resolved IR reflection absorption spectroscopy (TR-IRAS) and photoelectron spectroscopy (PES) using synchrotron radiation. The well-shaped Pd particles were prepared in situ by metal evaporation and growth under ultrahigh vacuum (UHV) conditions on a well-ordered Fe3O4 film on Pt(1 1 1). It is found that for oxidation temperatures up to 450 K oxygen predominantly chemisorbs on metallic Pd whereas at 500 K and above (∼10-6 mbar effective oxygen pressure) large amounts of Pd oxide are formed. These Pd oxide species preferentially form a thin layer at the particle/support interface, stabilized by the iron-oxide support. Their formation and reduction is fully reversible. Upon decomposition, oxygen is released which migrates back onto the metallic part of the Pd surface. In consequence, the Pd interface oxide layer acts as an oxygen reservoir, the capacity of which by far exceeds the amount of chemisorbed oxygen on the metallic surface. Additionally, Pd surface oxides can also be formed at temperatures above 500 K. The extent of surface oxide formation critically depends on the oxidation temperature. This effect is addressed to different onset temperatures for oxidation of the particle facets and sites. It is shown that the presence of Pd surface oxides sensitively modifies the adsorption and reaction properties of the model catalyst, i.e. by lowering the CO adsorption energy and CO oxidation probability. Still, a complete reduction of the Pd surface oxides can be obtained by extended CO exposure, fully reestablishing the metallic Pd surface. © 2006 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2006.nat.dchph.ppc20.format
Keywords: CO; IR reflection absorption spectroscopy; Iron-oxide; Model catalyst; Molecular beam; Oxidation; Palladium; Photoelectron spectroscopy; Surface oxide

Formation of the calcium/poly(3-hexylthiophene) interface: Structure and energetics - Zhu, Junfa; Bebensee, Fabian; Hieringer, Wolfgang; Zhao, Wei; Baricuatro, J. H.; Farmer, Jason A.; Bai, Yun; Steinrück, Hans-Peter; Gottfried, Michael; Campbell, C. T. (Journal of the American Chemical Society, 2009)
The adsorption of Ca on poly(3-hexylthiophene) (P3HT) has been studied by adsorption microcalorimetry, atomic beam/surface scattering, X-ray photoelectron spectroscopy (XPS), low-energy He ion scattering spectroscopy (LEIS), and first-principles calculations. The sticking probability of Ca on P3HT is initially 0.35 and increases to almost unity by 5 ML. A very high initial heat of adsorption in the first 0.02 ML (625-500 kJ/mol) is attributed to the reaction of Ca with defect sites or residual contamination. Between 0.1 and 0.5 ML, there is a high and nearly constant heat of adsorption of 405 kJ/mol, which we ascribe to Ca reacting with subsurface sulfur atoms from the thiophene rings of the polymer. This is supported by the absence of LEIS signal for Ca and the shift of the S 2p XPS binding energy by -2.8 eV for reacted S atoms. The heat of adsorption decreases above 0.6 ML coverage, reaching the sublimation enthalpy of Ca, 178 kJ/mol, by 4 ML. This is attributed to the formation of Ca nanoparticles and eventually a continuous solid Ca film, on top of the polymer. LEIS and XPS measurements, which show only a slow increase of the signals related to solid Ca, support this model. Incoming Ca atoms are subject to a kinetic competition between diffusing into the polymer to react with subsurface thiophene units versus forming or adding to three-dimensional Ca clusters on the surface. At ∼1.6 ML Ca coverage, Ca atoms have similar probabilities for either process, with the former dominating at lower coverage. Ultimately about 1.6 ML of Ca (1.2 x 10 atoms/cm) reacts with S atoms, corresponding to a reacted depth of ∼3 nm, or nearly five monomerunit layers. Density-functional theory calculations confirm that the heat of reaction and the shift of the S 2p signal are consistent with Ca abstracting S from the thiophene rings to form small CaS clusters. © 2009 American Chemical Society.

Formation of the ZnSe/(Te/)GaAs( 1 0 0 ) heterojunction - Gleim, Thomas; Heske, C.; Umbach, E.; Schumacher, C.; Gundel, S.; Faschinger, W.; Fleszar, A.; Ammon, Christian; Probst, Marc; Steinrück, Hans-Peter (Surface Science, 2003)
We have investigated the underlying electronic and structural effects of the previously published influence of a Te substrate pretreatment on the heterovalent ZnSe/GaAs(100) interface [Appl. Phys. Lett. 78 (2001) 1867]. For this purpose, photoelectron spectroscopy and density functional theory calculations were employed. To determine the valence band maximum accurately, the choice of suitable photon energies to maximize the contribution from the Γ-point as well as a variation of the k-vector by measuring under selected angles is investigated. We discuss the resulting band offsets with respect to the atomic interface structure and to the broadening of core level line shapes. The theoretical investigations focus on the effect of replacing Se by Te atoms at the interface, particularly in view of the lattice structure and the band offsets. We find that Te helps to establish a group-VI-rich interface, thus lowering the valence band offset, while maintaining a good crystal quality by acting as a diffusion barrier for Se atoms. © 2003 Elsevier Science B.V. All rights reserved.

Fossil biomass preserved as graphitic carbon in a late paleoproterozoic banded iron formation metamorphosed at more than 550°C - Papineau, Dominic; De Gregorio, Bradley T.; Sagar, James; Thorogate, Richard; Wang, Jianhua; Nittler, Larry; Kilcoyne, David A.; Marbach, Hubertus; Drost, Martin; Thornton, Geoff (Journal of the Geological Society, 2019)
Metamorphism is thought to destroy microfossils, partly through devolatilization and graphitization of biogenic organic matter. However, the extent to which there is a loss of molecular, elemental and isotope signatures from biomass during high-temperature metamorphism is not clearly established. We report on graphitic structures inside and coating apatite grains from the c. 1850 Ma Michigamme silicate banded iron formation from Michigan, metamorphosed above 550°C. Traces of N, S, O, H, Ca and Fe are preserved in this graphitic carbon and X-ray spectra show traces of aliphatic groups. Graphitic carbon has an expanded lattice around 3.6 Å, forms microscopic concentrically-layered and radiating polygonal flakes and has homogeneous δ13C values around −22‰, identical to bulk analyses. Graphitic carbon inside apatite is associated with nanometre-size ammoniated phyllosilicate. Precursors of these metamorphic minerals and graphitic carbon originated from ferruginous clayrich sediments with biomass. We conclude that graphite coatings and inclusions in apatite grains indicate fluid remobilization during amphibolite-facies metamorphism of precursor biomass. This new evidence fills in observational gaps of metamorphosed biomass into graphite and supports the existence of biosignatures in the highly metamorphosed iron formation from the Eoarchean Akilia Association, which dates from the beginning of the sedimentary rock record.
CRIS-Team Scopus Importer:2019-07-16

From 2D STXM to 3D Imaging: Soft X-ray Laminography of Thin Specimens - Witte, Katharina; Späth, Andreas; Finizio, Simone; Donnelly, Claire; Watts, Benjamin; Sarafimov, Blagoj; Odstrcil, Michal; Guizar-Sicairos, Manuel; Holler, Mirko; Fink, Rainer; Raabe, Jörg (Nano Letters, 2020)
X-ray tomography has become an indispensable tool for studying complex 3D interior structures with high spatial resolution. Three-dimensional imaging using soft X-rays offers powerful contrast mechanisms but has seen limited success with tomography due to the restrictions imposed by the much lower energy of the probe beam. The generalized geometry of laminography, characterized by a tilted axis of rotation, provides nm-scale 3D resolution for the investigation of extended (mm range) but thin (μm to nm) samples that are well suited to soft X-ray studies. This work reports on the implementation of soft X-ray laminography (SoXL) at the scanning transmission X-ray spectromicroscope of the PolLux beamline at the Swiss Light Source, Paul Scherrer Institut, which enables 3D imaging of extended specimens from 270 to 1500 eV. Soft X-ray imaging provides contrast mechanisms for both chemical sensitivity to molecular bonds and oxidation states and magnetic dichroism due to the much stronger attenuation of X-rays in this energy range. The presented examples of applications range from functionalized nanomaterials to biological photonic crystals and sophisticated nanoscaled magnetic domain patterns, thus illustrating the wide fields of research that can benefit from SoXL.
CRIS-Team Scopus Importer:2020-02-21
Keywords: 3D imaging; flat and extended specimens; laminography; soft X-rays; X-ray microscopy

From Flat Surfaces to Nanoparticles: In Situ Studies of the Reactivity of Model Catalysts - Papp, Christian (Catalysis Letters, 2017)
This perspective summarizes results of in situ adsorption and reaction experiments on graphene-supported nanoparticles: the particular aim is to point out similarities and differences between studies on ``traditional'' single crystal studies and the more complex, more realistic nanoparticles. It is shown that the use of quantitative X-ray photoelectron spectroscopy allows for gaining a detailed insight even into these complex systems, thereby facilitating a further step into bridging the materials gap from fundamental science to applied sciences. The use of graphene as a substrate gives intriguing new possibilities, as the template effect of graphene can lead to a very narrow size distribution of the clusters, while graphene itself is chemically innocent, thereby making side processes such as spill over and reverse spill over less likely. The systems discussed range from extremely well studied systems such as the adsorption and reaction of CO on a Pt(111) surface, to stepped surfaces and finally to nanocluster arrays supported on a graphene support. Also, the important chemistry of sulfur, being a strong catalyst poison, on such systems will be discussed. While the adsorption behavior on nanoclusters is strongly reminiscent of the adsorption on stepped surfaces, a strong increase in the reactivity of nanoparticles systems is found.
EAM Import::2019-03-14

Functionalization of oxide surfaces through reaction with 1,3-dialkylimidazolium ionic liquids - Schernich, Stefan; Laurin, Mathias; Lykhach, Yaroslava; Steinrück, Hans-Peter; Tsud, Nataliya; Skala, Tomas; Prince, Kevin C.; Taccardi, Nicola; Matolin, Vladimir; Wasserscheid, Peter; Libuda, Jörg (Journal of Physical Chemistry Letters, 2013)
Practical applications of ionic liquids (ILs) often involve IL/oxide interfaces, but little is known regarding their interfacial chemistry. The unusual physicochemical properties of ILs, including their exceptionally low vapor pressure, provide access to such interfaces using a surface science approach in ultrahigh vacuum (UHV). We have applied synchrotron radiation photoelectron spectroscopy (SR-PES) to the study of a thin film of the ionic liquid [CCIm][TfN] prepared in situ in UHV on ordered stoichiometric CeO(111) and partially reduced CeO . On the partially reduced surface, we mostly observe decomposition of the anion. On the stoichiometric CeO(111) surface, however, a layer of surface-anchored organic products with high thermal stability is formed upon reaction of the cation. The suggested acid-base reaction pathway may provide well-defined functionalized IL/solid interfaces on basic oxides. © 2012 American Chemical Society.

Functionalized Porphyrins on an Atomically Defined Oxide Surface: Anchoring and Coverage-Dependent Reorientation of MCTPP on Co3O4(111) - Werner, Kristin; Mohr, Susanne; Schwarz, Matthias; Xu, Tao; Amende, Maximilian; Döpper, Tibor; Görling, Andreas; Libuda, Jörg (Journal of Physical Chemistry Letters, 2016)
We have studied the adsorption of tetraphenylporphyrin (2HTPP) and its carboxylated counterpart mono-para-carboxyphenyltriphenylporphyrin (MCTPP) on an atomically defined CoO(111) film under ultrahigh vacuum (UHV) conditions. Using time-resolved infrared reflection absorption spectroscopy (TR-IRAS), we show that 2HTPP adsorbs molecularly in a flat-lying orientation, whereas MCTPP binds to the surface via formation of a chelating bidentate carboxylate upon deposition at 400 K. Combining TR-IRAS and density-functional theory (DFT), we determine the molecular tilting angle as a function of coverage. We show that the MCTPP adsorption geometry changes from a nearly flat-lying orientation (tilting angle <30°) at low coverage to a nearly perfectly upright-standing orientation (tilting angle of approximately 80°) in the full monolayer.

Functional nickel complexes of N-heterocyclic carbene ligands in pre-organized and supported thin film materials - Wang, Xinjiao; Sobota, Marek; Kohler, Florian; Morain, Bruno; Melcher, Berthold Ulrich; Laurin, Mathias; Wasserscheid, Peter; Libuda, Jörg; Meyer, Karsten (Journal of Materials Chemistry, 2012)
Nickel(ii) complexes with double alkyl chain functionalized N-heterocyclic carbene (NHC) ligands, [NiCl (C MIM) ] and [NiCl (C C IM) ], where C MIM = 1-dodecyl-3-methylimidazolin-2-ylidene (1) and C C IM = 1,3-didodecylimidazolin-2-ylidene (2), have been prepared and fully characterized by H NMR, C NMR, and CHN elemental analyses. Furthermore, we have developed a system, in which double long alkyl chain derivatized Ni-NHC complexes are dissolved in the related ionic liquid crystalline 1,3-didodecylimidazolium tetrafluoroborate, [C C IM][BF ], to form pre-organized structures for enhanced reactivity. Remarkably, differential scanning calorimetry, polarized optical microscopy, and temperature-programmed IR reflection absorption spectroscopy performed on a mixture of 10 wt% Ni complexes in [C C IM][BF ] demonstrate that this system retains an ionic liquid crystalline phase; even after immobilization onto a silica-100 support with pore filling α = 1. © 2012 The Royal Society of Chemistry.

Gallium-rich Pd-Ga phases as supported liquid metal catalysts - Taccardi, Nicola; Grabau, Mathias; Debuschewitz, Jonas; Distaso, Monica; Brandl, Marco; Hock, Rainer; Maier, Florian; Papp, Christian; Erhard, Jannis; Neiß, Christian; Peukert, Wolfgang; Görling, Andreas; et al. (Nature chemistry, 2017)
A strategy to develop improved catalysts is to create systems that merge the advantages of heterogeneous and molecular catalysis. One such system involves supported liquid-phase catalysts, which feature a molecularly defined, catalytically active liquid film/droplet layer adsorbed on a porous solid support. In the past decade, this concept has also been extended to supported ionic liquid-phase catalysts. Here we develop this idea further and describe supported catalytically active liquid metal solutions (SCALMS). We report a liquid mixture of gallium and palladium deposited on porous glass that forms an active catalyst for alkane dehydrogenation that is resistant to coke formation and is thus highly stable. X-ray diffraction and X-ray photoelectron spectroscopy, supported by theoretical calculations, confirm the liquid state of the catalytic phase under the reaction conditions. Unlike traditional heterogeneous catalysts, the supported liquid metal reported here is highly dynamic and catalysis does not proceed at the surface of the metal nanoparticles, but presumably at homogeneously distributed metal atoms at the surface of a liquid metallic phas

General and selective deoxygenation by hydrogen using a reusable earth-abundant metal catalyst - Schwob, T.; Kunnas, P.; De Jonge, Niels; Papp, Christian; Steinrück, Hans-Peter; Kempe, Rhett (Science Advances, 2019)
Chemoselective deoxygenation by hydrogen is particularly challenging but crucial for an efficient late-stage modification of functionality-laden fine chemicals, natural products, or pharmaceuticals and the economic upgrading of biomass-derived molecules into fuels and chemicals. We report here on a reusable earth-abundant metal catalyst that permits highly chemoselective deoxygenation using inexpensive hydrogen gas. Primary, secondary, and tertiary alcohols as well as alkyl and aryl ketones and aldehydes can be selectively deoxygenated, even when part of complex natural products, pharmaceuticals, or biomass-derived platform molecules. The catalyst tolerates many functional groups including hydrogenation-sensitive examples. It is efficient, easy to handle, and conveniently synthesized from a specific bimetallic coordination compound and commercially available charcoal. Selective, sustainable, and cost-efficient deoxygenation under industrially viable conditions seems feasible.
CRIS-Team Scopus Importer:2021-04-20

General Synthesis of Alkyl Amines via Borrowing Hydrogen and Reductive Amination - Elfinger, Matthias; Bauer, Christof; Schmauch, Jörg; Moritz, Michael; Wichmann, Christoph; Papp, Christian; Kempe, Rhett (dvanced Synthesis & Catalysis, 2023)
Amines are a very important class of compounds and the selective synthesis of differently substituted primary, secondary and tertiary alkyl amines is challenging. Here we present the synthesis of primary, secondary, and tertiary alkyl amines from ammonia and alcohols, aldehydes, ketones and hydrogen by combining borrowing hydrogen or hydrogen autotransfer and reductive amination with hydrogen. The key is a nanostructured, bimetallic Co/Sc catalyst able to mediate both reactions or concepts efficiently. We observe a broad product scope, a very good functional group tolerance, upscaling is easily accomplished and our catalyst is reusable.
CRIS-Team Scopus Importer:2023-12-01
Keywords: amines; borrowing hydrogen; cobalt; reductive amination; scandium

Generation of clean iron nanocrystals on an ultra-thin SiO x film on Si(001) - Walz, Marie-Madeleine; Vollnhals, Florian; Schirmer, Michael; Steinrück, Hans-Peter; Marbach, Hubertus (Physical Chemistry Chemical Physics, 2011)
Upon exposure to Fe(CO) , the formation of pure cubic Fe nanocrystals with dimensions up to ∼75 nm is reported on ultra-thin SiO films (thickness ≈ 0.5 nm) on Si(001), which have been prepared in situ under UHV conditions. The active centers for initial decomposition of Fe(CO) resulting in the growth of the Fe clusters are proposed to be SiO sites. After nucleation at these sites, further crystal growth is observed due to autocatalytic dissociation of Fe(CO) at room temperature. The density of the Fe clusters can be increased by irradiating the surface with a focused electron beam (15 keV) prior to gas exposure. The formation of the active SiO sites upon electron irradiation is attributed to oxygen desorption via the Knotek-Feibelman mechanism. © 2011 the Owner Societies.

Generation of clean iron structures by electron-beam-induced deposition and selective catalytic decomposition of iron pentacarbonyl on Rh(110) - Lukasczyk, Thomas; Schirmer, Michael; Steinrück, Hans-Peter; Marbach, Hubertus (Langmuir, 2009)
We explore the electron-beam-induced deposition (EBID) of iron pentacarbonyl, Fe(CO)5, in ultrahigh vacuum (UHV) on clean and modified Rh(110) surfaces by scanning electron microscopy (SEM), scanning Auger microscopy (SAM), and local Auger electron spectroscopy (AES). In EBID a highly focused electron beam is used to locally decompose the iron pentacarbonyl precursor molecules with the goal to generate pure iron nanostructures. It is demonstrated that the selectivity of the process strongly depends on the surface properties. On a perfect, clean Rh(110) surface almost no selectivity is observed; i.e., deposition of Fe is found on irradiated and nonirradiated surface regions due to catalytic decomposition of the Fe(CO)5. However, on a structurally nonperfect Rh(110) surface and on a Tiprecovered Rh(110) surface high selectivity is found; i.e., Fe deposits are primarily formed in irradiated regions. The role of catalytic and autocatalytic growth of iron on clean Rh respective iron deposits is discussed. The purity of the Fe deposits was always very high (>88%). It is demonstrated that the deposited Fe structures can be selectively oxidized to iron oxide by exposure to oxygen. Furthermore, attempts to write Fe line deposits were also successful, and line diameters smaller than 25 nm could be achieved. © 2009 American Chemical Society.

Geometrische Optik am Computer - Girwidz, Raimund; Schmidt, Jörg; Steinrück, Hans-Peter (Physik in unserer Zeit, 1999)
Strahlenverlaufsberechnungen werden heute praktisch nur noch am Computer durchgeführt. Dies ersetzt aufwendige Rechentechniken, und die physikalischen Ergebnisse rücken stärker in den Vordergrund. Das Programmpaket GOPTIK, das auf unserer Homepage abrufbar ist, kombiniert Computerprogramme mit Textinformationen.
UnivIS-Import:2015-03-05:Pub.1999.nat.dchph.lpc2.geomet

Geometry of the (2x1) reconstruction of diamond(111) - Heinz, Klaus; Maier, Florian; Ristein, Jürgen; Ley, Lothar; et al. (Journal of Physics: Condensed Matter, 2002)
UnivIS-Import:2015-04-14:Pub.2002.nat.dchph.lpc2._geome

Gluing Ionic Liquids to Oxide Surfaces: Chemical Anchoring of Functionalized Ionic Liquids by Vapor Deposition onto Cobalt(II) Oxide - Xu, Tao; Wähler, Tobias; Vecchietti, Julia; Bonivardi, Adrian; Bauer, Tanja; Schwegler, Johannes; Schulz, Peter; Wasserscheid, Peter; Libuda, Jörg (Angewandte Chemie International Edition, 2017)
Ionic liquids (IL) hold a great potential as novel electrolytes for applications in electronic materials and energy technology. The functionality of ILs in these applications relies on their interface to semiconducting nanomaterials. Therefore, methods to control the chemistry and structure of this interface are the key to assemble new IL-based electronic and electrochemical materials. Here, we present a new method to prepare a chemically well-defined interface between an oxide and an IL film. An imidazolium-based IL, which is carrying an ester group, is deposited onto cobalt oxide surface by evaporation. The IL binds covalently to the surface by thermally activated cleavage of the ester group and formation of a bridging carboxylate. The anchoring reaction shows high structure sensitivity, which implies that the IL film can be adhered selectively to specific oxide surfaces.
Keywords: chemical anchoring; cobalt oxide; ester functionalization; ionic liquids; vapor deposition

Gluing ionic liquids to oxide surfaces: Chemical anchoring of functionalized ionic liquids by vapor deposition onto cobalt(II) oxide // Gluing Ionic Liquids to Oxide Surfaces: Chemical Anchoring of Functionalized Ionic Liquids by Vapor Deposition onto Cobalt(II) Oxide - Xu, Tao; Wähler, Tobias; Vecchietti, Ph. D. Maria Julia; Bauer, Tanja; Schwegler, Johannes; Schulz, Peter; Wasserscheid, Peter; Libuda, Jörg (Angewandte Chemie, 2017)
Ionic liquids (IL) hold a great potential as novel electrolytes for applications in electronic materials and energy technology. The functionality of ILs in these applications relies on their interface to semiconducting nanomaterials. Therefore, methods to control the chemistry and structure of this interface are the key to assemble new IL-based electronic and electrochemical materials. Here, we present a new method to prepare a chemically well-defined interface between an oxide and an IL film. An imidazolium-based IL, which is carrying an ester group, is deposited onto cobalt oxide surface by evaporation. The IL binds covalently to the surface by thermally activated cleavage of the ester group and formation of a bridging carboxylate. The anchoring reaction shows high structure sensitivity, which implies that the IL film can be ``glued'' selectively specific oxide surfaces.
EAM Import::2019-03-13

Gold intercalation of boron-doped graphene on Ni(111): XPS and DFT study - Zhao, Wei; Gebhardt, Julian; Gotterbarm, Karin; Höfert, Oliver; Gleichweit, Christoph; Papp, Christian; Görling, Andreas; Steinrück, Hans-Peter (Journal of Physics: Condensed Matter, 2013)
The intercalation of a graphene layer adsorbed on a metal surface by gold or other metals is a standard procedure. While it was previously shown that pristine, i.e., undoped, and nitrogen-doped graphene sheets can be decoupled from a nickel substrate by intercalation with gold atoms in order to produce quasi-free-standing graphene, we find the gold intercalation behavior for boron-doped graphene on a Ni(111) surface to be more complex: for low boron contents (2-5%) in the graphene lattice only partial gold intercalation occurs and for higher boron contents (up to 20%) no intercalation is observed. In order to understand this different behavior, a density functional theory investigation is carried out, comparing undoped as well as substitutional nitrogen- and boron-doped graphene on Ni(111). We identify the stronger binding of the boron atoms to the nickel substrate as the factor responsible for the different intercalation behavior in the case of boron doping. However, the calculations predict that this energetic effect prevents the intercalation process only for large boron concentrations and that it can be overcome for smaller boron coverages, in line with our x-ray photoelectron spectroscopy experiments. © 2013 IOP Publishing Ltd.

Graphene on Ni(111): Coexistence of different surface structures - Zhao, Wei; Kozlov, Sergey M.; Höfert, Oliver; Gotterbarm, Karin; Lorenz, Michael Peter Andreas; Vines, Francesc; Papp, Christian; Görling, Andreas; Steinrück, Hans-Peter (Journal of Physical Chemistry Letters, 2011)
A combined high-resolution X-ray photoelectron spectroscopy (HR-XPS) and ab initio density functional theory study on graphene on Ni(111) shows the coexistence of two structures, a bridge-top and a top-fcc structure, that have almost identical energies according to DFT calculations. Consequently, both geometries are detected simultaneously on the Ni(111) surface by HR-XPS, while their relative fractions depend on minor surface defect concentrations (pinning sites). The two structures are identified due to their different core level shifts that are in line with DFT calculations. © 2011 American Chemical Society.

Graphene-Supported Pd Nanoclusters Probed by Carbon Monoxide Adsorption - Gotterbarm, Karin; Bronnbauer, Carina; Bauer, Udo; Papp, Christian; Steinrück, Hans-Peter (Journal of Physical Chemistry C, 2014)
The adsorption of CO on graphene-supported Pd nanoparticles was studied in situ with high-resolution synchrotron-based X-ray photoelectron spectroscopy. At 150 K, CO adsorbs mainly in bridge and 3-fold-hollow sites. The nanoparticles are considered as a mixture of low-index facets. The variation of the amount of deposited Pd revealed identical CO adsorption behavior for all investigated cases, confirming a similar average cluster size over a wide range of Pd coverages. The desorption characteristics were studied with temperature-programmed XPS. The observed desorption maxima at 230 and 430 K are in good agreement with temperature-programmed desorption data on stepped Pd single crystals. At 500 K, CO is completely desorbed from the Pd clusters. The adsorption and desorption of CO are found to be not fully reversible as the Pd particles undergo restructuring upon heating.

Graphene-Templated Growth of Pd Nanoclusters - Gotterbarm, Karin; Steiner, Christian; Bronnbauer, Carina; Bauer, Udo; Steinrück, Hans-Peter; Maier, Sabine; Papp, Christian (Journal of Physical Chemistry C, 2014)
Graphene grown on Rh(111) was used as a template for the growth of Pd nanoclusters. Using high-resolution synchrotron radiation-based X-ray photoelectron spectroscopy, we studied the deposition of Pd on corrugated graphene in situ. From the XP spectra, we deduce a cluster-by-cluster growth mode. The formation of clusters with 3 nm diameter was confirmed by low-temperature scanning tunneling microscopy measurements. The investigation of the thermal stability of the Pd particles showed three characteristic temperature regimes: Up to 550 K restructuring of the particles takes place, between 550 and 750 K the clusters coalesce into larger agglomerates, and finally between 750 and 900 K Pd intercalates between the graphene layer and the Rh surface.

Größenabhängiger Oxidationsmechanismus trägerfixierter Pd-Nanopartikel - Libuda, Jörg; et al. (Angewandte Chemie, 2006)
UnivIS-Import:2015-03-09:Pub.2006.nat.dchph.ppc20.grenab

Growth and electronic properties of thin Zn layers on Cu(1 1 1) - Ammon, Christian; Held, Georg; Pantförder, Jörg; Steinrück, Hans-Peter (Surface Science, 2001)
The growth and the electronic structure of thin Zn layers on Cu(111) in the coverage range 0 ≤ Θ ≤ 60 ML was studied by temperature-programmed desorption (TPD) of Zn and CO and angle resolved UV-photoelectron spectroscopy (ARUPS). CO titration experiments indicate two-dimensional growth for small amounts of Zn (up to 1 ML) after annealing to 400 K. Upon further annealing, the first Zn layer desorbs over a relatively wide temperature range between 500 and 640 K. For sub-monolayers of Zn an irreversible phase transition is found around 475 K which causes drastic changes in the shape of the CO-TPD spectra from these surfaces. The ARUPS data show a small but clear dispersion of the Zn 3d states for Zn layers above 0.5 ML. The transition at 475 K causes a narrowing of the Zn 3d bandwidth leaving the average binding energy unchanged. This indicates a larger separation of the Zn atoms in this surface arrangement which can be explained by a substitutional adsorption of Zn atoms. © 2001 Elsevier Science B.V. All rights reserved.

Growth and electronic structure of boron-doped graphene - Gebhardt, Julian; Koch, Roland; Zhao, Wei; Höfert, Oliver; Gotterbarm, Karin; Mammadov, Samir; Papp, Christian; Görling, Andreas; Steinrück, Hans-Peter; Seyller, Thomas (Physical Review B, 2013)
The doping of graphene to tune its electronic properties is essential for its further use in carbon-based electronics. Adapting strategies from classical silicon-based semiconductor technology, we use the incorporation of heteroatoms in the 2D graphene network as a straightforward way to achieve this goal. Here, we report on the synthesis of boron-doped graphene on Ni(111) in a chemical vapor deposition process of triethylborane on the one hand and by segregation of boron from the bulk of the substrate crystal on the other hand. The chemical environment of boron was determined by x-ray photoelectron spectroscopy, and angle-resolved photoelectron spectroscopy was used to analyze the impact on the band structure. Doping with boron leads to a shift of the graphene bands to lower binding energies. The shift depends on the doping concentration and for a doping level of 0.3 ML a shift of up to 1.2 eV is observed. The experimental results are in agreement with density-functional calculations. Furthermore, our calculations suggest that doping with boron leads to graphene preferentially adsorbed in the top-fcc geometry, since the boron atoms in the graphene lattice are then adsorbed at substrate fcc-hollow sites. The smaller distance of boron atoms incorporated into graphene compared to graphene carbon atoms leads to a bending of the doped graphene sheet in the vicinity of the boron atoms. By comparing calculations of doped and undoped graphene on Ni(111), as well as the respective freestanding cases, we are able to distinguish between the effects that doping and adsorption have on the band structure of graphene. Both doping and bonding to the surface result in opposing shifts on the graphene bands. © 2013 American Physical Society.

Growth and electronic structure of nitrogen-doped graphene on Ni(111) - Koch, Roland; Weser, M.; Zhao, Wei; Vines, Francesc; Gotterbarm, Karin; Kozlov, Sergey M.; Höfert, Oliver; Ostler, Markus; Papp, Christian; Gebhardt, Julian; Steinrück, Hans-Peter; Görling, Andreas; et al. (Physical Review B, 2012)
We report on experimental and theoretical investigations of nitrogen-doped graphene. The incorporation of nitrogen was achieved during chemical-vapor deposition on Ni(111) using pyridine as a precursor. The obtained graphene layers were investigated using photoelectron spectroscopy. By studying C 1s and N 1s core levels, we show that the nitrogen content is influenced by the growth temperature and determine the atomic arrangement of the nitrogen atoms. Valence-band photoelectron spectra show that the incorporation of nitrogen leads to a broadening of the photoemission lines and a shift of the π band. Density functional calculations for two possible geometric arrangements, the substitution of carbon atoms by nitrogen and vacancies in the graphene sheet with pyridinic nitrogen at the edges, reveal that the two arrangements have opposite effects on the band structure. For the present experimental approach, vacancies with pyridinic nitrogen are dominant. In the latter case the vacancies generated by the nitrogen doping, not the nitrogen itself, have the main effect on the band structure. By intercalating gold between the doped graphene layer and the Ni(111) substrate electronic decoupling is achieved. After intercalation the doping remains. © 2012 American Physical Society.

Growth and oxidation of graphene on Rh(111) - Gotterbarm, Karin; Zhao, Wei; Höfert, Oliver; Gleichweit, Christoph; Papp, Christian; Steinrück, Hans-Peter (Physical Chemistry Chemical Physics, 2013)
The growth and oxidation of graphene supported on Rh(111) was studied in situ by high-resolution X-ray photoelectron spectroscopy. By variation of propene pressure and surface temperature the optimum growth conditions were identified, yielding graphene with low defect density. Oxidation of graphene was studied at temperatures between 600 and 1000 K, at an oxygen pressure of ∼2 × 10 mbar. The oxidation follows sigmoidal reaction kinetics. In the beginning, the reaction rate is limited by the number of defects, which represent the active sites for oxygen dissociation. After an induction period, the reaction rate increases and graphene is rapidly removed from the surface by oxidation. For graphene with a high defect density we found that the oxidation is faster. In general, a reduction of the induction period and a faster oxidation occur at higher temperatures. © 2013 The Owner Societies.

Growth and stability of Pt nanoclusters from 1 to 50 atoms on h-BN/Rh(111) - Düll, Fabian; Meusel, Manuel; Späth, Florian; Schötz, Simon; Bauer, Udo; Bachmann, Philipp; Steinhauer, Johann; Steinrück, Hans-Peter; Bayer, Andreas; Papp, Christian (Physical Chemistry Chemical Physics, 2019)
The h-BN nanomesh on Rh(111) is used as eggbox-like template for the formation of arrays of Pt nanoclusters with a narrow size distribution. Nanoclusters with sizes from 1 up to 50 atoms are prepared simultaneously in a wedge-like structure by depositing a coverage gradient on the h-BN nanomesh, and thus can be investigated under identical conditions. We studied the preparation and properties of these Pt nanoclusters of different size in situ by high-resolution X-ray photoelectron spectroscopy and scanning tunneling microscopy. For a Pt coverage of 0.1 ML, all pores of the h-BN nanomesh are filled with nanoclusters with a remarkably uniform cluster size of ≈12 Pt atoms per pore, and high stability up to 400 K. Above 0.2 ML Pt, the clusters are less stable. The coverage dependent analysis shows that for Pt coverages below 0.1 ML, the number of nanoclusters is smaller - and the number of empty pores higher - than expected for a simple hit and stick mechanism. We assign this behavior to an initially higher mobility of the Pt atoms in a hot precursor state.
CRIS-Team Scopus Importer:2019-10-11

Growth of Multilayers of Ionic Liquids on Au(111) Investigated by Atomic Force Microscopy in Ultrahigh Vacuum - Meusel, Manuel; Lexow, Matthias; Gezmis, Emine; Bayer, Andreas; Maier, Florian; Steinrück, Hans-Peter (Langmuir, 2020)
Understanding the growth of ultrathin films of ionic liquids (ILs) on metal surfaces is of highest relevance for a variety of applications. We present a detailed study of the growth of the wetting layer and successive multilayers of 1,3-dimethylimidazolium bis[(trifluoromethyl)sulfonyl]imide ([C1C1Im][Tf2N]) on Au(111). By atomic force microscopy (AFM) in ultrahigh vacuum, we follow the temperature-dependent behavior between 110 and 300 K at defined coverages. We initially observe the formation of a wetting layer with a thickness of ∼0.37 nm with anions and cations arranged in a checkerboard structure. Stable AFM imaging up to 280 K allows us to follow the IL growing on top of the wetting layer in bilayers with an average thickness of ∼0.71 nm, that is, double the height of the wetting layer, in a bilayer-by-bilayer fashion. This growth behavior is independently confirmed from the surface morphology, as deduced from AFM and angle-resolved X-ray photoelectron spectroscopy. High-resolution AFM images at 110 K allow for identifying the molecular surface structure of the bilayers as a striped phase, which is one of the phases also seen for the wetting layer (Meusel, M.; Lexow, M.; Gezmis, A.; Schotz, S.; Wagner, M.; Bayer, A.; Maier, F.; Steinrück, H. P. Atomic Force and Scanning Tunneling Microscopy of Ordered Ionic Liquid Wetting Layers from 110 K up to Room Temperature. ACS Nano2020, 14, 9000-9010).
CRIS-Team Scopus Importer:2020-11-27

Growth of Stable Surface Oxides on Pt(111) at Near-Ambient Pressures - Fantauzzi, Donato; Krick Calderon, Sandra; Mueller, Jonathan E.; Grabau, Mathias; Papp, Christian; Steinrück, Hans-Peter; Senftle, Thomas P.; van Duin, Adri C. T.; Jacob, Timo (Angewandte Chemie-International Edition, 2017)
Detailed knowledge of the structure and degree of oxidation of platinum surfaces under operando conditions is essential for understanding catalytic performance. However, experimental investigations of platinum surface oxides have been hampered by technical limitations, preventing in situ investigations at relevant pressures. As a result, the time-dependent evolution of oxide formation has only received superficial treatment. In addition, the amorphous structures of many surface oxides have hindered realistic theoretical studies. Using near-ambient pressure X-ray photoelectron spectroscopy (NAP-XPS) we show that a time scale of hours (t≥4 h) is required for the formation of platinum surface oxides. These experimental observations are consistent with ReaxFF grand canonical Monte Carlo (ReaxFF-GCMC) calculations, predicting the structures and coverages of stable, amorphous surface oxides at temperatures between 430–680 K and an O partial pressure of 1 mbar.
Keywords: interfaces; kinetics; oxidation; phase transitions; surface chemistry

Growth of ultrathin Cr films on benzene-covered Ni(111) - Sklarek, Werner; Held, Georg; Ammon, Christian; Steinrück, Hans-Peter (Applied Surface Science, 1999)
Using X-ray photoelectron spectroscopy (XPS) and temperature programmed desorption (TPD) we studied the properties of thin Cr films in the nominal coverage range between 0.13 and 4 monolayers (ML), which were evaporated onto a Ni(111) surface pre-covered with up to 14 ML benzene. Evaporation of small amounts of Cr (< 0.5 ML) onto thick benzene layers (> 4 ML) at 100 K leads to the formation of non-metallic bis(benzene)chromium (Cr(CH)) rather than condensation of small clusters in the benzene matrix, as can be seen from the positions and shapes of the Cr 2p peaks in XPS. Upon annealing to 400 K these films transform into metallic Cr as is indicated by a Cr 2p peak shift of -0.8 eV, and significant changes in the peak shapes. For 0.5-2 ML a metallic Cr species, in addition to the non-metallic species, is already seen at 100 K. For higher coverages > 2 ML only the metallic species is seen in XPS and the Cr 2p peak shape does then not change upon annealing. The development of the C 1s spectra upon annealing reveals that there is a significant amount of benzene buried under the Cr layer, which is partially dissociated, depending on the annealing temperature and the Cr coverage.

Heterogeneous gold catalysts for efficient access to functionalized lactones - Neatu, Florentina; Li, Zhi; Richards, Ryan; Toullec, Patrick Y.; Genet, Jean-Pierre; Dumbuya, Karifala; Gottfried, Michael; Steinrück, Hans-Peter; Parvulescu, Vasile I.; Michelet, Veronique (Chemistry - A European Journal, 2008)
A novel class of heterogeneous gold catalysts supported on zeolite beta-NH was prepared by the deposition-precipitation method. This new class of catalyst showed interesting catalytic activities for the intramolecular cycloisomerization of γ-acetylenic carboxylic acids leading to functionalized γ-alkylidene γ-butyrolactones. Analysis of the supported gold species with in situ X-ray photoelectron spectroscopy (in situ XPS) suggests that cationic Au (possibly Au) can play an important role in such reactions. The high discrepancy in catalyst stability in favor of the Au supported on the zeolite system over bulk AuO is explained by 1) the size of the particles and 2) the reversibility of the redox deactivating process (Au→Au ) in the presence of oxygen for the supported system. The efficiency of this system allowed reaction under mild heterogeneous conditions. The potential for catalyst recycling was also highlighted. © 2008 Wiley-VCH Verlag GmbH & Co. KGaA.

Highly dispersed Pd nanoparticles within silica: Synthesis and characterization - Ofili, Ifeanyi Jimmy; Steinrück, Hans-Peter; Schwieger, Wilhelm; Ramakrishnan, Ayyappan; Dumbuya, K.; Gottfried, Michael (Applied Clay Science, 2011)
Well dispersed and homogeneously distributed Pd nanoparticles within a silica matrix were synthesized by a two stage process: (1) intercalation of palladium tetrammine ions into the layered aluminium-free silicate Na ilerite followed by (2) a self-reduction of the complex through decomposition of the tetrammine ligands by calcination at 550°C for 5h under N or air. Samples calcined in N predominantly contained nanoparticles of metallic Pd, while calcination in air led largely to the formation of PdO, as confirmed by XPS and supported by XRD and TGA. Thus, the Pd/PdO loading in the silica can be selectively tuned through this method. The intercalates were characterized by standard methods such as XRD, TGA, ICP and TEM. TGA of the intercalates indicated that the stabilization of the palladium tetrammine complex was enhanced by intercalation into Na ilerite. Based on ICP analysis, the Pd loadings in the intercalates were estimated to be about 18mass-%, which was also in agreement with the results from TGA. TEM revealed that the Pd/PdO nanoparticles were well dispersed in the silica matrix with an average particle size of approximately 8-10nm after calcination in air. © 2010 Elsevier B.V.

Highly Effective Propane Dehydrogenation Using Ga-Rh Supported Catalytically Active Liquid Metal Solutions - Raman, Narayanan; Maisel, Sven; Grabau, Mathias; Taccardi, Nicola; Debuschewitz, Jonas; Wolf, Moritz; Wittkämper, Haiko; Bauer, Tanja; Wu, Mingjian; Haumann, Marco; Papp, Christian; Görling, Andreas; et al. (ACS Catalysis, 2019)
Our contribution demonstrates that rhodium, an element that has barely been reported as an active metal for selective dehydrogenation of alkanes becomes a very active, selective, and robust dehydrogenation catalyst when exposed to propane in the form of single atoms at the interface of a solid-supported, highly dynamic liquid Ga-Rh mixture. We demonstrate that the transition to a fully liquid supported alloy droplet at Ga/Rh ratios above 80, results in a drastic increase in catalyst activity with high propylene selectivity. The combining results from catalytic studies, X-ray photoelectron spectroscopy, IR-spectroscopy under reaction conditions, microscopy, and density-functional theory calculations, we obtained a comprehensive microscopy picture of the working principle of the Ga-Rh supported catalytically active liquid metal solution.
CRIS-Team Scopus Importer:2019-10-18
Keywords: alkane; alkene; catalysis; dehydrogenation; gallium; rhodium

Highly efficient dissociation of condensed and adsorbed water via core-to-bound excitation - Coulman, D.; Puschmann, A.; Wurth, W.; Steinrück, Hans-Peter; Menzel, Dietrich (Chemical Physics Letters, 1988)
Synchrotron radiation has been used to investigate the energy, polarization and angular dependences of the O KLL Auger yield and the H/D ion yield from multilayers and monolayers of HO and DO on Ru(001) in the O 1s region. A sharp, narrow peak in the ion yield, directed along the surface normal, has been found at about 534 eV for all layers. Its counterpart in the Auger yield, which is representative of the absorption cross section, is comparatively weak. We assign this peak to the 1a → 4a core-to-bound transition. In this case, dissociation and core-hole decay appear to proceed on roughly the same time scale. © 1988.

High-resolution photoemission study of different NTCDA monolayers on Ag(111): Bonding and screening influences on the line shapes - Fink, Rainer; Umbach, Eberhard; Schoell, Achim; Schmidt, Thomas; et al. (Journal of Physical Chemistry B, 2004)
We present high-resolution C Is and O 1s photoemission results of different NTCDA monolayer states adsorbed on a Ag(111) substrate (NTCDA = 1,4,5,8-naphthalene-tetracarboxylic acid dianhydride). The comparison of mono- and multilayer data clearly proves the chemisorptive character of the bonding of this planar aromatic molecule to the metal substrate. The rich fine structures of the monolayer spectra exhibit large differences for the three distinct monolayer states observed, leading to the conclusion of significant differences in their bonding. The fine structures are interpreted in detail on the basis of a thorough peak-fit analysis which allows a consistent assignment of the various photoemission main and satellite lines. As a result, the binding energies of the 1s levels of all C and O atoms and the relative intensities of the most significant satellite lines are extracted, the latter providing important information on the bonding and the dynamic screening process.

High resolution surface sensitive C1s core level spectra of clean and hydrogen terminated diamond (100) and (111) surfaces - Maier, Florian; Ristein, Jürgen; Ley, Lothar; et al. (Physical Review B - Condensed Matter and Materials Physics, 1998)
UnivIS-Import:2015-03-05:Pub.1998.nat.dphy.IAP.exphys.highre

Holographic reconstruction of Pt(110) using multiple wave number photoelectron diffraction patterns - Steinrück, Hans-Peter; et al. (Surface Science, 1994)
Angular distributions of Pt4f 7 2 and 4f 5 2 photoelectrons were measured for the reconstructed Pt(110)l × 2 surface at six different kinetic energies ranging from 120 up to 370 eV, using an angle-multichannel electron analyzer. From the photoelectron diffraction patterns, holographic reconstructions were performed using (1) the single wave number reconstruction method and (2) the multiple wave number phased sum method. The results obtained from the two photoemission lines are overall very similar. For the single energy reconstruction, the quality of the reconstructed images strongly depends on the kinetic energy of the photoelectrons: at high kinetic energies (370 eV) the reconstructed images are dominated by the maxima attributed to the nearest neighbors in the plane above the emitter; at low kinetic energies (120 eV) artifacts dominate. The multiple wave number algorithm leads to strong twin-image suppression, a reduction of certain artifacts but no noticeable improvement of resolution. While the overall quality of the reconstructed images increases when using the multiple energy algorithm, the best quality is observed for the single energy reconstruction for a kinetic energy of 370 eV. In all cases the atomic positions are shifted from their true values by 0.2-0.3 Å due to the phase shift in the scattering process. © 1994.

Holography of clean and sulphur-covered Ni(111) using multiple wave number photoelectron diffraction patterns - Zharnikov, M.; Weinelt, M.; Zebisch, P.; Stichler, M.; Steinrück, Hans-Peter (Surface Science, 1995)
Angular distributions of Ni 3p photoelectrons for clean Ni(111) and of S 2p photoelectrons for the p(2 × 2)S and (5√3 × 2)S structures on Ni(111) were measured at seven different kinetic energies ranging from 239 to 417 eV for Ni 3p and from 130 to 322.5 eV for S 2p. From the photoelectron diffraction patterns, holographic reconstructions were performed using (1) the single wave number reconstruction method and (2) the multiple wave number phased sum method. For the clean surface, neighboring atoms in the plane of the emitter and some atoms in the second and third plane above the emitter can be identified; the holographic reconstruction in the first plane above the emitter is however dominated by intense artifacts. For Ni(111)-p(2 × 2)S, the three-fold hollow fcc adsorption site of sulphur can be unequivocally identified with a distance to the first Ni layer of about 1.6 Å. Holographic reconstructions for Ni(111)-(5√3 × 2)S allow to exclude the three-fold hollow position of sulphur and disagree with a proposed mixing of different non-symmetric adsorption sites. The distance of the sulphur atoms from the top Ni layer is determined to 1.1-1.2 Å. The reconstructions are consistent with a quasi-(100) reconstruction of the Ni(111) crystal surface. For all systems the potential of using only an azimuthal sector instead of the full hemispherical holograms for the reconstruction is discussed. © 1995.

Holography with photoelectrons: A direct approach - Steinrück, Hans-Peter; Zharnikov, Michael (Journal of Physics: Condensed Matter, 2001)
This article reviews the work performed by the authors regarding photoelectron holography on clean metal surfaces and simple adsorbate arrangements. The following systems were investigated: Pt(1 1 0)-1 × 2, Ni(1 1 0), Ni(1 1 1), Ni(1 1 0)-c(2 × 2) S, Ni(1 1 1)-p(2 × 2) S and Ni(1 1 1)-(5√3 × 2) S. The photoelectron diffraction patterns, which are interpreted as holograms, were recorded using synchrotron radiation at the German synchrotron facility BESSY-I in Berlin. For most systems these holograms were acquired at various kinetic energies. The real space structures were reconstructed from these data using the single wave number as well as the multiple wave number algorithm, without any prior assumptions. It was demonstrated that the local geometrical structure of clean single crystal surfaces and of adsorbate systems can be successfully reconstructed by using photoelectron holography with some restrictions.

Hot electron injection into semiconducting polymers in polymer based-perovskite solar cells and their fate - Jiménez-López, Jesús; Puscher, Bianka; Cambarau, Werther; Fink, Rainer; Palomares, Emilio; Guldi, Dirk Michael (Nanoscale, 2019)
Metal halide perovskites are known to possess upon photoexcitation long-lived hot carriers. By using femtosecond laser transient absorption spectroscopy, we probed in the current work interfacial charge transfer, that is, hot electrons and holes in methylammonium lead iodide perovskite. The focus was, on the one hand, on titanium dioxide as an electron transporting material and, on the other hand, on several organic semiconducting materials as hole transporting materials in perovskite solar cells. An unexpected carrier loss pathway for hot electrons was found in the form of injection into the low lying LUMOs of several organic semiconducting materials. Of great importance is the fact that the final photocurrents of perovskite solar cells scale with the suppression of this newly discovered loss pathway.
CRIS-Team Scopus Importer:2019-12-27

Hungry Porphyrins: Protonation and Self-Metalation of Tetraphenylporphyrin on TiO2(110)-1 x 1 - Köbl, Julia; Wang, Tao; Wang, Cici; Drost, Martin; TU, Fan; Xu, Qian; Ju, Huanxin; Wechsler, Daniel; Franke, Matthias; Pan, Haibin; Marbach, Hubertus; Steinrück, Hans-Peter; et al. (ChemistrySelect, 2016)
We have studied the adsorption and self-metalation of tetraphenylporphyrin (2HTPP) on TiO2(110) -1 x 1 with X-ray Photoelectron Spectroscopy (XPS) and Scanning Tunneling Microscopy (STM). Upon adsorption at room temperature the first monolayer of 2HTPP is protonated by protons from the surface, forming porphyrin diacid (4HTPP(2+)). In STM, single molecules with low mobility and no long-range order were observed. As the surface is heated to 400 K, any unprotonated 2HTPP molecules in the second layer metalate, forming titanyl tetraphenylporphyrin (TiOTPP), but the protonated molecules in the first layer remain. As the surface is heated further to 550 K even the protonated 4HTPP(2+) molecules metalate and only TiOTPP remain on the surface.
Keywords: Adsorption; Porphyrinoids; Oxide Surfaces; Surface Chemistry; Titania

Hydrogen activation on Pt-Sn nanoalloys supported on mixed Sn-Ce oxide films - Neitzel, Armin; Lykhach, Yaroslava; Skala, Tomas; Tsud, Nataliya; Johanek, Viktor; Vorokhta, Mykhailo; Prince, Kevin C.; Matolin, Vladimir; Libuda, Jörg (Physical Chemistry Chemical Physics, 2014)
We have studied the interaction of H-2 with Pt-Sn nanoalloys supported on Sn-Ce mixed oxide films of different composition by means of synchrotron radiation photoelectron spectroscopy and resonant photoemission spectroscopy. The model catalysts are prepared in a three step procedure that involves (i) the preparation of well-ordered CeO2(111) films on Cu(111) followed by subsequent physical vapor deposition of (ii) metallic Sn and (iii) metallic Pt. The formation of mixed Sn-Ce oxide is accompanied by partial reduction of Ce4+ cations to Ce3+. Pt deposition leads to the formation of Pt-Sn nanoalloys accompanied by the partial re-oxidation of Ce3+ to Ce4+. Subsequent annealing promotes further Pt-Sn alloy formation at expense of the Sn content in the Sn-Ce mixed oxide. Adsorption of H-2 on Pt-Sn/Sn-Ce-O at 150 K followed by stepwise annealing results in reversible reduction of Ce cations caused by spillover of dissociated hydrogen between 150 and 300 K. Above 500 K, annealing of Pt-Sn/Sn-Ce-O in a hydrogen atmosphere results in irreversible reduction of Ce cations. This reduction is caused by the reaction of hydrogen with oxygen provided by the mixed oxide substrate via the reverse spillover to Pt-Sn nanoalloy. The extent of the hydrogen and oxygen spillover strongly depends on the amount of Sn in the Sn-Ce mixed-oxide. We observe an enhancement of hydrogen spillover on Pt-Sn/Sn-Ce-O at low Sn concentration as compared to Sn-free Pt/CeO2. Although the extent of hydrogen spillover on Pt-Sn/Sn-Ce-O with high Sn concentration is comparable to Pt/CeO2, the reverse oxygen spillover is substantially suppressed on these samples.

Hydrogenation and dehydrogenation of nitrogen-doped graphene investigated by X-ray photoelectron spectroscopy - Späth, Florian; Zhao, Wei; Gleichweit, Christoph; Gotterbarm, K.; Bauer, Udo; Höfert, Oliver; Steinrück, Hans-Peter; Papp, Christian (Surface Science, 2015)
We studied the hydrogenation and dehydrogenation of nitrogen-doped graphene (NDG) by in situ high-resolution X-ray photoelectron spectroscopy (XPS) and temperature-programmed XPS (TPXPS). Nitrogen-doped graphene was prepared by low energy nitrogen implantation in pristine graphene on Ni(111). Hydrogenation of NDG was performed by exposure to atomic hydrogen. Upon hydrogenation the XP spectra in the C 1s region reveal one new peak, shifted to lower binding energies as compared to graphene, which is associated with newly formed CH groups. In the N 1s region two ne wpeaks, shifted to higher binding energies are observed; these are associated with hydrogenated pyridinic and graphitic nitrogen. TPXPS spectra reveal a different thermal stability of the two hydrogenated nitrogen species,while the C–H groups of graphene show no significant changes compared to undoped hydrogenated graphene.

Hydrogenation and hydrogen intercalation of hexagonal boron nitride on Ni(111): reactivity and electronic structure - Späth, Florian; Gebhardt, Julian; Düll, Fabian; Bauer, Udo; Bachmann, Philipp; Gleichweit, Christoph; Görling, Andreas; Steinrück, Hans-Peter; Papp, Christian (2D Materials, 2017)
We investigate the reactivity of hexagonal boron nitride (h-BN) on a Ni(1 1 1) single crystal towards atomic hydrogen over a wide exposure range. Near edge x-ray absorption fine structure and x-ray photoelectron spectroscopy (XPS) show that for low hydrogen exposures hydrogenation of the h-BN sheet is found. In contrast, intercalation of hydrogen between h-BN and the Ni(1 1 1) substrate occurs for high exposures. For intermediate regimes, a mixture of intercalation and hydrogenation is observed. From temperature-programmed desorption and temperature-programmed XPS experiments, we conclude that the hydrogen covalently bound to h-BN is rather stable with a desorption temperature of 600 K, while intercalated hydrogen is desorbing already at 390 K. Further insight into the structural arrangements and the thermodynamics of the system is obtained by comparing our experimental results with extensive density-functional theory calculations. Together with ultraviolet photoelectron spectroscopy measurements, the calculations provide detailed insight into the influence of hydrogenation on the electronic structure of h-BN.
Keywords: hexagonal boron nitride; hydrogenation; intercalation; electronic structure

Hydrogen, chemically stored - Papp, Christian; Wasserscheid, Peter; Libuda, Jörg; Steinrück, Hans-Peter (Nachrichten aus der Chemie, 2014)

Hydrogen spillover monitored by resonant photoemission spectroscopy - Lykhach, Yaroslava; Staudt, Thorsten; Vorokhta, Mykhailo; Skala, Tomas; Johanek, Viktor; Prince, Kevin C.; Matolin, Vladimir; Libuda, Jörg (Journal of Catalysis, 2012)
We have employed resonant photoemission spectroscopy to investigate the phenomenon of hydrogen spillover on well-defined model Pt/ceria catalysts. On Pt/CeO2(111)/Cu(111), hydrogen spillover and reverse spillover give rise to reversible changes of the oxidation state of the surface cerium ions. These changes are monitored with highest sensitivity via resonant enhancement of Ce3+- and Ce4+-related features in the valence band photoemission spectra. The temperature regions are precisely determined in which specific processes such hydrogen spillover, Ce3+ transport, and reverse spillover are activated. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: Ceria; Platinum; Hydrogen; Hydrogen spillover; Model catalyst; Heterogeneous catalysis; Resonant photoemission spectroscopy

Identifying surface species by vibrational spectroscopy: Bridging vs monodentate nitrates - Desikusumastuti, Aine; Staudt, Thorsten; Gronbeck, Henrik; Libuda, Jörg (Journal of Catalysis, 2008)
Identification of surface species by IR spectroscopy is often based on common knowledge, with a clear risk of misassignment. Combining density functional theory (DFT) and IR reflection absorption spectroscopy (IRAS), we investigated surface nitrate formation on BaO/Al2O3 thin films. We found that it is not possible to identify coordination geometries of nitrates based solely on their vibrational frequencies. For metal-supported thin films, however, differences in polarization of the NO stretching modes facilitate unambiguous identification. In contrast to traditional assignments, we show that both bridging and monodentate nitrates are formed on BaO, whereas on Al2O3 bridging nitrates dominate. (c) 2008 Elsevier Inc. All rights reserved.
Keywords: nitrogen dioxide; barium oxide; aluminum oxide; density functional theory; IR reflection absorption spectroscopy; supported model catalysts

Identifying the Thermal Decomposition Mechanism of Guaiacol on Pt(111): An Integrated X-ray Photoelectron Spectroscopy and Density Functional Theory Study - Hensley, Alyssa J. R.; Woeckel, Claudia; Gleichweit, Christoph; Gotterbarm, Karin; Papp, Christian; Steinrück, Hans-Peter; Wang, Yong; Denecke, Reinhard; Mcewen, Jean-Sabin (Journal of Physical Chemistry C, 2018)
Using a concerted effort from both experiment and theory, we determine the thermal decomposition mechanism for guaiacol on Pt(111), a reaction of interest in the area of bio-oil upgrading. This work serves as a demonstration of the power of combining in situ temperature-programmed X-ray photoelectron spectroscopy cos (TPXPS) and density functional theory (DFT) to elucidate complex reaction mechanisms occurring on heterogeneous surfaces. At low temperature (230 K), guaiacol was found to chemisorb with the aromatic ring parallel to the Pt(111) surface with five distinct carbon species and three oxygen species. As the temperature was increased, TPXPS showed several significant changes to the surface species. The increase in the species associated with the decomposition of the functional groups of guaiacol is followed by their subsequent disappearance and an increase in the nonaromatic carbon signal. On the basis of an energetic analysis of the various mechanisms using DFT, along with the comparison of the experimentally and theoretically derived core-level binding energies, we determined that guaiacol's decomposition mechanism occurs via the dehydrogenation of both the methyl and hydroxyl functional groups, followed by demethylation of the CH2 or CH group to form 1,2-benzoquinone. Further heating to above 375 K likely breaks the aromatic ring and results in the rapid formation and desorption of CO, accounting for the disappearance of the 0 is signal above 450 K These results show that a knowledgeable application of TPXPS and DFT can result in the quantitative identification of surface species during complex reactions, providing insight useful for the design of future heterogeneous surfaces.

Immobilized catalytically active composition for hydroformylation of olefin-containing mixtures. - Dyballa, Katrin M.; Franke, Robert; Hahn, Hanna; Becker, Marc; Schönweiz, Andreas; Debuschewitz, Jonas; Walter, Simon; Woelfel, Rene; Haumann, Marco; Wasserscheid, Peter; Kaftan, Andre; Laurin, Mathias; et al. (2014)
Compn. used as a catalyst for hydroformylation of olefinically unsatd. hydrocarbon mixts. comprises a metal complex, esp. an Rh complex having a phosphine or phosphite ligand, on an inert porous carrier, and is loaded for the purposes of the hydroformylation with the aldol byproduct of the desired aldehyde, in the manner of an application of the "Supported Liq. Phase" (SLP) concept. Thus, aldol ( 2-Methylpent-2-enal) doping leads to increasing yield of propanal as a product of hydroformylation of ethylene with H2 and CO on a solid catalyst consisting of acetylacetonatodicarbonylrhodium supported on Trisopor 423. [on SciFinder(R)]
Keywords: immobilized hydroformylation catalyst olefin aldehyde

Impact of Sulfur Poisoning on the NOx Uptake of a NOx Storage and Reduction (NSR) Model Catalyst - Happel, Markus; Desikusumastuti, Aine; Sobota, Marek; Laurin, Mathias; Libuda, Jörg (Journal of Physical Chemistry C, 2010)
Toward obtaining it more detailed understanding of the influence of SOx poisoning oil the mechanism of NOx uptake on a NOx storage and reduction (NSR) catalyst, we have performed a model Study under ultrahigh vacuum (UHV) conditions. A Supported model catalyst based oil a thin well-ordered alumina film grown oil a NiAl(110) single crystal is used Onto which BaO and Pd particles are deposited. Time-resolved (TR) infrared reflection absorption spectroscopy (IRAS) is applied to identify the species formed during NO2 uptake on the catalyst surface, which has been pretreated with SO2. These results are compared to the NO2 uptake on the corresponding fresh samples.It is shown that SO2 readily decomposes upon adsorption oil both the pristine Al2O3 surface and the BaO and Pd loaded model systems. NO2 reoxidizes the decomposition products 10 surface sulfites and sulfates. A pronounced influence of the SO2 species oil the interaction with NO2 is observed leading to reduced NO2 uptake and to a change of the preferential adsorption geometry from bridging to monodentate. A comparison of the integral intensity of the nitrate bands oil the Ba-free and the Ba-containing samples Furthermore Suggests that SO2 adsorbs preferentially on Ba2+ centers rather than oil the Al3+ centers.

Improved charge carrier dynamics in polymer/perovskite nanocrystal based hybrid ternary solar cells - Soltani, Rezvan; Puscher, Bianka; Katbab, Ali Asghar; Levchuk, Ievgen; Kazerouni, Negar; Gasparini, Nicola; Camaioni, Nadia; Osvet, Andres; Batentschuk, Miroslaw; Fink, Rainer; Guldi, Dirk Michael; Ameri, Tayebeh (Physical Chemistry Chemical Physics, 2018)
Here, brand new ternary hybrid solar cells comprising perovskite nanocrystals (NCs) with a complementary absorption profile of the organic host matrix are reported. In particular, NH2CHNH2PbI3 (FAPbI3) perovskite NCs are implemented in bulk heterojunction organic solar cells based on the pDPP5T-2 electron donating polymer and a [6,6]-phenyl-C61-butyric acid methyl ester (PC61BM) acceptor at various loading amounts and the fabricated hybrid photovoltaics are thoroughly studied by employing different optoelectrical characterization methods. Current-voltage measurements and photoinduced charge carrier extraction by linear increasing voltage (photo-CELIV) reveal improved charge generation and charge transport properties upon incorporation of perovskite NCs into the photo-active layer of the hybrid solar cell. The power conversion efficiency (PCE) of the hybrid solar cell comprising 5% perovskite NCs is 10% enhanced compared to the organic reference, mainly due to the enlarged light harvesting and increased short circuit current density (Jsc). However, results suggest that introducing a higher amount of perovskite content induces bimolecular and trap-assisted recombination in the ternary devices. We perform a comprehensive transient absorption study of the charge transfer/transport mechanisms by employing femto-second pump-probe transient absorption spectroscopy (fs-TAS). fs-TAS measurements demonstrate a slower charge carrier recombination rate due to the introduction of perovskite NCs into the photoactive layer. Results reveal that DPP injects electrons from the singlet excited state into the perovskite NCs, which causes the desired cascading charge carrier transfer. In ternary blends, a small amount of FAPbI3 NCs provides an additional pathway in favor of the charge-separated state via the NCs, which, despite accelerating the depopulation of DPP's singlet excited state slightly slows down the charge-separation process between DPP and PC61BM. Interestingly, the loss processes are slowed down; an effect that is more important and, hence, explains the improved solar cell efficiency. © 2018 the Owner Societie

Industrially scalable and cost-effective Mn2+ doped ZnxCd1-xS/ZnS nanocrystals with 70% photoluminescence quantum yield, as efficient down-shifting materials in photovoltaics - Levchuk, Ievgen; Wuerth, C.; Krause, F.; Osvet, Andres; Batentschuk, Miroslaw; Resch-Genger, Ute; Kolbeck, Claudia; Herre, Patrick; Steinrück, Hans-Peter; Peukert, Wolfgang; Brabec, Christoph (Energy and Environmental Science, 2016)
We present colloidally stable and highly luminescent ZnxCd1-xS:Mn/ZnS core–shell nanocrystals (NCs) synthesized via a simple non-injection one-pot, two-step synthetic route, which can be easily upscaled. A systematic variation of the reaction component, parameters and thickness of the ZnS shell yielded doped nanocrystals with a very high photoluminescence quantum yield ( extgreekFpl) of 70%, which is the highest value yet reported for these Mn-doped sulfide-semiconductor NCs. These materials can be synthesized with high reproducibility in large quantities of the same high quality, i.e., the same extgreekFpl using accordingly optimized reaction conditions. The application of these zero-reabsorption high quality NCs in the light conversion layers, deposited on top of a commercial monocrystalline silicon (mono-Si) solar cell, led to a significant enhancement of the external quantum efficiency (EQE) of this device in the ultraviolet spectral region between 300 and 400 nm up to ca. 12%. EQE enhancement is reflected by an increase in the power conversion efficiency (PCE) by nearly 0.5 percentage points and approached the theoretical limit (0.6%) expected from down-shifting for this Si solar cell. The resulting PCE may result in a BoM (bill of materials) cost reduction of app. 3% for mono-Si photovoltaic modules. Such small but distinct improvements are expected to pave the road for an industrial application of doped semiconductor NCs as cost-effective light converters for silicon photovoltaic (PV) and other optoelectronic applications.
EAM Import::2019-03-14

Influence of As passivation on the electronic level alignment at BeTe/Si(111) interfaces - Gleim, Thomas; Weinhardt, L.; Schmidt, Th.; Fink, Rainer; Heske, C.; Umbach, E.; Hansen, L.; Landwehr, G.; Waag, A.; Fleszar, A.; Richter, B.; Ammon, Christian; et al. (Physical Review B, 2003)
We have investigated the influence of As substrate passivation on the electronic level alignment of the heterovalent BeTe/Si(111) interface. Employing photoelectron spectroscopy, we have performed k-resolved measurements at selected excitation energies in the uv range to maximize the contribution from the F point for a correct determination of the valence band maximum. These results are compared with k-integrated data using a density-of-states function from density functional theory. For BeTe(100) and BeTe(111), we find a negligible influence of surface orientation on the position of the valence band maximum. The As passivation increases the valence band offset by 0.24 eV (±0.13 eV) compared to BeTe on an unpassivated Si substrate, thus leading to a significantly increased step in the valence band (0.37±0.13 eV). The results are discussed with respect to the barriers for electron and hole injection in heterostructures and with respect to the interface structure.

Influence of different anions on the surface composition of ionic liquids studied using ARXPS - Kolbeck, Claudia; Cremer, Till; Lovelock, Kevin; Paape, Natalia; Schulz, Peter; Wasserscheid, Peter; Maier, Florian; Steinrück, Hans-Peter (Journal of Physical Chemistry B, 2009)
Angle-resolved X-ray photoelectron spectroscopy has been used to study the influence of different types of anions on the surface composition of ionic liquids (ILs). We have investigated nine ILs with the same cation, 1-octyl-3-methylimidazolium [CCIm], but very different anions. In all cases, an enrichment of the cation alkyl chains is found at the expense of the polar cation head groups and the anions in the first molecular layer. This enhancement effect decreases with increasing size of the anion, which means it is most pronounced for the smallest anions and least pronounced for the largest anions. A simple model is proposed to explain the experimental observations. © 2009 American Chemical Society.

Influence of different substituents on the surface composition of ionic liquids studied using ARXPS - Lovelock, Kevin; Kolbeck, Claudia; Cremer, Till; Paape, Natalia; Schulz, Peter; Wasserscheid, Peter; Maier, Florian; Steinrück, Hans-Peter (Journal of Physical Chemistry B, 2009)
Angle resolved X-ray photoelectron spectroscopy has been used to study the surface composition of various nonfunctionalized and functionalized 1,3-dialkylimidazolium ionic liquids. For [C C Im][Tf N] (where n ) 2-16), an enrichment of the aliphatic carbon was observed for longer chains (n ≥ 4). Enrichment of the aliphatic carbon also occurs for alkyl chains attached to the anion, as observed for [C C Im][OcOSO ]. Oligo(ethyleneglycol)ether (PEG) functionalities in the cation lead to a surface composition close to bulk stoichiometry and thus a loss in enrichment of the chains. This effect is attributed to attractive interactions between the oxygen atoms on the cation to the hydrogen atoms on the imidazolium ring for [Et(EG) MIm][Tf N] and [Me(EG) MIm][Tf N]. © 2009 American Chemical Society.

Influence of steps on the adsorption and thermal evolution of SO2 on clean and oxygen precovered Pt surfaces - Streber, Regine; Papp, Christian; Lorenz, Michael Peter Andreas; Höfert, Oliver; Zhao, Wei; Wickert, Sandra; Darlatt, Erik; Bayer, Andreas; Denecke, Reinhard; Steinrück, Hans-Peter (Journal of Physical Chemistry C, 2010)
We investigated the adsorption and reaction of SO on clean and oxygen precovered, flat, and regularly stepped Pt surfaces, Pt(111), Pt(322), and Pt(355) by in situ high resolution X-ray photoelectron spectroscopy. Induced by the steps and/or the coadsorbed oxygen, several new SO species are observed, in addition to the two known SO species on Pt(111). On all investigated surfaces, a hit and stick mechanism is found for the adsorption, and no diffusion from terrace to step sites occurs at low temperatures. For the oxygen free stepped surfaces, a higher reactivity toward SO dissociation/disproportionation is found compared to Pt(111). On all three oxygen precovered Pt surfaces some SO is already formed directly upon SO exposure at low temperatures. Heating of this mixed O/SO layers first results in oxidation of more SO to SO, and at higher temperatures in subsequent oxidation of SO to SO, which finally decomposes above 450 K. The different reactions show a significant influence of the steps. © 2010 American Chemical Societ

Influence of steps on the adsorption of methane on platinum surfaces - Papp, Christian; Tränkenschuh, Barbara; Streber, Regine; Fuhrmann, Thomas; Denecke, Reinhard; Steinrück, Hans-Peter (Journal of Physical Chemistry C, 2007)
The activated adsorption of methane was investigated on two stepped Pt(355) and Pt(322) surfaces by timedependent in situ high-resolution X-ray photoelectron spectroscopy (XPS) combined with a supersonic molecular beam and was compared to corresponding results on Pt(111). Both stepped surfaces have five atom row wide (111) terraces but a different step orientation, namely, (111) and (100), respectively. Independent of the kinetic energy (0.45-0.83 eV) of impinging methane (CH or CD), methyl is formed on all surfaces upon adsorption at 120 K. For the stepped surfaces, two different methyl species are identified from the XP spectra, which are attributed to adsorption at terrace sites and at step sites. The total initial sticking coefficients (for terrace + step sites) and the total coverages are very similar for all three surfaces. At low coverages, diffusion of methyl from the terraces to the steps is significantly stronger on Pt(355) than on Pt(322), and the step saturation coverage is higher on Pt(355). The thermal evolution of methyl was also investigated by in situ temperature-programmed XPS. Overall, an enhanced reactivity toward dehydrogenation to methylidyne is found for both terrace and step sites on the stepped surfaces, with the (111) steps of Pt(355) exhibiting the highest activity. © 2007 American Chemical Society.

Influence of substituents and functional groups on the surface composition of ionic liquids - Kolbeck, Claudia; Niedermaier, Inga; Deyko, Alexey; Lovelock, Kevin; Taccardi, Nicola; Wei, Wei; Wasserscheid, Peter; Maier, Florian; Steinrück, Hans-Peter (Chemistry - A European Journal, 2014)
We have performed a systematic study addressing the surface behavior of a variety of functionalized and non-functionalized ionic liquids (ILs). From angle-resolved X-ray photoelectron spectroscopy, detailed conclusions on the surface enrichment of the functional groups and the molecular orientation of the cations and anions is derived. The systems include imidazolium-based ILs methylated at the C2 position, a phenyl-functionalized IL, an alkoxysilane-functionalized IL, halo-functionalized ILs, thioether- functionalized ILs, and amine-functionalized ILs. The results are compared with the results for corresponding non-functionalized ILs where available. Generally, enrichment of the functional group at the surface is only observed for systems that have very weak interaction between the functional group and the ionic head groups. Scratching the surface: The surface behavior of various functionalized ionic liquids (ILs) is studied by angle-resolved X-ray photoelectron spectroscopy and conclusions on surface-enrichment effects and molecular orientation of cations and anions are derived (see figure; Im=imidazolium, Tf=trifluoromethanesulfonyl). Overall, surface enrichment is only observed for functional groups that interact weakly with the ionic head groups. © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

In-operando studies of Ag-TCNQ nanocrystals using Raman and soft x-ray microspectroscopy - Rösner, Benedikt; Schmidt, Ute; Fink, Rainer (Journal of Physics: Conference Series, 2017)
We characterize individual Ag-TCNQ nanocrystals during switching their resistivity state in operando. Raman and soft X-ray absorption microspectroscopy are employed to disclose the electronic state of the organic component in dependency of applied voltage. Whereas Raman microspectroscopy offers qualitative insight into the conversion of negatively charged TCNQ molecules to their neutral counterpart, quantification of the neutral fraction can be achieved using X-ray absorption spectroscopy. These results allow a detailed investigation of resistivity switching in electrically bistable Ag-TCNQ nanocrystals.

Inside Back Cover: Zinc Porphyrin Metal-Center Exchange at the Solid–Liquid Interface (Chem. Eur. J. 25/2016) - Franke, Matthias; Marchini, Florencia; Jux, Norbert; Steinrück, Hans-Peter; Lytken, Ole; Williams, Federico J. (Chemistry - A European Journal, 2016)
Keywords: ion exchange; metalation; porphyrins; solid–liquid interfaces; zinc

Insights in the Reaction Mechanistics: Isotopic Exchange During the Metalation of Deuterated Tetraphenyl-21,23D-porphyrin on Cu(111) - Röckert, Michael; Franke, Matthias; Tariq, Quratulain; Lungerich, Dominik; Jux, Norbert; Stark, Michael Werner; Kaftan, Andre; Ditze, Stefanie; Marbach, Hubertus; Laurin, Mathias; Libuda, Jörg; Steinrück, Hans-Peter; et al. (Journal of Physical Chemistry C, 2014)
Using temperature-programmed desorption (TPD), the self-metalation and dehydrogenation of deuterated 5,10,15,20-tetraphenyl-21,23D-porphyrin on Cu(111) has been studied, resulting in new insight into the metalation of porphyrins on surfaces. The metalation is found to proceed through the transfer of the central aminic hydrogen atoms to the Cu(111) surface and not, as suggested by gas phase calculations, through the combination of the hydrogen atoms to molecular hydrogen above the partially inserted metal center. This finding suggests that the metalation reaction could be significantly influenced by the stability of hydrogen on the substrate surface. The metalation reaction and the subsequent hydrogenation and dehydrogenation of theperiphery of the porphyrin molecule leading to hydrogen-deuterium exchange are modeled with a simple microkinetic reaction model. The model is able to d escribe the main features of the TPD spectra.

Insights into the surface composition and enrichment effects of ionic liquids and ionic liquid mixtures - Maier, Florian; Cremer, Till; Kolbeck, Claudia; Lovelock, Kevin; Paape, Natalia; Schulz, Peter; Wasserscheid, Peter; Steinrück, Hans-Peter (Physical Chemistry Chemical Physics, 2010)
A systematic study of ionic liquid surfaces by angle resolved X-ray photoelectron spectroscopy (ARXPS) is presented. By reviewing recent and presenting new results for imidazolium-based ionic liquids (ILs), we discuss the impact of chemical differences on surface composition and on surface enrichment effects. (1) For the hydrophilic ethylene glycol (EG) functionalised ILs [Me(EG)MIm][TfN], [Et(EG)MIm][TfN] and [Me(EG)MIm][TfN], which vary in the number of ethylene glycol units (from 1 to 3), we find that the surface composition of the near-surface region is in excellent agreement with the bulk composition, which is attributed to attractive interactions between the oxygen atoms on the cation to the hydrogen atoms on the imidazolium ring. (2) For [CC Im][TfN] (where n = 1-16), i.e. ILs with an alkyl chain of increasing length, an enrichment of the aliphatic carbons is observed for longer chains (n > 2), at the expense of the polar cation head groups and the anions in the first molecular layer, both of which are located approximately at the same distance from the outer surface. (3) To study the influence of the anion on the surface enrichment, we investigated ten ILs [CC Im][X] with the same cation, but very different anions [X] . In all cases, surface enrichment of the cation alkyl chains is found, with the degree of enrichment decreasing with increasing size of the anion, i.e., it is most pronounced for the smallest anions and least pronounced for the largest anions. (4) For the IL mixture [CC Im][TfN] and [CCIm][Tf N] we find a homogeneous distribution in the outermost surface region with no specific enrichment of the [CCIm] cation. © 2010 the Owner Societies.

In-situ core-level photoelectron spectroscopy of adsorbates on surfaces involving a molecular beam - General setup and first experiments - Denecke, Reinhard; Kinne, Martin; Whelan, Caroline; Steinrück, Hans-Peter (Surface Review and Letters, 2002)
In this contribution we introduce a new apparatus combining high-resolution photoelectron spectroscopy and supersonic molecular beam techniques designed to follow simple surface reactions like adsorption, desorption or oxidation in situ in a time- and temperature-resolved manner. Using high brightness synchrotron radiation high resolution core-level spectra can be obtained in less than 3 s. The molecular beam allows for local pressures of up to 1 · 10 mbar and translational energies of the molecules of up to 2 eV in the case of CO. Preliminary examples of CO adsorption on Pt(111) are shown, where kinetic parameters can be derived from the coverage dependence of the different adsorption sites.

In situ high-resolution XPS studies on adsorption of NO on Pt(1 1 1) - Zhu, Junfa; Kinne, Martin; Fuhrmann, Thomas; Denecke, Reinhard; Steinrück, Hans-Peter (Surface Science, 2003)
High-resolution X-ray photoelectron spectroscopy (XPS) and temperature-programmed XPS at BESSY II have been applied to investigate the adsorption and desorption of NO on a Pt(1 1 1) surface. The coverage and temperature-dependent bonding configurations of NO have been identified from adsorbate O 1s and substrate Pt 4f core-level photoemission spectra, which were collected in situ during NO uptake or heating with data collection times per spectrum between 4 and 7 s. At 110 K, NO molecularly adsorbs on Pt(1 1 1) and sequentially populates three different adsorption sites. Up to coverages of 0.25 ML, only fcc-hollow sites are occupied, leading to the formation of a (2 × 2)-NO adsorbate structure. As coverage increases, in addition on-top sites are populated until at 0.5 ML a (2 × 2)-2NO structure is formed, which also represents the saturation structure at 250 K. Further increasing the coverage at 110 K leads to the occupation of hcp-hollow sites; at saturation, a (2 × 2)-3NO structure is observed with a coverage of 0.75 ML. Upon heating, the desorption of NO from the hcp-hollow sites gives rise to a desorption peak at 190 K. Further heating induces the desorption of on-top NO species starting at 275 K and fcc-hollow NO species starting at 320 K. No dissociation takes place. © 2003 Elsevier Science B.V. All rights reserved.

In situ high-resolution X-ray photoelectron spectroscopy – Fundamental insights in surface reactions - Steinrück, Hans-Peter; Papp, Christian (Surface Science Reports, 2013)
Since the advent of third generation synchrotron light sources optimized for providing soft X-rays up to 2 keV, X-ray photoelectron spectroscopy (XPS) has been developed to be an outstanding tool to study surface properties and surface reactions at an unprecedented level. The high resolution allows identifying various surface species, and for small molecules even the vibrational fine structure can be resolved in the XP spectra. The high photon flux reduces the required measuring time per spectrum to the domain of a few seconds or even less, which enables to follow surface processes in situ. Moreover, it also provides access to very small coverages down to below 0.1% of a monolayer, enabling the investigation of minority species or processes at defect sites. The photon energy can be adjusted according to the requirement of a particular experiment, i.e., to maximize or minimize the surface sensitivity or the photoionization cross-section of the substrate or the adsorbate. For a few instruments worldwide, a next step forward was taken by combining in situ high-resolution spectrometers with supersonic molecular beams. These beams allow to control and vary the kinetic and internal energies of the incident molecules and provide a local pressure of up to 10 mbar, which can be switched on and off in a controllable way, thus offering a well-defined time structure to study adsorption or reaction processes. Herein, we will review some specific scientific aspects which can be addressed by in situ XPS in order to demonstrate the power and potential of the method: In particular, the following topics will be addressed: (1) The sensitivity of the binding energy to adsorption sites will be analyzed, using CO on metals as example. From measurements at different temperatures, the binding energy difference between different sites can be derived, and exchange processes between different adsorbate species at step edges can be followed. (2) The vibrational fine structure of adsorbed small hydrocarbon species on metal surfaces will be analyzed in detail. We will first introduce the linear coupling model, then discuss the properties of adsorbed methyl and of a number of other small hydrocarbons, and show that the vibrational signature can be used as fingerprint for identifying surface species. (3) It is demonstrated that the binding energy of equivalent atoms in a molecule can be differentially changed by adsorption to a substrate; this sensitivity to the local environment will be discussed for adsorbed ethylene, benzene and graphene. (4) By temperature programmed XPS, the thermal evolution of adsorbed species can be followed in great detail, allowing for the identification of reaction intermediates and the determination of their stabilities. (5) The investigation of reaction kinetics by isothermal XPS measurements will be discussed; here results for the oxidation of sulfur and of CO will be presented and the corresponding activation energies of the rate limiting steps will be determined. © 2013 Elsevier B.V.

In Situ Hydrolysis of Imine Derivatives on Au(111) for the Formation of Aromatic Mixed Self-Assembled Monolayers: Multitechnique Analysis of This Tunable Surface Modification - Luo, Ying; Bernien, Matthias; Hermanns, Christian Felix; Miguel, Jorge; Jaekel, Simon; Chang, Yin-Ming; Kuch, Wolfgang; Haag, Rainer; et al. (Langmuir, 2012)
This paper presents a novel method for preparing aromatic, mixed self-assembled monolayers (SAMs) with a dilute surface fraction coverage of protonated amine via in situ hydrolysis of C=N double bond on gold surface. Two imine compounds, (4'-(4-(trifluoromethyl)benzylideneamino) biphenyl-4-yl)methanethiol (CF3-C6H4-CH=N-C6H4- C6H4-CH2-SH, TFBABPMT) and (4'-(4-cyanobenzylideneamino)biphenyl-4-yl)methanethiol (CN-C6H4-CH=N-C6H4-C6H4-CH2-SH, CBABPMT), self-assembled on Au(111) to form highly ordered monolayers, which was demonstrated by infrared reflection absorption spectroscopy (IRRAS) and X-ray photoelectron spectroscopy (XPS). A nearly upright molecular orientation for CF3- and CN-terminated SAM was detected by near edge X-ray absorption fine structure (NEXAFS) measurements. Afterward, the acidic catalyzed hydrolysis was carried out in chloroform or an aqueous solution of acetic acid (pH = 3). Systematic studies of this hydrolysis process for CN-terminated SAM in acetic acid at 25 C were performed by NEXAFS measurements. It was found that about 30% of the imine double bonds gradually cleaved in the first 40 min. Subsequently, a larger hydrolysis rate was observed due to the freer penetration of acetic acid in the SAM and resultant more open molecular packing. Furthermore, the molecular orientation in mixed SAMs did not change during the whole hydrolysis process. This partially hydrolyzed surface contains a controlled amount of free amines/ammonium ions which can be used for further chemical modifications.

In Situ Investigation of the Cu/CH3NH3PbI3 Interface in Perovskite Device - Ding, Honghe; Yan, Kangrong; Li, Bairu; Hu, Wanpei; Jia, Lingbo; Zareen, Shah; Freiberger, Marie; Huang, Jianmin; Hu, Jun; Xu, Qian; Li, Yu; Yang, Shangfeng; et al. (Advanced Materials Interfaces, 2021)
In this study, the electronic properties and chemical stability of the Cu/CH3NH3PbI3 interface are investigated in situ by a combination of X-ray photoelectron spectroscopy and synchrotron radiation photoemission spectroscopy (SRPES). The morphology of Cu deposited perovskite surface is monitored by scanning electron microscopy. The results show that the Cu/CH3NH3PbI3 interface is very stable and no chemical reaction between Cu and the perovskite takes place. Moreover, a 0.45 eV interface dipole and a 0.15 eV upward band bending are obtained at the Cu/CH3NH3PbI3 interface. Based on these fundamental findings, a prototype of Cu/CH3NH3PbI3/NiOx/indium tin oxide solar cell device is constructed to check the power conversion efficiency (PCE) and device stability. Although no electron transport material is used in this device, it still exhibits decent performance. The PCE of the device reaches up to 9.99% and remains almost unchanged over a long-time (49 d) storage in a N2-filled glovebox. Through this study it is demonstrated that fundamental understanding of the interfacial structure of a perovskite solar cell is essential in pursuit of rational design of superior perovskite solar cells, and moreover, Cu is a promising electrode candidate for perovskite solar cells.
CRIS-Team Scopus Importer:2021-06-04
Keywords: interfacial structure; long-term storage stability; perovskite solar cells; photoemission spectroscopy; power conversion efficiencies

In-situ-Schwingungsspektroskopie zur Untersuchung der Aktivität und Adsorbatplatzbesetzung von Katalysator-Nanopartikeln - Libuda, Jörg; et al. (Angewandte Chemie, 2003)
UnivIS-Import:2015-03-09:Pub.2003.nat.dchph.ppc20.insitu

In-situ spectroscopic analysis of the traditional dyeing pigment Turkey red inside textile matrix - Meyer, Markus; Huthwelker, T.; Borca, C. N.; Meßlinger, Karl; Bieber, M.; Fink, Rainer; Späth, Andreas (2018)
Turkey red is a traditional pigment for textile dyeing and its use has been proven for various cultures within the last three millennia. The pigment is a dye-mordant complex consisting of Al and an extract from R. tinctorum that contains mainly the anthraquinone derivative alizarin. The chemical structure of the complex has been analyzed by various spectroscopic and crystallographic techniques for extractions from textiles or directly in solution. We present an in-situ study of Turkey red by means of mu-XRF mapping and NEXAFS spectroscopy on textile fibres dyed according to a traditional process to gain insight into the coordination chemistry of the pigment in realistic matrix. We find an octahedral coordination of Al that corresponds well to the commonly accepted structure of the Al alizarin complex derived from ex-situ studies.
EVALuna2:35772

In situ STXM investigations of pentacene-based OFETs during operation - Hub, Christian; Burkhardt, Martin; Halik, Marcus; Tzvetkov, G.; Fink, Rainer (Journal of Materials Chemistry, 2010)
Ultrathin pentacene-based organic field-effect transistors (OFETs) on commercially available silicon nitride membranes suitable for transmission X-ray experiments are demonstrated. The devices produced by high-vacuum deposition show excellent electronic performance ( = 0.6 cm V s, I = 10). STXM-experiments recorded with the PolLux microspectroscope correlate structural and electronic properties at highest spatial and spectral resolution while the OFET is operated. Local NEXAFS spectra are used to analyze the different orientations of the pentacene nanocrystals. Spectral changes due to modifications in the electronic structure during OFET operation can hardly be detected with the current setup. © The Royal Society of Chemistry 2010.

In situ synchrotron radiation X-ray microspectroscopy of polymer microcontainers - Graf-Zeiler, Birgit; Fink, Rainer; Tzvetkov, George (ChemPhysChem, 2011)
Direct, real-time analytical techniques that provide high-resolution information on the chemical composition and submicrometer structure of various polymer micro- and nanoparticles are in high demand in a range of life science disciplines. Synchrotron-based scanning transmission X-ray microspectroscopy (STXM) combines both local-spot chemical information (assessed via near-edge X-ray absorption fine structure spectroscopy) and imaging with resolution of several tens of nanometers, and thus can yield new insights into the nanoscale properties of these materials. Furthermore, this method allows in situ examination of soft-matter samples in aqueous/gaseous environments and under external stimuli, such as temperature, pressure, ultrasound, and light irradiation. This Minireview highlights some recent progress in the application of the STXM technique to study the temperature-dependent behavior of polymer core-shell microcapsules and to characterize the physicochemical properties of the supporting shells of gas-filled microbubbles in their natural hydrated state. Copyright © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Integrated X-ray photoelectron spectroscopy and DFT characterization of benzene adsorption on Pt(111), Pt(355) and Pt(322) surfaces - Zhang, Renqin; Hensley, Alyssa J.; Mcewen, Jean-Sabin; Wickert, Sandra; Darlatt, Erik; Fischer, Kristina; Schöppke, Matthias; Denecke, Reinhard; Streber, Regine; Lorenz, Michael Peter Andreas; Papp, Christian; Steinrück, Hans-Peter (Physical Chemistry Chemical Physics, 2013)
We systematically investigate the adsorption of benzene on Pt(111), Pt(355) and Pt(322) surfaces by high-resolution X-ray photoelectron spectroscopy (XPS) and first-principle calculations based on density functional theory (DFT), including van der Waals corrections. By comparing the adsorption energies at 1/9, 1/16 and 1/25 ML on Pt(111), we find significant lateral interactions exist between the benzene molecules at 1/9 ML. The adsorption behavior on Pt(355) and Pt(322) is very different. While on Pt(355) a step species is clearly identified in the C 1s spectra at low coverages followed by occupation of a terrace species at high coverages, no evidence for a step species is found on Pt(322). These different adsorption sites are confirmed by extensive DFT calculations, where the most favorable adsorption configurations on Pt(355) and Pt(322) are also found to vary: a highly distorted across the step molecule is found on Pt(355) while a less distorted configuration adjacent to the step molecule is deduced for Pt(322). The theoretically proposed C 1s core level binding energy shifts between these most favorable configurations and the terrace species are found to correlate well with experiment: for Pt(355), two adsorbate states are found, separated by ∼0.4 eV in XPS and 0.3 eV in the calculations, in contrast to only one state on Pt(322). © 2013 the Owner Societies.

Interaction between silver nanowires and CO on a stepped platinum surface - Streber, Regine; Tränkenschuh, Barbara; Schöck, Johannes; Papp, Christian; Steinrück, Hans-Peter; Mcewen, J. -S.; Gaspard, P.; Denecke, Reinhard (Journal of Chemical Physics, 2009)
We studied the interplay between Ag decoration of a stepped Pt(355) surface and CO adsorption by in situ high-resolution x-ray photoelectron spectroscopy. Varying amounts of Ag deposited at 300 K initially lead to a row-by-row growth starting from the lower Pt step edges. Such decoration of the step sites results in a change in the CO adsorption behavior. An apparent blocking of step sites for low CO coverages is attributed to a change in the electronic structure, resulting in a C 1s binding energy of CO at step sites being equal to that for CO at terrace on-top sites in the presence of Ag. Higher CO coverages induce the formation of embedded Ag clusters within the upper terraces, thus freeing up a part of the original Pt step sites for CO adsorption, as was derived by a comparison to density functional theory calculations in the corresponding surface models. © 2009 American Institute of Physics.

Interaction of cobalt(II) tetraarylporphyrins with a Ag(111) surface studied with photoelectron spectroscopy - Jux, Norbert; Maier, Florian; Steinrück, Hans-Peter; et al. (Journal of Physical Chemistry C, 2007)
The interaction of cobalt(II) tetraphenylporphyrin (CoTPP) and cobalt(II) tetrakis-(3,5-di-tert-butylphenyl)-porphyrin (CoTTBPP) with a Ag(111) surface has been investigated with photoelectron spectroscopy (XPS/ UPS). It is demonstrated that these adsorbed metal complexes are excellent model systems for studying the electronic interaction between a coordinated metal ion and a metal surface. The photoelectron spectra and work function data provide evidence that the electronic interaction between the cobalt ion and the silver surface results in a transfer of electron density from the surface to the ion. The presence of an additional electronic state located ∼1 eV above the singly occupied molecular orbital (SOMO) of the metalloporphyrins is consistent with a molecular orbital (MO) model of the Co-Ag interaction as is the fact that the energetic position of this state depends on the distance between the Co ion and the Ag surface. The adsorbate-induced work function changes for the saturated monolayers amount to -0.72 eV for CoTPP and -0.91 eV for CoTTBPP. For comparison, we also present data of monolayer films of tetraphenylporphyrin and zinc(II) tetraphenylporphyrin. © 2007 American Chemical Society.

Interaction of Ester-Functionalized Ionic Liquids with Atomically-Defined Cobalt Oxides Surfaces: Adsorption, Reaction and Thermal Stability - Xu, Tao; Wähler, Tobias; Vecchietti, Julia; Bonivardi, Adrian; Bauer, Tanja; Schwegler, Johannes; Schulz, Peter; Wasserscheid, Peter; Libuda, Jörg (ChemPhysChem, 2017)
Hybrid materials consisting of ionic liquid (ILs) films on supported oxides hold a great potential for applications in electronic and energy materials. In this work, we have performed surface science model studies scrutinizing the interaction of ester-functionalized ILs with atomically defined Co3O4(111) and CoO(100) surfaces. Both supports are prepared under ultra-high vacuum (UHV) conditions in form of thin films on Ir(100) single crystals. Subsequently, thin films of three ILs, 3-butyl-1-methyl imidazolium bis(trifluoromethyl-sulfonyl) imide ([BMIM][NTf2]), 3-(4-methoxyl-4-oxobutyl)-1-methylimidazolium bis(trifluoromethyl-sulfonyl) imide ([MBMIM][NTf2]), and 3-(4-isopropoxy-4-oxobutyl)-1-methylimidazolium bis(trifluoromethyl-sulfonyl) imide ([IPBMIM][NTf2]), were deposited on these surfaces by physical vapor deposition (PVD). Time-resolved and temperature-programmed infrared reflection absorption spectroscopy (TR-IRAS, TP-IRAS) were applied to monitor insitu the adsorption, film growth, and thermally induced desorption. By TP-IRAS, we determined the multilayer desorption temperature of [BMIM][NTf2] (360 +/- 5K), [MBMIM][NTf2] (380K) and [IPBMIM][NTf2] (380K). Upon deposition below the multilayer desorption temperature, all three ILs physisorb on both cobalt oxide surfaces. However, strong orientation effects are observed in the first monolayer, where the [NTf2](-) ion interacts with the surface through the SO2 groups and the CF3 groups point towards the vacuum. For the two functionalized ILs, the [MBMIM](+) and [IPBMIM](+) interact with the surface Co2+ ions of both surfaces via the CO group of their ester function. A very different behavior is found, if the ILs are deposited above the multilayer desorption temperature (400K). While for [BMIM][NTf2] and [MBMIM][NTf2] a molecularly adsorbed monolayer film is formed, [IPBMIM][NTf2] undergoes a chemical transformation on the CoO(100) surface. Here, the ester group is cleaved and the cation is chemically linked to the surface by formation of a surface carboxylate. The IL-derived species in the monolayer desorb at temperatures around 500 to 550K.
Keywords: chemical anchoring; cobalt oxide; ionic liquids; IRAS; thermal stability

Interaction of NO2 with Model NSR Catalysts: Metal-Oxide Interaction Controls Initial NOx Storage Mechanism - Desikusumastuti, Aine; Staudt, Thorsten; Qin, Zhihui; Happel, Markus; Laurin, Mathias; Lykhach, Yaroslava; Shaikhutdinov, Shamil; Rohr, Friedemann; Libuda, Jörg (ChemPhysChem, 2008)
Using scanning tunneling microscopy (STM), molecular-beam (MB) methods and time-resolved infrared reflection absorption spectroscopy (TR-IRAS), we investigate the mechanism of initial NO, uptake on a model nitrogen storage and reduction (NSR) catalyst. The model system is prepared by co-deposition of Pd metal particles and Ba-containing oxide particles onto an ordered alumina film on NiAl(110). We show that the metal-oxide interaction between the active noble metal particles and the No, storage compound in NSR model catalysts plays an important; role in the reaction mechanism. We suggest that strong interaction facilitates reverse spillover of activated oxygen species from the NOx storage compound to the metal. This process leads to partial oxidation of the metal nanoparticles and simultaneous stabilization of the surface nitrite intermediate.
Keywords: heterogeneous catalysis; IR spectroscopy; model catalysts; molecular beams; reaction mechanisms

Interaction of NO with alumina supported palladium model catalysts - Libuda, Jörg; et al. (Physical Chemistry Chemical Physics, 2003)
The interaction of NO with a well-defined supported Pd model catalyst has been investigated, employing a combination of IR reflection absorption spectroscopy (IRAS) and molecular beam methods. The model catalyst is based on an ordered Al2O3 film, grown on NiAl(110) and has been characterized in detail with respect to its geometric and electronic structure previously. In a first step the interaction of NO with the pure Al 2O3 model support is studied. It is observed that NO slowly decomposes at low surface temperature (100 K), resulting in the formation of a variety of NxOy surface species. The decomposition process involves strong structural transformations of the Al 2O3 film and is initiated at oxide defect sites. The adsorption of NO on the Pd/Al2O3 model system is explored systematically as a function of surface coverage and temperature. For NO adsorption on the Pd particles, characteristic absorption bands are identified by comparison with single crystal data, which are indicative of particle-specific sites such as edges and other defects. At 300 K and above NO dissociation occurs on the Pd particles, whereas the low-temperature decomposition channel on the alumina support is found to be strongly suppressed in the presence of the Pd particles. Finally, co-adsorption of NO with oxygen- and CO-precovered Pd particles is investigated. Preadsorbed oxygen results in the formation of a mixed adsorbate layer with an enhanced NO population of on-top sites on the particles. NO adsorption on a CO layer, on the other hand, gives rise to a compression of the CO layer and an enhanced population of on-top sites by CO.
UnivIS-Import:2015-03-09:Pub.2003.nat.dchph.ppc20.intera

Interaction of oxygen with palladium deposited on a thin alumina film - Libuda, Jörg; et al. (Surface Science, 2002)
The interaction of oxygen with Pd particles, vapor deposited onto a thin alumina film grown on a NiAl(1 1 0) substrate, was studied by STM, AES, LEED, XPS, TPD and molecular beam techniques. The results show that O2 exposure at 400-500 K strongly influences the oxide support. We suggest that the oxygen atoms formed by dissociation on the Pd surface can diffuse through the alumina film and react with the NiAl substrate underneath the Pd particles, thus increasing the thickness of the oxide film. The surface oxygen inhibits hydrogen adsorption, and readily reacts with CO at 300-500 K. For large and crystalline Pd particles, the system exhibits adsorption-desorption properties which are very similar to those of the Pd(1 1 1) single crystal surface. The molecular beam and TPD experiments reveal that, at low coverage, CO adsorbs slightly stronger on the smaller Pd particles, with an adsorption energy difference of ≈5-7 kJ mol-1 for 1 and 3-5 nm Pd particles studied. © 2002 Elsevier Science B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2002.nat.dchph.ppc20.intera
Keywords: Aluminum oxide; Carbon monoxide; Chemisorption; Oxidation; Palladium

Interactions Between the Room-Temperature Ionic Liquid [C(2)C(1)Im][OTf] and Pd(111), Well-Ordered Al2O3, and Supported Pd Model Catalysts from IR Spectroscopy - Schernich, Stefan; Kostyshyn, Dmytro; Wagner, Valentin; Taccardi, Nicola; Laurin, Mathias; Wasserscheid, Peter; Libuda, Jörg (Journal of Physical Chemistry C, 2014)
The interactions between ionic liquids and their supports determine many of their applications. The adsorption of the ionic liquid 1-ethyl-3-methylimidazolium trifluoromethanesulfonate [C2C1Im][OTf] on Pd(111), ordered Al2O3/NiAl(110), and Pd nanoparticles supported on Al2O3/NiAl(110) was investigated under ultrahigh vacuum (UHV) conditions using time-resolved infrared reflection absorption spectroscopy (TR-IRAS). On Pd, the [OTf]- anion stands up with its CF3 group directed toward the vacuum, whereas the anion is less clearly oriented on the oxide. We also find that strong interactions of the IL with the Pd result in migration of the IL from the oxide to the metal nanoparticles.

Interactions of imidazolium-based ionic liquids with oxide surfaces controlled by alkyl chain functionalization - Schernich, Stefan; Laurin, Mathias; Lykhach, Yaroslava; Tsud, Nataliya; Sobota, Marek; Skala, Tomas; Prince, Kevin C.; Taccardi, Nicola; Wagner, Valentin; Steinrück, Hans-Peter; Matolin, Vladimir; Wasserscheid, Peter; et al. (ChemPhysChem, 2013)
From a different angle: Thin films of functionalized ionic liquids are deposited on cerium oxides following a surface science approach. The functionalization of the alkyl chain changes its orientation with respect to the surface plane from normal to parallel. This then leads to a different surface chemistry at higher temperatures. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Interface Controls Spontaneous Crystallization in Thin Films of the Ionic Liquid [C2C1Im][OTf] on Atomically Clean Pd(111) - Schernich, Stefan; Wagner, Valentin; Taccardi, Nicola; Wasserscheid, Peter; Laurin, Mathias; Libuda, Jörg (Langmuir, 2014)
A total of 5-30 monolayer thick films of the ionic liquid (IL) [C2C1Im][OTf] were vaporized in vacuo onto an atomically clean Pd(111) single crystal surface at 220 K. Time- and temperature-resolved infrared reflection-absorption spectroscopy reveals growth, interactions with the metallic support, and the macroscopic phase behavior of the layer. At 220 K, the IL layer first grows in the form of a glassy phase. Crystallization of the IL was witnessed above a critical thickness of about 10 monolayers. On the basis of the known bulk crystal structure of the IL, we suggest the formation of well-oriented checkerboard-like crystalline film structures on the surface. The preferential orientation manifested by the crystal phase with regard to the macroscopic metallic surface is attributed to strong interactions between anionic headgroups and the metal.

Interface Engineering of Molecular Charge Storage Dielectric Layers for Organic Thin-Film Memory Transistors - Khassanov, Artöm; Schmaltz, Thomas; Steinrück, Hans-Peter; Magerl, Andreas; Hirsch, Andreas; Halik, Marcus (Advanced Materials Interfaces, 2014)
Mixed self-assembled monolayers of C60-functionalized and different long-chained insulating phosphonic acids provide molecular scale non-volatile memory dielectrics for low-voltage organic thin-film transistors. The memory retention depends on the insulation of the C60 moiety and can be improved by embedding into the insulating SAM matrix and covering by corresponding insulating molecules.

Interface formation between calcium and electron-irradiated poly(3-hexylthiophene) - Bebensee, Fabian; Zhu, Junfa; Baricuatro, J. H.; Farmer, Jason A.; Bai, Yun; Steinrück, Hans-Peter; Campbell, C. T.; Gottfried, Michael (Langmuir, 2010)
The adsorption of Ca on electron-irradiated poly(3-hexylthiophene) (P3HT) surfaces at 300 K (E = 100 eV) has been studied by adsorption microcalorimetry, atomic beam/surface scattering, X-ray photoelectron spectroscopy (XPS), and low-energy He ion scattering spectroscopy (LEIS). The results are compared to previous studies of Ca adsorption on pristine P3HT. The major structural effect of electron irradiation is a substantial increase in the fraction of unsaturated carbon atoms, probably a result of electron-induced hydrogen abstraction from the hexyl chains and formation of new C=C double bonds. No loss of sulfur was observed. The combined XPS, LEIS, and calorimetry data indicate that the reaction and growth behavior of Ca on P3HT surfaces is not significantly affected by this electron damage, apart from an increased sticking probability at low coverages. The sticking probability of Ca on the irradiated P3HT is initially 0.63, compared to 0.36 on the pristine surface. It increases with coverage, approaching unity between 4 and 5 ML. The heat of adsorption stays nearly constant at 405 kJ/mol up to a coverage of 0.6 ML, which is ascribed to Ca diffusing below the surface and forming CaS clusters by abstraction of sulfur from the thiophene rings, based on XPS and LEIS data. The heat of adsorption then decreases gradually until it reaches the heat of sublimation of bulk Ca, 178 kJ/mol, by 4 ML; this is attributed to the formation of 3D Ca islands on top of the polymer, which eventually coalesce into a continuous Ca film by 11 ML. The heat of reaction versus coverage and the ultimate depth up to which the Ca atoms react with the polymer thiophene groups (∼3 nm) are nearly independent of electron damage, except for a difference in the heat of adsorption below 0.1 ML associated with defects or impurities. The increase in initial sticking probability caused by electron damage is attributed to stronger bonding of Ca adatoms to unsaturated versus saturated hydrocarbons. These very weakly held Ca adatoms are transient precursors to the two reactions which dominate the measured heat of adsorption (reaction with thiophene units and Ca cluster formation), but they can also desorb in this three-path kinetic competition. Mass spectrometer data show that these precursors have longer surface residence times on the electron-damaged surface. © 2010 American Chemical Society.

Interface of Ionic Liquids and Carbon: Ultrathin [C1C1Im][Tf2N] Films on Graphite and Graphene - Rietzler, Florian; Nagengast, Jens; Steinrück, Hans-Peter; Maier, Florian (Journal of Physical Chemistry C, 2015)
We investigated the initial adsorption behavior and growth of thin films of ionic liquid (IL) [CCIm][TfN] on highly ordered pyrolytic graphite (HOPG) and on a full and a fractional graphene layer on Ni(111). We found that the initial adsorption behavior and growth strongly depended on the underlying substrate. On HOPG, the IL forms an initial wetting layer with a coverage of 0.5 ML and anions and cations next to each other in direct contact with the substrate. On a complete graphene layer on Ni(111), the wetting layer has twice the thickness with alternately oriented ion pairs next to each other. On top of these wetting layers, further IL growth occurs in 3D islands, with the island formation being less pronounced on the graphene layer. On the fractional graphene layer on Ni(111), initial IL adsorption preferentially occurs on bare Ni surface areas, with anions on top of cations, followed by 3D island growth on both the bare and the graphene-covered surface regions.

Interface properties and physicochemical characterization of the low-temperature molten salt Li/K/Cs acetate - Deyko, Alexey; Bajus, Stephanie; Rietzler, Florian; Bösmann, Andreas; Wasserscheid, Peter; Steinrück, Hans-Peter; Maier, Florian (Journal of Physical Chemistry C, 2013)
The surface of macroscopic films of the ternary molten salt mixture Li KCs[OAc] has been investigated by angle-resolved X-ray photoelectron spectroscopy (XPS) as a function of temperature. With increasing temperature a preferential depletion of K is observed by ∼40%. From temperature programmed desorption we find that the onset for the cation desorption follows the order Cs, K, and Li, with activation energies of 125, 148, and 157 kJ mol, respectively; the corresponding value for the [OAc] anion is 147 kJ mol, which is, within the margin of error, identical to the average of the value found for the cations. Ultrathin films of the molten salt deposited on a Au(111) surface by physical vapor deposition show preferential enrichment of Cs, in line with the lower activation energy and thus higher desorption rate of Cs[OAc] from the ternary mixture. Angle-resolved XPS of the molten salt/gold interface demonstrates that the first molten salt monolayer grows in a layer-by-layer growth, followed by three-dimensional island growth at higher coverages. © 2013 American Chemical Society.

Interfaces of ionic liquids and transition metal surfaces - Adsorption, growth, and thermal reactions of ultrathin [C 1C 1Im] [Tf 2N] films on metallic and oxidised Ni(111) surfaces - Cremer, Till; Wibmer, Leonie; Krick Calderon, Sandra; Deyko, Alexey; Maier, Florian; Steinrück, Hans-Peter (Physical Chemistry Chemical Physics, 2012)
Ultrathin films of the ionic liquid 1,3-dimethylimidazolium bis(trifluoromethylsulfonyl)imide ([C C Im][Tf N]) were deposited on differently terminated Ni(111) single crystal surfaces. The initial wetting behaviour, the growth characteristics, the molecular arrangement at the interface, and thermal reactivity were investigated using angle-resolved X-ray photoelectron spectroscopy (ARXPS). On clean Ni(111), the initial growth occurs in a layer-by-layer mode. At submonolayer coverages up to at least 0.40 ML, a preferential arrangement of the IL ions in a bilayer structure, with the imidazolium cations in contact with the Ni surface atoms and the anions on top of the cation, is deduced. For higher coverages, a transition to a checkerboard-type arrangement occurs, which is most likely due to repulsive dipole-dipole interactions in the first layer. An overall preference for a checkerboard-type adsorption behaviour, i.e., anions and cations adsorbing next to each other, is found on the oxygen-precovered O(√3×√3)R30°Ni(111) surface. The thermal stability of adsorbed IL layers on Ni(111) and on a fully oxidised Ni(111) surface was studied by heating the layers to elevated temperatures. For clean Ni(111) reversible adsorption takes place. For the oxidised surface, however, only cation-related moieties desorb, starting at ∼450 K, while anion-related signals remain on the surface up to much higher temperatures. © 2012 the Owner Societies.

Interfacial behavior of thin ionic liquid films on mica - Deyko, Alexey; Cremer, Till; Rietzler, Florian; Perkin, Susan; Crowhurst, Lorna; Welton, Tom; Steinrück, Hans-Peter; Maier, Florian (Journal of Physical Chemistry C, 2013)
Ultrathin films of two imidazolium-based ionic liquids (ILs), [C CIm][TfN] (=1-methyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide) and [CCIm][Tf N] (=1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide) were deposited on mica surfaces by physical vapor deposition in ultrahigh vacuum. Using angle-resolved X-ray photoelectron spectroscopy (ARXPS), the initial wetting behavior, the growth characteristics, and the molecular arrangement of the ions at the interface were investigated. The measurements were performed on freshly air-cleaved mica surfaces with different carbon precoverages. ARXPS clearly reveals that the initial IL adsorption behavior strongly depends on the amount of preadsorbed carbon: On clean mica, 3D growth (complete dewetting) occurs, whereas on a fully carbon covered surface, initially a complete 2D wetting layer forms, followed by 3D growth. © 2013 American Chemical Society.

Interfacial coordination interactions studied on cobalt octaethylporphyrin and cobalt tetraphenylporphyrin monolayers on Au(111) - Bai, Yun; Sekita, Michael; Schmid, Martin; Bischof, Thomas; Steinrück, Hans-Peter; Gottfried, Michael (Physical Chemistry Chemical Physics, 2010)
Monolayers and multilayers of cobalt octaethylporphyrin (CoOEP), cobalt tetraphenylporphyrin (CoTPP) and the corresponding free-base porphyrins 2HOEP and 2HTPP on an Au(111) surface were investigated with X-ray and UV photoelectron spectroscopy (XPS and UPS). For CoTPP and CoOEP monolayers, the XP spectra show a characteristic splitting of the Co 2p signal, which suggests that only a fraction of the Co ions forms coordinative bonds to the Au(111) surface, while the others interact more weakly. This is a remarkable difference to previous results for CoOEP and CoTPP on Ag(111), where all Co ions in the monolayer were found to interact strongly and uniformly with the silver surface. Presumably, the lateral structural and electronic inhomogeneities of the reconstructed Au(111) surface are responsible for the more complex interaction behaviour on the gold surface. UP spectra of CoOEP and CoTPP monolayers show a new electronic state around 0.3 eV below the Fermi energy (E), i.e., at lower binding energy than in the case of Ag(111), where a strong signal appeared at 0.6 eV below E. In contrast, the free-base porphyrins 2HOEP and 2HTPP show no additional valence states in the monolayer, indicating that the Co ion plays a central role in the electronic interaction between the metal complexes and the substrate. These results have important implications for metal/organic interfaces in organic electronics or photovoltaic devices based on π-conjugated semiconducting metal complexes, because the character of the chemical bond at the interface determines important parameters such as charge injecting rates. © 2010 the Owner Societies.

Interfacial interactions between CoTPP molecules and MgO(100) thin films - Franke, Matthias; Wechsler, Daniel; Tariq, Quratulain; Röckert, Michael; Zhang, Liang; Thakur, Pardeep Kumar; Tsud, Nataliya; Bercha, Sofiia; Prince, Kevin; Lee, Tien-Lin; Steinrück, Hans-Peter; Lytken, Ole (Physical Chemistry Chemical Physics, 2017)
We have investigated the interactions between cobalt(II)-tetraphenylporphyrin (CoTPP) molecules and MgO( 100) thin films on Ag(100) by means of Synchrotron Radiation X-Ray and Ultra-Violet Photoelectron Spectroscopy (SR-XPS and SR-UPS). At room temperature, the CoTPP monolayer consists of two different species. A minority of molecules exhibits a strong electronic interaction with the substrate, whereas for the majority a similar spectroscopic signature as for multilayer molecules is observed. Based on the lateral inhomogeneity of the surface electronic structure, we tentatively suggest that the strongly interacting molecules adsorb with their metal center directly above oxygen ions. Unlike for metal substrates, where a monolayer can be prepared upon heating to above 500 K, most of the monolayer on MgO desorbs at 550 K together with the multilayers. This indicates either a weaker molecule- substrate bond than for most metal surfaces or a higher activation energy barrier for dehydrogenation. The remaining molecules are presumably MgTPP molecules, originating from a 2HTPP impurity in CoTPP.

Interfacial interactions of iron(II) tetrapyrrole complexes on Au(111) - Schmid, Martin; Zirzlmeier, Johannes; Steinrück, Hans-Peter; Gottfried, J. Michael (Journal of Physical Chemistry C, 2011)
The electronic structure of monolayers of iron(II) phthalocyanine (FePc), iron(II) octaethylporphyrin (FeOEP), and iron(II) tetraphenylporphyrin (FeTPP), adsorbed on Au(111), was examined with X-ray and UV photoelectron spectroscopy (XPS/UPS). Comparison of the Fe 2p signals of FePc multilayers and monolayers revealed an additional component in the monolayer signal with a binding energy characteristic of Fe(0). This component accounts for ∼20% of the integral Fe 2p intensity, in agreement with previous observations on cobalt porphyrins on Au(111). The partial modification of the Fe 2p states suggests a laterally inhomogeneous interaction of the adsorbed molecules with the metal surface and is possibly related to the complex, reconstructed Au(111) surface morphology. Similar results obtained for FeTPP and FeOEP monolayers indicate that this effect is independent from the structure of the peripheral substituents on the core porphin moiety. The UP spectra of FePc and FeTPP monolayers show further indications for a substrate-molecule interaction mediated by the central Fe atom. In addition, FePc, FeTPP, and 2HTPP monolayers lead to a complete depopulation of the Shockley surface state of the clean Au(111) surface. © 2011 American Chemical Society.

Interfacial Reactions of Tetraphenylporphyrin with Cobalt-Oxide Thin Films - Wechsler, Daniel; Fernandez, Cynthia C.; Tariq, Quratulain; Tsud, Nataliya; Prince, Kevin C.; Williams, Federico Jose; Steinrück, Hans-Peter; Lytken, Ole (Chemistry - A European Journal, 2019)
We have studied the adsorption and interfacial reactions of 2H-tetraphenylporphyrin (2HTPP) with cobalt-terminated Co3O4(111) and oxygen-terminated CoO(111) thin films using synchrotron-radiation X-ray photoelectron spectroscopy. Already at 275 K, we find evidence for the formation of a metalated species, most likely CoTPP, on both surfaces. The degree of self-metalation increases with temperature on both surfaces until 475 K, where the metalation is almost complete. At 575 K the porphyrin coverage decreases drastically on the reducible cobalt-terminated Co3O4(111) surface, while higher temperatures are needed on the non-reducible oxygen-terminated CoO(111). The low temperature self-metalation is similar to that observed on MgO(100) surfaces, but drastically different from that observed on TiO2(110), where no self-metalation is observed at room temperature.
CRIS-Team WoS Importer:2019-10-04

Interplay between the metal- support interaction and stability in Pt/ Co3O4(111) model catalysts - Lykhach, Yaroslava; Faisal, Firas; Skala, Tomas; Neitzel, Armin; Tsud, Nataliya; Vorokhta, Mykhailo; Dvorak, Filip; Beranova, Klara; Kosto, Yuliia; Prince, Kevin C.; Matolin, Vladimir; Libuda, Jörg (Journal of Materials Chemistry A, 2018)
The interplay between the metal-support interaction and stability with respect to sintering has been investigated for Pt nanoparticles supported on well-ordered Co3O4(111)/Ir(100) films in UHV and under oxidizing conditions by means of synchrotron radiation photoelectron spectroscopy (SRPES) and near ambient pressure X-ray photoelectron spectroscopy (NAP XPS). The electronic metal-support interaction between Pt and Co3O4(111) associated with charge transfer results in partial reduction of Co3O4(111) yielding partially oxidized Pt+ species at the interface. The stability of the supported Pt particles is coupled with the oxidation state of Pt+ species, which can be reduced or oxidized depending on the Pt coverage and reactive environment. Annealing of Pt/Co3O4(111)/Ir(100) in UHV triggers the reduction of Pt+ species. At higher temperature, reverse spillover of oxygen to the Pt nanoparticles is accompanied by reduction of Co3O4(111). Under these conditions, the oxidation state of Pt+ species depends strongly on Pt coverage. Thus, at low Pt coverage (0.3 ML Pt), Pt+ is converted to Pt4+, at intermediate coverage (1.3 ML Pt), Pt+ remains stable, and at high Pt coverage (1.93 ML), Pt+ is reduced to Pt-0. Sintering of Pt particles is associated with the reduction of the Pt+ species. This process is prevented under oxidizing conditions due to the formation of an interfacial oxide PtOx. The formation of an interfacial PtOx is observed at 300 K under exposure to 1 x 10(-6) mbar O-2 at Pt coverages below 1.3 ML. Using NAP XPS, we observe the formation of an interfacial PtOx at high Pt coverage (2.0 ML) in an oxygen atmosphere (1 mbar) at 300 K while the formation of surface PtOx is kinetically hindered and occurs above 550 K only.

"Inverted'' porphyrins: a distorted adsorption geometry of free-base porphyrins on Cu(111) - Lepper, Michael; Köbl, Julia; Schmitt, Tobias; Gurrath, Martin; De Siervo, Abner; Schneider, M. Alexander; Steinrück, Hans-Peter; Meyer, Bernd; Marbach, Hubertus; Hieringer, Wolfgang (Chemical Communications, 2017)
Based on density functional theory calculations combined with experimental results, we report and discuss an extremely distorted, "inverted'' adsorption geometry of free-base tetraphenylporphyrin on Cu(111). The current findings yield new insights into a wellstudied system, shedding light on the peculiar molecule-substrate interaction and the resulting intramolecular conformation.

Investigation of proximity effects in electron microscopy and lithography - Walz, Marie-Madeleine; Vollnhals, Florian; Rietzler, Florian; Schirmer, Michael; Steinrück, Hans-Peter; Marbach, Hubertus (Applied Physics Letters, 2012)
A fundamental challenge in lithographic and microscopic techniques employing focused electron beams are so-called proximity effects due to unintended electron emission and scattering in the sample. Herein, we apply a method that allows for visualizing electron induced surface modifications on a SiN substrate covered with a thin native oxide layer by means of iron deposits. Conventional wisdom holds that by using thin membranes proximity effects can be effectively reduced. We demonstrate that, contrary to the expectation, these can be indeed larger on a 200 nm SiN-membrane than on the respective bulk substrate due to charging effects. © 2012 American Institute of Physics.

Investigation of the foil structure and corrosion mechanisms of modern Zwischgold using advanced analysis techniques - Wu, Qing; Soppa, Karolina; Scherrer, Nadim; Watts, Benjamin; Yokosawa, Tadahiro; Bernard, Laetitia; Araki, Tohru; Doebeli, Max; Meyer, Markus; Spiecker, Erdmann; Fink, Rainer (Journal of Cultural Heritage, 2018)
Zwischgold is a two-sided metal foil made by adhering a gold leaf over a silver leaf to present a gold surface while using less gold than gold foils. Corroded Zwischgold surfaces appear dark, accompanied by gloss loss and possible mechanical stability issues. Zwischgold applied artefacts are commonly found in museums and churches across Europe and they currently face an uncertain future as conservators have little knowledge to base conservation treatments on. We present a comprehensive material analysis of Zwischgold models through advanced characterization techniques including focused ion beam coupled with scanning electron microscopy (FIB-SEM), transmission electron microscopy (TEM), scanning transmission X-ray microscopy (STXM), time-of-flight secondary ion mass spectrometry (TOF-SIMS) and Rutherford backscattering spectrometry (RBS). Complementary information on the foil thickness, sharpness of the gold-silver interface, gold purity, and the formation as well as distribution of corrosion products on Zwischgold models have been obtained, representing a starting point for understanding the morphology and the long-term chemistry of Zwischgold artefacts.
Keywords: Zwischgold; Interdiffusion; Gold; Silver; Corrosion; Conservation

Ionic liquid adsorption and ion exchange processes at single crystal surfaces - Steinrück, Hans-Peter (ABSTRACTS OF PAPERS OF THE AMERICAN CHEMICAL SOCIETY, 2019)
CRIS-Team WoS Importer:2019-08-23

Ionic liquid based model catalysis: Interaction of [BMIM][Tf2N] with Pd nanoparticles supported on an ordered alumina film - Sobota, Marek; Schmid, Martin; Happel, Markus; Amende, Maximilian; Maier, Florian; Steinrück, Hans-Peter; Paape, Natalia; Wasserscheid, Peter; Laurin, Mathias; Gottfried, Michael; Libuda, Jörg (Physical Chemistry Chemical Physics, 2010)
Towards a better understanding of novel catalytic materials consisting of supported noble metal catalysts modified by an ionic liquid (IL) film, we have performed a study under ultrahigh-vacuum (UHV) conditions. The model surface consists of Pd nanoparticles grown in UHV on an ordered alumina film on NiAl(110). Thin films of the room temperature IL 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide [BMIM][TfN] are deposited onto this surface by means of physical vapor deposition (PVD). The interaction of the IL with clean and CO-covered Pd/AlO/NiAl(110) at 300 K and the thermal behavior of the deposited IL films on Pd/AlO /NiAl(110) are investigated by time-resolved infrared reflection absorption spectroscopy (TR-IRAS) and X-ray photoelectron spectroscopy (XPS). At 300 K, the IL adsorbs molecularly both onto the Pd particles and onto the alumina. The IR spectra suggest that the [TfN] anions interact with Pd sites preferentially via the sulfonyl groups. CO pre-adsorbed on the Pd particles is partially displaced by the IL, even at 300 K, and only the part of CO adsorbed onto hollow sites on (111) facets of the Pd particles remains in place. Upon heating to temperatures higher than the desorption temperature of the IL (>400 K), molecular desorption of the IL competes with decomposition. The decomposition products, atomic species and small fragments, remain preferentially adsorbed onto the Pd nanoparticles and strongly modify their surface properties. Most of the decomposition products originate from the [BMIM] cations, whereas the [TfN] anions desorb for the most part. © 2010 the Owner Societies.

Ionic Liquid-Modified Electrocatalysts: The Interaction of [C1C2Im][OTf] with Pt(1 1 1) and its Influence on Methanol Oxidation Studied by Electrochemical IR Spectroscopy - Brummel, Olaf; Faisal, Firas; Bauer, Tanja; Pohako-Esko, Kaija; Wasserscheid, Peter; Libuda, Jörg (Electrochimica Acta, 2016)
Ionic liquids (ILs) have recently been proposed as modifying agents to tune the selectivity and the activity of electrocatalysts. In order to explore the origin of IL-induced effects on electrocatalytic reactions, we have investigated (i) the interaction of [CCIm][OTf]-water mixtures with Pt(1 1 1) single crystal electrodes and (ii) the influence of [CCIm][OTf] on methanol oxidation in acidic aqueous solution using cyclic voltammetry (CV) and electrochemical IR spectroscopy. We show that [CCIm][OTf] interacts strongly with the Pt(1 1 1) surface in the potential range from -0.2 V to 0.65 V, leading to partial blocking of the surface, partial suppression of hydrogen adsorption, and partial suppression of OH formation. The interaction of the IL with Pt occurs in this potential range via specific adsorption of the [OTf] anions which bind to Pt(1 1 1) via the SO group in a tilted adsorption geometry. The adsorption process is largely reversible as a function of the electrode potential, but shows a complex kinetics and becomes very slow at high IL coverage. Also, [CCIm][OTf] has a strong effect on the electro-oxidation of methanol in acidic solution. Adsorption of [OTf] leads to partial blocking of the indirect oxidation pathway to CO. The onset potential for CO oxidation is found to be shifted to more positive values indicating hindered access of HO to the electrode surface. CO and the [CCIm][OTf] form a mixed co-adsorption layer which is characterized by a strongly red-shifted CO stretching band. The effect is assigned to an IL-induced ligand effect in the mixed adsorbate layer and suggests that the direct modification of active centers by surface-bound IL species plays an important role in IL-modified electrocatalytic materials.
Keywords: carbon monoxide; electrochemical IR spectroscopy; Ionic liquids; methanol oxidation; platinum

Ionic-Liquid-Modified Hybrid Materials Prepared by Physical Vapor Codeposition: Cobalt and Cobalt Oxide Nanoparticles in [C(1)C(2)Im][OTf] Monitored by In Situ IR Spectroscopy - Mehl, Sascha; Bauer, Tanja; Brummel, Olaf; Pohako-Esko, Kaija; Schulz, Peter; Wasserscheid, Peter; Libuda, Jörg (Langmuir, 2016)
The synthesis of ionic-liquid-modified nanomaterials has, attracted much attention recently. In this study we explore the potential to prepare such systems in an ultraclean fashion by physical vapor codeposition (PVCD). We codeposit metallic cobalt and the room-temperature ionic liquid (IL) 1-ethyl-3-methylimidazolium trifluoromethanesulfonate [C(1)C(2)Im][OTf] simultaneously onto a Pd(111) surface at 100 K. This process is performed under ultrahigh-vacuum (UHV) conditions in the presence of CO, or in the presence of O-2 and CO. We use time-resolved (TR) and temperature-programmed (TP) infrared reflection absorption spectroscopy (IRAS) to investigate the formation and stability of the IL-modified Co deposits in situ during the PVD-based synthesis. CO is used as a probe molecule to monitor the growth. After initial growth of flat Co films on Pd(111), multilayers of Co nanoparticles (NPs) are formed. Characteristic shifts and intensity changes are observed in the vibrational bands of both CO and the IL, which originate from the electric field at the IL/Co interface (Stark effect) and from specific adsorption of the [OTf](-) anion. These observations indicate that the Co aggregates are stabilized by mixed adsorbate shells consisting of CO and [OTf](-). The CO coverage on the Co particle decreases with increasing temperature, but some CO is preserved up to the desorption temperature of the IL (370 K). Further, the IL shell suppresses the oxidation of the Co NPs if oxygen is introduced in the PVCD process. Only chemisorbed oxygen is formed at oxygen partial pressures that swiftly lead to formation of Co3O4 in the absence of the IL (5 X 10(-6) mbar O-2). This chemisorbed oxygen is found to destabilize the CO ligand shell. The oxidation of Co is not suppressed if IL and Co are deposited sequentially under otherwise identical conditions. In this case we observe the formation of fully oxidized cobalt oxide particles.

Ionic Liquids in Catalysis - Wasserscheid, Peter; Steinrück, Hans-Peter (Catalysis Letters, 2015)
Ionic liquids (ILs), salts with melting points below 100 °C, represent a fascinating class of liquid materials typically characterized by an extremely low vapor pressure. Besides their application as new solvents or as electrolytes for electrochemical purposes, there are two important concepts of using ILs in catalysis: Liquid–liquid biphasic catalysis and IL thin film catalysis. Liquid–liquid biphasic catalysis enables either a very efficient manner to apply catalytic ILs, e.g. in Friedel–Crafts reactions, or to apply ionic transition metal catalyst solutions. In both cases, phase separation after reaction allows an easy separation of reaction products and catalyst re-use. One problem of liquid–liquid biphasic catalysis is mass transfer limitation. If the chemical reaction is much faster than the liquid–liquid mass transfer the latter limits the overall reaction rate. This problem is overcome in IL thin film catalysis where diffusion pathways and thus the characteristic time of diffusion are short. Here, Supported Ionic Liquid Phase (SILP) and Solid Catalyst with Ionic Liquid Layer (SCILL) are the two most important concepts. In both, a high surface area solid substrate is covered with a thin IL film, which contains either a homogeneously dissolved transition metal complex for SILP, or which modifies catalytically active surface sites at the support for SCILL. In each concept, interface phenomena play a very important role: These may concern the interface of an IL phase with an organic phase in the case of liquid–liquid biphasic catalysis. For IL thin film catalysis, the interfaces of the IL with the gas phase and with catalytic nanoparticles and/or support materials are of critical importance. It has recently been demonstrated that these interfaces and also the bulk of ILs can be investigated in great detail using surface science studies, which greatly contributed to the fundamental understanding of the catalytic properties of ILs and supported IL materials. Exemplary results concerning the IL/vacuum or IL/gas interface, the solubility and surface enrichment of dissolved metal complexes, the IL/support interface and the in situ monitoring of chemical reactions in ILs are presented.
Keywords: Heterogeneous catalysis; Catalysis; Homogeneous catalysis; Green chemistry; Evaporation; Methodology and Phenomena; XPS; Spectroscopy and General Characterisation; Ionic liquids; Preparation and Materials

Iron assisted formation of CO2 over condensed CO and its relevance to interstellar chemistry - Methikkalam, Rabin Rajan J.; Ghosh, Jyotirmoy; Bhuin, Radha Gobinda; Bag, Soumabha; Ragupathy, Gopi; Pradeep, Thalappil (Physical Chemistry Chemical Physics, 2020)
Catalytic conversion of CO to CO2 has been investigated in ultrahigh vacuum (UHV) under cryogenic conditions (10 K). This cryogenic oxidation is assisted by iron upon its co-deposition with CO, on a substrate. The study shows that the interaction of Fe and CO results in a Fe-CO complex that reacts in the presence of excess CO at cryogenic conditions leading to CO2. Here, the presence of CO on the surface is a prerequisite for the reaction to occur. Different control experiments confirm that the reaction takes place in the condensed phase and not in the gas phase. Surface sensitive reflection absorption infrared spectroscopy (RAIRS), temperature programmed desorption (TPD), and Cs+ based low energy ion scattering are utilized for this study. The iron assisted formation of CO2 may be proposed as another pathway relevant in interstellar ices, containing CO. This direct oxidation process, which occurs at extremely low temperatures and pressures, in the presence of a reactive metal species like iron (the most abundant metal in the interstellar medium) may have astrochemical importance. It does not require any external energy in the form of photo-irradiation or thermal processing. Such reactions are highly relevant in cold dense molecular clouds where interactions between neutral species are more favoured.
CRIS-Team WoS Importer:2020-06-16

Isolated Rh atoms in dehydrogenation catalysis - Wittkämper, Haiko; Hock, Rainer; Weißer, Matthias; Dallmann, Johannes; Vogel, Carola; Raman, Narayanan; Tacardi, Nicola; Haumann, Marco; Wasserscheid, Peter; Hsieh, Tzung En; Maisel, Sven; Moritz, Michael; et al. (Scientific Reports, 2023)
Isolated active sites have great potential to be highly efficient and stable in heterogeneous catalysis, while enabling low costs due to the low transition metal content. Herein, we present results on the synthesis, first catalytic trials, and characterization of the Ga9Rh2 phase and the hitherto not-studied Ga3Rh phase. We used XRD and TEM for structural characterization, and with XPS, EDX we accessed the chemical composition and electronic structure of the intermetallic compounds. In combination with catalytic tests of these phases in the challenging propane dehydrogenation and by DFT calculations, we obtain a comprehensive picture of these novel catalyst materials. Their specific crystallographic structure leads to isolated Rhodium sites, which is proposed to be the decisive factor for the catalytic properties of the systems.
CRIS-Team Scopus Importer:2023-03-31

Isomerization and hydrogenation of cis-2-butene on Pd model catalyst - Brandt, Bjoern; Fischer, Jan-Henrik; Ludwig, Wiebke; Libuda, Jörg; Zaera, Francisco; Schauermann, Swetlana; Freund, Hans-Joachim (Journal of Physical Chemistry C, 2008)
The adsorption and kinetics of conversion of cis-2-butene with deuterium on model supported Pd catalyst (Pd/Fe3O4/Pt(111)) were characterized by reflection-absorption infrared spectroscopy (RAIRS), temperature-programmed desorption (TPD), and isothermal molecular beam (MB) experiments. It was found that selectivity toward cis-trans isomerization and hydrogenation depends critically on the nature of the carbonaceous deposits, which are typically present during reaction on real catalysts. At low temperatures (190-210 K) both reaction pathways were found to proceed on the initially clean surface, but the catalytic activity was observed to quickly vanish, presumably because of the accumulation of hydrocarbon species on the surface. At temperatures above 250 K, on the other hand, a sustained catalytic activity toward cis-trans isomerization was observed over long periods of time. Interestingly, no catalytic activity could be sustained for the competing hydrogenation on the initially clean catalyst even at these temperatures. Only when highly dehydrogenated carbonaceous fragments were preadsorbed on the surface was it possible to induce a persistent catalytic activity for the hydrogenation (and also the isomerization) of the alkene on our supported palladium particles. Possible reasons of this unique vacuum catalytic behavior are discussed, including different spatial requirements for the competing reaction pathways and changes in the adsorption state of deuterium on and beneath the surface modified by the carbonaceous deposits.

Isothermal Kinetic Study of Nitric Oxide Adsorption and Decomposition on Pd(111) Surfaces: Molecular Beam Experiments - Libuda, Jörg; et al. (Journal of Physical Chemistry B, 2005)
The kinetics of NO adsorption and dissociation on Pd(111) surfaces and the NO sticking coefficient (sNO) were probed by isothermal kinetic measurements between 300 and 525 K using a molecular beam instrument. NO dissociation and N2 productions were observed in the transient state from 425 K and above on Pd(111) surfaces with selective nitrogen production. Maximum nitrogen production was observed between 475 and 500 K. It was found that, at low temperatures, between 300 and 350 K, molecular adsorption occurs with a constant initial sNO of 0.5 until the Pd(111) surface is covered to about 70-80% by NO. Then sNO rapidly decreases with further increasing NO coverage, indicating typical precursor kinetics. The dynamic adsorption - desorption equilibrium on Pd(111) was probed in modulated beam experiments below 500 K. CO titration experiments after NO dosing indicate the diffusion of oxygen into the subsurface regions and beginning surface oxidation at ≥475 K. Finally, we discuss the results with respect to the rate-limiting character of the different elementary steps of the reaction system. © 2005 American Chemical Society.
UnivIS-Import:2015-03-09:Pub.2005.nat.dchph.ppc20.isothe

Jahn-Teller effect of the 2e2g level of chemisorbed benzene - Eiding, J.; Domcke, W.; Huber, W.; Steinrück, Hans-Peter (Chemical Physics Letters, 1991)
It is shown that the characteristic double-peak structure of the 2e band in the photoelectron spectra of CH and CD chemisorbed on metal surfaces arises from a fairly strong intramolecular multi-mode dynamical Jahn-Teller effect. An ab initio treatment of the multi-mode Jahn-Teller effect in the isolated 2e hole state of free benzene yields, after suitable broadening, a quantitative description of the band shape observed in the photoelectron spectra. In gas-phase benzene, the strong Jahn-Teller activity of the 2e hole is concealed by its overlapping and strong pseudo-Jahn-Teller coupling with the adjacent 1a hole state. © 1991.

Katalytische Aktivität und Vergiftung spezifischer aktiver Zentren von Metall-Nanopartikeln auf Trägern - Libuda, Jörg; et al. (Angewandte Chemie, 2002)
UnivIS-Import:2015-03-09:Pub.2002.nat.dchph.ppc20.kataly

Keeping argon under a graphene lid - Argon intercalation between graphene and nickel(111) - Steinrück, Hans-Peter; Bauer, Udo; Gotterbarm, Karin; Späth, Florian; Papp, Christian; Höfert, Oliver; Gleichweit, Christoph; Amende, Maximilian (Surface Science, 2016)
We report on the intercalation of graphene grown on a Ni(111) crystal with argon. Argon is implanted in the Ni(111) crystal by ion bombardment before graphene growth, and diffuses to the surface during the growth of graphene at elevated temperatures. Graphene acts as an atomically thin barrier and keeps the argon underneath. We investigated this system with high resolution X-ray photoelectron spectroscopy. From our experiments we determined the mean quantities of argon under graphene. From our analysis, a simple model to determine the pressure under the graphene layer is presented. In our measurements, we find an increased thermal stability of the intercalated graphene as compared to non-intercalated graphene on Ni(111).
Keywords: Graphene; Intercalation; Nickel; XPS

Key Parameters for the Synthesis of Active and Selective Nanostructured 3d Metal Catalysts Starting from Coordination Compounds - Case Study: Nickel Mediated Reductive Amination - Klarner, Mara; Blach, Patricia; Wittkämper, Haiko; De Jonge, Niels; Papp, Christian; Kempe, Rhett (ChemCatChem, 2021)
The design of nanostructured catalysts based on earth-abundant metals that mediate important reactions efficiently, selectively and with a broad scope is highly desirable. Unfortunately, the synthesis of such catalysts is poorly understood. We report here on highly active Ni catalysts for the reductive amination of ketones by ammonia employing hydrogen as a reducing agent. The key functions of the Ni-salen precursor complex during catalyst synthesis have been identified: (1) Ni-salen complexes sublime during catalyst synthesis, which allows molecular dispersion of the metal precursor on the support material. (2) The salen ligand forms a nitrogen-doped carbon shell by decomposition, which embeds and stabilizes the Ni nanoparticles on the gamma-Al2O3 support. (3) Parameters, such as flow rate of the pyrolysis gas, determine the carbon supply for the embedding process of Ni nanoparticles.
CRIS-Team WoS Importer:2021-06-11

Kinetic isotope effects and reaction intermediates in the decomposition of methyl on flat and stepped platinum (1 1 1) surfaces - Papp, Christian; Fuhrmann, Thomas; Tränkenschuh, Barbara; Denecke, Reinhard; Steinrück, Hans-Peter (Chemical Physics Letters, 2007)
We investigated the thermal evolution of methyl on Pt(1 1 1), Pt(3 2 2) and Pt(3 5 5) by in situ X-ray photoelectron spectroscopy. The dehydrogenation to methylidyne shows a pronounced kinetic isotope effect, with the characteristic temperature higher by 16 K for CD than for CH. The resulting difference in activation energies, 48 meV, agrees well with the difference in the zero point energies of the C-H and C-D stretching vibrations. For the stepped surfaces an enhanced reactivity is found. While dehydrogenation of methyl on Pt(3 2 2) at step and terrace sites occurs at the same temperature, for Pt(3 5 5) the steps are even more reactive. © 2007 Elsevier B.V. All rights reserved.

Kinetic parameters of CO adsorbed on Pt(111) studied by in situ high resolution x-ray photoelectron spectroscopy - Kinne, Martin; Fuhrmann, Thomas; Whelan, Caroline; Zhu, Junfa; Pantförder, Jörg; Probst, Marc; Held, Georg; Denecke, Reinhard; Steinrück, Hans-Peter (Journal of Chemical Physics, 2002)
The adsorption of CO on Pt(111) was examined in a time-resolved manner by high-resolution core level photoelectron spectroscopy using synchrotron radiation. From C1s, O1s, and Pt4f spectra, two species, namely on-top and bridge bound CO, were resolved with excellent agreement of binding energy values with literature reports.

Kinetic passivation of steps with sulfur and CO/S site exchange processes on stepped Pt surfaces - Streber, Regine; Papp, Christian; Lorenz, Michael Peter Andreas; Bayer, Andreas; Denecke, Reinhard; Steinrück, Hans-Peter (Chemical Physics Letters, 2008)
We studied the influence of preadsorbed sulfur on the adsorption of CO on Pt(3 5 5) and Pt(3 2 2) by in situ X-ray photoelectron spectroscopy. At low temperatures, no adsorption of CO at steps is found, indicating a passivation by sulfur. Upon heating, population of step sites with CO occurs. This behavior is attributed to a kinetic passivation of the steps by sulfur at low temperatures, which is lifted upon heating. The characteristic transition temperatures of 185 K for Pt(3 5 5) and 240 K for Pt(3 2 2) are significantly different, due to a higher activation barrier for the CO/S site exchange process for Pt(3 2 2). © 2007 Elsevier B.V. All rights reserved.

Kinetics of the CO oxidation reaction on Pt(111) studied by in situ high-resolution x-ray photoelectron spectroscopy - Kinne, Martin; Fuhrmann, Thomas; Zhu, Junfa; Whelan, Caroline; Denecke, Reinhard; Steinrück, Hans-Peter (Journal of Chemical Physics, 2004)
The coadsorption and reaction of CO with atomic oxygen on Pt(111) was examined by in situ high-resolution core level spectroscopy using synchrotron radiation. A atomic oxygen layer with a coverage of 0.25 ML was exposed to CO from a supersonic molecular beam at various sample temperatures and pressures. X ray photoelectron spectra were collected at photon energies of 380 eV for C 1s and 650 eV for the O 1s region in normal emission geometry. From an Arrhenius plot of the rate constant between 275 and 305 K an activation energy of (0.53±0.04) eV and a prefactor of 4.7×10 s were determined.

Kinetics of the sulfur oxidation on palladium: A combined in situ x-ray photoelectron spectroscopy and density-functional study - Gotterbarm, Karin; Luckas, Nicola; Höfert, Oliver; Lorenz, Michael Peter Andreas; Streber, Regine; Papp, Christian; Vines, Francesc; Steinrück, Hans-Peter; Görling, Andreas (Journal of Chemical Physics, 2012)
We studied the reaction kinetics of sulfur oxidation on the Pd(100) surface by in situ high resolution x-ray photoelectron spectroscopy and ab initio density functional calculations. Isothermal oxidation experiments were performed between 400 and 500 K for small amounts (∼0.02 ML) of preadsorbed sulfur, with oxygen in large excess. The main stable reaction intermediate found on the surface is SO , with SO and SO being only present in minor amounts. Density-functional calculations depict a reaction energy profile, which explains the sequential formation of SO , SO , and eventually SO , also highlighting that the in-plane formation of SO from S and O adatoms is the rate limiting step. From the experiments we determined the activation energy of the rate limiting step to be 85 6 kJ mol by Arrhenius analysis, matching the calculated endothermicity of the SO formation. © 2012 American Institute of Physics.

KOH-promoted Pt/Al2O3 catalysts for water gas shift and methanol steam reforming: An operando DRIFTS-MS study - Kaftan, Andre; Kusche, Matthias Manfred; Laurin, Mathias; Wasserscheid, Peter; Libuda, Jörg (Applied Catalysis B-Environmental, 2017)
The performance of KOH-modified Pt/AlO catalysts has been investigated under the conditions of the water-gas shift (WGS) reaction and methanol steam reforming (MSR) with diffuse reflectance infrared Fourier-transform spectroscopy (DRIFTS) coupled with online quadrupole mass spectrometry (QMS). We demonstrate that both the activity and the selectivity are enhanced in comparison to the uncoated catalyst by applying a thin coating of KOH. By means of IR spectroscopy, we were able to follow the formation of surface species on two different types of catalysts. During reaction, primarily formates are observed on the uncoated catalyst while a film of hydroxides and carbonates is observed on the KOH-coated sample. Additionally, the vibrational bands of CO adsorbed on Pt suggest a strong modification of the electronic structure of the Pt particles by K-coadsorption, leading to a weakening C[sbnd]O bond and a strengthening of the Pt[sbnd]C bond. As a result, we observe an increased selectivity to CO on the KOH modified system.
Keywords: Infrared spectroscopy; Methanol steam reforming; Online mass spectrometry; Platinum; Water-gas shift

Large-scale fabrication of graphene/polyamide-6 composite as a high thermal conductivity engineering composite for thermal radiators - Cao, Weiqi; Shaker, Majid; Meng, Xiaomin; Feng, Huan (Materials Letters, 2022)
In this study, graphene was mass-produced from graphite through ultrasonic-assisted exfoliation in N-methyl-2-pyrrooxone (NMP) and then mixed with polyamides Nylon (PA6) to obtain a high thermal conductivity engineering polymer (GP6). The thermal conductivity of GP6 is 30 W m−1 K−1 and the density is 1.8 g cm−1. GP6 could be used in heat dissipation systems of LED lamps and cameras with injection molding at 260 °C, thus cutting the cost by 30% and reducing the carbon emission.
CRIS-Team Scopus Importer:2022-03-18
Keywords: Exfoliation; Graphene; Polymeric composites; Thermal properties

Lateral interactions and azimuthal orientation of pure and coadsorbed benzene layers on Ni(111) - Huber, W.; Zebisch, P.; Bornemann, T.; Steinrück, Hans-Peter (Surface Science, 1991)
The adsorption of benzene and the coadsorption of benzene with electronegative coadsorbates on Ni(111) have been studied by angle-resolved UPS using linearly polarized synchrotron radiation. The electronic structure of benzene coadsorbed with NO, CO and O in the ordered (2 3×2 3)R30° layers and for the coadsorbed (3 × 3) benzene + NO layer is similar to that of pure benzene layers. Uniform shifts of the various benzene levels to lower binding energy (0.2-0.3 eV) in the coadsorbed layers are attributed to electrostatic initial state effects. In all pure and coadsorbed layers studied, the benzene molecules are oriented with their molecular plane parallel to the surface with the molecular symmetry reduced to C . In the nonsaturated benzene layer and in the coadsorbed layers with (2 3×2 3)R30° structure the molecules are azimuthally oriented with the hydrogens pointing along the [211] directions of the substrate. In the saturated pure ( 7× 7)R19.1° layer and the (3 × 3) benzene + NO layer the molecules are azimuthally reorientated due to lateral interactions. The proposed azimuthal reorientations are in agreement with expectations from steric arguments. For the saturated pure ( 7× 7)R19.1° layer the 2a levels exhibits a dispersion of 0.45 eV. also indicative of lateral interactions. © 1991.

Lattice Opening upon Bulk Reductive Covalent Functionalization of Black Phosphorus - Wild, Stefan; Fickert, Michael; Mitrovic, Aleksandra; Lloret Segura, Vicente Josep; Neiß, Christian; Alejandro Vidal-Moya, Jose; Angel Rivero-Crespo, Miguel; Leyva-Perez, Antonio; Werbach, Katharina; Peterlik, Herwig; Grabau, Mathias; Wittkämper, Haiko; et al. (Angewandte Chemie International Edition, 2019)

Ligand Effects at Ionic Liquid-Modified Interfaces: Coadsorption of [C(2)C(1)lm][OTf] and CO on Pd(111) - Bauer, Tanja; Mehl, Sascha; Brummel, Olaf; Pohako-Esko, Kaija; Wasserscheid, Peter; Libuda, Jörg (Journal of Physical Chemistry C, 2016)
Thin films of ionic liquids (ILs) can be used to tune the activity and selectivity of heterogeneous catalysts and electrocatalysts (solid catalysts with IL layer, SCILL). In several cases it has been found that these IL layers have a strong beneficial effect on the selectivity. To explore the molecular origin of this phenomenon, we have performed a model study on ultrahigh-vacuum conditions. We have investigated the coadsorption of CO and the room-temperature IL [CCIm][OTf] (1-ethyl-3-methylimidazolium trifluoromethanesulfonate) on Pd(111) by time-resolved infrared reflection-absorption spectroscopy, temperature-programmed reflection absorption spectroscopy, and temperature-programmed desorption. We find that the [OTf] anion adsorbs specifically to the Pd(111) surface via the SO group, thereby adopting a well-defined orientation with the molecular axis oriented perpendicular to the surface. At higher IL coverage, unspecific but oriented adsorption occurs, before the orientation is successively lost in the multilayer region. Upon coadsorption of [CCIm][OTf] on a CO-saturated Pd(111) surface at 300 K (θ = 0.5) a well-defined coadsorption layer is formed without any loss of adsorbed CO and with very similar CO site occupation. In the coadsorption layer [OTf] is specifically adsorbed between the CO with a molecular orientation perpendicular to the surface. Thus, a dense and homogeneous coadsorption layer is formed in which Pd surface atoms are simultaneously coordinated to both CO and [OTf] ions. From this compressed layer, CO desorbs with peak temperature at 410 K (heating rate, 3.3 K/s). Above this temperature, a low-coverage coadsorption phase of CO and surface-adsorbed IL resides, with little influence of the IL on the CO desorption temperature (peak temperature, 470 K). Coadsorption of the IL gives rise to a pronounced red shift of the CO stretching frequency in the order of 50 cm. The effect originates from the electrostatic interfacial field (Stark effect) generated by the coadsorbed IL and, at high coverage, possibly from additional short-range interactions. The results show that ILs form dense and well-defined mixed phases with strongly adsorbing reactants such as CO, in which a specifically adsorbed carpet of IL anions directly modifies the active surface sites by ligand-like effects.

Ligand Effects in SCILL Model Systems: Site-Specific Interactions with Pt and Pd Nanoparticles - Sobota, Marek; Happel, Markus; Amende, Maximilian; Paape, Natalia; Wasserscheid, Peter; Laurin, Mathias; Libuda, Jörg (Advanced Materials, 2011)
Ionic liquids (ILs), such as [BMIM][Tf_2N], on well-defined SCILL model catalysts are able to replace weakly adsorbed CO. On Pt, on-top CO remains adsorbed under the ionic liquid layer, but its IR signal red-shifts by over 30 cm-1. IL–adsorbate interactions are mediated by the noble metal and similar to ligands.

Ligand effects on the surface composition of Rh-containing ionic liquid solutions used in hydroformylation catalysis - Kolbeck, Claudia; Paape, Natalia; Cremer, Till; Schulz, Peter; Maier, Florian; Steinrück, Hans-Peter; Wasserscheid, Peter (Chemistry - A European Journal, 2010)
The chemical surface composition of Rh-containing ionic liquid solutions has been studied by angle-resolved X-ray photoelectron spectroscopy (ARXPS). Rh-tppts complexes of high relevance for multiphase hydroformylation catalysis showed remarkable surface activity, whereas non-tppts containing systems showed Rh depleting from the surface (tppts=tris(3-sodium sulfonatophenyl)phosphine). © 2010 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Light-atom location in adsorbed benzene by experiment and theory - Held, Georg; Braun, Wolfgang; Steinrück, Hans-Peter; Yamagishi, S.; Jenkins, S.J.; King, David A. (Physical Review Letters, 2001)
A study on the determination for the locations of light atoms in CD on Ru was performed using low energy electron diffraction (LEED) and density functional theory (DFT). An upward bending of the C-D bonds of 16° on average was found. The bending was observed to be not uniform but alternated between 9° and 24° for the inequivalent light atoms. The strong buckling behavior was explained in the terms of decreased aromaticity and a distortion of the molecule towards the chair geometry of cyclohexane.

Liquid organic hydrogen carriers (LOHCs): Toward a hydrogen-free hydrogen economy - Preuster, Patrick; Papp, Christian; Wasserscheid, Peter (Accounts of Chemical Research, 2017)
The need to drastically reduce CO2 emissions will lead to the transformation of our current, carbon-based energy system to a more sustainable, renewable-based one. In this process, hydrogen will gain increasing importance as secondary energy vector. Energy storage requirements on the TWh scale (to bridge extended times of low wind and sun harvest) and global logistics of renewable energy equivalents will create additional driving forces toward a future hydrogen economy. However, the nature of hydrogen requires dedicated infrastructures, and this has prevented so far the introduction of elemental hydrogen into the energy sector to a large extent. Recent scientific and technological progress in handling hydrogen in chemically bound form as liquid organic hydrogen carrier (LOHC) supports the technological vision that a future hydrogen economy may work without handling large amounts of elemental hydrogen. LOHC systems are composed of pairs of hydrogen-lean and hydrogen-rich organic compounds that store hydrogen by repeated catalytic hydrogenation and dehydrogenation cycles. While hydrogen handling in the form of LOHCs allows for using the existing infrastructure for fuels, it also builds on the existing public confidence in dealing with liquid energy carriers. In contrast to hydrogen storage by hydrogenation of gases, such as CO2 or N2, hydrogen release from LOHC systems produces pure hydrogen after condensation of the high-boiling carrier compounds. This Account highlights the current state-of-the-art in hydrogen storage using LOHC systems. It first introduces fundamental aspects of a future hydrogen economy and derives therefrom requirements for suitable LOHC compounds. Molecular structures that have been successfully applied in the literature are presented, and their property profiles are discussed. Fundamental and applied aspects of the involved hydrogenation and dehydrogenation catalysis are discussed, characteristic differences for the catalytic conversion of pure hydrocarbon and nitrogen-containing LOHC compounds are derived from the literature, and attractive future research directions are highlighted. Finally, applications of the LOHC technology are presented. This part covers stationary energy storage (on-grid and off-grid), hydrogen logistics, and on-board hydrogen production for mobile applications. Technology readiness of these fields is very different. For stationary energy storage systems, the feasibility of the LOHC technology has been recently proven in commercial demonstrators, and cost aspects will decide on their further commercial success. For other highly attractive options, such as, hydrogen delivery to hydrogen filling stations or direct-LOHC-fuel cell applications, significant efforts in fundamental and applied research are still needed and, hopefully, encouraged by this Account.

Liquid Organic Hydrogen Carriers: Model Catalytic Studies on the Thermal Dehydrogenation of 1-Cyclohexylethanol on Pt(111) - Schwaab, Valentin; Hemauer, Felix; Freiberger, Eva Marie; Waleska-Wellnhofer, Natalie; Steinrück, Hans-Peter; Papp, Christian (Journal of Physical Chemistry C, 2023)
The molecule pair of 1-cyclohexylethanol and acetophenone represents an interesting system for a chemical hydrogen storage cycle as it combines two different classes of so-called liquid organic hydrogen carriers (LOHCs), namely hydrogenated, formerly aromatic cyclic hydrocarbons and alcohols, i.e., hydrogenated carbonyls. In particular, the latter have recently attracted much attention due to their favorable dehydrogenation temperatures and the possibility to convert them directly into electricity in specially designed direct-LOHC fuel cells. Herein, we investigate the temperature-triggered dehydrogenation reaction of 1-cyclohexylethanol to acetophenone on a Pt(111) model catalyst using synchrotron-based temperature-programed X-ray photoelectron spectroscopy. To obtain a complete picture of the reaction mechanism, we consider not only the individual surface reactions of 1-cyclohexylethanol and acetophenone but also those of two potential dehydrogenation intermediates, namely, the partially dehydrogenated 1-cyclohexylethanone and 1-phenylethanol. We find a stepwise dehydrogenation of 1-cyclohexylethanol: the first step around ∼210 K at the alcohol moiety yields the ketone 1-cyclohexylethanone. The second step above ∼260 K at the cyclohexyl group is accompanied by the loss of an H-atom at the molecule’s methyl group and leads to the formation of an acetophenone-like phenyl-C(O)-CH2 species at ∼340 K. The same species are also identified in the surface reactions of acetophenone, 1-phenylethanol, and 1-cyclohexylethanone in this temperature range. Overall, the system shows good thermal robustness: a complete dehydrogenation of the hydrogen-rich carrier occurs without damage to the carbon framework.
CRIS-Team Scopus Importer:2023-07-07

Liquid Organic Hydrogen Carriers: Surface Science Studies of Carbazole Derivatives - Papp, Christian; Wasserscheid, Peter; Libuda, Jörg; Steinrück, Hans-Peter (Chemical Record, 2014)
We review recent results towards a molecular understanding of the adsorption and dehydrogenation of carbazole-derived liquid organic hydrogen carriers on platinum and palladium single crystals and on Al2O3-supported Pt and Pd nanoparticles. By combining synchrotron-based high-resolution X-ray photoelectron spectroscopy, infrared reflection-absorption spectroscopy, advanced molecular beam methods and temperature-programmed desorption spectroscopy, detailed insights into the reaction mechanism are obtained. On Pt(111), dehydrogenation of perhydro-N-ethylcarbazole, H-12-NEC, starts with activation of the hydrogen atoms at the pyrrole unit, yielding H-8-NEC as the first stable reaction intermediate at approximate to 340K, followed by further dehydrogenation to NEC at approximate to 380K. Above 390K, dealkylation starts, yielding carbazole as an undesired byproduct. On small supported Pt particles, the dealkylation sets in at lower temperatures, due to the higher reactivity of low-coordinated sites, while on larger particles with (111) facets a reactivity as on the flat surface is observed. Carbazole derivatives with ethyl, propyl and butyl chains show an overall very similar reactivity, both on Pt(111) and on Pt nanoparticles. When comparing the dealkylation behavior of H-12-NEC on Pt(111) and Pt nanoparticles to that on Pd(111) and Pd nanoparticles, we find a higher reactivity for the Pd systems.
Keywords: dehydrogenation; liquid organic hydrogen carriers; platinum; renewable resources; surface chemistry

Liquid/solid interface of ultrathin ionic liquid films: [C 1C1Im][Tf2N] and [C8C 1Im][Tf2N] on Au(111) - Cremer, Till; Stark, Michael Werner; Deyko, Alexey; Steinrück, Hans-Peter; Maier, Florian (Langmuir, 2011)
Ultrathin films of two imidazolium-based ionic liquids (IL), [C CIm][TfN] (= 1,3-dimethylimidazolium bis(trifluoromethyl)imide) and [CCIm][TfN] (= 1-methyl-3-octylimidazolium bis(trifluoromethyl)imide) were prepared on a Au(111) single-crystal surface by physical vapor deposition in ultrahigh vacuum. The adsorption behavior, orientation, and growth were monitored via angle-resolved X-ray photoelectron spectroscopy (ARXPS). Coverage-dependent chemical shifts of the IL-derived core levels indicate that for both ILs the first layer is formed from anions and cations directly in contact with the Au surface in a checkerboard arrangement and that for [CC Im][TfN] a reorientation of the alkyl chain with increasing coverage is found. For both ILs, geometry models of the first adsorption layer are proposed. For higher coverages, both ILs grow in a layer-by-layer fashion up to thicknesses of at least 9 nm (>10 ML). Moreover, beam damage effects are discussed, which are mainly related to the decomposition of [TfN] anions directly adsorbed at the gold surface. © 2011 American Chemical Society.

Local Characterization of Ultrathin ZnO Layers on Ag(111) by Scanning Tunneling Microscopy and Atomic Force Microscopy - Shiotari, Akitoshi; Liu, Bo-Hong; Jaekel, Simon; Grill, Leonhard; Shaikhutdinov, Shamil; Freund, Hans-Joachim; Wolf, Martin; Kumagai, Takashi (Journal of Physical Chemistry C, 2014)
We have studied the local structure of ultrathin ZnO layers grown on Ag(111) by the reactive deposition method using low-temperature scanning tunneling microscopy (STM) and noncontact atomic force microscopy (nc-AFM) at 5 K. The characteristic Moire patterns arising from the lattice mismatch between the ZnO(0001) layers and Ag(111) appear in STM, but it is not pronounced in nc-AFM images. This indicates an atomically flat geometrical structure of the ZnO layer and a dominant contribution of the electronic state to the Moire patterns imaged by STM. We found that the apparent height of STM for the ZnO layers strongly depends on the bias voltage and becomes comparable with that of nc-AFM when the bias voltage is below the conduction band edge of the ZnO layers. The ZnO layers with the STM (AFM) apparent height of 3.8 (4.0) +/- 0.3 and 5.8 (6.1) +/- 0.3 angstrom were observed. On the other hand, mapping the onset of the resonance state of the ZnO layer by scanning tunneling spectroscopy provides a basis for determining its thickness. Our results suggest that the ZnO layers on Ag(111) grow predominantly as bi- and trilayers under the conditions used.

Localized growth of carbon nanotubes via lithographic fabrication of metallic deposits - TU, Fan; Drost, Martin; Szenti, Imre; Kiss, Janos; Konya, Zoltan; Marbach, Hubertus (Beilstein Journal of Nanotechnology, 2017)
We report on the fabrication of carbon nanotubes (CNTs) at predefined positions and controlled morphology, for example, as individual nanotubes or as CNT forests. Electron beam induced deposition (EBID) with subsequent autocatalytic growth (AG) was applied to lithographically produce catalytically active seeds for the localized growth of CNTs via chemical vapor deposition (CVD). With the precursor Fe(CO)5 we were able to fabricate clean iron deposits via EBID and AG. After the proof-of-principle that these Fe deposits indeed act as seeds for the growth of CNTs, the influence of significant EBID/AG parameters on the deposit shape and finally the yield and morphology of the grown CNTs was investigated in detail. Based on these results, the parameters could be optimized such that EBID point matrixes (6 × 6) were fabricated on a silica surface whereby at each predefined site only one CNT was produced. Furthermore, the localized fabrication of CNT forests was targeted and successfully achieved on an Al2O3 layer on a silicon sample. A peculiar lift-up of the Fe seed structures as was observed and the mechanism was discussed. Finally, a proof-of-principle was presented showing that EBID deposits from the precursor Co(CO)3NO are also very effective catalysts for the CNT growth. Even though the metal content (Co) of the latter is reduced in comparison to the Fe deposits, effective CNT growth was observed for the Co-containing deposits at lower CVD temperatures than for the corresponding Fe deposits.
EAM Import::2019-03-12

Local reaction rates and surface diffusion on nanolithographically prepared model catalysts: Experiments and simulations - Libuda, Jörg; et al. (Journal of Chemical Physics, 2005)
Combining molecular beam methods and angular resolved mass spectrometry, we have studied the angular distribution of desorbing products during CO oxidation on a planar Pd/silica supported model catalyst. The model catalyst was prepared by means of electron beam lithography, allowing individual control of particle size, position, and aspect ratio, and was characterized by atomic force microscopy and scanning electron microscopy before and after reaction. In the experiment, both oxygen and CO rich regimes were investigated using separate molecular beams for the two reactants. This allows exploration of diffusion effects of reactants on the particles and of shadowing and backscattering phenomena. A reaction-diffusion model was developed in order to extract information about local reaction rates on the surface of the catalyst nanoparticles. The model takes into account the structural parameters of the catalyst as well as the backscattering of the reactants and products from the support. It allows a quantitative description of the experimental data and provides a detailed understanding of temperature and reactant flux dependent effects. Moreover, information on the surface mobility of oxygen under steady-state reaction conditions could be obtained by comparison with the experimental results.
UnivIS-Import:2015-03-09:Pub.2005.nat.dchph.ppc20.localr

Low Energy Electron- and Ion-Induced Surface Reactions of Fe(CO)(5) Thin Films - Bilgilisoy, Elif; Thorman, Rachel M.; Barclay, Michael S.; Marbach, Hubertus; Fairbrother, D. Howard (Journal of Physical Chemistry C, 2021)
Using in situ X-ray photoelectron spectroscopy (XPS), the effects of low energy (500 eV) electrons and low energy (1200 eV) Ar+ ions on thin films of Fe(CO)(5), a prototypical organometallic precursor, have been investigated. These studies were motivated by the important role that these surface reactions play in the charged-particle-induced deposition of nanostructures. XPS data from the C(1s) and O(1s) regions were used to construct kinetic models to describe the effects of electron and ion irradiation, both of which occurred through a sequence of two sequential surface reactions, although the details of each step differ. During electron irradiation, precursor molecules initially decompose as a result of electronic excitation, resulting in desorption of approximately 50% of the CO ligands and partial decarbonylation within the Fe(CO)(5) film. In the second step, the partially decarbonylated intermediates undergo a much slower electron-stimulated CO decomposition process to produce iron oxides encased in a graphitic film. Fe-2(CO)(9) and Fe-3(CO)(12) reacted similarly to Fe(CO)(5), but the initial rate of decomposition was an order of magnitude higher. During Ar+ bombardment, Fe(CO)(5) molecules decompose as a consequence of energy transfer from the incident ions, causing complete fragmentation of the precursor and desorption of approximate to 80% of the CO molecules. The remaining 20% undergo C O bond cleavage, forming adsorbed carbon and volatile oxygen species. In the second step of the reaction, the residual iron and carbon atoms are subject to Ar+ ion sputtering. The implications of these reactions for focused ion beam-induced deposition (FIBID) and focused electron beam-induced deposition (FEBID) from Fe(CO)(5) are also discussed.
CRIS-Team WoS Importer:2021-09-03

Low melting Li/K/Cs acetate salt mixtures as new ionic media for catalytic applications - first physico-chemical characterization - Bajus, Stephanie; Deyko, Alexey; Bösmann, Andreas; Maier, Florian; Steinrück, Hans-Peter; Wasserscheid, Peter (Dalton Transactions, 2012)
In order to expand the temperature limits of Supported Ionic Liquid Phase (SILP) or Solid Catalyst with Ionic Liquid Layer (SCILL) systems to higher operation temperatures, the mixture of lithium acetate, potassium acetate, and caesium acetate (molar ratio of 0.2/0.275/0.525) has been studied in detail. Physico-chemical properties of the bulk melt are reported together with stability data of the modern salt on various solid support materials showing attractive properties for many potential high temperature applications. © 2012 The Royal Society of Chemistry.

Low temperature decomposition of NO on ordered alumina films - Libuda, Jörg; et al. (Chemical Physics Letters, 2003)
We have investigated the interaction of NO with an ordered Al 2O3 film and a Pd/Al2O3 supported model catalyst, employing time-resolved IR reflection absorption spectroscopy (TR-IRAS) and molecular beam methods. It is observed that NO undergoes slow decomposition at low sample temperature, resulting in the formation of variety of NxOy surface species. The process involves strong structural transformations of the Al2O3 film. On Pd/Al2O3, decomposition of NO is found to be strongly suppressed. Based on the growth behavior of Pd nucleating at oxide defects, it is concluded that NO decomposition is preferentially initiated at specific defect sites on the alumina. © 2003 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2003.nat.dchph.ppc20.lowtem

Low-temperature partial dissociation of water on Cu(110) - Ammon, Christian; Bayer, Andreas; Steinrück, Hans-Peter; Held, Georg (Chemical Physics Letters, 2003)
The low-temperature reactivity of water (DO) adsorbed on clean and oxygen pre-covered Cu(110) was studied using high resolution X-ray photoelectron spectroscopy (HRXPS) and low energy electron diffraction (LEED). On the clean surface partial dissociation to hydroxyl was observed already at 95 K. Upon annealing to 220 K hydrogen bonded water-hydroxyl chains are formed. Upon further annealing water desorbs leaving behind a layer of hydroxyl, most of which desorbs recombinatively eventually. With pre-adsorbed oxygen water reacts to hydroxyl lifting the added-row reconstruction even below 225 K. Upon annealing this adsorbate layer passes through essentially the same stages as without pre-adsorbed oxygen. © 2003 Elsevier B.V. All rights reserve

Magnetotransport properties of iron microwires fabricated by focused electron beam induced autocatalytic growth - Porrati, F.; Sachser, R.; Walz, Marie-Madeleine; Vollnhals, Florian; Steinrück, Hans-Peter; Marbach, Hubertus; Huth, M. (Journal of Physics D-Applied Physics, 2011)
We have prepared iron microwires in a combination of focused electron beam induced deposition and autocatalytic growth from the iron pentacarbonyl, Fe(CO), precursor gas under ultra-high vacuum conditions. The electrical transport properties of the microwires were investigated and it was found that the temperature dependence of the longitudinal resistivity (ρ) shows a typical metallic behaviour with a room temperature value of about 88 νΩ cm. In order to investigate the magnetotransport properties we have measured the isothermal Hall-resistivities in the range between 4.2 and 260 K. From these measurements, positive values for the ordinary and the anomalous Hall coefficients were derived. The relation between anomalous Hall resistivity (ρ) and longitudinal resistivity is quadratic, , revealing an intrinsic origin of the anomalous Hall effect. Finally, at low temperature in the transversal geometry a negative magnetoresistance of about 0.2% was measured. © 2011 IOP Publishing Ltd.

Massive conformational changes during thermally induced self-metalation of 2H-tetrakis-(3,5-di-tert-butyl)-phenylporphyrin on Cu(111) - Stark, Michael Werner; Ditze, Stefanie; Lepper, Michael; Zhang, Liang; Schlott, Hannah; Buchner, Florian; Röckert, Michael; Chen, Min; Lytken, Ole; Steinrück, Hans-Peter; Marbach, Hubertus (Chemical Communications, 2014)
Based on a combined scanning tunnelling microscopy and X-ray photoelectron spectroscopy study we present detailed insights into pronounced changes of long-range order and intramolecular conformation during the self-metalation of 2H-5,10,15,20-tetrakis-(3,5-di-tert-butyl)-phenylporphyrin (2HTTBPP) to CuTTBPP on Cu(111). Upon metalation, the porphyrin literally ``pops up'' from the surface, due to a drastically reduced molecule–substrate interaction.

Matrix effects in the C 1s photoabsorption spectra of condensed naphthalene - Schmidt, Norman Anja; Wenzel, Jan; Dreuw, Andreas; Fink, Rainer; Hieringer, Wolfgang (Journal of Chemical Physics, 2016)
High-resolution C 1s near-edge x-ray absorption fine structure (NEXAFS) spectra of naphthalene are investigated. By comparing the spectral signatures of condensed naphthalene molecules with those of naphthalene in the gas phase, we are able to unambiguously identify spectral features which are affected by the intermolecular interactions in the condensed phase. With the help of calculations using time-dependent density-functional theory and the second-order algebraic-diagrammatic construction scheme for the polarization propagator, resonances in the relevant energy range can be assigned to valence and Rydberg-like excitations. Thus, we obtain a more detailed identification of NEXAFS resonances beyond the present literature.
EAM Import::2019-03-12

Maximum Noble-Metal Efficiency in Catalytic Materials: Atomically Dispersed Surface Platinum - Bruix, Albert; Lykhach, Yaroslava; Matolinova, Iva; Neitzel, Armin; Skala, Tomas; Tsud, Nataliya; Vorokhta, Mykhailo; Stetsovych, Vitalii; Sevcikova, Klara; Myslivecek, Josef; Fiala, Roman; Vaclavu, Michal; et al. (Angewandte Chemie International Edition, 2014)
Platinum is the most versatile element in catalysis, but it is rare and its high price limits large-scale applications, for example in fuel-cell technology. Still, conventional catalysts use only a small fraction of the Pt content, that is, those atoms located at the catalyst's surface. To maximize the noble-metal efficiency, the precious metal should be atomically dispersed and exclusively located within the outermost surface layer of the material. Such atomically dispersed Pt surface species can indeed be prepared with exceptionally high stability. Using DFT calculations we identify a specific structural element, a ceria "nanopocket", which binds Pt2+ so strongly that it withstands sintering and bulk diffusion. On model catalysts we experimentally confirm the theoretically predicted stability, and on real Pt-CeO2 nanocomposites showing high Pt efficiency in fuel-cell catalysis we also identify these anchoring sites.
Keywords: ceria nanoparticles; density functional calculations; heterogeneous catalysis; model catalyst; platinum

Mechanism of Sulfur Poisoning and Storage: Adsorption and Reaction of SO2 with Stoichiometric and Reduced Ceria Films on Cu(111) - Happel, Markus; Lykhach, Yaroslava; Tsud, Nataliya; Skala, Tomas; Prince, Kevin C.; Matolin, Vladimir; Libuda, Jörg (Journal of Physical Chemistry C, 2011)
We have performed a systematic synchrotron radiation photoelectron spectroscopy (SR-PES) study of the interaction of SO2 with stoichiometric CeO2(111) and reduced CeO2-x films supported on Cu(111). Resonant photoelectron spectroscopy (RPES) was utilized to monitor changes in the cerium oxidation states. Adsorption of SO2 at 150 and 300 K results mostly in formation of sulfite (SO32-) species on both reduced and stoichiometric ceria. Other species such as sulfate (SO42-), SO2 chemisorbed at cationic sites, anionic SO2-, atomic sulfur, surface sulfides, and bulk oxy-sulfides were detected. The origin of these species is discussed in relation to the changes in the oxidation state of ceria cations at the surface. The thermal evolution of the species formed upon adsorption at 150 and 300 K was studied systematically on both the stoichiometric and the reduced films. It was found that the sulfite partially desorbs to release SO2 and partially decomposes. In general, the reduced CeO2-x surface was found to be much more active toward cleavage of S-O bonds, as indicated by a higher amount of oxy-sulfide species produced. The decomposition pathways can be monitored via changes of the ceria oxidation state and are discussed in relation to the stoichiometry of the ceria surface.

Medieval nanotechnology: Thickness determination of Zwischgold samples - Wu, Qing; Watts, Benjamin; Döbeli, Max; Müller, Julian; Butz, Benjamin; Lombardo, Tiziana; Schmidt-Ott, Katharina; Fink, Rainer; Nolting, Frithjof; Ganz, David (Journal of Cultural Heritage, 2021)
A special gilding material called Zwischgold has been frequently observed in medieval gilded artefacts. As a bilayer metal leaf made from gold and silver, it exhibits similar but slightly paler golden colour tone compared to pure gold. Zwischgold surface can be darkened quickly due to the corrosion of its silver base. Despite its frequent mentions in medieval guild statutes, the production of Zwischgold and its important technological parameters have been under a veil of secrecy since the Middle Ages. Here, we examine the thicknesses and materials proportions of medieval Zwischgold, through high-resolution scanning electron microscopy coupled with energy dispersive X-ray analysis (SEM-EDX) on a large number of samples taken from late medieval gilded sculptures. We observe that medieval Zwischgold contains ultra-thin gold layers in a thickness range of ca. 20–50 nm, indicating the employment of high-precision technologies in manufacturing of delicate art materials in the late medieval period. It further clarifies some ambiguity in gilding history, regarding the colour appearance of medieval Zwischgold. As supportive data, Rutherford backscattering spectrometry (RBS) and scanning transmission electron microscopy (STEM) were applied, in order to confirm the precision and accuracy of the sample preparation and the SEM analysis.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Gilding; Medieval; Nanoscale; SEM; Thickness; Zwischgold

Metalation and coordination reactions of 2H-meso-trans-di(p-cyanophenyl) porphyrin on Ag(111) with coadsorbed cobalt atoms - Kuliga, Jan; Zhang, Liang; Lepper, Michael; Lungerich, Dominik; Hölzel, Helen; Jux, Norbert; Steinrück, Hans-Peter; Marbach, Hubertus (Physical Chemistry Chemical Physics, 2018)
We investigated the metalation and coordination reactions of Co with 2H-5,15-bis(para-cyanophenyl)10,20-bisphenylporphyrin (2HtransDCNPP) on a Ag(111) surface by scanning tunneling microscopy. At room temperature (RT), 2HtransDCNPPs self-assemble into a supramolecular structure stabilized by intermolecular hydrogen bonding. The metalation of 2HtransDCNPP is achieved either by depositing Co atoms onto the supramolecular structure at RT, or, alternatively, by depositing the molecules onto a submonolayer Co-precovered Ag(111) surface with a subsequent heating to 500 K. In addition, the molecules coordinate to Co atoms through the N atoms in the peripheral cyano groups with a preference of isolated 4-fold coordination motifs at RT.

Metalation of 2HTCNPP on Ag(111) with Zn: Evidence for the Sitting atop Complex at Room Temperature - Kuliga, Jan; De Campos Ferreirra, Rodrigo Cezar; Adhikari, Rajan; Massicot, Stephen; Lepper, Michael; Hölzel, Helen; Jux, Norbert; Marbach, Hubertus; De Siervo, Abner; Steinrück, Hans-Peter (ChemPhysChem, 2021)
We study the interaction and metalation reaction of a free base 5,10,15,20-terakis(4-cyanophenyl)porphyrin (2HTCNPP) with post-deposited Zn atoms and the targeted reaction product Zn-5,10,15,20-terakis(4-cyanophenyl)porphyrin (ZnTCNPP) on a Ag(111) surface. The investigations are performed with scanning tunneling microscopy at room temperature after Zn deposition and subsequent heating. The goal is to obtain further insights in the metalation reaction and the influence of the cyanogroups on this reaction. The interaction of 2HTCNPP with post-deposited Zn leads to the formation of three different 2D ordered island types that coexist on the surface. All contain a new species with a bright appearance, which increases with the amount of post-deposited Zn. We attribute this to metastable SAT ("sitting atop") complexes formed by Zn and the macrocycle, that is, an intermediate in the metalation reaction to ZnTCNPP, which occurs upon heating to 500 K. Interestingly, the activation barrier for the successive reaction of the SAT complex to the metalated ZnTCNPP species can also be overcome by a voltage pulse applied to the STM tip.
CRIS-Team WoS Importer:2021-01-29

Metal-Support Interaction and Charge Distribution in Ceria-Supported Au Particles Exposed to CO - Bezkrovnyi, Oleksii; Bruix, Albert; Blaumeiser, Dominik; Piliai, Lesia; Schötz, Simon; Bauer, Tanja; Khalakhan, Ivan; Skala, Tomas; Matvija, Peter; Kraszkiewicz, Piotr; Pawlyta, Miroslawa; Vorokhta, Mykhailo; et al. (Chemistry of Materials, 2022)
Understanding how reaction conditions affect metal-support interactions in catalytic materials is one of the most challenging tasks in heterogeneous catalysis research. Metal nanoparticles and their supports often undergo changes in structure and oxidation state when exposed to reactants, hindering a straightforward understanding of the structure-activity relations using only ex situ or ultrahigh vacuum techniques. Overcoming these limitations, we explored the metal-support interaction between gold nanoparticles and ceria supports in ultrahigh vacuum and after exposure to CO. A combination of in situ methods (on powder and model Au/CeO2 samples) and theoretical calculations was applied to investigate the gold/ceria interface and its reactivity toward CO exposure. X-ray photoelectron spectroscopy measurements rationalized by first-principles calculations reveal a distinctly inhomogeneous charge distribution, with Au+ atoms in contact with the ceria substrate and neutral Au0 atoms at the surface of the Au nanoparticles. Exposure to CO partially reduces the ceria substrate, leading to electron transfer to the supported Au nanoparticles. Transferred electrons can delocalize among the neutral Au atoms of the particle or contribute to forming inert Au- atoms near oxygen vacancies at the ceria surface. This charge redistribution is consistent with the evolution of the vibrational frequencies of CO adsorbed on Au particles obtained using diffuse reflectance infrared Fourier transform spectroscopy.
CRIS-Team Scopus Importer:2022-09-16

Methane activation by platinum: Critical role of edge and corner sites of metal nanoparticles - Vines, Francesc; Lykhach, Yaroslava; Staudt, Thorsten; Lorenz, Michael Peter Andreas; Papp, Christian; Steinrück, Hans-Peter; Libuda, Jörg; Neyman, Konstantin; Görling, Andreas (Chemistry - A European Journal, 2010)
Complete dehydrogenation of methane is studied on model Pt catalysts by means of state-of-the-art DFT methods and by a combination of supersonic molecular beams with highresolution photoelectron spectroscopy. The DFT results predict that intermediate species like CH and CH are specially stabilized at sites located at particles edges and corners by an amount of 50-80 kJ mol . This stabilization is caused by an enhanced activity of lowcoordinated sites accompanied by their special flexibility to accommodate adsorbates. The kinetics of the complete dehydrogenation of methane is substantially modified according to the reaction energy profiles when switching from Pt(111) extended surfaces to Pt nanoparticles. The CH and CH formation steps are endothermic on Pt(111) but markedly exothermic on Pt . An important decrease of the reaction barriers is observed in the latter case with values of approximately 60 kJmol for first C - H bond scission and 40 kJ mol for methyl decomposition. DFT predictions are experimentally confirmed by methane decomposition on Pt nanoparticles supported on an ordered CeO film on Cu(111). It is shown that CH generated on the Pt nanoparticles undergoes spontaneous dehydrogenation at 100 K. This is in sharp contrast to previous results on Pt single-crystal surfaces in which CH was stable up to much higher temperatures. This result underlines the critical role of particle edge sites in methane activation and dehydrogenation. © 2010 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.

Methane Oxidation Over Pd Supported on Ceria–Alumina Under Rich/Lean Cycling Conditions - Fouladvand, Sheedeh; Schernich, Stefan; Libuda, Jörg; Gronbeck, Henrik; Pingel, Torben; Olsson, Eva; Skoglundh, Magnus; Carlsson, Per-Anders (Topics in Catalysis, 2013)
Catalysts with highly dispersed palladium on alumina, alumina doped with 20 wt% ceria and ceria have been prepared, characterized and examined for net-lean methane oxidation. In particular, the activity and selectivity were investigated during rich/lean cycling of the feed. The ceria content is found to influence both the general and the instantaneous activity responses. The results indicate that the active phase of palladium changes between reduced and oxidised Pd during the rich/lean cycling, and that the process is influenced by the presence of ceria.

Methanol Steam Reforming Promoted by Molten Salt-Modified Platinum on Alumina Catalysts - Kusche, Matthias Manfred; Agel, Friederike; Ní Bhriain, Nollaig; Kaftan, Andre; Laurin, Mathias; Libuda, Jörg; Wasserscheid, Peter (Chemsuschem, 2014)
We herein describe a straight forward procedure to increase the performance of platinum-on-alumina catalysts in methanol steam reforming by applying an alkali hydroxide coating according to the "solid catalyst with ionic liquid layer" (SCILL) approach. We demonstrate by diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) and temperature-programmed desorption (TPD) studies that potassium doping plays an important role in the catalyst activation. Moreover, the hygroscopic nature and the basicity of the salt modification contribute to the considerable enhancement in catalytic performance. During reaction, a partly liquid film of alkali hydroxides/carbonates forms on the catalyst/alumina surface, thus significantly enhancing the availability of water at the catalytically active sites. Too high catalyst pore fillings with salt introduce a considerable mass transfer barrier into the system as indicated by kinetic studies. Thus, the optimum interplay between beneficial catalyst modification and detrimental mass transfer effects had to be identified and was found on the applied platinum-on-alumina catalyst at KOH loadings around 7.5 mass%.
Keywords: catalyst characterization; heterogeneous catalysis; methanol reforming; molten salts; platinum

Methylated [(arene)(1,3-cyclohexadiene)Ru(0)] complexes as low-melting MOCVD precursor complexes with a controlled follow-up chemistry of the ligands - Jipa, Ilona; Danova, Katia; Popovska, Nadejda; Siddiqi, M. Aslam; Siddiqui, Rehan A.; Atakan, B.; Cremer, Till; Maier, Florian; Marbach, Hubertus; Steinrück, Hans-Peter; Heinemann, Frank Wilhelm; Zenneck, Ulrich (Journal of Materials Chemistry, 2011)
[(Benzene)(2-methyl-1,3-cyclohexadiene)Ru(0)] (1), [(1,3-cyclohexadiene) (toluene)Ru(0)] (2), and [(methyl-cyclohexadiene)(toluene)Ru(0)] (3, mixture of isomers) have been prepared and tested as new metal organic ruthenium precursor complexes for chemical vapor deposition (MOCVD) with favorable properties. 1 is a low-melting precursor complex (mp = 29 °C) and the isomeric mixture 3 forms a liquid at room temperature. X-ray diffraction studies of single crystals of complexes 1 and 2 are characteristic for true Ru(0) π-complexes without molecular structure peculiarities or significant intermolecular interactions in the solid state, which could hinder undecomposed evaporation. Differential thermal analysis (DTA), differential scanning calorimetry (DSC) and vapor pressure data qualify the compounds as almost ideal MOCVD precursors. Thin ruthenium films have been deposited successfully on silicon wafers and substrate temperatures between 200 and 450 °C in inert gas atmospheres. Film growth and properties were evaluated by scanning electron microscopy (SEM), atomic force microscopy (AFM), X-ray photoelectron spectroscopy (XPS), and four-point probe conductivity measurements. All films consist of polycrystalline metallic ruthenium with a low surface roughness. © The Royal Society of Chemistry 2011.

Methylated [(benzene)(1,3-butadiene)Ru0] derivatives as novel MOCVD precursors with favorable properties - Jipa, Ilona; Siddiqi, M. Aslam; Siddiqui, Rehan A.; Atakan, Burak; Marbach, Hubertus; Cremer, Till; Maier, Florian; Steinrück, Hans-Peter; Danova, Katia; Popovska, Nadejda; Heinemann, Frank Wilhelm; Zenneck, Ulrich (Chemical Vapor Deposition, 2011)
[(Benzene)(2-methyl-1,3-butadiene)Ru] (1), [(benzene)(2,3- dimethyl-1,3-butadiene)Ru] (2), and [(2,3-dimethyl-1,3-butadiene) (toluene)Ru] (3) are prepared and tested as new metal-organic (MO) ruthenium precursor complexes with favorable deposition properties for the CVD of thin ruthenium films. X-ray diffraction (XRD) studies of single crystals of the complexes are characteristic for true Ru π-complexes without molecular structure peculiarities or significant intermolecular interactions in the solid state, which can hinder undecomposed evaporation. Differential thermal analysis (DTA) and vapor pressure data qualify the compounds as almost ideal MOCVD precursors. Thin ruthenium films are deposited successfully on silicon wafers at substrate temperatures between 200 and 400°C in a nitrogen gas atmosphere. X-ray photoelectron spectroscopy (XPS), four-point probe conductivity measurements, and atomic force microscopy (AFM) are used to characterize the films. All films consist of polycrystalline metallic ruthenium with a low surface roughness. © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Microscopic evidence of the metalation of a free-base porphyrin monolayer with iron - Buchner, Florian; Schwald, Veronika; Comanici, Karmen; Steinrück, Hans-Peter; Marbach, Hubertus (ChemPhysChem, 2007)
Microscopic evidence of the in situ complexation of Fe-porphyrins is presented. The figure shows the sub-molecular resolved scanning tunneling microscopy images which document the metalation of 2H-TPP (central cavity; TPP: tetraphenylporphyrin) with evaporated iron (protrusions are identified as Fe-TPP). This promising technique enables future surface science investigations of clean iron porphyrin films under ultrahigh vacuum conditions. © 2007 Wiley-VCH Verlag GmbH & Co. KGaA.

Microscopic insights into methane activation and related processes on Pt/Ceria model catalysts - Lykhach, Yaroslava; Staudt, Thorsten; Lorenz, Michael Peter Andreas; Streber, Regine; Bayer, Andreas; Steinrück, Hans-Peter; Libuda, Jörg (ChemPhysChem, 2010)
Ceria-based supported noble-metal catalysts release oxygen, which may help to reduce the formation of carbonaceous residues, for example during hydrocarbon reforming. To gain insight into the microscopic origins of these effects, a model study is performed under ultrahigh-vacuum conditions using single-crystal-based supported model catalysts. The model systems are based on ordered CeO (111) films on Cu(111), on which Pt nanoparticles are grown by physical vapor deposition. The growth and structure of the surfaces are characterized by means of scanning tunneling microscopy, and the electronic structure and reactivity are probed by X-ray photoelectron spectroscopy. Specifically, it is shown that the fully oxidized CeO thin films undergo slight reduction upon Pt deposition (CeO ). This effect is enhanced upon annealing (CeO ), thus indicating facile oxygen release and reverse spillover. The model system is structurally stable up to temperatures exceeding 700 K. The activation of methane is investigated using high-kinetic-energy CH (0.83 eV), generated by a supersonic molecular beam. It is shown that dehydrogenation occurs under rapid formation of CH or C species without detectable amounts of CH being formed, even at low temperatures (100 K). The released hydrogen spills over to the CeO support, which leads to the formation of OH groups. At 200 K and above, the OH groups start to decompose leaving additional Ce centers behind (CeO ). At up to 700 K, carbon deposits are quantitatively removed by reaction with oxygen, which is supplied by reverse spillover from the CeO film, thus leading to substantial reduction of the support ( CeO ). © 2010 Wiley-VCH Verlag GmbH& Co. KGaA, Weinheim.
Keywords: cerium oxide; heterogeneous catalysis; methane dehydrogenation; supported catalysts; platinum

Microscopic models of PdZn alloy catalysts: Structure and reactivity in methanol decomposition - Neyman, Konstantin; Lim, Kok Hwa; Chen, Zhao-Xu; Moskaleva, Lyudmila V.; Bayer, Andreas; Reindl, Armin; Borgmann, Dieter; Denecke, Reinhard; Steinrück, Hans-Peter; Rösch, Notker (Physical Chemistry Chemical Physics, 2007)
We review systematic experimental and theoretical efforts that explored formation, structure and reactivity of PdZn catalysts for methanol steam reforming, a material recently proposed to be superior to the industrially used Cu based catalysts. Experimentally, ordered surface alloys with a Pd: Zn ratio of ∼1: 1 were prepared by deposition of thin Zn layers on a Pd(111) surface and characterized by photoelectron spectroscopy and low-energy electron diffraction. The valence band spectrum of the PdZn alloy resembles closely the spectrum of Cu(111), in good agreement with the calculated density of states for a PdZn alloy of 1: 1 stoichiometry. Among the issues studied with the help of density functional calculations are surface structure and stability of PdZn alloys and effects of Zn segregation in them, and the nature of the most likely water-related surface species present under the conditions of methanol steam reforming. Furthermore, a series of elementary reactions starting with the decomposition of methoxide, CH O, along both C-H and C-O bond scission channels, on various surfaces of the 1: 1 PdZn alloy [planar (111), (100) and stepped (221)] were quantified in detail thermodynamically and kinetically in comparison with the corresponding reactions on the surfaces Pd(111) and Cu(111). The overall surface reactivity of PdZn alloy was found to be similar to that of metallic Cu. Reactive methanol adsorption was also investigated by in situ X-ray photoelectron spectroscopy for pressures between 3 × 10 and 0.3 mbar. © the Owner Societies.

Microspectroscopic analysis of the X-ray-induced photoreduction in Fe-and Mn-containing SMMs - Schmidt, Norman Anja; Scheurer, Andreas; Sperner, Stefan; Fink, Rainer (Zeitschrift für Naturforschung Section B-A Journal of Chemical Sciences, 2010)
Scanning transmission X-ray microspectroscopy (STXM) and L-edge near-edge X-ray absorption fine structure (NEXAFS) spectroscopy have been applied to study the valence states of metal ions in various Fe-and Mn-containing single-molecule magnet materials, in particular the ligand-stabilized metal complexes NaFe (so-called "ferric wheel"), Fe (so-called "ferric star") and Mn (so-called "manganese wheel"). We compare dose-dependent L-edge absorption spectra with the results of theoretical studies of the involved metal ions to conclude on the change in oxidation state upon increasing the X-ray dose. It is found that even low-intensity irradiation induces the reduction of the weakly interacting metal ions, and that the soft X-ray-induced photoreduction is less pronounced in microcrystalline films. © 2010 Verlag der Zeitschrift für Naturforschung, Tübingen.
Keywords: Single-molecule Magnet (SMM); X-Ray Absorption; X-Ray Microspectroscopy; STXM; Photoreduction

Mixed convection over a horizontal plate: self-similar and connecting boundary-layer flows - Steinrück, Hans-Peter (Fluid Dynamics Research, 1995)
The boundary-layer flow over a horizontal plate is considered. In case that the heat transfer is limited to the leading edge of the plate two similarity solutions exist, if the buoyancy parameter is above a critical value. By an asymptotic expansion with respect to buoyancy parameters near the critical value it is shown that steady-state (non-similar) solutions connecting both similarity solutions exist. Finally a slowly varying transient solution is constructed. The downstream behavior of the perturbation determines which steady flow will be attained. © 1995.

Model catalysis with ceria-based materials: Surface science models for heterogeneous catalysis and electrocatalysis - Libuda, Jörg (ABSTRACTS OF PAPERS OF THE AMERICAN CHEMICAL SOCIETY, 2019)
CRIS-Team WoS Importer:2020-05-02

Model catalytic studies of liquid organic hydrogen carriers: Dehydrogenation and decomposition mechanisms of dodecahydro-n-ethylcarbazole on pt(111) - Amende, Maximilian; Gleichweit, Christoph; Werner, Kristin; Schernich, Stefan; Zhao, Wei; Lorenz, Michael Peter Andreas; Höfert, Oliver; Papp, Christian; Koch, Marcus; Wasserscheid, Peter; Laurin, Mathias; Steinrück, Hans-Peter; et al. (ACS Catalysis, 2014)
Liquid organic hydrogen carriers (LOHC) are compounds that enable chemical energy storage through reversible hydrogenation. They are considered a promising technology to decouple energy production and consumption by combining high-energy densities with easy handling. A prominent LOHC is N-ethylcarbazole (NEC), which is reversibly hydrogenated to dodecahydro-N-ethylcarbazole (H -NEC). We studied the reaction of H-NEC on Pt(111) under ultrahigh vacuum (UHV) conditions by applying infrared reflection-absorption spectroscopy, synchrotron radiation-based high resolution X-ray photoelectron spectroscopy, and temperature-programmed molecular beam methods. We show that molecular adsorption of H-NEC on Pt(111) occurs at temperatures between 173 and 223 K, followed by initial C-H bond activation in direct proximity to the N atom. As the first stable dehydrogenation product, we identify octahydro-N-ethylcarbazole (H -NEC). Dehydrogenation to H-NEC occurs slowly between 223 and 273 K and much faster above 273 K. Stepwise dehydrogenation to NEC proceeds while heating to 380 K. An undesired side reaction, C-N bond scission, was observed above 390 K. H-NEC and H-carbazole are the dominant products desorbing from the surface. Desorption occurs at higher temperatures than H-NEC formation. We show that desorption and dehydrogenation activity are directly linked to the number of adsorption sites being blocked by reaction intermediates. © 2014 American Chemical Society.

Model Catalytic Studies of Liquid Organic Hydrogen Carriers: Indole/Indoline/Octahydroindole on Ni(111) - Steinhauer, Johann; Bachmann, Philipp; Freiberger, Marie; Bauer, Udo; Steinrück, Hans-Peter; Papp, Christian (Journal of Physical Chemistry C, 2020)
N-heterocycles belong to the class of so-called liquid organic hydrogen carriers (LOHCs), which have been identified as suitable materials for chemical hydrogen storage due to favorable hydrogen storage capacity and reaction kinetics. In this contribution, we focus on the dehydrogenation reaction of hydrogen-rich octahydroindole, its dehydrogenation intermediate indoline, and hydrogen-lean indole. Octahydroindole has a hydrogen storage capacity of 6.4 wt %, and indoline has 1.7 wt %. We investigated the mechanism of the temperature-induced dehydrogenation of the three compounds after adsorption on Ni(111) at low temperatures. Nickel is attractive as an effective and low-priced dehydrogenation catalyst, which potentially could replace more expensive Pt and Pd in industrial applications. We compare the obtained results with our previous work on Pt(111) for the same LOHC system and for N-ethylcarbazole/H-12-N-ethylcarbazole. A comprehensive understanding of the reaction mechanism was obtained by combining high-resolution X-ray photoelectron spectroscopy with temperature-programmed desorption lab experiments. For all three compounds, we find dehydrogenation at the nitrogen atom above 270 K (indole, >= 130 K; indoline, >240 K; octahydroindole, >270 K). For indoline and octahydroindole, we observe simultaneous dehydrogenation at the carbon atoms, resulting in an indolide surface species. For octahydroindole, small amounts of side products and decomposition products are observed throughout the reaction pathway. Above 380 K, the indolide species decomposes into fragments for all three compounds.
CRIS-Team WoS Importer:2020-11-27

Model Catalytic Studies of Novel Liquid Organic Hydrogen Carriers: Indole, Indoline and Octahydroindole on Pt(111) - Schwarz, Matthias; Bachmann, Philipp; Nascimento Silva, Thais; Mohr, Susanne; Scheuermeyer, Marlene; Späth, Florian; Bauer, Udo; Düll, Fabian; Steinhauer, Johann; Hohner, Chantal; Döpper, Tibor; Noei, Heshmat; et al. (Chemistry - A European Journal, 2017)
Indole derivatives were recently proposed as potential liquid organic hydrogen carriers (LOHC) for storage of renewable energies. In this work, we have investigated the adsorption, dehydrogenation and degradation mechanisms in the indole/indoline/octahydroindole system on Pt(111). We have combined infrared reflection absorption spectroscopy (IRAS), X-ray photoelectron spectroscopy (XPS) and DFT calculations. Indole multilayers show a crystallization transition at 200 K, in which the molecules adopt a strongly tilted orientation, before the multilayer desorbs at 220 K. For indoline, a less pronounced restructuring transition occurs at 150 K and multilayer desorption is observed at 200 K. Octahydroindole multilayers desorb already at 185 K, without any indication for restructuring. Adsorbed monolayers of all three compounds are stable up to room temperature and undergo deprotonation at the NH bond above 300 K. For indoline, the reaction is followed by partial dehydrogenation at the 5-membered ring, leading to the formation of a flat-lying di-sigma-indolide in the temperature range from 330-390 K. Noteworthy, the same surface intermediate is formed from indole. In contrast, the reaction of octahydroindole with Pt(111) leads to the formation of a different intermediate, which originates from partial dehydrogenation of the 6-membered ring. Above 390 K, all three compounds again form the same strongly dehydrogenated and partially decomposed surface species.
Keywords: density functional theory; infrared reflection absorption spectroscopy; liquid organic hydrogen carrier; octahydroindole; X-ray photoelectron spectroscopy

Model Catalytic Studies of the LOHC System 2,2′-Bipiperidine/2,2′-Bipyridine on Ni(111) - Steinhauer, Johann; Bachmann, Philipp; Bauer, Udo; Düll, Fabian; Steinrück, Hans-Peter; Papp, Christian (Journal of Physical Chemistry C, 2021)
N-heterocyclic compounds such as octahydroindole and dodecahydro-N-ethylcarbazole have been proposed as suitable liquid organic hydrogen carriers for chemical hydrogen storage. Following these studies, we focused on hydrogen-rich 2,2′-bipiperidine with a hydrogen storage capacity of 7.1 wt % and hydrogen-lean 2,2′-bipyridine. Both were adsorbed on Ni(111), and the temperature-induced reaction mechanism and decomposition were studied. The reaction was investigated using synchrotron-based XPS, NEXAFS, and TPD experiments. Upon adsorption, the formation of a flat-lying chemisorbed layer is observed. Above 370 K, 2,2′-bipyridine is dehydrogenated in the α-position to the nitrogen atoms to form an α-2,2′-bipyridyl species with a tilted adsorption geometry. The hydrogen-rich 2,2′-bipiperidine is partially dehydrogenated above 180 K and deprotonated at the nitrogen atoms above 250 K. Above 320 K, α-2,2′-bipyridyl is formed, which is accompanied by a byproduct that is partially dehydrogenated at the carbon atoms. Above 400 K, we observe the decomposition of the α-2,2′-bipyridyl species.
CRIS-Team Scopus Importer:2021-05-14

Modeling NOx storage materials: A high-resolution photoelectron spectroscopy study on the interaction of NO2 with Al2O3/NiAl(110) and BaO/Al2O3/NiAl(110) - Staudt, Thorsten; Desikusumastuti, Aine; Happel, Markus; Vesselli, E.; Baraldi, A.; Gardonio, S.; Lizzit, S.; Rohr, F.; Libuda, Jörg (Journal of Physical Chemistry C, 2008)
We have studied the interaction of NO2 with a single-crystal-based model NOx storage material, using high-resolution photoelectron spectroscopy (HR-PES). As a model surface, we use an ordered Al2O3 film on NiAl(110), on which BaO nanoparticles are grown by physical vapor deposition of metallic Ba and subsequent oxidation and annealing. On the Al2O3/NiAl(110), exposure to NO2 at 300 K leads to slow formation of surface nitrite species, saturating at exposures around 100-1000 L. The surface reaction is accompanied by further oxidation of the support, leading to an increasing thickness of the alumina film. The initial surface reaction is followed by two additional very slow processes, the formation of a small amount of surface nitrates and the decomposition to aluminum nitride species. Upon annealing, the weakly bound surface nitrites and nitrates desorb at temperatures below 500 K. During preparation of the BaO nanoparticles on Al2O3/NiAl(110), intermixing of Ba2+ and Al3+ ions occurs, even at 300 K. The process is accompanied by continuing increase of the oxide film thickness. Whereas intermixing is nearly complete for small particles at 300 K, there are kinetic limitations for mixed oxide (BaAl2xO1+3x) formation for larger nanoparticles. These, however, are overcome by annealing in O-2. In a last step, the interaction of the model NO., storage materials with NO2 is probed. At an initial stage of the reaction, only the formation of surface nitrites is observed. On the BaO containing surface, nitrite formation occurs at a higher rate than on the pristine Al2O3 support. Again, the reaction is connected to an increasinc, thickness of the alurnina layer. At exposures around 100-1000 L at 300 K, formation of surface nitrites stops and is followed by slow conversion into surface nitrates. In contrast to the pristine alumina support, decomposition to nitrides is strongly inhibited on the Ba containing model system.

Modeling NOx storage materials: On the formation of surface nitrites and nitrates and their identification by vibrational spectroscopy - Desikusumastuti, Aine; Happel, Markus; Dumbuya, K.; Staudt, Thorsten; Laurin, Mathias; Gottfried, Michael; Steinrück, Hans-Peter; Libuda, Jörg (Journal of Physical Chemistry C, 2008)
We have studied the reaction of NO with BaO nanoparticles supported on an ordered AlO thin film on NiAl (110). Combining chemical analysis by X-ray photoelectron spectroscopy (XPS) and vibrational spectroscopy by infrared reflection absorption spectroscopy (IRAS), performed in combination with molecular beam (MB) techniques, the sequence of appearance of various nitrogen-oxo surface intermediates and their spectral properties are identified. The initial intermediates at 300 K are surface nitrites (NO), which are preferentially oriented parallel to the surface. Whereas formation of nitrites is rapid even at 300 K, conversion of nitrites into surface nitrates (NO) occurs at a very low rate. After surface nitrate formation, no further reaction is observed. At higher temperature (500 K), conversion into surface nitrates is more facile and is followed by formation of ionic nitrates. All three nitrogen-oxo species can be clearly identified via their characteristic vibrational spectra. No spectroscopic evidence for the formation of other NO-derived surface species is found under the reaction conditions applied in this study. The results suggest that (i) conversion of the surface nitrite into the surface nitrate and (ii) formation of the ionic nitrate are the rate-controlling steps in the storage process. ©2008 American Chemical Society.

Model interfaces constructed from ordered oxide films: From heterogeneous catalysis to electrocatalysis, photoelectrocatalysis, and organic-oxide hybrid materials - Libuda, Jörg (ABSTRACTS OF PAPERS OF THE AMERICAN CHEMICAL SOCIETY, 2019)
CRIS-Team WoS Importer:2019-08-23

Model NOx Storage Materials at Realistic NO2 Pressures - Desikusumastuti, Aine; Schernich, Stefan; Happel, Markus; Sobota, Marek; Laurin, Mathias; Libuda, Jörg (ChemCatChem, 2009)
The interaction of NO2 with single-crystal-based model NOx storage materials, consisting of barium aluminate nanoparticles on Al2O3/NiAl(110), are investigated by time-resolved infrared reflection absorption spectroscopy (TR-IRAS) at realistic NO2 partial pressures up to 1.75 mbar. The data is compared to spectra obtained under ultrahigh vacuum (UHV) conditions on the same model system. At 300 K, the NO2 uptake at pressures around I mbar proceeds through rapid initial formation of surface nitrites and nitrates, similar to that under UHV conditions. The vibrational spectra of the surface species formed at realistic NO2 pressures are comparable to those for species formed under UHV conditions. Beyond the formation of surface species, the formation of bulk nitrates occurs, but is kinetically strongly hindered. At a very low rate, the formation of a disordered barium bulk nitrate is detected. At 500K, this kinetic hindrance is overcome and the available Ba2+ is quantitatively converted to bulk Ba(NO3)(2). The IRAs spectrum of these Ba(NO3)(2) particles differs characteristically from those obtained for nitrate multilayers formed upon incomplete conversion under UHV conditions. In addition to the formation of bulk Ba(NO3)(2), a more weakly bound disordered nitrate species is formed. This species gives rise to a dynamic NO2 uptake and release well below the decomposition temperature of bulk Ba(NO3)(2). The experiments show that model studies under UHV conditions mainly provide information on the initial reaction mechanism, whereas the observation of actual bulk NOx storage phases requires experiments at realistic temperatures and pressures.
Keywords: heterogeneous catalysis; vibrational spectroscopy; nitrogen oxides; scanning tunneling microscopy; supported catalysts

Model Studies in Heterogeneous Catalysis: From Structure to Kinetics - Libuda, Jörg; et al. (Monatshefte für Chemie, 2005)
Heterogeneous catalysis is one of the fields of modern technology, where the application of complex inorganic materials is of enormous economical importance. For a long time, the chemical and structural complexity of catalyst materials has precluded detailed insights into chemical processes on catalyst surfaces. In the last decades, however, substantial progress has been made toward a microscopic-level understanding of reaction mechanisms and kinetics, mainly based on the development of new well-defined model systems and on advances in experimental technology and theory. Scrutinizing the example of supported model catalysts, we review some of these innovations in model catalysis. As a particular challenging aspect of today's work, we discuss the question how detailed structural information on the model systems can be linked to catalytic reaction kinetics at the microscopic level. © Springer-Verlag 2004.
UnivIS-Import:2015-03-09:Pub.2005.nat.dchph.ppc20.models
Keywords: Carbon monoxide; Heterogeneous catalysis; Methanol; Nitrogen oxide; Palladium; Supported catalysts; Supported model catalysts

Modification of the growth of iron on Ag(111) by predeposited organic monolayers - Buchner, Florian; Kellner, Ina; Steinrück, Hans-Peter; Marbach, Hubertus (Zeitschrift für Physikalische Chemie-International Journal of Research in Physical Chemistry & Chemical Physics, 2009)
We study the modification of the growth behaviour of iron on Ag(l11) by preadsorbed monolayers of 2H-phthalocyanine (2HPc) and 2H-tetraphenylporphyrin (2HTPP) by scanning tunneling microscopy, upon Fe deposition in ultra-high vacuum at room temperature. The growth of iron on clean Ag(111) follows the scheme expected from reports of similar systems: For low coverages (up to-0.3 ML) an almost exclusive agglomeration of iron clusters at step edges occurs, which continue to grow in a dendritic fashion at higher coverages. Upon deposition onto Ag(l11) precovered with monolayers of 2HTPP and 2HPc, at coverages up to 0.037 ML no growth of Fe islands but complete metalation, i.e., incorporation of the Fe atoms in the macrocyle of the preadsorbed molecules is found. For higher amounts of deposited Fe (0.037 < 0 < 0.30 ML), the formation of Fe islands is observed, which occurs differently for 2HPC and 2HTPP. While on 2HTPP two-dimensional islands are formed presumably underneath a FeTPP monolayer, for 2HPc the Fe growth is dominated by the formation of small 3D clusters within a FePc monolayer. At 0 = 2.0 ML, both systems exhibit small three dimensional Fe islands. These results are discussed considering different aspects like the molecular conformation of FeTPP and FePc on Ag(111) and the diffusional properties of Fe on the clean and modified substrate. © by Oldenbourg Wissenschaftsverlag.

Molecular anchoring to oxide surfaces in ultrahigh vacuum and in aqueous electrolytes: phosphonic acids on atomically-defined cobalt oxide - Bertram, Manon; Schuschke, Christian; Waidhas, Fabian; Schwarz, Matthias; Hohner, Chantal; Montero, María A.; Brummel, Olaf; Libuda, Jörg (Physical Chemistry Chemical Physics, 2019)
In this work, we investigated the interaction of phenylphosphonic acid (PPA, C6H5PO3H2) with atomically-defined Co3O4(111) thin films, grown on Ir(100), under ultrahigh vacuum (UHV) conditions and in the electrochemical environment. In the first step, we employed infrared reflection absorption spectroscopy (IRAS) and followed the formation of a saturated monolayer (380 K) in UHV. We observed that the binding motif changes from a chelating tridentate in the sub-monolayer regime to a chelating bidentate at full monolayer coverages. In the electrochemical environment, we analyzed the interaction of PPA with the same Co3O4(111) surface by electrochemical infrared reflection absorption spectroscopy (EC-IRRAS) (0.3 VRHE-1.3 VRHE). When adsorbed at pH 10 from an ammonia buffered aqueous solution, PPA binds to the surface in form of a fully deprotonated chelating bidentate. With increasing electrode potential, we observed two fully reversible processes. At low buffer concentration, protons are released upon oxidation of surface Co2+ ions and lead to protonation of the anchored phosphonates. At high buffer concentration, most of the protons released are accepted by NH3. Simultaneously, the surface phosphonate changes its adsorption motif from bidentate to tridentate while adopting a more upright geometry.
CRIS-Team Scopus Importer:2019-11-08

Molecular beam experiments on model catalysts - Libuda, Jörg; et al. (Surface Science Reports, 2005)
Heterogeneous catalysts are highly complex materials with respect to both their composition and structure. The reaction kinetics on their surfaces is known to depend sensitively on numerous structural and chemical factors including the particle size and structure, the support or the presence of poisons and promotors. At the microscopic level, however, little is known about the microscopic origin of these effects. The main reason for this lack of knowledge is the vast complexity of typical heterogeneous catalysts and several experimental difficulties related to the application of modern surface science techniques to these systems. In this review, we summarize recent attempts to overcome these difficulties, based on the application of molecular beam methods to well-defined model catalysts. Using supported model catalysts, many aspects of the complex structural properties of real catalysts can be reproduced in a well-controlled manner. At the same time, the molecular beam approach allows quantitative and detailed investigations of the kinetics and dynamics of surface reactions. The combined information on structure and kinetics provides detailed insights into the kinetic phenomena on complex catalyst surfaces at the microscopic level. The processes studied so far include the kinetics of adsorption and desorption involving various adsorbates and the reaction kinetics of several simple surface reactions, such as, e.g. CO oxidation, NO dissociation, NO-CO reaction and methanol oxidation. Several kinetic phenomena have been identified which are specific to supported catalyst systems. These include, e.g. the role of the support in the reaction kinetics, the role of different types of adsorption and reaction sites on small active particles, the interplay of these sites via surface diffusion, the surface mobility of reactants, coverage fluctuations on small particles, local differences in catalytic activity and selectivity on active particles, as well as the role of co-adsorbates under reaction conditions. Special emphasis is put on the development of realistic microkinetics models based on experimentally determined structure and kinetics. © 2005 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2005.nat.dchph.ppc20.molecu
Keywords: Heterogeneous catalysis; Model catalysis; Molecular beams; Reaction kinetics; Surface reactions

Molecular Beams and Model Catalysis: Activity and Selectivity of Specific Reaction Centers on Supported Nanoparticles - Libuda, Jörg (ChemPhysChem, 2004)
Reaction kinetics on nanometer-scale particles are different from those on extended surfaces of bulk materials. This fact has been utilized for a long time to empirically maximize the performance of heterogeneous catalysts, but the understanding of the underlying effects is poor at the microscopic level. Modern molecular-beam-based methods, however, allow us to derive very detailed kinetic information on catalytically active surfaces. In combination with structurally highly controlled model catalysts, microscopic insights into the activity and selectivity of specific reaction centers on catalyst nanoparticles can be obtained. This combined approach is illustrated through simple model reactions.
UnivIS-Import:2015-03-09:Pub.2004.nat.dchph.ppc20.molecu
Keywords: Heterogeneous catalysis; Kinetics; Molecular beams; Nanostructures; Surface chemistry

Molecular Orientation and Structural Transformations in Phthalic Anhydride Thin Films on MgO(100)/Ag(100) - Mohr, Susanne; Xu, Tao; Döpper, Tibor; Laurin, Mathias; Görling, Andreas; Libuda, Jörg (Langmuir, 2015)
Structural control of organic thin films on dielectric substrates is the key to tailoring the. physical properties of hybrid Materials, for example, for application in solar energy conversion, molecular electronics, or catalysis. In, this work, we investigate the molecular orientation of phthalic: anhydride (PAA) films on atomically well-defined mgO(100) on Ag(100) using temperature-programmed infrared reflection absorption spectroscopy (TP-IRAS) in combination with density-functional theory (DFT). A robust procedure is presented to determine the orientation of the FAA Molecules, which relies on the intensity ratios of vibrational bands only We show that even at deposition temperatures of 110 K, the PAA multilayer grows with a-Specific molecular, orientation; that is the PAA Molecular plane is preferentially aligned parallel with the MgO surface,. No change of molecular orientation occurs up to a temperature of 145 K Between 145 and 160 K, the film restructures adopting a nearly flat lying molecular Orientation. Between 170 and 205 K, the film undergoes a second structural transition to a crystalline phase. This transition is associated with a pronounced molecular reorientation. The molecules adopt a tilted orientation and, simultaneously, rotate around their C-2 axes The reorientation behavior Suggests that the molecular orientation in the crystalline phase is controlled by the interaction with the MgO(100) substrate. At higher temperature, no further restructuring is observed until the PAA. multilayer desorbs at temperatures above 230 K.

Molecular Stacking on Graphene - Wei, Tao; Liu, Xin; Kohring, Malte; Al-Fogra, Sabrin; Moritz, Michael; Hemmeter, Daniel; Paap, Ulrike; Papp, Christian; Steinrück, Hans-Peter; Bachmann, Julien; Weber, Heiko B.; Hauke, Frank; et al. (Angewandte Chemie International Edition, 2022)
The sequentialverticalpolyfunctionalizationof 2D addend-patternedgrapheneis still elusive.Here,we reporta practicalrealizationof this goalvia a “molecularbuildingblocks”approach,whichis basedon a combinationof alithography-assistedreductivefunctionalizationapproachanda post-functionalizationstepto sequentiallyandcontrollablylink the molecularbuildingblocksethylpyridine,cis-dichlorobis(2,2’-bipyridyl)ruthenium,and triphenyl-phosphine(4-methylbenzenethiol,respectively)on selectedlatticeregionsof a graphenematrix.The assembled2Dhetero-architecturesare unambiguouslycharacterizedby variousspectroscopicand microscopicmeasurements,revealingthe stepwisestackingof the molecularbuildingblockson the graphenesurface.Our methodovercomesthe currentlimitationof a one-layer-onlybindingto the graphenesurfaceand opensthe doorfor a verticalgrowthin the z-directio

Monitoring of liquid-phase organic reactions by photoelectron spectroscopy - Kolbeck, Claudia; Niedermaier, Inga; Taccardi, Nicola; Schulz, Peter; Maier, Florian; Wasserscheid, Peter; Steinrück, Hans-Peter (Angewandte Chemie International Edition, 2012)
There are strings attached: After linking the reacting groups to head groups of ionic liquids to drastically lower the vapour pressures of the reactants, ordinary liquid-phase organic reactions can be monitored by in situ X-ray photoelectron spectroscopy. This approach is demonstrated for the nucleophilic substitution of an alkyl amine and an alkyl chloride moiety, which are attached to the cation and anion of ionic liquids, respectively. Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Morphology changes of ionic liquid encapsulating polymer microcontainers upon X-ray irradiation - Späth, Andreas; Minami, Hideto; Suzuki, Toyoko; Fink, Rainer (RSC Advances, 2014)
Microencapsulated ionic liquids represent a novel type of material with high potential for various applications in chemical synthesis, catalysis or separation processes. We present a detailed morphological analysis of this material by means of two imaging techniques, i.e., scanning transmission X-ray microspectroscopy (STXM) and transmission electron microscopy (TEM). While TEM can be utilized only in the dry state, STXM offers access to high-resolution imaging in liquid surroundings. In either case prolonged illumination leads to degradation of the stabilizing polymer. We discuss potential scenarios, e.g., formation of perforations within the polymer shell, to explain the experimental findings.

Morphology dependent interaction between Co(ii)-tetraphenylporphyrin and the MgO(100) surface - Ninova, Silviya; Malcıoğlu, Osman Barış; Auburger, Philipp; Franke, Matthias; Lytken, Ole; Steinrück, Hans-Peter; Bockstedte, Michel (Physical Chemistry Chemical Physics, 2021)
Porphyrins are key elements in organic-inorganic hybrid systems for a wide range of applications. Understanding their interaction with the substrate gives a handle on structural and electronic device properties. Here we investigate a single transition-metal porphyrin, namely Co(ii)-tetraphenylporphyrin (CoTPP), on the MgO(100) surface and the effect of multilayer film formation within hybrid density-functional theory and many-body perturbation theory. We focus on the relevant adsorption sites, simulate their photoemission spectra as a key fingerprint and compare with experiments on MgO(100) films on Ag(100). While we find only weak interaction between the cobalt centre and terrace sites on the MgO(100) surface, a strong interaction manifests itself with the low-coordinated sites. This leads to distinct features in both the valence and core-level regions of the electronic structure, as observed in the ultraviolet and X-ray photoemission spectra, corroborated by simulated spectra and calculated cobalt core-level shifts. Our work thus demonstrates the relevance of morphology-related low-coordinated sites and their properties in the adsorption of CoTPP on the MgO(100) surface.
CRIS-Team Scopus Importer:2021-02-12

Multiple surface plasmon excitations in overlayers of K and Na on Ru(001) - Zharnikov, M.; Mehl, D.; Steinrück, Hans-Peter (Journal of Electron Spectroscopy and Related Phenomena, 1994)
Electron energy loss spectra in the reflection geometry have been measured for potassium and sodium layers on Ru(001) for coverages ranging from N = 1 up to 16-20 layers. The experimental conditions (primary energy, angle-of-incidence) allowed excitation of multiple surface plasmons. For all systems, energy and damping of the surface plasmons together with the integral probability for surface plasmon excitation have been determined. For the variation of these parameters with alkali layer thickness, two coverage regimes can be distinguished that are correlated to different types of excitations. For N ≤ 1 one-electron excitations are very important; for N ≥ 2 a collective response (well-defined surface plasmon excitations) takes place. The slowly decreasing energy of the surface plasmon with increasing alkali thickness to the bulk values is in qualitative agreement with both macroscopic and microscopic descriptions. The thickness dependences of the damping and the integral excitation probability indicate that one-electron contributions which are very important for N = 1 are also present for N = 2 and only slowly decrease with increasing thickness of the alkali layer. The analysis of the EELS data for N ≥ 2 shows that the excitation probability for multiple surface plasmons follows the Poisson distribution; the data are consistent with the consecutive excitation of individual surface plasmons. © 1994.

mu-XRF Studies on the Colour Brilliance in Ancient Wool Carpets - Meyer, Markus; Borca, Camelia N.; Huthwelker, Thomas; Bieber, Manfred; Meßlinger, Karl; Fink, Rainer; Späth, Andreas (Scanning, 2017)
Many handmade ancient and recent oriental wool carpets show outstanding brilliance and persistence of colour that is not achieved by common industrial dyeing procedures. Anthropologists have suggested the influence of wool fermentation prior to dyeing as key technique to achieve the high dyeing quality. By means of mu-XRF elemental mapping of mordant metals we corroborate this view and show a deep and homogenous penetration of colourants into fermented wool fibres. Furthermore we are able to apply this technique and prove that the fermentation process for ancient specimens cannot be investigated by standard methods due to the lack of intact cuticle layers. This finding suggests a broad range of further investigations that will contribute to a deeper understanding of the development of traditional dyeing techniques. Spectroscopic studies add information on the oxidation states of the metal ions within the respective mordant-dye-complexes and suggest a partial charge transfer as basis for a significant colour change when Fe mordants are used.
EVALuna2:33356

Nanofacet Resolved CO Oxidation Kinetics on Alumina Supported Model Catalysts and the Role of Oxygen Diffusion - Libuda, Jörg; et al. (Chemical Physics Letters, 2002)
UnivIS-Import:2015-03-09:Pub.2002.nat.dchph.ppc20.nanofa

Nanolithographic Top-Down Patterning of Polyoxovanadate-based Nanostructures with Switchable Electrical Resistivity - Rösner, Benedikt; Fallica, Roberto; Johnson, Manuel; Späth, Andreas; Fink, Rainer; Ekinci, Yasin; David, Christian; Anjass, Montaha H.; Streb, Carsten (ChemNanoMat, 2020)
The top-down lithographic fabrication of functional metal oxide nanostructures enables technologically important applications such as catalysis and electronics. Here, we report the use of molecular vanadium oxides, polyoxovanadates, as molecular precursors for electron beam lithography to obtain functional vanadium oxide nanostructures. The new resist class described gives access to nanostructures with minimum dimensions close to 10 nm. The lithographically prepared structures exhibit temperature-dependent switching behaviour of their electrical resistivity. The work could lay the foundation for accessing functional vanadium oxide nanostructures in the sub-10-nm domain using industrially established nanolithographic methods.
CRIS-Team Scopus Importer:2020-08-28
Keywords: Metal Oxide; Nanostructure; Polyoxometalates; Self-Assembly; Vanadium Oxide

Nanomorphology in thin films of acetamide end-functionalised quaterthiophene - Zeilmann, Nina; Rösner, Benedikt; Späth, Andreas; Schmidt, Ute; Fink, Rainer (Thin Solid Films, 2015)
<span style="color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;">α,ω-Functionalised oligothiophenes are promising materials for organic field effect transistors due to their high degree of molecular ordering, crystallinity and π-π stacking. We employ several complementary microspectroscopic probes to investigate the formation of thermally evaporated films of 5,5‴-bis(<em style="margin: 0px; padding: 0px; box-sizing: border-box; color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;">N<span style="color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;">-acetamido-2-ethyl)-2,2′:5′,2″:5″,2‴quaterthiophene on inert substrates. These films were found to grow in a mixed fashion, featuring layer-by-layer domains with thicknesses of several monolayers and needle-shaped three-dimensional crystals. Detailed analysis of atomic force microscopy (AFM) and photoluminescence microscopy reveals the micro- and nanomorphology of the films. Linear dichroism in the near edge x-ray absorption fine structure and polarisation-dependent laser excitation corroborate the findings of AFM, <em style="margin: 0px; padding: 0px; box-sizing: border-box; color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;">i.e.<span style="color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;">, upright standing molecules in the multilayer regime. The shape of the 3-dimensional crystallites and multilayer domains indicates strongly anisotropic growth favoured by the herringbone-arrangement of the thiophene moieties and additional stabilisation by hydrogen bonding of the acetamide end groups.
Keywords: Quaterthiophene; Organic field effect transistor; Confocal Raman microscopy; Near edge x-ray absorption fine structure spectroscopy; Scanning transmission x-ray microscopy

Nanoporous Au: An Unsupported Pure Gold Catalyst? - Wittstock, Arne; Neumann, Björn; Schaefer, Andreas; Dumbuya, Karifala; Kübel, Christian; Biener, Monika M.; Zielasek, Volkmar; Steinrück, Hans-Peter; Gottfried, Michael; Biener, Jürgen; Hamza, Alex; Bäumer, Marcus (Journal of Physical Chemistry C, 2009)
The unique properties of gold especially in low temperature CO oxidation have been ascribed to a combination of various effects. In particular, particle sizes below a few nanometers and specific particle-support interactions have been shown to play important roles. In contrast, recent reports revealed that monolithic nanoporous gold (npAu) prepared by leaching a less noble metal, such as Ag, out of the corresponding alloy can also exhibit a remarkably high catalytic activity for CO oxidation, even though no support is present. Therefore, it was claimed to be a pure and unsupported gold catalyst. We investigated npAu with respect to its morphology, surface composition, and catalytic properties. In particular, we studied the reaction kinetics for low temperature CO oxidation in detail, taking the mass transport limitation due to the porous structure of the material into account. Our results reveal that Ag, even if removed almost completely from the bulk, segregates to the surface, resulting in surface concentrations of up to 10 atom %. Our data suggest that this Ag plays a significant role in activating of molecular oxygen. Therefore, npAu should be considered a bimetallic catalyst rather than a pure Au catalyst.

Nanoscale architecture of ceria-based model catalysts: Pt–Co nanostructures on well-ordered CeO2(111) thin films - Lykhach, Yaroslava; Skála, Tomáš; Neitzel, Armin; Tsud, Nataliya; Beranová, Klára; Prince, Kevin C.; Matolín, Vladimír; Libuda, Jörg (Chinese Journal of Catalysis, 2020)
We have prepared and characterized atomically well-defined model systems for ceria-supported Pt–Co core–shell catalysts. Pt@Co and Co@Pt core–shell nanostructures were grown on well-ordered CeO2(111) films on Cu(111) by physical vapour deposition of Pt and Co metals in ultrahigh vacuum and investigated by means of synchrotron radiation photoelectron spectroscopy and resonant photoemission spectroscopy. The deposition of Co onto CeO2(111) yields Co–CeO2(111) solid solution at low Co coverage (0.5 ML), followed by the growth of metallic Co nanoparticles at higher Co coverages. Both Pt@Co and Co@Pt model structures are stable against sintering in the temperature range between 300 and 500 K. After annealing at 500 K, the Pt@Co nanostructure contains nearly pure Co-shell while the Pt-shell in the Co@Pt is partially covered by metallic Co. Above 550 K, the re-ordering in the near surface regions yields a subsurface Pt–Co alloy and Pt-rich shells in both Pt@Co and Co@Pt nanostructures. In the case of Co@Pt nanoparticles, the chemical ordering in the near surface region depends on the initial thickness of the deposited Pt-shell. Annealing of the Co@Pt nanostructures in the presence of O2 triggers the decomposition of Pt–Co alloy along with the oxidation of Co, regardless of the thickness of the initial Pt-shell. Progressive oxidation of Co coupled with adsorbate-induced Co segregation leads to the formation of thick CoO layers on the surfaces of the supported Co@Pt nanostructures. This process is accompanied by the disintegration of the CeO2(111) film and encapsulation of oxidized Co@Pt nanostructures by CeO2 upon annealing in O2 above 550 K. Notably, during oxidation and reduction cycles with O2 and H2 at different temperatures, the changes in the structure and chemical composition of supported Co@Pt nanostructures were driven mainly by oxidation while reduction treatments had little effect regardless of the initial thickness of the Pt-shell.
CRIS-Team Scopus Importer:2020-02-07
Keywords: Cerium oxide; Chemical ordering; Core-shell nanoparticles; Model catalyst; Pt–Co; Synchrotron radiation photoelectron spectroscopy

Nanoscale Morphological and Structural Transformations of PtCu Alloy Electrocatalysts during Potentiodynamic Cycling - Khalakhan, Ivan; Waidhas, Fabian; Brummel, Olaf; Vorokhta, Mykhailo; Kus, Peter; Yakovlev, Yurii; Bertram, Manon; Dopita, Milan; Matolinova, Iva; Libuda, Jörg; Matolin, Vladimir (Journal of Physical Chemistry C, 2018)
PtCu bimetallic alloys are known to provide better activity than pure platinum in proton exchange membrane fuel cells. However, such catalysts undergo complex degradation processes during fuel cell operation, resulting in deterioration of their activity. By using in situ electrochemical (EC) atomic force microscopy combined with in situ EC infrared reflection absorption spectroscopy, we provide a comprehensive investigation of morphological and structural transformations of PtCu model thin film catalysts during accelerated degradation tests (ADTs). The ADTs consist of potentiodynamic cycling to three different upper potentials relevant for different modes of fuel cell operation. The results show that, depending on the upper potential limit, PtCu alloy electrocatalysts are subject to drastic changes in the surface composition, morphology, and structure.

Nanoscale Ruthenium-Containing Deposits from Ru(CO)4I2via Simultaneous Focused Electron Beam-Induced Deposition and Etching in Ultrahigh Vacuum: Mask Repair in Extreme Ultraviolet Lithography and beyond - Bilgilisoy, Elif; Yu, Jo Chi; Preischl, Christian; McElwee-White, Lisa; Steinrück, Hans-Peter; Marbach, Hubertus (ACS Applied Nano Materials, 2021)
The deposition of nanoscaled structures with a desired shape on the intended position of the substrate material is crucial for nanomaterial applications. Electron beam-induced deposition with a highly focused beam enables achievement of high accuracy and precision in this respect. Hence, we investigated the focused-electron-beam-induced deposition of Ru-containing deposits on SiO2 and sputter-cleaned silicon in ultrahigh vacuum to achieve comparably clean and morphologically well-defined Ru nanomaterials, which is relevant especially in the field of mask repair for extreme ultraviolet lithography. The precursor Ru(CO)4I2 was held at 340-345 K, and the applied electron doses were varied from 1.56 to 9.36 C/cm2 using a focused electron beam (5 keV, 1.5 nA, and 10 nm diameter). Local Auger electron spectroscopy along with subsequent sophisticated fitting procedures not only revealed the elemental composition but also enabled determination of the thickness of the fabricated deposits. Ru contents of up to 56% can be achieved at lower electron doses; at higher doses, the Ru content decreases to 45% and simultaneously the content increases. The initially lower I content is attributed to simultaneous focused electron beam-induced etching, which is found to be competing with the deposition process. The etching is evidenced by atomic force microscopy, where the structures are observed to have negative apparent height for low electron doses. With increasing electron doses, the deposits exhibit positive apparent heights because the etching is less pronounced at higher electron doses, once the Ru surface coverage has increased. The high Ru content and difficult balance between electron-induced deposition and etching considerably expand the possibilities of engineering nanostructured materials.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Auger electron spectroscopy (AES); focused electron beam-induced deposition (FEBID); focused electron beam-induced etching (FEBIE); ruthenium nanomaterials; scanning electron microscopy (SEM)

Nano-SMSI on Bimetallic FePt Clusters - Waleska-Wellnhofer, Natalie; Freiberger, Marie; Hemauer, Felix; Schwaab, Valentin; Papp, Christian (Journal of Physical Chemistry C, 2023)
Nano-strong metal-support interaction is observed in this work for bimetallic FePt nanoclusters on graphene/Rh(111). FePt clusters were prepared by successively depositing 1.27 ML Fe and 0.14 ML Pt on the graphene/Rh(111) substrate. Oxidation of Fe was achieved by CO dissociation, while CO was simultaneously used as a probe molecule to gather information about the clusters’ structure. After UHV annealing to 550 K, encapsulation of Pt with an Fe oxide layer and a strong decrease of the chemisorption capacity of the clusters was found. Further increase of the temperature to 900 K leads to the decomposition of the Fe oxide layer and the intercalation of Fe. Besides, the formation of an FePt alloy was observed at elevated temperature.
CRIS-Team Scopus Importer:2023-11-03

Nanostructure characterization by a combined x-ray absorption/scanning force microscopy system - Pilet, Nicolas; Raabe, Joerg; Stevenson, Stephanie E.; Romer, Sara; Bernard, Laetitia; Mcneill, Christopher R.; Fink, Rainer; Hug, Hans J.; Quitmann, Christoph (Nanotechnology, 2012)
A combined x-ray transmission and scanning force microscope setup (NanoXAS) recently installed at a dedicated beamline of the Swiss Light Source combines complementary experimental techniques to access chemical and physical sample properties with nanometer scale resolution. While scanning force microscopy probes physical properties such as sample topography, local mechanical properties, adhesion, electric and magnetic properties on lateral scales even down to atomic resolution, scanning transmission x-ray microscopy offers direct access to the local chemical composition, electronic structure and magnetization. Here we present three studies which underline the advantages of complementary access to nanoscale properties in prototype thin film samples. © 2012 IOP Publishing Ltd.

NanoXAS, a novel concept for high resolution microscopy - Fink, Rainer; Raabe, Jörg; Quitmann, Christoph; Hug, Hans J.; et al. (Journal of Physics: Conference Series (JPCS) Volume 186/Band 1, 2009)

NanoXAS - The in situ combination of scanning transmission X-ray and scanning probe microscopy - Wenzel, Stephan; Fink, Rainer; Raabe, Jörg; Quitmann, Christoph; Hug, Hans J.; et al. (10th International Conference on X-Ray Microscopy, 2010)
NanoXAS is a novel x-ray microscope installed at the Swiss Light Source combining laterally resolved soft x-ray spectroscopy with scanning probe microscopy. We report on first in situ studies from thin polymer blend films and magnetic materials where topographic and spectroscopic contrast are used and show how complementary imaging modes provide new insight into many materials. In the future the scanning probe tip will be used to collect photoelectrons. By this we expect a spatial resolution in the few-nm range and unique information on surface and bulk properties of nano-materials. © 2011 American Institute of Physics.

n-Butane, iso-Butane and 1-Butene Adsorption on Imidazolium-Based Ionic Liquids Studied with Molecular Beam Techniques - Winter, Leonhard; Bhuin, Radha Gobinda; Maier, Florian; Steinrück, Hans-Peter (Chemistry - A European Journal, 2021)
The interaction of molecules, especially hydrocarbons, at the gas/ionic liquid (IL) surface plays a crucial role in supported IL catalysis. The dynamics of this process is investigated by measuring the trapping probabilities of n-butane, iso-butane and 1-butene on a set of frozen 1-alkyl-3-methylimidazolium-based ILs [CnC1Im]X, where n=4, 8 and X−=Cl−, Br−, [PF6]− and [Tf2N]−. The decrease of the initial trapping probability with increasing surface temperature is used to determine the desorption energy of the hydrocarbons at the IL surfaces. It increases with increasing alkyl chain length n and decreasing anion size for the ILs studied. We attribute these effects to different degrees of alkyl chain surface enrichment, while interactions between the adsorbate and the anion do not play a significant role. The adsorption energy also depends on the adsorbing molecule: It decreases in the order n-butane>1-butene>iso-butane, which can be explained by different dispersion interactions.
CRIS-Team Scopus Importer:2021-10-08
Keywords: adsorption; catalysis; gas-surface dynamics; ionic liquids; molecular beam

Near ambient pressure XPS investigation of the interaction of ethanol with Co/CeO2(1 1 1) - Ovari, L.; Krick Calderon, Sandra; Lykhach, Yaroslava; Libuda, Jörg; Erdohelyi, A.; Papp, Christian; Kiss, J.; Steinrück, Hans-Peter (Journal of Catalysis, 2013)
Near ambient pressure X-ray photoelectron spectroscopy was applied to study the interaction of ethanol (CHCHOH) with a well-ordered CeO(1 1 1) film on Cu(1 1 1) and with a Co/CeO(1 1 1)/Cu(1 1 1) model catalyst. The oxidation state of the surface and the chemical nature of reaction intermediates were analyzed. At 300 K, the oxidation state of ceria decreased gradually with increasing ethanol pressure. At a constant pressure of 0.1 mbar, the reduction of Ce to Ce increased significantly between 320 and 600 K due to a higher mobility of oxygen or Ce centers at elevated temperatures. The main intermediate, ethoxide, was formed by dissociative adsorption of ethanol at room temperature. No coke formation was observed up to 600 K on CeO. Upon deposition of metallic cobalt, partial reduction of ceria was observed, leading to the formation of Co sites but still leaving metallic Co in the metal particles. During the reaction of ethanol with the Co/CeO(1 1 1) model catalyst, the amount of Co decreased drastically with increasing temperature, and at 600 K, the majority of Co was metallic. This process was accompanied by the severe reduction of ceria and the formation of significant carbon deposits. © 2013 Elsevier Inc. All rights reserved.

New hybrid materials consisting of solid or liquid substrate with tin ultra pure ionic liquid film. - Cremer, Till; Maier, Florian; Steinrück, Hans-Peter; Wasserscheid, Peter (2009)
This invention claims new hybrid materials consisting of a solid or liq. substrate and an extremely thin film of an ultra-pure ionic liq., where the film thickness of the applied ionic liq. amts. to less than ten nanometers, preferably less then two nanometers. This extremely thin, ultra-pure film lends to the new hybrid materials with surprising and tech. interesting surface properties, different to substrate it self, different to substrate with a thicker film and different to substrate with a less pure film of the same ionic liq. This extremely thin ultra-pure film on solid or liq. substrate changes elec. cond., catalytic activity, optical, tribol., mech. properties, sensory and permeation/sepn. capability or stability against oxidn. by air of coated substrate. The ultra pure ionic liq. has a formula [A]n+[Y]n-, where A is quaternary ammonium, phosphonium, imidazolium, pyridinium, pyrazolium and triazolium cation, n= 1 or 2 and Y is an anion such as tetrafluoroborate, hexafluorophosphate, dicyanamide, tricyanomethid, tetracyano borate, halogenide or others which is applied at temp. of 30-400° under high vacuum over liq. or solid substrate kept at -200-350°. [on SciFinder(R)]
Keywords: substrate pure ionic liq nanoscale surface modification hybrid material

New set-up for high-quality soft-X-ray absorption spectroscopy of large organic molecules in the gas phase - Holch, Florian; Huebner, Dominique; Fink, Rainer; Schoell, Achim; Umbach, Eberhard (Journal of Electron Spectroscopy and Related Phenomena, 2011)
We present a new experimental set-up for the investigation of large (>128 amu) organic molecules in the gas-phase by means of near-edge X-ray absorption fine structure spectroscopy in the soft X-ray range. Our approach uses a gas cell, which is sealed off against the surrounding vacuum and which can be heated above the sublimation temperature of the respective molecular compound. Using a confined volume rather than a molecular beam yields short acquisition times and intense signals due to the high molecular density, which can be tuned by the container temperature. In turn, the resulting spectra are of very high quality with respect to signal-to-noise ratio and energy resolution, which are the essential aspects for the analysis of fine spectroscopic details. Using the examples of ANQ, NTCDA, and PTCDA, specific challenges of gas phase measurements on large organic molecules with high sublimation temperatures are addressed in detail with respect to the presented set-up and possible ways to tackle them are outlined. © 2011 Published by Elsevier B.V. All rights reserved.

New setup for in situ x-ray photoelectron spectroscopy from ultrahigh vacuum to 1 mbar - Pantförder, Jörg; Pöllmann, Silke Andrea; Zhu, Junfa; Borgmann, Dieter; Denecke, Reinhard; Steinrück, Hans-Peter (Review of Scientific Instruments, 2005)
In an effort to extend the pressure range for electron-based spectroscopies from ultrahigh vacuum into the so-called pressure gap region, we have built a new apparatus for in situ x-ray photoelectron spectroscopy up to 1 mbar. The principle of the experimental setup is based on a modified hemispherical electron energy analyzer, a modified twin anode x-ray source, and several differential-pumping stages between sample region and electron detection. The reaction gas is provided in situ either by background dosing or, as a new feature, by beam dosing, using a directed gas beam from a small tube. The latter allows for higher local pressures. The performance of the new setup is discussed, deriving normalization procedures from the analysis of the attenuation of the substrate photoemission intensity by the increasing gas phase pressure. In addition, the change of the work function due to changes in surface composition can be evaluated in situ by analyzing the binding energy shift of the gas phase core-level peaks. As a first study, measurements for the pressure dependence of CO adsorption on Pd(111) between 5× 10-8 and 1 mbar are presented. © 2005 American Institute of Physics.

Nitrite and nitrate formation on model NOx storage materials: on the influence of particle size and composition - Desikusumastuti, Aine; Qin, Zhihui; Happel, Markus; Staudt, Thorsten; Lykhach, Yaroslava; Laurin, Mathias; Rohr, F.; Shaikhutdinov, S.; Libuda, Jörg (Physical Chemistry Chemical Physics, 2009)
A well-defined model-catalyst approach has been utilized to study the formation and decomposition of nitrite and nitrate species on a model NOx storage material. The model system comprises BaAl2xO1+3x particles of different size and stoichiometry, prepared under ultrahigh-vacuum (UHV) conditions on Al2O3/NiAl(110). Adsorption and reaction of NO2 has been investigated by molecular beam (MB) methods and time-resolved IR reflection absorption spectroscopy (TR-IRAS) in combination with structural characterization by scanning tunneling microscopy (STM). The growth behavior and chemical composition of the BaAl2xO1+3x particles has been investigated previously. In this work we focus on the effect of particle size and stoichiometry on the reaction with NO2. Particles of different size and of different Ba2+ :Al3+ surface ion ratio are prepared by varying the preparation conditions. It is shown that at 300 K the reaction mechanism is independent of particle size and composition, involving initial nitrite formation and subsequent transformation of nitrites into surface nitrates. The coordination geometry of the surface nitrates, however, changes characteristically with particle size. For small BaAl2xO1+3x particles high temperature (800 K) oxygen treatment gives rise to particle ripening, which has a minor effect on the NO2 uptake behavior, however. STM shows that the morphology of the particle system is largely conserved during NO2 exposure at 300 K. The reaction is limited to the formation of surface nitrites and nitrates, which are characterized by low thermal stability and completely decompose below 500 K. As no further sintering occurs before decomposition, NO2 uptake and release is a fully reversible process. For large BaAl2xO1+3x particles, aggregates with different Ba2+ :Al3+ surface ion ratio were prepared. It was shown that the stoichiometry has a major effect on the kinetics of NO2 uptake. For barium-aluminate-like particles with high Al3+ concentration, the formation of nitrites and nitrates on the BaAl2xO1+3x particles at 300 K is slow, and kinetically restricted to the formation of surface species. Only at elevated temperature (500 K) are surface nitrates converted into well-defined bulk Ba(NO3)(2). This bulk Ba(NO3)(2) exhibits substantially higher thermal stability and undergoes restructuring and sintering before it decomposes at 700 K. For Ba2+-rich BaAl2xO1+3x particles, on the other hand, nitrate formation occurs at a much higher rate than for the barium-aluminate-like particles. Furthermore, nitrate formation is not limited to the surface, but NO2 exposure gives rise to the formation of amorphous bulk Ba(NO3)(2) particles even at 300 K.

NO-induced reorganization of porphyrin arrays - Buchner, Florian; Seufert, Knud; Auwärter, Willi; Heim, Daniel; Barth, Johannes V.; Flechtner, Ken; Gottfried, Michael; Steinrück, Hans-Peter; Marbach, Hubertus (Acs Nano, 2009)
We studied the interaction of a highly ordered array of Co-tetraphenylporphyrin (CoTPP) with NO on Ag(111) by in situ scanning tunneling microscopy and X-ray photoelectron spectroscopy. Upon NO exposure, the initially quadratically ordered CoTPP layer reorganizes, showing a wealth of highly ordered NO+CoTPP coadsorbate phases with increasing size of the unit cell, interpreted as due to attractive lateral dipole-dipole interactions between the two species. The findings not only suggest a novel approach to control the arrangement of adsorbed porphyrins in particular but also should generally be considered in the production of functional layers from large organic molecules under ambient conditions or after exposure to small electronegative molecules. © 2009 American Chemical Society.

NO-induced reversible switching of the electronic interaction between a porphyrin-coordinated cobalt ion and a silver surface - Flechtner, Ken; Kretschmann, Andreas; Steinrück, Hans-Peter; Gottfried, Michael (Journal of the American Chemical Society, 2007)
The electronic interaction between a porphyrin-coordinated Co ion and a silver surface was switched by an axial nitric oxide (NO) ligand on the Co ion. This process is reversible and was monitored with X-ray and UV-photoelectron spectroscopy (XPS and UPS). The Co-Ag interaction leads to an electron transfer from the Ag surface to the Co ion and to a new electronic state close to the Fermi level. Both effects vanish if an axial NO ligand coordinates to the Co ion, indicating that the Co-Ag interaction is suppressed. As a possible explanation, we discuss a competition, similar to the trans effect, between the two axial ligands on the Co ion: the NO molecule and the Ag surface. These findings have important implications for sensor technology and for catalysis on supported metalloporphyrins, in which the catalytic activity of the metal center is controlled by the interaction with the underlying surface. Copyright © 2007 American Chemical Society.

O2 adsorption dependent photoluminescence emission from metal oxide nanoparticles - Gheisi, Amirreza; Neygandhi, Chris; Sternig, Andreas; Carrasco, Esther; Marbach, Hubertus; Thomele, Daniel; Diwald, Oliver (Physical Chemistry Chemical Physics, 2014)
Optical properties of metal oxide nanoparticles are subject to synthesis related defects and impurities. Using photoluminescence spectroscopy and UV diffuse reflectance in conjunction with Auger electron spectroscopic surface analysis we investigated the effect of surface composition and oxygen adsorption on the photoluminescence properties of vapor phase grown ZnO and MgO nanoparticles. On hydroxylated MgO nanoparticles as a reference system, intense photoluminescence features exclusively originate from surface excitons, the radiative deactivation of which results in collisional quenching in an O2 atmosphere. Conversely, on as-prepared ZnO nanoparticles a broad yellow emission feature centered at h extgreeknEm = 2.1 eV exhibits an O2 induced intensity increase. Attributed to oxygen interstitials as recombination centers this enhancement effect originates from adsorbate-induced band bending, which is pertinent to the photoluminescence active region of the nanoparticles. Annealing induced trends in the optical properties of the two prototypical metal oxide nanoparticle systems, ZnO and MgO, are explained by changes in the surface composition and underline that particle surface and interface changes that result from handling and processing of nanoparticles critically affect luminescence.
EAM Import::2019-03-08

One-dimensional band structures: Rare gases on Pt(110)1×2 - Weinelt, M.; Trischberger, P.; Widdra, Wolf; Eberle, K.; Zebisch, P.; Gokhale, S.; Menzel, Dietrich; Henk, Jürgen; Feder, R.; Dröge, H.; Steinrück, Hans-Peter (Physical Review B, 1995)
The formation of one-dimensional band structures has been observed for Kr and Xe adsorbed on the reconstructed Pt(110)1×2 surface at submonolayer coverages: The p3/2 and p1/2 valence levels of both adsorbates exhibit significant dispersion for the [110] direction, i.e., along the densely packed substrate rows, but no dispersion is observed for [001], i.e., perpendicular to the rows. The observed k-space periodicities and tight-binding band-structure calculations imply that both Kr and Xe are adsorbed in densely packed linear chains on the reconstructed Pt(110)1×2 surface, with negligible interaction between neighboring rows. © 1995 The American Physical Society.

One-dimensional xenon band structures on hydrogen modified and stepped platinum surfaces - Trischberger, P.; Dröge, H.; Gokhale, S.; Henk, Jürgen; Steinrück, Hans-Peter; Widdra, Wolf; Menzel, Dietrich (Surface Science, 1997)
The adsorption of xenon on hydrogen modified Pt(110)-(1 × 2) and on Pt(997) has been studied using TPD, LEED, XPS, and ARUPS. On Pt(110)-(1 × 2) with preadsorbed hydrogen, a single xenon species forming one-dimensional adsorbate chains in the [11̄0] direction is found. ARUPS shows well-resolved dispersion of the xenon 5p and the split Sp bands in the [11̄0] azimuth, but no dispersion in the [001] direction, in agreement with the packing density. On Pt(997) xenon decorates the close-packed steps in [11̄0] direction at low coverages. No dispersion of xenon bands is seen in ARUPS, indicating weak lateral adsorbate interaction along the chains as expected from the relatively large Xe-Xe distance of 5.6 Å extracted from LEED.

On-Surface Metathesis of an Ionic Liquid on Ag(111) - Massicot, Stephen; Sasaki, Tomoya; Lexow, Matthias; Maier, Florian; Kuwabata, Susumu; Steinrück, Hans-Peter (Chemistry - A European Journal, 2022)
We investigated the adsorption, surface enrichment, ion exchange, and on-surface metathesis of ultrathin mixed IL films on Ag(111). We stepwise deposited 0.5 ML of the protic IL diethylmethylammonium trifluoromethanesulfonate ([dema][TfO]) and 1.0 ML of the aprotic IL 1-methyl-3-octylimidazolium hexafluorophosphate ([C8C1Im][PF6]) at around 90 K. Thereafter, the resulting layered frozen film was heated to 550 K, and the thermally induced phenomena were monitored in situ by angle-resolved X-ray photoelectron spectroscopy. Between 135 and 200 K, [TfO]− anions at the Ag(111) surface are exchanged by [PF6]− anions and enriched together with [C8C1Im]+ cations at the IL/vacuum interface. Upon further heating, [dema][PF6] and [OMIm][PF6] desorb selectively at ∼235 and ∼380 K, respectively. Hereby, a wetting layer of pure [C8C1Im][TfO] is formed by on-surface metathesis at the IL/metal interface, which completely desorbs at ∼480 K. For comparison, ion enrichment at the vacuum/IL interface was also studied in macroscopic IL mixtures, where no influence of the solid support is expected.
CRIS-Team Scopus Importer:2022-04-22
Keywords: catalysis; ionic liquids; on-surface metathesis; ultra-thin films; X-ray photoelectron spectroscopy

On the adsorption of different tetranaphthylporphyrins on Cu(111) and Ag(111) - Brox, Jan; Adhikari, Rajan; Shaker, Majid; Ruppel, Michael; Jux, Norbert; Marbach, Hubertus; Jaekel, Simon; Steinrück, Hans-Peter (Surface Science, 2022)
We address the adsorption of 2H-tetranaphthylporphyrin (2HTNP) and 2H-tetranaphthylbenzoporphyrin (2HTNBP) on Cu(111) and Ag(111). The difference between the two molecules is that for 2HTNBP the pyrrole groups are replaced by isoindole groups. We were interested in the resulting differences in the adsorption behavior on the two surfaces, in particular the role of the naphthyl groups. The investigations are performed with scanning tunneling microscopy at room temperature (RT) and after heating treatments (500 and 600 K). On Ag(111), 2HTNP forms a commensurable superstructure at RT, which transforms to a denser packed, non-commensurable structure upon annealing. For 2HTNBP, individual molecules are observed on Cu(111) at RT, which exhibit different mobility. In contrast, on Ag(111) the formation of ordered 2HTNBP islands occurs, which are stabilized by T-type interactions. After heating to 500 K, these islands undergo a structural change to a denser packed structure, which is stabilized by π-π stacking of neighboring naphthyl groups.
CRIS-Team Scopus Importer:2022-04-01
Keywords: Commensurability; Naphthyl functionalization; Porphyrins; Self-assembly; STM

On the adsorption of ethylene on Ni(110) - Weinelt, M.; Zebisch, P.; Huber, W.; Pabst, M.; Birkenheuer, U.; Reichert, B.; Rösch, Notker; Steinrück, Hans-Peter (Proc. Symposium on Surface Science 3S'92, 1992)

On the adsorption of n-butane on alkyl imidazolium ionic liquids with different anions using a new molecular beam setup - Winter, Leonhard; Bhuin, Radha Gobinda; Lexow, Matthias; Maier, Florian; Steinrück, Hans-Peter (Journal of Chemical Physics, 2020)
The adsorption of reactants is an elementary step in the interaction of molecules with liquid or solid surfaces. We recently reported on the trapping of n-butane on the frozen surfaces of ionic liquids (ILs), namely, 1-Alkyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ILs ([CnC1Im][Tf2N]; n = 1, 2, 3, and 8). To study the influence of the anion, we now present results concerning the trapping of n-butane on 1-Alkyl-3-methylimidazolium hexafluorophosphate ILs ([CnC1Im][PF6]; n = 2, 4, and 8), that is, ILs with a smaller anion. The adsorption energies close to zero coverage are determined from the temperature dependence of the initial trapping probability using a novel approach. For both groups of ILs, the binding energy is dominated by the interaction of n-butane with the alkyl chain of the cation, whereas the ionic headgroups contribute only weakly. Comparing ILs with different alkyl chains at the IL cation, we find that the adsorption strength of n-butane increases with increasing length of the alkyl chain. In addition, detailed information on the new setup and the data analysis is provided.
CRIS-Team Scopus Importer:2020-12-25

On the catalytic and degradative role of oxygen-containing groups on carbon electrode in non-aqueous ORR - Inozemtseva, Alina I.; Kataev, Elmar; Frolov, Alexander S.; Amati, Matteo; Gregoratti, Luca; Beranová, Klára; Dieste, Virginia Pérez; Escudero, Carlos; Fedorov, Alexander; Tarasov, Artem V.; Usachov, Dmitry Yu; Vyalikh, Denis V.; et al. (Carbon, 2021)
Oxygen reduction reaction (ORR) is a crucial process that drives the operation of several energy storage devices. ORR can proceed on the neat carbon surface in the absence of a catalyst, and its electrochemical activity is determined by its microstructure and chemical composition. Oxygen functional groups unavoidably existing on the carbon surface can serve as adsorption sites for ORR intermediates; the presence of some oxygen functionalities gives rise to an increase in the density of electronic states (DOS) at the Fermi level (FL). Both factors should have a positive impact on the electron transfer rate that was demonstrated for ORR in aqueous media. To study the O-groups effect on the aprotic ORR, which is now of interest due to the extensive development of aprotic metal-air batteries, we use model oxidized carbon electrodes (HOPG and single-layer graphene). We demonstrate that oxygen functionalities (epoxy, carbonyl, and lactone) do not affect the rate of one-electron oxygen reduction in aprotic media in the absence of metal cations since their introduction practically does not increase DOS at FL. However, in Li+-containing electrolytes, oxygen groups enhance both the rate of second electron transfer and carbon degradation due to its oxidation by LiO2 yielding carbonate species.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Graphene; Li–O2 batteries; Oxygen functionalities; Oxygen reduction

On the critical role of the substrate: the adsorption behaviour of tetrabenzoporphyrins on different metal surfaces - Zhang, Liang; Lepper, Michael; Stark, Michael Werner; Menzel, Teresa; Lungerich, Dominik; Jux, Norbert; Hieringer, Wolfgang; Steinrück, Hans-Peter; Marbach, Hubertus (Physical Chemistry Chemical Physics, 2017)
The adsorption behaviour of 2H-5,10,15,20-tetraphenyltetrabenzoporphyrin (2HTPTBP) on different metal surfaces, i.e., Ag(111), Cu(111), Cu(110), and Cu(110)-(2 x 1)O was investigated by scanning tunnelling microscopy at room temperature. The adsorption of 2HTPTBP on Ag(111) leads to the formation of a well-ordered two-dimensional (2D) island structure due to the mutual stabilization through the intermolecular pi-pi stacking and T-type-like interactions of phenyl and benzene substituents of neighboring molecules. For 2HTPTBP on Cu(111), the formed 2D supramolecular structures exhibit a coverage-dependent behaviour, which can be understood from the interplay of molecule-substrate and molecule-molecule interactions. In contrast, on Cu(110) the 2HTPTBP molecules form dispersed one-dimensional (1D) molecular chains along the [1 (1) over bar0] direction of the substrate due to relatively strong attractive molecule-substrate interactions. Furthermore, we demonstrate that the reconstruction of the Cu(110) surface by oxygen atoms yields a change in dimensionality of the resulting nanostructures from 1D on Cu(110) to 2D on (2 x 1) oxygen-reconstructed Cu(110), induced by a decreased molecule-substrate interaction combined with attractive molecule-molecule interactions. This comprehensive study on these prototypical systems enables us to deepen the understanding of the particular role of the substrate concerning the adsorption behavior of organic molecules on metal surfaces and thus to tweak the ordering in functional molecular architectures.

On the Dynamic Interaction of n-Butane with Imidazolium-Based Ionic Liquids - Bhuin, Radha Gobinda; Winter, Leonhard; Lexow, Matthias; Maier, Florian; Steinrück, Hans-Peter (Angewandte Chemie International Edition, 2020)
The impact of a reactant from the gas phase on the surface of a liquid and its transfer through this gas/liquid interface are crucial for various concepts applying ionic liquids (ILs) in catalysis. We investigated the first step of the adsorption dynamics of n-butane on a series of 1-alkyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ILs ([CnC1Im][Tf2N]; n=1, 2, 3, 8). Using a supersonic molecular beam in ultra-high vacuum, the trapping of n-butane on the frozen ILs was determined as a function of surface temperature, between 90 and 125 K. On the C8- and C3-ILs, n-butane adsorbs at 90 K with an initial trapping probability of ≈0.89. The adsorption energy increases with increasing length of the IL alkyl chain, whereas the ionic headgroups seem to interact only weakly with n-butane. The absence of adsorption on the C1- and C2-ILs is attributed to a too short residence time on the IL surface to form nuclei for condensation even at 90 K.
CRIS-Team Scopus Importer:2020-07-10
Keywords: gas-surface dynamics; ionic liquids; molecular beam; n-butane; trapping and adsorption

On the Electron-Induced Reactions of (CH3)AuP(CH3)(3): A Combined UHV Surface Science and Gas-Phase Study - Kamali, Ali; Bilgilisoy, Elif; Wolfram, Alexander; Gentner, Thomas; Ballmann, Gerd; Harder, Sjoerd; Marbach, Hubertus; Ingolfsson, Oddur (Nanomaterials, 2022)
Focused-electron-beam-induced deposition (FEBID) is a powerful nanopatterning technique where electrons trigger the local dissociation of precursor molecules, leaving a deposit of non-volatile dissociation products. The fabrication of high-purity gold deposits via FEBID has significant potential to expand the scope of this method. For this, gold precursors that are stable under ambient conditions but fragment selectively under electron exposure are essential. Here, we investigated the potential gold precursor (CH3)AuP(CH3)(3) using FEBID under ultra-high vacuum (UHV) and spectroscopic characterization of the corresponding metal-containing deposits. For a detailed insight into electron-induced fragmentation, the deposit's composition was compared with the fragmentation pathways of this compound through dissociative ionization (DI) under single-collision conditions using quantum chemical calculations to aid the interpretation of these data. Further comparison was made with a previous high-vacuum (HV) FEBID study of this precursor. The average loss of about 2 carbon and 0.8 phosphor per incident was found in DI, which agreed well with the carbon content of the UHV FEBID deposits. However, the UHV deposits were found to be as good as free of phosphor, indicating that the trimethyl phosphate is a good leaving group. Differently, the HV FEBID experiments showed significant phosphor content in the deposits.
CRIS-Team WoS Importer:2022-08-26

On the energetics of conformational switching of molecules at and close to room temperature - Ditze, Stefanie; Stark, Michael Werner; Buchner, Florian; Aichert, André; Jux, Norbert; Luckas, Nicola; Görling, Andreas; Hieringer, Wolfgang; Hornegger, Joachim; Steinrück, Hans-Peter; Marbach, Hubertus (Journal of the American Chemical Society, 2014)
We observe and induce conformational switching of individual molecules via scanning tunneling microscopy (STM) at and close to room temperature. 2H-5,10,15,20-Tetrakis-(3,5-di-tert-butyl)-phenylporphyrin adsorbed on Cu(111) forms a peculiar supramolecular ordered phase in which the molecules arrange in alternating rows, with two distinct appearances in STM which are assigned to concave and convex intramolecular conformations. Around room temperature, frequent bidirectional conformational switching of individual molecules from concave to convex and vice versa is observed. From the temperature dependence, detailed insights into the energy barriers and entropic contributions of the switching processes are deduced. At 200 K, controlled STM tip-induced unidirectional switching is possible, yielding an information storage density of 4.9 × 10 bit/inch. With this contribution we demonstrate that controlled switching of individual molecules at comparably high temperatures is possible and that entropic effects can be a decisive factor in potential molecular devices at these temperatures. © 2014 American Chemical Society.

On the formation of mixed ordered structures in the coadsorption system benzene + NO on Ni(111) - Zebisch, P.; Huber, W.; Steinrück, Hans-Peter (Surface Science, 1991)
The adsorption, desorption and ordering behavior of coadsorbed benzene + NO layers on Ni(111) have been studied by TPD and LEED. With increasing NO exposure dissociation of benzene upon heating is more and more suppressed and molecular benzene desorption is observed in a variety of peaks between 370 and 440 K which strongly depend on the initial benzene and NO coverages. Under certain conditions dissociation of benzene can be completely suppressed. The desorption behavior of NO is essentially unchanged as compared to NO desorption from the bare Ni(111) surface. Depending on initial benzene and NO coverage four ordered benzene + NO structures have been observed: (2 3×2 3)R30 °, (3 × 3), c(2 3×4)rect and (2 3×4 3) R30 °. In all cases the coadsorbed layers were disordered after adsorption at 120 K and ordering was only observed after annealing to 250 K. The observed structures can be correlated to different molecular benzene desorption peaks. The formation of the various ordered benzene + NO structures and their correlation to the TPD spectra is discussed. © 1991.

On the interaction of Mg with the (111) and (110) surfaces of ceria - Nolan, Michael; Lykhach, Yaroslava; Tsud, Nataliya; Skala, Tomas; Staudt, Thorsten; Prince, Kevin C.; Matolin, Vladimir; Libuda, Jörg (Physical Chemistry Chemical Physics, 2012)
The catalytic activity of cerium dioxide can be modified by deposition of alkaline earth oxide layers or nanoparticles or by substitutional doping of metal cations at the Ce site in ceria. In order to understand the effect of Mg oxide deposition and doping, a combination of experiment and first principles simulations is a powerful tool. In this paper, we examine the interaction of Mg with the ceria (111) surface using both angle resolved X-ray (ARXPS) and resonant (RPES) photoelectron spectroscopy measurements and density functional theory (DFT) corrected for on-site Coulomb interactions (DFT + U). With DFT + U, we also examine the interaction of Mg with the ceria (110) surface. The experiments show that upon deposition of Mg, Ce ions are reduced to Ce3+, while Mg is oxidised. When Mg is incorporated into ceria, no reduced Ce3+ ions are found and oxygen vacancies are present. The DFT + U simulations show that each Mg that is introduced leads to formation of two reduced Ce3+ ions. When Mg is incorporated at a Ce site in the (111) surface, one oxygen vacancy is formed for each Mg to compensate the different valencies, so that all Ce ions are oxidised. The behaviour of Mg upon interaction with the (110) surface is the same as with the (111) surface. The combined results provide a basis for deeper insights into the catalytic behaviour of ceria-based mixed oxide catalysts.

On the magnetic properties of iron nanostructures fabricated via focused electron beam induced deposition and autocatalytic growth processes - TU, Fan; Drost, Martin; Vollnhals, Florian; Späth, Andreas; Carrasco, Esther; Fink, Rainer; Marbach, Hubertus (Nanotechnology, 2016)
We employ Electron beam induced deposition (EBID) in combination with autocatalytic growth (AG) processes to fabricate magnetic nanostructures with controllable shapes and thicknesses. Following this route, different Fe deposits were prepared on silicon nitride membranes under ultra-high vacuum conditions and studied by scanning electron microscopy (SEM) and scanning transmission x-ray microspectroscopy (STXM). The originally deposited Fe nanostructures are composed of pure iron, especially when fabricated via autocatalytic growth processes. Quantitative near-edge x-ray absorption fine structure (NEXAFS) spectroscopy was employed to derive information on the thickness dependent composition. X-ray magnetic circular dichroism (XMCD) in STXM was used to derive the magnetic properties of the EBID prepared structures. STXM and XMCD analysis evinces the existence of a thin iron oxide layer at the deposit-vacuum interface, which is formed during exposure to ambient conditions. We were able to extract magnetic hysteresis loops for individual deposits from XMCD micrographs with varying external magnetic field. Within the investigated thickness range (2-16 nm), the magnetic coercivity, as evaluated from the width of the hysteresis loops, increases with deposit thickness and reaches a maximum value of ∼160 Oe at around 10 nm. In summary, we present a viable technique to fabricate ferromagnetic nanostructures in a controllable way and gain detailed insight into their chemical and magnetic properties.
EAM Import::2019-03-08

On the platinum-oxide formation under gas-phase and electrochemical conditions - Farkas, Attila; Fantauzzi, Donato; Mueller, Jonathan E.; Zhu, Tianwei; Papp, Christian; Steinrück, Hans-Peter; Jacob, Timo (Journal of Electron Spectroscopy and Related Phenomena, 2017)
We summarize our recent results on the oxidation of platinum surfaces, stressing the close connection between theory and experiment. The present theoretical approach is based on ab-initio quantum mechanics methods, such as density functional theory (DFT), ab-initio atomistic thermodynamics, Monte-Carlo methods and reactive molecular dynamics (RMD). Experimentally, photoelectron spectroscopy (XPS) under UHV and in-situ conditions (NAP-XPS) provides most of the discussed results. The oxidation of an extended variety of platinum surfaces is reviewed, starting from atomically flat Pt(111) over stepped surfaces to regularly shaped nanoparticles, under conditions ranging from UHV through ambient pressures up to electrochemical interfaces.
EAM Import::2019-03-08

On the Principles of Tweaking Nanostructure Fabrication via Focused Electron Beam Induced Processing Combined with Catalytic Growth Processes - Drost, Martin; TU, Fan; Vollnhals, Florian; Szenti, Imre; Kiss, Janos; Marbach, Hubertus (Small Methods, 2017)
Novel pathways to use a focused electron beam in ultrahigh vacuum in combination with catalytic growth protocols are explored for the fabrication of well-defined nanostructures. Thereby, the basic process is the local deposition of material from different precursor molecules (Co(CO)3 NO, Fe(CO)5). This can be realized with a focused electron beam by direct deposition of the precursor or by a chemical modification of the substrate, such that it becomes activated toward the decomposition of the precursor. For both methods, autocatalytic growth (AG) processes can occur, yielding the deposition of additional material. Interestingly, significantly different chemical selectivities for the two precursors are found, which can drastically change upon subtle changes of the surface. It is demonstrated that AG can be tweaked by the choice of the substrate/precursor combination. One possibility to quench catalytic activity of a substrate is the preparation of a thin layer of organic molecules, here porphyrins, which enables the fabrication of hybrid metal–organic nanostructures with line widths below 20 nm. Based on these findings, corresponding techniques are developed which exploit (auto)catalytic effects for the controlled fabrication of nanostructures. These results indicate that every substrate is applicable to electron beam induced surface activation by preparation of a thin porphyrin layer.
EAM Import::2019-03-08

On the thermal stability of metal particles supported on a thin alumina film - Libuda, Jörg; et al. (Surface Science, 2003)
The structure of metal (Co, Rh, Pd) particles deposited on a thin alumina film grown on a NiAl(110) substrate were studied as a function of annealing temperature. The results reveal at least three processes to occur upon heating: (a) re-arrangement of metal atoms on the particle surface, (b) sintering of the particles, and (c) metal migration into the substrate. The latter process is probably mediated by the defect structure of the oxide film and dominates at higher temperatures. The thermal stability is found to be better for Co, which strongly interacts with the alumina support, as compared to Pd and Rh. Hydroxylation of the alumina film increases Pd and Rh dispersion and shifts processes (b) and (c) to higher temperatures, likely due to a stronger interaction of the metals with the hydroxylated film. © 2002 Elsevier Science B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2003.nat.dchph.ppc20.onthet
Keywords: Aluminum oxide; Carbon monoxide; Cobalt; Palladium; Rhodium

Operando DRIFTS and DFT Study of Propane Dehydrogenation over Solid- and Liquid-Supported GaxPty Catalysts - Bauer, Tanja; Maisel, Sven; Blaumeiser, Dominik; Vecchietti, Julia; Taccardi, Nicola; Wasserscheid, Peter; Bonivardi, Adrian; Görling, Andreas; Libuda, Jörg (ACS Catalysis, 2019)
Supported catalytically active liquid metal solutions (SCALMS) represent a class of catalytic materials that have only recently been developed, but have already proven to be highly active, e.g., for dehydrogenation reactions. Previous studies attributed the catalytic activity to isolated noble metal atoms at the surface of a liquid and inert Ga matrix. In this study, we apply diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) with CO as a probe molecule to Ga/Al2O3, Pt/Al2O3, and Ga37Pt/Al2O3 catalysts, to investigate in detail the nature of the active Pt species. Comparison of CO adsorption on Pt/Al2O3 and Ga37Pt/Al2O3 shows that isolated Pt atoms are, indeed, present at the surface of the liquid SCALMS. Combining DRIFTS with online gas chromatography (GC), we investigated the Ga/Al2O3, Pt/Al2O3, and Ga37Pt/Al2O3 systems under operando conditions during propane dehydrogenation in CO/propane and in Ar/propane. We find that the Pt/Al2O3 sample is rapidly poisoned by CO adsorption and coke, whereas propane dehydrogenation over Ga37Pt/Al2O3 SCALMS leads to higher conversion with no indication of poisoning effects. We show under operando conditions that isolated Pt atoms are present at the surface of SCALMS during the dehydrogenation reaction. IR spectra and density-functional theory (DFT) suggest that both the Ga matrix and the presence of coadsorbates alter the electronic properties of the surface Pt species.
CRIS-Team WoS Importer:2019-04-23

Operando Identification of the Reversible Skin Layer on Co3O4as a Three-Dimensional Reaction Zone for Oxygen Evolution - Wiegmann, Tim; Pacheco, Ivan; Reikowski, Finn; Stettner, Jochim; Qiu, Canrong; Bouvier, Mathilde; Bertram, Manon; Faisal, Firas; Brummel, Olaf; Libuda, Jörg; Drnec, Jakub; Allongue, Philippe; et al. (ACS Catalysis, 2022)
Co oxides and oxyhydroxides have been studied extensively in the past as promising electrocatalysts for the oxygen evolution reaction (OER) in neutral to alkaline media. Earlier studies showed the formation of an ultrathin CoOx(OH)y skin layer on Co3O4 at potentials above 1.15 V vs reversible hydrogen electrode (RHE), but the precise influence of this skin layer on the OER reactivity is still under debate. We present here a systematic study of epitaxial spinel-type Co3O4 films with defined (111) orientation, prepared on different substrates by electrodeposition or physical vapor deposition. The OER overpotential of these samples may vary up to 120 mV, corresponding to two orders of magnitude differences in current density, which cannot be accounted for by differences in the electrochemically active surface area. We demonstrate by a careful analysis of operando surface X-ray diffraction measurements that these differences are clearly correlated with the average thickness of the skin layer. The OER reactivity increases with the amount of formed skin layer, indicating that the entire three-dimensional skin layer is an OER-active interphase. Furthermore, a scaling relationship between the reaction centers in the skin layer and the OER activity is established. It suggests that two lattice sites are involved in the OER mechanism.
CRIS-Team Scopus Importer:2022-03-18
Keywords: Co oxide; electrocatalysis; model catalysts; oxygen evolution reaction; structure-activity relationship; surface restructuring; surface X-ray diffraction

Optimization of the Thermoelectric Properties of p-Type Mg2- yLi yGe1- xSn xand Mg2- yLi yGe1- zSi zwith x, z = 0.1 and 0.2 - Galwadu Arachchige, Vidushi; Kamila, Hasbuna; Sankhla, Aryan; Millerand, Léo; Tumminello, Silvana; Mitra, Kunal; Yasseri, Mohammad; Müller, Eckhard; De Boor, Johannes (ACS Applied Energy Materials, 2021)
According to recent investigations on p-type Mg2X (X = Si, Sn, Ge), p-type Mg2Ge is found to be far superior to the p-type binaries while having thermoelectric properties comparable to the best solid solutions of p-type Mg2(Si,Sn). The unexpectedly good properties are supposedly due to a nonrigid band structure with a temperature-dependent interband separation. Further optimization can be expected by alloying Si or Sn into the Ge site to lower the thermal conductivity, thereby increasing the figure of merit. Here, solid solutions of p-type Mg2Ge1-xSnx and p-type Mg2Ge1-zSiz with x, z = 0.1 and 0.2 are successfully synthesized via ball milling. The thermal conductivities are significantly reduced throughout the whole temperature range by around 30% due to the alloying effect. The electronic properties of all Ge-rich samples show similar temperature-dependent behavior to p-type Mg2Ge. For the Mg2(Ge,Sn) systems, a compensation of reduced thermal conductivity and decreased carrier mobility are found, leading to zT values comparable to p-type Mg2Ge. Whereas for the Si containing samples, a thermoelectric figure of merit zT of 0.49 ± 0.07 at 675 K for z = 0.1 is achieved, the highest reported so far for the p-type Mg2(Ge,Si) systems and a zTavg that is 30% higher than that of binary Mg2Ge.
CRIS-Team Scopus Importer:2021-07-02
Keywords: ball milling; microstructure; p-type Mg; p-type Mg; synthesis; thermoelectric properties

Ordering and phase transitions in ionic liquid-crystalline films - Sobota, Marek; Wang, Xinjiao; Fekete, Melinda; Happel, Markus; Meyer, Karsten; Wasserscheid, Peter; Laurin, Mathias; Libuda, Jörg (ChemPhysChem, 2010)
Watching phase transitions: Ordering processes and phase transitions in thin films of the liquid-crystalline ionic liquid 1,3-didodecylimidazolium tetrafluoroborate [CCIM][BF] on Pt(111) (see picture) are studied by means of temperature-dependent IR reflection absorption spectroscopy. The method allows in situ monitoring of the structural properties of liquid-crystalline supported ionic liquid phase (SILP) catalysts under reaction conditions. © 2010 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.

Ordering aspects and intramolecular conformation of tetraphenylporphyrins on Ag(111) - Buchner, Florian; Kellner, Ina; Hieringer, Wolfgang; Görling, Andreas; Steinrück, Hans-Peter; Marbach, Hubertus (Physical Chemistry Chemical Physics, 2010)
A systematic scanning tunnelling microscopy study of the self-assembly, intramolecular conformation and supramolecular ordering of different tetraphenylporphyrins (xTPP) with or without a central metal atom (x = 2H, Fe, Co) on Ag(111) at room temperature is presented. The investigation covers a wide range, i.e. the adsorption behaviour from the low sub-monolayer up to the multilayer regime is described in detail and conclusively discussed in regard to molecule-molecule and molecule-substrate interactions. At monolayer coverage the molecules self-assemble in domains with a square unit cell caused by "T-type" intermolecular interactions, while the orientation of the domains along the symmetry axes is determined by adsorbate-substrate interactions. Interestingly for ordered monolayers domain boundaries always separate domains of different organizational chirality but same orientation of the square unit cell. This demonstrates that in the particular system chirality obviously restricts the long range order of the supramolecular TPP assemblies. In combination with DFT calculations it is also demonstrated that the previously reported intramolecular saddle shape deformation of TPPs upon adsorption is more pronounced for metallo-TPP than for 2HTPP. © 2010 the Owner Societies.

Organic linkers on oxide surfaces: Adsorption and chemical bonding of phthalic anhydride on MgO(100) - Mohr, Susanne; Döpper, Tibor; Xu, Tao; Tariq, Quratulain; Lytken, Ole; Laurin, Mathias; Steinrück, Hans-Peter; Görling, Andreas; Libuda, Jörg (Surface Science, 2016)
To elucidate the adsorption behavior and interaction mechanisms of organic linker units on oxide surfaces, we have performed a model study under ultrahigh vacuum (UHV) conditions. We apply infrared reflection absorption spectroscopy (IRAS) in combination with density-functional theory (DFT), temperature programmed desorption (TPD), and X-ray photoelectron spectroscopy (XPS). Phthalic anhydride (PM) was deposited at temperatures between 100 and 300 K by physical vapor deposition (PVD) onto an ordered MgO(100) film grown on Ag(100). At 100 K, the first monolayer adsorbs molecularly with the molecular plane aligned parallel to the surface. Subsequent growth of a multilayer film at low temperature also occurs with preferential molecular alignment parallel to the surface. At 240 K, the multilayer desorbs without decomposition. At 300 K, a mixed monolayer of chemically modified ring-opened and intact phthalic anhydride exists on the surface. The chemically modified species binds in a strongly tilted geometry via opening of the anhydride ring to form a bis-carboxylate species. This species additionally stabilizes the coadsorbed molecular PM via intermolecular interactions. Finally, surface defects and hydroxyl groups are found to increase the amount of surface bis-carboxylate at 300 K, whereas the relative amount of coadsorbed molecular PAA decreases. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Phthalic anhydride; Magnesium oxide; Organic thin films; Infrared reflection absorption spectroscopy; Density-functional theory

Organic reactions in ionic liquids studied by in situ XPS - Niedermaier, Inga; Kolbeck, Claudia; Taccardi, Nicola; Schulz, Peter; Li, Jing; Drewello, Thomas; Wasserscheid, Peter; Steinrück, Hans-Peter; Maier, Florian (ChemPhysChem, 2012)
We demonstrate the application of in situ X-ray photoelectron spectroscopy (XPS) to monitor organic, liquid-phase reactions. By covalently attaching ionic head groups to the reacting organic molecules, their volatility can be reduced such that they withstand ultra high vacuum conditions. The applied method, which is new for the investigation of organic reactions, allows for following the fate of all elements present in the reaction mixtureexcept for hydrogenin a quantitative and oxidation-state-sensitive manner in one experiment. This concept is demonstrated for the alkylation of a tertiary amine attached to an imidazolium or phosphonium moiety by the anion 4-chlorobutylsulfonate ([ClC H SO ] ). In the course of the reaction, the covalently bound chlorine is converted to chloride and the amine to ammonium as reflected by the distinct shifts in the N 1s and Cl 2p binding energies. © 2012 Wiley-VCH Verlag GmbH& Co. KGaA, Weinheim.

Origin of surface conductivity in diamond - Ristein, Jürgen; Maier, Florian; Ley, Lothar; et al. (Physical Review Letters, 2000)
Experimental evidence is presented which supports an electrochemical model for the pronounced surface conductivity of hydrogen-terminated diamond. In this model hydrogenation rises the valence band maximum (VBM) of diamond sufficiently with respect to the vacuum level to place it just above the chemical potential of electrons in the liquid phase (μe) of a mildly acidic water layer physisorbed at the surface. Electron transfer from diamond to the H3O+/(H2O + H2) redox couple accounts for the hole accumulation layer. In equilibrium, the diamond surface Fermi level position is pinned at μe which coincides essentially with the VBM. Small variations in that Fermi level position with respect to VBM and thus variations in conductivity with the pH value of the wetting layer and the H2 partial pressure are quantitatively accounted for via Nernst's equation.
UnivIS-Import:2015-03-09:Pub.2000.nat.dphy.IAP.exphys.theori

Overcoming efficiency and stability limits in water-processing nanoparticular organic photovoltaics by minimizing microstructure defects - Xie, Chen; Heumüller, Thomas; Gruber, Wolfgang; Tang, Xiaofeng; Classen, Andrej; Schuldes, Isabel; Bidwell, Matthew; Späth, Andreas; Fink, Rainer; Unruh, Tobias; Mcculloch, Iain; Li, Ning; et al. (Nature Communications, 2018)
There is a strong market driven need for processing organic photovoltaics from eco-friendly solvents. Water-dispersed organic semiconducting nanoparticles (NPs) satisfy these premises convincingly. However, the necessity of surfactants, which are inevitable for stabilizing NPs, is a major obstacle towards realizing competitive power conversion efficiencies for water-processed devices. Here, we report on a concept for minimizing the adverse impact of surfactants on solar cell performance. A poloxamer facilitates the purification of organic semiconducting NPs through stripping excess surfactants from aqueous dispersion. The use of surfactant-stripped NPs based on poly(3-hexylthiophene) / non-fullerene acceptor leads to a device efficiency and stability comparable to the one from devices processed by halogenated solvents. A record efficiency of 7.5% is achieved for NP devices based on a low-band gap polymer system. This elegant approach opens an avenue that future organic photovoltaics processing may be indeed based on non-toxic water-based nanoparticle inks.
Keywords: microstructure-recombination correlation; organic photovoltaics; polymer-fullerene nanoparticles; water processed

Overcoming Interfacial Losses in Solution-Processed Organic Multi-Junction Solar Cells - Du, Xiaoyan; Lytken, Ole; Killian, Manuela; Cao, Jiamin; Stubhan, Tobias; Turbiez, Mathieu; Schmuki, Patrik; Steinrück, Hans-Peter; Ding, Liming; Fink, Rainer; Li, Ning; Brabec, Christoph (Advanced Energy Materials, 2016)
Organic solar cells are promising in terms of full-solution-processing which enables low-cost and large-scale fabrication. While single-junction solar cells have seen a boost in power conversion efficiency (PCE), multi-junction solar cells are promising to further enhance the PCE. In all-solution-processed multi-junction solar cells, interfacial losses are often encountered between hole-transporting layer (HTL) and the active layers and therefore greatly limit the application of newly developed high-performance donor and acceptor materials in multi-junction solar cells. Here, the authors report on a systematic study of interface losses in both single-junction and multi-junction solar cells based on representative polymer donors and HTLs using electron spectroscopy and time-of-flight secondary ion mass spectrometry. It is found that a facile mixed HTL containing poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) and MoO nanoparticles successfully overcomes the interfacial losses in both single- and multi-junction solar cells based on various active layers by reducing interface protonation, promoting better energy-level alignment, and forming a dense and smooth layer. Solution-processed single-junction solar cells are demonstrated to reach the same performance as with evaporated MoO (over 7%). Multi-junction solar cells with polymers containing nitrogen atoms as the first layer and the mixed PEDOT:PSS and MoO nanoparticles as hole extraction layer reach fill factor (FF) of over 60%, and PCE of over 8%, while the identical stack with pristine PEDOT:PSS or MoO nanoparticles show FF smaller than 50% and PCE less than 5%.
Keywords: Interfacial losses; Organic multi-junction solar cells; Organic photovoltaics; Recombination layer; Solution-processing

Overcoming Microstructural Limitations in Water Processed Organic Solar Cells by Engineering Customized Nanoparticulate Inks - Xie, Chen; Classen, Andrej; Späth, Andreas; Tang, Xiaofeng; Min, Jie; Meyer, Markus; Zhang, Chaohong; Li, Ning; Osvet, Andres; Fink, Rainer; Brabec, Christoph (Advanced Energy Materials, 2018)
The application of conjugated polymer and fullerene water-based nanoparticles (NP) as ecofriendly inks for organic photovoltaics (OPVs) is reported. A low bandgap polymer diketopyrrolopyrrole–quinquethiophene (PDPP5T-2) and the methanofullerene PC71BM are processed into three types of nanoparticles: pristine fullerene NPs, pristine polymer NPs, and mixed polymer:fullerene NPs, allowing the formation of bulk heterojunction (BHJ) composites with different domain sizes. Mild thermal annealing is required to melt the nanospheres and enable the formation of interconnected pathways within mixed phases. This BHJ is accompanied by a shrinkage of film, whereas the more compact layers show enhanced mobility. Consistently reduced recombination and better performance are found for mixed NP, containing both, the polymer and the fullerene within a single NP. The optimized solar cell processed by ultrasmall NPs delivers a power conversion efficiency of about 3.4%. This is among the highest values reported for aqueous processed OPVs but still lacks performance compared to those being processed from halogenated solvents. Incomplete crystallization is identified as the main root for reduced efficiency. It is nevertheless believed that postprocessing does not cut attraction from printing aqueous organic NP inks as a trendsetting strategy for the reliable and ecofriendly production of organic solar cells.
Keywords: Microstructure-recombination correlation; Organic photovoltaics; Polymer-fullerene nanoparticles; Water processed

Oxidation-driven self-assembly gives access to high-nuclearity molecular copper vanadium oxide clusters - Forster, Johannes; Rösner, Benedikt; Fink, Rainer; Nye, Leanne; Ivanovic-Burmazovic, Ivana; Kastner, Katharina; Tucher, Johannes; Streb, Carsten (Chemical Science, 2013)
We report a general fragmentation-and-re-assembly route which gives access to high-nuclearity, mixed-metal polyoxometalate clusters. Reduced vanadium(iv) precursors are oxidatively dis-assembled into reactive fragments which subsequently re-aggregate under template control in a one-pot reaction. It is shown that the oxidative dis-assembly is required, as the use of vanadium(v)-based precursors results in the formation of smaller clusters. The principle is exemplified by the synthesis of a ca. 1.8 × 1.7 × 1.0 nm, 36-nuclear copper vanadium oxide cluster, (nBu N)[CuVO(NO )(CHCN)]. The cluster is characterized in the solid-state and in solution by single-crystal XRD, ESI-MS and other spectroscopic and electrochemical measurements. Several lines of evidence show that the compound is indeed formed exclusively by fully oxidized vanadium(v) centres. In addition, primary fragmentation products of the type [VO(dmso)] were isolated. The cuprovanadate cluster features pentagonal secondary building units of the type (V)M (M = Cu, V) which show similar structural function as the well-known (Mo)Mo pentagons observed in giant molybdate clusters. The observation suggests that more complex vanadate clusters might be accessible based on these pentagonal units. © 2013 The Royal Society of Chemistry.

Oxidation induced restructuring of Rh-Ga SCALMS model catalyst systems - Wittkämper, Haiko; Maisel, Sven; Wu, Mingjian; Frisch, Johannes; Wilks, Regan G.; Grabau, Mathias; Spiecker, Erdmann; Bär, Marcus; Görling, Andreas; Steinrück, Hans-Peter; Papp, Christian (Journal of Chemical Physics, 2020)
Supported catalytically active liquid metal solutions have been receiving increasing attention recently. We investigated the oxidation behavior of macroscopic Rh-Ga alloy droplets and Rh-Ga model catalyst nanoparticles supported on SiO2/Si(100) with low Rh content (<2.5 at. %) by x-ray photoelectron spectroscopy in ultra-high vacuum and under near-ambient pressure conditions using different photon energies and also using transmission electron microscopy. The experiments are accompanied by computational studies on the Ga oxide/Rh-Ga interface and Rh-Ga intermetallic compounds. For both Rh-Ga alloy droplets and Rh-Ga model catalyst nanoparticles, exposure to molecular oxygen leads to the formation of an oxide shell in which Rh is enriched. Transmission electron microscopy on the Rh-Ga nanoparticles confirms the formation of an ∼4 nm thick gallium oxide film containing Rh. Based on ab initio molecular dynamics and computational studies on the Ga2O3/Ga interface, it is concluded that Rh incorporation into the Ga2O3 film occurs by substituting octahedrally coordinated Ga.
CRIS-Team Scopus Importer:2020-09-25

Oxidation of stepped Pt(111) studied by x-ray photoelectron spectroscopy and density functional theory - Bandlow, Jochen; Kaghazchi, Payam; Jacob, Timo; Papp, Christian; Tränkenschuh, Barbara; Streber, Regine; Lorenz, Michael Peter Andreas; Fuhrmann, Thomas; Denecke, R.; Steinrück, Hans-Peter (Physical Review B, 2011)
In this comparative density functional theory and x-ray photoelectron spectroscopy study on the interaction of oxygen with stepped Pt(111) surfaces, we show that both the initial adsorption and oxidation occur at the steps rather than terraces. An equivalent behavior was observed for the oxide formation at higher chemical potentials, where, after the formation of a one-dimensional PtO-type oxide at the steps, similar oxide chains form on the (111) terraces, indicating the initial stages of bulk oxide formation. © 2011 American Physical Society.

Oxide-based nanomaterials for fuel cell catalysis: the interplay between supported single Pt atoms and particles - Lykhach, Yaroslava; Bruix, Albert; Fabris, Stefano; Potin, Valerie; Matolinova, Iva; Matolin, Vladimir; Libuda, Jörg; Neyman, Konstantin M. (Catalysis: Science and Technology, 2017)
The concept of single atom catalysis offers maximum noble metal efficiency for the development of low-cost catalytic materials. Among possible applications are catalytic materials for proton exchange membrane fuel cells. In the present review, recent efforts towards the fabrication of single atom catalysts on nanostructured ceria and their reactivity are discussed in the prospect of their employment as anode catalysts. The remarkable performance and the durability of the ceria-based anode catalysts with ultra-low Pt loading result from the interplay between two states associated with supported atomically dispersed Pt and sub-nanometer Pt particles. The occurrence of these two states is a consequence of strong interactions between Pt and nanostructured ceria that yield atomically dispersed species under oxidizing conditions and sub-nanometer Pt particles under reducing conditions. The square-planar arrangement of four O atoms on 100 nanoterraces has been identified as the key structural element on the surface of the nanostructured ceria where Pt is anchored in the form of Pt2+ species. The conversion of Pt2+ species to sub-nanometer Pt particles is triggered by a redox process involving Ce3+ centers. The latter emerge due to either oxygen vacancies or adsorption of reducing agents. The unique properties of the sub-nanometer Pt particles arise from metal-support interactions involving charge transfer, structural flexibility, and spillover phenomena. The abundance of specific adsorption sites similar to those on 100 nanoterraces determines the ideal (maximum) Pt loading in Pt-CeOx films that still allows reversible switching between the atomically dispersed Pt and sub-nanometer particles yielding high activity and durability during fuel cell operation.

Oxygen Functionalization of Hexagonal Boron Nitride on Ni(111) - Späth, Florian; Soni, Himadriben; Steinhauer, Johann; Düll, Fabian; Bauer, Udo; Bachmann, Phillip; Hieringer, Wolfgang; Görling, Andreas; Steinrück, Hans-Peter; Papp, Christian (Chemistry - A European Journal, 2019)
The interaction of single-layer hexagonal boron nitride (h-BN) on Ni(111) with molecular oxygen from a supersonic molecular beam led to a covalently bonded molecular oxygen species, which was identified as being between a superoxide and a peroxide. This is a rare example of an activated adsorption process leading to a molecular adsorbate. The amount of oxygen functionalization depended on the kinetic energy of the molecular beam. For a kinetic energy of 0.7 eV, an oxygen coverage of 0.4 ML was found. Near-edge X-ray adsorption fine structure (NEXAFS) spectroscopy revealed a stronger bond of h-BN to the Ni(111) substrate in the presence of the covalently bound oxygen species. Oxygen adsorption also led to a shift of the valence bands to lower binding energies. Subsequent temperature-programmed X-ray photoelectron spectroscopy revealed that the oxygen boron bonds are stable up to approximately 580 K, when desorption, and simultaneously, etching of h-BN set in. The experimental results were substantiated by density functional theory calculations, which provided insight to the adsorption geometry, the adsorption energy and the reaction pathway.
CRIS-Team Scopus Importer:2019-06-21
Keywords: adsorption; boron nitride; density functional theory; oxygen functionalization; photoelectron spectroscopy

Oxygen-induced restructuring of a Pd/Fe3O4 model catalyst - Libuda, Jörg; et al. (Catalysis Letters, 2006)
We have studied the influence of oxygen on the structure and morphology of a Pd/Fe3O4 model catalyst using molecular beam (MB) methods, IR reflection absorption spectroscopy (IRAS) and scanning tunneling microcopy (STM). The model catalyst was prepared under ultrahigh vacuum (UHV) conditions by physical vapor deposition (PVD) and growth of Pd nanoparticles on an ordered Fe3O4 thin film on Pt(111). It is found that surface oxides are formed on the Pd nanoparticles even under mild oxidation conditions (temperatures of 500 K and effective oxygen partial pressures of around 10-6mbar). These surface oxides are initially generated at the Pd/Fe3O4 interface and, subsequently, are formed at the Pd/gas interface. The process of formation and reduction of surface and interface oxides on the Pd particles is fully reversible in that all oxides formed can be fully reduced. As a result, the oxide phase acts like a storage medium for oxygen during oxidation reactions, as probed via CO oxidation. The process of surface and interface oxidation is directly connected with the onset of a non-reversible sintering process of the Pd particles. It is suggested that this sintering process occurs via a mobile Pd oxide species, which is stabilized by interaction with the Fe3O4 support. The restructuring is monitored via STM and IRAS using CO as a probe molecule. In addition to a decrease in particle density and Pd surface area, a reshaping of the particles occurs, which is characterized by the formation of well-ordered crystallites and with a relatively large fraction of (100) facets. After a few oxidation/reduction cycles at 500K, the sintering process becomes very slow and the system shows a stable behavior under conditions of CO oxidation. © 2006 Springer Science+Business Media, Inc.
UnivIS-Import:2015-03-09:Pub.2006.nat.dchph.ppc20.oxygen
Keywords: CO; IR reflection absorption spectroscopy; Iron-oxide; Model catalysts; Molecular beams; Morphology; Oxidation; Palladium; STM

Oxygen-rich tetrahedral surface phase on high-temperature rutile VO2(110)(T) single crystals - Wagner, Margareta; Planer, Jakub; Heller, Bettina; Langer, Jens; Limbeck, Andreas; Boatner, Lynn A.; Steinrück, Hans-Peter; Redinger, Josef; Maier, Florian; Mittendorfer, Florian; Schmid, Michael; Diebold, Ulrike (Physical Review Materials, 2021)
Vanadium dioxide undergoes a metal-insulator transition from an insulating (monoclinic) to a metallic (tetragonal) phase close to room temperature, which makes it a promising functional material for many applications, e.g., as chemical sensors. Not much is known about its surface and interface properties, although these are critical in many applications. In this paper, we present an atomic-scale investigation of the tetragonal rutile VO2(110)(T) single-crystal surface and report results obtained with scanning tunneling microscopy, low-energy electron diffraction, and x-ray photoelectron spectroscopy, supported by density-functional-theory-based calculations. The surface reconstructs into an oxygen-rich (2 x 2) superstructure that coexists with small patches of the underlying unreconstructed (110)-(1 x 1) surface when the crystal is annealed >600 degrees C. The best structural model for the (2 x 2) surface termination, conceptually derived from a vanadium pentoxide (001) monolayer, consists of rings of corner-shared tetrahedra. Over a wide range of oxygen chemical potentials, this reconstruction is more stable than the unreconstructed (110) surface and models proposed in the literature.
CRIS-Team WoS Importer:2021-12-17

Oxygen Storage at the Metal/Oxide Interface of Catalyst Nanoparticles - Libuda, Jörg; et al. (Angewandte Chemie International Edition, 2005)
(Figure Presented) Holding its breath: Small Pd particles on an Fe 3O4 support reversibly store large quantities of oxygen in the form of a thin Pd oxide layer at the particle/support interface. Oxygen from this reservoir can be released during oxidation reactions, as shown by a combination of molecular beam methods, scanning tunneling microscopy, and photoelectron spectroscopy. © 2005 Wiley-VCH Verlag GmbH & Co. KGaA.
UnivIS-Import:2015-03-09:Pub.2005.nat.dchph.ppc20.oxygen
Keywords: Heterogeneous catalysis; Model catalysis; Nanoparticles; Reaction kinetics; Surface chemistry

Palladium-Mediated Ethylation of the Imidazolium Cation Monitored In Operando on a Solid Catalyst with Ionic Liquid Layer - Bauer, Tanja; Hager, Veit; Williams, Marc; Laurin, Mathias; Döpper, Tibor; Görling, Andreas; Szesni, Normen; Wasserscheid, Peter; Haumann, Marco; Libuda, Jörg (ChemCatChem, 2017)
The ionic liquid 1-ethyl-3-methylimidazolium ethylsulfate [EMIM][EtOSO] was supported on Pd-AlO to yield a solid catalyst with ionic liquid layer (SCILL) material. During the hydrogenation of ethene, it was found that ethene was incorporated into the imidazolium moiety in a reaction catalyzed by the palladium surface. The formation of 1,2-diethyl-3-methylimidazolium ethylsulfate was confirmed ex situ by means of NMR spectroscopy. Moreover, the reaction itself could be monitored in situ by diffuse reflection infrared Fourier transformation (DRIFT) spectroscopy. A reaction mechanism involving surface carbene species was proposed on the basis of the analytical data.
Keywords: carbenes; heterogeneous catalysis; ionic liquids; palladium; reaction mechanisms

Particle-Size-Dependent Interaction of NO2 with Pd Nanoparticles Supported on Model NOx Storage Materials - Desikusumastuti, Aine; Happel, Markus; Qin, Zhihui; Staudt, Thorsten; Lykhach, Yaroslava; Laurin, Mathias; Shaikhutdinov, S.; Rohr, F.; Libuda, Jörg (Journal of Physical Chemistry C, 2009)
Combining scanning tunneling microscopy, molecular beam methods, and time-resolved infrared reflection absorption spectroscopy, we investigate the structure and reactivity of Pd nanoparticles supported on single-crystal-based model NOx storage materials. The latter consist of barium aluminate-like nanoparticles supported on an Al2O3 film on a NiAl(110) substrate. On these surfaces, Pd deposition under ultra-high-vacuum conditions gives rise to the growth of three-dimensional Pd particles, nucleating at the predeposited barium aluminate aggregates. The reactivity of these systems toward NO2 is tested systematically as a function of NO2 exposure and Pd particle size. At room temperature, NOx generated by dissociative adsorption of NO2, sequentially covers the following sites on the Pd nanoparticles: (i) hollow sites on (111) facets, (ii) bridge sites at particles edges and particle defects, and, finally, (iii) on-top sites at particle corners. The occupation of different sites on the particles is monitored as a function of NO2 exposure and Pd particle size. Characteristic differences in the site occupation and the coverage dependence are observed as a function of particle size. At elevated NO2 exposures, all NO-related features disappear, indicating the onset of oxidation of the Pd particles. For the Pd-containing systems, several new vibrational bands are observed. These new features are assigned to surface nitrates adsorbed on oxidized Pd particles and, tentatively, to surface nitrates adsorbed on sites that arise from the interaction between barium aluminate and oxidized Pd particles. In the limit of high NO2 exposure, these new surface nitrates coexist with surface nitrates formed on the uncovered fraction of the barium aluminate nanoparticles.

Pd-Ga model SCALMS: Characterization and stability of Pd single atom sites - Kettner, Miroslav; Maisel, Sven; Stumm, Corinna; Schwarz, Matthias; Schuschke, Christian; Görling, Andreas; Libuda, Jörg (Journal of Catalysis, 2019)
We have prepared model systems for Pd-Ga supported catalytically active liquid metal solutions (SCALMS) by physical vapor deposition of Pd and Ga in ultrahigh vacuum onto highly oriented pyrolytic graphite (HOPG) pre-modified by Ar+ bombardment. Combining AFM and IRAS with CO as a probe molecule, we investigate the growth behavior, the morphology, the surface chemistry, and the stability of Pd-Ga alloys on HOPG. Our results prove the single atom character of the active sites in Ga-rich Pd-Ga alloys. We show that upon interaction with CO, Ga is displaced from the surface and CO adsorbs in on-top position on surface Pd atoms. Experimental data on the vibrational frequencies and binding energies of CO are compared to the results of DFT calculations for CO adsorption on four different Pd-Ga models, i.e. PdGa(1 0 0), PdGa( 1 1 1), Pd-doped extgreeka-Ga(0 0 1), and Pd-doped fcc-Ga(1 0 0). The comparison suggests that widely separated Pd sites are formed in the Ga matrix.
EAM Import::2019-03-12

Pd model catalysts on clean and modified HOPG: Growth, adsorption properties, and stability - Kettner, Miroslav; Stumm, Corinna; Schwarz, Matthias; Schuschke, Christian; Libuda, Jörg (Surface Science, 2019)
Carbon is a common support material for noble metal nanoparticles in heterogeneous catalysis and electro-catalysis. Very few surface-science-based model studies have been performed, however, with noble metal nanoparticles on carbon supports. In this work, we present the first model study on carbon-supported noble metal nanoparticles using infrared reflection absorption spectroscopy (IRAS). The model catalyst is prepared on highly oriented pyrolytic graphite (HOPG) by physical vapor deposition (PVD) of Pd metal. We characterize the particle growth and morphology by scanning tunneling microscopy (STM) and atomic force microscopy (AFM) and probe the adsorption properties by IRAS of adsorbed CO.PVD of Pd on clean HOPG leads to the formation of very large, weakly interacting particles. In order to increase the nucleation density upon Pd deposition, the HOPG surface was modified by Ar+ and O+ bombardment. The defect structures formed were characterized by STM and by IRAS during the ion bombardment. On the pretreated HOPG, Pd nucleates homogeneously and stable Pd nanoparticles (NPs) are formed. We investigated the adsorption properties of the Pd NPs as a function of the particle size and their thermal stability upon annealing. It is shown that carbon species migrate from the HOPG modified by ion bombardment onto the Pd NPs leading to modification of the CO adsorption properties.The work shows that Pd/HOPG is a very well-suited model system for in-situ adsorption and reaction studies by IRAS, in spite of the non-metallicity of the support.
Keywords: Infrared reflection absorption spectroscopy (IRAS); Highly oriented pyrolytic graphite (HOPG); Scanning tunneling microscopy (STM); Palladium; Carbon monoxide; Surface modification

Pd nanoparticle formation in ionic liquid thin films monitored by in situ vibrational spectroscopy - Mehl, Sascha; Toghan, Arafat; Bauer, Tanja; Brummel, Olaf; Taccardi, Nicola; Wasserscheid, Peter; Libuda, Jörg (Langmuir, 2015)
Ionic liquids (ILs) are flexible reaction media and solvents for the synthesis of metal nanoparticles (NPs). Here, we describe a new preparation method for metallic NPs in nanometer thick films of ultraclean ILs in an ultrahigh vacuum (UHV) environment. CO-covered Pd NPs are formed by simultaneous and by sequential physical vapor deposition (PVD) of the IL and the metal in the presence of low partial pressures of CO. The film thickness and the particle size can be controlled by the deposition parameters. We followed the formation of the NPs and their thermal behavior by time-resolved IR reflection absorption spectroscopy (TP-IRAS) and by temperature-programmed IRAS (TR-IRAS). Codeposition of Pd and [CCIm][OTf] in CO at 100 K leads to the growth of homogeneous multilayer films of CO-covered Pd aggregates in an IL matrix. The size of these NPs can be controlled by the metal fraction in the co-deposit. With increasing metal fraction, the size of the Pd NPs also increases. At very low metal content, small Pd carbonyl-like species are formed, which bind CO in on-top geometry only. Upon annealing, the [OTf] anion coadsorbs at the NP surface and partially displaces CO. Co-adsorption of CO and IL is indicated by a strong red-shift of the CO stretching bands. While the weakly bound on-top CO is mainly replaced below the melting transition of the IL, coadsorbate shells with bridge-bonded CO and IL are stable well above the melting point. Larger three-dimensional Pd NPs can be prepared by PVD of Pd onto a solid [CCIm][OTf] film at 100 K. Upon annealing, on-top CO desorbs from these NPs below 200 K. Upon melting of the IL film, the CO-covered Pd NPs immerse into the IL and again form a stable coadsorbate shell that consists of bridge-bonded CO and the IL.

Pentaarylazafullerenes and their triaryldihydro and tetraarylmonohydro precursors - Neubauer, Ralf; Heinemann, Frank Wilhelm; Hampel, Frank; Rubin, Yves; Hirsch, Andreas (Angewandte Chemie International Edition, 2012)
Give me five! The title compounds were isolated from the acid-catalyzed reaction of a CN precursor with electron-rich aromatic compounds. Single-crystal X-ray diffraction on two compounds reveals characteristic packing motifs; the triaryldihydro derivative has a pseudo-stacked arrangement (Cviolet/yellow, Nblue, Ored, Hwhite). Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Perspective: Chemical reactions in ionic liquids monitored through the gas (vacuum)/liquid interface - Maier, Florian; Niedermaier, Inga; Steinrück, Hans-Peter (Journal of Chemical Physics, 2017)
This perspective analyzes the potential of X-ray photoelectron spectroscopy under ultrahigh vacuum (UHV) conditions to follow chemical reactions in ionic liquids in situ. Traditionally, only reactions occurring on solid surfaces were investigated by X-ray photoelectron spectroscopy (XPS) in situ. This was due to the high vapor pressures of common liquids or solvents, which are not compatible with the required UHV conditions. It was only recently realized that the situation is very different when studying reactions in Ionic Liquids (ILs), which have an inherently low vapor pressure, and first studies have been performed within the last years. Compared to classical spectroscopy techniques used to monitor chemical reactions, the advantage of XPS is that through the analysis of their core levels all relevant elements can be quantified and their chemical state can be analyzed under well-defined (ultraclean) conditions. In this perspective, we cover six very different reactions which occur in the IL, with the IL, or at an IL/support interface, demonstrating the outstanding potential of in situ XPS to gain insights into liquid phase reactions in the near-surface region. (C) 2017 Author(s).

Phosphonic Acids on an Atomically Defined Oxide Surface: The Binding Motif Changes with Surface Coverage - Schuschke, Christian; Schwarz, Matthias; Hohner, Chantal; Silva, Thais N.; Fromm, Lukas; Döpper, Tibor; Görling, Andreas; Libuda, Jörg (Journal of Physical Chemistry Letters, 2018)
We have studied the anchoring mechanism of a phosphonic acid on an atomically defined oxide surface. Using time-resolved infrared reflection absorption spectroscopy, we investigated the reaction of deuterated phenylphosphonic acid (DPPA, C6HsPO3D2) with an atomically defined Co3O4(111) surface in situ during film growth by physical vapor deposition. We show that the binding motif of the phosphonate anchor group changes as a function of coverage. At low coverage, DPPA binds in the form of a chelating tridentate phosphonate, while a transition to a chelating bidentate occurs close to monolayer saturation coverage. However, the coverage-dependent change in the binding motif is not associated with a major change of the molecular orientation, suggesting that the rigid phosphonate linker always maintains the DPPA in a strongly tilted orientation irrespective of the surface coverage.

Phosphonic Acids on Well-Ordered CoO Surfaces: The Binding Motif Depends on the Surface Structure - Schuschke, Christian; Schwarz, Matthias; Hohner, Chantal; Silva, Thais N.; Libuda, Jörg (Journal of Physical Chemistry C, 2018)
In this work, we investigate the interaction of deuterated phenylphosphonic acid (DPPA, C6H5PO3D2) with two different well ordered cobalt-oxide thin films, CoO(111) and CoO(100), grown on Ir(100). We applied coverage-dependent infrared reflection absorption spectroscopy (IRAS) and temperature-programmed (TP)-IRAS under ultrahigh vacuum conditions to study surface reactions, film growth, and thermal stability, both in monolayer and multilayer regimes. The results are compared to our previous studies on Co3O4(111). In the multilayer regime, amorphous multilayer films of DPPA are formed at a low temperature (180 K), which are very similar on all surfaces. At 250 K, the multilayer films crystallize, leading to changes in the molecular orientation relative to the surface. Above 340 K, the multilayer desorbs while only the chemically anchored monolayer remains on the surface. The monolayer films on all three surfaces are stable up to at least 400 K. Coverage and binding geometry, however, depend sensitively on the structure of the oxide surface. On CoO(100), DPPA undergoes complete deprotonation and anchors to the surface forming a fully deprotonated tridentate phosphonate, which dominates over the full range of coverages. On the oxygen terminated CoO(111), we find, in contrast, the formation of a bidentate species in the limit of zero coverage. At a higher coverage, we observe full deprotonation and the formation of tridentate species, which we attribute to the restructuring of the surface. The behavior differs from Co3O4(111), where DPPA forms a fully deprotonated tridentate phosphonate at a low coverage and a partially protonated bidentate phosphonate at higher coverage.(1) The different binding motifs are discussed in view of the arrangement of surface Co ions on the three oxide surfaces.

Photochemical Energy Storage and Electrochemically Triggered Energy Release in the Norbornadiene-Quadricyclane System: UV Photochemistry and IR Spectroelectrochemistry in a Combined Experiment - Brummel, Olaf; Waidhas, Fabian; Bauer, Udo; Wu, Yanlin; Bochmann, Sebastian; Steinrück, Hans-Peter; Papp, Christian; Bachmann, Julien; Libuda, Jörg (Journal of Physical Chemistry Letters, 2017)
The two valence isomers norbornadiene (NBD) and quadricyclane (QC) enable solar energy storage in a single molecule system. We present a new photoelectrochemical infrared reflection absorption spectroscopy (PEC-IRRAS) experiment, which allows monitoring of the complete energy storage and release cycle by in situ vibrational spectroscopy. Both processes were investigated, the photochemical conversion from NBD to QC using the photosensitizer 4,4'-bis(dimethylamino)benzophenone (Michler's ketone, MK) and the electrochemically triggered cycloreversion from QC to NBD. Photochemical conversion was obtained with characteristic conversion times on the order of 500 ms. All experiments were performed under full potential control in a thin layer configuration with a Pt(111) working electrode. The vibrational spectra of NBD, QC, and MK were analyzed in the fingerprint region, permitting quantitative analysis of the spectroscopic data. We determined selectivities for both the photochemical conversion and the electrochemical cycloreversion and identified the critical steps that limit the reversibility of the storage cycle.

Photoelectron diffraction and holography of clean and sulphur-covered Ni(110) - Zharnikov, M.; Mehl, D.; Weinelt, Martin; Zebisch, P.; Steinrück, Hans-Peter (Surface Science, 1994)
We have measured angular distributions of Ni3p photoelectrons for clean Ni(110), and Ni3p as well as S2p and S2p photoelectrons for c(2 × 2)S on Ni(110) at kinetic energies below 300 eV. From the various photoelectron diffraction patterns ( = holograms) we have reconstructed real-space images using the formalism introduced by Barton and applying a Fourier filtering technique. For the clean surface, neighboring atoms in the plane of the emitter can be identified up to the fourth coordinate sphere. The maxima in the reconstructed image show deviations from the correct positions on the order of the expected resolution. In the plane above the emitter, intense artifacts are observed in the reconstructed images in addition to maxima at or close to the correct atomic positions, which hinders an unequivocal identification of substrate atoms in that spatial region. For c(2 × 2) S Ni(110) we are able to verify from the reconstructed images the fourfold hollow adsorption site of sulphur, with the distance above the first Ni layer of about 0.9 Å. The details of the reconstructed real-space images show some differences when using the S2p or S2p photoelectrons. From the reconstructed image in the plane of the emitter (adsorbate plane) an unequivocal identification of the neighboring S atoms in the c(2 × 2) layer is obscured by intense artifacts. © 1994.

Photoelectron diffraction and holography of clean metal surfaces - Mehl, D.; Zharnikov, M.; Zebisch, P.; Weinelt, M.; Steinrück, Hans-Peter (Symposium on Surface Science 3S'94, 1994)

Photoelectron spectroscopy of ionic liquid-based interfaces - Lovelock, Kevin R.J.; Villar-Garcia, Ignacio J.; Maier, Florian; Steinrück, Hans-Peter; Licence, Peter (Chemical Reviews, 2010)
Photoelectron spectroscopies (PES) are a class of surface analysis techniques that involve irradiating the sample in Vacuo with photons and measuring the kinetic energy of the electrons emitted. Ultrahigh vacuum (UHV) is generally required to analyze the emitted photoelectrons without interference from gas phase collisions. XPS can be used to identify and quantify the different chemical environments of the same element within a given IL. Each individual element signal is a function of the chemical environment of the atoms of interest. There are two contributions to the observed chemical shifts in XP spectra, namely initial and final state effects. Initial state effects are those that affect the charge of the atom before the photon strikes and are described by calculations of the ground state of a particular system.

Photoelectron spectroscopy of molecular-beam epitaxially grown BeTe/ZnSe and BeTe/GaAs heterostructures - Nagelstraßer, M.; Dröge, H.; Fischer, F.; Litz, T.; Waag, Andreas; Landwehr, G.; Steinrück, Hans-Peter (Journal of Crystal Growth, 1998)
BeTe is a new material within the class of II-VI semiconductors with novel and interesting properties. It is well lattice matched to GaAs as well as ZnSe and therefore can be combined in superlattices with these materials. Using photoelectron spectroscopy we have investigated the valence-band offset (ΔE) of BeTe/ZnSe and BeTe/GaAs heterojunctions, grown by molecular-beam epitaxy (MBE). For the BeTe/ZnSe heterostructure with a Zn-rich interface, we measured a valence-band offset of 1.26 ± 0.15 eV and for the heterovalent BeTe/GaAs interface we determined a far smaller valence-band offset of -0.25 ± 0.15 eV. From UPS measurements for increasing layer thickness of BeTe on ZnSe we calculated the accumulation layer of BeTe with a Debye-length of 6 nm and a defect concentration of 4.10cm. © 1998 Elsevier Science B.V. All rights reserved.

Photoemission study of the Na/ZnSe(100) interface - Fink, Rainer; Umbach, Eberhard; et al. (Physical Review B, 1999)
We report on a comprehensive study of the ZnSe(100)-c(2X2)-Na interface using x-ray and UV photo-emission, and x-ray-induced Auger spectroscopy. Spectra were taken after stepwise Na deposition onto a clean c(2X2)-reconstructed ZnSe(100) surface at room temperature up to a saturation coverage of about 1 ML of Na and after annealing. Based on the analysis of Auger parameters and of the relative intensity evolution of various Na, Zn, and Se species, we present the following model for the ZnSe(100)-c(2X2)-Na interface: below a coverage of 0.5 ML, Na is adsorbed on Zn vacancy sites; above 0.5 ML, a cation exchange reaction occurs between Na and Zn atoms; Zn atoms segregate on top of the Na overlayer forming metallic Zn. In addition, band-bending, surface dipole, valence-band and surface states will be discussed. ©1999 The American Physical Society.
UnivIS-Import:2015-03-05:Pub.1999.nat.dchph.ppc23.photoe

Photoinduced degradation of methylammonium lead triiodide perovskite semiconductors - Tang, Xiaofeng; Brandl, Marco; May, Benjamin; Levchuk, Ievgen; Hou, Yi; Richter, Moses; Chen, Haiwei; Chen, Shi; Kahmann, Simon; Osvet, Andres; Maier, Florian; Steinrück, Hans-Peter; et al. (Journal of Materials Chemistry A, 2016)
Photoinduced degradation is a critical obstacle for the real application of novel semiconductors for photovoltaic applications. In this paper, the photoinduced degradation of CHNHPbI in a vacuum and air (relative humidity 40%) is analyzed by ex situ and advanced in situ technologies. Without light illumination, CHNHPbI films slowly degrade under vacuum and air within 24 hours. However, we find that CHNHPbI converts to metallic lead (Pb) when exposed to vacuum and light illumination. Further, a series of lead salts (e.g. PbO, Pb(OH) and PbCO) are formed when CHNHPbI is degraded under environmental conditions, i.e. under the combination of light, oxygen and moisture. Photoinduced degradation is found to be determined by the environmental atmosphere as CHNHPbI films remain very stable under nitrogen conditions. The results from vacuum conditions underpin that the high volatility of the organic component (CHNHI) is in conflict with reaching excellent intrinsic stability due to its role in creating ion vacancies. The degradation in air suggests that both oxygen and water contribute to the fast photodecomposition of CHNHPbI into lead salts rather than water alone. Given these basic yet fundamental understandings, the design of hydrophobic capping layers becomes one prerequisite towards long-term stable perovskite-based devices.
Keywords: Engineering controlled terms: Lead; Perovskite; Salts; Slow light Environmental conditions; Intrinsic stability; Light illumination; Organic components; Photo-decomposition; Photoinduced degradation; Photovoltaic applications; Real applications Engineering main heading: Photodegradation

Physical vapor deposition of [EMIM][Tf2N]: A new approach to the modification of surface properties with ultrathin ionic liquid films - Cremer, Till; Killian, Manuela; Gottfried, Michael; Paape, Natalia; Wasserscheid, Peter; Maier, Florian; Steinrück, Hans-Peter (ChemPhysChem, 2008)
Ultrathin films of the ionic liquid (IL) 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, [EMIM][TfN], are prepared on a glass substrate by means of an in situ thermal-evaporation/condensation process under ultrahigh-vacuum conditions. By using X-ray photoelectron spectroscopy (XPS), it is demonstrated that the first layer of the IL film grows two dimensionally, followed by the three-dimensional growth of successive layers. The first molecular layer consists of a bilayer, with the [EMIM] cations in contact to the surface and the [TfN] anions at the vacuum side. The ultrathin IL films are found to be stable under ambient conditions. © 2008 Wiley-VCH Verlag GmbH & Co. KGaA.

Physical vapor deposition of Ga on polycrystalline Au surfaces studied using X-ray photoelectron spectroscopy - Grabau, Mathias; Steinrück, Hans-Peter; Papp, Christian (Surface Science, 2018)
We studied the deposition of Ga onto polycrystalline Au surfaces at room temperature by X-ray photoelectron spectroscopy (XPS). We find the formation of an alloy film with an average composition of Au7Ga3 in the near surface region probed by XPS, as deduced from qualitative and quantitative analysis of the Ga 2p(3/2), Ga 3d and Au 4f signals. The formation of the Au7Ga3 alloy is reversed, and the original spectroscopic Au 4f fingerprint is restored upon exposure of the alloy to molecular oxygen at elevated pressures and elevated temperatures. We find the formation of a GaxOy film on top of the Au substrate, which goes along with a dealloying of the surface near Au7Ga3 alloy phase.
Keywords: Au; Gold; Ga; Gallium; Intermetallic compound; IMC; PVD; XPS

Polarized X-ray scattering reveals non-crystalline orientational ordering in organic films - Collins, B. A.; Cochran, J. E.; Yan, Hongping; Gann, Eliot; Hub, Christian; Fink, Rainer; Wang, Cheng; Schuettfort, T.; Mcneill, C. R.; Chabinyc, M. L.; Ade, Harald (Nature Materials, 2012)
Molecular orientation critically influences the mechanical, chemical, optical and electronic properties of organic materials. So far, molecular-scale ordering in soft matter could be characterized with X-ray or electron microscopy techniques only if the sample exhibited sufficient crystallinity. Here, we show that the resonant scattering of polarized soft X-rays (P-SoXS) by molecular orbitals is not limited by crystallinity and that it can be used to probe molecular orientation down to size scales of 10nm. We first apply the technique on highly crystalline small-molecule thin films and subsequently use its high sensitivity to probe the impact of liquid-crystalline ordering on charge mobility in polymeric transistors. P-SoXS also reveals scattering anisotropy in amorphous domains of all-polymer organic solar cells where interfacial interactions pattern orientational alignment in the matrix phase, which probably plays an important role in the photophysics. The energy and q-dependence of the scattering anisotropy allows the identification of the composition and the degree of orientational order in the domains. © 2012 Macmillan Publishers Limited. All rights reserved.

Poly(benzimidazobenzophenanthroline)-Ladder-Type Two-Dimensional Conjugated Covalent Organic Framework for Fast Proton Storage** - Wang, Mingchao; Wang, Gang; Naisa, Chandrasekhar; Fu, Yubin; Gali, Sai Manoj; Paasch, Silvia; Wang, Mao; Wittkämper, Haiko; Papp, Christian; Brunner, Eike; Zhou, Shengqiang; Beljonne, David; et al. (Angewandte Chemie International Edition, 2023)
Electrochemical proton storage plays an essential role in designing next-generation high-rate energy storage devices, e.g., aqueous batteries. Two-dimensional conjugated covalent organic frameworks (2D c-COFs) are promising electrode materials, but their competitive proton and metal-ion insertion mechanisms remain elusive, and proton storage in COFs is rarely explored. Here, we report a perinone-based poly(benzimidazobenzophenanthroline) (BBL)-ladder-type 2D c-COF for fast proton storage in both a mild aqueous Zn-ion electrolyte and strong acid. We unveil that the discharged C−O− groups exhibit largely reduced basicity due to the considerable π-delocalization in perinone, thus affording the 2D c-COF a unique affinity for protons with fast kinetics. As a consequence, the 2D c-COF electrode presents an outstanding rate capability of up to 200 A g−1 (over 2500 C), surpassing the state-of-the-art conjugated polymers, COFs, and metal–organic frameworks. Our work reports the first example of pure proton storage among COFs and highlights the great potential of BBL-ladder-type 2D conjugated polymers in future energy devices.
CRIS-Team Scopus Importer:2023-10-20
Keywords: 2D Conjugated COFs; Poly(Benzimidazobenzophenanthroline); Proton Storage; Strong Acid; Zn-Ion Electrolyte

Polymorphism of porphyrin molecules on Ag(111) and how to weave a rigid monolayer - Buchner, Florian; Comanici, Karmen; Jux, Norbert; Steinrück, Hans-Peter; Marbach, Hubertus (Journal of Physical Chemistry C, 2007)
The molecular arrangement and the internal conformation of Co(II)-5,10,15,20-tetrakis-(3,5-di-tert-butylphenyl)-porphyrin (Co(II)-TTBPP) on Ag(111) was studied by scanning tunneling microscopy (STM) under ultrahigh vacuum (UHV) conditions. Interestingly, four different molecular arrangements were found using different routes to prepare the porphyrin films. After the preparation of a film with a coverage slightly below one monolayer by thermal sublimation, three clearly distinguishable molecular arrangements could be observed. Alternatively, a monolayer was prepared by deposition of a multilayer followed by subsequent annealing to desorb the excess multilayer molecules. Thereby, an additional, very rigid herringbone structure formed via a thermally activated process, covering most of the surface. The four ordered phases go along with different conformations of the individual molecules. On the basis of STM images with submolecular resolution, models for the lateral arrangements of the different polymorphs including the internal conformation of the individual molecules are proposed. Thereby, as an extension to previous works, the rotation of the upper tert-butyl groups of Co-TTBPP was taken into account. The derived molecular arrangements in combination with the intramolecular conformations give insight into the intermolecular interactions within and the nature of the different molecular phases. © 2007 American Chemical Society.

Porphine Homocoupling on Au(111) - Seufert, Knud; McBride, Fiona; Jaekel, Simon; Wit, Bareld; Haq, Samreen; Steiner, Alexander; Poli, Paolo; Persson, Mats; Raval, Rasmita; Grill, Leonhard (Journal of Physical Chemistry C, 2019)
The covalent coupling of porphine molecules on Au(111) is studied by scanning probe microscopy experiments and density functional theory. At sufficient temperatures, dehydrogenative C-C coupling of the un-functionalized molecules occurs directly on the surface. Characteristic dimer structures between individual porphine molecules are observed and assigned to various binding motifs that are distinguished by specific intermolecular connections. Different preparations show that the relative abundance of these motifs depends on the temperature of the gold sample during deposition and is explained by calculated free energies and kinetic aspects that are relevant during the linking process. Observations on the gold terraces are completed by studying polymerization at step edges, giving insight into their role during the covalent linking process.

Porphyrin Metalation at MgO Surfaces: A Spectroscopic and Quantum Mechanical Study on Complementary Model Systems - Schneider, Johannes; Franke, Matthias; Gurrath, Martin; Röckert, Michael; Berger, Thomas; Bernardi, Johannes; Meyer, Bernd; Steinrück, Hans-Peter; Lytken, Ole; Diwald, Oliver (Chemistry - A European Journal, 2016)
We show that both single-crystalline and nanostructured MgO surfaces convert free-base tetraphenyl porphyrin (2HTPP) into magnesium tetraphenyl porphyrin (MgTPP) at room temperature. The reaction can be viewed as an ion exchange between the two aminic protons of the 2HTPP molecule with a Mg ion from the surface. The driving force for the reaction is the strong stability of the formed hydroxyl groups along the steps and at defects on the MgO surface. We have used an integrated characterization approach that includes UV/Vis diffuse reflectance measurements on nanostructured powders, X-ray photoelectron spectroscopic investigation of atomically clean MgO(100) single-crystalline thin films, and density functional theory (DFT) calculations on model systems. The DFT calculations demonstrate that MgTPP formation is strongly exothermic at the corners, edges and steps, but slightly endothermic on terrace sites. This agrees well with the UV/Vis diffuse reflectance, which upon adsorption of 2HTPP shows a decrease in the absorption band associated with corner and edge sites on MgO nanocube powders. Porphyrin swap shop: Spectroscopic adsorption studies on two complementary model systems, atomically clean thin MgO(100) films and MgO nanocube powders, show that low-coordinated surface cations located in corner, edge, or step regions of the MgO surfaces are subject to ion exchange between adsorbed porphyrin molecules and the oxide surface.
Keywords: ion exchange; metalation; nanocubes; porphyrin; surface defects

Porphyrin Metalation at the MgO Nanocube/Toluene Interface - Schneider, Johannes; Kollhoff, Fabian; Bernardi, Johannes; Kaftan, Andre; Libuda, Jörg; Berger, Thomas; Laurin, Mathias; Diwaid, Oliver (ACS Applied Materials and Interfaces, 2015)
Molecular insights into porphyrin adsorption on nanostructured metal oxide surfaces and associated ion exchange reactions are key to the development of functional hybrids for energy conversion, sensing, and light emission devices. Here we investigated the adsorption of tetraphenylporphyrin (2HTPP) from toluene solution on two types of MgO powder. We compare MgO nanocubes with an average size d < 10 nm and MgO cubes with 10 nm <= d <= 1000 nm. Using molecular spectroscopy techniques such as UV/vis transmission and diffuse reflectance (DR), photoluminescence (PL), and diffuse reflectance infrared Fourier-transform (DRIFT) spectroscopy in combination with structural characterization techniques (powder X-ray diffraction and transmission electron microscopy, TEM), we identified a new room temperature metalation reaction that converts 2HTPP into magnesium tetraphenyl-porphyrin (MgTPP). Mg2+ uptake from the MgO nanocube surfaces and the concomitant protonation of the oxide surface level off at a concentration that corresponds to roughly one monolayer equivalent adsorbed on the MgO nanocubes. Larger MgO cubes, in contrast, show suppressed exchange, and only traces of MgTPP can be detected by photoluminescence.
Keywords: porphyrin metalation; MgO cubes; solid-liquid interface; molecular spectroscopies; dye adsorption; hybrid materials

Potential Screening at Electrode/Ionic Liquid Interfaces from In Situ X-ray Photoelectron Spectroscopy - Greco, Francesco; Shin, Sunghwan; Williams, Federico J.; Heller, Bettina; Maier, Florian; Steinrück, Hans-Peter (ChemistryOpen, 2019)
A new approach to investigate potential screening at the interface of ionic liquids (ILs) and charged electrodes in a two-electrode electrochemical cell by in situ X-ray photoelectron spectroscopy has been introduced. Using identical electrodes, we deduce the potential screening at the working and the counter electrodes as a function of applied voltage from the potential change of the bulk IL, as derived from corresponding core level binding energy shifts for different IL/electrode combinations. For imidazolium-based ILs and Pt electrodes, we find a significantly larger potential screening at the anode than at the cathode, which we attribute to strong attractive interactions between the imidazolium cation and Pt. In the absence of specific ion/electrode interactions, asymmetric potential screening only occurs for ILs with different cation and anion sizes as demonstrated for an imidazolium chloride IL and Au electrodes, which we assign to the different thicknesses of the electrical double layers. Our results imply that potential screening in ILs is mainly established by a single layer of counterions at the electrode.
CRIS-Team WoS Importer:2019-10-01

Precursors and trapping in the molecular chemisorption of CO on Ni(100) - D'Evelyn, M.P.; Steinrück, Hans-Peter; Madix, R.J. (Surface Science, 1987)
The dynamics of molecular chemisorption of CO on Ni(100) has been investigated using supersonic molecular beam techniques. In order to probe the role of energy accommodation and of so-called precursor states, we have determined the dependence of the molecular sticking probability and the angular scattering distribution on the translational energy and incident angle of the incoming molecules, on surface temperature, and on surface coverage. At low translational energy CO adsorption proceeds in a fashion indicative of classical precursor kinetics. However, both the temperature independence of the initial sticking probability and the form of the angular scattering distribution of non-chemisorbing molecules (obtained using modulated beam techniques) indicate that molecules that fail to chemisorb on the clean surface are directly scattered and do not become fully accommodated in a precursor state. As the translational energy of the CO molecules at normal incidence is increased from 2 to 30 kcal mol, S decreases smoothly from 0.91 to 0.5. Further, for translational energies greater than 10 kcal mol S decreases with increasing angle of incidence. This surprising result indicates that the chemisorption probability decreases as the component of incident velocity parallel to the surface increases, just as it does for the normal component, but at a larger rate. The dynamics of the accommodation process are discussed in terms of a "hot", not thermalized, precursor. Increasing the translational energy of the molecule affects not only the value of the sticking probability but also the form of the variation of sticking probability with coverage and with surface temperature. We report for the first time a transition between precursor adsorption kinetics at low translational energy (2 kcal mol) to direct (Langmuirian) adsorption at high incident energy (21 kcal mol). Scattering experiments performed on a surface with saturation coverage confirm this result. © 1987.

Prediction of the lithium storage capacity of hollow carbon nano-spheres based on their size and morphology - Shaker, Majid; Yaghmaee, Maziar Sahba; Shahalizade, Taieb; Ghazvini, Ali Asghar Sadeghi; Riahifar, Reza; Raissi, Babak; Ge, Qi (Journal of Materials Science: Materials in Electronics, 2022)
To date, there is an enormous experimental research focus on discovering the usage of carbon materials as Lithium-ion battery (LIB) anode active materials, though there is a limited number of scientific articles exploring the links between the properties of these materials and their lithium storage performance. The goal of this study is to find the relationship between the size and shape of carbon hollow spheres and their lithium storage capacity via modeling. This research considers the lithium storage of hollow carbon spheres originated from two distinct bulk- and surface-dependent mechanisms. Based on this assumption, a unique model is developed that uses a factor termed “normalized volume” to appropriately consider and estimate the contribution of the surface and bulk phenomena to the lithium storage capacity of a carbon hollow sphere. The model exhibited that shrinking the shell thickness of carbon hollow spheres to less than 20 nm significantly increases their lithium storage capacity. The agreement of the predicted and experimentally reported lithium storage capacities was evaluated by comparing the calculated values to experimental data from the literature. This model has the potential to be used as a foundational method or guideline to forecast the lithium storage capacity of different nano-scaled carbon materials regarding their inner structure, size, and shape.
CRIS-Team Scopus Importer:2022-05-13

Preparation and Adsorption Properties of Pd Nanoparticles Supported on TiO2 Nanotubes - Honciuc, Andrei; Laurin, Mathias; Albu, Sergiu; Amende, Maximilian; Sobota, Marek; Lynch, Robert; Schmuki, Patrik; Libuda, Jörg (Journal of Physical Chemistry C, 2010)
Here we present preparation methods for a series of novel model heterogeneous catalysts consisting of Pd nanoparticles dispersed on self-organized TiO2 nanotube arrays (TiNTs). For a comprehensive comparative study of TiNTs' surface adsorption properties, different chemical and physical methods were employed for the deposition of the Pd nanoparticles: (i) e-beam deposition in high vacuum (HV) and (ii) in ultrahigh vacuum (UHV), (iii) impregnation, and (iv) metal precipitation. Following preparation, the Pd/TiNTs were exposed to several O-2 (oxidative) and CO (reductive) cleaning cycles at 500 K in UHV. After each cleaning cycle, the CO adsorption properties were systematically probed with time-resolved infrared reflection-adsorption spectroscopy to monitor the surface state of the catalyst. It is shown that clean and well-defined Pd/TiNT catalysts can be obtained, which are well suited for future adsorption and reactivity studies.

Preparation and characterization of model catalysts: from ultrahigh vacuum to in situ conditions at the atomic dimension - Libuda, Jörg; et al. (Journal of Catalysis, 2003)
In situ characterization and reaction studies of working catalytic systems are an issue of current interest. We present studies on well characterized model systems, i.e., deposited metal nanoparticles, applying a variety of experimental techniques in an attempt to bridge gaps between surface science and catalysis. In particular, we investigate methanol dehydrogenation and ethene hydrogenation under UHV as well as ambient conditions and apply nonlinear optical techniques. We use electron spin resonance to study intermediately formed radicals in Ziegler-Natta polymerization of ethene. It is concluded that there is a chance to transfer results from studies on model systems toward an understanding of catalysis. © 2003 Elsevier Science (USA). All rights reserved.
UnivIS-Import:2015-03-09:Pub.2003.nat.dchph.ppc20.prepar
Keywords: Electron spin resonance; Ethene hydrogenation; Ethene polymerization; In-situ studies; Methanol dehydrogenation; Model catalysts; Sum frequency generation

Preparation and characterization of ultrathin [Ru(CO) 3Cl 2] 2 and [BMIM][Tf 2N] films on Al 2O 3/NiAl(110) under UHV conditions - Sobota, Marek; Schernich, Stefan; Schulz, Hannes; Hieringer, Wolfgang; Paape, Natalia; Wasserscheid, Peter; Görling, Andreas; Laurin, Mathias; Libuda, Jörg (Physical Chemistry Chemical Physics, 2012)
Towards a better understanding of the interface chemistry of ionic liquid (IL) thin film catalytic systems we have applied a rigorous surface science model approach. For the first time, a model homogeneous catalyst has been prepared under ultrahigh vacuum conditions. The catalyst, di-μ- chlorobis(chlorotricarbonylruthenium) [Ru(CO) Cl ] , and the solvent, the IL 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide [BMIM][Tf N], have been deposited by physical vapor deposition onto an alumina model support [Al O /NiAl(110)]. First, the interaction between thin films of [Ru(CO) Cl ] and the support is investigated. Then, the ruthenium complex is co-deposited with the IL and the influence of the solvent on the catalyst is discussed. D O, which is a model reactant, is further added. Growth, surface interactions, and mutual interactions in the thin films are studied with IRAS in combination with density functional (DFT) calculations. At 105 K, molecular adsorption of [Ru(CO) Cl ] is observed on Al O /NiAl(110). The IRAS spectra of the binary [Ru(CO) Cl ] + [BMIM][Tf N] and ternary [Ru(CO) Cl ] + [BMIM][Tf N] + D O show every characteristic band of the individual components. Above 223 K, partial decomposition of the ruthenium complex leads to species of molecular nature attributed to Ru(CO) and Ru(CO) surface species. Formation of metallic ruthenium clusters occurs above 300 K and the model catalyst decomposes further at higher temperatures. Neither the presence of the IL nor of D O prevents this partial decomposition of [Ru(CO) Cl ] on alumina. © 2012 the Owner Societies.

Preparation of complex model electrocatalysts in ultra-high vacuum and transfer into the electrolyte for electrochemical IR spectroscopy and other techniques - Faisal, Firas; Bertram, Manon; Stumm, Corinna; Waidhas, Fabian; Brummel, Olaf; Libuda, Jörg (Review of Scientific Instruments, 2018)
Model studies at complex, yet well-defined electrodes can provide a better understanding of electrocatalytic reactions. New experimental devices are required to prepare such model electrocatalysts with atomic-level control. In this work, we discuss the design of a new setup, which enables the preparation of well-defined electrocatalysts in ultra-high vacuum (UHV) using the full portfolio of surface science techniques. The setup allows for direct transfer of samples from UHV and the immersion into the electrolyte without contact to air. As a special feature, the single crystal sample is transferred without any sample holder, which makes the system easily compatible with most electrochemical in situ methods, specifically with electrochemical infrared reflection absorption spectroscopy, but also with other characterization methods such as single-crystal cyclic voltammetry, differential electrochemical mass spectrometry, or electrochemical scanning tunneling microscopy. We demonstrate the preparation in UHV, the transfer in inert atmosphere, and the immersion into the electrolyte for a complex model catalyst that requires surface science methods for preparation. Specifically, we study Pt nanoparticles supported on well-ordered Co3O4(111) films which are grown on an Ir(100) single crystal. In comparison with reference experiments on Pt(111), the model catalyst shows a remarkably different adsorption and reaction behavior during CO electrooxidation in alkaline environments. Published by AIP Publishing.

Preparation of geometrically highly controlled Ga particle arrays on quasi-planar nanostructured surfaces as a SCALMS model system - Hofer, André; Taccardi, Nicola; Moritz, Michael; Wichmann, Christoph; Hübner, Sabine; Drobek, Dominik; Engelhardt, Matthias; Papastavrou, Georg; Spiecker, Erdmann; Papp, Christian; Wasserscheid, Peter; Bachmann, Julien (RSC Advances, 2023)
This study establishes a preparative route towards a model system for supported catalytically active liquid metal solutions (SCALMS) on nanostructured substrates. This model is characterized by a uniquely precise geometrical control of the gallium particle size distribution. In a SCALMS system, the Ga serves as a matrix material which can be decorated with a catalytically active material subsequently. The corresponding Ga containing precursor is spin-coated on aluminum based substrates, previously nanostructured by electrochemical anodization. The highly ordered substrates are functionalized with distinct oxide coatings by atomic layer deposition (ALD) independently from the morphology. After preparation of the metal particles on the oxide interface, the characterization of our model system in terms of its geometry parameters (droplet diameter, size distribution and population density) points to SiO2 as the best suited surface for a highly controlled geometry. This flexible model system can be functionalized with a dissolved noble metal catalyst for the application chosen.<br

Principle and mechanism of direct porphyrin metalation: Joint experimental and theoretical investigation - Shubina, Tatyana; Marbach, Hubertus; Flechtner, Ken; Kretschmann, Andreas; Jux, Norbert; Buchner, Florian; Steinrück, Hans-Peter; Clark, Timothy; Gottfried, Michael (Journal of the American Chemical Society, 2007)
The direct metalation of tetraphenylporphyrin with bare metal atoms (Co and Zn) was studied with X-ray photoelectron spectroscopy, scanning tunneling microscopy, and temperature-programmed reaction measurements on ordered monolayer films of the molecules adsorbed on a Ag(111) surface. The mechanism of this novel type of surface reaction was investigated using density functional theory (DFT) calculations for the related gas-phase reactions of the unsubstituted porphyrin with the metals Fe, Co, Ni, Cu, and Zn. The reaction starts with the formation of an initial complex, in which the metal atom is coordinated by the intact unreduced porphyrin. This complex resembles the sitting-atop complex proposed for porphyrin metalation with metal ions in solution. In two subsequent steps, the pyrrolic hydrogen atoms are transferred to the metal atom, forming H , which is eventually released. The activation barriers of the H-transfer steps vary for the different metal atoms. DFT calculations suggest that metalations with Fe, Co, and Ni show two-state reactivity, while those with Cu and Zn proceed on a single potential energy surface. For metalation with Zn, we calculated a barrier of the first hydrogen transfer step of 32.6 kcal mol , in good agreement with the overall experimental activation energy of 31 kcal mol . © 2007 American Chemical Society.

Probing a gas/liquid acid-base reaction by X-ray photoelectron spectroscopy - Niedermaier, Inga; Taccardi, Nicola; Wasserscheid, Peter; Maier, Florian; Steinrück, Hans-Peter (Angewandte Chemie International Edition, 2013)
A mechanistic study: In a Brønsted acid/base reaction, gaseous triflic acid (OTfH) transfers its proton to the basic Cl anion of the ionic liquid [CCIm]Cl forming volatile HCl and the IL [CCIm][TfO]. This anion exchange reaction is monitored in the near-surface region quantitatively by X-ray photoelectron spectroscopy as a function of time (see picture; BE=binding energy). Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Probing Surface and Interfacial Tension of Ionic Liquids in Vacuum with the Pendant Drop and Sessile Drop Method - Paap, Ulrike; Kreß, Bernd; Steinrück, Hans-Peter; Maier, Florian (International Journal of Molecular Sciences, 2022)
We report on the surface and interface tension measurements of the two ionic liquids (ILs) [C8C1Im][PF6] and [m(PEGn)2Im]I (n = 2, 4, 6) in a surface science approach. The measurements were performed in a newly developed and unique experimental setup, which allows for surface tension (ST) measurements using the pendant drop method and for contact angle measurements using the sessile drop method under the well-defined conditions of a high vacuum (from 10−7 mbar). The setup also allows for in vacuum transfer to an ultrahigh vacuum system for surface preparation and analysis, such as in angle-resolved X-ray photoelectron spectroscopy. For [C8C1Im][PF6], we observe a linear decrease in the surface tension with increasing temperature. The ST measured under high vacuum is consistently found to be larger than under ambient conditions, which is attributed to the influence of water uptake in air by the IL. For [m(PEGn)2Im]I (n = 2, 4, 6), we observe a decrease in the ST with increasing polyethylene glycol chain length in a vacuum, similar to very recent observations under 1 bar Argon. This decrease is attributed to an increasing enrichment of the PEG chains at the surface. The ST data obtained under these ultraclean conditions are essential for a fundamental understanding of the relevant parameters determining ST on the microscopic level and can serve as a benchmark for theoretical calculations, such as molecular dynamic simulations. In addition to the ST measurements, proof-of-principle data are presented for sessile drop measurements in HV, and a detailed description and characterization of the new setup is provided.
CRIS-Team Scopus Importer:2022-11-25
Keywords: interface tension; ionic liquids (ILs); pendant drop; sessile drop; surface science; surface tension; vacuum

Probing the interaction of Rh, Co and bimetallic Rh-Co nanoparticles with the CeO2 support: catalytic materials for alternative energy generation - Varga, E.; Pusztai, P.; Ovari, L.; Oszko, A.; Erdohelyi, A.; Papp, Christian; Steinrück, Hans-Peter; Konya, Zoltan; Kiss, J. (Physical Chemistry Chemical Physics, 2015)
The interaction of CeO2-supported Rh, Co and bimetallic Rh-Co nanoparticles, which are active catalysts in hydrogen production via steam reforming of ethanol, a process related to renewable energy generation, was studied by X-ray diffraction (XRD), high resolution electron microscopy (HRTEM), X-ray photoelectron spectroscopy (XPS) and low energy ion scattering (LEIS). Furthermore, diffuse reflectance infrared spectroscopy (DRIFTS) of adsorbed CO as a probe molecule was used to characterize the morphology of metal particles. At small loadings (0.1%), Rh is in a much dispersed state on ceria, while at higher contents (1-5%), Rh forms 2-8 nm particles. Between 473-673 K pronounced oxygen transfer from ceria to Rh is observed and at 773 K significant agglomeration of Rh occurs. On reduced ceria, XPS indicates a possible electron transfer from Rh to ceria. The formation of smaller ceria crystallites upon loading with Co was concluded from XRD and HRTEM; for 10% Co, the CeO2 particle size decreased from 27.6 to 10.7 nm. A strong dissolution of Co into ceria and a certain extent of encapsulation by ceria were deduced by XRD, XPS and LEIS. In the bimetallic system, the presence of Rh enhances the reduction of cobalt and ceria. During thermal treatments, reoxidation of Co occurs, and Rh agglomeration as well as oxygen migration from ceria to Rh are hindered in the presence of cobalt.

Probing the Roughness of Porphyrin Thin Films with X-ray Photoelectron Spectroscopy - Kataev, Elmar; Wechsler, Daniel; Williams, Federico J.; Köbl, Julia; Tsud, Natalia; Franchi, Stefano; Steinrück, Hans-Peter; Lytken, Ole (ChemPhysChem, 2020)
Thin-film growth of molecular systems is of interest for many applications, such as for instance organic electronics. In this study, we demonstrate how X-ray photoelectron spectroscopy (XPS) can be used to study the growth behavior of such molecular systems. In XPS, coverages are often calculated assuming a uniform thickness across a surface. This results in an error for rough films, and the magnitude of this error depends on the kinetic energy of the photoelectrons analyzed. We have used this kinetic-energy dependency to estimate the roughnesses of thin porphyrin films grown on rutile TiO2(110). We used two different molecules: cobalt (II) monocarboxyphenyl-10,15,20-triphenylporphyrin (CoMCTPP), with carboxylic-acid anchor groups, and cobalt (II) tetraphenylporphyrin (CoTPP), without anchor groups. We find CoMCTPP to grow as rough films at room temperature across the studied coverage range, whereas for CoTPP the first two layers remain smooth and even; depositing additional CoTPP results in rough films. Although, XPS is not a common technique for measuring roughness, it is fast and provides information of both roughness and thickness in one measurement.
CRIS-Team Scopus Importer:2020-10-02
Keywords: Growth; Porphyrin molecules; Thin films; X-ray photoelectron spectroscopy

Probing the Surface Tension of Ionic Liquids Using the Langmuir Principle - Shimizu, Karina; Heller, Bettina; Maier, Florian; Steinrück, Hans-Peter; Canongia Lopes, Jose N. (Langmuir, 2018)
At 298 K, the surface tension of ionic liquids (ILs) of the 1-alkyl-3-methylimidazolium bis- (trifluoromethylsulfonyl)imide series, [CnC1,Im][NTf2 ], ranges 36 from around 35 mN center dot m(-1) for [C2C1 Im][NTf2] to just below 30 mN center dot m(-1)for [C(12)C(1)Im][NTf2]. However, the decrease rate along the series is not constant: a large decrease from [C(2)C(1)Im][NTf2] to [C(8)C(1)Im][NTf2] is followed by almost constant values from [C(8)C(1)Im][NTf2] to [C(12)C(1)Im][NTf2]. Such behavior is hard to interpret from a molecular point of view without suitable information about the free-surface structure of the different ILs. In this work, we have successfully used the Langmuir principle in combination with structural data obtained from angle-resolved Xray photoelectron spectroscopy experiments and molecular dynamics simulations, to predict the correct surface tension trend along the IL series. The concepts unveiled for this particular homologous IL family can be easily extended to other systems.

Production of nitrogen-doped graphene by low-energy nitrogen implantation - Zhao, Wei; Höfert, Oliver; Gotterbarm, Karin; Zhu, Junfa; Papp, Christian; Steinrück, Hans-Peter (Journal of Physical Chemistry C, 2012)
Nitrogen doping of graphene is a suitable route to tune the electronic structure of graphene, leading to n-type conductive materials. Herein, we report a simple way to insert nitrogen atoms into graphene by low-energy nitrogen bombardment, forming nitrogen-doped graphene. The formation of nitrogen-doped graphene is investigated with high resolution X-ray photoelectron spectroscopy, allowing to determine the doping level and to identify two different carbon-nitrogen species. By application of different ion implantation energies and times, we demonstrate that a doping level of up to 0.05 monolayers is achievable and that the branching ratio of the two nitrogen species can be varied. © 2012 American Chemical Society.

Pronounced surface enrichment of fluorinated ionic liquids in binary mixtures with methoxy-functionalized ionic liquids - Heller, Bettina; Paap, Ulrike; Maier, Florian; Steinrück, Hans-Peter (Journal of Molecular Liquids, 2020)
Different binary mixtures of two functionalized ionic liquids (ILs), namely 1,3-di(methoxy)imidazolium hexafluorophosphate, [(MeO)2Im][PF6], and 3-methyl-1-(3,3,4,4,4-pentafluorobutyl)imidazolium hexafluorophosphate, [PFBMIm][PF6], are investigated in the liquid state by angle-resolved X-ray photoelectron spectroscopy (ARXPS). Both ILs consist of the same [PF6]− anion but differ in the functionalization of the cation: [(MeO)2Im][PF6] has an oxygen atom directly bound to each nitrogen atom of the imidazolium ring whereas in [PFBMIm][PF6] the two terminal carbon atoms of the butyl chain are fully fluorinated. Due to different electronic structures of the cations of both ILs, the ARXP signals of the two cations and of the anion can be well distinguished, which allows to identify preferential chain orientation as well as enrichment and depletion effects at the surface. In the mixtures with 50, 90 and 95 mol% [(MeO)2Im][PF6], a very pronounced enrichment of the [PFBMIm]+ cation at the IL/vacuum interface is observed. The fluorinated chain points towards the vacuum side and thereby attenuates the signal of the [PF6]− anion. Decreasing the temperature from 95 °C to close to the solidification temperatures of the mixtures leads to a more pronounced surface enrichment of the [PFBMIm]+ cation and of the fluorinated chain.
CRIS-Team Scopus Importer:2020-03-17
Keywords: Ionic liquid; Mixture; Surface enrichment; X-ray photoelectron spectroscopy

Pt‒CeO2 catalysts for fuel cell applications: From surface science to electrochemistry - Lykhach, Yaroslava; Brummel, Olaf; Bruix, Albert; Fabris, Stefano; Matolinova, Iva; Matolin, Vladimir; Neyman, Konstantin M.; Libuda, Jörg (2017)
EAM Import::2019-03-08

Pt–Ga Model SCALMS on Modified HOPG: Growth and Adsorption Properties - Hohner, Chantal; Kettner, Miroslav; Stumm, Corinna; Schuschke, Christian; Schwarz, Matthias; Libuda, Jörg (Topics in Catalysis, 2019)
Single atom catalysts hold a great potential in heterogeneous catalysis. In this model study, we report on the observation of Pt single atoms in low-melting-point Pt–Ga alloy prepared on modified highly oriented pyrolytic graphite (HOPG) under ultrahigh vacuum (UHV) conditions. In the first part, we examined the growth of Pt nanoparticles (NP) on HOPG modified by Ar+ bombardment. In the second part, we used physical vapor co-deposition of Pt and Ga to prepare model systems for supported catalytically active liquid metal solutions. We employed infrared reflection absorption spectroscopy with CO as a probe molecule and atomic force microscopy to study the growth and adsorption properties of Pt–Ga aggregates in comparison to Pt NPs. The presence of CO during Pt deposition leads to formation of ordered Pt particles mainly exposing terrace sites. On Pt–Ga nanoalloys, CO induces Pt segregation to the surface. In contrast, Ga deposition onto Pt in UHV or evaporation of small amounts of Pt onto Ga results in the formation of isolated Pt atoms on the surface of the alloy. Comparing alloys with different Pt concentrations, we show that the coordination environment around Pt influences the binding energy of the adsorbed CO.
CRIS-Team Scopus Importer:2019-10-25
Keywords: Atomic force microscopy (AFM); Gallium; Highly oriented pyrolytic graphite (HOPG); Infrared reflection absorption spectroscopy (IRAS); Platinum; Supported catalytically active liquid metal solutions (SCALMS)

Pt-Ga Model SCALMS on Modified HOPG: Thermal Behavior and Stability in UHV and under Near-Ambient Conditions - Hohner, Chantal; Kettner, Miroslav; Stumm, Corinna; Blaumeiser, Dominik; Wittkämper, Haiko; Grabau, Mathias; Schwarz, Matthias; Schuschke, Christian; Lykhach, Yaroslava; Papp, Christian; Steinrück, Hans-Peter; Libuda, Jörg (Journal of Physical Chemistry C, 2020)
We have prepared model systems for Pt-Ga supported catalytically active liquid metal solutions (SCALMS) by physical vapor deposition of Pt and Ga onto highly oriented pyrolytic graphite (HOPG). Prior to metal deposition, the HOPG support was modified by Ar+ bombardment. In this work, we focus on the stability of the Pt-Ga deposits toward agglomeration, which is a critical challenge in application. Specifically, we study the behavior of the model catalysts in ultrahigh vacuum (UHV) and under near ambient pressure (NAP) conditions at different temperatures. We use CO as a probe molecule to examine changes in the surface composition of the Pt-Ga deposits by in situ infrared reflection absorption spectroscopy (IRAS). In specific, we combine IRAS and ex situ atomic force microscopy (AFM) to study changes induced by annealing. We find that sintering effects are strongly dependent on the thickness of the deposited Pt-Ga layers. Our data suggest that particle ripening leads to a separation of the system into disperse Pt-rich and large Ga-rich particles. In the NAP regime, we performed simultaneous measurements with polarization modulation IRAS (PM-IRAS) and near ambient pressure X-ray photoelectron spectroscopy (NAP-XPS). The alloying of Pt and Ga is accompanied by a shift of Pt 4f and Ga 3d photoelectron lines to higher binding energies. Although partial oxidation of Ga is observed upon CO exposure at pressures in the millibar regime, PM-IRAS shows'adsorbed CO at a frequency typical for Pt ensembles in a Ga matrix.
CRIS-Team WoS Importer:2020-02-18

Pt Nanoclusters Sandwiched between Hexagonal Boron Nitride and Nanographene as van der Waals Heterostructures for Optoelectronics - Düll, Fabian; Freiberger, Eva Marie; Bachmann, Philipp; Steinhauer, Johann; Papp, Christian (ACS Applied Nano Materials, 2019)
We report on the formation of nanoscopic heterostructures composed of the semimetal graphene, the metal Pt, and the insulator hexagonal boron nitride (h-BN). Both graphene and h-BN are chemically inert two-dimensional materials with similar geometric but different electronic properties. Between these materials, a Pt nanoparticle array was encapsulated. Thereby, the h-BN/Rh(111) nanomesh served as a template for a well-ordered array of Pt nanoclusters, which were overgrown with graphene, forming single-crystal nanoheterostructures. We investigated this process in situ by high-resolution, synchrotron-radiation-based X-ray photoelectron spectroscopy and near-edge X-ray absorption fine structure. The nanographene layers proved tight against CO under the tested conditions. These nanoheterostructures could find possible application in optoelectronics or as a data storage material. At the same time, our approach represents a new route for the synthesis of nanographene.
CRIS-Team Scopus Importer:2019-11-22
Keywords: hexagonal boron nitride; nanographene; Pt nanoclusters

Pyridine on flat Pt(111) and stepped Pt(355) - An in situ HRXPS investigation of adsorption and thermal evolution - Steinrück, Hans-Peter; Welke, Martin; Eilert, Andre; Denecke, Reinhard; Schoeppke, Matthias; Wöckel, Claudia (Journal of Chemical Physics, 2016)
We investigated the adsorption and reaction of pyridine on flat Pt(111) and stepped Pt(355) surfaces via high-resolution in situ x-ray photoelectron spectroscopy. The surfaces were exposed to pyridine at temperatures between 112 and 300 K while simultaneously recording XP spectra. Subsequently, the crystals were annealed and the temperature dependencies of the N 1s and C 1s core levels were studied again in a continuous and quantitative way. Various surface species were found, namely, physisorbed, flat-lying and end-on pyridine, α-pyridyl species on the terraces and on the steps and several unidentified high temperature species. We were able to show an influence of the steps of Pt(355) by pre-adsorbing silver next to the step, which selectively suppresses the step adsorption.

Quantitative Analysis of the Oxidation State of Cobalt Oxides by Resonant Photoemission Spectroscopy - Lykhach, Yaroslava; Piccinin, Simone; Skála, Tomáš; Bertram, Manon; Tsud, Nataliya; Brummel, Olaf; Farnesi Camellone, Matteo; Beranová, Klára; Neitzel, Armin; Fabris, Stefano; Prince, Kevin C.; Matolín, Vladimír; et al. (Journal of Physical Chemistry Letters, 2019)
Quantitative assessment of the charge transfer phenomena in cobalt oxides and cobalt complexes is essential for the design of advanced catalytic materials. We propose a method for the evaluation of the oxidation state of cobalt oxides with mixed valence states using resonant photoemission spectroscopy. The method is based on the calculation of the resonant enhancement ratio (RER) from the heights of the resonant features associated with the Co3+ and Co2+ states. The nature of the corresponding states was corroborated by means of density functional calculations. We employed a well-ordered Co3O4(111) film to calibrate the RER with respect to the atomic Co3+/Co2+ ratio. The method was applied to monitor the reduction of a well-ordered Co3O4(111) film to CoO(111) upon annealing under exposure to isopropanol. We demonstrate that this method yields the stoichiometry of cobalt oxides at a level of accuracy that cannot be achieved when fitting the Co 2p core level spectra.
CRIS-Team Scopus Importer:2019-10-15

Quantitative calcium measurements in subcellular compartments of Plasmodium falciparum-infected erythrocytes - Rohrbach, Petra; Friedrich, Oliver; Hentschel, Joachim; Plattner, Helmut; Fink, Rainer; Lanzer, Michael (Journal of Biological Chemistry, 2005)
The acidic food vacuole exerts several important functions during intraerythrocytic development of the human malarial parasite Plasmodium falciparum. Hemoglobin taken up from the host erythrocyte is degraded in the food vacuole, and the heme liberated during this process is crystallized to inert hemozoin. Several antimalarial drugs target food vacuolar pathways, such as hemoglobin degradation and heme crystallization. Resistance and sensitization to some antimalarials is associated with mutations in food vacuolar membrane proteins. Other studies suggest a role of the food vacuole in ion homeostasis, and release of Ca from the food vacuole may mediate adopted physiological responses. To investigate whether the food vacuole is an intracellular Ca store, which in turn may affect other physiological functions in which this organelle partakes, we have investigated total and exchangeable Ca within the parasite's food vacuole using x-ray microanalysis and quantitative confocal live cell Ca imaging. Apparent free Ca concentrations of ∼90, ∼350, and ∼400 nM were found in the host erythrocyte cytosol, the parasite cytoplasm, and the food vacuole, respectively. In our efforts to determine free intracellular Ca concentrations, we evaluated several Ca-sensitive fluorochromes in a live cell confocal setting. We found that the ratiometric Ca indicator Fura-Red provides reliable determinations, whereas measurements using the frequently used Fluo-4 are compromised due to problems arising from phototoxicity, photobleaching, and the strong pH dependence of the dye. Our data suggest that the food vacuole contains only moderate amounts of Ca, disfavoring a role as a major intracellular Ca store. © 2005 by The American Society for Biochemistry and Molecular Biology, Inc.

QVibeplot: A Program To Visualize Molecular Vibrations in Two Dimensions - Laurin, Mathias (Journal of Chemical Education, 2013)
QVibeplot is a software program that automatically generates twodimensional visualizations of molecular vibrations. The representations show the changes of bond lengths, angles, and torsions occurring upon a vibration. This is consistent with the experimentalist's understanding of molecular vibrations that makes a distinction between stretching and deformation modes. Twodimensionality is achieved by basing the representation on a skeletal formula of the molecule. The program also displays the spectrum and the list of frequencies. The phase and amplitude are indicated as well, providing a comprehensive visualization of molecular vibrations. The software is available online as a free and open-source software.
EAM Import::2019-03-13

Reaction Kinetics on Complex Model Catalysts under Single Scattering Conditions - Libuda, Jörg; et al. (Journal of Physical Chemistry B, 2002)
To approach a microscopic understanding of the reaction kinetics on complex surfaces of heterogeneous catalysts, we combine multimolecular beam techniques and a supported model catalyst approach. The model systems are prepared under ultrahigh vacuum (UHV) conditions and have been characterized in detail with respect to their geometric and electronic structure. To probe the kinetics of catalytic reactions on these systems, we have developed a molecular beam instrument, which allows us to cross up to three beams on the sample surface. The simultaneous detection of reaction products and surface species is established by a combination of angle- and time-resolved gas-phase detection and in situ time-resolved IR reflection absorption spectroscopy. In this paper, we review a variety of representative experiments, illustrating the experimental possibilities of the molecular beam approach. As a model surface, we focus on alumina supported palladium particles. We cover the adsorption and desorption kinetics of small molecules and the kinetics of simple surface reactions on these systems. The reaction kinetics is probed via systematic steady state measurements, transient experiments, time-resolved in situ IR spectroscopy and measurements of the angular distribution of products. A central topic is the CO oxidation, a model reaction, which has been thoroughly investigated on a variety of single crystal surfaces. For the supported model catalysts, it is shown how structure and size dependencies can be identified by performing systematic kinetic measurements. These effects can be linked to the inherent heterogeneity of the model surfaces via microkinetic mean-field and Monte Carlo simulations. It is shown that the particular kinetic effects on the model catalyst surfaces can be understood by explicitly accounting for their inherent complexity. Finally, we outline possible future directions of the molecular beam approach applied to complex model surfaces.
UnivIS-Import:2015-03-09:Pub.2002.nat.dchph.ppc20.reacti

Reaction kinetics on model catalysts: Molecular beam methods and time-resolved vibrational spectroscopy - Libuda, Jörg (Surface Science, 2005)
Reaction kinetics on nanometer-scale particles are different from perfect single crystal surfaces. In heterogeneous catalysts this fact is empirically made use of in order to maximize the catalytic performance. Molecular beam experiments combined with vibrational spectroscopy on structurally well-defined model catalysts can provide detailed insight into the underlying reaction kinetics at the microscopic level. We critically review the recent developments, achievements and open questions of this approach. Scrutinizing simple test reactions, the application to various kinetic phenomena and their relevance for catalysis is discussed, including e.g., the role of the support and the identification of particle heterogeneities and specific reactive sites. It turns out that even for the simplest model catalysts, complex kinetic phenomena occur making the spectroscopic identification and monitoring of multiple coexisting reactant species one of the main challenges for future kinetic studies. © 2005 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2005.nat.dchph.ppc20.reacti
Keywords: Carbon monoxide; Heterogeneous catalysis; IR reflection absorption spectroscopy; Methanol; Molecular beams; Nitrogen oxide; Palladium; Supported catalysts

Reaction of Hydrogen and Oxygen on h-BN - Späth, Florian; Steinhauer, Johann; Düll, Fabian; Bauer, Udo; Bachmann, Philipp; Steinrück, Hans-Peter; Papp, Christian (Journal of Physical Chemistry C, 2020)
We report the reversible functionalization of hexagonal boron nitride (h-BN) on Ni(111) with a molecular oxygen species and atomic hydrogen, as studied by high-resolution X-ray photoelectron spectroscopy, ultraviolet photoelectron spectroscopy, and near-edge X-ray absorption fine structure. As a first step, we prepare oxygen-functionalized h-BN by exposure to a supersonic beam of molecular oxygen. Subsequent exposure to atomic hydrogen leads to complete removal of the oxygen species and the formation of hydrogen-functionalized h-BN. In turn, this hydrogen-functionalized h-BN can be reconverted to oxygen-functionalized h-BN by exposure to the supersonic oxygen beam. This reaction occurs at a lower rate as the initial functionalization of pristine h-BN with oxygen. We further demonstrate that the core levels and valence bands of h-BN can be shifted at will between the boundaries obtained for the purely oxygen- and hydrogen-functionalized h-BN layers.
CRIS-Team WoS Importer:2020-09-18

Reactions of a Polyhalide Ionic Liquid with Copper, Silver, and Gold - Lexow, Matthias; May, Benjamin; Taccardi, Nicola; Steinrück, Hans-Peter; Maier, Florian (ChemistryOpen, 2018)
Keywords: ionic liquids; corrosion; photoelectron spectroscopy; metal dissolution; surface analysis

Reactions of Superoxide with Iron Porphyrins in the Bulk and the Near-Surface Region of Ionic Liquids - Dees, Anne; Jux, Norbert; Tröppner, Oliver; Dürr, Katharina L.; Lippert, Rainer; Schmid, Martin; Kuestner, Bernd; Schluecker, Sebastian; Steinrück, Hans-Peter; Gottfried, J. Michael; Ivanovic-Burmazovic, Ivana (Inorganic Chemistry, 2015)
The redox reaction of superoxide (KO2) with highly charged iron porphyrins (Fe(P4+), Fe(P8+), and Fe(P8-)) has been investigated in the ionic liquids (IL) [EMIM] [Tf2N] (1-ethyl-3-methylimidazolium bis (trifluoromethylsulfonyl)imide) and [EMIM] [B(CN)(4)] (1-ethyl-3-methylimidazolium tetracyanoborate) by using time-resolved UV/vis stopped-flow, electrochemistry, cryospray mass spectrometry, EPR, and XPS measurements. Stable KO2 solutions in [EMIM] [Tf2N] can be prepared up to a IS mM concentration and are characterized by a signal in EPR spectrum at g = 2.0039 and by the 1215 cm(-1) stretching vibration in the resonance Raman spectrum While the negatively charged iron porphyrin Fe(P8-) does not react with superoxide in IL, Fe(P4+) and Fe(P8+) do react in a two-step process (first a reduction of the Fe(III) to the Fe(II) form, followed by the binding of superoxide to Fe(II)). In the reaction with KO2, Fe(P4+) and Fe(P8+) show similar rate constants (e.g., in the case of Fe(P4+): k(1) = 18.6 +/- 0.5 M-1 s(-1) for the first reaction step, and k(2) = 2.8 +/- 0.1 M-1 s(-1) for the second reaction step). Notably, these rate constants are four to five orders of magnitude lower in [EMIM] [Tf2N] than in conventional solvents such as DMSO. The influence of the ionic liquid is also apparent during electrochemical experiments, where the redox potentials for the corresponding Fe(III)/Fe(II) couples are much more negative in [EMIM] [Tf2N] than in DMSO. This modified redox and kinetic behavior of the positively charged iron porphyrins results from their interactions with the anions of the ionic liquid, while the nucleophilicity of the superoxide is reduced by its interactions with the cations of the ionic liquid. A negligible vapor pressure of [EMIM][B(CN)(4)] and a sufficient enrichment of Fe(P8+) in a close proximity to the surface enabled XPS measurements as a case study for monitoring direct changes in the electronic structure of the metal centers during redox processes in solution and at liquid/solid interfaces.

Reactivity and Passivation of Fe Nanoclusters on h-BN/Rh(111) - Waleska, Natalie; Düll, Fabian; Bachmann, Philipp; Hemauer, Felix; Steinhauer, Johann; Papp, Christian (Chemistry - A European Journal, 2021)
The reactivity of iron nanocluster arrays on h-BN/Rh(111) was studied using in situ high-resolution X-ray photoelectron spectroscopy. The morphology and reactivity of the iron nanoclusters (Fe-NCs) were investigated by CO adsorption. On-top and hollow/edge sites were determined to be the available adsorption sites on the as-prepared Fe-NCs and CO dissociation was observed at 300 K. C- and O-precovered Fe-NCs showed no catalytic activity towards CO dissociation because the hollow/edge sites were blocked by the C and O atoms. Therefore, these adsorption sites were identified to be the most active sites of the Fe-NCs.
CRIS-Team Scopus Importer:2021-09-10
Keywords: heterogeneous catalysis; iron; model catalysis; nanocluster array; XPS

Reactivity of atomically dispersed Pt2+ species towards H-2: model Pt-CeO2 fuel cell catalyst - Lykhach, Yaroslava; Figueroba, Alberto; Camellone, Matteo Farnesi; Neitzel, Armin; Skala, Tomas; Negreiros, Fabio R.; Vorokhta, Mykhailo; Tsud, Nataliya; Prince, Kevin C.; Fabris, Stefano; Neyman, Konstantin M.; Matolin, Vladimir; et al. (Physical Chemistry Chemical Physics, 2016)
The reactivity of atomically dispersed Pt2+ species on the surface of nanostructured CeO2 films and the mechanism of H-2 activation on these sites have been investigated by means of synchrotron radiation photoelectron spectroscopy and resonant photoemission spectroscopy in combination with density functional calculations. Isolated Pt2+ sites are found to be inactive towards H-2 dissociation due to high activation energy required for H-H bond scission. Trace amounts of metallic Pt are necessary to initiate H-2 dissociation on Pt-CeO2 films. H-2 dissociation triggers the reduction of Ce4+ cations which, in turn, is coupled with the reduction of Pt2+ species. The mechanism of Pt2+ reduction involves reverse oxygen spillover and formation of oxygen vacancies on Pt-CeO2 films. Our calculations suggest the existence of a threshold concentration of oxygen vacancies associated with the onset of Pt2+ reduction.

Reactivity of CO and C2H4 on Bimetallic PtxAg1-x/Pt(111) Surface Alloys Investigated by High-Resolution X-ray Photoelectron Spectroscopy - Bauer, Udo; Späth, Florian; Düll, Fabian; Bachmann, Phillip; Steinhauer, Johann; Steinrück, Hans-Peter; Papp, Christian (ChemPhysChem, 2018)
We have investigated the adsorption and thermal reactivity of CO and C2H4 on well-defined bimetallic PtxAg1-x/Pt(111) surface alloys (with x=0.67, 0.50, 0.38 and 0.32) using insitu synchrotron-based high-resolution X-ray photoelectron spectroscopy. During low-temperature (140K) adsorption of CO, we find population of the energetically more stable Pt on-top site followed by the Pt bridge site, as known from clean Pt(111); CO does not adsorb on Ag facets under the applied conditions. The total CO coverage linearly decreases with Ag surface content. Upon heating, COon-top and CObridge desorb at higher temperatures than on bare Pt(111), for example, by approximate to 65K for COon-top for an Ag content of 33%. This shift is due to the well-known electronic ligand-effect of Ag atoms surrounding Pt atoms/clusters. For C2H4 adsorption on the AgPt alloys at low temperature (120K), we find two species in the C1s XP spectrum, each displaying a vibrational fine structure; this contrasts the situation on clean Pt(111), where only one species is found. Upon heating, ethylene reacts with ethylidyne being the dominant intermediate; in contrast to clean Pt(111), on the alloy surfaces the reaction to CCH3 occurs at much lower temperatures, e.g. by approximate to 60K for the alloy with 68% Ag, and no ethylene desorption is found.
Keywords: carbon monoxide; ethylene; platinum; silver; X-ray photoelectron spectroscopy

Reactivity of CO on Sulfur-Passivated Graphene-Supported Palladium Nanocluster Arrays - Düll, Fabian; Späth, Florian; Bachmann, Philipp; Bauer, Udo; Steinrück, Hans-Peter; Papp, Christian (Journal of Physical Chemistry C, 2017)
Nanocluster arrays on graphene are suitable model systems for catalysis. We use this model system to study sulfur poisoning, which is a major deactivation process of heterogeneous catalysts. Using high-resolution X-ray photoelectron spectroscopy, we investigated the adsorption and desorption of CO on sulfur-poisoned graphene-supported palladium nanoparticles. We find that sulfur blocks CO adsorption sites, with hollow sites being most affected. From the unchanged desorption temperatures, we conclude that the Pd-CO bond strength is not altered by co-adsorbed sulfur. The degree of site blocking compared to the amount of sulfur indicates that the palladium nanoparticle surface is dominated by (111) and (100) facets.

Reactivity of CO on Sulfur-Passivated Graphene-Supported Platinum Nanocluster Arrays - Düll, Fabian; Späth, Florian; Bauer, Udo; Bachmann, Philipp; Steinhauer, Johann; Steinrück, Hans-Peter; Papp, Christian (Journal of Physical Chemistry C, 2018)

Reactivity of Graphene-Supported Pt Nanocluster Arrays - Gotterbarm, Karin; Späth, Florian; Bauer, Udo; Bronnbauer, Carina; Steinrück, Hans-Peter; Papp, Christian (ACS Catalysis, 2015)
Nanocluster arrays on graphene (Gr) are intriguing model systems for catalysis. We studied the adsorption and oxidation of CO on Pt/Gr/Rh(111) with synchrotron-based high-resolution X-ray photoelectron spectroscopy. On the nanoclusters, CO is found to adsorb at three different sites: namely, on-top, bridge, and step. The C 1s spectra exhibit remarkable similarities to those on the stepped Pt(355) surface. Similar to the case for stepped Pt surfaces, a clear preference for the adsorption on the step sites is found, while the preference for the adsorption on the on-top site over the bridge site on the terraces is much less pronounced in comparison to that on Pt single crystals. Temperature-programmed X-ray photoelectron spectroscopy revealed an enhanced binding energy for the cluster step sites, similar to the situation on stepped Pt surfaces. The oxidation of CO on graphene-supported Pt nanoclusters follows a pseudo-first-order rate law. Applying an Arrhenius analysis, we found an activation energy of 13 ± 4 kJ/mol, which is much smaller than that on Pt(111), due to the more reactive step and kink sites on the nanoclusters.

Reactivity of TiO2 Nanotube-Supported Platinum Particles in the CO Oxidation Reaction - Krick Calderon, Sandra; Grabau, Mathias; Yoo, Jeong Eun; Killian, Manuela; Schmuki, Patrik; Steinrück, Hans-Peter; Papp, Christian (ChemCatChem, 2017)
The CO oxidation on different platinum model catalysts, in particular differently sized Pt particles on vertically aligned TiO nanotubes (d=80, l=200nm) was investigated by near-ambient-pressure X-ray photoelectron spectroscopy and simultaneous online gas analysis. The results are compared to the behavior on a TiO(110) rutile crystal with a similar Pt coverage and a Pt(111) single crystal. Temperature-programmed reaction experiments at total pressures of 10 to 1.0mbar, and a CO/O ratio of 1:4 were performed to evaluate the reactivity of the samples. The onset temperature of the reaction on the Pt/TiO nanotube samples was found to be lower than on Pt(111) and Pt/TiO(110) and to decrease with decreasing particle size. For all particle samples, a steep increase in reaction rate at a defined temperature was observed, and at high temperatures the reaction became mass transfer-limited in all cases. Isothermal measurements showed that no CO is adsorbed on the particles when CO oxidation has a high activity and metallic platinum is the active catalyst. Ageing of the TiO-supported samples is observed resulting in changes of the reaction onset and CO conversion.
Keywords: Nanotubes; Oxidation; Platinum; Supported catalysts; X-ray absorption spectroscopy

Reactivity studies of ethylene, benzene and cyclohexane on carbide-modified Mo(110) using high resolution X-ray photoelectron spectroscopy - Bauer, Udo; Gleichweit, Christoph; Höfert, Oliver; Späth, Florian; Gotterbarm, Karin; Steinrück, Hans-Peter; Papp, Christian (Surface Science, 2018)
Keywords: Benzene; High-resolution X-ray photoelectron spectroscopy; Molybdenum; Ethylene; Heterogeneous catalysis; Transition metal carbides; Near edge X-ray absorption fine structure; Temperature programmed desorption

Recent developments in the study of ionic liquid interfaces using X-ray photoelectron spectroscopy and potential future directions - Steinrück, Hans-Peter (Physical Chemistry Chemical Physics, 2012)
A perspective is given on the potential of X-ray photoelectron spectroscopy to investigate ionic liquid (IL) interfaces and related bulk properties. To allow for cross-correlation of different IL properties, the study is restricted to imidazolium-based systems. By systematic variation of alkyl chain lengths, by investigation of different anions, and by introduction of functional groups detailed information on surface orientation, enrichment effects, cation-anion interactions, and the correlation to macroscopic properties such as density and surface tension of ILs are derived. Furthermore, the molecular arrangement and growth behaviour of ultrathin ionic liquid layers on various substrates, in situ monitoring of chemical reactions, and the dissolution of transition metal complexes are addressed. © 2012 the Owner Societies.

Redox Behavior of Pt/Co3O4(111) Model Electrocatalyst Studied by X-ray Photoelectron Spectroscopy Coupled with an Electrochemical Cell - Brummel, Olaf; Lykhach, Yaroslava; Vorokhta, Mykhailo; Smid, Bretislav; Stumm, Corinna; Faisal, Firas; Skala, Tomas; Tsud, Nataliya; Neitzel, Armin; Beranova, Klara; Prince, Kevin C.; Matolin, Vladimir; et al. (Journal of Physical Chemistry C, 2019)
Achieving high stability of supported noble metal nanoparticles with respect to sintering is one of the major challenges in electrocatalysis. In this study, we explored the role of metal-support interaction in stabilizing the morphology of a well-defined model electrode consisting of Pt nanoparticles supported on well-ordered Co 3 O 4 (111) films on Ir(100). We employed X-ray photoelectron spectroscopy coupled with an electrochemical cell to analyze changes in the oxidation states of both the supported Pt nanoparticles and Co 3 O 4 (111) support as a function of electrode potential. We found that immersion into the aqueous electrolyte at pH 10 (phosphate buffer) has no effect on the integrity and chemical composition of the Co 3 O 4 (111) film in a potential window between 0.5 and 1.4 V RHE . At lower potentials, reduction of the Co 3 O 4 (111) to Co(OH) 2 and metallic Co is accompanied by rapid dissolution of the film. In the presence of supported Pt particles, metal-support interaction gives rise to the formation of partially oxidized Pt δ+ species at the metal/oxide interface. Under electrochemical conditions, these species are readily oxidized yielding platinum oxide at the Pt/Co 3 O 4 (111) interface at potentials as low as 0.5 V RHE . The appearance of interfacial platinum oxide is accompanied by the formation of surface and bulk platinum oxides at potentials above 1.0 and 1.1 V RHE , respectively. While the formation and decomposition of surface and bulk platinum oxides depend on the electrode potential, the interface platinum oxide is stable between 0.5 and 1.4 V RHE . We propose that the high stability of supported Pt nanoparticles with respect to sintering is associated with the presence of platinum interface oxide stabilized by the metal-support interaction. ©
CRIS-Team Scopus Importer:2019-05-02

Redox chemistry, solubility, and surface distribution of Pt(II) and Pt(IV) complexes dissolved in ionic liquids - Kolbeck, Claudia; Taccardi, Nicola; Paape, Natalia; Schulz, Peter; Wasserscheid, Peter; Steinrück, Hans-Peter; Maier, Florian (Journal of Molecular Liquids, 2014)
An X-ray photoelectron spectroscopy (XPS) study of Pt(II) and Pt(IV) complexes dissolved in ionic liquids (ILs) revealed the occurrence of a rich redox chemistry, which is partly induced by X-ray radiation. Depending on the IL anion either a reduction of Pt(IV) to Pt(II) in the case of ethylsulfate ([EtOSO])-based ILs, or an oxidation of Pt(II) to Pt(IV) in the case of bis[(trifluoromethyl)sulfonyl]imide ([TfN] )-based ILs was observed upon X-ray irradiation. Moreover, surface enrichment or depletion effects of the Pt complexes were deduced from angle-resolved XPS (ARXPS) data; while the Pt complexes dissolved in imidazolium-based ILs tended to deplete from the surface, in pyrrolidinium-based solutions a surface enrichment of the Pt complexes was observed. © 2013 Elsevier B.V. All rights reserved.

Redox materials chemistry at the nanoscale - Lykhach, Yaroslava; Skala, Tomas; Tsud, Nataliya; Myslivecek, Josef; Prince, Kevin; Matolin, Vladimir; Libuda, Jörg (ABSTRACTS OF PAPERS OF THE AMERICAN CHEMICAL SOCIETY, 2019)
CRIS-Team WoS Importer:2019-08-23

Redox-mediated C-C bond scission in alcohols adsorbed on CeO2-xthin films - Lykhach, Yaroslava; Johánek, Viktor; Neitzel, Armin; Skála, Tomáš; Tsud, Nataliya; Beranová, Klára; Mysliveček, Josef; Brummel, Olaf; Libuda, Jörg (Journal of Physics: Condensed Matter, 2022)
The decomposition mechanisms of ethanol and ethylene glycol on well-ordered stoichiometric CeO2(111) and partially reduced CeO2-x(111) films were investigated by means of synchrotron radiation photoelectron spectroscopy, resonant photoemission spectroscopy, and temperature programmed desorption. Both alcohols partially deprotonate upon adsorption at 150 K and subsequent annealing yielding stable ethoxy and ethylenedioxy species. The C-C bond scission in both ethoxy and ethylenedioxy species on stoichiometric CeO2(111) involves formation of acetaldehyde-like intermediates and yields CO and CO2accompanied by desorption of acetaldehyde, H2O, and H2. This decomposition pathway leads to the formation of oxygen vacancies. In the presence of oxygen vacancies, C-O bond scission in ethoxy species yields C2H4. In contrast, C-C bond scission in ethylenedioxy species on the partially reduced CeO2-x(111) is favored with respect to C-O bond scission and yields methanol, formaldehyde, and CO accompanied by the desorption of H2O and H2. Still, scission of C-O bonds on both sides of the ethylenedioxy species yields minor amounts of accompanying C2H4and C2H2. C-O bond scission is coupled with a partial recovery of the lattice oxygen in competition with its removal in the form of water.
CRIS-Team Scopus Importer:2022-03-18
Keywords: alcohols; cerium oxide; C–C bond scission; C–O bond scission; ethanol; ethylene glycol; vacancies

Redox-mediated conversion of atomically dispersed platinum to sub-nanometer particles - Lykhach, Yaroslava; Figueroba, Alberto; Skala, Tomas; Duchon, Tomas; Tsud, Nataliya; Aulicka, Marie; Neitzel, Armin; Veltruska, Katerina; Prince, Kevin C.; Matolin, Vladimir; Neyman, Konstantin M.; Libuda, Jörg (Journal of Materials Chemistry A, 2017)
The stability and the conversion of atomically dispersed Pt2+ species to sub-nanometer Pt particles have been investigated as a function of the Sn concentration in Pt-CeO2 films by means of synchrotron radiation photoelectron spectroscopy, resonant photoemission spectroscopy, and angle-resolved X-ray photoelectron spectroscopy in combination with density functional calculations. The deposition of Sn onto the Pt-CeO2 films triggers the reduction of Ce4+ cations to Ce3+ yielding Sn2+ cations. Consecutively, the redox coupling between the Ce3+ and Pt2+ species triggers the reduction of Pt2+ species yielding sub-nanometer Pt particles. The onset of reduction of Pt2+ species is directly related to the concentration of Ce3+ centers which, in turn, is controlled by the concentration of Sn2+ cations in the Pt-CeO2 film. On average, the formation of 6Ce(3+) centers corresponding to the adsorption of 3Sn atoms gives rise to the reduction of one Pt2+ species. The analysis of the depth distribution of Sn atoms in the Pt-CeO2 films revealed preferential adsorption of Sn2+ at the surface followed by diffusion of Sn2+ ions into the bulk at higher Sn coverages. Density functional modeling suggested that the adsorption of three Sn atoms in the vicinity of the Pt2+ species results in a rearrangement of the local coordination accompanied by substantial destabilization of the Pt2+ species followed by its conversion to Pt-0 atoms. The formation of sub-nanometer Pt particles is coupled with re-oxidation of two Ce3+ centers per one Pt2+ species reduced. Annealing of the Pt-CeO2 films in the presence of metallic Sn also leads to the reduction of the Pt2+ species due to thermally triggered oxidation of metallic Sn residues followed by diffusion of Sn2+ into the bulk. Annealing of the Pt-CeO2 films to temperatures above 600 K results in a loss of Sn yielding sub-nanometer Pt particles supported on nearly stoichiometric and Sn-free CeO2 films.

Reduction of Pt2+ species in model Pt-CeO2 fuel cell catalysts upon reaction with methanol - Neitzel, Armin; Johanek, Viktor; Lykhach, Yaroslava; Skala, Tomas; Tsud, Nataliya; Vorokhta, Mykhailo; Matolin, Vladimir; Libuda, Jörg (Applied Surface Science, 2016)
The stability of atomically dispersed Pt2+ species on the surface of nanostructured CeO2 films during the reaction with methanol has been investigated by means of synchrotron radiation photoelectron spectroscopy and resonant photoemission spectroscopy. The isolated Pt2+ species were prepared at low Pt concentration in Pt-CeO2 film. Additionally, Pt2+ species coexisting with metallic Pt particles were prepared at high Pt concentration. We found that adsorption of methanol yields similar decomposition products regardless of Pt concentration in Pt-CeO2 films. A small number of oxygen vacancies formed during the methanol decomposition can be replenished in the Pt-CeO2 film with low Pt concentration by diffusion of oxygen from the bulk. In the presence of supported Pt particles, a higher number of oxygen vacancies leads to a partial reduction of the Pt2+ species. The isolated Pt2+ species are reduced under rather strongly reducing conditions only, i.e. during annealing under continuous exposure to methanol. Reduction of isolated Pt2+ species results in the formation of ultra-small Pt particles containing around 25 atoms per particle or less. Such ultra-small Pt particles demonstrate excellent stability against sintering during annealing of Pt-CeO2 film with low Pt concentration under reducing conditions. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: platinum; Ceria Model catalyst; Fuel cell; Methanol; Synchrotron radiation photoelectron spectroscopy; Resonant photoemission spectroscopy

Reduction of the ZnSe/GaAs(100) valence band offset by a Te interlayer - Gleim, Thomas; Heske, C.; Umbach, E.; Schumacher, C.; Faschinger, W.; Ammon, Christian; Probst, Marc; Steinrück, Hans-Peter (Applied Physics Letters, 2001)
For the heterovalent system ZnSe/GaAs(100), we have investigated the influence of a Te pretreatment of the substrate on the electronic structure of the interface by photoelectron spectroscopy. We have paid special attention to correctly determine the valence band maximum in a k-resolved fashion, including the use of photon energies which enable excitation at the Γ point. We find that the Te pretreatment leads to a decrease of the valence band discontinuity as large as 0.3 eV. From photoemission depth profiling we conclude that some Te atoms remain localized at the interface, thus causing the change of the valence band offset while others float on the ZnSe surface, probably acting as surfactants. © 2001 American Institute of Physics.

Reductive Functionalization of Graphenides With Nickel(II) Porphyrin Diazonium Compounds - Hou, Huilei; Dasler, Daniela; Hauke, Frank; Hirsch, Andreas (Physica Status Solidi-Rapid Research Letters, 2017)
Keywords: diazonium; graphene; hybrid materials; porphyrine; radicals

REELS measurements on a CdTe(1 0 0) surface - Dröge, H.; Fleszar, A.; Steinrück, Hans-Peter (Journal of Crystal Growth, 1998)
The (1 0 0) surface of CdTe has been studied by reflection electron energy loss spectroscopy (REELS). The sample was prepared in situ in our UHV system and shows a c (2×2) reconstruction. The angle resolved REELS measurements for primary energies between 30 and 100 eV show distinct losses between 2 and 15eV that are attributed to interband transitions, d-band transitions as well as surface and bulk plasmons. The experimental investigations are accompanied by ab initio calculations (LDA/RPA) for the bulk loss function -Im(1/ε) of CdTe. From these calculations the surface loss function -Im(1/(ε + 1)) is determined. The dominant loss feature at 8.7 eV in the experimental spectra is assigned to a surface plasmon. Its energetic position is ∼ 1 eV below the maximum of the calculated surface loss function and earlier measurements for the nonpolar CdTe(1 1 0) surface. This shift is attributed to the reconstruction of the CdTe(1 0 0) surface that leads to a reduced surface charge density. © 1998 Elsevier Science B.V. All rights reserved.

Regeneration of LOHC dehydrogenation catalysts: In-situ IR spectroscopy on single crystals, model catalysts, and real catalysts from UHV to near ambient pressure - Amende, Maximilian; Kaftan, Andre; Bachmann, Philipp; Brehmer, Richard; Preuster, Patrick; Koch, Marcus; Wasserscheid, Peter; Libuda, Jörg (Applied Surface Science, 2016)
The Liquid Organic Hydrogen Carrier (LOHC) concept offers an efficient route to store hydrogen using organic compounds that are reversibly hydrogenated and dehydrogenated. One important challenge towards application of the LOHC technology at a larger scale is to minimize degradation of Pt-based dehydrogenation catalysts during long-term operation. Herein, we investigate the regeneration of Pt/alumina catalysts poisoned by LOHC degradation. We combine ultrahigh vacuum (UHV) studies on Pt(111), investigations on well-defined Pt/AlO model catalysts, and near-ambient pressure (NAP) measurements on real core-shell Pt/AlO catalyst pellets. The catalysts were purposely poisoned by reaction with the LOHC perhydro-dibenzyltoluene (H18-MSH) and with dicyclohexylmethane (DCHM) as a simpler model compound. We focus on oxidative regeneration under conditions that may be applied in real dehydrogenation reactors. The degree of poisoning and regeneration under oxidative reaction conditions was quantified using CO as a probe molecule and measured by infrared reflection-absorption spectroscopy (IRAS) and diffuse reflectance Fourier transform IR spectroscopy (DRIFTS) for planar model systems and real catalysts, respectively. We find that regeneration strongly depends on the composition of the catalyst surface. While the clean surface of a poisoned Pt(111) single crystal is fully restored upon thermal treatment in oxygen up to 700 K, contaminated Pt/AlO model catalyst and core-shell pellet were only partially restored under the applied reaction conditions. Whereas partial regeneration on facet-like sites on supported catalysts is more facile than on Pt(111), carbonaceous deposits adsorbed at low-coordinated defect sites impede full regeneration of the Pt/AlO catalysts.
Keywords: Infrared spectroscopy; Liquid Organic Hydrogen Carrier; Materials gap; Model catalysis; Pressure gap; Real catalysis

Region-selective Deposition of Core–Shell Nanoparticles for 3 D Hierarchical Assemblies by the Huisgen 1,3-Dipolar Cycloaddition - Etschel, Sebastian; Portilla Berlanga, Luis; Kirschner, Johannes; Drost, Martin; Marbach, Hubertus; Tykwinski, Rik; Halik, Marcus (Angewandte Chemie International Edition, 2015)
A method for the region-selective deposition of nanoparticles (NPs) by the Huisgen 1,3-dipolar cycloaddition is presented. The approach enables defined stacking of various oxide NPs in any order with control over layer thickness. Thereby the reaction is performed between a substrate, functionalized with a self-assembled monolayer of an azide-bearing phosphonic acid (PA) and aluminum oxide (AlOx) NPs functionalized with an alkyne bearing PA. The layer of alkyne functionalized AlOx NPs is then used as substrate for the deposition of azide-functionalized indium tin oxide (ITO) NPs to provide a binary stack. This progression is then conducted with alkyne-functionalized CeO2 NPs, yielding a ternary stack of NPs with three different NP cores. The stacks are characterized by AFM and SEM, defining the region-selectivity of the deposition technique. Finally, these assemblies have been tested in devices as a dielectric to form a capacitor resulting in a dramatic increase in the measured capacitance.

Region-Selective Self-Assembly of Functionalized Carbon Allotropes from Solution - Wang, Zhenxing; Mohammadzadeh, Saeideh; Schmaltz, Thomas; Kirschner, Johannes; Khassanov, Artöm; Eigler, Siegfried; Mundloch, Udo; Backes, Claudia; Steinrück, Hans-Peter; Magerl, Andreas; Hauke, Frank; Hirsch, Andreas; et al. (Acs Nano, 2013)
Approaches for the selective self-assembly of functionalized carbon allotropes from solution are developed and validated for 0D-fullerenes, 1D-carbon nanotubes and 2D-graphene. By choosing the right molecular interaction of self-assembled monolayers (serving the surface) with the functionalization features of carbon materials, which provide the solubility but also serve the driving force for assembly, we demonstrate a region-selective and self-terminating assembly of the materials. Active layers of the carbon allotropes can be selectively deposited in the channel region of thin-film transistor (TFT) devices by this approach. As an example for a 0D system, molecules of C functionalized octadecylphosphonic acids are used to realize self-assembled monolayer field-effect transistors (SAMFETs) based on a selective molecular exchange reaction of stearic acid in the channel region. For noncovalently functionalized single-walled carbon nanotubes (SWCNTs) and graphene oxide (GO) flakes, the electrostatic Coulomb interactions between the functional groups of the carbon allotropes and the charged head groups of a SAM dielectric layer are utilized to implement the selective deposition. © 2013 American Chemical Societ

Removing photoemission features from Auger-yield NEXAFS spectra - Lytken, Ole; Wechsler, Daniel; Steinrück, Hans-Peter (Journal of Electron Spectroscopy and Related Phenomena, 2017)
Two-dimensional spectral images, as opposed to one-dimensional spectra, are crucial for both recognizing the presence and verifying the removal of photoemission features in Auger-yield NEXAFS. We present a procedure for removing such photoemission features, which relies on describing the measured Auger yield NEXAFS image as three simple, one-dimensional spectra: NEXAFS, Auger, and XPS. This allows for a very successful and fast removal of even extreme photoemission features, as illustrated by four examples. The procedure requires no additional reference measurements other than photon flux, and provides a significant amount of additional information, such as NEXAFS, Auger and XPS spectra and images, which can be used to verify the validity of the underlying assumptions and success of the cleanup process. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: X-ray absorption fine structure (XAFS); X-ray absorption near edge structure (XANES); Near edge X-ray absorption fine structure (NEXAFS); Photoemission removal; Photoemission correction; Image analysis

Reply to Choukroun et al.: IR and TPD data suggest the formation of clathrate hydrates in laboratory experiments simulating ISM - Ghosh, Jyotirmoy; Methikkalam, Rabin Rajan J.; Bhuin, Radha Gobinda; Ragupathy, Gopi; Choudhary, Nilesh; Kumar, Rajnish; Pradeep, Thalappil (Proceedings of the National Academy of Sciences of the United States of America, 2019)
CRIS-Team Scopus Importer:2019-07-23

Resonant excitation and decay of core holes in condensed layers of furan and pyrrole - Mauerer, M.; Zebisch, P.; Weinelt, Martin; Steinrück, Hans-Peter (Journal of Chemical Physics, 1993)
Near edge x-ray absorption spectra and decay electron spectra for resonant and nonresortant excitations in the C 1s and N 1s regions have been measured for condensed furan (CHO) and pyrrole (CH NH) layers. The decay spectra after resonant excitation into the lowest unoccupied orbital (π*) are pure autoionization spectra. The participant channels show strong resonant enhancements of the photoelectron peaks, in particular after excitation of the C 1s core electrons. Overall however, the spectra are dominated by the spectator channels. The spectator spectra resemble the normal Auger spectra shifted by spectator shifts of ≈4 eV for furan and ≈2.5 eV for pyrrole. For furan the participant spectra for excitation at the two different carbon atoms show significant differences that can be qualitatively understood in terms of a simple one-electron picture by considering the localization of the corresponding orbitals on the core hole. The decay spectra after excitation into the π* orbital show negligible enhancement of the participant channel, a strongly reduced spectator shift, and less-pronounced structures than at higher photon energies. The latter is attributed to a competition of spectator decay and normal Auger decay after internal photoionization into Rydberg derived bands in the condensate. For excitations into the σ*-resonances pure Auger spectra are observed, indicating that these resonances fully ionize before core decay takes place. © 1993 American Institute of Physics.

Resonant inelastic soft x-​ray scattering of Be chalcogenides - Fink, Rainer; Umbach, Eberhard; Hanke, W.; Heske, Clemens; et al. (Physical Review B, 2006)

Reversible and Efficient Light-Induced Molecular Switching on an Insulator Surface - Jaekel, Simon; Richter, Antje; Lindner, Robert; Bechstein, Ralf; Nacci, Christophe; Hecht, Stefan; Kühnle, Angelika; Grill, Leonhard (ACS nano, 2018)
Prototypical molecular switches such as azobenzenes exhibit two states, i.e., trans and cis, with different characteristic physical properties. In recent years various derivatives were investigated on metallic surfaces. However, bulk insulators as supporting substrate reveal important advantages since they allow electronic decoupling from the environment, which is key to control the switching properties. Here, we report on the light-induced isomerization of an azobenzene derivative on a bulk insulator surface, in this case calcite (10 (1) over bar4), studied by atomic force microscopy with submolecular resolution. Surprisingly, cis isomers appear on the surface already directly after preparation, indicating kinetic trapping. The photoisomerization process is reversible, as the use of different light sources results in specific molecular assemblies of each isomer. The process turns out to be very efficient and even comparable to molecules in solution, which we assign to the rather weak molecular interaction with the insulator surface, in contrast to metals.
Keywords: molecular switch; azobenzene; atomic force microscopy; bulk insulator; molecular assembly; photochemistry

Reversible Hydrogenation of Graphene on Ni(111)-Synthesis of ’Graphone’ - Zhao, Wei; Gebhardt, Julian; Späth, Florian; Gotterbarm, Karin; Gleichweit, Christoph; Steinrück, Hans-Peter; Görling, Andreas; Papp, Christian (Chemistry - A European Journal, 2015)
Understanding the adsorption and reaction between hydrogen and graphene is of fundamental importance for developing graphene-based concepts for hydrogen storage and for the chemical functionalization of graphene by hydrogenation. Recently, theoretical studies of single-sided hydrogenated graphene, so called graphone, predicted it to be a promising semiconductor for applications in graphene-based electronics. Here, we report on the synthesis of graphone bound to a Ni(111) surface. We investigate the formation process by X-ray photoelectron spectroscopy (XPS), temperature-programmed desorption (TPD), and density-functional theory calculations, showing that the hydrogenation of graphene with atomic hydrogen indeed leads to graphone, that is, a hydrogen coverage of 1ML (4.2 wt %). The dehydrogenation of graphone reveals complex desorption processes that are attributed to coverage-dependent changes in the activation energies for the associative desorption of hydrogen as molecular H2 .
Keywords: dehydrogenation; density functional calculations; graphene; graphone; hydrogenation; X-ray photoelectron spectroscopy

Reversible Photoswitching of a Spin‐Crossover Molecular Complex in the Solid State at Room Temperature - Rösner, Benedikt; Milek, Magdalena; Witt, Alexander; Gobaut, Benoit; Torelli, Piero; Fink, Rainer; Khusniyarov, Marat (Angewandte Chemie, 2015)
Spin‐crossover metal complexes are highly promising magnetic molecular switches for prospective molecule‐based devices. The spin‐crossover molecular photoswitches developed so far operate either at very low temperatures or in the liquid phase, which hinders practical applications. Herein, we present a molecular spin‐crossover iron(II) complex that can be switched between paramagnetic high‐spin and diamagnetic low‐spin states with light at room temperature in the solid state. The reversible photoswitching is induced by alternating irradiation with ultraviolet and visible light and proceeds at the molecular level.
Keywords: molecular switches; photochromism; photomagnetism; spin‐crossover; X‐ray absorption spectroscopy

Reversible thermally induced phase transition in ordered domains of Co(II)-5,10,15,20-tetrakis-(3,5-di-tert-butylphenyl)-porphyrin on Cu(111) - Steinrück, Hans-Peter; Stark, Michael Werner; Ditze, Stefanie; Thomann, Michael; Lungerich, Dominik; Jux, Norbert; Marbach, Hubertus (Surface Science, 2016)
We investigated the adsorption behavior of Co(II)-5,10,15,20-tetrakis-(3,5-di-tert-butylphenyl)-porphyrin (CoTTBPP) on Cu(111) by scanning tunneling microscopy (STM). At room temperature (RT), the coverage dependent adsorption behavior follows an expected scheme: at low coverage step decoration is found, which evolves into supramolecular domains with a hexagonal order at higher coverage. Interestingly, upon cooling the sample to 180 K the occurrence of a clearly distinguishable coexisting herringbone phase is observed. Upon heating to RT again, the herringbone phase vanishes. Thus a temperature dependent, fully reversible phase transition was observed. High resolution STM micrographs allow for the determination of the intramolecular conformations which are different for the two supramolecular arrangements. In addition, we studied the bias voltage dependent appearance of the molecule in STM and assigned a dominant contribution of the central Co at negative bias voltages close to the Fermi edge to the occupied d orbital. Interestingly, the herringbone phase, which dominates at 180 K, exhibits a significantly higher molecular density than the monomodal hexagonal arrangement at RT, which is in line with the "normal" behavior of freezing substances.
Keywords: Bias voltage dependence; Intramolecular conformation; Porphyrin; Reversible phase transition; Scanning tunneling microscopy; Self-assembly

Revisiting surface core-level shifts for ionic compounds - Bagus, Paul S.; Nelin, Connie J.; Zhao, Xunhua; Levchenko, Sergey; Davis, Earl; Weng, Xuefei; Späth, Florian; Papp, Christian; Kuhlenbeck, Helmut; Freund, Hans-Joachim (Physical Review B, 2019)
The shifts of core-level binding energies can provide powerful information about the electronic structure of a material. Understanding the physical origin of these shifts for catalytically relevant oxides may provide important insight into their properties. This requires reliable theoretical methods which are able to relate the binding energy shifts to the electronic structure. In order to establish such a methodology, the CaO(100) surface to bulk core-level binding energy shifts have been studied with Hartree-Fock and density-functional theory methods using both cluster and periodic slab models. The shifts obtained from the different theoretical methods are compared with each other and with data from synchrotron-based x-ray photoelectron spectroscopy (XPS) measurements. With a common approximation for the slab model treatment of XPS, the predicted binding energy shifts are seriously in error. The origin of the error is identified as arising from a flawed treatment of the surface atom binding energies, and a method for correcting the failure is presented.
CRIS-Team WoS Importer:2019-09-27

Robot-Based High-Throughput Engineering of Alcoholic Polymer: Fullerene Nanoparticle Inks for an Eco-Friendly Processing of Organic Solar Cells - Xie, Chen; Tang, Xiaofeng; Berlinghof, Marvin; Langner, Stefan; Chen, Shi; Späth, Andreas; Li, Ning; Fink, Rainer; Unruh, Tobias; Brabec, Christoph (ACS Applied Materials and Interfaces, 2018)
Development of high-quality organic nanoparticle inks is a significant scientific challenge for the industrial production of solution processed organic photovoltaics (OPVs) with eco-friendly processing methods. In this work, we demonstrate a novel, robot-based, high throughput procedure performing automatic poly(3-hexylthio-phene-2,5-diyl) and indene-C-60 bisadduct nanoparticle ink synthesis in nontoxic alcohols. A novel methodology to prepare particle dispersions for fully functional OPVs by manipulating the particle size and solvent system was studied in detail. The ethanol dispersion with a particle diameter of around 80-100 nm exhibits reduced degradation, yielding a power conversion efficiency of 4.52%, which is the highest performance reported so far for water/alcohol-processed OPV devices. By successfully deploying the high-throughput robot-based approach for an organic nanoparticle ink preparation, we believe that the findings demonstrated in this work will trigger more research interest and effort on eco-friendly industrial production of OPVs.
Keywords: organic photovoltaics; eco-friendly industrial production; robot-based systems; high-throughput organic nanoparticle synthesis; stable organic nanoparticle inks; organic nanoparticle size control

Role of Fiber Thickness and Surface Treatment of Electrospun Polycaprolactone Matrices on the Growth of Different Breast Cancer‐Associated Cells - Sivakumar, Sankaranarayanan; Schmid, Rafael; Wieland, Annalena; Strissel, Pamela; Strick, Reiner; Fischer, Lena; Thievessen, Ingo; Kataev, Elmar; Arkudas, Andreas; Horch, Raymund E.; Schubert, Dirk W.; Kengelbach-Weigand, Annika (Advanced Materials Interfaces, 2022)
Cancer models mimicking the tumor microenvironment are necessary to successfully develop and predict responses of oncological drugs. In this study, electrospun polycaprolactone (PCL) matrices are tested for the development of an in vitro breast cancer model. The effects of fiber thickness and plasma-treatment of the matrices on in vitro growth of breast cancer-associated cells, namely breast cancer cells MDA-MB-231, primary adipose-derived stem cells (ADSCs) and primary endothelial progenitor cells (EPCs) are evaluated. Surface treatment of the matrices by air-plasma leads to increased oxygen/carbon ratio and hydrophilicity. WST-8 analysis reveals that the proliferation of all three cell types increased exponentially over 12 d on all matrices. MDA-MB-231 and ADSC show a higher proliferation on nanofibers due to enhanced cellular adhesion compared to microfibers. In contrast, EPCs show a significantly higher proliferation on microfibers than on nanofibers at day 12 which can further be significantly improved by air-plasma treatment. Cross-sectioning analysis shows that cells grow on the surface of nanofibers, while microfibers have considerable cellular infiltration. These findings suggest that the electrospun PCL matrices are a suitable tool for the development of breast cancer models containing several cell types, which can ultimately lead to designing novel tumor therapies.<br

Role of Oxygen in Acetic Acid Decomposition on Pt(111) - Neitzel, Armin; Lykhach, Yaroslava; Johanek, Viktor; Tsud, Nataliya; Skala, Tomas; Prince, Kevin C.; Matolin, Vladimir; Libuda, Jörg (Journal of Physical Chemistry C, 2014)
We have investigated the role of coadsorbed atomic oxygen during the decomposition of acetic acid on Pt(111) by means of temperature-programmed desorption (TPD) and synchrotron radiation photoelectron spectroscopy (SRPES). Reaction mechanisms have been established through identification of desorbing products and surface species formed during decomposition of acetic acid, both on Pt(111) and oxygen pre-exposed p(2 X 2)-O/Pt(111). Acetate and molecularly adsorbed acetic acid are formed on both samples during the adsorption of acetic acid at 150 K. On p(2 X 2)-O/Pt(111), however, surface acetyl is identified as the principal species. The major decomposition channel for acetate and acetic acid involves formation of ketene and acetaldehyde at 222 K, and this reaction is not affected by coadsorbed oxygen. In the following reactions, partial decomposition of acetaldehyde yielded ethylene, ethylidene, ethylidyne, and small amounts of CO and methoxy on both samples. Above 222 K, decomposition of acetate on Pt(111) yields acetic acid, hydrogen, methane, and CO. In contrast, the species desorbing from p(2 X 2)-O/Pt(111) are the products of acetyl decomposition. In particular, the reaction of acetyl with atomic oxygen and surface hydroxyl groups yields methanol and acetic anhydride at 300 and 450 K, and methane and CO2 at 390 K. Decomposition of acetic acid on both Pt(111) and p(2 x 2)-O/Pt(111) results in surface carbon from decomposition of ethylidyne and partial C-C bond cleavage in the acetyl species.

Role of Specific Intermolecular Interactions for the Arrangement of Ni(II)-5, 10, 15, 20-Tetraphenyltetrabenzoporphyrin on Cu(111) - Lepper, Michael; Zhang, Liang; Stark, Michael Werner; Ditze, Stefanie; Lungerich, Dominik; Jux, Norbert; Hieringer, Wolfgang; Steinrück, Hans-Peter; Marbach, Hubertus (Journal of Physical Chemistry C, 2015)
We have studied the coverage-dependent adsorption behavior of Ni(II)-5,10,15,20-tetraphenyltetra-benzoporphyrin on Cu(111) by scanning tunneling microscopy (STM) at room temperature. At medium coverages, the molecules self-assemble into two-dimensional islands, due to mutual stabilization through intermolecular interactions. Altogether, three different supramolecular arrangements coexist at low-to-medium coverages. On the basis of high-resolution STM images and density functional theory calculations, models for the three arrangements and the corresponding intramolecular conformations of the individual molecules are proposed. The observed polymorphism is attributed to a complex interplay of specific T-type and pi-pi stacking interactions between the phenyl groups. For Ni(II)-meso-tetrakis (4-tert-butylphenyl) benzoporphyrin, in which the aromatic periphery is modified by the attachment of tert-butyl groups, only one supramolecular arrangement on Cu(111) is found. This difference highlights the fact that the choice of peripheral ligands of the porphyrin derivatives plays an important role in the fabrication and tailoring of functional molecular architectures.

Sauerstoffspeicherung an der Metall-Oxid-Grenzfläche von Katalysatornanopartikeln - Libuda, Jörg; et al. (Angewandte Chemie, 2005)
UnivIS-Import:2015-03-09:Pub.2005.nat.dchph.ppc20.sauers

Seeing structural evolution of organic molecular nano-crystallites using 4D scanning confocal electron diffraction (4D-SCED) - Wu, Mingjian; Harreiß, Christina; Ophus, Colin; Johnson, Manuel; Fink, Rainer; Spiecker, Erdmann (Nature Communications, 2022)
Direct observation of organic molecular nanocrystals and their evolution using electron microscopy is extremely challenging, due to their radiation sensitivity and complex structure. Here, we introduce 4D-scanning confocal electron diffraction (4D-SCED), which enables direct in situ observation of bulk heterojunction (BHJ) thin films. 4D-SCED combines confocal electron optic setup with a pixelated detector to record focused spot-like diffraction patterns with high angular resolution, using an order of magnitude lower dose than previous methods. We apply it to study an active layer in organic solar cells, namely DRCN5T:PC71BM BHJ thin films. Structural details of DRCN5T nano-crystallites oriented both in- and out-of-plane are imaged at 5 nm resolution and dose budget of 5 e−/Å2. We use in situ annealing to observe the growth of the donor crystals, evolution of the crystal orientation, and progressive enrichment of PC71BM at interfaces. This highly dose-efficient method opens more possibilities for studying beam sensitive soft materials.<br
Keywords: Organic molecules in materials science; Self-assembly; Solar cells; Transmission electron microscopy

Segregation effects and chemical properties of nickel monolayers on Cu(1 1 1) - Domnick, Ralph; Held, Georg; Koschel, Herbert; Ammon, Christian; Steinrück, Hans-Peter (Surface Science, 2001)
Temperature-dependent structural changes of Ni monolayers on Cu(111) and the adsorption of benzene on these layers were investigated using photoelectron spectroscopy (XPS) and low energy electron diffraction (LEED). Ni films evaporated at 120 K show a sharp (1 x 1) LEED pattern after annealing to 300 K. Further annealing to 600 K leads to the segregation of Cu atoms on top of the Ni film. This is seen from the appearance of a surface core level shift in the Cu 2p XPS signal. The Ni2p signal does not show any shifts in this temperature range; only annealing to 800 K leads to a change in the Ni 2p peak energy which indicates the formation of a Cu-Ni bulk alloy. Adsorption of benzene on the Ni-adlayer (annealed to 300 K) causes a small peak shift in the Ni 2p signal. The C 1s signal indicates molecularly chemisorbed benzene up to 300 K. Further annealing to 500 K leads to the decomposition of benzene into hydrogen and carbon which remains on the surface and forms a stable bond with the Ni-adlayer, preventing Cu segregation up to 500 K. © 2001 Elsevier Science B.V. All rights reserved.

Selective Oxygen and Hydrogen Functionalization of the h-BN/Rh(111) Nanomesh - Freiberger, Eva Marie; Späth, Florian; Bauer, Udo; Düll, Fabian; Bachmann, Philipp; Steinhauer, Johann; Hemauer, Felix; Waleska, Natalie; Schwaab, Valentin; Steinrück, Hans-Peter; Papp, Christian (Chemistry - A European Journal, 2021)
We present detailed studies on the covalent adsorption of molecular oxygen and atomic hydrogen on the hexagonal boron nitride (h-BN) nanomesh on Rh(111). The functionalization of this two-dimensional (2D) material was investigated under ultra-high vacuum conditions using synchrotron radiation-based in situ high-resolution X-ray photoelectron spectroscopy, temperature-programmed X-ray photoelectron spectroscopy and ultraviolet photoelectron spectroscopy. We are able to provide a deep insight into the adsorption behavior and thermal stability of oxygen and hydrogen on h-BN/Rh(111). Oxygen functionalization was achieved via a supersonic molecular beam while hydrogen functionalization was realized using an atomic hydrogen source. Adsorption of the respective species was observed to occur selectively in the pores of h-BN leading to spatially defined modification of the 2D layer. The adsorption of the observed molecular oxygen species was found to be an activated process that requires high-energy oxygen molecules. Upon heating to 700 K, oxygen functionalization was observed to be almost reversible except for small amounts of boron oxides evolving due to the reaction of oxygen with the 2D material. Hydrogen functionalization of h-BN/Rh(111) was fully reversed upon heating to about 640 K.
CRIS-Team WoS Importer:2021-08-20

Self-Assembled 2D-Coordination Kagome, Quadratic, and Close-Packed Hexagonal Lattices Formed from a Cyano-Functionalized Benzoporphyrin on Cu(111) - Adhikari, Rajan; Kuliga, Jan; Ruppel, Michael; Jux, Norbert; Marbach, Hubertus; Steinrück, Hans-Peter (Journal of Physical Chemistry C, 2021)
We investigated the adsorption of 2H-5,10,15,20-Tetracyanophenyl-Tetrabenzoporphyrin (2H-TCNPTBP) molecules on Cu(111) by scanning tunneling microscopy in ultrahigh vacuum at room temperature. Three types of network structures are observed to coexist on the surface. The first two, a porous Kagome lattice and a porous quadratic structure, are stabilized by cyano-Cu-cyano bonds with Cu adatoms; the third is a close-packed hexagonal network, with much weaker intermolecular H-bonds and dipole-dipole interactions of oppositely oriented cyano end groups. The coexistence of the three structures is attributed to very similar energetics. While the two metal-coordinated porous structures with identical molecular density are stabilized by the energy gain due to the network formation, the hexagonal network compensates the weaker intermolecular interactions by a factor of 2.3 higher molecular density; furthermore, kinetic stabilization might play a role. Our results show that cyano functionalization of benzoporphyrins gives rise to unusual two-dimensional self-Assembled lattice structures.
CRIS-Team Scopus Importer:2021-05-14

Self-assembly and coverage dependent thermally induced conformational changes of Ni(II)-meso-tetrakis (4-tert-butylphenyl) benzoporphyrin on Cu(111) - Zhang, Liang; Lepper, Michael; Stark, Michael Werner; Lungerich, Dominik; Jux, Norbert; Hieringer, Wolfgang; Steinrück, Hans-Peter; Marbach, Hubertus (Physical Chemistry Chemical Physics, 2015)
A systematic scanning tunnelling microscopy investigation of the self-assembly and of thermally induced conformational changes of Ni(II)-meso-tetrakis (4-tert-butylphenyl) benzoporphyrin (Ni-TTBPBP) on Cu(111) is presented. At room temperature, Ni-TTBPBPs diffuse on the surface and self-assemble into ordered islands with well-defined registry to the substrate, with two different azimuthal orientations. The formation of the characteristic supramolecular structure is attributed to van der Waals interactions between the tert-butyl groups. Upon moderate heating, the intramolecular conformation changes irreversibly due to a dehydrogenative intramolecular aryl-aryl coupling reaction. This reaction is coverage dependent, with a lower rate at higher initial coverage; this behaviour is attributed to a stabilization of Ni-TTBPBP in the ordered islands at higher coverage.

Self-metalation of monophosphonic acid tetraphenylporphyrin on TiO2(110)-(1×1) - Fernández, Cynthia C.; Wechsler, Daniel; Lytken, Ole; Steinrück, Hans-Peter; Williams, Federico J. (Surface Science, 2022)
Fundamental studies on the interaction of porphyrin molecules with oxide surfaces are important due to the relevance of these systems in emerging technologies. In this work, we used X-ray photoelectron spectroscopy (XPS) to study the interaction of solution-deposited monophosphonic acid tetraphenylporphyrin (MPTPP) molecules with well-defined rutile TiO2(110)-(1×1) surfaces as a function of coverage and temperature. We found that molecules adsorb mainly in their free-base form with some molecules protonating on the surface at room temperature. In agreement with the behavior of carboxylic acid functionalized porphyrin molecules, raising the temperature results in porphyrin self-metalation and the temperature onset for self-metalation shifts to higher values as the coverage is increased. Furthermore, we found that self-metalation is accompanied by surface reduction, and we propose a mechanism based on the formation of oxygen vacancies driven by water desorption. Our findings contribute towards the understanding of the rich surface chemistry that porphyrin molecules have on oxide surfaces.
CRIS-Team Scopus Importer:2021-12-24
Keywords: Porphyrin molecules; Self-metalation; TiO

Sensitivity of CO oxidation toward metal oxidation state in ceria-supported catalysts: an operando DRIFTS-MS study - Kaftan, Andre; Kollhoff, Fabian; Thanh-Son Nguyen,; Piccolo, Laurent; Laurina, Mathias; Libuda, Jörg (Catalysis: Science and Technology, 2016)
The oxidation of carbon monoxide has been studied on pristine CeO2, Rh-CeO2, and Pt-CeO2 powders prepared in one step by solution combustion synthesis (SCS). The reaction was cycled between an oxygenrich and a CO-rich feed with regard to the stoichiometric conditions. CO2 production was monitored by mass spectrometry, while the surface species were probed by operando DRIFTS (Diffuse Reflectance Infrared Fourier Transform Spectroscopy). Whereas the reaction starts above 150 degrees C on CeO2 and Rh-CeO2 and does not depend on the state of the surface (oxidized or reduced), the reaction on Pt-CeO2 shows strong dependency on the initial state and substantial activity is achieved at much lower temperatures with the CO-rich feed. We relate this result to the change in the oxidation state of Pt via strong interaction with ceria.

Single Scattering Reaction Kinetics on Complex Model Catalysts - Libuda, Jörg; et al. (Journal of Physical Chemistry B, 2002)
UnivIS-Import:2015-03-09:Pub.2002.nat.dchph.ppc20.single

Site blocking and CO/sulfur site exchange processes on stepped Pt surfaces - Streber, Regine; Papp, Christian; Lorenz, Michael Peter Andreas; Bayer, Andreas; Wickert, Sandra; Schöppke, Matthias; Denecke, Reinhard; Steinrück, Hans-Peter (Journal of Physics: Condensed Matter, 2009)
The influence of preadsorbed sulfur on the adsorption of CO on Pt(355) and Pt(322) is investigated systematically for sulfur precoverages between 0.02 and 0.30ML by insitu x-ray photoelectron spectroscopy of the C 1s and S 2p core levels. The two surfaces have the same nominal terrace width of 5 atomic rows, but different step orientation. For both, at low temperatures (130 and 150K), S preferentially adsorbs at the steps and passivates them for COadsorption. The required S precoverage is significantly smaller for Pt(322), because of the lower number of steps as a result of the S-induced double-step formation. Upon heating, population of step sites with CO occurs due to irreversible CO/S site exchange. At low S precoverages, the characteristic transition temperatures of 165K for Pt(355) and 245K for Pt(322) are significantly different, indicating a higher activation barrier for the CO/S site exchange process for Pt(322). For medium to high S precoverages the transition temperature stays unchanged for Pt(322) but increases for Pt(355). The observed behavior is attributed to a kinetic passivation of the steps by sulfur at low temperatures, which is lifted upon heating. © 2009 IOP Publishing Lt

Site Occupation and Activity of Catalyst Nanoparticles Monitored by In Situ Vibrational Spectroscopy - Libuda, Jörg; et al. (Angewandte Chemie International Edition, 2003)
On the edge? The distribution of reactants and products over regular and edge sites of well-shaped palladium nanocrystallites is monitored during catalytic NO decomposition by using a combination of molecular beam techniques and in situ vibrational spectroscopy (see scheme, TR-IRAS = time-resolved IR reflection absorption spectroscopy, QMS = quadrupole mass spectrometer). Atomic nitrogen and oxygen species preferentially occupy edge sites on the catalyst particles. The presence of these co-adsorbates controls the NO dissociation activity.
UnivIS-Import:2015-03-09:Pub.2003.nat.dchph.ppc20.siteoc
Keywords: Heterogeneous catalysis; Kinetics; Nitrogen oxide; Supported catalysts; Surface chemistry

Site selectivity of benzene adsorption on Ni(111) studied by high-resolution x-ray photoelectron spectroscopy - Papp, Christian; Fuhrmann, Thomas; Tränkenschuh, Barbara; Denecke, Reinhard; Steinrück, Hans-Peter (Physical Review B, 2006)
The adsorption and thermal evolution of deuterated and nondeuterated benzene on Ni(111) has been studied by in situ high-resolution x-ray photoelectron spectroscopy. The recorded C 1s spectra show vibrational fine structure due to vibrational excitations of the C-H bonds in the ionic final state. Furthermore, different adsorption sites can be identified, since carbon atoms within the same molecule, but with different positions relative to the substrate have different C 1s binding energies. At 200 K for both C6 H6 and C6 D6 a well ordered (7×7) R19.1°superstructure is observed at saturation of the chemisorbed layer, with a nominal coverage of 0.143 ML. From a quantitative analysis of the XP spectra collected during adsorption one finds that up to a coverage of 0.10 ML benzene occupies only bridge adsorption sites. At higher coverage, a change to hcp hollow sites, accompanied by a rotation of the molecules by 30°, occurs for C6 H6 and C6 D6. In contrast to these results, an isotopic effect is found for adsorption at 125 K. While the adsorption behavior for C6 D6 is similar as at 200 K, for C6 H6 no change in adsorption site is observed, i.e., up to saturation of the chemisorbed layer bridge sites are occupied. Only upon heating, a site change from bridge to hcp hollow of the adsorbed C6 H6 is induced, starting around 180 K. A simple explanation for the observed behavior is proposed. © 2006 The American Physical Society.

Size and structure effects controlling the stability of the liquid organic hydrogen carrier dodecahydro- N -ethylcarbazole during dehydrogenation over pt model catalysts - Amende, Maximilian; Gleichweit, Christoph; Schernich, Stefan; Höfert, Oliver; Lorenz, Michael Peter Andreas; Zhao, Wei; Koch, Marcus; Obesser, Katharina; Papp, Christian; Wasserscheid, Peter; Steinrück, Hans-Peter; Libuda, Jörg (Journal of Physical Chemistry Letters, 2014)
Hydrogen can be stored conveniently using so-called liquid organic hydrogen carriers (LOHCs), for example, N-ethylcarbazole (NEC), which can be reversibly hydrogenated to dodecahydro-N-ethylcarbazole (H-NEC). In this study, we focus on the dealkylation of H-NEC, an undesired side reaction, which competes with dehydrogenation. The structural sensivity of dealkylation was studied by high-resolution X-ray photoelectron spectroscopy (HR-XPS) on AlO-supported Pt model catalysts and Pt(111) single crystals. We show that the morphology of the Pt deposit strongly influences LOHC degradation via C-N bond breakage. On smaller, defect-rich Pt particles, the onset of dealkylation is shifted by 90 K to lower temperatures as compared to large, well-shaped particles and well-ordered Pt(111). We attribute these effects to a reduced activation barrier for C-N bond breakage at low-coordinated Pt sites, which are abundant on small Pt aggregates but are rare on large particles and single crystal surfaces. © 2014 American Chemical Society.

Size-Dependent Oxidation Mechanism of Supported Pd Nanoparticles - Libuda, Jörg; et al. (Angewandte Chemie International Edition, 2006)
The oxidation and reduction of Fe3O4-supported Pd nanoparticles is strongly size-dependent and implies that the oxidation mechanism is controlled by the metal oxide interface. Molecular beam experiments and scanning tunneling microscopy indicate that this size dependence gives rise to a pronounced maximum of the oxygen-storage capacity as a function of metal loading. (Graph Presented) © 2006 Wiley-VCH Verlag GmbH & Co. KGaA.
UnivIS-Import:2015-03-09:Pub.2006.nat.dchph.ppc20.sizede
Keywords: Heterogeneous catalysis; Nanoparticles; Oxidation; Palladium; Surface chemistry

SO2 adsorption and thermal evolution on clean and oxygen precovered Pt(111) - Streber, Regine; Papp, Christian; Lorenz, Michael Peter Andreas; Höfert, Oliver; Darlatt, Erik; Bayer, Andreas; Denecke, Reinhard; Steinrück, Hans-Peter (Chemical Physics Letters, 2010)
We studied the adsorption and reaction of sulfur dioxide on clean and oxygen precovered platinum surfaces by in situ high resolution X-ray photoelectron spectroscopy and discuss earlier, contradicting results. On the clean surface we find flat lying and upright standing SO, adsorbing in similar amounts at low temperature. Upon heating, the ratio changes strongly favoring the standing SO; subsequently almost all SO desorbs. On the oxygen precovered surface the standing SO is preferably populated and even at low temperatures a direct reaction of SO to SO occurs. Upon heating, SO oxidation to SO and subsequently to SO is found. © 2010 Elsevier B.V. All rights reserve

SO2 adsorption on Pt(111) and oxygen precovered Pt(111): A combined infrared reflection absorption spectroscopy and density functional study - Happel, Markus; Luckas, Nicola; Vines Solana, Francesc; Sobota, Marek; Laurin, Mathias; Görling, Andreas; Libuda, Jörg (Journal of Physical Chemistry C, 2011)
We have performed a combined molecular beam (MB)/infrared reflection absorption spectroscopy (IRAS) and density functional (DF) study on the adsorption of sulfur dioxide (SO) on clean and oxygen precovered Pt(111). The adsorbate species formed as a function of coverage and their structural and chemical transformations upon subsequent annealing were followed systematically by IRAS. It is shown that, upon adsorption on clean Pt(111) at 100 K, SO adsorbs molecularly in two geometries. Calculations reveal that these geometries correspond to molecules oriented parallel or perpendicular to the surface. Upon heating up to 250 K, conversion between the two species occurs with the fraction of upright standing SO increasing with increasing temperature. Between 300 and 350 K, all surface species desorb without decomposition. This is in sharp contrast to oxygen precovered Pt(111), on which, in addition to the formation of molecular SO in flat and perpendicular geometry, partial formation of SO is observed even at low temperature. Upon annealing, part of the surface SO species are converted to SO and, subsequently, to SO, which remains stable up to 450 K. DF calculations on the stable adsorption structures of SO species provide characteristic IR frequencies, which can be correlated with the present IRAS data and photoelectron spectroscopy (PES) data previously published. © 2010 American Chemical Society.

SO2 Decomposition on Pt/CeO2(111) Model Catalysts: On the Reaction Mechanism and the Influence of H-2 and CO - Happel, Markus; Lykhach, Yaroslava; Tsud, Nataliya; Skala, Tomas; Johanek, Viktor; Prince, Kevin C.; Matolin, Vladimir; Libuda, Jörg (Journal of Physical Chemistry C, 2012)
We have performed a synchrotron radiation photoelectron spectroscopy (SR-PES) study on the mechanism of SO2 decomposition on Pt/CeO2(111) model catalysts prepared on Cu(111). Resonant photoemission spectroscopy (RPES) was applied to monitor changes of the cerium oxidation state. Adsorption of SO2 at 150 K on Pt/CeO2(111)/Cu(111) yields surface sulfites (SO32-) on ceria and upright standing molecular SO2 (SO2st) on Pt along with traces of atomic sulfur. Partial decomposition and desorption of the adsorbed species in the form of SO2 occur between 150 and 300 K. In this temperature region, slow accumulation of atomic sulfur is accompanied by reduction of the ceria support. Above 300 K, all surface species completely transform into atomic sulfur; this process is accompanied by a strong reoxidation of ceria. As probed by CO adsorption, the majority of the atomic sulfur species is located on the surface of the Pt particles. Possible reaction mechanisms involving spillover of numerous sulfur-derived species are considered. Finally, reverse spillover of the sulfur from Pt to the ceria support and formation of a cerium oxysulfide phase occurs above 550 K. The spillover of atomic sulfur is readily promoted under reducing conditions, e.g., in the presence of coadsorbed hydrogen or CO.

Soft X-ray induced damage in PVA-based membranes in water environment monitored by X-ray absorption spectroscopy - Tzvetkov, George; Späth, Andreas; Fink, Rainer (Radiation Physics and Chemistry, 2014)
The effect of synchrotron X-ray flux in a soft X-ray scanning-transmission microspectroscope (STXM) instrument on the chemical structure of air-filled poly(vinyl alcohol) (PVA) based microbubbles and their stabilizing shell has been examined. Prolonged soft X-ray illumination of the particles in aqueous suspension leads to the breaking of the microbubbles[U+05F3] protective polymer shell and substantial chemical changes. The latter were clarified via a micro-spot C K-edge near-edge X-ray absorption fine structure (NEXAFS) spectroscopy with further respect to the absorbed X-ray doses. Our results revealed a continuous degradation of the PVA network associated with formation of carbonyl- and carboxyl-containing species as well as an increased content of unsaturated bonds. The observed effects must be taken into account in studies of micro- and nanostructured polymer materials utilizing X-rays. © 2014.

Soft x-ray microscopy with 7 nm resolution - Roesner, Benedikt; Finizio, Simone; Koch, Frieder; Doring, Florian; Guzenko, Vitaliy A.; Langer, Manuel; Kirk, Eugenie; Watts, Benjamin; Meyer, Markus; Lorona Ornelas, Joshua; Späth, Andreas; Stanescu, Stefan; et al. (Optica, 2020)
The availability of intense soft x-ray beams with tunable energy and polarization has pushed the development of highly sensitive, element-specific, and noninvasive microscopy techniques to investigate condensed matter with high spatial and temporal resolution. The short wavelengths of soft x-rays promise to reach spatial resolutions in the deep single-digit nanometer regime, providing unprecedented access to magnetic phenomena at fundamental length scales. Despite considerable efforts in soft x-ray microscopy techniques, a two-dimensional resolution of 10 nm has not yet been surpassed in direct imaging. Here, we report on a significant step beyond this long-standing limit by combining newly developed soft x-ray Fresnel zone plate lenses with advanced precision in scanning control and careful optical design. With this approach, we achieve an image resolution of 7 nm. By combining this highly precise microscopy technique with the x-ray magnetic circular dichroism effect, we reveal dimensionality effects in an ensemble of interacting magnetic nanoparticles. Such effects are topical in current nanomagnetism research and highlight the opportunities of high-resolution soft x-ray microscopy in magnetism research and beyond. (C) 2020 Optical Society of America under the terms of the OSA Open Access Publishing Agreement
CRIS-Team WoS Importer:2020-12-18

Solar energy storage at an atomically defined organic-oxide hybrid interface - Schuschke, Christian; Hohner, Chantal; Jevric, Martyn; Petersen, Anne Ugleholdt; Wang, Zhihang; Schwarz, Matthias; Kettner, Miroslav; Waidhas, Fabian; Fromm, Lukas; Sumby, Christopher J.; Görling, Andreas; Brummel, Olaf; et al. (Nature Communications, 2019)
Molecular photoswitches provide an extremely simple solution for solar energy conversion and storage. To convert stored energy to electricity, however, the photoswitch has to be coupled to a semiconducting electrode. In this work, we report on the assembly of an operational solar-energy-storing organic-oxide hybrid interface, which consists of a tailor-made molecular photoswitch and an atomically-defined semiconducting oxide film. The synthesized norbornadiene derivative 2-cyano-3-(4-carboxyphenyl)norbornadiene (CNBD) was anchored to a well-ordered Co3O4(111) surface by physical vapor deposition in ultrahigh vacuum. Using a photochemical infrared reflection absorption spectroscopy experiment, we demonstrate that the anchored CNBD monolayer remains operational, i.e., can be photo-converted to its energy-rich counterpart 2-cyano-3-(4-carboxyphenyl)quadricyclane (CQC). We show that the activation barrier for energy release remains unaffected by the anchoring reaction and the anchored photoswitch can be charged and discharged with high reversibility. Our atomically-defined solar-energy-storing model interface enables detailed studies of energy conversion processes at organic/oxide hybrid interfaces.
CRIS-Team WoS Importer:2019-06-18

Solving the Puzzle of the Coexistence of Different Adsorption Geometries of Graphene on Ni(111) - Matysik, Sabine; Papp, Christian; Görling, Andreas (Journal of Physical Chemistry C, 2018)
Graphene and the Ni(111) surface have almost identical unit cells, enabling the synthesis of high-quality graphene layers in perfect registry with the Ni surface in simple 1 x 1 unit cells. The relative orientation of graphene to the Ni(111) surface, however, is an open puzzle: up to three different structures (top-fcc, top-hcp, and bridge-top) have been found experimentally. The present dispersion-corrected ab initio density-functional theory study on the adsorption of graphene on Ni(111) reveals a dependence of the adsorption geometry on the concentration of subsurface interstitial carbon and presents a possible solution to this puzzle. At very high local interstitial carbon concentrations, we observe only physisorption. At intermediate concentrations, chemisorbed top-hcp graphene is energetically most favorable whereas at low concentrations bridge-top and top-fcc are the preferred chemisorbed structures.

SOx storage and release kinetics for ceria-supported platinum - Happel, Markus; Kylhammar, Lisa; Carlsson, Per-Anders; Libuda, Jörg; Gronbeck, Henrik; Skoglundh, Magnus (Applied Catalysis B-Environmental, 2009)

Spectroscopic Observation and Molecular Dynamics Simulation of Ga Surface Segregation in Liquid Pd-Ga Alloys - Grabau, Mathias; Erhard, Jannis; Taccardi, Nicola; Krick Calderon, Sandra; Wasserscheid, Peter; Görling, Andreas; Steinrück, Hans-Peter; Papp, Christian (Chemistry - A European Journal, 2017)
Liquid binary Pd-Ga alloys with low Pd contents of 0.8, 1.8, and 4.7at% of Pd were examined as a function of sample temperature in ultra-high vacuum by using angle-resolved XPS. Upon cooling from 750 to 400K, a pronounced temperature-dependence of the Pd concentration in the liquid phase was observed, which was explained by the transition from the pure liquid phase to a two-phase system, consisting of a solid Ga5Pd phase and a Pd-depleted liquid Pd-Ga alloy. In the liquid Pd-Ga alloy, Pd is always depleted from the topmost interface layer, as deduced from angle-resolved XPS at 0 and 80 degrees emission, independent of temperature and Pd concentration. This observation is interpreted as an inhomogeneous depth distribution function of Pd, that is, the segregation of Ga to the surface of the liquid phase. The results of a DFT-based molecular dynamics simulation (MD) independently show interfacial stratification of Ga and an inhomogeneous Pd distribution along the surface normal. The evaluation of the experimental data with a rigid layer model based on the MD calculations leads to excellent agreement with the simulation.
Keywords: DFT MD; gallium; liquid-metal catalysis; palladium; XPS

Spontaneous Formation of Tetrahydrofuran Hydrate in Ultrahigh Vacuum - Ghosh, Jyotirmoy; Bhuin, Radha Gobinda; Ragupathy, Gopi; Pradeep, Thalappil (Journal of Physical Chemistry C, 2019)
Clathrate hydrates (CHs) typically nucleate under high-pressure conditions, but their existence in ultrahigh vacuum (UHV) is an open question. Here, we report the formation of tetrahydrofuran (THF) hydrate in UHV, using reflection absorption infrared spectroscopy (RAIRS). Annealing both sequentially and co-deposited mixtures of THF and H2O to 130 K for adequate time, originally prepared at 10 K, led to the formation of THF hydrate, at 10(-10) mbar. Nucleation of THF hydrate was associated with the crystallization of amorphous solid water. Crystallization kinetics was examined through isothermal kinetic measurements using RAIRS in the temperature range of 120-130 K. The kinetic measurements revealed that the THF hydrate formation was a diffusion-controlled process and the overall activation energy for the process was found to be similar to 23.12 kJ mol(-1). This considerably lower activation energy as compared to that for the crystallization of pure ice established the spontaneity of the process. The results provide valuable insights into the low-pressure characteristics of CHs and associated thermodynamics.
CRIS-Team WoS Importer:2019-07-26

Stability and Exchange Processes in Ionic Liquid/Porphyrin Composite Films on Metal Surfaces - Lexow, Matthias; Massicot, Stephen; Maier, Florian; Steinrück, Hans-Peter (Journal of Physical Chemistry C, 2019)
In light of increasing interest in the development of organic-organic multicomponent heterostructures on metals, this molecular-scale study investigates prototypical composite systems of ultrathin porphyrin and ionic liquid (IL) films on metallic supports under well-defined ultrahigh vacuum conditions. By means of angle-resolved X-ray photoelectron spectroscopy, we investigated the adsorption, stability, and thermal exchange of the resulting films after sequential physical vapor deposition of the free-base porphyrin 5,10,15,20-tetraphenylporphyrin, 2H-TPP, and the IL 1-methyl-3-octylimidazolium hexafluorophosphate, [C8C1Im][PF6], on Ag(111) and Au(111). 2H-TPP shows two-dimensional growth of up to two closed molecular layers on Ag(111) and Au(111) and three-dimensional island growth for thicker films. IL films on top of a monolayer of 2H-TPP exhibit Stranski-Krastanov-like growth and are stable up to 385 K. The 2H-TPP layer leads to destabilization of the IL films, compared to the IL in direct contact with the bare metals, by inhibiting the specific adsorption of the ions on the metal surfaces. When the porphyrin is deposited on top of [C8C1Im][PF6] at low temperature, the 2H-TPP molecules adsorb on top of the IL film at first but replace the IL at the IL/metal interfaces upon heating above 240 K. This exchange process is most likely driven by the higher adsorption energy of 2H-TPP on Ag(111) and Au(111) surfaces, as compared to the IL. The behavior observed on Ag(111) and Au(111) is identical. The results are highly relevant for the stability of porphyrin/IL-based thin film catalyst systems and molecular devices, and more generally, stacked organic multilayer architectures.
CRIS-Team Scopus Importer:2019-12-31

Stabilization of Small Platinum Nanoparticles on Pt-CeO2 Thin Film Electrocatalysts During Methanol Oxidation - Brummel, Olaf; Waidhas, Fabian; Faisal, Firas; Fiala, Roman; Vorokhta, Mykhailo; Khalakhan, Ivan; Dubau, Martin; Figueroba, Alberto; Kovacs, Gabor; Aleksandrov, Hristiyan A.; Vayssilov, Georgi N.; Kozlov, Sergey M.; et al. (Journal of Physical Chemistry C, 2016)
Pt-doped CeOx thin film electrocatalysts have recently been shown to exhibit high activity and stability at the anode of proton exchange membrane fuel cells (PEM-FC). To identify, the role of the Pt dopant and the origin of the high stability of Pt-CeOx films, we applied electrochemical in situ IR spectroscopy on Pt-CeOx model thin film catalysts during methanol (1 M methanol) oxidation. The model catalysts were prepared by magnetron cosputtering of Pt (9-21 atom %), and CeO2 onto clean, and carbon-coated Au supports, All samples were characterized by scanning electron microscopy (SEM), energy-dispersive, X-ray spectroscopy (EDX), and X-ray photoelectron spectroscopy (XPS) before and after reaction. At pH 1 (0.1 MHClO4) the Pt-CeOx dissolves partially during potential cycling, whereas the films: are largely stable at pH 6 (0.1 M phosphate buffer). Electrochemical IR spectroscopy of the adsorbed CO shows that Metallic Pt is formed on all Pt-CeOx samples during methanol oxidation. In comparison to Pt(111), Pt aggregates on Pt-CeOx show a CO on-top signal, which is red shifted by at least 25 cm(-1) and suppression of the bridging CO signals. Whereas the Pt particles on Pt-CeOx,films with high Pt concentration (>20 atom %) undergo rapid sintering during the potential cycling, small metallic Pt aggregates are stable under the Same conditions on films with lbw Pt concentration (<15 atom % Pt). By means of density functional theory (DFT) calculations we analyzed the spectral shifts of adsorbed CO as a function of nanoparticle size both on free and ceria-supported Pt particles, Comparison with the experiment suggests the formation of "subnano"-particles, i.e., particles with up to 30 atoms (<1 nm particle diameter), which do not expose regular (111) facet sites. At sufficiently low Pt loading) these subnano-Pt particles are efficiently stabilized by the interaction with the ceria support under conditions of the dynamically changing electrode potential.

Steering the formation of supported Pt-Sn nanoalloys by reactive metal-oxide interaction - Neitzel, Armin; Kovacs, Gabor; Lykhach, Yaroslava; Tsud, Nataliya; Kozlov, Sergey M.; Skala, Tomas; Vorokhta, Mykhailo; Matolin, Vladimir; Neyman, Konstantin M.; Libuda, Jörg (RSC Advances, 2016)
The formation of a supported Pt-Sn nanoalloy upon reactive metal-oxide interaction between Pt nanoparticles and a Sn-CeO2 substrate has been investigated by means of synchrotron radiation photoelectron spectroscopy and resonant photoemission spectroscopy in combination with density functional modeling. It was found that Pt deposition onto a Sn-CeO2 substrate triggers the reduction of Sn2+ cations yielding Pt-Sn nanoalloys at 300 K under ultra-high vacuum conditions. Three distinct stages of Pt-Sn nanoalloy formation were identified associated with the growth of (I) ultra-small monometallic Pt particles on a Sn-CeO2 substrate, (II) Pt-Sn nanoalloys on a Sn-CeO2 substrate, and (III) Pt-Sn nanoalloys on a stoichiometric CeO2 substrate. These findings suggest the existence of a critical size of monometallic Pt particles above which the formation of a Pt-Sn nanoalloy becomes favorable. In this respect, density functional modeling revealed a strong dependence of the formation energy of the PtxSn nanoalloy on the size of the Pt particle. Additionally, the thermodynamically favorable bulk and surface Pt/Sn stoichiometries were identified as two parameters that determine the composition of the supported Pt-Sn nanoalloys and limit the extraction of Sn2+ from the Sn-CeO2 substrate. Primarily, the formation of a bulk Pt3Sn alloy phase drives the growth of the Pt-Sn nanoalloy upon Pt deposition at 300 K. Upon annealing, Sn segregation on the surface of the Pt-Sn nanoalloy promotes further extraction of Sn2+ until the thermodynamically stable Pt/Sn concentration ratios of 3 for the bulk and approximately 1.6 for the surface are reached.

Strong repulsion and site exclusion in a system with ontop and bridge sites on a one-dimensional lattice: Equilibrium and kinetics - Payne, Stephen H.; Kreuzer, Hans Jürgen; Kinne, Martin; Denecke, Reinhard; Steinrück, Hans-Peter (Surface Science, 2002)
We derive the kinetics for an adsorbate with strong nearest neighbor repulsion and additional second neighbor lateral interactions, starting from a kinetic lattice gas model. We then make the connection with site exclusion, first, as a demonstration, for an adsorbate with one adsorption site and next with both top and bridge adsorption, to elucidate the principal effects on sticking coefficients and desorption spectra. This paper is restricted to one-dimensional systems. © 2002 Elsevier Science B.V. All rights reserved.
Keywords: Equilibrium thermodynamics and statistical mechanics; Models of surface kinetics; Adsorption kinetics; Sticking; Thermal desorption; Single crystal surfaces

Strong size effects in supported ionic nanoparticles: Tailoring the stability of NOx storage catalysts - Desikusumastuti, Aine; Laurin, Mathias; Happel, Markus; Qin, Zhihui; Shaikhutdinov, Shamil; Libuda, Jörg (Catalysis Letters, 2008)
Based on a well-defined model-catalyst approach, we study the particle size dependent properties of NO (x) storage materials. The single-crystal based model systems are prepared on an ordered Al2O3 film, on which BaO nanoparticles are grown under ultrahigh-vacuum (UVH) conditions. Particle size and density are characterized by scanning tunneling microscopy (STM). The interaction with NO2 is probed by molecular beam (MB) methods in combination with time-resolved IR reflection absorption spectroscopy (TR-IRAS). It is found that both, the stability and the formation kinetics of alumina supported barium nitrate nanoparticles show a strong dependence on particle size. Very small BaO particles are rapidly converted into nitrates, however, the resulting aggregates exhibit a strongly reduced thermal stability. Surface and bulk nitrate and nitrate features are identified by means of vibrational spectroscopy. It is concluded that the size dependencies are related to the formation and decomposition of surface-related BaNO (x) species the decomposition temperature of which can be tuned over an exceptionally large temperature interval. It is suggested that the stability of these surface NO (x) species is strongly modified by the underlying support.
Keywords: supported model catalysts; NSR catalysts; barium oxide; nitrogen dioxide; particle size effects; IR reflection absorption spectroscopy; scanning tunneling microscopy

Structural characterization of alpha,omega-DH6T monolayer films grown at the liquid-liquid interface - Johnson, Manuel; Hawly, Tim; Wu, Mingjian; Spiecker, Erdmann; Fink, Rainer (Soft Matter, 2021)
The molecular self-organization of alpha,omega-dihexylsexithiophene (alpha,omega-DH6T) monolayers prepared at the solvent-water interface is investigated by complementary microscopy techniques. Our study focuses on the influence of solvents and initial droplet volume on the resulting film morphology. Long-range extended domains in the monolayer regime are detected by visible light microscopy only for toluene. Small-area electron diffraction (SAED) proves the formation of single-crystalline monolayers with structural parameters identical to the organic bulk crystals. In comparison with conventional vacuum sublimated thin films a deviant molecular orientation, derived from near-edge-X-ray absorption fine structure (NEXAFS) in combination with a lower step height measured by atomic-force-microscopy (AFM), indicates a different behaviour of the flexible terminal hexyl chains during growth in a liquid surrounding. Furthermore, a structural degradation over time is observed which is caused by residual solvent molecules that are incorporated during the transfer procedure.
Created from Fastlane, WoS look-up

Structural investigation on thermoresponsive PVA/poly(methacrylate-co-N- isopropylacrylamide) microgels across the volume phase transition - Ghugare, Shivkumar V.; Chiessi, Ester; Fink, Rainer; Gerelli, Yuri; Scotti, Andrea; Deriu, Antonio; Carrot, Geraldine; Paradossi, Gaio (Macromolecules, 2011)
Characterization of switchable microgels is a major task in drug delivery science. The study of soft polymeric devices requires a combined use of spectroscopy, microscopy, and scattering approaches enabling the characterization of nanostructured features across a volume phase transition. In this work the structural changes of poly(vinyl alcohol) based thermoreversible microgel particles which incorporate p(NiPAAm-co-methacrylate) chains across the transition temperature occurring at 33 °C have been addressed by utilizing reciprocal and direct space approaches such as small angle neutron scattering, SANS, dynamic light scattering, DLS, soft transmittance X-ray microscopy, STXM, and confocal laser scanning microscopy, CLSM, respectively. The comparison between the results obtained from those approaches allows an evaluation of the driving forces acting in the transition and reveals the changes in the microgel structure at nanoscale level. The structure of the poly(vinyl alcohol) based microgel particles, incorporating p(NiPAAm) sequences, consist of a hydrogel core and of a crown of polymer chains projected, at room temperature, in aqueous medium. An increase of the temperature above 33 °C causes a volume phase transition of the system characterized by the collapse of the particle core and of the chains grafted at the particle surface. This transition is accompanied by a massive release of water and an increase of the interface with the dispersing aqueous medium, causing the passage from a permeable to a semipermeable structure. © 2011 American Chemical Society.

Structural transformations and adsorption properties of PtNi nanoalloy thin film electrocatalysts prepared by magnetron co-sputtering - Brummel, Olaf; Waidhas, Fabian; Khalakhan, Ivan; Vorokhta, Mykhailo; Dubau, Martin; Kovacs, Gabor; Aleksandrov, Hristiyan A.; Neyman, Konstantin M.; Matolin, Vladimir; Libuda, Jörg (Electrochimica Acta, 2017)
PtNi thin film catalysts provide higher activity and enhanced Pt efficiency in the oxygen reduction reaction (ORR) in comparison to pure Pt catalysts. We explored the structural transformations and degradation mechanisms in such films by cyclic voltammetry (CV), electrochemical atomic force microscopy (EC-AFM), and electrochemical infrared reflection absorption spectroscopy (EC-IRRAS) using CO as a probe. The model catalysts were prepared by magnetron sputtering, and the results were compared to reference experiments on Pt(111). Freshly prepared catalysts show two characteristic IR bands in the on-top CO region. The signal at lower wavenumbers is assigned to isolated CO on Pt sites. Based on density functional theory (DFT) calculations, we suggest that another blue-shifted CO band can be attributed to dicarbonyls on low-coordinated Pt centers, generated by the leaching of surface Ni. This band vanishes upon cycling to 1.1 V versus the reversible hydrogen electrode (V-RHE) and the catalyst shows a weak decrease in grain size in AFM. A dramatic change of the film structure is observed upon potential cycling to 1.2 V-RHE. CV indicates the formation of [110] and [100] steps and AFM points to a strong decrease in particle size. Simultaneously, EC-IRRAS shows the appearance of a new, strongly red-shifted CO band. Based on DFT, we assign these changes to a transient enrichment of Ni in the (sub) surface region. Upon cycling to higher potential, Ni is completely leached from the surface region, and large Pt particles are formed. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: platinum; nickel; catalyst stability; electrochemical infrared spectroscopy; density functional theory

Structure and Conformation of Individual Molecules upon Adsorption of a Mixture of Benzoporphyrins on Ag(111), Cu(111), and Cu(110) Surfaces - Adhikari, Rajan; Brox, Jan; Massicot, Stephen; Ruppel, Michael; Jux, Norbert; Marbach, Hubertus; Steinrück, Hans-Peter (ChemPhysChem, 2023)
We investigated the adsorption behavior of a mixture of six 2H-tetrakis-(3, 5-di-tert-butylphenyl)(x)benzoporphyrins (2H-diTTBP(x)BPs, x=0, 1, 2-cis, 2-trans, 3, and 4) on Ag(111), Cu(111) and Cu(110) at room temperature by scanning tunneling microscopy (STM) under ultra-high vacuum conditions. On Ag(111), we observe an ordered two-dimensional square phase, which is stable up to 400 K. On Cu(111), the same square phase coexists with a stripe phase, which disappears at 400 K. In contrast, on Cu(110), 2H-diTTBP(x)BPs adsorb as immobile isolated molecules or dispersed short chains along the [1 (Formula presented.) 0] substrate direction, which remain intact up to 450 K. The stabilization of the 2D supramolecular structures on Ag(111) and Cu(111), and of the 1D short chains on Cu(110) is attributed to van der Waals interactions between the tert-butyl and phenyl groups of neighboring molecules. From high-resolution STM, we can assign all six 2H-diTTBP(x)BPs within the ordered structures. Moreover, we deduce a crown shape quadratic conformation on Ag(111) and Cu(111), an additional saddle-shape on Cu(111), and an inverted structure and a quadratic appearance on Cu(110). The different conformations are attributed to the different degree of interaction of the iminic nitrogen atoms of the isoindole and pyrrole groups with the substrate atoms.
CRIS-Team Scopus Importer:2023-07-21
Keywords: 2H-diTTBP(x)BPs; benzoporphyrin; isoindole groups; scanning tunneling microscopy; self-assembly

Structure and Reactivity of the Ionic Liquid [C(1)C(1)Im][Tf2N] on Cu(111) - Adhikari, Rajan; Massicot, Stephen; Fromm, Lukas; Talwar, Timo; Gezmis, Emine; Meusel, Manuel; Bayer, Andreas; Jaekel, Simon; Maier, Florian; Görling, Andreas; Steinrück, Hans-Peter (Topics in Catalysis, 2023)
We studied the adsorption and reaction behavior of the ionic liquid (IL) 1,3-dimethylimidazolium bis[(trifluoromethyl)sulfonyl]imide ([C(1)C(1)Im][Tf2N]) on Cu(111) using non-contact atomic force microscopy (nc-AFM), scanning tunneling microscopy (STM), and angle-resolved X-ray photoelectron spectroscopy (ARXPS) in ultrahigh vacuum as a function of temperature, supported by density-functional theory (DFT) calculations. Our nc-AFM results for sub-monolayer IL films show that at 200 K, the IL self-assembles into highly ordered islands, with cations and anions arranged next to each other in a checkerboard-type phase. After extended annealing at 300 K, the structure transforms first to a hexagonal phase and then to a porous honeycomb phase. Simultaneously, many small, disordered islands are formed. Complementary ARXPS reveals no IL desorption until 300 K. However, a significant fraction of the IL is converted to a new species as deduced from new, strongly shifted peaks that develop in the XP spectra at around 275 K and grow with annealing time at 300 K. We correlate the remaining unshifted peaks to the ordered phases observed in nc-AFM and the shifted peaks to decomposition products, which appear as disordered islands in nc-AFM and STM. Upon further heating to 360 K, about 50% of the anions or their decomposition products desorb from the surface, while cation-related fragments mostly remain on the surface. From DFT, we obtain additional information on the structure of the ordered phases and the interaction of the IL with the substrate.
CRIS-Team WoS Importer:2023-05-05

Structure and Surface Behavior of Rh Complexes in Ionic Liquids Studied Using Angle-Resolved X-ray Photoelectron Spectroscopy - Hemmeter, Daniel; Paap, Ulrike; Maier, Florian; Steinrück, Hans-Peter (Catalysts, 2023)
We present an ARXPS study on the surface composition and interfacial behavior of commercial [Rh(COD)2][TfO] in [C2C1Im][TfO], [C4C1Im][TfO], [C8C1Im][TfO], and [C2C1Im][EtOSO3]. The complex was found to be non-intact in a solution of these ILs through the loss of COD ligands, accompanied by the depletion of the metal center from the IL/vacuum interface. Increasing the chain length of the aliphatic substituent on the imidazolium cation of the [TfO]−-based ILs led to a more pronounced depletion from the interface, due to the higher surface affinity of the solvent cations with the longer alkyl chains. The loss of COD ligands offered facile in situ ligand substitution with surface-active TPPTS to afford a moderate increase in the surface concentration of Rh. We propose the formation of a Schrock−Osborn-type catalyst [Rh(COD)(TPPTS)2][TfO]. Information on the surface composition and targeted design of the gas/IL interface is highly relevant for applications in IL-based catalytic systems, such as in supported ionic liquid phase (SILP) catalysis.
CRIS-Team Scopus Importer:2023-06-09
Keywords: catalysis; ionic liquids; rhodium catalysts; surface analysis; X-ray photoelectron spectroscopy (XPS)

Structure-Dependent Anchoring of Organic Molecules to Atomically Defined Oxide Surfaces: Phthalic Acid on Co3O4(111), CoO(100), and CoO(111) - Xu, Tao; Schwarz, Matthias; Werner, Kristin; Mohr, Susanne; Amende, Maximilian; Libuda, Jörg (Chemistry - A European Journal, 2016)
We have performed a model study to explore the influence of surface structure on the anchoring of organic molecules on oxide materials. Specifically, we have investigated the adsorption of phthalic acid (PA) on three different, well-ordered, and atomically defined cobalt oxide surfaces, namely 1)Co3O4(111), 2)CoO(111), and 3)CoO(100) on Ir(100). PA was deposited by physical vapor deposition (PVD). The formation of the PA films and interfacial reactions were monitored in situ during growth by isothermal time-resolved IR reflection absorption spectroscopy (TR-IRAS) under ultrahigh vacuum (UHV) conditions. We observed a pronounced structure dependence on the three surfaces with three distinctively different binding geometries and characteristic differences depending on the temperature and coverage. 1)PA initially binds to Co3O4(111) through the formation of a chelating bis-carboxylate with the molecular plane oriented perpendicularly to the surface. Similar species were observed both at low temperature (130K) and at room temperature (300K). With increasing exposure, chelating mono-carboxylates became more abundant and partially replaced the bis-carboxylate. 2)PA binds to CoO(100) in the form of a bridging bis-carboxylate for low coverage. Upon prolonged deposition of PA at low temperature, the bis-carboxylates were converted into mono-carboxylate species. In contrast, the bis-carboxylate layer was very stable at 300K. 3)For CoO(111) we observed a temperature-dependent change in the adsorption mechanism. Although PA binds as a mono-carboxylate in a bridging bidentate fashion at low temperature (130K), a strongly distorted bis-carboxylate was formed at 300K, possibly as a result of temperature-dependent restructuring of the surface. The results show that the adsorption geometry of PA depends on the atomic structure of the oxide surface. The structure dependence can be rationalized by the different arrangements of cobalt ions at the three surfaces.
Keywords: adsorption; carboxylic acids; cobalt; IR spectroscopy; thin films

Structure-Dependent Dissociation of Water on Cobalt Oxide - Schwarz, Matthias; Faisal, Firas; Mohr, Susanne; Hohner, Chantal; Werner, Kristin; Xu, Tao; Skala, Tomas; Tsud, Nataliya; Prince, Kevin C.; Matolin, Vladimir; Lykhach, Yaroslava; Libuda, Jörg (Journal of Physical Chemistry Letters, 2018)
Understanding the correlation between structure and reactivity of oxide surfaces is vital for the rational design of catalytic materials. In this work, we demonstrate the exceptional degree of structure sensitivity of the water dissociation reaction for one of the most important materials in catalysis and electrocatalysis. We studied H2O on two atomically defined cobalt oxide surfaces, CoO(100) and Co3O4(111). Both surfaces are terminated by O2- and Co2+ in different coordination. By infrared reflection absorption spectroscopy and synchrotron radiation photoelectron spectroscopy we show that H2O adsorbs molecularly on CoO(100), while it dissociates and forms very strongly bound OH and partially dissociated (H2O)(n)(OH)(m) clusters on Co3O4(111). We rationalize this structure dependence by the coordination number of surface Co2+. Our results show that specific well-ordered cobalt oxide surfaces interact very strongly with H2O whereas others do not. We propose that this structure dependence plays a key role in catalysis with cobalt oxide nanomaterials.

Structure, morphology and interface properties of ultrathin SnTTBPP(OH)2-films adsorbed on Ag(100) - Schmidt, Norman Anja; Hub, Christian; Gnichwitz, Jan-Frederik; Hieringer, Wolfgang; Hirsch, Andreas; Fink, Rainer (Physical Chemistry Chemical Physics, 2011)
The molecular interaction of dihydroxo[5,10,15,20-tetrakis(4-tert-butyl- phenyl)porphyrinato]-tin(iv) (SnTTBPP(OH)), the structural order and growth of ultrathin films on Ag(100) have been studied by means of low-energy electron diffraction (LEED) and synchrotron based photoelectron spectroscopy, i.e., X-ray photoemission (XPS) and near-edge X-ray absorption fine structure (NEXAFS/XANES) spectroscopy. For the first time, monolayer adsorption of a metalloporphyrin with octahedral coordination of the metal center by two additional axial hydroxo ligands is investigated in a multi-technique study. The delicate balance of molecule-substrate interactions and intermolecular interactions leads to the formation of a densely-packed organic monolayer which is commensurate with the Ag(100) substrate. From NEXAFS linear dichroism an almost coplanar orientation of the porphyrin system is derived. XPS and NEXAFS clearly indicate that the axial hydroxo ligands are cleaved in monolayer films, i.e., upon adsorption to the Ag substrate. With increasing film thickness orientational order gets lost and leads to polycrystalline growth for thicker films as confirmed by scanning X-ray transmission microscopy (STXM). © 2011 the Owner Societies.

Studying the dynamic behaviour of porphyrins as prototype functional molecules by scanning tunnelling microscopy close to room temperature - Marbach, Hubertus; Steinrück, Hans-Peter (Chemical Communications, 2014)
Scanning tunnelling microscopy (STM) enables us to directly observe the dynamic behaviour of organic molecules on surfaces. White imaging atoms and molecules using STM is certainly fascinating by itself, corresponding temperature-dependent measurements allow for the quantitative determination of the energetics and kinetics of the underlying molecular surface processes. Herein, we review recent advances in the STM investigation of the dynamic behaviour of adsorbed porphyrins at and close to room temperature. Three different case studies are discussed, providing insight into the dynamics of diffusion, rotation, reaction, and molecular switching at surfaces, based on isothermal STM measurements. The reviewed examples demonstrate that variable temperature STM can be a suitable toot to directly monitor the dynamic behaviour of individual adsorbed molecules, at and close to room temperature. Free base porphyrins on Cu(111) proved to be particularly suitable for these studies due to the strong bonding interaction between the iminic nitrogen atoms in the porphyrin macrocycle and the Cu substrate atoms. As a consequence, the corresponding activation energies for surface diffusion, self-metalation reaction and conformational switching are of a magnitude that allows for monitoring the processes at and around room temperature, in contrast to most previous studies, which were performed at cryogenic temperatures. The kinetic analysis of the surface diffusion and setf-metalation was performed using an Arrhenius approach, yielding the corresponding activation energies and preexponential factors. In contrast, the conformational switching process was analysed in the framework of transition state theory, based on the Eyring equation. This approach provides a more detailed insight into interpretable thermodynamic potentials, i.e., the enthalpic and entropic contributions to the activation barrier. The analysis shows that at room temperature the adsorption and switching behaviour of the investigated free base porphyrin on Cu(111) is dominated by entropic effects. Since the entropic energy contribution vanishes at low temperatures, the importance of experiments conducted at temperatures close to room temperature is emphasized.

Study on Growth of Tungsten Bronze Phase from Niobate Perovskite Ceramics in Controlled Atmosphere for Photoferroelectric Applications - Shi, Xi; Bai, Yang; Wichmann, Christoph; Moritz, Michael; Kuhfuß, Michel; Papp, Christian; Khansur, Neamul Hayet (Advanced Electronic Materials, 2023)
Recent research has found that by introducing A-site deficiency into Ba/Ni co-doped (K,Na)NbO3 ABO3-type perovskite, a beneficial interface for photoferroelectric applications is formed between the perovskite and tungsten bronze (TB) phases. To date, such an interface is formed only spontaneously, and the growth mechanism of the TB phase in the perovskite phase is unclear. This work investigates controlled interface formation using KNBNNO (K0.50Na0.44Ba0.04Ni0.02Nb0.98O2.98) annealed at different temperatures for different durations, and in various atmospheres. Structural, microstructural, and chemical analyses suggest that vacuum, N2, and O2 atmospheres promote the growth of the TB phase from the sample surface, of which the thickness increases with annealing temperature and duration. In contrast, annealing in air does not promote such growth due to lower evaporation of K and Na. Among all atmospheres, the growth starts the earliest, i.e., at 800 °C, in vacuum compared to that as late as 1000 °C in O2. The association of growth of the TB phase with the degree of alkali volatilization that is dependent on the atmosphere, and that with the resultant variation in diffusion rate, uncovers the formation mechanism of the beneficial interface that may also be applicable to other KNN-based materials for advanced photoferroelectric applications.
CRIS-Team Scopus Importer:2023-12-15
Keywords: (K; Na)NbO3 perovskite; photoferroelectric applications; tetragonal tungsten bronze phase

STXM goes 3D: Digital reconstruction of focal stacks as novel approach towards confocal soft x-ray microscopy - Späth, Andreas; Schöll, Simon; Riess, Christian; Schmidtel, Daniel; Paradossi, Gaio; Raabe, Jörg; Hornegger, Joachim; Fink, Rainer (Ultramicroscopy, 2014)
Fresnel zone plate based soft x-ray transmission microspectroscopy has developed into a routine technique for high-resolution elemental or chemical 2D imaging of thin film specimens. The availability of high resolution Fresnel lenses with short depth of focus offers the possibility of optical slicing (in the third dimension) by focus series with resolutions in the submicron regime. We introduce a 3D reconstruction algorithm that uses a variance-based metric to assign a focus measure as basis for volume rendering. The algorithm is applied to simulated geometries and opaque soft matter specimens thus enabling 3D visualization. These studies with z-resolution of few 100. nm serve as important step towards the vision of a confocal transmission x-ray microscope. © 2014 Elsevier B.

Substrate-mediated phase separation of two porphyrin derivatives on Cu(111) - Buchner, Florian; Zillner, Elisabeth; Röckert, Michael; Gläßel, Stefanie; Steinrück, Hans-Peter; Marbach, Hubertus (Chemistry - A European Journal, 2011)
Sorting molecules: Effective phase separation of two porphyrin species, namely CoTPP and 2HTPP (TPP= tetraphenylporphyrin, 2HTPP=2H- tetraphenylporphyrin), on Cu(111) is reported. The separation process can be conclusively explained by the domination of molecule-molecule interactions for CoTPP, whereas the adsorption behavior of 2HTPP is dominated by molecule-substrate interactions (see figure). Copyright © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Successful double aberration correction in a low energy electron microscope - Fink, Rainer; Schmidt, Thomas; Umbach, Eberhard; Freund, Hans-Joachim; et al. (Ultramicroscopy, 2010)
UnivIS-Import:2015-03-09:Pub.2010.nat.dchph.ppc23.succes

Sulfur oxidation on graphene-supported platinum nanocluster arrays - Düll, Fabian; Schwaab, Valentin; Späth, Florian; Bauer, Udo; Bachmann, Philipp; Steinhauer, Johann; Steinrück, Hans-Peter; Papp, Christian (Chemical Physics Letters, 2018)
Nanocluster arrays grown on a graphene Moire on Rh(1 1 1) are an excellent model system that can bridge the materials gap between single crystals and real catalysts. They feature different adsorption sites like edges, kinks, and facets, but are at the same time well-ordered with a small size distribution. Herein, we used platinum nanocluster arrays to investigate the oxidation of sulfur, which is a common catalyst poison, as a possible route to restore the catalyst. We studied the kinetics in a site-resolved manner with high-resolution XPS, despite the complex shape of the nanoparticles. Since SO3 and SO4 were the only observable SOx surface species, the reaction of S to SO was identified as the rate-determining step. As a secondary process, the displacement of sulfur from edge to facet sites caused by oxygen was observed.

Sulfur oxidation on Pt(355): It is the steps! - Streber, Regine; Papp, Christian; Lorenz, Michael Peter Andreas; Bayer, Andreas; Denecke, Reinhard; Steinrück, Hans-Peter (Angewandte Chemie International Edition, 2009)
Steps in the right direction: The role of steps in the removal of sulfur from a Pt model catalyst via metastable SO and SO species, was demonstrated by in situ high-resolution X-ray photoelectron spectroscopy. From isothermal experiments the activation energy of the rate-determining step was deduced to be 34 kJmol. © 2009 Wiley-VCH Verlag GmbH &. Co. KGaA.

Sulphur dioxide adsorption on the Ni(110) surface - Zebisch, P.; Weinelt, M.; Steinrück, Hans-Peter (Surface Science, 1993)
The adsorption of SO on Ni(110) has been studied in detail by temperature programmed desorption (TPD), low energy electron diffraction (LEED), X-ray photoelectron spectroscopy (XPS), and angle resolved UV photoelectron spectroscopy (ARUPS) using linearly polarized synchrotron radiation. At 100 K SO is found to chemisorb in molecular form on Ni(110) with a saturation coverage of 0.5 ML (1 ML = 1 molecule Ni-atom). The saturated chemisorbed layer exhibits a c(2 × 2) LEED pattern. At initial coverages below 0.25 ML, SO completely decomposes upon heating to 750 K; for higher coverages molecular SO desorption is also observed in a single peak between 300 and 400 K. From the angle resolved UPS spectra and symmetry selection rules we deduce the symmetry of the adsorbed SO molecules for low coverages as C (σ), with the molecular O-S-O plane oriented perpendicular to the surface and aligned along the [001] azimuth (perpendicular to the close-packed substrate rows). Within the plane the molecule is tilted, which is attributed to an additional Ni-O interaction. In the saturated layer the symmetry is further reduced to C indicating an additional tilting and/or rotation of the molecular plane with respect to the substrate. © 1993.

Supported catalytically active liquid metal solutions: From operando studies to model catalysis - Libuda, Jörg (ABSTRACTS OF PAPERS OF THE AMERICAN CHEMICAL SOCIETY, 2019)
CRIS-Team WoS Importer:2019-08-23

Supported homogeneous catalyst makes its own liquid phase - Kaftan, Andre; Schönweiz, Andreas; Nikiforidis, Ioannis; Hieringer, Wolfgang; Dyballa, Katrin M.; Franke, Robert; Görling, Andreas; Libuda, Jörg; Wasserscheid, Peter; Laurin, Mathias; Haumann, Marco (Journal of Catalysis, 2015)
2,2'-((3,3'-di-tert-butyl-5,5'-dimethoxy-[1,1'-biphenylj-2,2'-diyl)-bis(oxy))bis(4,4,5,5-tetraphenyl-1,3,2-dioxaphospholane) modified rhodium complexes molecularly adsorbed onto porous silica powder show surprisingly high activity and regioselectivity in the gas-phase hydroformylation of propene to but-anal, with no sign of deactivation. Operando IR investigations combined with density functional theory calculations confirm a side reaction: the aldol condensation of the butanal products. These heavier by-products accumulate inside the pores of the catalytic material. IR and gas chromatography show a direct relation between formation of enones, products of the aldol condensation, performance, and stability of the catalytic system. This demonstrates that the aldol condensation products generated in situ act as a solvent providing an ideal environment to the impregnated homogeneous catalyst. (c) 2014 Elsevier Inc. All rights reserved.
Keywords: Hydroformylation; Supported homogeneous catalysis; Operando spectroscopy; Infrared spectroscopy; Density functional theory; Silicon dioxide; Rhodium

Supported liquid metals - A new class of robust dehydrogenation catalysts - Taccardi, Nicola; Grabau, Mathias; Debuschewltz, Jonas; Distaso, Monica; Brandl, Marco; Hock, Rainer; Maier, Florian; Papp, Christian; Erhard, Jannis; Neiß, Christian; Peukert, Wolfgang; Görling, Andreas; et al. (12th Natural Gas Conversion Symposium 2019, 2019)
CRIS-Team Scopus Importer:2019-12-10

Support nanostructure boosts oxygen transfer to catalytically active platinum nanoparticles - Vayssilov, Georgi N.; Lykhach, Yaroslava; Migani, Annapaola; Staudt, Thorsten; Petrova, Galina P.; Tsud, Nataliya; Skala, Tomas; Bruix, Albert; Illas, Francesc; Prince, Kevin C.; Matolin, Vladimir; Neyman, Konstantin M.; et al. (Nature Materials, 2011)
Interactions of metal particles with oxide supports can radically enhance the performance of supported catalysts. At the microscopic level, the details of such metal-oxide interactions usually remain obscure. This study identifies two types of oxidative metal-oxide interaction on well-defined models of technologically important Pt-ceria catalysts: (1) electron transfer from the Pt nanoparticle to the support, and (2) oxygen transfer from ceria to Pt. The electron transfer is favourable on ceria supports, irrespective of their morphology. Remarkably, the oxygen transfer is shown to require the presence of nanostructured ceria in close contact with Pt and, thus, is inherently a nanoscale effect. Our findings enable us to detail the formation mechanism of the catalytically indispensable Pt-O species on ceria and to elucidate the extraordinary structure-activity dependence of ceria-based catalysts in general.

Suppressing Nonradiative Recombination in Lead-Tin Perovskite Solar Cells through Bulk and Surface Passivation to Reduce Open Circuit Voltage Losses - Zhang, Kaicheng; Späth, Andreas; Almora, Osbel; Le Corre, Vincent Marc; Wortmann, Jonas; Zhang, Jiyun; Xie, Zhiqiang; Barabash, Anastasiia; Hammer, Maria; Heumüller, Thomas; Min, Jie; Fink, Rainer; et al. (ACS Energy Letters, 2022)
Lead-Tin perovskite solar cells (Pb/Sn PSCs) are limited by the intrinsic instability of Sn(II), which tends to oxidize forming Sn vacancies in perovskite films. Herein, a Lewis base β-guanidinopropionic acid (GUA) and hydrazinium iodide (HAI) are introduced to effectively passivate the perovskite bulk and surface, respectively. The synergistic approach leads to Pb/Sn PSCs with a promising power conversion efficiency of 20.5% owing to the significantly reduced nonradiative recombination and voltage losses. As a result, the VOC × FF product of PSCs is significantly improved, which is among the highest values documented in the literature, being favorable for perovskite-based tandem applications. Additionally, the strategy demonstrated in this work could also improve the stability of PSCs by enhancing the chemical robustness of the perovskite layer. These results emphasize the significance of bulk and surface passivation in the development of efficient and stable PSCs based on Pb/Sn perovskites.
CRIS-Team Scopus Importer:2022-09-30

Suppression of Hysteresis Effects in Organohalide Perovskite Solar Cells - Hou, Yi; Scheiner, Simon; Tang, Xiaofeng; Gasparini, Nicola; Richter, Moses; Li, Ning; Schweizer, Peter; Chen, Shi; Chen, Haiwei; Ramírez Quiroz, César Omar; Du, Xiaoyan; Matt, Gebhard; et al. (Advanced Materials Interfaces, 2017)
Thin-film solar cell based on hybrid perovskites shows excellent light-to-power conversion efficiencies exceeding 22%. However, the mixed ionic-electronic semiconductor hybrid perovskite exhibits many unusual properties such as slow photocurrent instabilities, hysteresis behavior, and low-frequency giant capacitance, which still question us so far. This study presents a direct surface functionalization of transparent conductive oxide electrode with an ultrathin ≈2 nm thick phosphonic acid based mixed C60/organic self-assembled monolayer (SAM) that significantly reduces hysteresis. Moreover, due to the strong phosphonates bonds with indium tin oxide (ITO) substrates, the SAM/ITO substrates also exhibit an excellent recyclability merit from the perspective of cost effectiveness. Impedance studies find the fingerprint of an ion-based diffusion process in the millisecond to second regime for TiO2-based devices, which, however, is not observed for SAM-based devices at these low frequencies. It is experimentally demonstrated that ion migration can be considerably suppressed by carefully engineering SAM interfaces, which allows effectively suppressing hysteresis and unstable diode behavior in the frequency regime between ≈1 and 100 Hz. It is suggested that a reduced density of ionic defects in combination with the absence of charge carrier accumulation at the interface is the main physical origin for the reduced hysteresis.

Supramolecular order and structural dynamics: A STM study of 2H-tetraphenylporphycene on Cu(111) - Stark, Michael Werner; Träg, Johannes; Ditze, Stefanie; Brenner, Wolfgang; Jux, Norbert; Steinrück, Hans-Peter; Marbach, Hubertus (Journal of Chemical Physics, 2015)
The adsorption of 2H-tetraphenylporphycene (2HTPPc) on Cu(111) was investigated by scanning tunneling microscopy (STM). At medium coverages, supramolecular ordered islands are observed. The individual 2HTPPc molecules appear as two pairs of intense protrusions which are separated by an elongated depression. In the islands, the molecules are organized in rows oriented along one of the close packed Cu(111) substrate rows; the structure is stabilized by T-type interactions of the phenyl substituents of neighboring molecules. Two types of rows are observed, namely, highly ordered rows in which all molecules exhibit the same orientation, and less ordered rows in which the molecules exhibit two perpendicular orientations. Altogether, three different azimuthal orientations of 2HTPPc are observed within one domain, all of them rotated by 15° ± 1° relative to one closed packed Cu direction. The highly ordered rows are always separated by either one or two less ordered rows, with the latter structure being the thermodynamically more stable one. The situation in the islands is highly dynamic, such that molecules in the less ordered rows occasionally change orientation, also complete highly ordered rows can move. The supramolecular order and structural dynamics are discussed on the basis of the specific molecule-substrate and molecule-molecule interactions.

Surface analysis of Pd/ZnO catalysts dispersed on micro-channeled Al-foils by XPS - Dumbuya, K.; Denecke, Reinhard; Steinrück, Hans-Peter (Applied Catalysis A-General, 2008)
We have investigated the surface composition of Pd/ZnO catalysts dispersed on micro-channeled Al-foils in a non-activated and in the activated state, between 300 and 700 K using X-ray photoelectron spectroscopy (XPS). While the surface of the non-activated catalyst, as obtained after calcination, is composed of PdO, the surface of the activated (reduced) catalyst consists of predominantly PdZn and ∼30% metallic Pd. When increasing the temperature up to 700 K in UHV significant structural surface changes were observed for both samples. For the non-activated sample, PdO was reduced mainly to the Pd metal with some fraction of PdZn alloy. For the activated catalyst, the fraction of metallic Pd was also converted to PdZn, yielding a pure alloy, which is stable to at least 600 K. At 700 K both samples show changes due to segregation of Mg from the micro-channeled Al-foils onto which the powdered catalysts were deposited, which contains 3% Mg. © 2008 Elsevier B.V. All rights reserved.

Surface behavior of low-temperature molten salt mixtures during the transition from liquid to solid - Bhuin, Radha Gobinda; Schreiber, Patrick; Heller, Bettina; Scheuermeyer, Marlene; Wasserscheid, Peter; Steinrück, Hans-Peter; Maier, Florian (Journal of Molecular Liquids, 2019)
We report on surface investigations of cesium and tetraphenylphosphonium bis(trifluoromethylsulfonyl)imide (Cs[Tf2N], [PPh4][Tf2N]) molten salts and their mixtures. Depending on composition, these ionic compounds combine low melting points with exceptionally high thermal stability, and thus, exhibit considerably enlarged thermal operation windows compared to conventional ionic liquids. To elucidate their liquid-solid transition behavior in the near-surface region, temperature-dependent angle-resolved X-ray photoelectron spectroscopy (ARXPS) investigations were performed using our unique laboratory electron spectrometer DASSA ("Dual Analyzer System for Surface Analysis"), dedicated for investigations of macroscopic liquid samples. We followed temperature-induced changes in bulk and surface composition within the first nanometers of the neat salt melts and of Cs[Tf2N]: (PPh4][Tf2N]= 3 : 1 and 1 : 3 mixtures. In the mixtures, pronounced surface enrichment of Cs+ on expense of the bulky [PPne ions was found in the liquid state at temperatures close to the liquid-solid transition. In the solid state of Cs[Tf2N]-rich mixtures, [PPH4](+) completely vanishes from the near-surface region probed by XPS. (C) 2018 The Authors. Published by Elsevier B.V. This is an open access article under the CC BY license.
CRIS-Team WoS Importer:2019-02-27

Surface characterization of functionalized imidazolium-based ionic liquids - Kolbeck, Claudia; Killian, Manuela; Maier, Florian; Paape, Natalia; Wasserscheid, Peter; Steinrück, Hans-Peter (Langmuir, 2008)
The surface composition of oligo(ethylene glycol) ether functionalized bis(trifluoromethylsulfonyl)imide ionic liquids has been studied by means of X-ray photoelectron spectroscopy (XPS). For [Me(EG)MIM] [TfN], [Et(EG)MIM]-[TfN], and [Me(EG)MIM][Tf N], which vary by the number of ethylene glycol (EG) units (from 1 to 3), we have shown that the stoichiometry of the surface near region is in excellent agreement with the bulk stoichiometry, which confirms the high purity of the ionic liquid samples investigated and rules out pronounced surface orientation effects. This has been deduced from the experimental observation that the angle-resolved XP spectra of all elements present in the IL anions and cations (C, N, O, F, S) show identical signals in the bulk and surfaces sensitive geometry, i.e., at 0° and 70° emission angle, respectively. The relative intensity ratios of all elements were found to be in nearly perfect agreement with the nominal values for the individual ILs. In contrast to these findings, we identified surfaceactive impurities in [Me(EG)MIM]I, which is the starting material for the final anion exchange step to synthesize [Me(EG)MIM][Tf2N]. Sputtering of the surface led to a depletion of this layer, which however recovered with time. The buildup of this contamination is attributed to a surface enrichment of a minor bulk contamination that shows surface activity in the iodide melt. © 2008 American Chemical Society.

Surface chemistry of 2,3-dibromosubstituted norbornadiene/quadricyclane as molecular solar thermal energy storage system on Ni(111) - Bauer, Udo; Fromm, Lukas; Weiß, Cornelius; Späth, Florian; Bachmann, Philipp; Düll, Fabian; Steinhauer, Johann; Matysik, Sabine; Pominov, Arkadii; Görling, Andreas; Hirsch, Andreas; Steinrück, Hans-Peter; et al. (Journal of Chemical Physics, 2019)
Dwindling fossil fuels force humanity to search for new energy production routes. Besides energy generation, its storage is a crucial aspect. One promising approach is to store energy from the sun chemically in strained organic molecules, so-called molecular solar thermal (MOST) systems, which can release the stored energy catalytically. A prototypical MOST system is norbornadiene/quadricyclane (NBD/QC) whose energy release and surface chemistry need to be understood. Besides important key parameters such as molecular weight, endergonic reaction profiles, and sufficient quantum yields, the position of the absorption onset of NBD is crucial to cover preferably a large range of sunlight's spectrum. For this purpose, one typically derivatizes NBD with electron-donating and/or electron-accepting substituents. To keep the model system simple enough to be investigated with photoemission techniques, we introduced bromine atoms at the 2,3-position of both compounds. We study the adsorption behavior, energy release, and surface chemistry on Ni(111) using high-resolution X-ray photoelectron spectroscopy (HR-XPS), UV photoelectron spectroscopy, and density functional theory calculations. Both Br 2 -NBD and Br 2 -QC partially dissociate on the surface at ∼120 K, with Br 2 -QC being more stable. Several stable adsorption geometries for intact and dissociated species were calculated, and the most stable structures are determined for both molecules. By temperature-programmed HR-XPS, we were able to observe the conversion of Br 2 -QC to Br 2 -NBD in situ at 170 K. The decomposition of Br 2 -NBD starts at 190 K when C-Br bond cleavage occurs and benzene and methylidene are formed. For Br 2 -QC, the cleavage already occurs at 130 K when cycloreversion to Br 2 -NBD sets in.
CRIS-Team Scopus Importer:2019-05-28

Surface Chemistry of the Molecular Solar Thermal Energy Storage System 2,3-Dicyano-Norbornadiene/Quadricyclane on Ni(111) - Hemauer, Felix; Bauer, Udo; Fromm, Lukas; Weiß, Cornelius; Leng, Andreas; Bachmann, Philipp; Düll, Fabian; Steinhauer, Johann; Schwaab, Valentin; Grzonka, Robert; Hirsch, Andreas; Görling, Andreas; et al. (ChemPhysChem, 2022)
Molecular solar thermal (MOST) systems are a promising approach for the introduction of sustainable energy storage solutions. We investigated the feasibility of the dicyano-substituted norbornadiene/quadricyclane molecule pair on Ni(111) for catalytic model studies. This derivatization is known to lead to a desired bathochromic shift of the absorption maximum of the parent compound. In our experiments further favorable properties were found: At low temperatures, both molecules adsorb intact without any dissociation. In situ temperature-programmed HR-XPS experiments reveal the conversion of (CN)(2)-quadricyclane to (CN)(2)-norbornadiene under energy release between 175 and 260 K. The absence of other surface species due to side reactions indicates full isomerization. Further heating leads to the decomposition of the molecular framework into smaller carbonaceous fragments above 290 K and finally to amorphous structures, carbide and nitride above 400 K. DFT calculations gave insights into the adsorption geometries. (CN)(2)-norbornadiene is expected to interact stronger with the surface, with flat configurations being favorable. (CN)(2)-quadricyclane exhibits smaller adsorption energies with negligible differences for flat and side-on geometries. Simulated XP spectra are in good agreement with experimental findings further supporting the specific spectroscopic fingerprints for both valence isomers.
CRIS-Team WoS Importer:2022-07-08

Surface-confined two-step synthesis of the complex (ammine)(meso- tetraphenylporphyrinato)-zinc(II) on Ag(111) - Flechtner, Ken; Kretschmann, Andreas; Bradshaw, Liam R.; Walz, Marie-Madeleine; Steinrück, Hans-Peter; Gottfried, Michael (Journal of Physical Chemistry C, 2007)
We report the first example of a surface-confined two-step synthesis of axially coordinated metalloporphyrin complexes in an ultrahigh vacuum environment. Specifically, a monolayer of tetraphenylporphyrin on an Ag(111) surface was metalated with coadsorbed Zn atoms, and thereafter, NH ligands were attached to the metal centers. The surface reactions were monitored with X-ray photoelectron spectroscopy. The approach outlined in this work can be employed to produce and study adsorbates of various axially coordinated porphyrin complexes, including biologically relevant systems. © 2007 American Chemical Society.

Surface electronic properties of diamond - Ristein, Jürgen; Maier, Florian; Ley, Lothar; et al. (physica status solidi (a), 2000)
The influence of surface states, defects and adsorbates on the electronic properties of diamond surfaces are discussed. As far as surface states and reconstructions are concerned the principal crystallographic surfaces, (100), (111) and (110), are essentially understood in their adsorbate free form and also when terminated by hydrogen. The role of surface defects is addressed and the correlation between the position of the surface Fermi level and the concentration of surface defects is discussed quantitatively for p-type diamond. Hydrogen passivation leads to a negative electron affinity of diamond surfaces due to a dipole layer which is induced by the heteropolar carbon-hydrogen bonds of the surface atoms. This aspect is discussed quantitatively. Finally, an experiment in which photoelectron spectroscopy and in situ conductivity measurements were combined to elucidate the surface conductivity of diamond is described and analyzed.
UnivIS-Import:2015-03-09:Pub.2000.nat.dphy.IAP.exphys.surfac

Surface enrichment and depletion effects of ions dissolved in an ionic liquid: An X-ray photoelectron spectroscopy study - Maier, Florian; Gottfried, Michael; Rossa, Jürgen; Gerhard, Dirk; Schulz, Peter; Schwieger, Wilhelm; Wasserscheid, Peter; Steinrück, Hans-Peter (Angewandte Chemie International Edition, 2006)
(Graph Presented) Surfaces of ionic liquids: Angle-dependent X-ray photoelectron spectroscopy (XPS) shows that the surface composition of a solution of [Pt(NH)]Cl in the ionic liquid 1-ethyl-3-methylimidazolium ethyl sulfate ([EMIM][EtOSO]) deviates considerably from the bulk composition. The [Pt-(NH) ] cation is enriched on the surface at the expense of the [EMIM] cation (see picture), while the Cl anion is depleted to below the XPS detection limit. © 2006 Wiley-VCH Verlag GmbH & Co. KGaA.

Surface Enrichment in Equimolar Mixtures of Non-Functionalized and Functionalized Imidazolium-Based Ionic Liquids - Heller, Bettina; Kolbeck, Claudia; Niedermaier, Inga; Dommer, Sabine; Schatz, Jürgen; Hunt, Patricia; Maier, Florian; Steinrück, Hans-Peter (ChemPhysChem, 2018)
Keywords: density functional theory; electronic structure; angle-resolved X-ray photoelectron spectroscopy (ARXPS); ionic liquid mixture; surface science

Surface Enrichment in Equimolar Mixtures of Non-Functionalized and Functionalized Imidazolium-Based Ionic Liquids - Heller, Bettina; Kolbeck, Claudia; Niedermaier, Inga; Dommer, Sabine; Schatz, Jürgen; Hunt, Patricia; Maier, Florian; Steinrück, Hans-Peter (ChemPhysChem, 2018)
For equimolar mixtures of ionic liquids with imidazolium-based cations of very different electronic structure, we observe very pronounced surface enrichment effects by angle-resolved X-ray photoelectron spectroscopy (XPS). For a mixture with the same anion, that is, 1-methyl-3-octylimidazolium hexafluorophos phate+1,3-di(methoxy)imidazolium hexafluorophosphate ([C8C1Im][PF6]+[(MeO)2Im][PF6]), we find a strong enrichment of the octyl chain-containing [C8C1Im]+ cation and a correspond ing depletion of the [(MeO)2Im]+ cation in the topmost layer. For a mixture with different cations and anions, that is, [C8C1Im] [Tf2N]+[(MeO)2Im][PF6], we find both surface enrichment of the [C8C1Im]+ cation and the [Tf2N]@ (bis[(trifluoromethyl)sulfonyl] imide) anion, while [(MeO)2Im]+ and [PF6]@ are depleted from the surface. We propose that the observed behavior in these mixtures is due to a lowering of the surface tension by the enriched components. Interestingly, we observe pronounced differences in the chemical shifts of the imidazolium ring signals of the [(MeO)2Im]+ cations as compared to the non-functional ized cations. Calculations of the electronic structure and the intramolecular partial charge distribution of the cations contrib ute to interpreting these shifts for the two different cations.

Surface enrichment of Pt in Ga2O3 films grown on liquid Pt/Ga alloys - Grabau, Mathias; Krick Calderon, Sandra; Rietzler, Florian; Niedermaier, Inga; Taccardi, Nicola; Wasserscheid, Peter; Maier, Florian; Steinrück, Hans-Peter; Papp, Christian (Surface Science, 2016)
The formation of surface GaO films on liquid samples of Ga, and Pt-Ga alloys with 0.7 and 1.8 at.% Pt was examined using near-ambient pressure (NAP) X-ray photoelectron spectroscopy (XPS). Thickness, composition and growth of the oxide films were deduced as a function of temperature and Pt content of the alloys, in ultra-high vacuum and at oxygen pressures of 3 × 10, 3 × 10 and 1 mbar. We examined oxide layers up to a thickness of 37 Å. Different growth modes were found for oxidation at low and high pressures. The formed GaO oxide films showed an increased Pt content, while the pristine GaPt alloy showed a surface depletion of Pt at the examined temperatures. Upon growth of GaO on Pt/Ga alloys a linear increase of Pt content was observed, due to the incorporation of 3.6 at.% Pt in the GaO. The Pt content in GaO, at the examined temperatures and bulk Pt concentrations is found to be independent of pressure, temperature and the nominal Pt content of the metallic alloy.
Keywords: Bimetallic catalysts; Gallium oxide; NAP XPS; Pt/Ga alloys

Surface-functionalized ionic liquid crystal-supported ionic liquid phase materials: Ionic liquid crystals in mesopores - Kohler, Florian; Morain, Bruno; Weiß, Alexander; Laurin, Mathias; Libuda, Jörg; Wagner, Valentin; Melcher, Berthold Ulrich; Wang, Xinjiao; Meyer, Karsten; Wasserscheid, Peter (ChemPhysChem, 2011)
The influence of confinement on the ionic liquid crystal (ILC) [C C Im][OTf] is studied using differential scanning calorimetry (DSC), polarized optical microscopy (POM), and diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS). The ILC studied is supported on Si-based powders and glasses with pore sizes ranging from 11 to 50 nm. The temperature of the solid-to-liquid-crystalline phase transition seems mostly unaffected by the confinement, whereas the temperature of the liquid-crystalline-to-liquid phase transition is depressed for smaller pore sizes. A contact layer with a thickness in the order of 2 nm is identified. The contact layer exhibits a phase transition at a temperature 30 K lower than the solid-to-liquid-crystalline phase transition observed for the neat ILC. For applications within the "supported ionic liquid phase (SILP)" concept, the experiments show that in pores of diameter 50 nm a pore filling of α>0.4 is sufficient to reproduce the phase transitions of the neat ILC. © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Surface-Induced Changes in the Thermochromic Transformation of an Ionic Liquid Cobalt Thiocyanate Complex - May, Benjamin; Hoenle, Michael; Heller, Bettina; Greco, Francesco; Bhuin, Radha Gobinda; Steinrück, Hans-Peter; Maier, Florian (Journal of Physical Chemistry Letters, 2017)
We demonstrate that a thermodynamic. complex equilibrium within an ionic liquid film can be significantly influenced by the presence of the liquid-vacuum interface. Using surface sensitive X-ray photoelectron spectroscopy, we find that the temperature-driven transition from the blue-colored tetrahedral [Co(II) (NCS)(4)](2-) to the red-colored octahedral [Co(II) (NCS)(6)](4-) complex already occurs within the outermost nanometers at around +4 degrees C as compared with -25 degrees C in the bulk. This thermochromic transformation in the near-surface region goes along with a loss in preferential surface orientation of free [SCN](-) anions and with a pronounced decrease in the complex density; both effects are attributed to the formation of a weakly bound solvation shell around the [Co(II) (NCS)(6)](4-) anion, leading to an effective complex dilution. Our results are not only relevant for high-surface area thin film systems, such as in sensor and catalysis applications, but also shed light on the role of ionic liquid surfaces in particular and liquid surfaces in general.

Surface-Mediated in Situ Metalation of Porphyrins at the Solid-Vacuum Interface - Marbach, Hubertus (Accounts of Chemical Research, 2015)
The investigation of porphyrin derivatives at the solid-vacuum interface has become a vivid research field with the prospect to tailor functional molecular architectures and as prototype examples to study the fundamental properties of porphyrin derivatives in regard to their vital role in many natural processes. The functional properties of the porphyrin derivatives are mainly determined by the central metal atom. Thus, the recent exploration of the surface-confined in situ metalation of porphyrins is an important step toward the realization of molecule-based functional devices. The corresponding metalation reaction of free base porphyrin derivatives can be conveniently realized in situ in ultrahigh vacuum by post- or predeposition of metal atoms or directly with substrate atoms in the so-called self-metalation. Moderate heating above room temperature (RT) might be necessary either to realize the transport of the metal to the porphyrin via diffusion or to overcome an activation barrier determined by the redox reaction itself. Surface science techniques like scanning tunneling microscopy (STM), X-ray photoelectron spectroscopy (XPS), and temperature-programmed desorption (TPD) are powerful tools to scrutinize the reaction and give valuable insights into the metalation process. For example, the completed metalation can be reflected in an enhanced apparent height of the corresponding porphyrin in STM or can be evidenced by characteristic changes in the N 1s region in XPS. These signatures allow monitoring of the progress of the metalation, and it was found that the reaction generally proceeds with very high yield. Surface diffusion of the coadsorbed metal atoms mediates the reaction and is crucial for the high yields of the corresponding reactions with pre- and postadsorbed metals. It was also demonstrated that the completed metalation can indeed significantly alter the adsorption behavior and the electronic properties and thus the functionality of the porphyrin molecules. These alterations can be used to monitor the kinetics of a particular porphyrin self-metalation reaction by STM and to estimate the activation barrier for that reaction based on isothermal measurements at different temperatures. Also TPD measurements of the H2 and D2 signals allow for the determination of corresponding activation energies for the metalation of free base porphyrins and their deuterized analogues. Gas phase DFT calculations of the metalation of the free base porphyrin macrocycle identify intermediate reaction steps with the transfer of the first hydrogen atom to the metal center being the main barrier to overcome. The values from these calculations are in fair agreement with experimentally determined ones. However, TPD based results indicate that exchanges of deuterium and hydrogen between the central nitrogen and the surface occur, which indicate an active role of the surface and challenge the findings from gas phase DFT. The in situ metalation of porphyrins at the solid-vacuum interface is established as a novel and convenient route to tailor functional molecular architectures. With different surface science techniques detailed insights into the surface-mediated metalation reaction were achieved for this class of prototype functional molecules.
EAM Import::2019-03-12

Surface oxidation-induced restructuring of liquid Pd-Ga SCALMS model catalysts - Wittkämper, Haiko; Maisel, Sven; Moritz, Michael; Grabau, Mathias; Görling, Andreas; Steinrück, Hans-Peter; Papp, Christian (Physical Chemistry Chemical Physics, 2021)
We have examined model systems for the recently reported Pd-Ga Supported Catalytically Active Liquid Metal Solutions (SCALMS) catalysts using near-ambient pressure X-ray photoelectron spectroscopy (NAP-XPS) under oxidizing conditions. Gallium is known to be highly prone to oxidation and in practical applications, handling of the catalyst material in air or the presence of traces of oxygen in the reactor are unavoidable. Therefore, we expect our results to be of high relevance for the application of Ga-based SCALMS catalysts. Pd-Ga alloy samples of 1.3 and 1.8 at% Pd content were exposed to molecular oxygen at different pressures between 3 x 10(-7) and 1 mbar and a temperature of 550 K. We observe the formation of wetting Ga2O3 films upon exposure to molecular oxygen. The absolute thicknesses of the oxide films depend on oxygen pressure, with values ranging from similar to 12 angstrom at 10(-7) to 10(-5) mbar to similar to 50 angstrom at 1 mbar. The formed metal-oxide interface leads to a redistribution of Pd, which accumulates at the boundary between the wetting oxide film and the metal substrate as a response to the oxide film growth. A maximum Pd 3d intensity is observed at an oxide thickness of 5 angstrom. For thicker films, the Pd 3d signal and the Ga 3d signal ascribed to the metallic substrate decrease in parallel, which is attributed to the oxide layer growing on top of the liquid metal alloy. From this observation, we conclude that no significant amount of Pd is bound in the newly formed oxide film. Density-functional theory (DFT) calculations support the experimental observations.
CRIS-Team WoS Importer:2021-08-06

Surface polymerization of poly(p -phenylene-terephthalamide) on Ag(111) investigated by X-ray photoelectron spectroscopy and scanning tunneling microscopy - Schmitz, Christoph H.; Schmid, Martin; Gärtner, Stefan; Steinrück, Hans-Peter; Gottfried, Michael; Sokolowski, Moritz (Journal of Physical Chemistry C, 2011)
The formation of poly(p-phenylene-terephthalamide) (PPTA) by surface-assisted polymerization of terephthaloyl chloride (TPC) and p-phenylenediamine (PPD) on Ag(111) has been studied by X-ray photoelectron spectroscopy (XPS) and scanning tunneling microscopy (STM). Analysis of the XPS data reveals that the polymer is formed in the (sub-) monolayer regime already at room temperature. Upon vacuum deposition of TPC onto the single-crystal surface, the carbon-chlorine bond is cleaved, and the polymerization proceeds via a p-phenylene dicarbonyl species, which is presumably surface stabilized. This contrasts the reaction mechanism in solution, where the chlorine atom is expelled after a nucleophilic attack by the amine group. Annealing of the sample leads to desorption of residual PPD monomers, lateral ordering of the polymer chains, and further progress of the polymerization that can be followed by XPS. The chain length distribution of the polyamide, as extracted from the XP spectra, is consistent with the typical chain lengths found in STM images. © 2011 American Chemical Society.

Surface Porphyrins Metalate with Zn Ions from Solution - Franke, Matthias; Marchini, Florencia; Steinrück, Hans-Peter; Lytken, Ole; Williams, Federico J. (Journal of Physical Chemistry Letters, 2015)
Controlling the metalation of surface porphyrins is a critical process in porphyrin-based devices. Indeed, surface porphyrins are known to metalate in ultrahigh vacuum from codeposited metal atoms or substrate atoms; however, it is not yet known if surface porphyrins could metalate from ions in solution, that is, the most likely environment for porphyrin-based devices. Using X-ray photoelectron spectroscopy we have studied the metalation of monolayers and multilayers of a free-base tetraphenyl porphyrin adsorbed on Au(111) with ions in solution. We found that full metalation with Zn can be achieved already at room temperature in contrast with the elevated temperatures required for metalation with codeposited metal atoms.
Keywords: free-base porphyrin; metalation; surface; XPS; ZnTPP

Surface Reaction of CO on Carbide-Modified Mo(110) - Gleichweit, Christoph; Neiß, Christian; Maisel, Sven; Bauer, Udo; Späth, Florian; Höfert, Oliver; Görling, Andreas; Steinrück, Hans-Peter; Papp, Christian (Journal of Physical Chemistry C, 2017)
The adsorption and reaction of CO on a monolayer carbide and a bulk carbide, prepared on Mo(110), was studied with synchrotron-based XPS, TPD, and density-functional calculations using slab models. In the experiments on the monolayer carbide, we find two CO species at 140 K, with a saturation coverage of similar to 0.7 ML, while on the bulk carbide, Mo2C, three molecular adsorption states are found, showing a similar total coverage of similar to 0.7 ML at saturation. In addition, CO partly dissociates on both surfaces (monolayer carbide: 7%, bulk carbide: 15%). The calculations on the monolayer carbide show that the adsorption of CO on Mo sites is most stable. At increased coverages, several different adsorption sites on the monolayer carbide become possible. From the core level shifts, an assignment to the experimentally found species becomes available. Upon heating, we find on both carbides the competing processes of desorption, interconversion of different CO species, and dissociation of CO. The detailed quantitative analysis of these processes shows that desorption and dissociation to atomic oxygen and carbon is completed at similar to 400 K on the monolayer carbide and similar to 450 K on the bulk carbide; in both cases, about 35% (0.25 ML) of the initially adsorbed CO decomposes upon heating. Above 800 K, atomic carbon and oxygen desorb associatively, and at 1200 K the carbide surfaces are restore

Surface Reactions and Electronic Structure of Carboxylic Acid Porphyrins Adsorbed on TiO2(110) - Wechsler, Daniel; Vensaus, Priscila; Tsud, Nataliya; Steinrück, Hans-Peter; Lytken, Ole; Williams, Federico J. (Journal of Physical Chemistry C, 2021)
We studied the coverage- and temperature-dependent proton transfer and self-metalation reactions of tetraphenylporphyrin molecules containing a carboxyl functional group (MCTPP) on rutile TiO2(110) surfaces. Furthermore, we also determined changes in the molecular geometric and electronic structures as a function of coverage and temperature. The investigation was carried out by means of synchrotron radiation X-ray photoelectron spectroscopy and near-edge X-ray absorption fine structure measurements. We found that at a coverage of 0.2 ML, most MCTPP molecules adsorb with the iminic nitrogen atoms protonated; at 0.5 ML, a decrease in the proportion of protonated molecules is observed; and at a monolayer coverage, most molecules are not protonated. Raising the temperature to above 500 K, where hydroxyl groups recombine to desorb as water, causes a decrease in the number of protonated porphyrin molecules. In roughly the same temperature range, we start to observe the self-metalation of the free-base molecules, which produces flat-lying titanyl porphyrin molecules on the TiO2(110) surface. This reaction is found to be coverage dependent: For 0.2 ML, it starts above 450 K, and for 1.0 ML, temperatures above 650 K are needed. Metalation shifts the surface state located in the semiconductor band gap to lower energies. Our results suggest that protonation and self-metalation depend on the proximity of the macrocycle to the surface and show that metalation modifies the molecular occupied and vacant electronic states.
CRIS-Team WoS Importer:2021-05-07

Surface reactions of complex molecular systems: From supported graphene to hydrogen storage molecules - Steinrück, Hans-Peter (ABSTRACTS OF PAPERS OF THE AMERICAN CHEMICAL SOCIETY, 2019)
CRIS-Team WoS Importer:2020-04-28

Surface Reactions of Dicyclohexylmethane on Pt(111) - Gleichweit, Christoph; Amende, Maximilian; Höfert, Oliver; Xu, Tao; Späth, Florian; Brückner, Nicole; Wasserscheid, Peter; Libuda, Jörg; Steinrück, Hans-Peter; Papp, Christian (Journal of Physical Chemistry C, 2015)
We investigated the surface reaction of the liquid organic hydrogen carrier dicydohexylmethane (DCHM) on Pt(111) in ultrahigh vacuum by high-resolution X-ray photoelectron spectroscopy, temperature-programmed desorption, near-edge X-ray absorption fine structure, and infrared reflection absorption spectroscopy. Additionally, the hydrogen-lean molecule diphenylmethane and the relevant molecular fragments of DCHM, methylcyclohexane, and toluene were studied to elucidate the reaction steps of DCHM. We find dehydrogenation of DCHM in the range of 200-260 K, to form a double-sided pi-allylic species coadsorbed with hydrogen. Subsequently, similar to 30% of the molecules desorb, and for similar to 70%, one of the pi-allyls reacts to a phenyl group between 260 and 330 K, accompanied by associative hydrogen desorption. Above 360 K, the second pi-allylic species is dehydrogenated to a phenyl ring. This is accompanied by C-H bond scission at the methylene group, which is an unwanted decomposition step in the hydrogen storage cycle, as it alters the original hydrogen carrier DCHM. Above 450 K, we find further decomposition steps which we assign to C-H abstraction at the phenyl rings.

Surface Reactions of Low-Energy Argon Ions with Organometallic Precursors - Bilgilisoy, Elif; Thorman, Rachel M.; Yu, Jo Chi; Dunn, Timothy B.; Marbach, Hubertus; Mcelwee-White, Lisa; Fairbrother, D. Howard (Journal of Physical Chemistry C, 2020)
A combination of in situ X-ray photoelectron spectroscopy and mass spectrometry has been used to elucidate the elementary surface reactions initiated by the interaction of low-energy (860 eV) argon ions with three organometallic precursors [Ru(CO)4I2, Co(CO)3NO, and WN(NMe2)3]. The effects of ion exposure on each precursor can be described by a largely sequential series of surface reactions. The initial step involves ion-induced decomposition of the precursor to create a nonvolatile deposit, followed by physical sputtering of the atoms in the deposit. For the precursors that contain CO ligands [Ru(CO)4I2 and Co(CO)3NO], ion-induced decomposition is accompanied by desorption of the majority of the CO groups. This is in marked contrast to previous studies of low-energy electron-induced reactions with the same precursors where precursor decomposition yielded only partial desorption of the CO ligands. Conversely, argon ion bombardment of WN(NMe2)3 led to decomposition without ligand loss. For all three precursors, the initial ion-induced decomposition step was not accompanied by significant desorption of intact precursor molecules, while during subsequent physical sputtering of the deposited atoms, ligand-derived organic and inorganic contaminants were removed at higher rates than the metals. This indicates that controlled ion beam deposition conditions could be used to produce deposits with high metal contents from all three precursors. Comparison of low-energy electron-induced reactions of these three precursors with results of this investigation indicates that secondary electrons do not play an important role in the deposition process, but rather precursor decomposition occurs via efficient ion-molecule energy transfer. These reactions are discussed in the context of focused ion beam-induced deposition.
CRIS-Team Scopus Importer:2020-11-20

Surface science and liquid phase investigations of oxanorbornadiene/oxaquadricyclane ester derivatives as molecular solar thermal energy storage systems on Pt(111) - Hemauer, Felix; Krappmann, Daniel; Schwaab, Valentin; Hussain, Zarah; Freiberger, Eva Marie; Waleska-Wellnhofer, Natalie; Franz, Evanie; Hampel, Frank; Brummel, Olaf; Libuda, Jörg; Hirsch, Andreas; Steinrück, Hans-Peter; et al. (Journal of Chemical Physics, 2023)
The transition to renewable energy sources comes along with the search for new energy storage solutions. Molecular solar thermal systems directly harvest and store solar energy in a chemical manner. By a suitable molecular design, a higher overall efficiency can be achieved. In this study, we investigate the surface chemistry of oxa-norbornadiene/quadricyclane derivatives on a Pt(111) surface. Specifically, we focus on the energy storage and release properties of molecules that are substituted with ester moieties of different sizes. For our model catalytic approach, synchrotron radiation-based x-ray photoelectron spectroscopy measurements were conducted in ultra-high vacuum (UHV) and correlated with the catalytic behavior in the liquid phase monitored by photochemical infrared reflection absorption spectroscopy. The differences in their spectral appearance enabled us to unambiguously differentiate the energy-lean and energy-rich isomers and decomposition products. Next to qualitative information on the adsorption motifs, temperature-programmed experiments allowed for the observation of thermally induced reactions and the deduction of the related reaction pathways. We analyzed the selectivity of the cycloreversion reaction from the energy-rich quadricyclane derivative to its energy-lean norbornadiene isomer and competing processes, such as desorption and decomposition. For the 2,3-bis(methylester)-substitution, the cycloreversion reaction was found to occur between 310 and 340 K, while the thermal stability limit of the compounds was determined to be 380 K. The larger 2,3-bis(benzylester) derivatives have a lower apparent adsorption energy and a decomposition onset already at 135 K. In the liquid phase (in acetonitrile), we determined the rate constants for the cycloreversion reaction on Pt(111) to k = 5.3 × 10-4 s-1 for the 2,3-bis(methylester)-substitution and k = 6.3 × 10-4 s-1 for the 2,3-bis(benzylester) derivative. The selectivities were of >99% and 98% for the two molecules, respectively. The difference in the catalytic behavior of Pt(111) for both derivatives is less pronounced in the liquid phase than in UHV, which we attribute to the passivation of the Pt(111) surface by carbonaceous species under ambient conditions.
CRIS-Team Scopus Importer:2023-09-01

Surface science and model catalysis with ionic liquid-modified materials - Steinrück, Hans-Peter; Libuda, Jörg; Wasserscheid, Peter; Cremer, Till; Kolbeck, Claudia; Laurin, Mathias; Maier, Florian; Sobota, Marek; Schulz, Peter; Stark, Michael Werner (Advanced Materials, 2011)
Materials making use of thin ionic liquid (IL) films as support-modifying functional layer open up a variety of new possibilities in heterogeneous catalysis, which range from the tailoring of gas-surface interactions to the immobilization of molecularly defined reactive sites. The present report reviews recent progress towards an understanding of "supported ionic liquid phase (SILP)" and "solid catalysts with ionic liquid layer (SCILL)" materials at the microscopic level, using a surface science and model catalysis type of approach. Thin film IL systems can be prepared not only ex-situ, but also in-situ under ultrahigh vacuum (UHV) conditions using atomically well-defined surfaces as substrates, for example by physical vapor deposition (PVD). Due to their low vapor pressure, these systems can be studied in UHV using the full spectrum of surface science techniques. We discuss general strategies and considerations of this approach and exemplify the information available from complementary methods, specifically photoelectron spectroscopy and surface vibrational spectroscopy. Copyright © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Surface science goes liquid ! - Steinrück, Hans-Peter (Surface Science, 2010)
Ionic liquids are a new class of materials with most interesting properties. They are liquid at room temperature, but have a negligible vapour pressure. Consequently they can, in contrast to normal liquids, be investigated by all UHV-based methods of surface science. This allows to determine their properties with the same atomic level accuracy that is presently common for solid surfaces and conventional adsorbate systems. Apart from the investigation of the specific properties of ionic liquids, which are relevant for many applications, this also opens the possibility to obtain more detailed insight in the general physical and chemical properties of liquids. In that sense it opens the door to a new chapter of surface science - "Ionic Liquid Surface Science". © 2010 Elsevier B.V. All rights reserved.

Surface sensitivity in scanning transmission x-ray microspectroscopy using secondary electron detection - Hub, Christian; Wenzel, Stephan; Raabe, J.; Ade, Harald; Fink, Rainer (Review of Scientific Instruments, 2010)
The successful integration of electron detection into an existing scanning transmission x-ray microspectroscope (STXM) at the Swiss Light Source is demonstrated. In conventional x-ray detection using a photomultiplier, STXM offers mainly bulk sensitivity combined with high lateral resolution. However, by implementation of a channeltron electron multiplier, the surface sensitivity can be established by the detection of secondary electrons emitted from the sample upon resonant excitation. We describe the experimental setup and discuss several relevant aspects, in particular the schemes to correct for self-absorption in the specimen due to back illumination in case of thicker films. © 2010 American Institute of Physics.

Surface sites on Pt-CeO2 mixed oxide catalysts probed by CO adsorption: a synchrotron radiation photoelectron spectroscopy study - Neitzel, Armin; Lykhach, Yaroslava; Skala, Tomas; Tsud, Nataliya; Vorokhta, Mykhailo; Mazur, Daniel; Prince, Kevin C.; Matolin, Vladimir; Libuda, Jörg (Physical Chemistry Chemical Physics, 2014)
By means of synchrotron radiation photoemission spectroscopy, we have investigated Pt-CeO2 mixed oxide films prepared on CeO2(111)/Cu(111). Using CO molecules as a probe, we associate the corresponding surface species with specific surface sites. This allows us to identify the changes in the composition and morphology of Pt-CeO2 mixed oxide films caused by annealing in an ultrahigh vacuum. Specifically, two peaks in C 1s spectra at 289.4 and 291.2 eV, associated with tridentate and bidentate carbonate species, are formed on the nanostructured stoichiometric CeO2 film. The peak at 290.5-291.0 eV in the C 1s spectra indicates the onset of restructuring, i.e. coarsening, of the Pt-CeO2 film. This peak is associated with a carbonate species formed near an oxygen vacancy. The onset of cerium oxide reduction is indicated by the peak at 287.8-288.0 eV associated with carbonite species formed near Ce3+ cations. The development of surface species on the Pt-CeO2 mixed oxides suggests that restructuring of the films occurs above 300 K irrespective of Pt loadings. We do not find any adsorbed CO species associated with Pt4+ or Pt2+. The onset of Pt2+ reduction is indicated by the peak at 286.9 eV in the C 1s spectra due to CO adsorption on metallic Pt particles. The thermal stability of Pt2+ in Pt-CeO2 mixed oxide depends on Pt loading. We find excellent stability of Pt2+ for 12% Pt content in the CeO2 film, whereas at a Pt concentration of 25% in the CeO2 film, a large fraction of the Pt2+ is converted into metallic Pt particles above 300 K.

Surface structure analysis based on the exclusive use of the specular LEED spot - A theoretical study - Held, Georg; Steinrück, Hans-Peter (Surface Science, 2001)
The exclusive use of the specularly reflected beam (the (0,0) spot) may be a more practical way of collecting data for a LEED I-V structure analysis under certain experimental conditions. In this paper we discuss the special properties of the (0,0) spot intensity and test its sensitivity towards structural changes for the model system CO/Ni(1 1 1) within the framework of a R factor analysis. It is found that the (0,0) spot can, indeed, be used for a reliable structure determination if the energy range is increased by collecting data at different polar and azimuthal angles of incidence. The R factor contrast is, however, reduced with respect to a conventional LEED I-V analysis. © 2001 Elsevier Science B.V. All rights reserved.

Surface structure characterization by photoelectron holography - Zharnikov, M.; Weinelt, Martin; Zebisch, P.; Steinrück, Hans-Peter (Thin Solid Films, 1996)
The applicability of photoelectron holography to determine the structure of clean and adsorbate-covered metal surfaces is investigated. The real space structure of various systems is reconstructed from photoelectron diffraction patterns at various kinetic energies using (1) the single wavenumber and (2) the multiple wavenumber reconstruction algorithm. It is demonstrated that adsorption sites can be unequivocally identified using the multiple wavenumber approach.

Surface Studies on the Energy Release of the MOST System 2-Carbethoxy-3-Phenyl-Norbornadiene/Quadricyclane (PENBD/PEQC) on Pt(111) and Ni(111) - Hemauer, Felix; Schwaab, Valentin; Freiberger, Eva Marie; Waleska, Natalie; Leng, Andreas; Weiß, Cornelius; Steinhauer, Johann; Düll, Fabian; Bachmann, Philipp; Hirsch, Andreas; Steinrück, Hans-Peter; Papp, Christian (Chemistry - A European Journal, 2023)
Novel energy-storage solutions are necessary for the transition from fossil to renewable energy sources. Auspicious candidates are so-called molecular solar thermal (MOST) systems. In our study, we investigate the surface chemistry of a derivatized norbornadiene/quadricyclane molecule pair. By using suitable push–pull substituents, a bathochromic shift of the absorption onset is achieved, allowing a greater overlap with the solar spectrum. Specifically, the adsorption and thermally induced reactions of 2-carbethoxy-3-phenyl-norbornadiene/quadricyclane are assessed on Pt(111) and Ni(111) as model catalyst surfaces by synchrotron radiation-based X-ray photoelectron spectroscopy (XPS). Comparison of the respective XP spectra enables the distinction of the energy-rich molecule from its energy-lean counterpart and allows qualitative information on the adsorption motifs to be derived. Monitoring the quantitative cycloreversion between 140 and 230 K spectroscopically demonstrates the release of the stored energy to be successfully triggered on Pt(111). Heating to above 300 K leads to fragmentation of the molecular framework. On Ni(111), no conversion of the energy-rich compound takes place. The individual decomposition pathways of the two isomers begin at 160 and 180 K, respectively. Pronounced desorption of almost the entire surface coverage only occurs for the energy-lean molecule on Ni(111) above 280 K; this suggests weakly bound species. The correlation between adsorption motif and desorption behavior is important for applications of MOST systems in heterogeneously catalyzed processes.
CRIS-Team Scopus Importer:2023-03-31
Keywords: catalysis; energy storage; MOST system; photoelectron spectroscopy; surface reactions

Surface tension and viscosity of binary ionic liquid mixtures from high vacuum up to pressures of 10 MPa - Zhai, Ziwen; Paap, Ulrike; Gezmis, Afra; Maier, Florian; Steinrück, Hans-Peter; Koller, Thomas Manfred (Journal of Molecular Liquids, 2023)
In the present study, we investigated the surface tension and viscosity of binary ionic liquid (IL) mixtures at or close to saturation conditions from high vacuum conditions up to elevated pressures. We studied four different mixtures of 1,3-bis(2-(2-methoxyethoxy)ethyl)imida-zolium iodide ([(mPEG2)2Im]I) and 1-methyl-3-octylimidazolium hexafluorophosphate ([C8C1Im][PF6]) with [C8C1Im][PF6] mole contents between (4.6 and 49.8) mol%. Argon (Ar) gas of relatively low solubility was used to vary the applied pressure between (0.1 and 10) MPa. For temperatures from (303 to 363) K, the surface tension obtained by the pendant-drop (PD) method was used to determine the saturated liquid viscosity from surface light scattering (SLS). These studies are complemented by additional PD measurements under ultraclean high vacuum (HV) conditions in a second setup. At about 0.1 MPa, the surface tension and viscosity of the IL mixtures show negative deviations from a linear mixing rule based on the molar bulk composition, which is more pronounced at lower temperatures. The surface tension values at 0.1 MPa and under HV agree with each other and lie closer to the values of [C8C1Im][PF6] that has a distinctly lower surface tension than [(mPEG2)2Im]I and is surface-active. For the equimolar IL mixture at 303 K, an increase in the pressure up to 10 MPa has a negligible influence on the viscosity, while it causes a distinct reduction in the surface tension compared to the value at 0.1 MPa. The pressure-dependent relative change for the viscosity of the ternary mixtures of the two ILs and Ar corresponds well to the mean values of the positive and negative relative changes observed for the two binary [(mPEG2)2Im]I-Ar and [C8C1Im][PF6]-Ar subsystems, respectively. For the surface tension, the absolute changes at a given pressure are very similar regardless of the IL bulk composition, suggesting a similar weak Ar enrichment at the gas–liquid interface.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Ionic liquid mixtures; Pendant-drop method; Pressure; Surface light scattering; Surface tension; Viscosity

Surface Tension and Viscosity of Binary Mixtures of the Fluorinated and Non-fluorinated Ionic Liquids [PFBMIm][PF6] and [C4C1Im][PF6] by the Pendant Drop Method and Surface Light Scattering - Koller, Thomas Manfred; Lenahan, Frances; Schmidt, Patrick; Klein, Tobias; Mehler, Julian; Maier, Florian; Rausch, Michael Heinrich; Wasserscheid, Peter; Steinrück, Hans-Peter; Fröba, Andreas Paul (International Journal of Thermophysics, 2020)
Mixtures of fluorinated and non-fluorinated ionic liquids (ILs) show a distinct structural organization in the bulk and at the surface. To understand how such microscopic effects influence the macroscopic bulk and surface properties of IL mixtures, knowledge of corresponding thermophysical properties including viscosity and surface tension is required yet lacking. With the intention of investigating surface enrichment effects of the fluorinated IL [PFBMIm][PF6] (3-methyl-1-(3,3,4,4,4-pentafluorobutyl)imidazolium hexafluorophosphate) in mixtures with the structurally similar, non-fluorinated IL [C4C1Im][PF6] (1-butyl-3-methylimidazolium hexafluorophosphate) observed with angle-resolved X-ray photoelectron spectroscopy (ARXPS), the pendant drop method and surface light scattering (SLS) were applied in the present study to determine surface tension and dynamic viscosity between (293 and 368) K. By adding small amounts of [PFBMIm][PF6] up to 9 mol %, a distinct increase in the viscosity and decrease in the surface tension of the mixtures relative to the properties of pure [C4C1Im][PF6] was found. This behavior reflects the nanosegregated structure in the bulk and at the surface of the binary IL mixtures. Using the results about the pronounced surface enrichment of the fluorinated chain of [PFBMIm][PF6] quantified by ARXPS, a linear mixing rule for the surface tension of the IL mixtures based on the surface tensions of the pure ILs and the surface concentration of their most surface-active groups is suggested.
CRIS-Team Scopus Importer:2020-08-21
Keywords: Ionic liquids; Mixtures; Pendant drop method; Surface light scattering; Surface tension; Viscosity

Switching adsorption and growth behavior of ultrathin [C(2)C(1)lm][OTf] films on Au(111) by Pd deposition - Rietzler, Florian; May, Benjamin; Steinrück, Hans-Peter; Maier, Florian (Physical Chemistry Chemical Physics, 2016)
Combining in vacuo deposition of ultrathin ionic liquid (UTIL) films with angle-resolved X-ray photoelectron spectroscopy (ARXPS), we demonstrate that by deposition of submonolayer amounts of Pd onto Au(111) the initial growth mode of the ionic liquid (IL) 1-ethyl-3-methylimidazolium trifluoro-methanesulfonate ([C(2)C(1)lm][OTf]) can be switched from three-dimensional (3D) to two-dimensional (2D) growth, that is, from non-wetting to wetting. On clean Au(111), pronounced 3D growth occurs on top of an initially formed 2D wetting layer with cations and anions next to each other in a checkerboard arrangement. After pre- or postdeposition of only 0.7 ML Pd, two-dimensional layer-by-layer growth is found, which is attributed to strong attractive interactions between [C(2)C(1)lm][OTf] and surface Pd. For Pd post deposition onto the IL, the ARXPS data revealed particularly strong interactions between the dialkylimidazolium cation and Pd atoms, which considerably reduce the regular surface alloying of Pd with the Au substrate stabilizing Pd at the metal surface. In the context of heterogeneous catalysis using the SCILL (solid catalyst coated with ionic liquid layer) concept, these results directly provide a possible explanation on the molecular level for the beneficial influence of the IL layer in case of heterogeneous metal alloy catalysts.

Switching behaviour of individual Ag-TCNQ nanowires: an in situ transmission electron microscopy study - Ran, Ke; Rösner, Benedikt; Butz, Benjamin; Fink, Rainer; Spiecker, Erdmann (Nanotechnology, 2016)
The organic semiconductor silver-tetracyanoquinodimethane (Ag-TCNQ) exhibits electrical switching and memory characteristics. Employing a scanning tunnelling microscopy setup inside a transmission electron microscope, the switching behaviour of individual Ag-TCNQ nanowires (NWs) is investigated in detail. For a large number of NWs, the switching between a high (OFF) and a low (ON) resistance state was successfully stimulated by negative bias sweeps. Fitting the experimental I-V curves with a Schottky emission function makes the switching features prominent and thus enables a direct evaluation of the switching process. A memory cycle including writing, reading and erasing features is demonstrated at an individual NW. Moreover, electronic failure mechanisms due to Joule heating are discussed. These findings have a significant impact on our understanding of the switching behaviour of Ag-TCNQ.
Keywords: Ag-TCNQ nanowires; in situ transmission electron microscopy; electrical switching; organic memory device; organic electronics

Synthesis, characterization, and photoinduced energy and electron transfer in a supramolecular tetrakis (ruthenium(II) phthalocyanine) perylenediimide pentad - Jimenez, Angel J.; Grimm, Bruno; Gunderson, Victoria L.; Vagnini, Michael T.; Krick Calderon, Sandra; Salome Rodriguez-Morgade, M.; Wasielewski, Michael R.; Guldi, Dirk Michael; Torres, Tomas (Chemistry - A European Journal, 2011)
Metal coordination was probed as a versatile approach for designing a novel electron donor/acceptor hybrid [PDIpy Ru(CO)Pc ] (1), in which four pyridines placed at the bay region of a perylenediimides (PDIpy ) coordinate with four ruthenium phthalocyanine units [Ru(CO)Pc]. This structural motif was expected to promote strong electronic coupling between the electron donors and the electron acceptor, a hypothesis that was confirmed in a full-fledged physicochemical investigation focusing on the ground and excited state reactivities. As far as the ground state is concerned, absorption and electrochemical assays indeed reveal a notable redistribution of electron density, that is, from the electron-donating [Ru(CO)Pc] to the electron-accepting PDIpy . The most important thing to note in this context is that both the [Ru(CO)Pc] oxidation and the PDIpy reduction are rendered more difficult in 1 than in the individual building blocks. Likewise, in the excited state, strong electronic communication is the inception for a rapid charge-transfer process in photoexcited 1. Regardless of exciting [Ru(CO)Pc] or PDIpy , spectral characteristics of the [RuPc] radical cation (broad absorptive features from 425 to 600 nm with a maximum at 575 nm, as well as a band centered at 725 nm) and of the PDI radical anion (780 nm maximum) emerge. The correspondingly formed radical ion pair state lasts for up to several hundred picoseconds in toluene, for example. On the other hand, employing more polar solvents, such as dichloromethane, destabilizes the radical ion pair state. © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Synthetic Image Rendering Solves Annotation Problem in Deep Learning Nanoparticle Segmentation - Mill, Leonid; Wolff, David; Gerrits, Nele; Philipp, Patrick; Kling, Lasse; Vollnhals, Florian; Ignatenko, Andrew; Jaremenko, Christian; Huang, Yixing; De Castro, Olivier; Audinot, Jean Nicolas; Nelissen, Inge; et al. (Small Methods, 2021)
Nanoparticles occur in various environments as a consequence of man-made processes, which raises concerns about their impact on the environment and human health. To allow for proper risk assessment, a precise and statistically relevant analysis of particle characteristics (such as size, shape, and composition) is required that would greatly benefit from automated image analysis procedures. While deep learning shows impressive results in object detection tasks, its applicability is limited by the amount of representative, experimentally collected and manually annotated training data. Here, an elegant, flexible, and versatile method to bypass this costly and tedious data acquisition process is presented. It shows that using a rendering software allows to generate realistic, synthetic training data to train a state-of-the art deep neural network. Using this approach, a segmentation accuracy can be derived that is comparable to man-made annotations for toxicologically relevant metal-oxide nanoparticle ensembles which were chosen as examples. The presented study paves the way toward the use of deep learning for automated, high-throughput particle detection in a variety of imaging techniques such as in microscopies and spectroscopies, for a wide range of applications, including the detection of micro- and nanoplastic particles in water and tissue samples.
CRIS-Team Scopus Importer:2021-05-14
Keywords: helium ion microscopy; image analysis; machine learning; nanoparticles; segmentation; toxicology

Systematics of the 4f energies in a series of rare-earth organic complexes determined by resonant photoemission - Fink, Rainer; Umbach, Eberhard; et al. (Physical Review B, 2004)
We report a photoemission study of the systematics of the 4f electronic structure of a family of rare-earth organic compounds. Resonant photoemission has been used to determine the binding energies of the 4f ground states, relative to those of the ligand orbitals, of a number of rare-earth tris-8-hydroxyquinolines (REQ's). Using an empirical model these results have been extrapolated, to the full series (Ce-Lu) of REQ's. It is found that in all cases, with the possible exception of Ce, the energy of the 4f ground state is less than that of the highest occupied molecular orbital, and therefore individual holes on lanthanide sites will not be stable.

Tailored solution‐based N‐heterotriangulene thin films: Unravelling the self‐assembly - Hawly, Tim; Streller, Fabian; Johnson, Manuel; Miguez Lago, Sandra; Hammer, Natalie; Hampel, Frank; Vivod, Dustin; Zahn, Dirk; Kivala, Milan; Branscheid, Robert; Spiecker, Erdmann; Fink, Rainer (ChemPhysChem, 2021)
The ability of a series of bridged triarylamines, so‐called N‐heterotriangulenes, to form multilayer‐type 2D‐extended films via a solution‐based processing method was examined using complementary microscopic techniques. We found that the long‐range order, crystallinity, and layer thickness decisively depend on the nature of the substituents attached to the polycyclic backbone. Owing to their flat core unit, compounds exhibiting a carbonyl unit at the bridge position provide a superior building block as compared to thioketone‐bridged derivatives. In addition, nature and length of the peripheral substituents affect the orientation of the aromatic core unit within highly crystalline films. Hence, our results stress the significance of a suitable molecular framework and provide deeper understanding of structure formation in 2D‐confined surroundings for such compounds.<br
Keywords: bridged triarylamines; self-assembly; organic semiconductors; 2D nanomaterials; organic electronics

Tailoring the Selectivity of 1,3-Butadiene versus 1-Butene Adsorption on Pt(111) by Ultrathin Ionic Liquid Films - Winter, Leonhard; Trzeciak, Simon; Fernandez, Cynthia Carolina; Massicot, Stephen; Talwar, Timo; Maier, Florian; Zahn, Dirk; Steinrück, Hans-Peter (ACS Catalysis, 2023)
The solid catalyst with ionic liquid layer (SCILL) concept is a promising approach to enhance the selectivity of hydrogenation reactions, like the selective hydrogenation of 1,3-butadiene to 1-butene using transition-metal catalysts. In this context, the adsorption dynamics of 1,3-butadiene and 1-butene were studied on Pt(111) modified with ultrathin layers of the ionic liquid (IL) 1,3-dimethylimidazolium bis(trifluoromethanesulfonyl)imide ([C1C1Im][Tf2N]). The sticking coefficients of the two hydrocarbons are measured using the direct method of King and Wells. Both olefins show pronounced precursor-mediated dynamics on clean Pt(111) and on the IL-modified surface. Increasing the IL coverage leads to an increased blocking of adsorption sites for the incoming olefins. Coadsorbed hydrogen does not significantly affect the precursor and site-blocking effects for 1,3-butadiene. Interestingly, a smaller IL amount is needed to prevent 1-butene adsorption compared to 1,3-butadiene adsorption, which is proposed to be directly related to the IL’s influence on selective hydrogenation in SCILL catalysis. Indeed, molecular dynamics simulations show IL film densification/relaxation as the key mechanism to allowing/excluding olefin adsorption on the metal. Being a function of IL coverage, the energy of film penetration is used to control the effective olefin adsorption energy and thus creates an operation regime for suppressing 1-butene while permitting 1,3-butadiene adsorption.
CRIS-Team Scopus Importer:2023-09-01
Keywords: adsorption; gas-surface dynamics; hydrogenation; ionic liquids; molecular beam; molecular dynamics; SCILL; selectivity

Taking a Nanoscale "look" at Chemical Reactions on Surfaces - Sykes, E. Charles H.; Steinrück, Hans-Peter (Accounts of Chemical Research, 2015)

Temperature dependance of the sticking coefficient for H 2 on various nickel surfaces - Luger, M.; Winkler, A.; Rendulic, K.D.; Steinrück, Hans-Peter (Symposium on Surface Science 3S'85, 1985)

Temperature dependence of the sticking coefficient for H2 on various nickel surfaces - Luger, M.; Winkler, A.; Rendulic, K.D.; Steinrück, Hans-Peter (Proc. Symposium on Surface Science, 1985)
UnivIS-Import:2015-04-16:Pub.1985.nat.dchph.lpc2.temper

Temperature-dependent chemical and structural transformations from 2H-tetraphenylporphyrin to copper(II)-tetraphenylporphyrin on Cu(111) - Xiao, Jie; Ditze, Stefanie; Chen, Min; Buchner, Florian; Stark, Michael Werner; Drost, Martin; Steinrück, Hans-Peter; Gottfried, J. Michael; Marbach, Hubertus (Journal of Physical Chemistry C, 2012)
Temperature-dependent chemical and structural changes of a submonolayer of 2H-tetraphenylporphyrin (2HTPP) on Cu(111) were studied with photoelectron spectroscopy (XPS/UPS) and scanning tunneling microscopy (STM). 2HTPP reacts with Cu atoms from the substrate to form copper(II)-tetraphenylporphyrin (CuTPP). This metalation reaction starts at about 400 K and was investigated at various temperatures up to 500 K. At room temperature, adsorbed 2HTPP adopts an orientation with the molecular plane parallel to the substrate; the same holds for its reaction product CuTPP after annealing to 400 K. In contrast, annealing at 450 K yields a tilted orientation of CuTPP, as indicated by STM and supported by C 1s XPS shifts and changes in the Cu(111) surface state. Subsequent annealing at 500 K restores a flat-lying orientation; however, the appearance of the complex in STM images differs from the original appearance of CuTPP. In summary, 2HTPP undergoes three irreversible transformations upon annealing on Cu(111), a metalation reaction to CuTPP followed by two intramolecular structural changes. © 2012 American Chemical Society.

Temperature-dependent dielectric anomalies in powder aerosol deposited ferroelectric ceramic films - Eckstein, Udo; Exner, Jörg; Bencan Golob, Andreja; Ziberna, Katarina; Drazic, Goran; Ursic, Hana; Wittkämper, Haiko; Papp, Christian; Kita, Jaroslaw; Moos, Ralf; Webber, Kyle Grant; Khansur, Neamul Hayet (Journal of Materiomics, 2022)
Room-temperature fabrication of functional ceramic films using powder aerosol deposition (AD) is important for practical applications. However, the as-processed ferroelectric films show unusual temperature-dependent dielectric response, including enhanced conductivity in the as-processed state and subsequent significant increase in the permittivity following heat treatment. In this work, we investigate the influence of the residual internal stresses developed during the high-impact consolidation process on the dielectric response. Moreover, the recombination of charged defects generated during deposition is driven by the temperature and the atmospheric condition during the heat treatment as well as the carrier gas type used during deposition. Thermal treatment up to 500 °C in different atmospheres was used to tune the dielectric and ferroelectric response, highlighting that irrespective of the type of carrier gas, AD deposition process induces charged defects in polar oxide ceramics that can be reduced through heat-treatment far-below their bulk sintering temperature. Macroscopic electromechanical properties are contrasted to in-situ heating scanning transmission electron microscopy to observe possible local effects, such as crystallization, grain growth, crystal defect structure, or grain reorientation. In addition X-ray diffraction and X-ray photoelectron spectroscopy studies were conducted to gain insight into the effect of annealing on the crystal structure and local moisture adsorption.
CRIS-Team Scopus Importer:2022-11-18
Keywords: Aerosol deposition; Energy storage; Functional ceramic thick films; Structural characterization

Temperature dependent oxidation of thin Ni layers on Cu(1 1 1) - Domnick, Ralph; Held, Georg; Steinrück, Hans-Peter (Surface Science, 2002)
The initial stages of surface oxidation were investigated for pseudomorphic Ni layers (1-3 ML) on Cu(1 1 1) after oxygen adsorption at 150 and 300 K. At 150 K, the oxidation proceeds in a two-step process: first, oxygen chemisorbs on the surface up to a coverage of 0.7 ML leaving the top-most Ni atoms metallic. In the second step these Ni atoms are oxidized parallel to the adsorption of additional sub-surface oxygen (up to 2.0 ML), which is indicated by drastic changes in the Ni2p spectra. No bulk oxidation beyond the first layer of metal atoms is observed after adsorption at 150 K. At 300 K, the mobility of the Ni atoms is high enough to allow also the oxidation of the lower lying metal atoms and the formation of NiO clusters on the surface. The sequence of chemisorption and oxidation and the amount of oxygen required for the complete oxidation of 1 ML Ni is the same as for 150 K. © 2002 Elsevier Science B.V. All rights reserved.

Temperature-Dependent Reactions of Phthalic Acid on Ag(100) - Franke, Matthias; Marchini, Florencia; Zhang, Liang; Tariq, Quratulain; Tsud, Nataliya; Vorokhta, Mykhailo; Vondráček, Martin; Prince, Kevin C.; Röckert, Michael; Williams, Federico J.; Steinrück, Hans-Peter; Lytken, Ole (Journal of Physical Chemistry C, 2015)
We have investigated the adsorption and temperature-dependent reactions of phthalic acid on Ag(100), in the temperature range 110-700 K, by synchrotron radiation X-ray photoelectron spectrocopy (SR-XPS), temperature-programmed desorption (TPD) and near-edge X-ray absorption fine structure (NEXAFS). Phthalic acid adsorbs intact at 110 K, but decomposes to phthalic anhydride and polyanhdride at 150 K. When heated further, phthalic anhydride desorbs at 250 K, leaving only polyanhydride on the surface, which at 350 K decomposes into a carboxylate, through desorption of phthalic anhydride and water. The carboxylate is stable until 500 K, after which it decomposes, through desorption of CO and benzene, into carbon; the latter diffuses into the bulk, leaving only a little carbon on the Ag(100) surface at 600 K.

Temperature-Dependent Surface Enrichment Effects in Binary Mixtures of Fluorinated and Non-Fluorinated Ionic Liquids - Heller, Bettina; Lexow, Matthias; Greco, Francesco; Shin, Sunghwan; Partl, Gabriel; Maier, Florian; Steinrück, Hans-Peter (Chemistry - A European Journal, 2020)
Using angle-resolved X-ray photoelectron spectroscopy (ARXPS), we investigate the topmost nanometers of various binary ionic liquid (IL) mixtures at different temperatures in the liquid state. The mixtures consist of ILs with the same [PF6]− anion but two different cations, namely 3-methyl-1-(3,3,4,4,4-pentafluorobutyl)imidazolium hexafluorophosphate, [PFBMIm][PF6], and 1-butyl-3-methylimidazolium hexafluorophosphate, [C4C1Im][PF6], with 10, 25, 50 and 75 mol % content of [PFBMIm][PF6]. We observe a preferential enrichment of the fluorinated chain in the topmost layer, relative to the bulk composition, which is most pronounced for the lowest content of [PFBMIm][PF6]. Upon cooling the mixtures stepwise from 95 °C until surface charging effects in XPS indicate solidification, we observe a pronounced increase in surface enrichment of the fluorinated chain with decreasing temperature in the liquid state. In contrast to the mixtures with lower [PFBMIm][PF6] contents, cooling the 75 mol % mixture additionally shows an abrupt decrease of the fluorinated chain signal before complete solidification occurs, which is assigned to partial precipitation effects.
CRIS-Team Scopus Importer:2020-02-04
Keywords: ionic liquids; mixtures; photoelectron spectroscopy; surface enrichment

Temperature-dependent surface-enrichment effects of imidazolium-based ionic liquids - Kolbeck, Claudia; Deyko, Alexey; Matsuda, Takashi; Kohler, Florian; Wasserscheid, Peter; Maier, Florian; Steinrück, Hans-Peter (ChemPhysChem, 2013)
We present the first systematic study of the influence of temperature on the degree of surface enrichment of 1-alkyl-3-methylimidazolium-based ionic liquids (ILs). Using angle-resolved X-ray photoelectron spectroscopy, we demonstrate that the degree of surface enrichment strongly decreases with increasing temperature for all the studied ILs. For ILs with the same cation, but different anions, [CCIm]Br, [CC Im][TfO] and [CCIm][TfN], no significant differences of the temperature-induced partial loss of surface enrichment are found. Measurements for [CCIm][TfO], [CCIm][TfO] and [CCIm][TfO] indicate a small effect of the chain length. For [CC Im][TfO], a continuous decrease of alkyl surface enrichment is found with increasing temperature, with no abrupt changes at the phase-transition temperature from the smectic A to the isotropic phase, indicating that the surface enrichment is not affected by this phase transition. Loss of order! The surface enrichment of the alkyl chains of five imidazolium-based ionic liquids (ILs) at the liquid/vacuum interface is studied as a function of temperature by angle-resolved X-ray photoelectron spectroscopy; both the anion and the alkyl chain length at the cation are varied. At room temperature, the alkyl chains are enriched at the outer surface. Upon increasing the temperature, the degree of surface enrichment decreases. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Temperature-dependent XPS studies on Ga-In alloys through the melting-point - Wittkämper, Haiko; Maisel, Sven; Moritz, Michael; Grabau, Mathias; Görling, Andreas; Steinrück, Hans-Peter; Papp, Christian (Surface Science, 2022)
Gallium indium alloys are known to be liquid at remarkably low temperatures. Herein, we provide X-ray photoelectron spectroscopy (XPS) studies and DFT-based ab-initio molecular dynamics (MD) calculations on the composition of the liquid alloy surface. We find that alloying Ga and In in ratios close to the eutectic composition results in only minor signal shifts of the corresponding In core levels. The topmost surface layer of the liquid alloy exhibits significant In enrichment for all measured temperatures, between 300 K to 800 K the observed enrichment slightly decreases with increasing temperature. This behavior is seen in both temperature-dependent XPS and ab-initio MD simulations. Furthermore, we investigate changes in the surface composition during the liquid-to-solid phase transition by time-dependent XPS during cooling of the alloy sample. The surface of the alloy presents an advantageous nucleation site, where we regularly observe the precipitation of indium. During cooling, the precipitation processes were followed by both XPS and by monitoring the sample temperature/heating power.
CRIS-Team Scopus Importer:2022-04-14
Keywords: DFT; GaIn; XPS

Tetraphenylporphyrin picks up zinc atoms from a silver surface - Kretschmann, Andreas; Walz, Marie-Madeleine; Flechtner, Ken; Steinrück, Hans-Peter; Gottfried, Michael (Chemical Communications, 2007)
We demonstrate that adsorbed meso-tetraphenylporphyrin molecules can coordinate Zn atoms that are pre-deposited on an Ag(111) surface, forming a complex that is identical to directly deposited tetraphenylporphyrinato-zinc(ii) ; this reaction, which we studied with XPS, is the first example of an oxidative dissolution of a metal by a large organic ligand under ultrahigh vacuum conditions. © The Royal Society of Chemistry.
UnivIS-Import:2015-04-14:Pub.2007.nat.dchph.lpc2.tetrap

The adsorption of acetylene on Ni(110): An experimental and theoretical study - Weinelt, M.; Huber, W.; Zebisch, P.; Steinrück, Hans-Peter; Ulbricht, P.; Birkenheuer, U.; Boettger, J.C.; Rösch, Notker (Journal of Chemical Physics, 1995)
The adsorption of acetylene on Ni(110) was investigated by temperature programmed desorption (TPD), low energy electron diffraction (LEED), angle resolved ultraviolet-photoelectron spectroscopy (ARUPS), and near edge x-ray absorption fine structure (NEXAFS) measurements, as well as by detailed model cluster calculations and slab model band structure calculations. By combining the experimental results and those of the cluster studies an orientation of the molecules is deduced with the C-C axis parallel to the surface and preferentially aligned along the substrate troughs ([110] azimuth) as well as with a highly coordinated adsorption site in the substrate troughs. A detailed analysis of the photoemission spectrum is given. The proposed adsorption geometry is corroborated by band structure calculations for various alternative sites and orientations that are shown to be very sensitive to the azimuthal orientation of the adsorbed molecules. © 1995 American Institute of Physics.

The adsorption of benzene mono- and multilayers on Ni(111) studied by TPD and LEED - Steinrück, Hans-Peter; Huber, W.; Pache, T.; Menzel, Dietrich (Surface Science, 1989)
Benzene adsorption on Ni(111) has been studied by LEED and TPD for adsorption temperatures between 110 and 310 K. At initial coverages θ < 0.05 ML (relative to Ni) complete decomposition of benzene occurs upon heating above 650 K. At higher coverages (θ > 0.05 ML) molecular desorption precedes decomposition. The saturation coverage of chemisorbed benzene can only be achieved at adsorption temperatures below 270 K and reveals a sharp (√7×√7)R19.1° LEED pattern corresponding to a coverage of 0.143 ML. This LEED pattern disappears upon heating to 300 K; simultaneously a very sharp molecular benzene desorption peak is observed at 294 K, indicating that desorption is coupled to this order-disorder phase transition. A previously reported (2√3× 2√3)R30 ° structure for room temperature adsorption can only be observed by coadsorbing CO; the relative coverages in the coadsorbed benzene + CO layer are θ : theta; = 1:2. Adsorption of benzene at 110 K leads to the formation of multilayers. Three distinct states, α , α and α can be resolved with desorption temperatures of 154, 136 and 146 K, respectively. The α peak corresponds to the first physisorbed layer on top of the chemisorbed benzene, probably also oriented parallel to the surface. The α peak exhibits typical zero-order desorption behaviour and is attributed to bulk sublimation. The α peak seems to be due to a transition layer between the α layer and bulk benzene. This behaviour is similar to that observed before on Ru(001). For chemisorbed and physisorbed benzene we compile and compare the results on other surfaces. © 1989.

The adsorption of H2O on clean and oxygen precovered Ni(111) studied by ARUPS and TPD - Pache, T.; Steinrück, Hans-Peter; Huber, W.; Menzel, Dietrich (Surface Science, 1989)
Using TPD, ARUPS, XPS, LEED and work function measurements the adsorption of water has been studied on the clean Ni(111) surface and on a Ni(111) surface precovered with 0.25 ML of oxygen. For the clean surface the saturation coverage of chemisorbed water is determined to 0.66 ML by XPS. The observed ( 3 × 3)R30° structure must then be non-primitive containing two molecules per unit cell. Angle resolved UPS spectra show a splitting of the 3a level indicating the existence of two nonequivalent molecules in the chemisorbed layer, both being tilted with respect to the surface normal. The so-called "bilayer" structure is proposed for this saturated chemisorbed layer. The TPD spectra show three distinct peaks at 171, 152 and 158 K that are attributed to desorption from the chemisorbed bilayer, a transition layer and condensed water, respectively. Upon oxygen preadsorption an additional peak is observed in TPD of water reaching from 180 to 260 K with a saturation coverage of 0.25 ML. This peak is attributed to intact HO molecules directly chemisorbed on the Ni(111) surface. The angle resolved UPS spectra show very distinct angular dependences of all molecular levels. No evidence for dissociation is found. The orientation of the molecules is proposed to be tilted perpendicular to the molecular plane possibly due to hydrogen bonding to two neighbouring oxygen atoms. © 1989.

The adsorption of H2O on K precovered Ni(111) studied by ARUPS and TPD - Bornemann, T.; Steinrück, Hans-Peter; Huber, W.; Eberle, K.; Glanz, M.; Menzel, Dietrich (Surface Science, 1991)
The adsorption of HO on a Ni(111) surface precovered with various amounts of potassium has been studied by TPD, work-function measurements, and angle-resolved UPS using linearly polarized synchrotron radiation. Coadsorption of potassium leads to major changes in the desorption characterics of water which depend strongly on the amount of preadsorbed potassium. At potassium precoverages below θ ≈ 0.14 ML water is molecularly adsorbed; for higher potassium precoverages dissociation of HO into an OH species as well as molecular adsorption is observed at 110 K. The molecularly bound species is significantly stabilized on the surface, as concluded from a high temperature desorption state (170-280 K) in TPD. At low potassium precoverages approximately three HO molecules are affected by one potassium atom. Using symmetry selection rules the symmetry of the adsorbed HO molecules is determined to C(σ), which is probably due to a tilting in the HOH plane. At high potassium precoverages HO decomposes upon adsorption forming an OH species; this OH species is stable up to temperatures above 400 K. The ratio of K to OH formed by dissociation is found to be about 1. From the angle and polarization dependences of the molecular orbitals a tilted orientation of the OH species is derived. The results are compared to those obtained for HO adsorption on clean and oxygen-precovered Ni(111) surfaces, and other alkali/metal systems. © 1991.

The adsorption of NO on an oxygen pre-covered Pt(1 1 1) surface: In situ high-resolution XPS combined with molecular beam studies - Zhu, Junfa; Kinne, Martin; Fuhrmann, Thomas; Tränkenschuh, Barbara; Denecke, Reinhard; Steinrück, Hans-Peter (Surface Science, 2003)
Adsorption of NO on a Pt(111) surface pre-covered with a p(2×2) atomic oxygen layer has been studied in situ by high-resolution X-ray photoelectron spectroscopy and temperature-programmed XPS using third-generation synchrotron radiation at BESSY II, Berlin, combined with molecular beam techniques and ex situ by low energy electron diffraction and temperature-programmed desorption. O 1s XP spectra reveal that an ordered p(2×2)-O layer dramatically changes the adsorption behavior of NO as compared to the clean surface. The atomic oxygen occupies fcc hollow sites, and therefore blocks NO adsorption on these sites, which are energetically preferred on clean Pt(111). As a consequence, NO populates on-top sites at low coverage. At 110 K for higher coverages, NO can additionally adsorb on hcp hollow sites, thereby inducing a shift of the O 1s binding energy of atomic oxygen towards lower energies by about 0.25 eV. The bond strength of the hcp hollow NO species to the substrate is weakened by the presence of atomic oxygen. A sharp p(2×2) LEED pattern is observed for NO adsorption on the oxygen pre-covered surface, up to saturation coverage. The total saturation coverage of NO on Pt(111) pre-covered with varying amounts of oxygen (below 0.25 ML) decreases linearly with the coverage of oxygen. The initial sticking coefficient of NO is reduced from 0.96 on clean Pt(111) to 0.88 on a p(2×2) oxygen pre-covered surface. © 2003 Elsevier B.V. All rights reserved.

The atomic structure of low-index surfaces of the intermetallic compound InPd - McGuirk, Garry M.; Ledieu, Julian; Gaudry, Émilie; de Weerd, Marie-Cecile; Hahne, Michael; Gille, Peter; Ivarsson, Dennis C. A.; Armbrüster, Marc; Ardini, Jacopo; Held, Georg; Maccherozzi, Francesco; Bayer, Andreas; et al. (Journal of Chemical Physics, 2015)
The intermetallic compound InPd (CsCl type of crystal structure with a broad compositional range) is considered as a candidate catalyst for the steam reforming of methanol. Single crystals of this phase have been grown to study the structure of its three low-index surfaces under ultra-high vacuum conditions, using low energy electron diffraction (LEED), X-ray photoemission spectroscopy (XPS), and scanning tunneling microscopy (STM). During surface preparation, preferential sputtering leads to a depletion of In within the top few layers for all three surfaces. The near-surface regions remain slightly Pd-rich until annealing to ∼580 K. A transition occurs between 580 and 660 K where In segregates towards the surface and the near-surface regions become slightly In-rich above ∼660 K. This transition is accompanied by a sharpening of LEED patterns and formation of flat step-terrace morphology, as observed by STM. Several superstructures have been identified for the different surfaces associated with this process. Annealing to higher temperatures (≥750 K) leads to faceting via thermal etching as shown for the (110) surface, with a bulk In composition close to the In-rich limit of the existence domain of the cubic phase. The Pd-rich InPd(111) is found to be consistent with a Pd-terminated bulk truncation model as shown by dynamical LEED analysis while, after annealing at higher temperature, the In-rich InPd(111) is consistent with an In-terminated bulk truncation, in agreement with density functional theory (DFT) calculations of the relative surface energies. More complex surface structures are observed for the (100) surface. Additionally, individual grains of a polycrystalline sample are characterized by micro-spot XPS and LEED as well as low-energy electron microscopy. Results from both individual grains and “global” measurements are interpreted based on comparison to our single crystals findings, DFT calculations and previous literature.
Keywords: Low energy electron diffraction; Surface structure; X-ray photoelectron spectroscopy; Scanning tunneling microscopy; Surface composition

The Buoy Effect: Surface Enrichment of a Pt Complex in IL Solution by Ligand Design - Hemmeter, Daniel; Kremitzl, Daniel; Schulz, Peter; Wasserscheid, Peter; Maier, Florian; Steinrück, Hans-Peter (Chemistry - A European Journal, 2023)
The targeted enrichment of a Pt complex with an ionic liquid (IL)-derived ligand system in IL solution is demonstrated by using angle-resolved X-ray photoelectron spectroscopy. When the ligand system is complemented with fluorinated side chains, the complex accumulates strongly at the IL/gas interface, while in an equivalent solution of a complex without these substituents no such effect could be observed. This buoy-like behavior induces strong population of the complex at the outermost molecular layer close to surface saturation, which was studied over a range from 5 to 30 %mol. The surface enrichment was found to be most efficient at the lowest concentration, which is particularly favorable for catalytic applications such as supported ionic-liquid-phase (SILP) catalysis.
CRIS-Team Scopus Importer:2023-01-20
Keywords: catalysis; ionic liquids; surface analysis; surface enrichment; X-ray photoelectron spectroscopy (XPS)

The dissimilar twins - a comparative, site-selective in situ study of CO adsorption and desorption on Pt(3 2 2) and Pt(3 5 5) - Tränkenschuh, Barbara; Papp, Christian; Fuhrmann, Thomas; Denecke, Reinhard; Steinrück, Hans-Peter (Surface Science, 2007)
The adsorption and desorption of CO on stepped Pt(3 2 2) = Pt(S)-[5(1 1 1) × (1 0 0)] and Pt(3 5 5) = Pt(S)-[5(1 1 1) × (1 1 1)] were investigated using in situ high-resolution X-ray photoelectron spectroscopy at BESSY II, which allows to clearly distinguish between different step and terrace adsorption sites. For the two surfaces, with the same nominal terrace width of five atomic rows, but different step orientation, significant differences are observed. While for Pt(3 5 5) CO adsorption at steps only occurs at on-top sites, on Pt(3 2 2) both step on-top and bridge sites are occupied, albeit with a significantly lower coverage (0.07 vs. 0.13 ML at 200 K). On both surfaces terrace sites are only occupied when the step sites are almost saturated confirming the enhanced binding energy at step sites. CO adsorbed at the (1 1 1) steps on Pt(3 5 5) is more strongly bound than on the (1 0 0) steps on Pt(3 2 2), which is attributed to the different electronic and geometric structure of the steps. The relative occupation of terrace and step sites at a given coverage remains the same between 120 and 290 K on Pt(3 5 5) K, but shows major changes on Pt(3 2 2), between step on-top and bridge sites as well as terrace on-top and bridge sites. On Pt(3 5 5) a smaller CO terrace coverage is found (0.36 vs. 0.40 ML on Pt(3 2 2) at 200 K), mainly due to the lower occupation of terrace bridge sites. For Pt(3 2 2), an ordered adsorbate phase is deduced from a c(4 × 2)-like LEED pattern, which indicates adsorbate order beyond the extension of a single terrace. A model for this structure is proposed. © 2006 Elsevier B.V. All rights reserved.

The Dynamics of Alcane Activation on Nickel and Iridium Single-Crystal Surfaces - Madix, R.J.; Hamza, Alex; Steinrück, Hans-Peter (Journal of the American Chemical Society, 1986)

The Dynamics of Alkane Activation on Ni(100) and Ir(110) - Hamza, Alex; Steinrück, Hans-Peter; Madix, R.J. (Journal of Vacuum Science & Technology A, 1987)

The dynamics of the dissociative adsorption of alkanes on Ir(110) - Hamza, Alex; Steinrück, Hans-Peter; Madix, R.J. (Journal of Chemical Physics, 1987)
The dissociative adsorption of C-C alkanes on Ir(110)-(1×2) was investigated using supersonic molecular beam techniques. Three regimes of reactivity were observed. At incident kinetic energies less than 100 kJ/mol the dissociative adsorption probability for propane and butane increased to about 0.6 with both decreasing surface temperature and decreasing translational energy of the incident molecule suggesting that activation occured via trapping of the alkane on the surface. At kinetic energies below 110 kJ/mol for butane, 90 kJ/mol for propane, 60 kJ/mol for ethane, 40 kJ/mol for methane, and at elevated surface temperatures the reaction probabilities for alkanes were independent of surface temperature and translational energy, but increased significantly with the molecular weight or carbon chain length of the incident alkane. This behavior indicates an unactivated reaction channel for each species except methane. At kinetic energies above 110 kJ/mol for butane, 90 kJ/mol for propane, 60 kJ/mol for ethane, and 40 kJ/mol for methane the initial dissociative sticking probability increased with increasing translational energy and was independent of surface temperature, indicating direct translational activation of the incident alkane. The translational energy required to activate the incident alkane via this channel increased with carbon number or molecular weight, indicative of energy transfer processes that dissipate energy in the reactive collision. The dissipative transfer of translational energy out of the reactive channel via a hard cube collision with the surface accounts qualitatively for the increase in the apparent activation barrier with increasing molecular weight in this activated channel. © 1987 American Institute of Physics.

The electronic structure and molecular symmetry of pure benzene and benzene coadsorbed with CO on Ni(111) - Huber, W.; Steinrück, Hans-Peter; Pache, T.; Menzel, Dietrich (Surface Science, 1989)
Benzene adsorption on Ni(111) was studied by ARUPS using linearly polarized synchrotron radiation at various benzene coverages and for benzene coadsorbed with CO. Overall the electronic structure of chemisorbed benzene is found to be very similar for the different benzene coverages and in the presence of coadsorbed CO: only small shifts in the electronic binding energies are observed which are attributed to electrostatic initial state changes. Using dipole selection rules the orientation of the adsorbed benzene molecules is determined to be parallel to the surface for all layers investigated. The molecular symmetry is reduced to C in all cases. The photon energy dependence of the photoionization cross section shows a pronounced resonance of the 2e level at a photon energy of 25 eV (E ≈ 13 eV); the corresponding electron emission is centered along the surface normal. This resonance is attributed to a shape resonance into an a final state. © 1989.

The electronic structure of cobalt(II) phthalocyanine adsorbed on Ag(111) - Schmid, Martin; Kaftan, Andre; Steinrück, Hans-Peter; Gottfried, Michael (Surface Science, 2012)
The electronic states of submonolayers and multilayers of cobalt(II) phthalocyanine (CoPc) adsorbed on Ag(111) were examined with photoelectron spectroscopy to obtain insight into the details of the substrate-adsorbate interaction. UV photoelectron spectroscopy (UPS) reveals the presence of two interaction-related valence states in the direct vicinity of the Fermi edge, in agreement with previous DFT calculations. X-ray photoelectron spectra indicate that the substrate-adsorbate interaction results in transfer of electron density from the substrate to the Co(II) ion. Substantial changes in the Co 2p multiplet structure, a spectral pattern induced by the open-shell character of the central Co(II) ion, indicate a complete quenching of the molecular spin. While pristine CoPc molecules are paramagnetic with S = 1/2, molecules in direct contact to the Ag(111) substrate appear to be in a diamagnetic state. © 2012 Elsevier B.V. All rights reserved.

The electronic structure of ethylene on Ni(110): an experimental and theoretical study - Weinelt, M.; Huber, W.; Zebisch, P.; Steinrück, Hans-Peter; Pabst, M.; Rösch, Notker (Surface Science, 1992)
The electronic structure of ethylene adsorbed on Ni(110) has been studied by ARUPS using linearly polarized synchrotron radiation, and by LCGTO-LDF model cluster calculations. The adsorption system has also been characterized by TPD and LEED. The ARUPS measurement were performed for a dilute ethylene layer (θ ≈ 1 2θ ), where lateral interactions are not important. From the detailed analysis of the polarization, polar angle and azimuthal dependence of the ARUPS spectra we deduce an orientation of the ethylene molecules with the molecular plane coplanar to the surface and the C-C axis preferentially aligned along the [110] azimuth. The symmetry of the adsorption complex is determined as C . The ethylene π-orbital 1b exhibits a differential shift of 1.1 eV to higher binding energy as compared to the free molecule. The corresponding theoretical value is found to be ∼ 1.7 eV. In the cluster calculations a partial optimization of the adsorbate geometry has been carried out assuming C symmetry. The adsorption bonding is found to be quite similar in π and di-σ coordination, for both cases the π donation to the substrate being stronger than the π backdonation. The π donation is mediated mainly by Nis and p contributions, gp backdonation mostly by Ni d orbitals. The optimized geometry parameters for the π-bonded species are: CC: 1.42 Å: NiC: 2.01 Å tilting of a CH group relative to the (110) crystal plane: 23°. © 1992.

The growth of thin Cu layers on Ni(111) studied by CO titration and photoelectron spectroscopy - Koschel, Herbert; Held, Georg; Steinrück, Hans-Peter (Surface Science, 2000)
The growth of thin Cu layers (up to 14 ML) on Ni(111) was studied by temperature-programmed desorption (TPD) of CO and X-ray photoelectron spectroscopy (XPS). CO TPD spectra display desorption features from both nickel- and copper-terminated areas, which are clearly separated in temperature. Using XPS and TPD for titrating the uncovered Ni areas, the quality of the copper layer in the 1 ML range was studied as a function of annealing temperature. We find that a pseudomorphic Cu monolayer on Ni(111) is best produced by evaporating the appropriate amount of Cu onto the cold sample at 100 K, followed by annealing to temperatures around 800 K. This temperature is high enough to convert three-dimensional islands that are found at low temperatures into smooth two-dimensional Cu layers, but low enough to avoid alloying, which is observed for higher annealing temperatures. For higher Cu coverages, annealing to 800 K leads to significant diffusion of Ni atoms into the Cu multilayer. © 2000 Elsevier Science B.V. All rights reserved.

The Impact of Aggregation on the Photophysics of Spiro-Bridged Heterotriangulenes - Krug, Marcel; Wagner, Maximilian; Schaub, Tobias A.; Zhang, Wen-Shan; Schüßlbauer, Christoph; Ascherl, Johannes D. R.; Münich, Peter Wilhelm; Schroeder, Rasmus R.; Gröhn, Franziska; Dral, Pavlo O.; Barbatti, Mario; Guldi, Dirk Michael; et al. (Angewandte Chemie International Edition, 2020)
We report on the impact of the central heteroatom on structural, electronic, and spectroscopic properties of a series of spirofluorene-bridged heterotriangulenes and provide a detailed study on their aggregates. The in-depth analysis of their molecular structure by NMR spectroscopy and X-ray crystallography was further complemented by density functional theory calculations. With the aid of extensive photophysical analysis the complex fluorescence spectra were deconvoluted showing contributions from the peripheral fluorenes and the heteroaromatic cores. Beyond the molecular scale, we examined the aggregation behavior of these heterotriangulenes in THF/H2O mixtures and analyzed the aggregates by static and dynamic light scattering. The excited-state interactions within the aggregates were found to be similar to those found in the solid state. A plethora of morphologies and superstructures were observed by scanning electron microscopy of drop-casted dispersions.
CRIS-Team WoS Importer:2020-07-24

The interaction of CO and Ar molecular beams with Ir(110) - Steinrück, Hans-Peter; Madix, R.J. (Surface Science, 1987)
Supersonic molecular beam techniques were used to study the scattering of CO and Ar from clean and CO-covered Ir(110) surfaces over a wide range of kinetic energies of the incident species. The initial sticking coefficient, S, for CO on a clean Ir(110) surface decreases from 0.80 at 2 kcal/mol beam energy to 0.35 at 34 kcal/mol. At each beam enery S is independent of surface temperature in the interval 200≤T≤500 K. Scattering of CO from a CO-saturated surface shows a transition from mainly trapping/desorption scattering at low beam energy to direct inelastic scattering at high beam energy. The trapping probability for CO on the covered surface decreases with beam energy. Ar and CO scattering from the covered surface are very similar. The dependence of the trapping probability on beam energy for CO and Ar is identical within the margin of error of the experiment. Comparison of the Ar scattering from the CO-covered surface with that from the clean surface reveals much smaller trapping probabilities for Ar on the clean surface. This indicates that the adsorbed CO layer increases the efficiency of the energy transfer from the gas to the surface. © 1987 Elsevier Science Publishers B.V.

The Interaction of Cobalt with CeO2(111) Prepared on Cu(111) - Vari, Gabor; Ovari, Laszlo; Papp, Christian; Steinrück, Hans-Peter; Kiss, Janos; Konya, Zoltan (Journal of Physical Chemistry C, 2015)
The interaction of cobalt with an ultrathiri CeO2(111) film on Cu(111) was studied by low energy ion scattering spectroscopy and X-ray photoelectron spectroscopy. At room temperature, Co grows three-dimensionally on the ceria film. For small Co coverages (0.2 ML), oxidation to Co2+ occurs together with the formation Of Ce3+ in the ceria. At higher Co coverages (07 and 2 ML), an increasing fraction of Co remained Metallic after deposition. Annealing to higher temperatures induced diffusion of Co2+ ions into the ceria film, and for metallic Co, presumably agglomeration occurs. At T >= 800 K, oxidation of significant amounts of Co-0 to Co2+ is found, along with diffusion, into the ceria. film, and partly also in the copper crystal underneath. On a reduced CeOx surface, the redox reaction between cobalt and cerium was hindered, which, in turn, slowed down cobalt migration into the ceria film.

The Kinetics of Methanol Oxidation on Alumina Supported Pd Nanoparticles - Libuda, Jörg; et al. (Journal of Catalysis, 2003)
UnivIS-Import:2015-03-09:Pub.2003.nat.dchph.ppc20.thekin

The Mechanism of Hydrocarbon Oxygenate Reforming: C-C Bond Scission, Carbon Formation, and Noble-Metal-Free Oxide Catalysts - Lykhach, Yaroslava; Neitzel, Armin; Sevcikova, Klara; Johanek, Viktor; Tsud, Nataliya; Skala, Tomas; Prince, Kevin C.; Matolin, Vladimir; Libuda, Jörg (Chemsuschem, 2014)
Towards a molecular understanding of the mechanism behind catalytic reforming of bioderived hydrocarbon oxygenates, we explore the C-C bond scission of C-2 model compounds (acetic acid, ethanol, ethylene glycol) on ceria model catalysts of different complexity, with and without platinum. Synchrotron photoelectron spectroscopy reveals that the reaction pathway depends very specifically on both the reactant molecule and the catalyst surface. Whereas C-C bond scission on Pt sites and on oxygen vacancies involves intermittent surface carbon species, the reaction occurs without any carbon formation and deposition for ethylene glycol on CeO2(111).
Keywords: catalytic reforming; ceria; heterogeneous catalysis; photoelectron spectroscopy; platinum

The Molecular Origins of Selectivity in Methanol Decomposition on Pd Nanoparticles - Libuda, Jörg; et al. (Catalysis Letters, 2002)
We have combined multi-molecular beam methods and in-situ time-resolved IR reflection absorption spectroscopy (IRAS) to explore the kinetics of methanol decomposition on a supported Pd model catalyst. The well-shaped Pd nanoparticles are prepared under ultra-high vacuum conditions on a well-ordered alumina film and have previously been characterized with respect to size, density, and morphology. Two competing decomposition pathways are observed: Whereas dehydrogenation to CO represents the dominating reaction channel, C-O bond scission proceeds at much lower rates and leads to the formation of carbon and hydrocarbon species. Using CO as a probe molecule, we show via IRAS spectroscopy that these carbon and hydrocarbon species preferentially block defect sites on the Pd particles such as steps or edges, whereas the (111) facet sites are affected to a lesser extent. Employing quantitative IR Sigma AS and steady-state isotope exchange experiements, the reaction rates for both channels are measured as a function of carbon coverage. It is found that with increasing carbon coverage, the rate of carbon formation drops rapidly, whereas the kinetics of dehydrogenation is hardly affected. These results demonstrate that the rate of C-O bond scission is drastically enhanced at the particle steps and edges, whereas for the dehydrogenation pathway this is not the case.
UnivIS-Import:2015-03-09:Pub.2002.nat.dchph.ppc20.themol
Keywords: Alumina; IR reflection absorption spectroscopy; Methanol; Model catalysts; Molecular beams; Palladium

The Norbornadiene/Quadricyclane Pair as Molecular Solar Thermal Energy Storage System: Surface Science Investigations - Hemauer, Felix; Steinrück, Hans-Peter; Papp, Christian (ChemPhysChem, 2024)
For the transition to renewable energy sources, novel energy storage materials are more important than ever. This review addresses so-called molecular solar thermal (MOST) systems, which appear very promising since they combine light harvesting and energy storing in one-photon one-molecule processes. The focus is on norbornadiene (NBD), a particularly interesting candidate, which is converted to the strained valence isomer quadricyclane (QC) upon irradiation. The stored energy can be released on demand. The energy-releasing cycloreversion from QC to NBD can be initiated by a thermal, catalytic, or electrochemical trigger. The reversibility of the energy storage and release cycles determines the general practicality of a MOST system. In the search for derivatives, which enable large-scale applications, fundamental surface science studies help to assess the feasibility of potential substituted NBD/QC couples. We include investigations under well-defined ultra-high vacuum (UHV) conditions as well as experiments in liquid phase. Next to the influence of the catalytically active surfaces on the isomerization between the two valence isomers, information on adsorption geometries, thermal stability limits, and reaction pathways of the respective molecules are discussed. Moreover, laboratory-scaled test devices demonstrate the proof of concept in various areas of application.
CRIS-Team Scopus Importer:2024-03-15
Keywords: energy storage; heterogeneous catalysis; MOST systems; norbornadiene; surface science

The orientation of benzene on bimetallic surfaces - Koschel, Herbert; Held, Georg; Steinrück, Hans-Peter (Surface Review and Letters, 1999)
Angle-resolved UV photoelectron spectroscopy (ARUPS) using linearly polarized synchrotron radiation is used to determine the orientation of benzene molecules on two modifications of the pseudomorphic Ni/Cu(111) layer, the Ni-terminated adlayer and the Cu-terminated Ni sublayer. It is found that the molecules adsorb with their C-H bonds 30° off the close-packed substrate rows (σ orientation) on the Ni adlayer whereas no preferential orientation was found for the Cu-terminated Ni sublayer. For these and other close-packed mono- and bimetallic surfaces involving Cu, Ni and Ru, the correlation between adsorption geometry and reactivity of benzene is explored in connection with temperature-programmed desorption (TPD). Like for the Ni/Cu(111) sublayer, no preferential lateral orientation and a weak bond is found on most other Cu-terminated surfaces at 80 K. This goes along with the absence of any dissociation on these surfaces. Only on the stretched 1 ML Cu/Ru(0001) surface is the substrate-benzene bond strong enough to induce a clear preferential orientation (σ with C-H bonds parallel to the close-packed rows) but still too weak to induce dissociation. The same orientation was found for the saturated benzene layer on Ni(111) where the molecules also do not dissociate. Dissociation is, however, observed for the saturation coverage of benzene on the Ni/Cu(111) adlayer and for low benzene coverages on Ni(111). On these surfaces the azimuthal orientation of the benzene molecules is σ, i.e. rotated by 30° with respect to the close-packed rows.

The photoelectron spectrum of ethylene oxide adsorbed at metal surfaces: a density functional model cluster study of C2H4O Ni(110) - Ulbricht, P.; Häberlen, O.D.; Weinelt, M.; Steinrück, Hans-Peter; Rösch, Notker (Surface Science, 1995)
The electronic structure of ethylene oxide adsorbed at Ni(110) has been calculated by the LCGTO-DF method using cluster models of various adsorption sites. At the local density level of theory a weak binding of the adsorbate to the substrate is found, but a repulsive interaction results for a gradient corrected energy functional. No major differences are calculated between the one-electron level spectrum of gas phase and of adsorbed ethylene oxide molecules. A new assignment of the photoelectron spectrum of ethylene oxide adsorbed at metal surfaces is proposed which differs from previous experimental and theoretical investigations of ethylene oxide adsorbed at various metal surfaces. © 1995.

The polLux microspectroscopy beam line at the swiss light source - Fink, Rainer; Raabe, Jörg; Quitmann, Christoph; Ade, Harald; et al. (SYNCHROTRON RADIATION INSTRUMENTATION, 2007)
The optical design and performance expectations of a Fresnel zone plate based scanning transmission x-ray microscopy (STXM) beamline at a bending magnet of the Swiss Light Source is described. The instrument allows microspectroscopy in polymer science in the water window and the study of magnetic materials with circularly polarized light. The beamline is based on a spherical grating monochromator with two gratings at a constant deviation angle and covers a photon energy range from 200 eV to 1000 eV. © 2007 American Institute of Physics.

Thermal evolution of cobalt deposits on Co3O4(111): Atomically dispersed cobalt, two-dimensional CoO islands, and metallic Co nanoparticles - Mehl, Sascha; Ferstl, Pascal; Schuler, Marina; Toghan, A.; Brummel, Olaf; Hammer, Lutz; Schneider, M. Alexander; Libuda, Jörg (Physical Chemistry Chemical Physics, 2015)
Cobalt oxide nanomaterials show high activity in several catalytic reactions thereby offering the potential to replace noble metals in some applications. We have developed a well-defined model system for partially reduced cobalt oxide materials aiming at a molecular level understanding of cobalt-oxide-based catalysis. Starting from a well-ordered Co3O4(111) film on Ir(100), we modified the surface by deposition of metallic cobalt. Growth, structure, and adsorption properties of the cobalt-modified surface were investigated by scanning tunneling microscopy (STM), low-energy electron diffraction (LEED), and infrared reflection absorption spectroscopy (IRAS) using CO as a probe molecule. The deposition of a submonolayer of cobalt at 300 K leads to the formation of atomically dispersed cobalt ions distorting the surface layer of the Co3O4 film. Upon annealing to 500 K the Co ions are incorporated into the surface layer forming ordered two-dimensional CoO islands on the Co3O4 grains. At 700 K, Co ions diffuse from the CoO islands into the bulk and the ordered Co3O4(111) surface is restored. Deposition of larger amounts of Co at 300 K leads to formation of metallic Co aggregates on the dispersed cobalt phase. The metallic particles sinter at 500 K and diffuse into the bulk at 700 K. Depending on the degree of bulk reduction, extended Co3O4 grains switch to the CoO(111) structure. All above structures show characteristic CO adsorption behavior and can therefore be identified by IR spectroscopy of adsorbed CO.

Thermally Activated Self-metalation of Carboxy-functionalized Porphyrin Films on MgO Nanocubes - Kollhoff, Fabian; Schneider, Johannes; Berger, Thomas; Diwald, Oliver; Libuda, Jörg (ChemPhysChem, 2018)
We investigated the adsorption of different free-base carboxyl-functionalized porphyrins, 5,10,15,20-tetrakis(4-carboxyphenyl)-21,23H-porphyrin (2H-TCPP) and 5(4-carboxyphenyl)-10,15,20-triphenyl-21,23H-porphyrin (2H-MCTPP), on MgO nanocubes combining IR, UV/Vis and photoluminescence emission spectroscopy. The thermal behavior of the films was monitored in-situ during annealing. Both porphyrins bind to the nanocubes via one and two acid groups respectively, yielding monolayer films consisting of tilted molecules. For 2H-TCPP, two acid groups remain free and give rise to a characteristic IR band. Self-assembly in a tilted adsorbate layer suppresses metalation at room temperature, in contrast to non-functionalized 2H-TPP, which adsorbs flat-lying. Upon heating, 2H-MCTPP undergoes full metalation at temperatures below 280 degrees C, whereas 2H-TCPP does not metalate at all. The hindered metalation reaction is attributed to the rigidity of the adsorbate film preventing complexation. Our results show that the properties of porphyrin films on oxides can be tuned in a wide range via the position and arrangement of carboxyl anchoring groups.
Keywords: porphyrin; oxide nanoparticles; infrared spectroscopy; UV; Vis spectroscopy; in-situ metalation

Thermally stable bis(trifluoromethylsulfonyl)imide salts and their mixtures - Scheuermeyer, Marlene; Kusche, Matthias Manfred; Agel, Friederike; Schreiber, Patrick; Maier, Florian; Steinrück, Hans-Peter; Davis, James H.; Heym, Florian; Jess, Andreas; Wasserscheid, Peter (New Journal of Chemistry, 2016)
We show that both tetraphenylphosphonium bis(trifluoromethylsulfonyl)imide ([PPh4][NTf2]) and Cs[NTf2] are low melting salts of exceptionally high and also very similar thermal stability. This similarity indicates that the thermal stability is dominated by the anion. Moreover, eutectic mixtures of [PPh4][NTf2] and Cs[NTf2] with melting points below 100 degrees C are presented. Surface analysis of the latter in the liquid state reveals a surprising depletion of (PPh4](+) ions from the surface.

Thermal stability of Pt films on TiO2(110): evidence for encapsulation - Pesty, François; Steinrück, Hans-Peter; Madey, Theodore E. (Surface Science, 1995)
We have studied the thermal stability of ultrathin platinum films on a rutile TiO(110) surface, using low energy ion scattering (LEIS) and X-ray photoelectron spectroscopy (XPS). At room temperature, Pt grows in three-dimensional islands on the TiO surface, with little indication of an interface reaction. Upon annealing to temperatures above 450 K in UHV, encapsulation of the Pt islands by Ti suboxides is observed; the rate of this process increases with annealing temperature and decreases with island thickness. The Ti layer on top of the Pt islands is identified as a reduced Ti species (1 ≤ n ≤ 3) with the degree of reduction depending on the thickness of the Pt islands. These results are discussed in the framework of the strong metal-support interaction (SMSI) effect. © 1995.

The role of defects in the dissociative adsorption of CO on Ni(100) - Steinrück, Hans-Peter; D'Evelyn, M.P.; Madix, R.J. (Surface Science, 1986)
We present a molecular beam study on the dissociative sticking coefficient for CO on a Ni(100) surface. In the range from 1.6 to 20 kcal/mol the observed dissociative sticking coefficient at a surface temperature of 500 K is 0.02 and independent of beam energy. Investigations on a sputter-damaged surface result in a sticking coefficient of 0.40, again independent of beam energy. The observed behavior can be explained by CO dissociation at defect sites. © 1986.

The role of defects in the photoconversion of 2-propanol on rutile titania: Operando spectroscopy combined with elementary studies - Kräuter, Jessica; Franz, Evanie; Waidhas, Fabian; Brummel, Olaf; Libuda, Jörg; Al-Shamery, Katharina (Journal of Catalysis, 2022)
Previous studies on the reaction chemistry of 2-propanol at rutile powders in liquid phase as well as at TiO2(1 1 0) surfaces under UHV conditions, both with low reduction degree, exhibited that partial photo oxidation is observable in the presence of oxygen, however, with low yields. Here, we show that at highly reduced surfaces a partial photo oxidation of 2-propanol is not only possible in the presence of oxygen but also in coadsorption with water or even without coadsorbates below room temperature. Thermally, only the conversion towards propane and propene was observed at temperatures above 550 K. Liquid Phase experiments further showed that the coadsorbate influences the acetone yield of the partial photo oxidation. While in the presence of oxygen an increasing acetone conversion was observed, the acetone yield is reduced in the presence of water in accordance with the hypothesis of an active site blocking by water.
CRIS-Team Scopus Importer:2022-02-04
Keywords: Acetone; Isopropanol; Liquid Phase; Model Catalysis; PC-IRRAS; Photo Oxidation; Rutile TiO; UHV; UV Irradiation

The role of solvation effects in the growth of TCNQ-based charge-transfer salts - Rösner, Benedikt; Späth, Andreas; Fink, Rainer (Journal of Crystal Growth, 2013)
Combining various microscopic techniques (VLM, SEM, STXM) we were able to investigate the growth TCNQ-based charge transfer salts nanocrystals in the wet chemical route. The results unambiguously show the impact of diffusion processes on the formation of Ag-TCNQ nanocrystals to support a modified mechanism for crystal formation. TCNQ-based charge transfer salts represent an attractive class of materials for utilisation in nanoscaled electronic devices. Detailed knowledge about the formation of metal-TCNQ salts is essential to control the growth of well-defined nanostructures. Silver template patterns were used to define well-ordered Ag-TCNQ structures. A comprehensive microscopic and spectroscopic investigation was conducted to examine the growth mechanism in wet-chemical environment in detail. Scanning electron microscopy (SEM) disclosed the overall morphology of the fabricated nanostructures while Scanning Transmission X-Ray Microscopy (STXM) provided insight into the chemical behaviour of the metal cation during the growth. The experimental results give clear evidence that solvation and diffusion of the metal counter ions controls the growth of well-defined metal-TCNQ nanocrystals. © 2013 Elsevier B.V. All rights reserved.

The role of surface defects in the adsorption and sesorption of hydrogen on Ni(111) - Rendulic, K.D.; Winkler, A.; Steinrück, Hans-Peter (Surface Science, 1987)
On a smooth Ni(111) surface both the β and the β state show activated adsorption. The desorption flux is highly peaked towards the surface normal. Defects introduce non-activated adsorption sites which lower the desorption temperatures in flash desorption. At the same time a cosine dependence of the desorption flux is obtained. Because of its small sticking coefficient the β state is already influenced by small defect concentrations; the β state is only affected on highly defective surfaces. © 1987 Elsevier Science Publishers B.V.

The sticking coefficient of H2 on Ni(111) as a function of particle energy and angle of incidence: A test of detailed balancing - Steinrück, Hans-Peter; Rendulic, K.D.; Winkler, A. (Surface Science, 1985)
The sticking coefficient of H/Ni(111) changes proportionally to the beam energy. The angular distribution of the probability of adsorption varies with cosθ; the angular distribution of desorption is found to change as cosθ at 300 K. Assuming validity of detailed balancing, the adsorption data suggest an energy distribution for desorption which agrees with existing time-of-flight measurements. © 1985.

The surface geometries of the medium and high coverage carbon monoxide structures c(2 × 4)-(2CO) and p(√7 × √7)R19°-(4CO) on Ni1 1 1 - Braun, Wolfgang; Steinrück, Hans-Peter; Held, Georg (Surface Science, 2005)
The surface geometries of the p(7×7)R19°-(4CO) and c(2 × 4)-(2CO) layers on Ni1 1 1 and the clean Ni1 1 1 surface were determined by low energy electron diffraction structure analysis. For the clean surface small but significant contractions of d and d (both 2.02 Å) were found with respect to the bulk interlayer distance (2.03 Å). In the c(2 × 4)-(2CO) structure these distances are expanded, with values of d = 2.08 Å and d = 2.06 Å and buckling of 0.08 and 0.02 Å, respectively, in the first and second layer. CO resides near hcp and fcc hollow sites with relatively large lateral shifts away from the ideal positions leading to unequal C-Ni bond lengths between 1.76 and 1.99 Å. For the p(7×7)R19°-(4CO) layer two best fit geometries were found, which agree in most of their atomic positions, except for one out of four CO molecules, which is either near atop or between bridge and atop. The remaining three molecules reside near hcp and fcc sites, again with large lateral deviations from their ideal positions. The average C-Ni bond length for these molecules is, however, the same as for CO on hollow sites at low coverage. The average C-Ni bond length at hollow sites, the interlayer distances, and buckling in the first Ni layer are similar to the c(2 × 4)-(2CO) geometry, only the buckling in the second layer (0.08 Å) is significantly larger. Lateral and vertical shifts of the Ni atoms in the first layer lead to unsymmetric environments for the CO molecules, which can be regarded as an imprint of the chiral p(7×7)R19° lattice geometry onto the substrate. © 2004 Elsevier B.V. All rights reserved.
Keywords: nickel; carbon monoxide; low energy electron diffraction (LEED)

The surface geometry of carbonmonoxide and hydrogen co-adsorbed on Ni1 1 1 - Braun, Wolfgang; Steinrück, Hans-Peter; Held, Georg (Surface Science, 2005)
A combination of photoelectron spectroscopy, temperature programmed desorption and low energy electron diffraction structure determinations have been applied to study the p(2 × 2) structures of pure hydrogen and co-adsorbed hydrogen and CO on Ni1 1 1. In agreement with earlier work atomic hydrogen is found to adsorb on fcc and hcp sites in the pure layer with H-Ni bond lengths of 1.74 Å. The substrate interlayer distances, d = 2.05 Å and d = 2.06 Å, are expanded with respect to clean Ni1 1 1 with buckling of 0.04 Å in the first layer. In the co-adsorbed phase CO occupies hcp sites and only the hydrogen atoms on fcc sites remain on the surface. d is even further expanded to 2.08 Å with buckling in the first and second layer of 0.06 and 0.02 Å, respectively. The C-O, C-Ni, and H-Ni bond lengths are within the range of values also found for the pure adsorbates. © 2004 Elsevier B.V. All rights reserved.

The surface geometry of carbon monoxide and oxygen co-adsorbed on Ni111 - Braun, Wolfgang; Steinrück, Hans-Peter; Held, Georg (Zeitschrift für Physikalische Chemie-International Journal of Research in Physical Chemistry & Chemical Physics, 2004)
Low energy electron diffraction (LEED) structure determinations have been performed for the p(2 x 2) structures of pure oxygen and oxygen co-adsorbed with CO on Ni 111. Optimisation of the non-geometric parameters led to very good agreement between experimental and theoretical IV-curves and hence to a high accuracy in the structural parameters. In agreement with earlier work atomic oxygen is found to adsorb on fcc sites in both structures. In the co-adsorbed phase CO occupies atop sites. The positions of the substrate atoms are almost identical, within 0.02 Å, in both structures, implying that the interaction with oxygen dominates the arrangement of Ni atoms at the surface.

The surface structure matters: thermal stability of phthalic acid anchored to atomically-defined cobalt oxide films - Xu, Tao; Schwarz, Matthias; Werner, Kristin; Mohr, Susanne; Amende, Maximilian; Libuda, Jörg (Physical Chemistry Chemical Physics, 2016)
We have investigated the influence of the structure of oxide surfaces on the thermal stability of anchored phthalic acid (PA) thin films. Specifically, we have performed temperature programmed infrared reflection absorption spectroscopy (TP-IRAS) of PA films deposited by physical vapor deposition (PVD) in ultra-high vacuum (UVH) onto three well-ordered surfaces: Co3O4(111), CoO(111) and CoO(100), all grown on Ir(100). Restructuring and desorption of PA were monitored in situ by TP-IRAS. Upon annealing of PA multilayers, co-adsorbed phthalic anhydride (PAA) desorbs at 200 K and a structural transition to a flat-lying adsorption geometry occurs at 250 K, before the PA multilayer desorbs at 300 K. At temperatures up to 400 K co-adsorbed mono-carboxylates partially desorb and partially convert to bis-carboxylates. Pronounced structure dependencies are observed regarding the thermal stability of the anchored bis-carboxylate monolayers. From Co3O4(111) the anchored PA desorbs over a wide range of temperatures centered at around 540 K. Weaker binding is observed for CoO(111) with desorption temperatures centered around 490 K. The strongest binding occurs on CoO(100), where the anchored PA films are found to be perfectly stable up to 510 K, before desorption starts and centers at around 580 K. The differences in binding strength are rationalized based on the density and the accessibility of the surface Co2+ ions. The findings show that the atomic structure of the oxide surface plays an important role in the stability of organic hybrid interfaces.

The surface trans effect: Influence of axial ligands on the surface chemical bonds of adsorbed metalloporphyrins - Hieringer, Wolfgang; Flechtner, Ken; Kretschmann, Andreas; Seufert, Knud; Auswärter, Willi; Barth, Johannes V.; Görling, Andreas; Steinrück, Hans-Peter; Gottfried, Michael (Journal of the American Chemical Society, 2011)
The chemical bond between an adsorbed, laterally coordinated metal ion and a metal surface is affected by an additional axial ligand on the metal ion. This surface analogon of the trans effect was studied in detail using monolayers of various M(II)-tetraphenylporphyrins (MTTPs, M = Fe, Co, Zn) and their nitrosyl complexes on a Ag(111) surface. X-ray photoelectron spectroscopy (XPS) shows that the oxidation state of the Fe and Co (but not Zn) ions in the MTPP monolayers is reduced because of the interaction with the substrate. This partial reduction is accompanied by the appearance of new valence states in the UV photoelectron and scanning tunneling spectra (UPS and STS), revealing the covalent character of the ion-substrate bond. Subsequent coordination of nitric oxide (NO) to the metal ions (Fe, Co) reverses these surface-induced effects, resulting in an increase of the oxidation states and the disappearance of the new valence states. Removal of the NO ligands by thermal desorption restores the original spectroscopic features, indicating that the described processes are fully reversible. The NO coordination also changes the spin state and thus the magnetic properties of the metal ions. Density-functional theory (DFT) calculations on model systems provide structural and energetic data on the adsorbed molecules and the surface chemical bond. The calculations reveal that competition effects, similar to the trans effect, play a central role and lead to a mutual interference of the two axial ligands, NO and Ag, and their bonds to the metal center. These findings have important implications for sensor technology and catalysis using supported planar metal complexes, in which the activity of the metal center is sensitively influenced by the substrate. © 2011 American Chemical Society.

The Synthesis of Nanostructured Ni5P4 Films and their Use as a Non-Noble Bifunctional Electrocatalyst for Full Water Splitting - Ledendecker, Marc; Calderon, Sandra Krick; Papp, Christian; Steinrück, Hans-Peter; Antonietti, Markus; Shalom, Menny (Angewandte Chemie International Edition, 2015)
The investigation of nickel phosphide (Ni5P4) as a catalyst for the hydrogen (HER) and oxygen evolution reaction (OER) in strong acidic and alkaline environment is described. The catalyst can be grown in a 3D hierarchical structure directly on a nickel substrate, thus making it an ideal candidate for practical water splitting devices. The activity of the catalyst towards the HER, together with its high stability especially in acidic solution, makes it one of the best non-noble materials described to date. Furthermore, Ni5P4 was investigated in the OER and showed activity superior to pristine nickel or platinum. The practical relevance of Ni5P4 as a bifunctional catalyst for the overall water splitting reaction was demonstrated, with 10 mA cm(-2) achieved below 1.7 V.
Keywords: ceramics; hydrogen evolution reaction; nickel phosphides; oxygen evolution reaction; water splitting reaction

The thermal chemistry of saturated layers of acetylene and ethylene on Ni(100) studied by in situ synchrotron x-ray photoelectron spectroscopy - Neubauer, Ralf; Whelan, Caroline; Denecke, Reinhard; Steinrück, Hans-Peter (Journal of Chemical Physics, 2003)
The thermal chemistry of saturated layers of acetylene and ethylene on Ni(100) was studied using in situ synchrotron x-ray photoelectron spectroscopy. The vibrational excitation of the C-H mode in gas phase ethylene was in the range of 410-420 meV, higher than the adsorbed states. It was concluded that the two peaks at 283.74 and 284.07 eV represented a single molecularly adsorbed ethylene species.

The transition from oxygen chemisorption to oxidation of ultra-thin Ni layers on Cu(111) - Domnick, Ralph; Held, Georg; Witte, Patrick; Steinrück, Hans-Peter (Journal of Chemical Physics, 2001)
The oxygen chemisorption and oxidation of Ni monolayers on Cu(111) were studied by high resolution XPS. As a result, new insight in the electronic state of the top-most surface atoms during adsorption and reaction of molecules which cannot be retrieved from single crystal surfaces because of the dominating bulk signal was obtained.

Thin membranes versus bulk substrates: Investigation of proximity effects in focused electron beam-induced processing - Walz, Marie-Madeleine; Vollnhals, Florian; Rietzler, Florian; Schirmer, Michael; Kunzmann, Andreas; Steinrück, Hans-Peter; Marbach, Hubertus (Journal of Physics D-Applied Physics, 2012)
The resolution of focused electron beam induced processing techniques is limited by electron scattering processes. General wisdom holds that using a membrane, this can be effectively improved due to a cutoff of the electron interaction volume and thus diminished proximity effects. Recently, we demonstrated that in contrast to the expectation, proximity effects can be indeed larger on a 200nm silicon nitride membrane than on the respective bulk substrate, due to charging-induced surface activation. Herein, we expand these investigations on proximity effects in electron beam-induced surface activation to other substrates and to electron beam-induced deposition followed by autocatalytic growth. © 2012 IOP Publishing Ltd.

Three-dimensional focal stack imaging in scanning transmission X-ray microscopy with an improved reconstruction algorithm - Ma, Limei; Zhang, Xiangzhi; Xu, Zijian; Späth, Andreas; Xing, Zhenjiang; Sun, Tianxiao; Tai, Renzhong (Optics Express, 2019)
Focal stack (FS) is an effective technique for fast 3D imaging in high-resolution scanning transmission X-ray microscopy. Its crucial issue is to assign each object within the sample to the correct position along the optical axis according to a proper focus measure. There is probably information loss with previous algorithms for FS reconstruction because the old algorithms can only detect one focused object along each optical-axial pixel line (OAPL). In this study, we present an improved FS algorithm, which utilizes an elaborately calculated threshold for normalized local variances to extract multiple focused objects in each OAPL. Simulation and experimental results show its feasibility and high efficiency for 3D imaging of high contrast, sparse samples. It is expected that our advanced approach has potential applications in 3D X-ray microscopy for more complex samples. (C) 2019 Optical Society of America under the terms of the OSA Open Access Publishing Agreement
CRIS-Team WoS Importer:2019-03-15

Tilted adsorption of benzene on Pt (110) 1 × 2 - Zebisch, P.; Stichler, M.; Trischberger, P.; Weinelt, M.; Steinrück, Hans-Peter (Surface Science, 1998)
The adsorption of benzene on the reconstructed Pt (110) 1 × 2 surface was studied by temperature-programmed desorption (TPD), low-energy electron diffraction (LEED), angle-resolved UV photoemission (ARUPS) and near-edge X-ray absorption spectroscopy (NEXAFS). At 100 K, benzene is molecularly adsorbed on the Pt (110) 1 × 2 surface. The saturated layer is disordered and corresponds to a coverage of ∼0.28 ML. Annealing to 280 K leads to partial benzene desorption and to the formation of a well-ordered (4 × 2) layer (relative to the unreconstructed surface) with a coverage of 0.25 ML. The missing ((2n + 1)/4, 0) adsorbate LEED spots along [11̄0] indicate a glide plane in the adsorbate structure and the existence of two molecules per unit cell. In this layer, benzene adsorbs with the molecular plane tilted by ∼30° in the [001] direction, as determined from ARUPS and NEXAFS. This geometry corresponds to a nearly flat adsorption on the (111) microfacets of the troughs of the reconstructed surface. The molecules have a well-defined azimuthal orientation with a C-H bond along the [11̄0] azimuth. For dilute layers (θ = 0.12 ML) and a disordered layer with the same coverage as the ordered layer (θ = 0.25 ML), the molecules are also tilted into the troughs, a preferential azimuthal orientation is, however, not observed. © 1998 Elsevier Science B.V.

Time- and Temperature-Dependent Growth Behavior of Ionic Liquids on Au(111) Studied by Atomic Force Microscopy in Ultrahigh Vacuum - Meusel, Manuel; Gezmis, Emine; Jaekel, Simon; Lexow, Matthias; Bayer, Andreas; Maier, Florian; Steinrück, Hans-Peter (Journal of Physical Chemistry C, 2021)
We deposited defined amounts of [C1C1Im][Tf2N] on Au(111) at different temperatures and investigated the morphology and wetting behavior of the deposited films by atomic force microscopy. For multilayer coverages, we observe a drastically different growth behavior when comparing deposition at room temperature (RT) and deposition below 170 K followed by slow annealing to RT. Upon deposition at RT, we find the formation of 2–30 nm high and 50–500 nm wide metastable 3D droplets on top of a checkerboard-type wetting layer. These droplets spread out into stable 2D bilayers, on the time scale of hours and days. The same 2D bilayer structure is obtained after deposition below 170 K and slow annealing to RT. We present a statistical analysis on the time-dependent changes of the shape and volume of the 3D droplets and the 2D bilayers. We attribute the stabilization of the 2D bilayers on the wetting layer and on already formed bilayers to the high degree of order in these layers. Notably, the transformation process from the 3D droplets to 2D bilayer islands is accelerated by tip effects and also X-ray radiatio

Time-dependent changes in the growth of ultrathin ionic liquid films on Ag(111) - Lexow, Matthias; Talwar, Timo; Heller, Bettina; May, Benjamin; Bhuin, Radha Gobinda; Maier, Florian; Steinrück, Hans-Peter (Physical Chemistry Chemical Physics, 2018)
Various amounts of the ionic liquids (ILs) [C(1)C(1)Im][Tf2N] and [C(8)C(1)Im][Tf2N] were deposited in vacuo by physical vapour deposition (PVD) on single crystalline Ag(111) at room temperature and subsequently monitored by angle-resolved X-ray photoelectron spectroscopy (ARXPS) as a function of time. For very low coverages of up to one closed molecular layer, an initial wetting layer was rapidly formed for both ILs. Deposition of higher amounts of [C(1)C(1)Im][Tf2N] revealed an initial three-dimensional film morphology. On the time scale of hours, characteristic changes of the XPS signals were observed. These are interpreted as island spreading and a transformation towards a nearly two dimensional [C(1)C(1)Im][Tf2N] film as the final state. In contrast, a film morphology close to 2D was found from the very beginning for [C(8)C(1)Im][Tf2N] deposited on Ag(111) demonstrating the influence of the alkyl chain length on the growth kinetics. These studies also highlight the suitability of time-resolved ARXPS for the investigation of IL/solid interfaces, which play a crucial role in IL thin film applications such as in catalysis, sensor, lubrication, and coating technologies.

Toward ionic-liquid-based model catalysis: Growth, orientation, conformation, and interaction mechanism of the [Tf2N]- anion in [BMIM][Tf2N] thin films on a well-ordered alumina surface - Sobota, Marek; Nikiforidis, Ioannis; Hieringer, Wolfgang; Paape, Natalia; Happel, Markus; Steinrück, Hans-Peter; Görling, Andreas; Wasserscheid, Peter; Laurin, Mathias; Libuda, Jörg (Langmuir, 2010)
Aiming at a better understanding of the interaction of ionic liquid (IL) thin films with oxide supports, we have performed a model study under ultrahigh vacuum (UHV) conditions. We apply infrared reflection absorption spectroscopy (IRAS) in combination with density functional theory (DFT). Thin films of 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide [BMIM][Tf N] are grown on an atomically flat, well-ordered alumina film on NiAl(110) using a novel UHV-compatible evaporator. Time-resolved IRAS measured during the growth and subsequent thermal desorption points toward reversible molecular adsorption and desorption. There was no indication of decomposition. The vibrational bands are assigned with the help of DFT calculations. Strong relative intensity changes in individual [TfN] bands are observed in the monolayer region. This indicates pronounced orientation effects for the anion. The adsorption geometry of [TfN] is determined on the basis of a detailed comparison with DFT. The results suggest that [TfN] anions adopt a cis conformation in the submonolayer region. They adsorb in a slightly tilted orientation with respect to the surface, mainly interacting with the support via the sulfonyl groups. © 2010 American Chemical Society.

Towards a molecular understanding of cation-anion interactions-Probing the electronic structure of imidazolium ionic liquids by NMR spectroscopy, X-ray photoelectron spectroscopy and theoretical calculations - Cremer, Till; Kolbeck, Claudia; Lovelock, Kevin; Paape, Natalia; Woelfel, Rene; Schulz, Peter; Wasserscheid, Peter; Weber, Henry; Thar, Jens; Kirchner, Barbara; Maier, Florian; Steinrück, Hans-Peter (Chemistry - A European Journal, 2010)
Ten [CCIm] (1-methyl-3- octylimidazolium)-based ionic liquids with anions Cl, Br , I, [NO], [BF] , [TfO], [PF], [Tf N], [PfN], and [FAP] (TfO = trifluoromethylsulfonate, TfN = bis(trifluoromethylsulfonyl) imide, PfN = bis(pentafluoroethylsulfonyl)imide, FAP = tris-(pentafluoroethyl)trifluorophosphate) and two [CC CIm] (1,2-dimethyl-3-octylimidazolium)-based ionic liquids with anions Br and [TfN] were investigated by using X-ray photoelectron spectroscopy (XPS), NMR spectroscopy and theoretical calculations. WhileH NMR spectroscopy is found to probe very specifically the strongest hydrogen-bond interaction between the hydrogen attached to the C position and the anion, a comparative XPS study provides first direct experimental evidence for cation-anion charge-transfer phenomena in ionic liquids as a function of the ionic liquid's anion. These charge-transfer effects are found to be surprisingly similar for [CCIm] and [CCC Im] salts of the same anion, which in combination with theoretical calculations leads to the conclusion that hydrogen bonding and charge transfer occur independently from each other, but are both more pronounced for small and more strongly coordinating anions, and are greatly reduced in the case of large and weakly coordinating anions. © 2010 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.

Towards an efficient liquid organic hydrogen carrier fuel cell concept - Sievi, Gabriel; Geburtig, Denise; Skeledzic, Tanja; Bösmann, Andreas; Preuster, Patrick; Brummel, Olaf; Waidhas, Fabian; Montero, María A.; Khanipourmehrin, Peyman; Katsounaros, Ioannis; Libuda, Jörg; Mayrhofer, Karl; et al. (Energy and Environmental Science, 2019)
The high temperature required for hydrogen release from Liquid Organic Hydrogen Carrier (LOHC) systems has been considered in the past as the main drawback of this otherwise highly attractive and fully infrastructure-compatible form of chemical hydrogen storage. According to the state-of-the art, the production of electrical energy from LOHC-bound hydrogen, e.g. from perhydro-dibenzyltoluene (H18-DBT), requires provision of the dehydrogenation enthalpy (e.g. 65 kJ mol-1 (H2) for H18-DBT) at a temperature level of 300 °C followed by purification of the released hydrogen for subsequent fuel cell operation. Here, we demonstrate that a combination of a heterogeneously catalysed transfer hydrogenation from H18-DBT to acetone and fuel cell operation with the resulting 2-propanol as a fuel, allows for an electrification of LOHC-bound hydrogen in high efficiency (>50%) and at surprisingly mild conditions (temperatures below 200 °C). Most importantly, our proposed new sequence does not require an external heat input as the transfer hydrogenation from H18-DBT to acetone is almost thermoneutral. In the PEMFC operation with 2-propanol, the endothermal proton release at the anode is compensated by the exothermic formation of water. Ideally the proposed sequence does not form and consume molecular H2 at any point which adds a very appealing safety feature to this way of producing electricity from LOHC-bound hydrogen, e.g. for applications on mobile platforms.
CRIS-Team Scopus Importer:2019-07-23

Towards the engineering of molecular nanostructures: Local anchoring and functionalization of porphyrins on model-templates - Ditze, Stefanie; Röckert, Michael; Buchner, Florian; Zillner, Elisabeth; Stark, Michael Werner; Steinrück, Hans-Peter; Marbach, Hubertus (Nanotechnology, 2013)
We demonstrate that Cu(111) surfaces pre-covered with a submonolayer of copper oxide or metallic nickel are suitable model-templates for the selective adsorption and/or localized functionalization of functional molecules such as different free base porphyrins and metalloporphyrins. The oxide/Cu(111) model-template is able to steer the adsorption of tetraphenylporphyrins (TPP): 2HTPP selectively adsorbs on the bare Cu areas, and for CoTPP anchoring at the rim of the copper oxide islands is found. On the Ni/Cu(111) model-template TPP molecules are pinned on the Ni areas while they are mobile on the bare Cu surface. Interestingly, adsorption of free base octaethylporphyrin on Ni/Cu(111) leads to a local functionalization, namely the metalation to NiOEP on the Ni areas. Model-template preparation and characterization by scanning tunneling microscopy is performed at room temperature. © 2013 IOP Publishing Ltd.

Toward well-defined metal-polymer interfaces: Temperature-controlled suppression of subsurface diffusion and reaction at the calcium/poly(3- Hexylthiophene) interface - Bebensee, Fabian; Schmid, Martin; Steinrück, Hans-Peter; Campbell, C. T.; Gottfried, Michael (Journal of the American Chemical Society, 2010)
The thickness of the reaction zone at the interface between calcium and regioregular poly(3-hexylthiophene), which is one of the best performing metal/polymer combinations in photovoltaic devices, depends critically on the temperature of the polymer during the initial phase of metal deposition. It is shown that deposition at 130 K reduces the thickness of the reaction zone, an effect that also persists after warming to room temperature. © 2010 American Chemical Society.

Triaqua surface coordination complex on Co3O4(111) - Yan, George; Wähler, Tobias; Schuster, Ralf; Schwarz, Matthias; Hohner, Chantal; Werner, Kristin; Libuda, Jörg; Sautet, Philippe (ABSTRACTS OF PAPERS OF THE AMERICAN CHEMICAL SOCIETY, 2019)
CRIS-Team WoS Importer:2020-05-02

Tuning the light absorption of a molecular vanadium oxide system for enhanced photooxidation performance - Forster, Johannes; Rösner, Benedikt; Khusniyarov, Marat; Streb, Carsten (Chemical Communications, 2011)

Tuning the molecular order of C60-based self-assembled monolayers in field-effect transistors - Schmaltz, Thomas; Khassanov, Artöm; Steinrück, Hans-Peter; Magerl, Andreas; Hirsch, Andreas; Halik, Marcus (Nanoscale, 2014)
The control of order in organic semiconductor systems is crucial to achieve desired properties in electronic devices. We have studied the order in fullerene functionalized self-assembled monolayers by mixing the active molecules with supporting alkyl phosphonic acids of different chain length. By adjusting the length of the molecules, structural modifications of the alignment of the C60 head groups within the SAM can be tuned in a controlled way. These changes on the sub-nanometre scale were analysed by grazing incidence X-ray diffraction and X-ray reflectivity. To study the electron transport properties across these layers, self-assembled monolayer field-effect transistors (SAMFETs) were fabricated containing only the single fullerene monolayer as semiconductor. Electrical measurements revealed that a high 2D crystalline order is not the only important aspect. If the fullerene head groups are too confined by the supporting alkyl phosphonic acid molecules, defects in the crystalline C60 film, such as grain boundaries, start to strongly limit the charge transport properties. By close interpretation of the results of structural investigations and correlating them to the results of electrical characterization, an optimum chain length of the supporting alkyl phosphonic acids in the range of C10 was determined. With this study we show that minor changes in the order on the sub-nanometre scale, can strongly influence electronic properties of functional self-assembled monolayers.

Ultrafast x-ray photoelectron spectroscopy in the microsecond time domain - Höfert, Oliver; Gleichweit, Christoph; Steinrück, Hans-Peter; Papp, Christian (Review of Scientific Instruments, 2013)
We introduce a new approach for ultrafast in situ high-resolution X-ray photoelectron spectroscopy (XPS) to study surface processes and reaction kinetics on the microsecond timescale. The main idea is to follow the intensity at a fixed binding energy using a commercial 7 channeltron electron analyzer with a modified signal processing setup. This concept allows for flexible switching between measuring conventional XP spectra and ultrafast XPS. The experimental modifications are described in detail. As an example, we present measurements for the adsorption and desorption of CO on Pt(111), performed at the synchrotron radiation facility BESSY II, with a time resolution of 500 μs. Due to the ultrafast measurements, we are able to follow adsorption and desorption in situ at pressures of 2 × 10 mbar and temperatures up to 500 K. The data are consistently analyzed using a simple model in line with data obtained with conventional fast XPS at temperatures below 460 K. Technically, our new approach allows measurement on even shorter timescales, down to 20 μs. © 2013 AIP Publishing LLC.

Ultrathin Carbon Nanomembranes from 5,10,15,20-Tetraphenylporphyrin: Electron Beam Induced Fabrication and Functionalization via Focused Electron Beam Induced Processing - Preischl, Christian; Rohdenburg, Markus; Bilgilisoy, Elif; Cartaya, René; Swiderek, Petra; Marbach, Hubertus (Journal of Physical Chemistry C, 2021)
Two-dimensional (2D) materials are promising candidates as main components for future applications in electronics, optics, and magnetics due to their specific properties. One method to fabricate such 2D materials is electron-induced cross-linking of organic precursor molecules. In this work, we significantly expand the concept from wet chemically prepared self-assembled monolayers (SAMs) to physisorbed molecular layers of functional organic molecules prepared by thermal sublimation under (ultrahigh) vacuum. More specifically, 1.5 nm thick carbon nanomembranes (CNM) were fabricated from a porphyrin, namely 5,10,15,20-tetraphenylporphyrin (2H-TPP) molecules. The processes occurring on a molecular scale during electron-induced cross-linking of 2H-TPP molecules are analyzed by reflection absorption infrared spectroscopy (RAIRS) and electron stimulated desorption (ESD). ESD shows that beside hydrogen, no further fragments desorb during electron irradiation. In RAIRS, most of the significant bands resulting from C-H or N-H bonds have disappeared after electron irradiation. The resulting 2D nanomembranes can be functionalized by focused electron beam induced processing (FEBIP). Clean iron nanostructures are fabricated on top of the 2D material via either electron beam induced deposition (EBID) or electron beam induced surface activation (EBISA). The resulting hybrids consisting of metallic nanostructures and nonmetallic 2D material can be transferred onto either solid substrates or onto grids to obtain free-standing metal/CNM hybrid structures. This transfer process gives evidence of the flexibility and high mechanical stability of the CNM fabricated from 2H-TPP molecules. In this work, we thus demonstrate that porphyrins, which are of high scientific interest and play a crucial role in nature, can be used for the fabrication of stable 2D materials.
CRIS-Team Scopus Importer:2021-01-15

Ultrathin films of Pt on TiO2(110): Growth and chemisorption-induced surfactant effects - Steinrück, Hans-Peter; Pesty, François; Zhang, Lei; Madey, Theodore E. (Physical Review B, 1995)
The growth of ultrathin platinum films on a rutile TiO2(110) surface has been studied using low-energy ion scattering and x-ray photoelectron spectroscopy. In the temperature range between 160 and 420 K, Pt grows in three-dimensional islands on the TiO2 surface with the size of the islands increasing with increasing surface temperature and without indication of an interface reaction. Evaporation of Pt in the presence of CO leads to a significantly higher degree of wetting. This behavior is attributed to a chemisorption-induced surfactant effect. © 1995 The American Physical Society.

Ultrathin ionic liquid films on metal surfaces: adsorption, growth, stability and exchange phenomena - Lexow, Matthias; Maier, Florian; Steinrück, Hans-Peter (Advances in Physics: X, 2020)
The interface of ionic liquids (ILs) with solid surfaces is of pivotal interest for many applications, ranging from sensors, lubrication, separation technology, and electronics to electrochemistry and catalysis. We present a short review on ultrathin layers of ionic liquids on metal surfaces using a surface science approach. We mainly focus on specific examples of imidazolium-based ionic liquids on Ag(111) and Au(111) studied by angle-resolved X-ray photoelectron spectroscopy, and relate the obtained results to existing literature. We address a variety of phenomena on the molecular level, namely, (i) the adsorption, growth and wetting behavior of ILs, (ii) the thermal stability and desorption of ILs, (iii) exchange processes of anions and cations at the IL/solid interface, and (iv) the replacement of ILs from the IL/solid interface by porphyrins.
CRIS-Team Scopus Importer:2020-07-31
Keywords: growth mode; Ionic Liquids; liquid/solid interface; surface Science; X-ray photoelectron spectroscopy

Understanding the Buoy Effect of Surface-Enriched Pt Complexes in Ionic Liquids: A Combined ARXPS and Pendant Drop Study** - Hemmeter, Daniel; Paap, Ulrike; Wellnhofer, Nicolas; Gezmis, Emine; Kremitzl, Daniel; Wasserscheid, Peter; Steinrück, Hans-Peter; Maier, Florian (ChemPhysChem, 2023)
Recently, we demonstrated that Pt catalyst complexes dissolved in the ionic liquid (IL) [C4C1Im][PF6] can be deliberately enriched at the IL surface by introducing perfluorinated substituents, which act like buoys dragging the metal complex towards the surface. Herein, we extend our previous angle-resolved X-ray photoelectron spectroscopy (ARXPS) studies at complex concentrations between 30 and 5 %mol down to 1 %mol and present complementary surface tension pendant drop (PD) measurements under ultraclean vacuum conditions. This combination allows for connecting the microscopic information on the IL/gas interface derived from ARXPS with the macroscopic property surface tension. The surface enrichment of the Pt complexes is found to be most pronounced at 1 %mol. It also displays a strong temperature dependence, which was not observed for 5 %mol and above, where the surface is already saturated with the complex. The surface enrichment deduced from ARXPS is also reflected by the pronounced decrease in surface tension with increasing concentration of the catalyst. We furthermore observe by ARXPS and PD a much stronger surface affinity of the buoy-complex as compared to the free ligands in solution. Our results are highly interesting for an optimum design of IL-based catalyst systems with large contact areas to the surrounding reactant/product phase, such as in supported IL phase (SILP) catalysis.
CRIS-Team Scopus Importer:2023-11-10
Keywords: homogeneous catalysis; ionic liquids; surface enrichment; surface tension; X-ray photoelectron spectroscopy (XPS)

Understanding the contrast mechanism in Scanning Tunneling Microscopy (STM) images of an intermixed tetraphenylporphyrin layer on Ag(111) - Comanici, Karmen; Buchner, Florian; Flechtner, Ken; Lukasczyk, Thomas; Gottfried, Michael; Steinrück, Hans-Peter; Marbach, Hubertus (Langmuir, 2008)
The appearance of tetraphenylporphyrins in scanning tunneling micrographs depends strongly on the applied bias voltage. Here, we report the observation and identification of certain features in scanning tunneling microscopy (STM) images of intermixed layers of tetraphenylporphyrin (2HTPP) and cobalt-tetraphenylporphyrin (CoTPP) on Ag(111). A significant fraction of an ordered monolayer of commercially available CoTPP appears as "pits" at negative bias voltages around - 1 V. The obvious possibility that these pits are missing molecules within the ordered layer could be ruled out by imaging the molecules at reduced bias voltages, at which the contrast of the pits fades, and at positive bias voltages around +1 V, at which the image contrast is inverted. With the investigation of the electronic structure, in particular the density of states (DOS) close to the Fermi level, of CoTPP and 2HTPP layers by means of ultraviolet photoelectron spectroscopy (UPS) and scanning tunneling spectroscopy (STS), the contrast mechanism was clarified. The correlation of the bias dependent contrast with the UPS data enabled us to interpret the"pits" as individual 2HTPP molecules. Additional evidence could be provided by imaging layers of different mixtures of 2HTPP and CoTPP and by high-resolution STM imaging of the features in CoTPP. © 2008 American Chemical Society.

Unexpected Michael Additions on the Way to 2.3,8.9-Dibenzanthanthrenes with Interesting Structural Properties - Reus, Christian; Lechner, Marc; Schulze, Matthias; Lungerich, Dominik; Diner, Colin; Gruber, Marco; Stryker, Jeffrey M.; Hampel, Frank; Jux, Norbert; Tykwinski, Rik (Chemistry - A European Journal, 2016)
The synthesis and properties of a new polycyclic aromatic hydrocarbon containing eight annulated rings and based on the anthanthrene core is described. An unexpected, nucleophile-dependent Michael addition to a dibenzanthanthrene-1,7-dione is found, giving a product with three triisopropylsilylacetylene units and a remarkable solid-state structure (as determined by X-ray crystallography).
EAM Import::2019-03-12

Unraveling the Effect of Rh Isolation on Shallow d States of Gallium-Rhodium Alloys - Hsieh, Tzung En; Maisel, Sven; Wittkämper, Haiko; Frisch, Johannes; Steffen, Julien; Wilks, Regan G.; Papp, Christian; Görling, Andreas; Bär, Marcus (Journal of Physical Chemistry C, 2023)
In this study, we report the electronic and chemical structure of supported GaRh alloys as model systems for the active phase in supported catalytically active liquid metal solutions (SCALMS). We prepared a series of gallium-rhodium samples with different Rh contents and tracked the evolution of the sample topography and surface electronic structure via photoemission spectroscopy in combination with ab initio calculations and electron microscopy. Our results reveal a characteristic shift of the Rh 3d core levels and narrowing and shifting of the Rh 4d derived band with decreasing Rh content. Calculations show that these spectroscopic observations can be explained by the coexistence of isolated Rh atoms in random GaRh alloys and GaRh intermetallic compounds (IMCs). These results contribute to an enhancement of the fundamental understanding of the electronic surface structure of GaRh alloys, which is crucially required for apprehending and thus further exploiting the improved catalytic activity of GaRh SCALMS.
CRIS-Team Scopus Importer:2023-11-17

Vacuum Surface Science Meets Heterogeneous Catalysis: Dehydrogenation of a Liquid Organic Hydrogen Carrier in the Liquid State - Matsuda, Takashi; Taccardi, Nicola; Schwegler, Johannes; Wasserscheid, Peter; Steinrück, Hans-Peter; Maier, Florian (ChemPhysChem, 2015)
Ultrahigh vacuum (UHV) surface science techniques are used to study the heterogeneous catalytic dehydrogenation of a liquid organic hydrogen carrier in its liquid state close to the conditions of real catalysis. For this purpose, perhydrocarbazole (PH), otherwise volatile under UHV, is covalently linked as functional group to an imidazolium cation, forming a non-volatile ionic liquid (IL). The catalysed dehydrogenation of the PH unit as a function of temperature is investigated for a Pt foil covered by a macroscopically thick PH-IL film and for Pd particles suspended in the PH-IL film, and for PH-IL on Au as inert support. X-ray photoelectron spectroscopy and thermal desorption spectroscopy allows us to follow in situ the catalysed transition of perhydrocarbazole to carbazole at technical reaction temperatures. The data demonstrate the crucial role of the Pt and Pd catalysts in order to shift the dehydrogenation temperature below the critical temperature of thermal decomposition.
Keywords: heterogeneous catalysis; ionic liquids; liquid organic hydrogen carrier; surface science; x-ray photoelectron spectroscopy

Vibrationally resolved in situ XPS study of activated adsorption of methane on Pt(111) - Fuhrmann, Thomas; Kinne, Martin; Whelan, Caroline; Zhu, Junfa; Denecke, Reinhard; Steinrück, Hans-Peter (Chemical Physics Letters, 2004)
A combination of high-resolution X-ray photoelectron spectroscopy at BESSY II and molecular beam techniques has been used to investigate the dissociative adsorption of CH and CD on a Pt(111) surface. From a detailed analysis of C 1s core-level spectra, CH (CD ) has been identified as the adsorbed species at 120 K, independent of the kinetic energy of the impinging methane molecules (in the range from 0.25 to 0.83 eV). The spectra show a unique fine structure, caused by vibrational excitations of C-H (C-D) stretching modes in the photoemission process. Using temperature-programmed XPS, CH is identified as the intermediate in the dehydrogenation process, forming at 260 K and further dehydrogenating to carbon above 500 K. © 2004 Elsevier B.V. All rights reserved.

Wasserstoff, chemisch gespeichert - Papp, Christian; Wasserscheid, Peter; Libuda, Jörg; Steinrück, Hans-Peter (Nachrichten aus der Chemie, 2014)
Ein Ansatz, Energie chemisch zu speichern, sind flüssige organische Wasserstoffträger. Die Oberflächenforschung leistet Beiträge zum mechanistischen Verständnis der katalytischen Wasserstofffreisetzung und zieht Schlussfolgerungen für die praktische Anwendung solcher Techniken.

Water Chemistry on Model Ceria and Pt/Ceria Catalysts - Lykhach, Yaroslava; Johanek, Viktor; Aleksandrov, Hristiyan A.; Kozlov, Sergey M.; Happel, Markus; Skala, Tomas; St Petkov, Petko; Tsud, Nataliya; Vayssilov, Georgi N.; Prince, Kevin C.; Neyman, Konstantin M.; Matolin, Vladimir; et al. (Journal of Physical Chemistry C, 2012)
We have studied the interaction of water with stoichiometric CeO2(111)/Cu(111), partially reduced CeO2-x/Cu(111), and Pt/CeO2/Cu(111) model catalysts by means of synchrotron-radiation photoelectron spectroscopy (SRPES), resonant photoemission spectroscopy (RPES) at the Ce 4d edge, infrared reflection absorption spectroscopy (IRAS), and density functional (DF) calculations. The principal species formed during adsorption of water at 160 K on CeO2(111) films is chemisorbed molecular water. On the surface of CeO2-x water partially dissociates yielding hydroxyl groups. By use of core-level PES, differentiation between chemisorbed water and hydroxyl groups is complicated by the overlap of the corresponding spectral features. Nevertheless, we determined three characteristic indicators for OH groups on ceria: (i) the presence of 1 pi and 3 sigma states in valence band (VB) PES; (ii) an increase of the binding energy (BE) separation between the O 1s spectral components of lattice oxygen and OH/H2O; (iii) an increase of the amplitude of the Ce3+ resonance in RPES. Chemisorbed water desorbs below 400 K and hydroxyl groups vanish at 500 K. The most favorable configurations of chemisorbed water and hydroxyl groups have been investigated by DF calculations. Both CeO2(111) and CeO2-x involve strongly tilted H2O and OH species which complicate their detection by IRAS. On Pt/CeO2, water adsorbs molecularly at 160 K but undergoes partial dissociation during annealing. The dissociation of water is accompanied by spillover of hydrogen to ceria and formation of hydroxyl groups between 180 and 250 K. Above 250 K, decomposition of hydroxyl groups and reverse spillover of hydrogen from ceria to Pt occurs, followed by desorption of molecular water.

Water-dispersible PVA-based dry microballoons with potential for biomedical applications - Tzvetkov, George; Paradossi, Gaio; Tortora, Mariarosaria; Fernandes, Paulo; Fery, Andreas; Graf-Zeiler, Birgit; Fink, Rainer (Materials Science and Engineering C, 2010)
This paper reports on the preparation and characterization of stable poly(vinyl alcohol) (PVA)-based dry hollow microparticles, readily convertible to gas-filled microballoons (MBs) in water suspension. The rehydrated MBs can be used as ultrasound contrast agents and for targeted drug delivery, while the dry MBs are suitable for encapsulation of biologically active gases. The MBs powder material is obtained by freeze-drying the as-prepared telechelic PVA-shelled MBs aqueous dispersion. The microstructure of the lyophilized MBs as well as of the starting and the reconstituted MBs in water suspension was examined using transmission electron microscopy (TEM), scanning electron microscopy (SEM), scanning transmission X-ray microspectroscopy (STXM) and confocal laser scanning microscopy (CLSM). STXM observations below and above the oxygen K-edge reveal that 80% of the MBs originating from the lyophilized particles are gas-filled. Moreover, local carbon K near-edge X-ray absorption fine structure spectroscopy (NEXAFS) measurements evidenced that the chemical composition of the polymeric shell is preserved during the freeze-drying process and subsequent shelf storage for at least more than one year. © 2010 Elsevier B.V. All rights reserved.

Water on Atomically-Defined Cobalt Oxide Surfaces Studied by Temperature-Programmed IR Reflection Absorption Spectroscopy and Steady State Isotopic Exchange - Schwarz, Matthias; Mohr, Susanne; Hohner, Chantal; Werner, Kristin; Xu, Tao; Libuda, Jörg (Journal of Physical Chemistry C, 2018)
In this work, we investigate the interaction of water with three different atomically defined cobalt oxide surfaces under ultrahigh vacuum (UHV) conditions using time-resolved and temperature-programmed infrared reflection–absorption spectroscopy (TR-IRAS, TP-IRAS) in combination with isotopic exchange experiments. The three surfaces, CoO(100), CoO(111), and Co3O4(111), are prepared in form of well-ordered films on Ir(100). Very different behavior is observed on the three surfaces, both with respect to D2O adsorption and desorption. On CoO(100), water adsorbs molecularly. It forms extended ice clusters even at low adsorption temperature (200 K) and which desorb molecularly at 200 K (Ea,des ∼ 60 kJ·mol–1). A very small amount of defect sites is observed at which D2O dissociates and forms strongly bound OD groups. On CoO(111), the interaction with ordered facets is very weak and no adsorption occurs at these sites at 200 K. The CoO(111) films expose, however, a higher density of defects as compared to the CoO(100) films, at which D2O dissociates and forms strongly bound OD species with desorption temperatures of 455 ± 10 and 620 ± 10 K, respectively. In contrast to the above cases, water interacts strongly with the Co3O4(111) surface. At 200 K, D2O dissociates readily and forms a partially dissociated (D2O)n(OD)m network. With increasing temperature, the (D2O)n(OD)m network breaks up into (D2O)n(OD)m clusters the size of which decreases with increasing temperature. Desorption of molecular D2O occurs over a broad temperature range from 210 to 470 K (Ea,des ∼ 60 to ∼ 140 kJ·mol–1). Above 470 K, only isolated OD species reside on the surface which desorb at 540 ± 20 K. Isotopic exchange experiments with D2O and H2O on Co3O4(111) show that isotopic scrambling in the (D2O)n(OD)m clusters is slow in comparison to exchange with the gas phase and that the clusters are composed of distinct species that show different exchange rates with the gas phase. The structure-dependent differences regarding the interaction with D2O are rationalized in terms of the surface termination and coordination environment of the surface ions on the three different surfaces.
EAM Import::2019-03-12

Water on Oxide Surfaces: A Triaqua Surface Coordination Complex on Co3O4(111) - Yan, George; Wähler, Tobias; Schuster, Ralf; Schwarz, Matthias; Hohner, Chantal; Werner, Kristin; Libuda, Jörg; Sautet, Philippe (Journal of the American Chemical Society, 2019)
The interaction of water with metal oxides controls their activity and stability in heterogeneous catalysis and electrocatalysis. In this work, we combine density functional theory calculations and infrared reflection absorption spectroscopy (IRAS) to identify the structural motifs formed upon interaction of water with an atomically defined Co3O4(111) surface. Three principal structures are observed: (i) strongly bound isolated OD, (ii) extended hydrogen-bonded OD/D2O structures, and (iii) a third structure which has not been reported to our knowledge. In this structure, surface Co2+ ions bind to three D2O molecules to form an octahedrally coordinated Co2+ with a "half hydration shell". We propose that this hydration structure represents an important intermediate in reorganization and dissolution on oxide surfaces which expose highly unsaturated surface cations.
CRIS-Team WoS Importer:2019-05-03

Water on Oxide Surfaces: A Triaqua Surface Coordination Complex on Co3O4(111) - Yan, George; Wähler, Tobias; Schuster, Ralf; Schwarz, Matthias; Hohner, Chantal; Werner, Kristin; Libuda, Jörg; Sautet, Philippe (Journal of the American Chemical Society, 2019)
The interaction of water with metal oxides controls their activity and stability in heterogeneous catalysis and electrocatalysis. In this work, we combine density functional theory calculations and infrared reflection absorption spectroscopy (IRAS) to identify the structural motifs formed upon interaction of water with an atomically defined Co 3 O 4 (111) surface. Three principal structures are observed: (i) strongly bound isolated OD, (ii) extended hydrogen-bonded OD/D 2 O structures, and (iii) a third structure which has not been reported to our knowledge. In this structure, surface Co 2+ ions bind to three D 2 O molecules to form an octahedrally coordinated Co 2+ with a "half hydration shell". We propose that this hydration structure represents an important intermediate in reorganization and dissolution on oxide surfaces which expose highly unsaturated surface cations.
CRIS-Team Scopus Importer:2019-05-02

Wet-chemically prepared porphyrin layers on rutile tio2(110) - Wechsler, Daniel; Carolina Fernandez, Cynthia; Köbl, Julia; Augustin, Lisa-Marie; Stumm, Corinna; Jux, Norbert; Steinrück, Hans-Peter; Williams, Federico Jose; Lytken, Ole (Molecules, 2021)
Porphyrins are large organic molecules that are interesting for different applications, such as photovoltaic cells, gas sensors, or in catalysis. For many of these applications, the interactions between adsorbed molecules and surfaces play a crucial role. Studies of porphyrins on surfaces typically fall into one of two groups: (1) evaporation onto well-defined single-crystal surfaces under well-controlled ultrahigh vacuum conditions or (2) more application-oriented wet chemical deposition onto less well-defined high surface area surfaces under ambient conditions. In this study, we will investigate the wet chemical deposition of 5-(monocarboxyphenyl)-10,15,20-triphenylporphyrin (MCTPP) on well-defined rutile TiO2 (110) single crystals under ambient conditions. Prior to deposition, the TiO2(110) crystals were also cleaned wet-chemically under ambient conditions, meaning none of the preparation steps were done in ultrahigh vacuum. However, after each preparation step, the surfaces were characterized in ultrahigh vacuum with X-ray photoelectron spectroscopy (XPS) and the result was compared with porphyrin layers prepared in ultrahigh vacuum (UHV) by evaporation. The differences of both preparations when exposed to zinc ion solutions will also be discussed.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Interfaces; Metalation; Oxide surfaces; Porphyrins; Wet chemical preparation

Wet Chemical Synthesis of Graphene - Eigler, Siegfried; Enzelberger-Heim, Michael; Grimm, Stefan; Hofmann, Philipp; Kroener, Wolfgang; Geworski, Andreas; Dotzer, Christoph; Röckert, Michael; Xiao, Jie; Papp, Christian; Lytken, Ole; Steinrück, Hans-Peter; et al. (Advanced Materials, 2013)
A suitable technology for the preparation of graphene based on versatile wet chemistry is presented for the first time. The protocol allows the wet chemical synthesis of graphene from a new form of graphene oxide that consists of an intact hexagonal extgreeks-framework of C-atoms. Thus, it can be easily reduced to graphene that is no longer dominated by defects.

Wilkinson-type catalysts in ionic liquids for hydrogenation of small alkenes: understanding and improving catalyst stability - Kratzer, Eva; Schötz, Simon; Maisel, Sven; Blaumeiser, Dominik; Khan Antara, Sharmin; Ewald, Leon; Dotzel, Daniel; Haumann, Marco; Görling, Andreas; Korth, Wolfgang; Jess, Andreas; Retzer, Tanja (Catalysis: Science and Technology, 2023)
In this work, we apply supported ionic liquid phase (SILP) catalysts to hydrogenate 1-alkenes in a continuous fixed-bed reactor. SILP catalyts were prepared using the ionic liquid (IL) 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide [C4C1Im][NTf2] and tris(triphenylphosphine)rhodium(i) chloride [RhCl(PPh3)3] as a dissolved catalyst. Under isothermal conditions, we observe an increase in activity related to restructuring of the catalyst via formation of supported metal nanoparticles (NPs). Combined in situ infrared spectroscopic and theoretical studies show that NP formation is a step-wise process including the sequential loss of ligands and formation of isolated, supported Rh+-ions as intermediates. To stabilize the highly selective homogeneous catalyst, we systematically vary the experimental conditions (co-feeding of CO) and catalyst design (application of strongly binding CO or chelating xantphos ligand). This knowledge-driven approach results in a stabilization of the molecular Rh complex under hydrogenation conditions.
CRIS-Team Scopus Importer:2023-03-24

X-ray microscopy reveals the outstanding craftsmanship of Siberian Iron Age textile dyers - Späth, Andreas; Meyer, Markus; Huthwelker, Thomas; Borca, Camelia N.; Meßlinger, Karl; Bieber, Manfred; Barkova, Ludmilla L.; Fink, Rainer (Scientific Reports, 2021)
The excellent craftsmanship of ancient Oriental and Central Asian textile dyers is already demonstrated in the remarkable brilliance and fastness of the colours of the so-called Pazyryk carpet, the by far oldest pile carpet found to date. This specimen resembles the advanced craftsmanship of Iron Age Central Asian textile production. We have employed synchrotron-based µ-XRF imaging to detect the distribution of metal organic pigments within individual fibres of the Pazyryk carpet (about 2500 years old) and compare the results to wool fibres, which we prepared according to traditional Anatolian dyeing recipes. We observe congruent pigment distribution within specimens from the Pazyryk carpet and natural wool fibres that we have fermented prior to dyeing. Therefore, we conclude that the superior fermentation technique has been utilized about 2000 years earlier than known so far.
CRIS-Team Scopus Importer:2021-03-19

Zinc Porphyrin Metal-Center Exchange at the Solid-Liquid Interface - Franke, Matthias; Marchini, Florencia; Jux, Norbert; Steinrück, Hans-Peter; Lytken, Ole; Williams, Federico J. (Chemistry - A European Journal, 2016)
Demetalation of zinc 5,10,15,20-tetraphenylporphyrin (ZnTPP) under acidic conditions and ion exchange with Cu ions at neutral pH are both rapid reactions in the liquid medium. However, for ZnTPP monolayers adsorbed on a Au(111) surface exposed to aqueous solution, we find that, although ion exchange takes place rapidly as expected, demetalation does not occur, even at pH values as low as 0. Based on this, we conclude that metal center exchange on the surface does not proceed through a free-base porphyrin as an intermediate. Furthermore, once formed, CuTPP is stable on the surface and the reverse exchange from CuTPP to ZnTPP in the presence of Zn ions could not be achieved. The preference for copper is so strong that even an attempt to exchange adsorbed ZnTPP with Ni ions in the presence of traces of Cu yielded CuTPP rather than NiTPP.
Keywords: Ion exchange; Metalation; Porphyrins; Solid-liquid interfaces; Zinc

ZnO Nanoparticle Formation from the Molecular Precursor [MeZnOtBu](4) by Ozone Treatment in Ionic Liquids: in-situ Vibrational Spectroscopy in an Ultrahigh Vacuum Environment - Bauer, Tanja; Voggenreiter, Markus; Xu, Tao; Wähler, Tobias; Agel, Friederike; Pohako-Esko, Kaija; Schulz, Peter; Döpper, Tibor; Görling, Andreas; Polarz, Sebastian; Wasserscheid, Peter; Libuda, Jörg (Zeitschrift für Anorganische und Allgemeine Chemie, 2017)
As reported previously, novel ZnO nanostructures can be grown by oxidation of [MeZnOtBu](4) building blocks with O-3 in ionic liquids (ILs). In this study, we have explored the role of the IL during ZnO formation by in-situ infrared reflection absorption spectroscopy (IRAS) in ultrahigh vacuum (UHV). [MeZnOtBu](4) and [C(2)C(1)Im][OTf] were (co-)deposited as thin films by physical vapor deposition (PVD) onto Au(111), separately or simultaneously. The IR spectrum of [MeZnOtBu](4) was analyzed between 300 and 4000 cm(-1) based on calculated spectra from density-functional theory (DFT). Spectral changes in the IL-related bands during the thermal treatment of [MeZnOtBu](4) in [C(2)C(1)Im][OTf] indicate the loss of the precursor ligands and the interaction of the IL with the growing ZnO aggregates. The films were treated with ozone (10(-6) mbar) in UHV and the spectral changes were monitored in-situ by IRAS. Slow ozonolysis of [C(2)C(1)Im][OTf] is observed. Spectroscopically we identify the primary ozonide formed by addition of O-3 to [C(2)C(1)Im](+) and suggest a reaction mechanism, which leads to a biuret derivative. Upon ozone treatment of mixed [MeZnOtBu](4)/[C(2)C(1)Im][OTf] films, ZnO aggregates are formed at the IL/vacuum interface. Ozonolysis of [C(2)C(1)Im][OTf] is suppressed. Upon annealing to 320 K, further ZnO aggregates are formed, leading to enclosure of [C(2)C(1)Im][OTf] in the ZnO film. At 380 K the IL is released from the mixed film. The pure [C(2)C(1)Im][OTf] desorbs at 420 K, leaving behind the ZnO phase.
Keywords: Ionic liquid; Ozone; IR spectroscopy; ZnO nanoparticles; Surface science

ZnO Nanoparticle Formation from the Molecular Precursor [MeZnOtBu]4 by Ozone Treatment in Ionic Liquids: in-situ Vibrational Spectroscopy in an Ultrahigh Vacuum Environment - Bauer, Tanja; Voggenreiter, Markus; Xu, Tao; Wähler, Tobias; Agel, Friederike; Pohako-Esko, Kaija; Schulz, Peter; Döpper, Tibor; Görling, Andreas; Polarz, Sebastian; Wasserscheid, Peter; Libuda, Jörg (Zeitschrift für Anorganische und Allgemeine Chemie, 2017)
As reported previously, novel ZnO nanostructures can be grown by oxidation of [MeZnOtBu]“building blocks” with Oin ionic liquids (ILs). In this study, we have explored the role of the IL during ZnO formation by in-situ infrared reflection absorption spectroscopy (IRAS) in ultrahigh vacuum (UHV). [MeZnOtBu]and [CCIm][OTf] were (co-)deposited as thin films by physical vapor deposition (PVD) onto Au(111), separately or simultaneously. The IR spectrum of [MeZnOtBu]was analyzed between 300 and 4000 cmbased on calculated spectra from density-functional theory (DFT). Spectral changes in the IL-related bands during the thermal treatment of [MeZnOtBu]in [CCIm][OTf] indicate the loss of the precursor ligands and the interaction of the IL with the growing ZnO aggregates. The films were treated with ozone (10mbar) in UHV and the spectral changes were monitored in-situ by IRAS. Slow ozonolysis of [CCIm][OTf] is observed. Spectroscopically we identify the primary ozonide formed by addition of Oto [CCIm]and suggest a reaction mechanism, which leads to a biuret derivative. Upon ozone treatment of mixed [MeZnOtBu]/[CCIm][OTf] films, ZnO aggregates are formed at the IL/vacuum interface. Ozonolysis of [CCIm][OTf] is suppressed. Upon annealing to 320 K, further ZnO aggregates are formed, leading to enclosure of [CCIm][OTf] in the ZnO film. At 380 K the IL is released from the mixed film. The pure [CCIm][OTf] desorbs at 420 K, leaving behind the ZnO phase.
Keywords: Ionic liquid; Ozone; IR spectroscopy; ZnO nanoparticles; Surface science

Zone-plate based nanospectroscopy with soft X-rays at the SLS - Fink, Rainer; Hub, Christian; Tzvetkov, G. (Acta Physica Polonica A, 2009)
With the advance of nanostructuring techniques and the availability of third-generation synchrotron sources, Fresnel-type zone plate optics is widely used for nanospectroscopic investigations with resolutions of several 10 nm. Whereas hard X-rays commonly use diffraction or elemental contrast (e.g. using X-ray fluorescence), soft X-rays are favored to utilize the spectroscopic contrast in the near-edge region of the absorption edge. In particular, for soft materials, the relevant C-, N- and O 1s absorption edges show distinct resonances which allow fingerprint-type chemical identification, even in water surroundings. Few selected examples from modern material science will be discussed to demonstrate that the combination of X-ray absorption spectroscopy with high spatial resolution yields new insight into the nanoscale properties of these materials.